The Transnational Institutionalization of the Ideal-Filipino-Hero of Overseas Filipino Workers (OFWs) in Vancouver, Canada - Calamba, Rincy Dominic C. (Simon Fraser University, 2026)
Overseas Filipino Workers (OFWs) in Vancouver, Canada experience ongoing systematic conditioning processes that are rooted in Philippine colonial history. Utilizing a multi-ethnographic approach and a framework drawn from Berger and Luckmann's concept of institutionalization and Foucault's biopower, I rethink the Filipino labour diaspora and interrogate how empire, labour, and migration, shape Filipino trajectories. Existing scholarship has documented the structural and working conditions of Filipino labour migration; this research contributes by foregrounding how these arrangements between the Philippines and Canada are lived, internalized, and reproduced through the institutionalized subjectivities of the Filipino citizen, the ideal migrant, and the Bagong Bayani (new hero). These subjectivities sustain systemic inequalities, coerce joining the labour diaspora, and render OFWs more vulnerable to exploitation while glorifying their sacrifices as noble contributions to family and nation. I further discuss the agency and resistance of OFWs, who actively reimagine their subjectivities and challenge these neocolonial paradigms.

Racial Discrimination at Work and Health of Canadian Workers: A Mixed Methods Study - Dalexis, Rose Darly (University of Ottawa, 2026)
Workplace racial discrimination remains a pervasive and harmful reality with profound implications for health and well-being. Drawing on evidence from three interrelated independent studies using both primary and secondary Canadian data, this research provides a comprehensive understanding of how workplace racial discrimination functions as both a social determinant of health and a chronic stressor contributing to adverse health outcomes and persistent health inequities. The findings demonstrate that workplace racial discrimination, manifesting through inequities in hiring, promotion, retention, and interpersonal interactions, increases the risks of significant psychological, physiological, and physical health outcomes for racialized workers. Experiencing workplace racial discrimination was strongly associated with heightened risks of anxiety, depression, stress and post-traumatic stress disorders, reinforcing mental health disparities across racialized groups. In addition, workplace racial discrimination increased perceptions of work-related stress, which in turn elevated the risk of diagnosed chronic conditions such as cardiovascular disease, Type 2 diabetes, high cholesterol, stroke effects and musculoskeletal disorders. Physiological assessments further revealed that recalling racial discrimination experiences contributes to dysregulated cardiovascular reactivity, including elevated systolic and diastolic blood pressure, as well as mean arterial pressure values above the normal range. Particularly severe forms of racial discrimination, implicating job loss, early retirement, undesirable resignation or leaves were linked to greater blood pressure increases. When incidents of racial discrimination were reported, especially when participants received acknowledgment of their experiences, physiological responses were attenuated. These results underscore the importance of personal action, recognition, accountability and institutional action in mitigating health risks. These findings underscore how workplace psychosocial stressors trigger harmful biological and physiological responses that may result in lasting health consequences. Taken together, this research highlights workplace racial discrimination as a critical public health concern that transcends individual experiences and reflects broader organizational inequities. Conceptualizing discrimination as a chronic stressor provides an essential understanding in addressing racial health disparities. The evidence points to the urgent need for organizational reforms, robust anti-discrimination policies, and workplace practices that not only prevent discrimination but also support the mental and physical health of racialized workers. Addressing workplace racism is not solely a matter of social justice; it is a public health imperative with the potential to reduce disparities, promote workplace equity, and improve the overall well-being of diverse populations.

Migrant Stories, Industry Narratives: A Critical Discourse Analysis on Migrant Labour in Canadian Agriculture - Helps, William Louis (University of Guelph, 2025)
Since the onset of the COVID-19 pandemic in early 2020, many Canadians have become newly aware of problematic power imbalances and potential for abuse under the Temporary Foreign Worker Program (TFWP), which forms a key component of the Canadian agri-food workforce. The increased attention brought to some of the negative outcomes of Canada’s agricultural migrant labour system appear to have prompted an industry response, including through the More than a Migrant Worker initiative launched by a collection of agri-food industry groups. This dissertation presents the results of research on texts gathered from the More than a Migrant Worker initiative. Critical discourse analysis was used to identify themes, arguments, and rhetorical techniques the initiative employs to convey a narrative about migrant farm workers to the public. Findings indicate that these agri-food industry groups have adopted a defensive stance in response to critiques of migrant labour policies, as demonstrated by the discourse’s treatment of themes such as migrant workers’ and their families’ financial motivations, the purported necessity of migrant labour to sustain Canadian food production, and the formal rights and protections built into the TFWP, combined with a de-emphasis of the evidence of persistent systemic issues in the protection of migrant workers from mistreatment. The findings support a theoretical framework of managed migration based on a combination of Labour Market Segmentation Theory and the New Economics of Labour Migration, in which the devaluation of agricultural work in the domestic labour market and the disruption of traditional economies by neoliberal global market forces generate a demand for and supply of migrant labour, respectively. The paper’s conclusion provides directions for further research to expand academic knowledge of migrant labour discourse and migration theory, as well as recommendations for policy makers, the agri-food industry, and advocacy groups for productive policy discussions that find consensus on ways to protect and improve the conditions of migrant farm workers.

Neoliberal Policies and Rhetoric in the Struggle for Ontario Gig Workers' Rights - Abernethy, Zoe Ming Hui Gibbons (Carleton University, 2025)
How have neoliberal discourses of the gig economy shaped the terrain of gig worker organizing in Ontario? This thesis interrogates and contextualizes Uber’s efforts to legitimize and further expand its operations in Ontario during and after the COVID-19 pandemic, focusing on the centrality of its appeals to (and reproduction of) workers’ entrepreneurial common sense in these endeavors. Drawing on ten-semi structured interviews with current and former Uber drivers and delivery workers, it explores the contradictory form of independence experienced by platform-mediated gig workers, reflecting on the significance of gig work being perceived as the “least worst option” within the contemporary labour landscape.

The Intersection of Work and Care: Exploring the Facilitators and Barriers of Maternal Employment in Canada - Abraham, Haneen Alia (University of Alberta, 2025)
Since the 1970s, many OECD countries have seen a significant increase in maternal employment rates. In cross-national comparison, Canada has high maternal employment rates, but lags behind some Nordic and East European countries. Within this context, this study explores how larger social, cultural and policy environments shape mothers' employment experiences, challenging the notion that women prefer to opt out of the labour force when they have children To conduct this analysis, I drew on focus groups (n=19) and individual interviews (n=39) with 58 mothers in Canada with preschool children in the province of Alberta. The key finding from this study was that the majority of mothers, despite wanting to continue their careers alongside parenthood, experienced challenges integrating unpaid and paid work. To navigate these challenges, mothers employed various strategies, including seeking flexibility at work, reducing work hours, or opting out of employment. Yet, many remained ambivalent regarding their employment arrangements. I detail the ways in which paid parental leave and childcare policies acted as facilitators or barriers to mothers’ labour force participation. Overall, the findings indicate that current policies are not sufficient to support mothers in the labour force. This study adds to a body of Canadian literature that examines how barriers such as pervasive gender norms in the workplace and households, and workplace inflexibility, create barriers to mothers’ labour force participation and impact mothers’ experiences in the labour market.

Technological Change and an Aging Workforce: Investigating the Career Experiences of Older Workers - Adeniyi, Judah I. (Memorial University of Newfoundland, 2025)
This dissertation examines the intersection between two significant economic and societal challenges: an aging workforce and rapid technological change. The aging workforce is a growing concern, particularly in Canada, where the population of older workers (55 years and older) surpasses that of younger entrants (15 to 24 years). This demographic shift, already contributing to labour shortages in key sectors like manufacturing and healthcare, poses risks to labour participation rates and the stability of healthcare and pension systems (Acemoglu & Restrepo, 2017; Maestas et al., 2016). Given the projected exodus of older workers and limited incoming replacements, scholars and practitioners advocate for delayed or phased retirements to mitigate talent shortages. Simultaneously, technological change reshapes work, presenting opportunities and challenges, especially for older workers who may find adapting to new technologies daunting. This environment makes it critical to understand how technology affects older workers' experiences, including their retirement intentions. I conducted two studies to better understand the impact of technology and technological changes on older workers' work experiences. In Study One, I conducted a systematic literature review to synthesize existing research on technology's impact on older workers, with a comprehensive analysis of 121 articles, including both peer-reviewed (n=82) and grey literature sources (n=39). Thematic analysis revealed key areas in the current literature, such as socio-demographic factors, training and development, and retirement planning. The results of this study also included descriptive insights on journals, methodologies, regions, and publication dates, highlighting 14 important research gaps. These gaps guided recommendations for future studies, which aim to address the implications of technological innovations on an aging workforce. In the second study, I empirically examined the relationship between technological change and older workers' retirement intentions using a sample of 361 participants. Testing a moderated mediation model grounded in the Job Demand-Resources (JD-R) theory, I analyzed burnout and perceived work ability as serial mediators alongside moderating factors of computer self-efficacy, technological training, and organizational justice. Findings accentuate the complex interplay of burnout, work ability, and retirement intentions, emphasizing that burnout negatively impacts work ability, which in turn influences retirement intentions. Notably, technological training significantly moderated the relationship between burnout and work ability, reinforcing its role as an important factor shaping older workers' capacity to adapt within technologically evolving work environments. Ultimately, this dissertation provides valuable implications for both theory and practice. The findings from both studies provide important directions for the successful integration and retention of older employees in the rapidly changing technological work environment, as well as for creating a supportive work environment for them.

"Everything I Know Is Canada": Migrant Farmworkers and the Making of Homes Across Borders - Baeza Martinez, Regina (Simon Fraser University, 2025)
Canada is wholly reliant on migrant farmworkers who provide cheap labour while being barred from a wide range of rights and services, including pathways to permanent residency (Sharma, 2012; Satzewhich, 1990; Basok, 2002). Whereas most of the research on migrant farmworkers follows a deficit model, my thesis focuses on collective agency by asking: how do migrant farmworkers create a sense of home in Canada while unable to settle permanently in the country? Drawing from interviews and participant observation conducted in Guatemala and Canada, I show how migrant farmworkers exceed the boundaries of the farms where they live and work, forging their own modes of social organization using Indigenous Mayan cultural logic. Framing migrant farmworkers as strategic boundary-crossers, I highlight how they breach farm borders and, through the exchange of ideas across nation-states, inspire new migration journeys.

Thwarted and Delayed: Three Eras of Legislating Labour Rights in the Ontario Public Service, 1867-2017 - Carson, Thomas Jonathan (York University, 2025)
Seeking to understand why public servants took so long to achieve labour rights—particularly the right to strike—compared to those in the broader economy, this dissertation explores the historical evolution of labour relations within the Ontario Public Service (OPS) from 1867 to 2017. Through an examination of the interplay between institutions and broader socio-economic and political forces, viewed through a critical institutionalist framework, this study argues that the development of OPS labour relations is defined by three distinct eras. The first era, from Confederation until the 1960s, was dominated by the principle of parliamentary sovereignty, which limited the labour rights available to public servants. The second era, from the 1960s to the 1990s, saw the ideology of the governing party as the primary dynamic, with party ideology playing a significant role in the emergence of public servants’ right to strike. Starting in the 1990s, the third era saw the rise of neoliberalism shift the focus of governments of all partisan stripes toward cost containment. As a result, this era was marked by hard bargaining and practical constraints on the feasibility of the strike option. This study demonstrates how these primary factors, along with other influences such as worker militancy and class relations, have shaped the long development of the OPS labour relations regime. The dissertation concludes that, despite significant legislative changes, the government has nevertheless retained considerable control over the material outcomes of the public service labour relations system.

Foodwork as Relationality: Labour and the Creation of Culinary Placemaking - Chartrand, Stephanie (University of Toronto, Ontario Institute for Studies in Education, 2025)
This thesis explores the concept of culinary placemaking through the lens of Global Political Economy (GPE), focusing on how foodwork functions as a relational practice that shapes social, cultural, and economic spaces. It examines the relationships among food, labour, and place, emphasizing the ways in which workers transform culinary environments into meaningful places through their physical, emotional, and creative contributions. Drawing on existing literature, the research highlights how neoliberal policies have commodified food and labour, leading to increased precarity and alienation for food workers. Despite these challenges, culinary workers actively resist the pressures of globalization by fostering localized food systems, emphasizing cultural and social engagement, and envisioning alternative economic models such as cooperatives and farm-to-table initiatives. This thesis finds that culinary placemaking not only resists commodification but also offers opportunities for social cohesion, cultural expression, and economic resilience. Furthermore, the research touches upon the gendered dimensions of culinary labour, demonstrating how workers navigate power dynamics within professional kitchens and community food spaces. Future research directions include exploring the evolving role of consumers in culinary placemaking, addressing labour precarity through policy interventions, and investigating how Indigenous economies contribute to decolonial approaches to food sovereignty. By situating foodwork within the broader political and economic context, this thesis contributes to a deeper understanding of the transformative potential of culinary labour in fostering inclusive, sustainable, and culturally resonant food spaces.

Soldiers in Capitalist Society: Critique of the Labour of Political Violence - Chorley Foster, Jasmine (University of Toronto, 2025)
This dissertation critiques the soldier in capitalist society as a category of social labour that produces the state capacity for political violence. Identifying soldiering labour is essential to historicizing how this social capacity of labouring people is fetishized as the military power of the state. From the perspective of this project, the substance of the labour of the soldier is affected but not resolved by a resolution of form (such as the standing army, or transition from a draft to an all-volunteer army). What is discovered through historical and theoretical analysis and soldiers’ struggles themselves, is that historical class struggles in the military can be read as contests for political sovereignty over the labour of political violence: literal power over cooperative labour, not merely over institutions, or freedom in the ‘spheres’ of politics and economics. It captures the necessity of emancipation in one as a condition of the emancipation of the other; and that of the soldier as a condition for everyone else’s so long as we are to be concerned with the entirety of human life and not the exception of a single nation-state’s population.

Legal Silence, Worker Suffering: Law, Electronic Workplace Surveillance, and Amazon Warehouse Worker Injuries in Ontario - Del Riccio, Jennifer (University of Toronto, 2025)
In the American and Canadian warehouses of the e-commerce giant Amazon, electronic workplace surveillance (“EWS”) technologies permit the unprecedented quantification and datafication of worker activity, enabling the setting and enforcing of unsafe productivity ‘quotas’ that lead to serious occupational injuries for warehouse workers. In this paper, I consider the role of Canadian law – namely, the employment, privacy, and occupational health and safety legal regimes in the province of Ontario – in enabling, and in potentially constraining, this phenomenon in Ontario’s Amazon warehouses. In doing so, I identify the ‘legal silence’ that shapes the lived experiences of Amazon warehouse workers in Ontario; contribute to the emerging theorization, particularly from a legal perspective, of EWS as a factor impacting workers’ physical health; and propose legal reforms that would improve the safety and well-being of Amazon warehouse workers – and other similarly-situated workers – across the province.

"When you are accepting money you have to do as you are told:" The CAHA/NHL Relationship and the Rise of the Professional Sponsorship System, 1936-1952. - Di Gravio, Michael (Western University, 2025)
This thesis undertook an interpretivist historical analysis of the publicly available Canadian Amateur Hockey Association (CAHA) meeting minutes from 1936 to 1952. A Foucauldian lens of disciplinary power was used to answer the research question: how was the National Hockey League (NHL) able to develop a professional sponsorship system within the CAHA following World War II, and what effects did this have on Canadian minor hockey. The results found that following the signing of the CAHA/NHL agreement, the NHL exercised its disciplinary power over the CAHA members to instill in them what Foucault termed ‘docility.’ The birth of the professional sponsorship system following WWII was a result of this disciplining and docility. Through this system, the NHL brought its disciplinary technologies directly to bear on Canadian minor hockey and gained the ability to control players' rights from ages as young as twelve years old.

"The Gilt-Edged Class": American and Canadian Telegraphers' Bodies and Work - Feagan, Michael (Western University, 2025)
This dissertation examines the lives and work of American and Canadian telegraph operators from 1870 to 1929. While historians have studied the telegraph as a technology and a business, few have integrated telegraphy with histories of class, gender, or the human body. Integrating the bodily turn means recognizing the physicality of telegraph work. This dissertation centres the bodies of telegraph operators and seeks to contextualize those bodies within the larger technological and corporate systems in which they were embedded. Operators’ class identities have often been ambiguous or misunderstood. I argue that telegraph work was real, physical work, in a way that has too often been elided, and that it is important to see operators as part of the working class. Ultimately, this dissertation demonstrates the ways in which human bodies and human labour can be erased within large technological networks. I explore the historical significance of that erasure and its relevance for understanding the precarity of labour in high-tech industries today.

Conflict And Solidarity Between Anti-Colonial Environmentalism, Indigenous Anti-Pipeline Resistance, and Labour - Golkar, Niloofar (York University, 2025)
Climate change has reached crisis mode, and confronting it requires confronting corporations, economic planning, policies that exacerbate this process, and social relations that enable such policies and economic paths. This dissertation shows how settler colonialism in Canada revolves today around extractivism. This fact makes the struggle for land critical and highlights how Canadian nationalism is an obstacle to Indigenous solidarity and environmentalism. In 2020, the Shut Down Canada movement that started from Wet'suwet'en territories against building the CGL pipeline on their land, which was a scale-up from the Idle No More movement, underscored the importance of the Land Back movement for environmental justice. Its tactic of shutting down critical infrastructures was the largest scale in Canada's recent history of Indigenous resistance at the time. The well-documented militarized attacks on Wet'suwet'en unceded territories creates a dilemma that should concern every activist. At the same time, the impressive organizing efforts that started from Unist'ot'en as a space of resistance provide lessons for every movement. The case of the CGL pipeline and Wet'suwet'en resistance puts us at the conjuncture of three movements: the issue of solidarity between labour, anti-capitalist Environmentalists and the Indigenous movement. In this dissertation, I strategically explore possibilities for building strong Indigenous-environmentalist-labour solidarity. Through extensive policy analysis of the critical infrastructure risk management approach and media analysis of the CIRG task force, I explore a hidden link between the security arm of one of the largest global investment corporations, KKR, RCMP, and TC Energy executives. The government's risk management approach has enabled such a link, which facilitates and encourages conversations between the involved actors. The state's claim to the so-called public/Canadian interest in pipelines is of utmost importance to this dissertation. The concept of Canadian interest works as a settler colonial and national ideology of governing; historically and presently, the concept creates an umbrella that includes the Canadian working class as it excludes Indigenous communities, along with the processes of reproducing nature and non-capitalist forms of economy that many radical environmentalists try to create through commons. A lack of land-based analysis of the situation of working-class people in Canadian labour has turned the labour movement into a more economistic version of trade unionism, one that does not actively oppose Canadian nationalism.

Depicting Mexican Labour for/within Contemporary Canadian Imperialism: Photography, Participation, and Power - Gonzalez Teran, Anahi (Western University, 2025)
This studio-based dissertation project emerges from my engagement with the politics of representation of labour and visual culture. Rooted in my experience as a Mexican artist living in Canada, the project examines how Mexican labour is framed through photography, performance, and installation. These themes form the central focus of my research, which moves across Lands and disciplinary forms to investigate how systems of power shape the representation of Mexican workers and how irony can be used as a tool to question dominant narratives. The written component of this dissertation forms part of an interdisciplinary thesis that includes a series of exhibitions and performances carried out between 2021 and 2025 in today’s Mexico and Canada. The artworks, presented across artist-run centres in Ontario and as outdoor installations, use staged photographs, installations, participatory works, to examine labour, value, and exchange. These pieces were shown in the province of Ontario, Canada and the state of Coahuila, Mexico. My thesis engages with a range of theoretical frameworks to support and extend my artistic practice. Drawing from visual culture theory, performance studies, and participatory art discourse, I incorporate the work of theorists such as Stuart Hall, Jacques Derrida, and Claire Bishop, among others. As a whole, this dissertation considers how visual and performance-based practices can challenge representations of Mexican labour across Lands and reflect on the systems that shape the movement of people, goods, and images. The written component includes five chapters, followed by photographic documentation of the works and exhibitions produced during my doctoral studies. Together, the writing and the artworks propose a critical reflection on contemporary labour and visual politics.

Labour, Migration and Resistance: The Legacy of INTERCEDE in Domestic Workers Advocacy in 1980s Ontario. - Haruna, Jamila (Trent University, 2025)
In 1980s Ontario, racialized migrant domestic workers faced systemic exploitation, precarious immigration status, and exclusion from labour protections, reinforced by provincial and federal policies that devalued domestic labour. This thesis examines how INTERCEDE, a Toronto-based coalition, challenged these structural inequalities. Employing an intersectional approach, this study reveals how race, gender, immigration status, and class collectively marginalized migrant care workers. Drawing on extensive primary sources, it analyzes INTERCEDE's influence on major policy changes, including reforms to the Foreign Domestic Movement (FDM) program and to provincial labour laws. The thesis argues that while INTERCEDE efforts contributed to securing significant, albeit often fragile, victories, these gains highlighted both the power of activism and the persistent challenges under neoliberal regimes. It contributes to feminist labour history, migration studies, and care work scholarship by demonstrating how organized resistance reshaped Canadian policy and contested institutionalized marginalization.
Keywords: Care activism; Care work history; Feminist labour history; History; Labor relations; Migrant domestic workers; Resistance; Womens studies

Transnational Circuits of Precarity: A Qualitative Examination of Temporary Worker Wellbeing in Manitoba - Huynh, Anthony (University of Manitoba, 2025)
Background: In western Canada, Manitoba is a critical hub for a large population of migrant workers. Usually with limited English or French language ability and possessing limited rights and protections under the current TFWP, Temporary foreign workers (TFWs) are often tied to a single employer, leaving them vulnerable to employer abuse and the under-reporting of workplace injuries and illnesses due to the threat of deportation. Within the context of the COVID-19 pandemic, when my dissertation research began, the many cases seen among TFWs in Manitoba raises additional important public health questions on the health and wellbeing of migrant workers in Manitoba that I discuss in this dissertation. Methodology: In close collaboration with Migrante Manitoba (MB), I conducted a qualitative study to explore the precarious lives of migrant workers during the COVID-19 pandemic. I virtually interviewed 20 migrant workers who entered Canada through the TFWP, employed either as seasonal agricultural workers (n=7) or TFWs (n=13). Thirteen TFWs came from Philippines and seven farmworkers from Mexico (n=6) and Jamaica (n=1). Theoretical contribution: I developed the notion of transnational circuits of precarity to understand the multiple temporal-spatial layers of precarity that migrant workers encounter along their journeys to Manitoba. This multivalent concept is comprised of the following interconnected pieces: 1) a broader political economic “force-field” that compels the movement of human labour resources from the global South to the global North; 2) the rigid and regulated pathway put in place to ensure workers arrival at their work destinations; 3) the process of making “model minorities” through training programs that ensure the “smooth” transition of workers in their host country; and 4) the affective economy that is fueled by workers’ hopes, dreams, and desires. Altogether, these seemingly disparate processes articulate to produce complex temporal and spatial realities that shape the precarious trajectories of migrant workers. Such a paradigm shift away from the narrow temporal and spatial limits of a focus on “occupational health hazards” will be critical if workers are to realize any meaningful and substantive changes to their overall physical and mental well-being.

In What Ways Does a Lack of Status Influence the Psychosocial Well-Being of Non-Status Migrants in Alberta? - Karnjanavijaya, Jakkapan R. (University of Alberta, 2025)
Canada is a country whose economy benefits considerably from migrant workers in the Temporary Foreign Worker Program (TFWP). With little protection from workplace exploitation, as well as unclear and constantly changing immigration policies, migrant workers often lose their legal immigration status due to conditions out of their control, becoming non-status. Living in the shadows and without access to most publicly funded services, non-status migrants experience a myriad of chronic daily stressors. In partnership with non-status community members, this Community-based Participatory Research project explores the question, “In what ways does a lack of status influence the psychosocial well-being of non-status migrants in Alberta?”. Both non-status migrants and service providers participated in semi-structured interviews, while a group of service providers working in mental health also participated in a focus group interview. The interpretation of this study’s findings was guided by the socio-ecological systems framework. Non-status realities were described from the perspective of both non-status migrants and service providers. Findings included insights into how the TFWP creates systemic vulnerabilities for migrant workers and facilitates the loss of immigration status. This lack of status led to a scarcity of access to most basic services and resources, leading to significant detrimental impacts on psychosocial well-being. This produced internalized experiences of shame and un-belonging, as well as a range of deleterious mental health outcomes. Furthermore, the impacts associated with a lack of access were significantly exacerbated by a discriminatory and hostile sociopolitical environment. Recommendations centered around the inclusion of non-status migrants in collaborative partnerships with service providers and policymakers alike. In light of these findings and recommendations, the implications for counselling psychology practice are also illuminated.

Collective Labour in a Capitalist Market: The Historical Struggle to Secure a Place for Worker Cooperatives in the Canadian Political Economy. - Kinsey, Simon Wilson (Carleton University, 2025)
This thesis seeks to understand the historical conditions that have relegated worker cooperatives to the periphery of the Canadian political economy. It begins with a theoretical exploration of the relationship between worker cooperatives and capitalism, highlighting two key dynamics: 1) worker cooperatives are a form of collective property that allow workers to secure their subsistence outside of the wage-labour market; 2) worker cooperatives can serve a wide range of interests depending on the subjectivities of the worker-members and the objective conditions of their political-economic environment. This framework is then used to examine subjective and objective considerations in the context of Canadian worker cooperatives, with a focus on the emergence of the contemporary sector in the 1970s and 1980s. Material need has at times produced upswings of grassroots momentum, but this momentum has struggled to sustain itself in the absence of support from major institutions of the Canadian political economy.

Navigating the Gendered Landscape: The Impact of Institutional Participation and Professional Culture in Shaping Inequality - Mogoşanu, Andreea (University of Toronto, 2025)
The Gender Revolution significantly improved women’s status, but recent progress towards equity is “uneven and stalled” (England 2010:149). This dissertation uncovers the complex role of institutional processes in shaping the evolution and persistence of gender inequality. The first study offers a macro-level analysis trends in men and women’s perceptions of mastery across the life course of different cohorts. Perceptions of mastery —control over one’s life— reflect differences in status and gendered notions of agency (Connell 1987; 2005). Institutional participation —educational achievement and employment levels— is key in shaping movement towards and away from gender equality. While high levels of education and employment lead to converging perceptions of mastery, the effect of institutional participation is strongly gendered: women benefitted more from education, while men are penalized more when working less than full-time. Workforce participation emerged as a key driver of men’s higher perceptions of agency in younger cohorts. Drawing on the legal profession as a case study, subsequent studies highlight the role of workplace culture in shaping gender inequality. Using longitudinal data on private sector lawyers, the second paper finds norms of hegemonic masculinity —measured as technical competence, authoritative leadership, work devotion, breadwinner status, and individual preferences— (re)create wage inequality across the earnings distribution. The analysis further uncovers a hierarchy of valuation based on gender and parental status, as fathers earn the highest wage premiums, followed by mothers; women without children earn the least after controls. The final paper investigates how perceptions of professional fit —signaled by professional role confidence (PRC)— shapes perceptions of job security among early-career lawyers. The legal profession is marked by a ‘masculine mystique’ that challenge female lawyers’ PRC —measured as expertise confidence and career fit. Findings indicate that men derive higher perceptions of job security for the same levels of PRC, explaining women’s lower perceptions of job security. Professional fit therefore reinforces gender inequality, possibly through women’s awareness (but not internalization) of their lower status in law. This dissertation provides a nuanced understanding of gender inequality, with institutional participation and culture emerging as key mechanisms shaping the dynamic evolution of gender inequality.

Performing the Subject-Self: A Critical Exploration of Sex Worker Resistance and Activism in Canada - Murray, Julie Anne Cordeiro (Université d'Ottawa / University of Ottawa, 2025)
The contemporary movement for sex workers' rights emerges from a lengthy and complex legal history of sex workers challenging dominant discourses that frame prostitution as a public nuisance, moral offence, and violence against women. The existing literature demonstrates that sex workers and sex work activists resist oppressive and reductive discourse via community-based initiatives, lobbying efforts, and strategic litigation such as the successful constitutional challenge against Canada's prostitution laws in 2013 (Canada (Attorney General) v. Bedford, 2013). However, there is a significant gap in understanding how sex workers and sex work activists enact resistance through embodied performance. As such, this thesis explores the ways in which sex worker rights activists resist dominant discourse and troubling public perceptions through symbolic communication and attire during protests. To this end, this research builds a conceptual framework that puts resistance literature in conversation with key theoretical insights from Michel Foucault and Judith Butler. Based on 143 publicly accessible images of sex worker rights protests in Canada between 2013-2023, a qualitative visual content analysis is deployed to examine how sex workers and sex work activists enact resistance through what the author calls the performance of the subject-self. The findings reveal how the subtle, creative, and symbolic aspects of sex work activism are serious and significant forms of political expression.

Bridging the Gap: Exploring the Experiences of South Asian Women Immigrant Teachers in Toronto - Omar, Rozalina (University of Toronto, Ontario Institute for Studies in Education, 2025)
In this dissertation, I share the voices of South Asian women immigrant school teachers living in Toronto. In this era of global mass migration and the increasing number of women immigrants, I argue that it is important to examine how gender and race affect racialized immigrant women’s working experiences. Historically, racialized immigrant women in Canada have faced various forms of discrimination in the labour market: not only are their previous qualifications and experiences devalued in the job market, but after entering the job market, racial and gender identity remain a concern in their professional lives (Crea-Arsenio et al. 2022; Premji et al. 2014). While scholars have highlighted the common labour market barriers, the struggles of South Asian women when facing these challenges in seeking a specific career do not get enough attention in the academic world. A significant number of South Asian women must engage in precarious jobs that are not consistent with their skills and qualifications. Here, I recruited South Asian immigrant women who hold a teaching certificate in Ontario and are coping with the secondary-education labour market and/or other related jobs in Toronto. Guided by a Critical Race Feminist perspective, I used interpretive inquiry as a research methodology to facilitate participants telling their struggles, challenges, and negotiations of their everyday lives while living in a large urban center like Toronto. My analysis of this research shows that these South Asian groups of women must overcome barriers that are similar to many other non-racialized female professional immigrants - but as racialized female immigrants, they also face more challenges in accessing and coping with their current professions. My findings suggest that policymakers should focus on an adaptable labour-market transition process for these professional groups after migration. This could also be helpful for other racialized groups in general. Promulgation to eliminate systematic barriers through various forms is needed to decrease the substantial existence of teacher diversity gap in Ontario. Therefore, this study extends the available literature by considering voices of racialized immigrant women, thereby addressing some existing gaps in policy framework.

Realities of Precarity in Canada's Seasonal Fields: Struggles, Advocacy, and Restricted Spaces and Voices - Patterson, Dominica (University of Ottawa, 2025)
The following thesis examines the complex reality of temporary migration within Canada's agricultural sector by investigating the Seasonal Agricultural Worker Program (SAWP). The relevance of this inquiry hosts far-reaching implications for not only the wellbeing of migrant workers, but for the Canadian food-system, as well as migrant sending states. Furthermore, this research contributes additional knowledge and insights regarding the evolving interconnections between the climate and migration crisis that host critical impacts for Canada and the world moreover. In analyzing the impact of the SAWP on migrant workers' lives through two case studies, the project explores the interplay between climate change, globalization, neoliberalism, and liberalization in shaping the precarity faced by migrant workers in Canada. Despite the commonly advertised benefits of the SAWP, the study finds that structural barriers and power imbalances limit the realization of these benefits for migrant workers. The study ultimately explores the divided calls for reform across the sector, revealing the influence of widespread industry malpractice, and the presence of entrenched power hierarchies that have served to dominate the scope and direction of change. The research finds that the SAWP's structure and the broader context of inequalities related to globalization and neoliberalism hinder migrant workers' ability to leverage their assets and improve their livelihoods in Canada.

Harassment and Violence faced by Latinas on Ontario Construction Industry work sites - Ratsch, Valeria (University of Toronto, Ontario Institute for Studies in Education, 2025)
The aim of my dissertation is to examine the Harassment and Violence (HV) that Latinas face while working in the Ontario Construction Industry (OCI). I was specifically interested in the toxic impact HV has on Latina worker’s professional careers, as well as their personal lives. My qualitative research interviews (pláticas) with fourteen Latina construction workers, provided me with the capacity to explain how the labour they perform, and the legal invisibility by which they are defined, systematically combine to disenfranchise Latinas. I explain how the hyper-visible identity of Latinas on job sites, compounds the invisibility of their labour, even as language barriers significantly diminish their individual capacity to report and combat HV effectively. This dissertation also illuminates the persistent state of vulnerability (harassment, wage theft, and/or working in dangerous conditions) experienced by Latinas working without status in the OCI. I open with a literature review illuminating my uniquely intersectional, methodological position as a Canadian-born, Spanish-speaking academic researcher with more than two decades of experience working as a safety inspector in the OCI. My pláticas with fourteen Latinas working in the OCI reveal how workplace dynamics and regulatory inconsistencies contribute to their vulnerability to supervisory exploitation and discrimination from co-workers. The concepts of tokenism, intersectionality, and the conditionality of precarious status help explain how systemic labour policies have placed women in positions where following workplace regulations can inadvertently reinforce their collective marginalization. I found that the toxic, racialized, gendered culture of the OCI is reproduced even when women receive status, such as in the case of supervisors. I recommend a systemic shift in the culture of the OCI which keeps HV underground and normalizes the approach to Latina women in the industry. My dissertation concludes by recommending that support groups, operating outside of state structures, should be funded to serve as the frontline of protection.

Bridging Education and Career: Post-Secondary Music Performance Curriculum and the Portfolio Practices of Classical Musicians - Richards, Jenna (University of Ottawa, 2025)
This dissertation explores the intersections of music curriculum, identity, and career components to provide a deeper understanding of musicians’ livelihoods in Canada. To assess the alignment of post-secondary training with the practices of professional musicians today, the author studies undergraduate music performance curricula and nontraditional performance work, examines rhetoric surrounding musicians’ identities, and delineates portfolio careers. Drawing on first-hand Canadian data through a national survey and interviews with graduates of post-secondary music performance programs, a survey of adaptive concert performers, and a curriculum analysis based on web-scraped data from five prominent institutions, the dissertation applies social constructionist theory and the transformative lens to emphasize musicians’ perspectives in a practical dissemination of findings. Three core articles address three critical aspects of musicians’ careers: (1) Canadian undergraduate music performance curricula, focusing on coursework beyond core musicianship; (2) the portfolio careers of Canadian-trained classical musicians, assessing employment patterns, career sustainability, training relevancy, and identity formation; and (3) nontraditional performance work, with specific focus on adaptive concerts as an emerging performance avenue. The synthesis and conclusion distill key takeaways and present actionable recommendations for curriculum reform, identity affirmation, and professional preparation. The careers of classical musicians are increasingly precarious and multifaceted, challenging the legitimacy of traditional conservatory models that frame success primarily in terms of full-time performance careers. This research contributes to discourse on music careers by identifying gaps in institutional training and exposing the realities of professional life for performance graduates. By integrating concepts from the performing arts, curriculum, and entrepreneurship, this dissertation offers interdisciplinary insights into how institutions and society might better support musicians in building sustainable careers.

Poverty Policy: Historic Institutional Approaches to Poor Relief in Canada - Robbenhaar, Madeline E. A. (University of Alberta, 2025)
In Canada, social assistance programs act as a ‘safety net’ to prevent those living in poverty from reaching destitution. However, this safety net comes with expectations – in the form of welfare-to-work programs that mandate beneficiaries’ participation in work-related activities. Underlying these welfare-to-work programs are ideas surrounding citizenship, activation, dependency, and the role of the state in supporting the welfare of its citizens. Embedded in these programs are the ideas of market citizenship and activation, two ideas that tell the story of the ideal citizen in Canada: a self-sufficient and appropriately activated market citizen, who fulfils their obligation of supporting themselves through participation in paid employment. Subsequently, through the ideas of market citizenship and activation, social assistance beneficiaries represent the antagonist to the ideal citizen: an unmotivated, dependent, support-needing citizen. Although scholars often situate the emergence of the ideas of market citizenship and activation during the late 20th century period of welfare reform in Canada, this perspective negates the history of these ideas in social assistance policies. Informed by the theory of Critical Human Ecology and the methodology of Ideational Analysis, this thesis explores the development of the ideas of market citizenship and activation across institutional approaches to poor relief in Canada. By taking a long-term historical perspective, this thesis finds evidence of the ideas of market citizenship and activation as early as the 17th century in Canadian institutional approaches to poor relief, and counters the prevailing perspective that market citizenship and activation emerged in the late 20th century in Canadian institutional approaches to poor relief.

The Practice of Intolerance by the Alberta Social Credit Government and the Growth of Jewish Activism Between 1943 and 1968 - Rohfritsch, Jason (University of Ottawa, 2025)
The following thesis paper examines the continued presence of antisemitism in the ruling Alberta Social Credit Party (SCP) between 1943 and 1968, and Canadian Jewish organizational efforts to obtain anti-discrimination legislation. The Alberta Social Credit grassroots movement involved radical monetary policies, religious fundamentalism, conspiracy theories and antisemitic rhetoric. How did such an unorthodox party retain provincial control for thirty-six years despite the organization's persistent antisemitism? The question is significant to the ongoing narrative of Alberta politics amid a sharp rise in antisemitism within Canada today. The principal methodology includes qualitative research of primary sources from the SCP and Canadian Jewish archives and academic literature. Within this study period, the Canadian Jewish Congress (CJC) transitioned from an organization with little infrastructure to a leading institution with strong ties to other Canadian Jewish bodies, and labour and civil groups, struggling to enshrine protections for Canadian Jews. The results demonstrate that in the 1950s and early 1960s, as many Canadian provincial governments enacted equal rights legislation, Premier Ernest Manning's Social Credit government resisted such laws in Alberta. As a result, Jewish leaders escalated initiatives in Alberta. Throughout his leadership, Manning routinely denied accusations of antisemitism leveled against his party. Eventually, Manning and the Alberta SCP government were forced to establish human rights legislation in 1966, although the provisions were limited in scope. Manning curtailed Social Credit antisemitism when it became a political liability, but he did not comprehensively eliminate it. Through collaborative efforts, the CJC and other Canadian Jewish groups finally achieved legalized protections for the Jewish community in Alberta.

Food Insecurity In Canada: Gaining A Better Understanding Of Where And Why It Exists - Russo Spena, Anna (University of Guelph, 2025)
Food insecurity remains a challenge even in high-income countries. This study has two main goals: (i) to explore the factors driving differences in household food security between urban and rural areas; and (ii) to examine public perceptions regarding the existence, causes, and solutions to food insecurity. The first objective is addressed through a multinomial logit analysis of data from the CIS 2021. The second builds on Attribution Theory and involves a survey conducted with a representative Canadian sample, analyzed using factor analysis. Findings show that rural households would be 1.4% more likely to experience food insecurity than urban ones. The identified public antecedents include economic conditions, the food system and government, social support, and individual factors. The government is seen as primarily responsible for addressing the issue. Recommended policy measures include reducing food prices for low-income populations, improving access to affordable food shops, and supporting increased local food production.

Les travailleurs migrants temporaires du secteur de l'entretien ménager dans la région de Québec : Entre précarité, mobilité et agentivité - Tapia, Janelvi Caroline (Université Laval, 2025)
Le contexte de pénurie de main-d'œuvre au Québec lors des dernières années a entraîné une augmentation du recrutement de travailleurs migrants temporaires dans différents secteurs d'emploi. Ces travailleurs sont souvent engagés par des agences de recrutement à l'international ou des agences de placement, particulièrement dans des secteurs considérés précaires et « essentiels ». Hors du secteur de l'entretien ménager, la littérature a montré que les agences façonnent le lien d'emploi des travailleurs avec leur employeur, créant ainsi une main-d'œuvre « flexible », conçue pour répondre aux besoins ponctuels et temporaires des entreprises (Belzile, 2018; Mercure, 2014). Ce mémoire s'intéresse aux travailleurs migrants temporaires du secteur de l'entretien ménager, recrutés par une agence de recrutement à l'international, principalement en hôtellerie, dans la région de Québec. Ce secteur présente une forte variabilité saisonnière des conditions de travail et, par le fait même, est fortement touché par la pénurie de main-d'œuvre puisque de nombreux employés revendiquent précisément cela; de meilleures conditions de travail (Guilbault, 2024). Cette dynamique est particulièrement marquée dans la région de Québec où la nécessité d'embaucher de la main-d'œuvre à l'international est devenue de plus en plus cruciale pour le secteur de l'entretien ménager. Cette étude s'inscrit dans un projet plus large financé par le Conseil de recherches en sciences humaines (CRSH); le projet PARtenariat sur les migrants Temporaires en EMPloi (PARTEMP), qui vise à produire des connaissances sur les travailleurs migrants temporaires dans la région de Québec (Chaire de recherche du Canada sur les dynamiques migratoires mondiales, 2021). L'objectif principal de ce mémoire est de comprendre les expériences et les conditions de travail de ces travailleurs au sein d'un secteur peu exploré dans la littérature en contexte québécois. Les concepts de précarité, de mobilité et d'agentivité sont mobilisés pour appréhender l'expérience des travailleurs migrants temporaires. 14 entretiens semi-dirigés avec des travailleurs de nationalités différentes, majoritairement des latinoaméricains et des femmes, ont été réalisés entre mai et août 2023. L'analyse révèle plusieurs formes de précarité par le croisement de la relation d'emploi, le statut migratoire, le manque d'accès à l'information et la barrière de la langue. La flexibilité, une exigence structurelle du secteur d'emploi, et la mobilité sont des facteurs de précarisation. Le secteur exige des déplacements fréquents verticaux sur le lieu de travail, d'un étage à l'autre, et horizontaux sur le territoire. Cependant, ces travailleurs se montrent créatifs et « résilients », faisant preuve d'agentivité individuelle et collective dans le but d'améliorer leurs conditions de travail et de vie dans la région de Québec.

Deconstructing Human Capital Theory: The Silenced Narratives of Immigrant Women of Colour - Thananayagam, Shanmugapriya Thanuja (University of Toronto, Ontario Institute for Studies in Education, 2025)
This study critically examines the limitations and inadequacies of Human Capital Theory (HCT) in addressing the employment realities of immigrant women of colour in Canada. Rooted in neoliberal ideology and neoclassical economics, HCT assumes that individual investments in education and skills directly lead to economic success. However, this framework fails to account for systemic barriers, structural racism, and gendered discrimination that disproportionately disadvantage equity-deserving communities. Applying Pierre Bourdieu’s concepts of social capital and habitus alongside critical race theory (CRT), this research interrogates HCT to examine how race- and gender-based exclusions, social networks, cultural norms, and institutionalized biases shape career trajectories. While intersectionality is not the central focus, the study integrates an intersectional analysis to highlight the compounded disadvantages faced by immigrant women of colour in the labour market. Employing Indigenous storytelling methodologies and narrative inquiry, this research foregrounds the lived experiences of immigrant women of colour to challenge the assumptions of HCT. By conducting a comprehensive literature review and examining CRT, the study further interrogates how race, power, and systemic exclusion intersect with economic mobility. Despite its widespread acceptance, HCT remains insufficient in explaining the persistent employment gaps and labour market marginalization of immigrant women of colour. This study argues that access to social capital is a critical determinant of career success, often privileging dominant groups while excluding racialized immigrants. The interplay between HCT and social capital theory creates compounded barriers, reinforcing systemic inequalities and limiting career advancement for marginalized populations. As Bourdieu’s work does not explicitly address racial disparities, this study integrates CRT to demonstrate how race fundamentally influences labour market outcomes. By bridging these theoretical perspectives, the research challenges dominant economic narratives and calls for policy reforms that recognize and dismantle structural barriers to economic equity for immigrant women of colour.

Resource Rhetoric in Three Canadian Novels, 1919-1945 - Uher, Valerie (University of Waterloo, 2025)
In this dissertation, I propose the term resource rhetoric to describe the cultural logic that renders extractivism an interminable part of Canadian identity. As Canada solidified its settler-colonial expansion in the nineteenth and early twentieth century, there was an attendant formalization of infrastructures promoting the extractivist ambitions of the state. Within those infrastructures a resource discourse—of natural resources and human resource management—was born. In Resource Rhetoric in Three Canadian Novels, 1919-1945, I examine three novels that articulate a cultural dimension to Canada’s broad attempt to adapt workers to a confluence of precarious working conditions in the first half of the twentieth century. I analyze the downplaying of class formation in these novels and link it to their use of resource rhetoric—tropes and figures that assert the primacy of the extractivist state over and against the primacy of the working-class collective. My thesis develops by first establishing the 1919-1945 period as one marked by an unease about whether workers could truly become the “human resources” Canada’s extractivist economy needed. I explore how this uncertainty is manifested in Douglas Durkin’s 1923 novel The Magpie, an economic novel set during the 1919 Winnipeg General Strike. I then demonstrate that during the interwar period, a worker’s success in embodying the ideal Canadian “human resource” identity was measured against a racial hierarchy emerging from eugenic ideology. In my analysis of Irene Baird’s 1938 novel Waste Heritage, I consider how the “rank and sort” logic of eugenics is used to calibrate moral rectitude in the novel’s portrayal of labour strife among Canada’s Depression-era unemployed. In the second part of my thesis, I consider how human resource discourse expanded to include social reproductive labour in the period just prior to the establishment of Canada’s welfare state. I argue that Gabrielle Roy’s 1945 novel The Tin Flute makes the home a terrain for potential class struggle against the exploitation of women’s work, while at the same time positioning this work as vital for the Canadian state to function. The rhetorical framing of workers in these novels consistently emphasizes their lack of agency and cooperation; foregrounds their interchangeability, and stresses workers’ inability to overcome their circumstances because of these factors. They articulate a deep-seated clash between the imperative that workers act as assets to Canada’s resource state, and the imperative that they might improve their lives through class formation and solidarity. While these novels are generally aligned with the resource discourse of the era, they demonstrate one fundamental failure of extractivist ideologies and resource logic: a person can never truly be a “dematerialized asset,” or a “universal Canadian worker subject.” My main claim in this thesis is that these novels show that to be a human resource is an unattainable goal.

Dependent Contractors and the Ontario Labour Relations Board: Understanding the Board's Role in a Capitalist Economy - Walchuk, Bradley Peter (York University, 2025)
This dissertation explores the evolution and politics behind the concept of the ‘dependent contractor’ in Ontario, from its earliest incarnations in the late 1970s to its current usage in the gig economy, as interpreted and applied by the Ontario Labour Relations Board (OLRB). It examines how the Board’s interpretation and application of dependent contractor provisions has impacted workers whose employment status falls somewhere between traditional notions of independent contractor and employee, i.e. the ‘grey area’ as the Board has referred to it, over a period of changing employment relationships and of increasingly precarious work. The research tracks these changes over time, examining how previous OLRB jurisprudence on dependent contractors can be seen to impact its decisions in more contemporary contexts (e.g Foodora, 2020) and what this might tell us about the Board’s understanding of employment relations in a changing capitalist economy. The analysis seeks to place the actions of the OLRB into a broader social context to assess what factors have influenced the Board’s decisions and gauge how it understands both its potential to address employment inequities and the limits it faces in doing so within a capitalist economy. This dissertation argues that the OLRB operated with an implicit industrial pluralist understanding of labour-capital relations and made decisions informed by that approach and, in doing so, lacked an appreciation of how capitalist workplaces were changing over time in a way that evaded control via that understanding. It further argues that while bodies such as the OLRB have some autonomy from capitalists and the capitalist state, they are unable to, nor are they designed to, overcome or dramatically alter the power imbalances that exist in capitalist civil society.

Empowered Margins: Women, Work, and Justice in Educational Labor - Woodford, Erin (Antioch University, 2025)
This dissertation examines economic justice and employment precarity faced by educators in both K-12 and post-secondary education systems. While literature explores themes of changing demographics in union membership, collective bargaining, labor activism, and gendered and intersectional inequities in academia, and women in leadership in unions, a critical gap of disabled women’s voices and solutions to the inequities remains. This study highlights how job insecurity, unequal pay, hiring biases, limited recognition of prior learning, and inadequate institutional support exacerbates mental health challenges, professional invisibility, and economic instability. In the K-12 unionized system, systemic barriers such include disregard for substitute teaching as a viable career and challenges for experienced teachers to get hired over cheaper, inexperienced teachers. In post-secondary education, shifting immigration policies, funding cuts, and undervaluation of non-traditional scholarship deepen instability. This research advances equity-focused strategies. By integrating lived experience with structural and systemic critique, the study calls for reforms that prioritize stability, recognition, and inclusive pathways for all educators navigating precarious employment and economic justice. The study contributes to broader conversations on improving women’s engagement and addressing the inequalities inherent in current labor systems.

Ethical Procurement In The 2026 FIFA Men's World Cup: Toronto's Efforts In Combating Sweatshop Labour - Al Horoub, Yazan (York University, 2024)
The anti-sweatshop movement has long committed to abolishing sweatshop labour and ensuring workers’ rights for all. There is an established body of literature on sport and the anti-sweatshop movement on the roles played by a range of actors concerning the mega-sporting events, which have been plagued with abuses of workers’ lives in the name of the sport spectacle. In effort to move past this troubled history, FIFA has embedded internationally recognized human and labour rights into their 2026 bid process. This study evaluates how the City of Toronto, Canada Soccer Association, and FIFA have considered ethical procurement and sweatshop labour as part of their bid for co-hosting the 2026 FIFA Men’s World Cup. Employing a critical theoretical approach, this study finds that despite the varying levels of considerations given to ethical (anti-sweatshop) procurement, the efforts remain insufficient. This is attributed to the unequal power dynamics that prioritize a discourse of (neoliberal capitalist) development for soft power.

Stigmatized (M)Others: Navigating Stigma, Sex Work, and Motherhood in Canada - Annett, Michelle Lesley (Carleton University, 2024)
Despite a large body of research exploring the obstacles sex workers face due to their occupational stigma, little research focuses on how their stigmatized paid work influences their navigation of unpaid care, especially in the context of the COVID-19 pandemic. My dissertation examines the narrated and photographic experiences of womxn in Canada who identify as both mothers and sex workers and asks: how do these womxn navigate and negotiate the daily work of unwaged social reproduction and paid work in stigmatized and precarious conditions? This dissertation is informed by feminist methodologies, visual methodologies, and contributes to literatures on stigma, sex work stigma, social reproduction, unpaid care work, mothering, and working motherhood. Fourteen participants in this qualitative project engaged in autophotography, capturing their daily routines and surroundings to provide visual insight into their daily lives. Then each participant attended a photo elicitation interview to discuss the meanings, experiences, and feelings being conveyed in their selected photographs. My findings illuminate that sex work stigma operates contextually, influencing these mothers’ engagement with and disclosure of their stigmatized paid work, their families’ experiences with courtesy stigma, and the structural barriers they face as sex working mothers. This dissertation also explores participants’ engagement with mothering practices, crediting their ability to be good, empathetic mothers because of their experiences navigating stigmatic occupations and their transferrable skills as sex workers. Womxn’s choices to navigate sex work and mothering are acknowledged as being both calculated and meaningful— granting sex workers financial security, flexible working hours, and unique opportunities to invest time into themselves and their families. To uphold the aims of producing accessible research, these images were displayed in public fundraising exhibits, relying on participant observation and anonymous feedback to further assess the project’s ability to co-produce destigmatizing and empathetic knowledges—by, with and for sex workers. All funds raised from these exhibits were donated to various sex worker grassroots organizations in Canada to assist in funding their ongoing mutual aid efforts and to ensure this research possess tangible benefits for sex workers themselves.

Platform Labour, Migration, And Resistance: Organizing Against Hyper-Exploitation In Paris And Toronto's Food Delivery Industries - Baril, Emile (York University, 2024)
This doctoral thesis combines empirical research and theoretical innovations aimed at comprehending the dynamics of platform labour within advanced-capitalist economies. Through case studies in Paris, France, and Toronto, Canada, the thesis contributes to the evolving landscape of platform labour studies, migration studies, and labour geography. The over-representation of racialized immigrants engaged in platform food delivery has attracted significant attention from both academia and mainstream media, notably in Toronto with international students from India and in Paris with sans-papiers from Africa. Focusing specifically on migration and working conditions, this study unveils hyper-precarity in Euro-American cities. The primary objective of the thesis is to provide a new perspective that includes immigration and citizenship within current discourse on platform labour. Drawing inspiration from critical urban studies, migration studies, and science and technology studies, the research introduces two conceptual propositions: i) “citizen-rentier-ship”, designed to elucidate how various stakeholders benefit from precarious citizenship status, and ii) a “relational comparison” of platform labour resistance, offering insights into the evolution of the unrest against platform labour exploitation—a crucial facet of urban development. The thesis is based on extensive interviews with food riders, workers, spokespersons, and other key actors, shedding light on their capacity for self-organization within advanced capitalist societies. By exploring strategies, limitations, and the dimensions of resistance—both digital and physical—through interactions with riders and individuals who resisted deactivation, low wages, and algorithmic management, the research contributes to a nuanced understanding of the challenges and opportunities faced by these workers. The case studies place emphasis on migrant workers’ perspectives. They reshape ongoing debates about global platforms by centering attention on the bottom ends of labour markets. In conclusion, the study contends that the struggles of migrant workers are deeply entwined with labour laws, immigration policies, misclassification practices, and urban policies in France and Canada.

Working-Class Affects: Connecting Affect Theory to Trade Union Revitalization Efforts - Barnett, Bronwen (Simon Fraser University, 2024)
In recent years, labour unrest in Canada and elsewhere has led to a resurgence in union organizing, job action and contract gains. This thesis sets out to understand how greater attentiveness to working-class affects or emotions might support this potentially revitalizing moment. Given the limited scholarship in this area, this study connects a literature review of affect theory with radical labour history to develop a framework for thinking about the affective dimensions of collective action within unions. Using that framework, the study then investigates the affective life of two Western Canadian unions through surveys and interviews. The thesis concludes that acknowledging and becoming more intentional in efforts to mediate the affective intensities that circulate, move people and organize life at the level of union membership represents an important focal point as a new cycle of class recomposition potentially takes shape.

Advocating for Labour Mobility and Permanent Residency for Canada's Seasonal Agricultural Workers from an International Human Rights Law Perspective - Barzegarikhanghah, Lily (Faezeh) (University of Manitoba, Faculty of Law, 2024)
This paper delves into the implications of Canada's Seasonal Agricultural Worker Program (SAWP) through the lens of international human rights law (IHRL), spotlighting the nuanced effects on migrant agricultural workers' rights. Originating in 1966, the SAWP has been pivotal in recruiting labour from Mexico and the Caribbean to bolster Canada's agricultural sector. The paper critiques the program's core policies, notably the restrictive employment system that ties workers to specific employers and the significant barriers to obtaining permanent residency (PR) and citizenship. These policies are scrutinized for their potential violation of fundamental human rights, including the rights to equality, liberty and security, and access to justice, under both Canadian and international legal frameworks. A comprehensive analysis is presented, underpinning Canada's obligations under IHRL and the apparent discrepancies within its treatment of SAWP participants. The study proposes substantial policy reforms aimed at rectifying these discrepancies, advocating for a transition towards open work permits, and establishing clear pathways to PR and citizenship for SAWP workers. The research underscores the necessity for Canada to reconcile its labour demands within the agricultural sector with its human rights obligations, ensuring a fair and humane treatment of migrant workers who play a crucial role in the country's economy.

Tell Dem Wagwan Fanon: On [Colonial] Violence and Prison Labour in Canada - Batelaan, Krystal Alisha (York University, 2024)
In this dissertation, I draw on Frantz Fanon’s concepts of cultural imposition and collective catharsis to examine how the colonized subject, like the incarcerated Black worker, undergoes a double process of dehumanization wherein they are perceived as both an invisible and hypervisible subject. I argue that the colonized subject is invisible insofar as they are subjected to various forms of dehumanization such as physiological and psychological abuse, lack of access to resources, and neglect. However, they are also perceived as hypervisible because they are viewed as existing in excess as hypersexual, hyper deviant, and hyper criminal creatures and therefore deserving of the treatment they endure. Similarly, the incarcerated worker is viewed as invisible and hypervisible because they are viewed as unskilled and subhuman beings undeserving of adequate pay and protections but are also perceived as best suited to work in poor conditions doing less skilled, undervalued, low-paying work. By tracing how this relationship between race, racialization and labour is underpinned by whiteness both historically and in a contemporary sense, I demonstrate how the use of prison labour within a Canadian multicultural context must necessarily be read through a normalizing white gaze, under the guise of public safety and rehabilitation; here the prison functions as a disciplinary site wherein Black and racialized prisoners are constructed as inferior beings in need of heightened control through labour. In doing so, I argue that the use of prison labour in Canadian prisons is a form of colonial violence that reproduces inferior and superior colonial identities.

Policing Sex Work Online: Sex Workers’ Views on the Risks and Benefits of Using AI to Police Online Ads for Sexual Services - Brown, Sydney (Simon Fraser University, 2024)
This thesis explored the potential use of artificial intelligence (AI)-based policing models in law enforcement anti-trafficking initiatives and examined potential impacts of expanding state surveillance through police use of AI-based policing models. Computer scientists aspire to develop AI to identify victims of trafficking through websites that host ads for sexual services. Little research has explored sex workers’ views on the proposed AI-based policing models and their likely impacts. To fill this gap, I conducted 21 semistructured interviews with sex workers, academics, and members of sex worker rights organizations to discuss the effects of AI-based policing models. Participants expressed concern that these models will continue a long history of anti-trafficking initiatives causing harm, particularly against racialized, migrant, and transgender sex workers. Findings also suggest developers should be cautious about creating AI-based policing models without input of sex workers and without a firm knowledge base of the sex industry.

Masculinity and Gig Work: A Case Study of Rideshare Workers in Toronto - Campo, Maya Selina (York University, 2024)
This thesis examines shifting masculinities and platform labour, following eleven semi-structured interviews conducted with male Toronto-based Uber and Lyft rideshare workers with dependents (children). Women have commonly done non-standard work, hence the proliferation of non-standard work being contextualized as the ‘feminization of work’ (Zahn, 2019). In contrast, rideshare work is a non-standard form of gig work done predominantly by men, rendering it a relevant form of platform work to examine with its complicated relationship to the historical context of gender and nonstandard work. This thesis argues for a need to organize the worker as a whole, examining how workers’ unpaid social reproductive labour and balancing of rideshare work, and often another form of paid work, impacts the viability of classic organizing methods. I argue that these issues of convoluted boundaries between paid and unpaid work must be incorporated into the potential organizing demands of a rideshare workers’ union and identify areas for further research on organizing rideshare workers accounting for shifting masculinities.

Disposable Qualifications, Disposable Lives: Examining the Labour Market Experiences of Foreign-Educated Racialized Immigrant Women - Chinchamie, Lisa (University of Toronto, Ontario Institute for Studies in Education, 2024)
This qualitative research study examines how the Labour Market Integration (LMI) site constitutes a site of ongoing colonial violence and spirit injury, where race plays a central role in legitimizing the politics of credential recognition, in which Foreign Educated Racialized Immigrant Women (FERIW) are evicted from the category “qualified” in Canada. My analysis draws upon concepts of racial capitalism and structural violence to locate the acts of eviction that FERIW are subjected to within the LMI space in Canada and the consequences and impacts of this eviction. I argue that racialized immigration on the move to Canada represents the human face of Canada’s ongoing nation-building and economic policy agenda. The LMI space reinforces and reproduces the colonial racial hierarchical order in Canada. Based on qualitative interviews with 12 FERIW, I explore how within the LMI space, racialized immigrant women are stripped of their foreign credentials, discursively framed as unqualified and deficient, and repurposed as a source of cheap labour within the political economy. Delegitimization carries severe material and socio-economic consequences. The intersectionality of race, ethnicity, gender, class, and immigrant status results in FERIW becoming “ghettoized” into low-paying, precarious, low-end jobs, and, for many of these women, low income and poverty. This work represents a decolonial work articulated through anti-colonial and feminist anti-racist theory, to present a nuanced historical account of the experiences of gendered racialized immigrant labour within global and local structures that look very similar to the old structures of colonialism.
Accepted: 2024-11-08T16:57:10Z

Queer Oral Histories of Deindustrializing Cape Breton - Devitt, Liam (Concordia University, 2024)
Queer history in Canada has often centred around metropolitan areas, like Toronto and Montreal, usually foregrounding social movements. This means that queer histories of the periphery are often overlooked, and that histories of metropole are taken as representative of the national context. In this thesis, I examine queer oral histories of Cape Breton, Nova Scotia. Through these oral histories I aim to complicate dominant narratives in both queer history and histories of deindustrialization in Canada. Cape Breton is a former steel and coal region in Nova Scotia that underwent a comparatively slow, state-managed deindustrialization in the latter half of the 20th century. Today, like in deindustrialized areas across the world, the “structure of feeling” of industrial life remains, despite plant and mine closure. Often, histories of deindustrialization center around a mythologized white male (and indubitably heterosexual) breadwinner, centering not just workers, but the specific function that masculine industrial labour played in the social reproduction of the Fordist accord in the household. By taking up the life stories of queer people, we can critically examine this centring of the nuclear family in deindustrialization studies. In the first chapter, I offer a theoretical and historiographical intervention arguing for a queer investigation of deindustrialization. In the second chapter, I apply this line of thinking to oral histories of Cape Breton queers, arguing that these narrators’ desires for queer history and queer future are ultimately filtered through the prism of deindustrialization’s half-life.

The Making of Blindness in Ontario: Incarceration and Class Formation, 1872–1926 - Dressler, Harrison (Queen's University, 2024)
This thesis examines the experiences of pupils-cum-inmates who attended the Ontario Institution for the Education of the Blind (OIB) during the late nineteenth and early twentieth centuries. Customary assessments of segregated education, which investigate administrators’ campaigns to implement pedagogical or curricular advancements, have characterized institutionalization as educational and emancipatory. Instead, this project challenges identity-centric, rights-based narratives by reframing the OIB as constitutive of Ontario’s carceral apparatus. Drawing upon first-person testimony gathered during four investigations into the OIB conducted by the Government of Ontario, the analysis demonstrates that capitalist development dispossessed blind Canadians from waged labour, generating an underclass of precarious and oft-wageless proletarians. Institutionalization socialized the workers-in-training within a prison-like environment where punishments like whippings and beatings, solitary confinement, and material deprivation were commonplace. Educational opportunities were haphazard and irregular, while living and working conditions were uncomfortable, bordering on intolerable. Biomedical understandings of blindness rationalized the mistreatment of inmates, as administrators attempted to reintegrate graduates into waged labour. Children and adolescents survived by developing cultures of delinquency and transgression; inmates, especially working-class inmates, organized popular resistance movements that challenged institutional authority. Educational authorities responded by overseeing the repression of working-class culture. By funneling graduates into either working-class occupations or “gentlemanly” and “learned” professions, institutionalization fomented processes of class formation, creating, first, an underclass of labourers and musicians and, second, a vanguard of capitalists and professionals.

Maritime Mastery: An Appendage of the West Indian Plantation and New England in Colonial Canada - Eaton, Jesse R. (University of Calgary`, 2024)
Scholarship on the development of slavery in the colonial Maritimes region during the pre-Loyalist period remains scarce, with even fewer studies examining slave ownership. By situating the expansion of slaveholding in the region (that makes up present-day Nova Scotia, New Brunswick, and Prince Edward Island) within the Atlantic world socio-economic context, I show how Maritime society reproduced anti-Black attitudes and slaving practices found in West Indian slave societies. Through trading and social relationships with New Englanders, the region’s colonisation became tethered to the Caribbean. New England’s commercial dependence on West Indian plantations beginning in 1637, and expanding thereafter, fostered intra-regional mercantile and military ventures, bringing their Caribbean partnerships into the Maritimes after the Treaty of Utrecht in 1713. The social aspects of these commercial interactions reveal how settling New Englanders transplanted their ideological, interpersonal, and familial connections to the Caribbean and their slaveholding norms to the Maritimes. By comparing Maritime slave-owning practices to those found in the West Indies, we see Maritime slaveholding to be, in many ways, a mere extension of the plantation regime.

The Confederation of Canadian Unions (CCU), 1969-1992 - Godden, Mason (McMaster University, 2024)
This dissertation provides the first historical overview of the Confederation of Canadian Unions (CCU) and its affiliates from 1969 to 1992. Formed at the end of the 1960s as a foil to the Canadian Labour Congress (CLC), the CCU sought to nationalize the Canadian labour movement by fomenting the formation of Canadian unions. As a left-nationalist labour body, the CCU charged the CLC with conservatism, complacency, and collaboration in its approach to organizing and collective bargaining. Chief among the CCU’s concerns was the domination of American international unions in the CLC. Throughout the 1970s and 1980s, the CCU organized workplaces in unorganized industries, bringing a host of immigrant women into the ranks of the Canadian labour movement, while establishing large bargaining units in industries primarily organized by American unions. At the same time, the CCU forwarded a left-nationalist politics inspired by the New Canadian Political Economy (NCPE) that criticized Canada’s economic, political, and cultural dependence on the United States, and used this politics to mobilize its members against continental free trade and towards a nationalized, socialized home economy. The CCU and its affiliates also formed important linkages with the New Left and the women’s movement during these decades and proved itself a militant actor in confrontations with the state and industrial law. Several CCU affiliates eventually merged with the Canadian Autoworkers (CAW) in the 1990s in the wake of extensive economic restructuring and corresponding changes in the Canadian labour movement. The dissertation contributes to the scholarship on industrial relations, industrial legality, and nationalism by providing a historical case study of a left-nationalist labour institution that simultaneously challenged and was shaped by federal and provincial law. It provides a critical institutionalist perspective on union federations that accounts for the law as a contested terrain, and nationalism as a historically contingent politics.

Not All Disability Is Created Equal: A Comparative Historiography of Workers' Compensation and Disability Benefits in Ontario, Canada - Heath, Bonita Lee (York University, 2024)
This dissertation establishes that work injury and injured workers are relatively neglected in Critical Disability Studies (CDS). A further observation is that CDS tends to avoid a class analysis of disability politics in favour of identitarian approaches. This research focuses on income security. Through a Marxist critical policy historiography, I compare workers’ compensation benefits and state-sponsored benefits for disabled people whose disabilities originated outside of the workplace in Ontario. I argue that the workers’ compensation program is superior to the state-sponsored program because of the class location and politics of the respective groups of people with disabilities seeking income security. The discussion also highlights some of the reasons for the missing injured worker in CDS. Specifically, injured workers experience disability as a loss worthy of compensation rather than a positive identity. Further, rather than viewing prevention measures as the erasure of disabled people, injured workers support the prevention of disability through occupational health and safety laws and workplace practices. By focusing on the political economy of each program, the historical narrative suggests that disability benefit programs in Ontario were developed less by moral suasion and more because of their role in capital accumulation. Although the argument holds for the early history of the two programs in their early history. the negative impact of neoliberalism on both workers’ compensation and the current benefits program in Ontario (the Ontario Disability Support Program) has created a convergence of interests between permanently impaired injured workers and other disabled people, underscoring the importance of including injured workers’ perspectives in CDS.

Experimental Regulation to Address Modern Slavery and Forced Labour in Global Supply Chains: Canada's Passage of Transparency Modern Slavery Legislation - Humphrey, Jonelle (McMaster University, 2024)
Embargoed until: 2025-11-29 This thesis explores Canada’s regulatory response to modern slavery in global supply chains. It investigates the factors which influenced Canada to enact transparency modern slavery legislation. It also analyzes Canada’s strategy of utilizing multiple soft and hard law governance and regulatory techniques to strengthen its response to modern slavery. Using a theoretical framework which combines global governance and regulation literature with literature regarding the national institutionalization of global norms, this thesis examines how international actors that comprise the global anti-slavery network disseminate anti-slavery and corporate accountability norms. These norms are subsequently filtered through a country’s domestic political economy, and are translated into either transparency or mandatory human rights due diligence (MHRDD) legislation. The qualitative methods used in this thesis were documentary analysis and key informant interviews. Key informant interviews in conjunction with an analysis of relevant reports and parliamentary debates provided insight into the influences behind Canada’s enactment of various governance and regulatory techniques. Doctrinal legal analysis, and an assessment of the various techniques implemented in Canada, revealed the effectiveness of the individual techniques and how they interacted with each other. This thesis found that Canada adopted a transparency law due to a combination of: (1) International norm diffusion via an epistemic, global anti-slavery network; and (2) Canada’s unique domestic political economy. Features of Canada’s domestic political economy, including its affiliation as part of the Anglosphere, and its powerful mining industry, ultimately determined the enactment of transparency legislation. The thesis also found that Canada’s use of multiple, increasingly hard law governance and regulatory techniques is currently ineffective as these techniques do not complement each other, and actually weaken Canada’s regulatory response to modern slavery. Consequently, labour standards have not improved for supply chain workers. This thesis posits that Canada should prioritize centering and empowering workers to protect their own rights.

The Effects of Minimum Wage Increases on Employment and Average Wages of Affected Workers in Canada - Iray Makvandi, Alaleh (Concordia University, 2024)
The employment effects of the minimum wage are debated among economists, with traditional competitive models suggesting potential job losses for low-wage workers, while alternative models like institutional and dynamic monopsony suggest potential positive impacts. The institutional model posits that raising the minimum wage could boost employment if wages are below the marginal product of labor, and the dynamic monopsony model suggests that higher minimum wages could reduce turnover costs in low-wage labor markets, mitigating predicted job losses. Empirical studies, even within the competitive model, show mixed results, with some indicating significant disemployment effects and others not. This thesis provides a comprehensive analysis of the impacts of minimum wage increases on employment and wages across Canada, utilizing a robust methodological framework including the bunching approach, event study analysis, and difference-in-difference methods to examine the effects of varying provincial minimum wages over time.To accomplish this, I first employ the bunching approach to detect any concentration of wages just above the minimum wage threshold, providing insights into employer behavior in response to wage regulations. This technique identifies subtle adjustments in wage distribution that might not be apparent through other methods. Next, I utilize event study analysis to explore the immediate and long-term effects of minimum wage hikes, comparing employment and wage data from periods before and after the increases. This method captures both short-term disruptions and long-term adjustments in the labor market. Additionally, the difference-in-difference method is employed to compare outcomes between provinces with and without minimum wage increases, isolating the specific effects of these policies by controlling for other influencing variables. This approach underscores the importance of regional economic conditions in shaping the effectiveness of wage regulations. The empirical analysis begins with Labor Force Survey data from Ontario, which experienced significant real minimum wage increases in January 2018. The study estimates the counterfactual frequency distribution of hourly wages in Ontario for three years before and two years after the minimum wage increase. The findings show a significant decrease in jobs paying below the new minimum wage and a proportional increase in jobs paying up to $4 above the real minimum wage, indicating no significant overall employment impact. Contrary to anticipated employment effects, the average wage of affected workers increased significantly by 22.7% over the two years following the minimum wage shock. The only exception in the Ontario study was for the teen group; contrary to much of the existing Canadian literature such as Fossati and Marchand (2024), I found a significant positive employment effect for teenagers. However, overall, I did not observe a significant negative employment effect for young adults. Further analysis includes other provinces, such as Alberta, and cities such as Gatineau versus Ottawa, which also experienced substantial nominal and real minimum wage increases. The study applies the same methodology to assess the employment and wage effects, finding similar results to the Ontario study. Contrary to the Ontario study, in the Alberta study, I found a significant negative employment effect for the teen group, but overall, I did not find a significant negative employment effect for young adults. Since referring to a single minimum wage is inherently problematic, I also investigated a pooled analysis of hourly wage data from all Canadian provinces from 1999 to 2019. This analysis, covering 56 minimum wage increases, reveals no significant employment effect (-2%) over six months following minimum wage increases but a significant average wage increase (6.4%) for affected workers. The study also investigates potential employment shifts from low-skilled to high-skilled workers, finding no indication of such shifts. Subgroup analyses by education level, age, and other demographics show approximately similar employment and wage effects, suggesting that the consequences of minimum wage policies are shared among different worker groups. Additionally, sectoral analyses show no negative employment effect in the food industry, aligning with Card and Krueger (1993)’s findings on the impact of minimum wage increases in the fast-food industry. However, a significant negative employment effect (-4%) was observed in the retail sector, highlighting the influence of local industry composition on minimum wage impacts. Finally, in the Canada study (pooling all 56 minimum wage increase across all provinces), I assess the size of wage spillovers, finding that only 7% of the impact on average wages of affected workers comes from wage spillovers at the lower part of the wage distribution, which was statistically insignificant. This aligns with Canadian literature, such as Campolieti (2015), which found modest wage spillovers based on Canadian data compared to American data. Overall, this thesis provides robust evidence on the employment and wage effects of minimum wage increases in Canada. The findings suggest that, contrary to the traditional competitive model, minimum wage increases do not significantly reduce overall employment of low-wage workers and can lead to substantial wage gains for them. This has important implications for policymakers considering minimum wage adjustments to improve labor market outcomes for low-wage workers.

Workers in Canada's Energy Future: Sociotechnical Imaginaries, Settler-Colonialism, and the Coastal Gaslink Pipeline - Lajoie O'Malley, Alana (University of Ottawa, 2024)
In recent years, scholars of science and technology studies (STS) have increasingly turned their attention to the role of collective imagination in shaping sociotechnical futures. This scholarship leaves open the question of how the collectives involved in bringing these futures to life come into being. Starting with one episode in the ongoing conflict over the construction of Coastal GasLink pipeline on Wet’suwet’en territory in settler-colonial Canada, this discourse analysis draws on scholarship in feminist, anticolonial, and co-productionist STS to study this process of collective formation in relation to sociotechnical futures. It does so by examining how oil and gas workers become enrolled into a sociotechnical imaginary I call Canadian resource techno-nationalism. Comparing media and politicians’ representations of oil and gas workers with White workers’ representations of themselves indicates that they can end up participating in this imaginary regardless of their affinity to it. Examining policy documents and scholarly literature about the inclusion of Indigenous knowledges in impact assessment, as well as political debates and mainstream media coverage about the conflict over the Coastal GasLink pipeline, draws attention to how elites’ active construction and protection of the boundary between knowledge and politics works to enroll Indigenous people into oil and gas jobs and, therefore, into the collective performing Canadian resource techno-nationalism. In both cases, elite actors deploy the resources at their disposal in ways that help funnel oil and gas workers into lives imagined for them, securing the power of the settler state in the process. This dynamic illustrates the importance of disentangling participation in the collective performance of sociotechnical imaginaries from freely given consent. Residents of liberal states can end up performing dominant imaginaries less out of any sense of affinity to them than as a response to the disciplinary power these imaginaries help sustain.

Smoke on the Water: A Critical Discourse Analysis of Reconciliation in the Case of the Mi’kmaq Moderate Livelihood Fisheries - MacCarthy, Liam (Dalhousie University, 2024)
Indigenous communities have been in direct conflict with the Canadian state when asserting their right to self-determination. Literature reveals that the Canadian state interprets Indigenous resistance as a threat to settler authority, responding with violence and criminal enforcement. This thesis investigates the relationship between the norms related to Indigenous rights articulated in the Truth and Reconciliation Commission and the institutional enforcement response to Indigenous resistance in the case of Mi’kmaw moderate livelihood fishing. Through a critical discourse analysis of Fisheries and Oceans Canada and Royal Canadian Mounted Police’s public statements, policy documents, and recorded actions, this research found a discursive influence on state institutions. Despite the rhetorical commitments, this research found that state response continued an approach of criminalization and violence against Mi’kmaw moderate livelihood fishers. These contradictions between rhetoric and practice challenge the institutional legitimacy of settler authority.
Accepted: 2024-08-30T13:35:43Z

Ableism in Higher Education: Collective Agreements, EDI [Electronic Data Interchange] Initiatives, and Accommodation Policies - McCabe, Kealin M. (University of British Columbia, 2024)
This study explores ableism within higher education through an examination of the collective agreements and institutional policies that govern the academic responsibilities of disabled faculty members. Critical disability theory serves as the theoretical framework for this study, which employs both institutional ethnography and qualitative content analysis in the review of the publicly available documents from English speaking U15 Group of Canadian Research Universities (n=13). The study unfolds in three parts: Part I presents the findings from the analysis of the collective agreements and institutional policies outlining the tenure and promotion process and the barriers disabled faculty members experience in fulfilling their academic responsibilities. Part II explores the tensions and contradictions between institutional accommodation processes and the language used in their public presentation of EDI initiatives, while Part III represents the everyday experiences of disabled faculty members though interviews, representing the embodiment and internalization of the texts examined in parts I and II. This research challenges and disrupts normative understandings of what it means to be a “good academic”, by addressing an absence in the literature exploring ableist representations and assumptions present in collective agreements and institutional policies. The examination of these texts and the lived experiences of disabled faculty members through interviews has illuminated the existing contradictions and tensions in these texts, showing ableism is strongly entrenched and condoned in university policies and governance.

"His Toolbox is not Full": Unpacking Worker Experiences and Addressing Labour Support in Atlantic Canadian Fishing - McTaggart, Benjamin (University of Ottawa, 2024)
Given the importance of the fishing industry to the Newfoundland economy and identity, understanding the realities of fish work in the province allows for a deeper understanding of labour practices, safety regulations, and the health of the many fisheries the bolster that Newfoundland economy and identity. Initially designed to assess the working experiences of migrant workers on Canadian fishing boats, this thesis turns to domestic workers to unpack labour realties and address the potential of exploitative and abusive practices that help chart fishing among one of the most dangerous jobs in the world. This research took place in Newfoundland in October of 2022, where crew members, boat captains, their owners, and industry and union representatives were approached to gather work experiences and opinions on the broader regional fishing industry in the province. From these experiences, an assessment of how and if exploitative working conditions can be improved utilizes existing and proposed international labour conventions, understandings of unionization, and the political economy, to represent exploitative labour conditions along a continuum. The evolving and changing economic and environmental realities of fishing both globally and in eastern Canada highlight how an already risk-taking, masculine, and community focused industry lives with, is shaped by, and can work towards limiting, the more damaging forms of exploitation. This thesis utilizes qualitative data to inform its assessment of precarious labour realities at sea in the Newfoundland fishing industry to further advocate for the move towards regionalized and industry specific seafarer support mechanisms. Through promoting these mechanisms, such as a seafarer support centre and the ratification of the Work in Fishing Convention (C188), this research calls for Newfoundland's fishing industry to lead the way towards better practices nationally.

Learners or Earners? Interviews with International Students in Canada on Navigating Student-Worker Mobility Pathways - Merriam, Deanna (University of New Brunswick, 2024)
This thesis explores the lived experiences of international students in Canada, examining the impacts and outcomes of Canada’s International Student Program (ISP) that positions students as not only educational participants but also flexible economic assets. Through a brief review of international student policy developments, it is argued that these changes reflect a deliberate effort to commodify international students' labor to meet Canadian labor market demands. The thesis also draws on migration literature to highlight the exploitative risks inherent in foreign labor pathways, applying these concerns to the International Student Program. Through the use of qualitative semi-structured interviews with international students and support professionals, this study reveals the challenges students face under these policies including permit or program navigation, financial instability, and most notably adverse impacts on well-being. This study highlights the complex relationship between Canada’s various mobility programs and notes the benefits of utilizing qualitative methodologies in researching program outcomes.

An Unexpected Alliance: A Participatory Case Study of Labour-Environmentalist Collaboration for Better Transit in the Central Okanagan - Pulles, Kirstin (University of British Columbia, 2024)
This thesis investigates the role of Kelowna’s public transit union (the Amalgamated Transit Union Local 1722 – ATU 1722) and a youth-led environmental group (Fridays for Future Kelowna) in the formation of the Okanagan Transit Alliance (OTA). The OTA is a grassroots movement for better public transit in the Central Okanagan. The central research question is, "how can transit unions engage in climate activism?". A participatory activist methodology is employed to study the joint campaign for more accessible, publicly managed, and community-driven transit. The findings are organized into three themes. The first theme is ecosocialism – a political ideology which centers ecological concerns in socialist thought – because the campaign advocates for an ecosocialist goal of ending the private management of Kelowna’s transit. The findings in this area highlight the importance of organizing around people’s basic needs, uncertainty about the role of the government in the campaign, and that engaging in collective struggle is important for developing working-class power. The campaign was co-led by the ATU 1722, and so the second theme, unions, examines their role in the campaign. Under this theme are the findings that the two leading organizations developed a mutually beneficial collaboration, and that the public facing role of bus drivers helped the union build connections with the community. At the same time, contemporary union challenges impacted the ATU 1722’s ability to engage in effective advocacy. Finally, under the third theme of organizing, the research broadly explores organizing tactics to develop the climate justice movement. We found that a welcoming environment and co-creation led to high participation levels, and that relationships were fundamental to the campaign. This thesis highlights the potential of unions to play a pivotal role in climate activism, bridging the gap between labor and environmental concerns. The case of ATU 1722, Fridays for Future Kelowna, and the OTA serves as an inspiring example of how labor organizations can actively contribute to the broader movement for environmental justice and ecosocialist transformation. This study not only informs the ongoing discourse on the intersection of labor and climate activism but also inspires future collaborations for anti-capitalist climate justice.

Labour Market Gatekeepers: The Role of Human Resource Management Professionals in Immigrant Labour Market Integration in Alberta, Canada. - Redwood, Chene Royan (University of Calgary, 2024)
Despite new immigrants having higher educational attainment and an immigrant selection policy that admits “the best and the brightest,” one of Canada’s major social policy concerns is the continued deterioration of immigrants’ economic outcomes. This paradox is illustrated by data showing immigrants suffer from higher unemployment, earn less than similarly educated Canadian-born workers, face skill underutilization, and are relegated to the secondary labour market made up of low-wage, unstable jobs, lacking protections such as unemployment benefits. The underutilization of immigrant skills is economically disastrous; it costs the Canadian economy $50 billion yearly. While many studies discuss immigrants' poor labour market integration, offering explanations such as immigrant human capital factors or macroeconomic condition factors, few explore the role of meso-level organizational social actors who decide which immigrants are recruited, shortlisted, and ultimately hired. This dissertation seeks to fill this gap by exploring the role of Human Resource Management (HRM) professionals in immigrant labour market integration in Alberta. Using interviews and critical discourse analysis of HRM textbooks and course outlines, I examine HRM professional's decision-making policies, processes, considerations and constraints when evaluating immigrant applications for jobs. The study reveals that immigrants, particularly racialized immigrants, face barriers to employment in the primary labour market because of the professional and institutional logic of strategic human resource management (SHRM). SHRM promoted in HRM professional education recommends that HRM professionals prioritize business objectives over equal treatment, consideration, and fairness in hiring. SHRM enables unequal power relations between hiring managers (team supervisors) and HRM professionals, which enables cultural racism to go unchecked in hiring. SHRM justifies organizational discriminatory and social closure practices as well as enables the denial of immigrant claims for employment. This is based on the perception that immigrants pose administrative burdens and financial risks stemming from the misidentification of immigrants as temporary migrants and possessing human capital and cultural deficiencies. Hiring decision-makers often do not rely on objective assessments like work sampling tests when making hiring decisions. Instead, when evaluating immigrant job applicants, they rely on racial cultural stereotypes and signals of White Canadian cultural competency as the basis for callbacks and selection.

Temporary Foreign Workers in Canadian Labour and Human Rights Tribunals: A Comparative Analysis - Reid, Taelor (University of Guelph, 2024)
Due to their status, it is difficult for temporary foreign workers to report grievances related to instances of discrimination, exploitation, harassment, abuse, and health and safety violations. While the subject of temporary migrant work and legal action has been studied before, available research focuses on the impacts of high-profile cases at the Supreme Court. As such, there is limited research about the tribunals that handle the grievances of TFWs most often. This thesis fills that gap by presenting a comparative analysis of the fortunes of temporary foreign workers in human rights tribunals and labour tribunals in Ontario and Alberta. This analysis shows the nature and outcome of these hearings have important differences that depend on the tribunal type. More specifically, human rights tribunals seem to be better equipped to assess the grievances of TFWs despite there being a higher volume of TFWs using labour tribunals.

Not Just Nice Guys: The Growth and Constraint of the Nova Scotia Teachers’ Union, 1950-1975 - Robben, Alex (Dalhousie University, 2024)
This study traces the mid-twentieth century history of the Nova Scotia Teachers’ Union (NSTU), with particular focus on the union’s democratic, professional, and bargaining structures. Traditionally underrepresented in labour union histories, teachers’ unions are a keystone public occupation with extremely high industrial density and a complex relationship with numerous levels of government. In the period studied, teachers were paid both by provincial and local governments but were technically only allowed to bargain with the former; this relationship was instrumental in keeping teachers’ demands depressed but was too unstable to contain teacher militancy effectively. Following an interrogation of the union’s restrictive legislative and organizational foundation, the thesis analyzes the adoption of professionalism as a status-raising strategy, but with severe exclusionary tendencies. The thesis continues with a chronological recounting of provincial and local-level negotiations, the contention of which forced the union and the provincial government to renegotiate their bargaining mechanisms.
Accepted: 2024-08-30T13:51:36Z

Navigating Precarious Paths: An Assessment of the Open Work Permit for Vulnerable Migrant Workers - Weeks, Alyssa (Dalhousie University, 2024)
Temporary migrant workers on closed work permits are vulnerable to exploitation and abuse. To address this precarity, the Government of Canada introduced the Open Work Permit for Vulnerable Workers (OWP-V) in June 2019. This permit allows migrant workers in abusive situations, or at risk of abuse, to leave their employers and find new work in Canada for up to 12 months. Drawing from secondary literature, policy analysis and qualitative interviews with migrant support workers and experts, this research assesses the implementation of the OWP-V policy in the Maritimes by examining its benefits and critiques. This research demonstrates that although some perceive the policy as a step in the right direction, significant barriers remain that hinder the effectiveness of the OWP-V in removing migrants from abusive conditions. Further findings demonstrate that even with systemic and technological improvements, stakeholders remain dissatisfied with the policy as it fails to protect migrant workers from re-entering cycles of abuse and exploitation, serving only as temporary relief. To improve the implementation of this policy, stakeholders provided several suggestions pertaining to accessibility, language options, processing times, and inspections. Overall, this thesis argues that while these changes could help improve the working conditions of temporary migrant workers in Canada, substantial systemic issues remain.

The Affective Basis of Judgements and Narratives Surrounding Sexual Commerce in Western Canada in the Late Nineteenth and Early Twentieth Centuries - York-Bertram, Sarah Elizabeth (York University, 2024)
This dissertation undertakes an affective reading of late-nineteenth and early-twentieth century Canadian primary sources through which to analyze the affective basis of judgments and narratives surrounding sexual commerce. Situated in the interdisciplinary subfield of the history of emotions, this dissertation centres sexual commerce as a site of colonial worldmaking in what are currently the southern regions of the provinces of Manitoba, Saskatchewan, and Alberta, and traces emotional through-lines across fields in social space. Beginning with a self-reflexive prologue drawing from a method feminist theorist Clare Hemmings (2011) terms “situated horror,” this dissertation then turns to the Dominion of Canada’s post-1867 westward expansion, its legal mechanisms, and affective mobilizations. Across the empire, Britain tied legislative powers to feelings that reflected its goals, ideal social order, and habitus of its peoples. Like a mathematical equation, peace in the colonies would emerge through order and good government and law-abiding citizens would be its beneficiaries. That equation was integral to the shift from a fur trade economy to a settler colonial one oriented toward a British imperial and Canadian economic disposition. The corollary effect of the equation was the normalization of British and Canadian views on what constituted peace, their conceptions of capital, and the conceptual transplant of disorderly figures, such as the “rebel,” the “vagrant,” and the “prostitute” – or, broadly, people defined as “outlaws.” Three main sites of colonial worldmaking are examined in this work: that of the journalistic field in chapter four, that of the political field in chapter five, and that of the juridical field in chapter six. By tracing emotion in oft-cited, and not-so-oft-cited, primary sources that discuss concerns about and responses to sexual commerce, the emotions underpinning narratives and judgments surrounding sexual commerce become evident. This method offers an emotions history of western Canadian colonial expansion, revealing how sex workers, histories of sex work, and feelings about sexual commerce were integral to Canadian worldmaking. Responses to sexual commerce were informed by the Dominion of Canada’s worldmaking mission, concerns over human unfreedom, and dynamic social positionings in emergent settler colonial society. British imperial and Canadian whiteness were produced through gendered-racialized processes of differentiation at the local, municipal, provincial, federal, and imperial levels. White men’s feelings of satisfaction dominated in this history, as they intensified their gendered monopoly on resources, space, and authority in a region that had been known as Indigenous peoples’ territories. This analysis of masculinized emotions contributes to the feminist theorization of colonialism and sexuality.

Queer Utopian Theory for Transformative Change in Theatre Organizations - Zarrillo, Maria (Royal Roads University, 2024)
Canadian theatre has the potential to incite social change but inequitable working environments within theatre organizations have hindered this prospect. The sector needs new frameworks to improve conditions for arts workers. Inspired by several scholars such as José Esteban Muñoz, Jack Halberstam, and Lee Edelman, I look to the concept of queer utopia to address inequities within the theatre sector, with a focus on the role of theatre organizations. By defining Queer Utopian Theory (QUT), analyzing calls to action in the Canadian theatre sector, and employing three focus groups, I created a Queer Utopian framework for Canadian theatre organizations to answer the research question: What is the utility of the concept of queer utopia in addressing inequities in the Canadian theatre sector? My research found that relationship building, embracing fear, and subverting socio-political norms are aspects of QUT that are of utility to organizational leaders who wish to foster equitable environments.

From the Voices of Mexican Seasonal Farm Workers in Alberta - Barba González,, Maricruz (University of Alberta, 2023)
In response to labour shortages across various sectors, including agriculture, the Government of Canada created the Temporary Labour Program, one stream of which is the Seasonal Agricultural Worker Program (SAWP). Mexico is currently the major partnering country, which runs the matching Programa de Trabajadores Agrícolas Temporales (PTAT) which accounts for 43.8% of all migrant seasonal farm labourers in Canada (SRE, 2022). With the increasing number of migrant workers in Canada, there are growing concerns about their labour and living conditions. Loo (2014) and other authors contend that to improve international labour programs so as to better serve foreign workers, it is critical to learn migrant workers’ perspectives by having their voices heard. There are, however, challenges to speaking with foreign farm workers, including language differences, rural locations, long workdays, living constraints, and fear of speaking out. Most research on migrant workers has been conducted in Ontario, Quebec and British Columbia, which have the highest provincial numbers. Conversely, there has been little research examining migrant workers’ experiences in the province of Alberta. My qualitative, participatory research contributes to the literature by exploring the perspectives of Mexican seasonal agriculture workers who have participated in the PTAT in Alberta. I used a focused ethnographic approach and methods of PhotoVoice and semi-structured interviews to learn about their motivations for enrolling in the PTAT and their experiences of working in the agriculture sector in this provincial context. Participants' narratives and photographic images provided information about: their motives for enrolling in the PTAT; how they navigated the application process; their lived experiences while working on farms and other agriculture businesses in Alberta; the impacts on their health and well-being; and, their perspectives on their role in Canada’s agri-food system. I also explored workers’ perspectives on being part of this international labour program during the COVID-19 pandemic and how this influenced the different stages of their experiences, both in Mexico and Canada. As part of the investigation of participants’ perspectives on health and well-being, I asked them about their access to health services and healthy and culturally appropriate food, and opportunities they had to experience community life in Alberta. Many of the findings from this research align with previous studies illuminating the vulnerable and challenging working and living conditions of migrant agricultural workers in Canada. Novel insights gained through this participatory research with Mexican migrant agriculture workers in Alberta focus on the application process and institutional context in Mexico, workers’ perspectives on their health and well-being, and their narratives and photographic images about their lived experiences in Alberta during the COVID-19 pandemic.

“Short-Term Band-Aid Solutions”: A Feminist Analysis of Family Caregiving and Caregiver Immigration Policies in Canada - Champagne-Holland, Morag (University of Victoria, 2023)
Throughout Canada, the need for care provision services is on the rise. The number of people willing and able to provide these care services is insufficient to address the growing need for care. Care work is provided by a mix of paid workers and unpaid family members. The majority of both these groups of care workers are women. Care work has long been undervalued as feminized labour, resulting in insufficient government support for family caregivers, and persistent labour issues within paid care sectors. In this thesis, I explore two distinct sets of Canadian federal policies related to care provision – Employment Insurance (EI) benefits for unpaid family caregivers, and the Home Child Care Provider and Home Support Worker Pilot Programs, which facilitate the immigration of private in-home caregivers to Canada – in order to discover whether they are underpinned by a shared set of similar assumptions about the nature of care work, who is best suited to perform it, and how it should be provided. In examining the assumptions about care that underpin and shape these policies related to care provision in Canada, I identify a number of consistent gendered themes about care and care providers and analyze their impact on policy outcomes.

The Politics of Low Pay: Corporatism, Left-Wing Parties and Low-Wage Workers - Durocher, Dominic (University of Ottawa, 2023)
Politics has often been conceptualized as a conflict between political parties that represent the economic interests of different groups in society. This conception of politics has, however, been considerably weakened by the economic and social transformations of the last decades and by the rise of post-materialist values among newer generations of electors. Indeed, the vote of manual workers for left-wing parties has declined significantly in recent decades as did the impact of left-wing parties on social spending. At the same time, the issue of low-wage work has become prominent in the partisan debates of several countries such as the United States, Canada and the United Kingdom following the mobilization of low-paid workers, unions and community associations. Low-wage workers who mainly work in the service sector have often precarious work and living conditions following decades of labor markets deregulation and are highly dependent on governmental policies to insure decent living and work conditions. One of these policies, the minimum wage, has been at the center of the electoral campaigns of many left-wing parties in recent years. However, the issue of low-wage work has rarely been studied in political science. This thesis seeks to explain the partisan dynamics surrounding the issue of low-wage work. My main argument is that low-wage workers tend to vote for left-wing parties in accordance with their economic interests, especially in countries with a weak degree of corporatism such as the United States and the United Kingdom. In those countries, left-wing parties have strong incentives to make pledges related to low-wage work like increasing the minimum wage in their electoral manifesto, because unions are unable to negotiate decent working conditions for the majority of workers. Indeed, in countries with weak corporatism, low-wage workers are very dependent on governmental interventions to ensure minimum working standards and improve their living conditions. In countries with strong corporatism, however, unions negotiate collective agreements that ensure minimum working conditions for the majority of workers, workers with weaker bargaining power are thus less dependent on government policies to insure decent working conditions. Therefore, left-wing parties should be able to consolidate their vote among low-wage workers in countries with a weak degree of corporatism. Once in power, left-wing parties should also increase the minimum wage and the direct cash transfers to low-income families more than governments led by right-wing parties, especially when corporatism is weak. The emphasis on policies targeted to low-wage workers by left-wing parties in countries with a weak degree of corporatism could also limit the capacity of radical parties to attract the vote of low-wage workers. This thesis is composed of 4 articles, one on electoral pledges related to low-wage work, one on the vote of low-wage workers, one on the impact of left-wing parties on minimum wages and one on the impact of left-wing parties on direct cash transfers received by low-income families. These four articles demonstrate the relevance of a materialist conception of politics and the role of institutions regulating the labor market on partisan dynamics.

College Contract Faculty in Ontario: Professional Identities and Precarious Employment - Fick, Emmanuelle Eve (University of Toronto, Ontario Institute for Studies in Education, 2023)
Partial-load college faculty simultaneously occupy insider/outsider positions in their respective higher education institutions. How do they perceive the relationship between their employment status and their work as educators? In recent scholarship, it has been argued that part-time faculty occupy liminal positions as simultaneous professionals and precarious labourers in higher education. None of the literature attends to how part-time college faculty (a cohort that makes up 70%+ of Ontario’s college faculty) who specifically aspire to full-time teaching positions think about their work and professional identities, much less in the context of the province of Ontario, Canada. Through semi-structured and open-ended interviews with ten partial-load college faculty who aspire to full-time teaching positions across three colleges in the Greater Toronto Area (GTA), this study asks faculty to reflect upon the relationship between their conditions of employment and their work as educators. How partial-load college faculty think about their work and professional identities has direct import for what continues to be the foundational mission, purview, and day-to-day activities of colleges – teaching and learning. Holland, Lachicotte, Skinner, and Cain’s (1998) identity theory provides the framework for enabling a nuanced analyses as to how partial-load college faculty think about, make sense of, and narrate their experiences in the liminal space of precarious professionals. The results of this study show that partial-load faculty are largely excluded from the pedagogical communities of their departments and institutions and that every aspect of their work as educators (curriculum development, professional development, and relationships with colleagues) is negotiated and filtered through their precarious status. This research sheds light on the centrality of partial-load college faculty on the enactment of curriculum in colleges as well as explores how various stakeholders can make meaningful change to address the professional goals and curricular inclusion of this significant teaching cohort.
Accepted: 2023-11-14T17:10:58Z

Labour Community Services and the State of Community Unionism in Toronto - Gooder, Austin (McMaster University, 2023)
Community unionism is still contested in the literature, and its presence across various industries and union formations is often not concretely described. This thesis engages in an examination of community unionism within the literature and assesses its potential presence in Toronto’s Labour Community Services, an organization which provides administrative and organizational support to labour unions and community groups in the Greater Toronto Area. Interviews with LCS organizers and staff members and other Toronto labour activists are assessed against common depictions of community unionism within the literature to determine if LCS is engaged in community unionism, or perhaps some other organizational strategies or philosophies. Interviews demonstrated a clear commitment to community building and deepened ties between the labour movement and various formations of community across Toronto and surrounding regions. Interviews also reveal the state of union-community resources, the barriers commonly experienced in this form of organizing, and how organizers and staff members perceive their role in the broader labour movement. Interviews with key informants reveal a series of strategies and choices which shape how Labour Community Services operates. Ultimately, Labour Community Services does not engage in community unionism as a whole practice, but rather utilizes several strategies and operative choices that share common ground with community unionism. A byproduct of these strategic choices is the creation of forms of community unionism between both the labour unions and community groups that LCS frequently works with.

“A New Saskatchewan?”: Political Culture Change in Saskatchewan Party-Era Saskatchewan - Hill, Lauren (University of Alberta, 2023)
Since its founding as a province, Saskatchewan has been depicted by the academic literature as possessing a political culture that was distinctly collectivist, dirigiste, protectionist, and polarized, largely owed to the historical political dominance of the Co-operative Commonwealth Federation (CCF) and the New Democratic Party (NDP) in the province. Such narratives have outlived the political fortunes of both the CCF and NDP, and have, until this point, persisted despite the rise of the right-wing Saskatchewan Party. This thesis aims to fill a scholarly gap, through considering the influence of prolonged Saskatchewan Party governance on the province’s politics and assessing the current state of Saskatchewan’s political culture. Specifically, I ask the following question: what is the dominant political culture strand in Saskatchewan Party-era Saskatchewan? Through a series of online focus group activities involving people from across the province, I assess and substantiate the influence of political culture pillars, such as collectivism, laissez-faire, heartland, and adversarialism, in shaping Saskatchewan’s provincial identity and contemporary political culture. This study demonstrates that Saskatchewan’s political culture has changed. Specifically, this thesis finds Saskatchewan’s contemporary political culture to be ‘blended’, containing components of both traditional and alternative political culture strands, although displaying a slight preference for the neoliberal and conservative alternative political culture. The findings suggest that the current Saskatchewan political culture has departed from its collectivist and hinterland traditions in favour of individualism and heartland. Meanwhile, the political orientations towards the provincial government’s role in the society and the economy (dirigisme or laissez-faire) or the attitudes Saskatchewanians possess towards political actors and the political system (adversarialism or pragmatism) are considerably more varied and lack ideological consistence. Ultimately, this study highlights the influence of political party shifts in serving as mechanisms and reflections of political culture change and provides an overview of Saskatchewan’s contemporary political culture under prolonged Saskatchewan Party governance. A concluding discussion highlights the value and significance of this research and suggests area of future exploration about Saskatchewan provincial politics and political culture.

Honouring Grief Experiences in Life, Death, and the Workplace: A Critical Analysis of Bereavement Accommodation for Workers in Precarious Employment in Canada - Joy, Karima (University of Toronto, Dalla Lana School of Public Health, 2023)
Bereavement scholarship predominantly explores psychological aspects of grief, which neglects the role of social, economic, and political factors that shape the space allotted to accommodate these experiences. The current Canadian social context offers minimal space to honour bereavement as a part of the human condition. Aiming to respond to calls for enhancing bereavement care, this dissertation explores bereavement accommodation for workers in precarious employment in Ontario, Canada. Drawing on critical qualitative research and feminist ethics, this study employs policy analysis and in-depth interviews to generate multi-scalar knowledge on the everyday experiences of bereaved workers in precarious employment. I argue that there are discrepancies between how bereavement is represented in the social context and the everyday experiences of bereaved workers. The current representation portrays bereavement as a short-term, workplace disruption, neglecting grief and many forms of practical and emotional labour in bereavement. Participants expressed they were uninformed and unprepared for grief and bereavement labour, and that navigating the current context created tension, stress, exhaustion, isolation, and stigma. I argue we need a collective, ontological reckoning with our sense of autonomy, recognizing and honouring our interdependence in life and death. I argue that bereavement is a neglected public health issue driven by socio-political forces that devalue relationality, stigmatize emotions, and render bereavement an individual responsibility. This thesis makes broad recommendations for a public health approach to bereavement care, including enhancing grief literacy, creating more responsive care pathways and strategies for addressing individual and collective grief, and establishing safeguards for precarious workers.
Accepted: 2023-11-14T16:46:15Z

The Thicker the Agreement, The Poorer the Relationship: An Examination of Public Sector Environments in Canada and the Intersection of Organisational Trust, COVID-19, and Collective Bargaining Agreements - Lawton, Teigan R.G. (Australian Institute of Business, 2023)
In late December 2019, a new and emerging coronavirus came out of Wuhan, China. The severe acute respiratory syndrome coronavirus 2, widely known as “COVID-19” (WHO, 2022), significantly impacted nearly every aspect of human life on Earth. This study, referred to throughout the thesis as a “project,” examined the intersection of collective bargaining agreements and COVID-19 in unionised environments in the public sector of Canada. –From Executive Summary

Building Blocks of Victory in Oshawa 1937: The Left, the Rank and File, and the International Union - Leah, Anthony D. (McMaster University, 2023)
The Oshawa 1937 strike against General Motors was a major turning point in Canadian labour history. This thesis explores the factors that led to its success, including the historical background of working class struggle; the economic and political context of the times; prior organizing by Communists; the engagement of rank-and-file GM workers and the remarkable stewards’ body they established; and the support and leadership of the UAW International union. The influence of Communists meant that the strike incorporated many features of what might now be called rank-and-file unionism: industrial unionism, democratic engagement of rank-and-file workers, militancy on the shop floor, building solidarity within the workforce and in the community, international solidarity, and rejecting cooperation with corporations. The contending forces of workers, corporations, and rabidly anti-union governments that clashed in Oshawa in 1937 are largely the same ones we see in the battles going on in North America today. Thus, understanding the factors that led to the success of the Oshawa strikers can provide valuable lessons to those seeking to revive today’s labour movement.

Provincial Bargaining, Provincial Union Power, and the Ontario Secondary School Teachers’ Federation: A Case Study of Ontario Teacher Union Democracy in an Era of Centralized Bargaining - Mancini, Chantal Yvonne (McMaster University, 2023)
This thesis explores the impact of the centralization of bargaining in Ontario’s education sector on the internal democracy of the Ontario Secondary School Teachers’ Federation (OSSTF), the province’s second-largest teacher union and self-described defender of public education. Using multiple theoretical lenses of union democracy, public sector unionism, labour geography and teacher professionalism, this thesis examines OSSTF’s history and the evolution of its internal processes and structures, with a focus on the union’s response to the gradual shift to a centralized bargaining regime. Initially formed in 1919 as a conservative organization committed to raising the professional status of teachers, OSSTF expanded into a union that represents both teachers and support staff, bargaining contracts for members with local employers. Positioned within a public sector context of austerity and neoliberal governments looking to contain the costs of public education, OSSTF found itself subjected to legislation intended to upscale education funding and bargaining, beginning in the late 1990s. This thesis finds that the external context of centralization of bargaining has been the most important factor in shaping the internal democratic life of OSSTF, shifting scales of power from the local to the provincial level of the union, exacerbating tensions between provincial and local actors, increasing the overall bureaucracy of the organization, and reducing democratic participation by the rank-and-file. These findings lead to the greater question of whether these internal changes have enhanced or limited the ability of OSSTF to effectively further their members’ interests and resist the neoliberalization of the school system, with a view to considering the role of teacher unions within the future of public education in Ontario.

(De)constructing Nation and Race Along the Canadian Pacific Railway: First Nations and Chinese Migrants in the Colonial Project - Petrie, Emilee (University of Victoria, 2023)
Much has been written on the history of the Canadian Pacific Railway (CPR), but rarely are conversations regarding the experiences of First Nations and Chinese immigrants on the railway brought together. This thesis will analyze how First Nations and Chinese people in Western Canada experienced the construction of the railway and how, as racialized peoples, they were excluded from the original national mythology centered on the completion of a transcontinental railway. The seemingly benign symbol of a railway representing the nation continues the violence of naturalizing colonial, capitalist structures in the national landscape. A closer look at this history reveals the dispossession of Indigenous peoples, the destruction of their ways of life and incorporation of the capitalist economy—all processes that continues today. The history of the railway also reveals the place of Chinese immigrants as a distinct, racialized labour force in late-nineteenth-century Canada that reinforced and that was informed by the racial and economic interests of the national subject at an important time in the development of the nation and its national myths. Drawing on the insights of Manu Karuka’s Empire’s Tracks, this analysis situates the CPR as a tool of colonial, capitalist, countersovereignty.

Syndicalisme au Québec et rapport à la société civile : sociologie historique de la trajectoire clérico-nationale de la CSN - Scott, Jonathan (Université du Québec à Montréal, 2023)
L’intuition sociologique qui a orienté notre démarche de recherche se présente ainsi : pour saisir la trajectoire de l’histoire du syndicalisme en sol québécois, de son émergence à sa représentation actuelle, il importe de lier cette évolution au processus d’émergence et de transformation de la société civile. Afin de travailler cette intuition, nous avons revisité l’histoire du syndicalisme en nous concentrant sur ce que nous nommons « la filiation clérico-nationale », laquelle définit l’identité de la CSN. Ce travail s’avère essentiel pour nous permettre de compléter les analyses d’historiens sociaux et de sociologues des relations du travail en proposant une lecture sociologique nouvelle des périodisations existantes de l’histoire du syndicalisme québécois. Cette intuition nous demandera de qualifier l’évolution récente du syndicalisme québécois du fait qu’en contexte néolibéral, le répertoire d’action du partenariat social, défini à l’aube des années 1980, s’est essoufflé parce qu’il est non seulement soumis à rude épreuve, mais aussi parce qu’il peine à se renouveler. Sur ce point, des auteurs voient dans la baisse du taux de syndicalisation des personnes salariées des pays développés une preuve validant l’hypothèse d’un affaiblissement du syndicalisme. De plus, en sol québécois, malgré une stabilisation du taux de syndicalisation autour de 38%, les syndicats donnent l’impression d’avoir perdu de leur capacité d’être la composante de la société civile la plus représentative auprès du législateur québécois. En qualifiant l’évolution récente de la CSN, nous avons été en mesure de montrer qu’il y a eu recomposition de la centralité des capacités d’action d’une composante importante du mouvement syndical québécois. À partir d’une méthodologie partagée entre la recension d’écrits et l’analyse de contenu de documents de la CSN, nous répondrons aux questions centrales que nous nous sommes posées et validerons ou invaliderons nos hypothèses de travail. Notre thèse nous permettra de proposer une périodisation enrichie de l’action syndicale québécoise. Cette « nouvelle périodisation » apportera des précisions sociologiques aux périodisations historiques existantes. Elle le fera en fournissant des éclairages nouveaux sur les conditions d’émergence du syndicalisme, sur son évolution et surtout, elle abordera la période contemporaine correspondant aux quarante dernières années. De plus, en concentrant notre travail sur la filiation clérico-nationale, nous mettrons en lumière le caractère historique de la posture de concertation et de collaboration des organisations syndicales québécoises : de son émergence à son renouvellement actuel. Plus précisément, l’analyse des données que nous présenterons sur la période récente fournira des éléments clés pour saisir la particularité du syndicalisme québécois. Ce dernier se développe, selon notre lecture, de façon symbiotique. L’amorce de cette relation symbiotique est clairement apparue avec la première configuration développementale, laquelle prend naissance dans les années 1930 sous le leadership du haut clergé québécois. Depuis, cette relation symbiotique s’est maintenue et a été développée au fil des mises à niveau du modèle québécois de développement. De nos jours, elle prend une couleur particulière que nous avons qualifiée de partenariat social stratégique. Notre étude de la CSN illustrera comment les logiques d’actions de cette organisation sont partagées entre la collaboration avec le capital, l’État et des organisations de la société civile, tout en mobilisant, au besoin, la conflictualité. Nous montrerons comment, au fil des quarante dernières années, les discours de la CSN font état d’une relation ambidextre avec les grands secteurs institutionnels. Une relation qui est partagée entre collaboration et conflictualité tout en étant teintée de développementalisme. _____________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : CSN, histoire sociale, institutionnalisation, logique d’action, néolibéralisme, société civile, syndicalisme

The Framing of Temporary Foreign Workers in Canadian Parliamentary Debates - Shaheen, Tartil (University of Windsor, 2023)
This study examines the framing of temporary foreign workers (TFWs) and the Temporary Foreign Worker Program (TFWP) within the context of Canadian political discourse. Through a qualitative content analysis of parliamentary speeches spanning from 2006 to 2022, it investigates how TFWs and the TFWP have been framed by members of three federal political parties: Conservatives, Liberals and the NDP. With an aim to understand influences on framing strategies, the analysis considers significant events such as the COVID-19 pandemic and a change in government. The findings highlight the significance of party ideology in shaping perspectives on TFWs and the TFWP, with all three parties recognizing the necessity of this group and program in achieving Canada’s economic goals. At the same time, despite their increasing significance in the economy, the study highlights the conditional inclusion of TFWs in Canada. Policymakers adapt their frames based on perceived contribution of these workers and their alignment with Canadian interests. This research illuminates the crucial role of framing in shaping policy outcomes regarding TFWs and the TFWP.

Enabling Settler Citizens: Disability, Age, Public Health, and Settler Colonialism in Northern Ontario, 1876-1951 - Wiener, Leah (Simon Fraser University, 2023)
My dissertation analyzes the relationship between public health and settler colonialism, employing age and ability as key categories of analysis. I argue that settler colonialism and public health were constitutive of one another. Public health policy weaves together notions about land, race, labour, age, and ability, to structure and stratify societies. Public health relied on white supremacist tropes to justify the state's attempts to subjugate and dispossess the Anishinaabeg in Northern Ontario. The idea of a "public" was critical and contested in the intersection of policy and the emerging social science of public health. Settler standards of public imagined a "public" that was white, male, middle-class, and adult, with a body that could be made healthy through individual effort. Settler ideas about Indigenous Peoples shaped the "public" as a racialized and age-stratified concept in Canadian public health and health policy. In this dissertation, I seek to highlight how material and symbolic age, and material and symbolic children, figured in settler-colonial processes of state formation in the context of public health policies. I examine how bureaucrats and institutions in the public and voluntary sectors constructed and portrayed Indigenous and settler health, measuring each against a middle-class standard of "public" health. To do this, I set forth four interconnected arguments. First, settler colonialism and settler public health policy were mutually constitutive. Second, disability existed alongside and entangled with age as a key framing for settler public health policies. Third, these public health policies drew from a bifurcated notion of the "public," resulting in policies focused on protection and surveillance based on racialized lines. Finally, these framings of disability, age, and the "public" had clear material impacts in Northern Ontario's settler-colonial context, enabling settlement while dispossessing Indigenous Peoples.

Comparing Public Secondary Teachers in Ontario with Different Labour Contracts in a Time of Crisis - Wilkin, Andrew (McMaster University, 2023)
This dissertation compares the work and life of secondary public-school teachers in Ontario with different labour contracts during a time of crisis. The COVID public health crisis along with neoliberalism, the defunding of public education, and a climate crisis have all influenced governmental policies and the labour process of public secondary teachers in Ontario. The influences that different contracts can have on the labour process of teachers, how they feel towards their union, and the impacts on their individual health and household wellbeing before and during the first year of the COVID pandemic is the focus of this dissertation. To help explore these contexts and the influences on the life and labour of public secondary teachers in Ontario with different contracts, I have used research from studies in Labour Process Theory, precarious work, and educational labour to inform my analysis. Along with those areas of discourse, I have also used insights from research into Critical Realism and Thematic Analysis to think through and discuss the differences between the teachers I interviewed and connect their experiences with work, their union, and their individual health and household well-being to larger systems, structures, and histories. The interviews conducted revealed three points of interest: that precarious labour contracts can function as a disciplinary device, that larger contexts outside the contract shaped how the contract was experienced, and that teachers’ unions can act as a source of solidarity and security during a crisis and when there are certain associations with its purpose. This exploratory research aims to open up future areas of research into educational labour and differences between the experiences of educators with different contracts.

“You Appear Silent to People Who Are Deaf to What You Say”: Solidarity, Schisms, and Alterity in Immigrant Women’s Political Organizing in Toronto, 1970s-1990s - Aguiar, Julia Elizabeth (Queen's University, 2022)
This thesis considers the connections between the increased migration of racialized women to Canada and the ascendancy of social movements in Toronto from the 1970s to the 1990s. In the mid-1970s, there was a surge of grassroots organizations founded by and for immigrant women in Toronto. They were established to address the distinct needs and experiences of immigrant women where government and preexisting, decidedly hypermasculine, ethnocultural organizations did not. This thesis argues that these organizations, and the individuals associated with them, were fundamentally political. In situating these organizations within the broader progressive political landscape of Toronto, this thesis elucidates the ways in which immigrant women’s political organizing challenged and transformed dominant social movements. In particular, immigrant women’s fraught relationship to the mainstream women’s movement in Toronto is closely examined. I argue that immigrant women organized both within and without the Toronto women’s movement. In their relationship to the women’s movement, immigrant women contested the limited perspective of white feminism by drawing closer attention to class and race. This was most evident within immigrant women’s organizing for reproductive freedom. Additionally, immigrant women organizer’s relationship to the Canadian state is analyzed as a site of struggle which dialectically constrained and sustained their activism. Because immigrant women worked in higher numbers than their Canadian counterparts and often in exploitative sectors, labour became a central issue within their activism. Through their labour organizing, immigrant women forged important alliances with the labour movement. This thesis also attends to the uneven racialization of immigrant women which informed their activism. Immigrant women’s activism offered alternative perspectives and methods of organizing which did not conform to dominant ones. By taking a relational rather than assimilationist or pluralistic approach to the relationship between immigrant women’s organizing and broader social movements, a fuller, more nuanced portrait of the intersections between immigration, gender, race, and social movements can emerge.

Craft Capitalism: Labour and the Narratives of Artisanal Production - Anderson, Benjamin (Simon Fraser University, 2022)
In the last decade, considerable attention has been paid to the category of craft. Within the disciplines, particularly in sociology and art theory, scholars like Richard Sennett, Susan Luckman, and Glenn Adamson have attempted to define, theorize and delineate the history of craft and its influence in contemporary capitalist culture. Popularly, books and television shows feature the work of makers and craftspeople, their popularity compounded by online crafting communities like Etsy. For all of this attention, considerably less has been paid to the labour that creates the craft products to begin with. This dissertation interrogates the category of craft from a critical labour studies perspective, first by analyzing its labour process, and, second, by amplifying the voices of workers in these industries in order to reflect the conditions they face, their attitudes about craft, and their reflections on class and organizing. In order to accomplish both, the dissertation reports on participant interviews and critically examines cultural artifacts concerning so-called making (typically understood as amateur or semi-professional small-scale production) and craft industrialism (used to define scalable industries that use craft branding and terminology). Its key case studies are making/makerspaces and craft brewing in the Cascadia region of North America, although it also visits the roasteries, bike shops, and bakeries that make up some of the other primary sites of the artisanal economy. This dissertation makes four primary contributions to the critical study of craft. First, it reorients the common approaches to craft, which either prioritize craft objects or individual maker activity. By redirecting attention to the social process of production, it avoids the object-orientation of many approaches as well as the maker-as-virtuoso narratives of popular accounts. By focusing on the social dynamics of craft, the dissertation transcends the singular craftsperson to make its second contribution: the reconceptualization of skill as social category rather than individual attribute. This social approach to skill paves the way toward the dissertation's third contribution: a dialectical consideration of the craftworker as distinct from but intrinsically related to the craftsperson. Analysis of cultural artifacts and discussions with workers highlighted the dependency of craftsmanship and support work. Finally, the dissertation distills maker and worker attitudes into a set of observations regarding the maker movement's narratives of emancipation through self-directed work as well as the potential of solidarity in craft industries.
OCLC: 1375299912

Indigenous Workers and Trade Unions: Settler-Colonial Capitalism, Indigenous Peoples' Labour and Union Engagement - Karim, Alia Neisha (York University, 2022)
It is only in the last few decades that Canadian trade unions have expressed labour solidarity with Indigenous peoples by bringing their attention to the distinct concerns of Indigenous workers in the workplace and beyond it. Trade unions have taken important steps to express support for their Indigenous members and their communities, yet little is understood about Indigenous peoples’ experiences in the capitalist labour market shaped by land dispossession, the ongoing manifestations of settler-colonial oppression, and the systemic economic marginalization by Canadian institutions and employers. It is pertinent to identify what unions are doing to support them and where they can strengthen labour solidarity so that they can develop critical sites of resistance against colonial-capitalist power. A closer analysis is needed to understand Indigenous peoples’ relationships to unions, relations between Indigenous and non-Indigenous working people, and the challenges for unions to build united struggles with Indigenous peoples. This study examines the spaces of union engagement with Indigenous workers and their communities amongst the challenges presented by the reality of ongoing colonial oppression in Canada. The purpose of this study is twofold: 1) to examine the roles that trade unions have had with Indigenous peoples in the paid labour market and recent initiatives that they have taken to meet the needs of Indigenous workers and unionists, and 2) to analyze the ways trade unionists understand and approach Indigenous peoples’ concerns and anti-colonial struggles within the broader confines of settler-colonial capitalism, and to determine the challenges to transforming their practices of solidarity with Indigenous peoples. This study draws upon semi-structured, indepth interviews with 22 Indigenous and non-Indigenous key informants who are elected trade union officials, staff, and rank-and-file unionists. The study’s findings reveal emerging activism of Indigenous workers within their workplaces, unions, and beyond, and the complexities between Indigenous peoples’ relationships with paid labour, unions, and struggles for selfdetermination. I argue that unions are turning their attention to support the distinct needs of Indigenous workers and to support anti-colonial struggles, but they are limited to redressing the effects of settler-colonial capitalism. They face difficulty engaging in solidarity due to the structural limitations of settler-colonial capitalism. By reflecting on participant insights into these challenges, this study proposes an anti-colonial framework for unionists to transform their practices of labour solidarity.

Just in Principle?: Assessing the Contributions of Organic Farming to Socio-Ecological Sustainability in Canadian Agriculture - Klassen, Susanna (Susanna Elsie) (University of British Columbia, 2022)
Agriculture is at the centre of society’s most pressing sustainability challenges, including food insecurity, climate change, ecological degradation, and social inequity. Organic agriculture, when practiced according to an ethic grounded in ecology, health, fairness, and care, has been proposed as a remedy to these challenges. Building on a movement for an alternative to socially and ecologically exploitative food production, organic agriculture is now a multi-billion-dollar industry with established legal and regulatory frameworks around the world. While this growth could be seen as a success, empirical research has called into question the extent to which organic agriculture and market-oriented third-party certifications can foster sustainability transitions and has found that performance is often context dependent (e.g. depending on which practices are adopted). There remain significant gaps in knowledge about how organic agriculture is practiced in jurisdictions around the world relative to the sustainability-related principles on which it was founded, especially the principle of fairness. To address these gaps, I developed a mixed-method assessment grounded in a critical realist methodological approach to evaluate the contributions of organic agriculture to socio-ecological sustainability in Canada. I utilized both qualitative and quantitative methods—drawing from interviews with farmers, inspectors and organic policymakers, analysis of census data for farms across Canada, surveys of vegetable farmers in British Columbia and organic policy documents—to investigate how organic agriculture is shaped and enacted by organic community members at multiple scales. My analysis of organic standards in North America, along with census and survey data in Canada, provide strong evidence for higher levels of adoption of ecologically sustainable management in organic agriculture relative to all other farms. Yet, despite explicit attention to the principle of fairness in organic standards and among organic community actors, I found little evidence that organic agriculture in Canada is correlated with improved working conditions for farmworkers in practice. Across Mexico, the US and Canada, no organic standards contain any requirements related to social sustainability. At the same time, standards governance and community-led efforts toward integrating the principle of fairness into certification show potential to advance a more just and sustainable agriculture.

A Critical Analysis of the Construction of the New Essential Worker Through the Discursive Practices of the Canadian News Media During COVID-19: Implications for Occupational Rights - Kupidy, Steven (Dalhousie University, 2022)
The COVID-19 pandemic and subsequent government responses resulted in a shift in the identity of the essential worker that now included low wage essential workers. Using a critical discourse analysis methodology written news media texts were analyzed revealing various discursive strategies were utilized to construct the new essential worker identity. Findings revealed a fluid, complex identity that was politicized to advance other issues. The need to re-frame the definition of the essential worker was discussed along with the implications on the attainment of occupational rights for low wage essential workers.
Accepted: 2022-04-14T13:41:56Z

The Anti-Conscription Movement in BC and Its Contribution to the Labour Revolt of 1918-19 - Latimer, Brian (Simon Fraser University, 2022)
Historians have generally interpreted the conscription crisis of 1917 as reflective of contending nationalist perspectives in Canada. In contrast this study examines the pivotal role of the labour led anti-conscription movement which developed in British Columbia and throughout Canada in World War One to oppose the threat poses by conscription and other war time acts of repression by the Borden government. A careful study of primary sources and newspapers of the era show that this movement of resistance to conscription also included others threated by conscription: conscientious objectors, Indigenous nations, farmers, and pacifist social gospel activists. The resistance movement had the effect of changing Federal government policy on conscription during the war and changing the political environment after the war and acted as a catalyst in helping to spark the post-war labour revolt.

The Decline of the International Ladies’ Garment Workers’ Union: Shifting Workers’ Identities in Montreal and New York City - MacDonald, Katherine (University of New Brunswick, 2022)
A part of the labour movement for ninety-five years, the International Ladies’ Garment Workers’ Union (ILGWU) worked to better the conditions of garment workers across North America. Although they saw gains for workers in the garment industry over fifty years of progress, in the last forty years of the ILGWU’s history, the union faced a dramatic decline. Large membership losses and a weakening of negotiating power in the industry left the ILGWU a shell of their former self. What happened to this union? This declension did not begin with rapid membership decline, but a steady drop in members was a symptom of missed opportunities and misunderstandings on the part of union leadership of the increasingly diverse needs of garment workers across North America. Using the ILGWU in Montréal and New York City from the 1960s to the 1980s, this dissertation highlights the intrinsic difficulties of with transnational unionization efforts in the late 20th century. The ILGWU’s could not maintain a collective identity for garment worker across North America. Shifting identities made it difficult for the union to maintain their membership and motivate nonunionized workers to join the organization. The decline of this powerful and important labour organization offers critical insights into women’s history and labour activism at the end of the 20th century and reveals new elements of the history of capitalism, especially as it relates to ethnicity and gender.

The 1907 Anti-Asian Riots: The Making of Sensibility Among Working Class Men - McKeen, Patara (University of British Columbia, 2022)
This research explores how racialized sensibility emerged through the 1907 anti-Asian riots in Vancouver and links the riots in Vancouver to the riots in Bellingham earlier in the same year. It uses mixed methods to collect data on portraits, photographs, images, editorials, and documents, employing archival ethnography to read documents along and against the grain (Stoler, 2002; 2012) to make sense of the time period and the sensibilities that underpinned the riots. Archival ethnography helps bring to light the accounts, conversations, and dialogues of colonial agents and actors, and to interpret missing data in the archive. Missing data in the archive consists of historical documents that are overlooked, misinterpreted, or destroyed. My thesis also accounts for gaps, silences, and erasures in the archive by applying critical fabulation to rearrange and reconstruct intersecting viewpoints (see Hartman, 1997; 2008; 2019). To provide a thicker analysis of archival documents, this research interprets olfactory and auditory senses as integral to the making of these riots (see Simmel, 1908/2002; see Campt, 2017; see Lee, 2010; see Mawani, 2009; see Russell, 2019; see also Blaikie, 2002). It is only through the process of combining mixed-methods, theory, and practice that the missing data in the archive can be reimagined and written as part of the historical narrative.

Art, Work: Subsumption, Posthumanism and Artistic Responses to Surveillance Capitalism - Mirzayan, Anna (Western University, 2022)
This dissertation brings together multiple discourses, including surveillance studies, autonomist Marxism and posthumanism, as the groundwork for a novel discussion of contemporary visual art— in particular surveillance art, that is, art that addresses and problematizes the omnipresent digital monitoring now part of everyday life. Because in this dissertation contemporary art is defined as necessarily political, aesthetic (in the Kantian sense) and responsive to conditions of current history and society, I use Marxist theory to identify the particular features of contemporary capitalism that this art is responding to. I first characterize post-Fordist capitalism, focusing on the increasing reliance on extracting network value from what Maurizio Lazzarato called immaterial labour. I discuss Marx’s theories of formal and real subsumption vis-a-vis their impacts on production, technology and subjectivity, and conclude that we need a new term that adequately emphasizes the novel imbrication of technology and subjectivity. In particular, I claim that surveillance capitalism, rising from military technologies and research, characterizes capitalist valorization under hypersubsumption. I then look at the impact of surveillance on labour and subjectivity, with a particular focus on unwaged immaterial activities. Do these activities count as work? To answer that, I propose looking at a combination of Marx’s concept of unproductive labour with a modified type of constant capital. I conclude that the effects of hypersubsumption on labour, consumption and production have produced a new type of capitalist subjectivity: coerced posthumanism, which I contrast with Marx’s authentic species-being. In order glimpse a post-capitalist species-being, I articulate a theory of contemporary art by bringing together Jacques Rancière’s dissensus with Peter Osborne’s notion of contemporary art; both theorists show how contemporary art is necessarily political— what’s more, it is oriented towards an open future. I then apply their ideas to particular artists who have responded to capitalist surveillance by creating ‘artveillance’ (art about surveillance). I evaluate the political effectiveness of three categories of artveillance as experiments in post-capitalist sensoriums.

Race to the Bottom? : A Critical Analysis of Canada's Modern Slavery in Supply Chain Legislation - Sicoli, Angelo (Université d'Ottawa / University of Ottawa, 2022)
This study critically examines the Government of Canada's conceptualization of transnational corporate accountability and exploitative labour in its legislative response to modern slavery in global supply chains. With a primary focus on the government's recently proposed Bill S-216: Modern Slavery Act - which would mandate companies to report on their activities to reduce modern slavery in their supply chains - empirical data is drawn from parliamentary debates about this bill and its earlier iterations as well as a report produced by the House of Commons committee originally charged with studying the issue. Informed by the corporate crime and business management literature as well as a neo-Marxist theoretical lens that employs such concepts as Antonio Gramsci's theory of cultural hegemony and global capitalism, the dominant views taken up in conversations hosted by the Canadian state are captured using critical discourse analysis. Overall, dominant voices accepted into the federal government's approach reinforce neoliberal assumptions of wealth accumulation, profit maximization, and free-market economies, thereby trusting transnational corporations to self-regulate and use their financial capital to curb the conditions that engender exploitative labour. The findings of this interdisciplinary study reveal that the legislative proposal culminating from the policy-making discourse defers to measures that prioritize the social benefits of corporate social responsibility, which ultimately eclipse the need for criminal sanctions against Canadian corporations with operations that employ modern slavery. This research helps to expose the reproduction of corporate impunity as a result of the inability/unwillingness to address the status quo of global capitalism.

Accounting for Racialized Immigrant Workers: Historiography of the Colour Coded System of Disability Exclusion - Simpson, Yvonne Velma (York University, 2022)
Canada’s quest and historical reliance on an immigrant labour force to sustain the nation’s economic and population growth are well established. This has been the case since the formation of New France, where the conquest of people and acquisition of lands and resources, in part, inspired the recording of the first North American census of 1666. However, record keeping practices that commenced in what is now called Canada were part of a larger scheme of a systematic power over governance structure in settler-colonial administrative edicts that cast the foundational structure for inclusion and exclusion criteria based on a colonial racist ideological model of who should be accounted for in the French settlement. As such, Indigenous People were not counted. Similarly, the records of people of Black African ancestry who were brought to New France through the inter-continental routes as enslaved labourers were obliterated from official administrative records. In this first-of-a-kind historiographical query, primary and secondary records of racialized immigrant workers were examined to determine the extent to which Indigenous and racialized immigrant workers existed in governmental demographic records and other sources over time, inclusive of contributions, incurred injuries, disability and fatalities in labour force participation. A purposeful, cross-regional selection of Canada’s occupational health policy experts was engaged in semi-structured interviews on the question of demographic identity, including the intersectionality dimension of race and immigrant status. Insightful findings on the gaps in evolving race-based data collection in the nation’s contemporary occupational health and safety systems were garnered, revealing significant implications regarding the vestiges of colonial determinism in a perpetual colonial system, which underlies the absence of Indigenous and racialized workers from the nation’s informatics on occupational health and safety. Ultimately, this project implicates an urgency for policy changes, aligned with the nation’s persistent reliance on racialized immigrant workers while relegating them to over-representation in work that is more dangerous and injury prone without visible accountability. Dismantling the current policy framework for health and safety by imposing meaningful strategic intervention measures and data collection on ethno-racial demographic identity in the nation's public reporting systems is the resounding outcome of this project.

Great War Profiteering, Patriotism, and the Democratic Revolt in English Canada, 1914 to 1922 - Targa, Ryan (York University, 2022)
In Canadian Great War historiography, the late-war and post-WWI revolt has remained a conspicuous subject for exploring regional and class conflict. This dissertation examines the revolt with a new analytical perspective centred on patriotism and profiteering. The first section of this study constructs a cultural framework called Great War culture. Based on the limitations of the state, it became necessary to militarize socialization so that a major war effort could be undertaken. Through this process, Canada experienced a war-centric cultural shift, whereby social and political belonging became premised on patriotic identity. The term “profiteering” emerged as part of the war-centric lexicon to designate those who were disregarding patriotic sensibilities and selfishly exploiting the war for profit. The second section of this dissertation examines three major interpretations of Great War profiteering between 1914 and 1918: war profiteering, food profiteering, and alien profiteering. It provides an understanding of each controversy through the perspective of federal politicians and state officials; leaders in the labour, farmers’, and veterans’ movements; and ordinary patriots in English Canada. It argues that Borden’s administration failed to curb patriotic outrage and disillusionment, setting the stage for explosive post-war militancy and unrest. The final section examines how workers, farmers, and veterans drew upon the legitimacy of the Great War as a struggle for democracy to challenge the terms of post-war reconstruction. As this section explores, patriots undertook this revolt by using direct action involving violence and industrial militancy. They also used political action to challenge party politics, which some believed to be a root cause of the profiteering evil.

Being Precarious: An Autoethnographic Account of One Precarious Faculty Member's Lived Experience Working in Four British Columbia Higher Education Institutions - Allen, Lisa Marie (University of British Columbia, 2021)
Precarious faculty, once used by higher education institutions as auxiliary labour, now dominate post-secondary campuses. With as much as half of post-secondary institutions’ courses now taught by contract academic faculty, post-secondary institutions have systematically come to rely on hiring precarious contract faculty for their respective departmental teaching capacity. As an emerging and significant trend in higher education, this study aims to examine the precarious faculty experience through autoethnographic methods that reflects on my personal experience as a precarious faculty member working at four different higher education institutions in British Columbia from 2016-2018: the Private Online University, City College, the Teaching University, and the Institute. Using Tierney’s (1997) Organizational Culture Theory, coupled with theories of organizational socialization and the role of models and mentorship, I compare my personal experiences of being hired and onboarded at the four different institutions in which I worked as a precarious faculty member. I focus on three themes: the faculty interview process, being evaluated as a precarious faculty member, and resources that I was given (or not). A literature review precedes each personal autoethnographic account; I then proceed to compare and contrast my personal experiences with that of the literature as a way to examine the ways in which my experiences working as a precarious faculty member are consistent with, and divergent from the literature. To conclude, I suggest that there is a lack of standard processes and practices when it comes to hiring precarious faculty. Additionally, I suggest that one’s career stage plays a significant role during hiring. I also suggest that good student evaluations of teaching lead to reappointment for precarious faculty. In terms of performance evaluations, I stress the importance of communication and suggest that precarious faculty are evaluated (sometimes) both formally, and informally. Finally, in terms of resources, I echo the literature that office space is a place of power, and that professional development is a two-way street. I conclude that more personal stories—like mine—are required to better understand what it’s like to be a precarious faculty member in higher education.

History, Memory, and Struggle in Saint-Henri, Montreal - Burrill, Fred (Concordia University, 2021)
The working-class neighbourhood of Saint-Henri in the Southwest of Montreal was long at the heart of capitalist production in Canada. Like other industrial cities across North America, the area experienced a precipitous deindustrialization and decline in the postwar period, a process whose brutality was matched only by that of the subsequent refashioning of the sector into a post-industrial paradise of restaurants and condominiums. Taking as its point of departure the competing historical discourses at play in present-day Saint-Henri – a post-industrial structure of feeling advanced by developers, business owners, and sanitized heritage projects; an oppositional working-class culture rooted in memories of industrial labour and the hard years of unemployment; and a common, structuring framework of settler whiteness – this thesis uses oral history and archival work to excavate the roots of gendered working-class consciousness, settler identity, and local forms of political resistance in a part of the city long seen as a quintessentially Québécois space. Beginning with the 1967 shutdown of Dominion Textile, the thesis examines the changing patterns of capital accumulation that led to factory shutdowns and the brief 1970s overlap within community organizing around productive and reproductive labour issues, a nexus that conditioned local resistance into the 1990s. It then turns to the State and capital’s conscious redevelopment of the neighbourhood in the image of bankers and hedge funds, a process particularly difficult for the women largely responsible for the affective and reproductive labour of collective survival. Gradually, local activism became integrated into the nationalist State apparatus, as deindustrialization fed into gentrification and the “worker's neighbourhood” slowly became re-imagined as a white-coded “quartier populaire.” Finally, the dissertation turns to a more in-depth investigation of the structuring forces of settler colonialism and anti-blackness on working-class lifeways in Saint-Henri, before concluding with some thoughts on active, public history and the role it can play in imagining transformative ways of organizing local resistance. The dissertation is an intervention into deindustrialization studies, inserting perspectives of race and gender into the discussion; gentrification studies, challenging the field to centre working-class experiences of displacement; Quebec and Canadian labour history, contesting dominant national/ist frameworks; and public history.

'One Day Stronger': A Public History Theatrical Experiment about Remembered Sudbury Strikes, 1958-2010 - Duthie, Richard (Carleton University, 2021)
This dissertation honours and pays tribute to Sudbury residents and many others for whom labour strikes played a significant role in shaping their lives. Set in the context of a public history theatrical experiment, this study investigates local and community memories pertaining to Sudbury mining strikes in the postwar period from 1958 through to 2010. Archival research and oral history interviews were conducted on major labour strikes in this era and that research was used to script, rehearse, and stage a theatrical play. Interviews with audience members and performers were also conducted at all stages of the process. This process allows the dissertation to consider the perspectives of both performers and audience members, each enacting their roles as producers and consumers of public history. The dissertation also assesses the value of this form of history making, as it relates to the formation of historical consciousness, both then and now, of individuals within the Sudbury community. This study argues that public history as theatre has the potential to provide an effective and affecting means to nurture critical, reflexive historical consciousness both on and off the stage.
OCLC: 1445862901
Keywords: Academic theses; Canada – History; Public history; Theater; Thèses et écrits académiques; dissertations

The Contested Academy: African Canadian Women’s Experiences as Tenured, Tenure Stream and Non-tenured Faculty - Hylton, Treisha Hanna-Kay (University of Toronto, Ontario Institute for Studies in Education, 2021)
This thesis explores the experiences of Black women who are in tenured, tenure-stream, and non-tenured faculty positions and presents how Black women negotiate their intersectional identities in the academy. The study documents their self-identifications and struggles with the academy in terms of power relations in their respective universities, including racial and sexual discrimination. In addition, the study explores the career paths of Black women faculty from contract faculty to full professor. Methodologically, the study uses Black Feminist theorizing along with autoethnography in order to explore the nature of the experiences of Black Canadian women faculty within the academy. I interviewed 13 self-identified Black women across Canadian universities, including myself as the fourteenth key informant. This study reveals a complex and rich text of how Black women see themselves in the university, their experiences with multiple and overlapping oppressions and how this affects their careers, and finally, their contributions to the academy and their visions of success.

“especially in this free Country:” Webs of Empire, Slavery and the Fur Trade - Lindsay, [Margaret] Anne (University of Manitoba, 2021)
Predicated on a narrative of mutuality and cooperation, what has come to be known as the Canadian fur trade has long been positioned as exceptional in its relationships between colonizers and Indigenous peoples. In this framing the fur trade in what would become Canada is represented as having experienced little of the colonial violence that manifested in other colonial encounters and has been constructed as devoid of the unfreedom of chattel slavery. In fact, this characterization is untrue. Located within the French and British empires, the Canadian fur trade reflected the violences of its empires. From the seventeenth, and well into the nineteenth centuries chattel slavery existed in the fur trade as it did in the empires of which it was a part. Here, as elsewhere, complex webs of family/business relationships carried the violence of empire to and between its colonies. The creation and maintenance of these webs offered spaces where women as well as men could participate in the success of their family/businesses, but also in the transmission of colonial violence. One example of this is the Wedderburn Colvile family, their involvement in both West Indian plantation slavery and in the Hudson’s Bay Company, and in the interventions of one of its members, Jean Wedderburn Douglas, Lady Selkirk in what has become known as the fur trade wars. A closer look at the Wedderburn Colvile family and their interests in the Northern North American fur trade offers insights into how colonial violence and changes in the laws relating to chattel slavery impacted the fur trade, as the effects of these changes traveled along family/business webs of networks of relationship. This research draws on primary sources gleaned from archives and libraries in Scotland, England, the West Indies, the United States and Canada. It brings together a wide range of secondary literature to argue that, just as in other parts of empire, colonial violence, including chattel slavery, connected through webs of family/business relationships, existed in the Canadian fur trade. At the same time, this project argues, the erasure of that story is something we are only now beginning to address.

Making Ukrainian Canadians: Identity, Politics, and Power in Cold War Canada - Luciuk, Kassandra Larysa (University of Toronto, 2021)
This dissertation examines the process by which a singular Ukrainian Canadian identity was constructed and entrenched throughout the twentieth century. It details how one of Canada’s largest and best organized diasporic communities, utilizing changing notions of cultural pluralism and the politics of the Cold War, crafted an increasingly nationalist, anti-communist version of identity that eradicated previously popular articulations of what it meant to be a Ukrainian in Canada. The traditional historiography posits that the community defined itself on its own terms, relying on individualized acts of agency and migrant resilience to entrench a version of Ukrainian-ness that was a democratic, bottom-up reflection of the collective. This project offers an alternative perspective by focusing on the battle over community narratives between communists, represented by the Ukrainian Labour Farmer Temple Association (ULFTA) and then the Association of United Ukrainian Canadians (AUUC), and the nationalists, organized under the umbrella of the Ukrainian Canadian Committee (UCC). I show how, with the help of state officials, the nationalists overpowered their ideological enemies on the left, concreting their identity as hegemonic. Through this process of coherence, they further bound specific aspects of their own ideology, perceived as innocuous, apolitical, and simply common sense, into mainstream political consciousness. Beyond a simple community study, this dissertation is also a case study about the building of anti-communist hegemony in Canada. Chapter One examines the role of state surveillance and political policing to show how state officials collaborated with the UCC to weaken the domestic left. Chapter Two analyzes the rise and fall of a government bureaucracy that acculturated the nationalists so as to embed them in Canada’s structures of power and bolster their anti-communism. Chapter Three looks more closely at acts of anti-communist violence, which seriously deterred participation in the AUUC. The state’s refusal to condemn the violence also telegraphed its preferences and helped define Canada’s social, political, and judicial boundaries. Chapter Four focuses on the nationalists’ appropriation of cultural pluralism to further entrench their version of Ukrainian identity. Lastly, Chapter Five explores commemoration, where competing visions for certain cultural figures were articulated and, eventually, nationalist narratives were set.
https://thenewcanadianhistory.com/2018/10/05/making-ukrainian-canadians-a-reflection-on-identity-and-power/ ISBN: 9798496550642 https://cha-shc.ca/prize-winner/kassandra-l-luciuk/
Keywords: Canadian history; Communism; Ethnicity; History; Migration; Nationalism; Politics; Ukrainian Canadian

«L'heure des pétitions est passée, il faut des actes» : les sans-travail et la protestation au Québec durant l'entre-deux-guerres (1919-1939) - Marsan, Benoit (Université du Québec à Montréal, 2021)
« L’heure des pétitions est passée, il faut des actes » présente une histoire vue d’en bas des sans-travail québécois au cours de l’entre-deux-guerres (1919-1939). L’objectif de cette thèse est de démontrer la contribution de l’action collective des sans-emploi à la politisation du problème du chômage au Québec durant les années 1920 et 1930. Cette période est un événement matrice pour l’histoire du chômage au Québec et au Canada. Le chômage, qui est déjà un phénomène important au cours du processus d’industrialisation au XIXe siècle, atteint au cours de la Grande Dépression des proportions jusqu’alors inégalées. Ce problème, qui jusqu’à la Première Guerre mondiale est encore largement considéré comme relevant d’une éthique du travail déficiente, de l’imprévoyance des individus, ou encore la conséquence des cycles saisonniers de l’économie, se présente de plus en plus comme un phénomène politique et systémique remettant en cause l’organisation de la société québécoise et canadienne. Dans ce changement de paradigme, l’action collective des sans-travail joue un rôle déterminant. Grâce à celle-ci, le chômage prend la forme d’un problème à la fois collectif, social et politique, qui ultimement remet en question la relation entre la démocratie et le capitalisme. L’étude du répertoire d’action collective des sans-travail québécois permet de mieux comprendre leur rôle dans l’histoire du chômage. Leurs protestations prennent racine dans une économie morale qui annonce une redéfinition de la citoyenneté fondée sur la formulation de nouvelles attentes envers l’État. Considérant que le chômage est indépendant de leur volonté, les sans-emploi estiment alors avoir le droit à une assistance contre le chômage. Bien que les manifestations de sans-travail ne soient pas un phénomène nouveau dans l’histoire québécoise, au cours des années 1920 et 1930, celles-ci apparaissent de moins en moins marginales. Prenant racine à Montréal dans le contexte de la Révolte ouvrière, elles s’étendent à plusieurs autres villes de la province au cours de la Grande Dépression. Perçus comme une menace à la paix sociale, dans un moment fortement marqué par l’anticommunisme, ces mouvements forcent les pouvoirs publics à intervenir. Encore peu étudiées à ce jour, ces manifestations, jumelées à celles qui se déroulent ailleurs au Canada, expliquent pourquoi le chômage devient, pour la première fois, un problème politique d’importance et débattu au sein de la sphère publique.
https://cha-shc.ca/prize-winner/benoit-marsan/

“The Severity of This Service…” Canadien Inland Mariners in the Early Post-Conquest Era, 1760 to 1817 - More, John David (Queen's University, 2021)
Beginning just a long decade after New France became part of the British Empire in 1763, a half-century of major crises engulfed British North America; the American Revolutionary War (1775-83), the postwar forced migration and resettlement of thousands of destitute and hungry British-American Loyalist refugees (1784-86), and the War of 1812 (1812-1814). In order to surmount, indeed, just to survive these crises, the British colonial regime in Quebec found it necessary to seek and retain the services of thousands of skilled, native-born, French-Canadian (Canadien) inland mariners in the newly acquired colony. For more than half a century, the Canadiens were needed to fulfill a variety of essential roles. Small boat (batteau) crews hauled virtually all the necessary supplies, including food, to sustain war and resettlement efforts west of Montreal for British soldiers and sailors, Loyalist settlers, militiamen, Indigenous allies and refugees. Canadien mariners also constructed, commanded, and crewed British warships on the Great Lakes. Some men were disabled in combat or became prisoners-of-war. Others died in shipwrecks or drowned on the river. The mariners left few personal records, but their actions were critically important for the successful defense and retention in the British Empire of the colonies that would eventually form central Canada. The contributions of Canadien inland mariners deserve serious consideration when examining the relationships between the people of the former New France and their new British rulers during the challenging, early transitional years of the British colonial regime.

Beyond the Railway Narrative: Exclusion and Agency in Chinese Canadian History Before 1947 - Oliver, Diane Christine (Saint Mary's University, 2021)
This thesis examines the role of Chinese in Canadian history by looking beyond the popular railway narrative that reinforces a stereotype of docile cheap labour and a reductive lens of racism. The research will look at what brought Chinese sojourners to Canada and the economic and legislation restraints and discriminatory labour practices by the government and employers. It will look at how Chinese people began to resist the prohibitive social, economic, and political policies through protests, Chinese unions, and collaborative efforts of Chinese and white Canadians. The railway narrative rendered Chinese women invisible within Canadian history as it focuses on the racial discrimination of Chinese men. The research will show Chinese women were impacted economically and socially by their lack of visibility within society due to gender and cultural discrimination by both white and Chinese communities. Finally, without acknowledgement and education the perpetuation of racial stereotypes will continue.

Paycheques & Paper Promises: Coast Salish and Mi’kmaw Work And Family Life under Canadian Settler Colonialism - Osmond, Colin Murray (University of Saskatchewan, 2021)
Using Community-Engaged research and an intersectional approach, this dissertation examines and interprets the ways two different Indigenous communities – The Tla’amin of British Columbia and the Mi’kmaq of Pictou, Nova Scotia –responded to the challenges and opportunities associated with settler colonialism, the creation of Indian Reserves, and the establishment of a capitalist wage labour economy in Indigenous territories. It primarily situates this discussion within the context of colonial efforts to geographically anchor Indigenous families in specific places while they struggled to retain meaningful connections with their broader territories. This dissertation provides critical analysis of the utility of using ‘settler colonialism’ as a catch-all to explain the various types of colonialism that impacted Indigenous people in Canada. Various types of colonialism contributed to a process where Atlantic Mi’kmaw and Pacific Coast Salish people with complex understandings of their territories and resources based on seasonal procurement and kinship systems, became geographically anchored on reserves as part of Indian Bands in the late nineteenth century. Within this confusing and often contradictory colonial world, the Tla’amin and the Mi’kmaq built adaptive and flexible economies that emphasized multiple occupations and relied on labour inputs from women and men to function. I argue that these new markets for Indigenous labour and commodities played an as of yet underappreciated role in the historical understanding of Indigenous motivations for securing specific reserve lands during the colonial survey of Indigenous lands in Canada. This dissertation adds to a growing body of literature that celebrates and historicizes Indigenous contributions to the labour history of Canada, and does so in ways that express how Indigenous people developed dynamic and responsive economies within emerging settler colonial economies in the nineteenth and twentieth centuries.

Towards a Critical History of The Writers' Union of Canada, 1972-1992 - Ramlo, Erin (McMaster University, 2021)
The Writers’ Union of Canada was founded in November of 1973 “to unite Canadian writers for the advancement of their common interests.” Drawing on extensive archival collections – from both the Writers’ Union and its member authors – this dissertation offers the first critical history of the organization and its work, from pre-founding to the early 1990s, arguing that the Writers’ Union has fundamentally influenced Canadian literature, as an industry, as a community, and as a field of study. I begin by tracing the contextual history of the organization’s founding, interrogating how union organizing, celebrity, and friendship underpin the organization’s work. Chapter One discusses the Writers’ Union’s programs, reforms, and interventions aimed at ‘fostering’ writing in Canada as I argue that the Union was instrumental in building a fiscal-cultural futurity for CanLit. In Chapter Two, I consider the role that women played in this important work, as I highlight the labour of female Union members and the all-female administrative staff, who maintained and supported the organization’s work through its first twenty years. In Chapter Three I draw attention to the stories of, perspectives of, and experiences of BIPOC authors in relation to the Writers’ Union. While the Writers’ Union’s involvement in race relations is often positioned as having ‘begun’ with the Writing Thru Race conference in 1994, this chapter uses the archives to reveal a much longer trajectory of racialized conflict within and around the organization, providing important context for the very controversial and public battles about appropriation and race that would explode in the late 1980s and early 1990s. Throughout this work, I look to see how institutional narratives are deployed and upheld, and to what ends; how successful advocacy work is often effaced and forgotten; how institutional structures function; and how their boundaries and intentions are challenged and developed over time.

The Provincial Workmen’s Association of Nova Scotia, 1879-1898 - Reilly, Sharon M. (Dalhousie University, 2021)
This thesis examines the history of the Provincial Workmen's Association of Nova Scotia, from iits formation in 1879, until the resignation of the union's first Grand Secretary in 1898. The study begins with a description of the economic background of the province's coal trade during the 19th century. The end of the "golden age" of wood, wind and sail, and the region's attempts to industrialize in response to the National Policy are discussed in relation to the coal industry. The difficulties experienced by tlthe miners as a result of these changing economic conditions are considered in the second chapter, and the formation of the P.W.A. is described. The early organizational activitities, constitution, ritual and structure of the society are also detailed. The following chapter investigates the three tactics employed by the P.W.A. to protect the rights and improve the condition of the Nova Scotia miners. The utility and ideological underpinnings of each method - strikes, governmennt lobbying and electoral politics - is considered in order to clarify the degree of success achieved by the union in its stated goals. Chapter Four focuses more directly on the idtdeology of the P.W.A. "Loyalist" and "rebel" attitudes toward the coal masters, the increasing alientation of the mine1ers from their work resulting from the development of industrial capitalism, and the growth of trade union consciousness and working class awareness are described. The influence of Robert Drummond on the Nova Scotia miners is also discussed. The fifth and final chapter describes the rank and file disconterent with leadership that emerged in the late 1880s and culminated with the company store dispute in 1896. The "invasion of thee Knights of Labor" and the resignation of Robert Drummond are examined. Final conclusions are then presented, followed by an epilogue, which describes briefly the path taken by the P.W.A. from 1898 until the dissolution of the union in 1917.
Accepted: 2021-11-08T18:22:58Z

Trade Union Decline and Renewal: A Case Study of Precariousness, Labour Standards, and Union Responses in Ontario's Unionized Supermarket Sector - Rogers, Sarah (York University, 2021)
There is now a vast scholarship that explores union decline and renewal in various economic sectors and workplaces. To date, however, there is little understanding of how union decline has impacted unionized retail environments in Canada. Using a feminist political economy framework, this dissertation explores dynamics of union decline and renewal through a case study of labour standards in Ontarios unionized supermarket sector. Drawing on qualitative interviews with 28 union representatives and an analysis of collective agreements, this study examines the decline and trajectory of labour standards in unionized supermarkets, explores the unions perspectives and responses to changing standards, assesses how changing labour standards reflects the problem of union decline, and assesses how the case of Ontarios unionized supermarkets informs union renewal research and strategy. Findings suggest that the decline and trajectory of labour standards in Ontarios unionized supermarkets reflects a shift towards increasing precariousness in this sector. While there have been some wins for supermarket workers, unions have been largely unable to secure substantial improvements through collective bargaining. The precariousness associated with supermarket work is both contractually negotiated, as evidenced by provisions in collective agreements that ensure low wages and minimal and infrequent wage increases, demanding availability requirements, and limitations to the number of hours of work, as well as experiential, as indicated in workplace dynamics such as competition between workers, high turnover, and reduced health and safety measures. During the period under study, several factors have contributed to the increase in precariousness in this sector. While unions have implemented a variety of strategies in an effort to mitigate precariousness in unionized supermarkets, the persistence of deeply ingrained business union cultures and practices make improving labour standards through collective bargaining difficult. Continued precariousness in unionized supermarkets and the persistence of business unionism point to the need for an interrogation of the cultures and practices within unions that may contribute to the ongoing precariousness in unionized supermarkets and the challenges facing unions in this sector. The complex nature of union decline in this sector also suggests that multiple forms of union action are required to improve labour standards in unionized supermarkets and the strength of unions more broadly.

To Bite the Hands That Feed: Control and Competition in Temporary Foreign Worker Programs Amidst a Pandemic - Sevilla Valenzuela, Victor (University of British Columbia, 2021)
Canada’s continuous reliance on temporary foreign workers to address its labour shortage and maintain its competitive advantage has resulted in a seasonal transnational workforce characterized by its precarious living and working conditions, cumulative legal disenfranchisement based on the lack of permanent status, and vulnerability to the ongoing pandemic. Despite the common portrayal of the Seasonal Agricultural Worker Program (SAWP) as a ‘model for migration management’ by governments and growers, a large body of academic publications has studied their precarious conditions in an attempt to explain the seeming contradiction between a highly-exploited workforce and the steady growth of willing participants. This project examines the exploitative practices embedded in the cycles of transmigration through a series of individual interviews with SAWP participants, scholars, and government officials. The central argument is that the differential treatment of migrant and citizen workers lies at the heart of the former’s precarity. It stems from the paradoxical promotion of human rights at the macro-level, while relying on an exploited workforce at the micro-level. The program creates mechanisms that keep workers in a state of continuous marginalization despite decades of participation in the program. The legal, subtle, and overt mechanisms that maintain workers in a continuous state of control and competition are among the key findings of this project. This project challenges the idealization of the SAWP by analyzing the main beneficiaries, its shortcomings, and its projected future. It presents a unique opportunity to reimagine temporary foreign worker programs and methodological nationalism in a globalized context.

Jobs, Homes, and the Right to Exist: Neighbourhood Activism in Deindustrializing Toronto and Montreal, 1963-1989 - Vickers, Simon Thomas (University of Toronto, 2021)
This dissertation explores the points of tension between dominant histories of neighbourhood activism in Toronto and Montreal between 1963-1989 and the lived experiences of locally embedded activists who organized for access to safe jobs, homes, and the right to exist in their neighbourhoods. It demonstrates how material conditions, determined by the overlapping processes of deindustrialization, post-industrial development, and the movement of capital from Montreal to Toronto, shaped how neighbourhood activists organized, who they organized with, what they organized for, and how they recorded what they were doing. Dominant narratives of neighbourhood activism during this period over-emphasize the perspectives white, middle-class, and cis-gendered male activists who benefitted from the world the sixties made. Their upward mobility, made possible through the expansion of public spending and their involvement in gentrification, gave them the time and resources to document what they were doing, elevating their perspectives in the historical record. At the same time, embedded poor and working-class, racialized, disabled, and trans activists who continued to experience the ongoing structural violence of the capitalist city also continued to collectively resist that violence. Unfortunately, their ongoing precarity denied them of the resources necessary to produce historical records to the same degree as their upwardly mobile contemporaries. By historicizing how uneven material conditions shaped what activists were doing and how they recorded what they were doing, this thesis demonstrates how power shaped the production of neighbourhood activism history. It also presents opportunities to contest this power in the historical record.
https://cha-shc.ca/prize-winner/simon-vickers/

Sewing in Arviat: Inuit Women’s Work Through Stories and Parkas - Williamson, Christina (Carleton University, 2021)
Sewing has long been a core part of Inuit women's land-based labour in Arviat, Nunavut. The objects that Inuit women produce by sewing, such as parkas, embody their responses to and perspectives of colonialism and the entrenchment of the capitalist economy in their communities. This dissertation takes an interdisciplinary approach using archival records and photographs, museums objects, interviews with seamstresses and experiential learning. In this project, gendered work is inherently connected to gendered knowledge. The amauti, a women's parka with a pouch to carry small children is useful for understanding both work and knowledge because it is a tool for women's work, while also serving as a conceptual lens through which to discuss Inuit women's knowledge transmission. I use methodologies developed in material culture studies to carefully develop three case studies to trace Inuit women's labour through three sewing mediums. The first case study uses caribou skin parka designs to examine women's responses to shifting patterns of subsistence and contact with First Nations and Qallunaat. This chapter argues that changes in caribou skin parka designs embody Inuit women's work as they render changes in their designs to respond to changes in their worlds, thereby enabling the continued work of all family members. Ann Meekitijuk Hanson's concept of Inuktization underpins the next two chapters. One examines the use of trade commodity beads, to centre the decisions of Inuit seamstresses as they undertake the physical and intellectual labour that resulted in beadwork that reflects Inuit aesthetics and worldviews. In the final case study, I argue that the shift to fabric parka sewing in the twentieth century demonstrates that sewing remains a significant part of women's work in the mixed economy of Arviat. Inuit women Inuktized fabric into something that suited their needs despite the deprivations caused by colonial policies. The findings of this project foreground Inuit women's work in historical records by centring the sewn objects that women make; they use their knowledge and skills to create a distinctly Inuit modernity.

(End)Zones and (Out)Fields of Production: Contemporary Conditions of Labor and Artistic Critique - Anderson, Stephanie (Western University, 2020)
In a 2013 exhibition publication titled It’s the Political Economy, Stupid!, John Roberts made the observation that “Over the last ten years we have become witness to an extraordinary assimilation of art theory and practice into the categories of labor and production.” Whereas once art claimed for itself a critical capacity in relation to the larger system of capitalist domination by its status as a putatively ‘autonomous’ sphere of production from which it leveraged its difference and critique, today it is largely acknowledged that there is no longer any such ‘outside’ to be aspired to. If, in the recent past, the immaterial, informational, creative, experiential, and affective elements of conceptual art were seen as potential resistant forces, in our current climate, where these forms of labor have become the dominant mode of production for the capitalist economy, these potentialities are now being widely questioned. With these developments in mind, this dissertation consists of a series of integrated articles that focus on the increasingly diffuse and interconnected circuits of global exchange and labor as they interact with specific sites and interventions of contemporary artistic production. In this, they coalesce around a general binding inquiry: does artistic labor today have the capacity to function as a critique of the (transforming) mechanisms of control and exploitation characteristic of capitalism in the twenty-first century? And if not, what does that entail about the continued political viability, and persisting social functions of contemporary artworks? Drawing on autonomist Marxist thought, the sociology of work and labor, performance studies, and critical readings on the relationship between artistic labor and recent forms of capitalist production, the chapters are organized around exhibitions and artworks which represent, critique, or (re)produce the conditions of production in late capitalism, while situating these within a global economy characterized by an uneven network of productive relations. In so doing, they trace the trajectory of labor relations and production practices as they have transformed over the last half decade through artworks and exhibitions that engage specific emblematic sites of production—the factory, the prison, and the museum (or amalgams of these spaces), and attempts to tease out places where reflection on the relationship between ‘artistic’ and ‘non-artistic’ labor in each may lead to clarity regarding the socio-political efficacy of contemporary art in an increasingly saturated and complex economic infrastructure.

Analyse critique de l'extractivisme comme mode de développement nordique à partir du cas de l'exploitation du minerai de fer au Québec - Bédard, Samuel (Université du Québec à Montréal, 2020)
Ce mémoire de maîtrise traite du rapport qu’entretiennent les grandes entreprises minières avec les collectivités locales, dans un contexte nordique. À partir du cas québécois de l’exploitation du minerai de fer, nous tentons d’apporter un éclairage nouveau à l’idée communément admise selon laquelle l’implantation, sur des territoires enclavés, de grands projets extractifs, constitue un vecteur de développement régional important. La démarche d’économie politique proposée prend pour objet les modes de gestion des ressources humaines et financières privilégiés dans le secteur minier de la Côte-Nord. Les données recueillies dans le cadre d’une analyse documentaire et d’une série d’entretiens semi-dirigés, menés à l’hiver 2019, convergent vers la thèse suivante : la diminution des retombées économiques constatée dans cette région est attribuable à la déterritorialisation de l’organisation contemporaine du travail dans les mines ainsi qu’à l’émergence de stratégies de restructuration épousant la dynamique du cycle de commodités.

Temporary Foreign Work, Precarious Migrant Labor and Advocacy in Canada: A Critical Exploratory Case Study - Brown-McLaughlin, Simone (University of Alberta, 2020)
Over the past forty-seven years, thousands of temporary foreign migrant workers have been arriving in Canada annually, to labor in sectors of precarious work including farming, caregiving and the service sector given the demand from employers seeking cheaper sources of labor or for work that Canadians are not available to do or are unwilling to do. Given the context of 21st century neoliberal capitalist globalization which has transformed the international division of labor, there has been an increase in the demand for migrants as a flexible source of cheap labor. Canada’s dependence on migrant workers has been facilitated through bilateral and unilateral programs with countries of the Global South to provide a steady stream of workers for its workforce. The purpose of this research was to critically explore and develop an understanding of precarious migrant worker exploitation and concerns pertaining to the Temporary Foreign Workers Program (TFWP) in Canada to inform advocacy undertaken by migrant organizations. Utilizing a race-gendered neo-Marxist perspective on capital and migrant labor a case study strategy was adopted and developed pertaining to the Seasonal Agricultural Workers Program (SAWP) and the Caregivers Program. Data collection included in-depth and focus group interviews with 17 farm and caregiver migrant workers and advocates, document reviews and analysis of web materials. Thematic analysis suggests temporary migrant work is marked by coercion, misrepresentation of contracts and bonded contractual arrangements. Migrant work and living in Canada are characterized by increasing levels of labor unfreedom experienced as domination, subordination, and race-gendered exploitation. Temporary foreign migrant workers are being driven further into debt, endure substandard working conditions and a social experience in Canada marred by prejudice, discrimination, and oppression. These preliminary critical exploratory findings inform advocacy work for migrant workers by contributing to new ways of "knowing and doing” and to challenge existing predatory precarious migrant work policies, processes, and experiences in Canada and internationally.

Le syndicalisme entre deux âges : le mouvement ouvrier à Québec et Lévis, 1896-1914 - Cadieux, Alex (Université d'Ottawa / University of Ottawa, 2020)
Dans notre thèse, nous étudions la période de « flottement » et de réorganisation du mouvement ouvrier entre le déclin de l’organisation des Chevaliers du Travail et l’ascension du syndicalisme catholique. Notre étude révèle que cette expérience de transition, entre les années 1896 et 1914, est formatrice pour le mouvement ouvrier de Québec et Lévis. L’analyse de ces années s’avère essentielle mieux saisir et caractériser la suite des évènements dans le monde syndical de cette région. Notre regard nouveau sur le mouvement ouvrier de Québec et Lévis permet d’éclairer le rôle actif des travailleurs et de nuancer le misérabilisme contenu dans une partie de l’historiographie ouvrière. En effet, nous montrons que les travailleurs de Québec et Lévis s’activent dans le monde du travail, mais aussi sur la scène politique, entre 1896 et 1914 afin d’améliorer leurs conditions de vie et de travail. Notre thèse indique aussi que, contrairement au contexte montréalais, Québec devient le bastion du syndicalisme national durant cette période. Cette conjecture peut trouver racine dans la relation particulière qui se développe à Québec et Lévis entre les patrons, la classe ouvrière et l’Église. En effet, l’Église de Québec et Lévis se montre un acteur important entre 1896 et 1914 ; la classe ouvrière doit ainsi négocier avec cette dernière pour se développer. Notre analyse permet ainsi d’expliquer le cheminement particulier des ouvriers de Québec et Lévis entre 1896 et 1914 et de mieux saisir leurs idéologies et leur conduite.

Mining Ontario: Corporate Power, the Mining Industry, and Public Policy in Ontario - Corbeil, Matthew Joseph (York University, 2020)
This dissertation critically examines the history of the government of Ontarios policies towards the mining industry to analyze the impact of concentrated economic power on political processes in liberal democracies. It is the first comprehensive study of the political power of one of the provinces largest and most influential industries. Drawing on critical theories of business power, this dissertation examines policy developments across four contentious issue areas, namely fiscal policy, air pollution control, occupational health and safety, and access to mineral lands. Employing a qualitative historical narrative, the study draws on data collected from the Public Archives of Ontario, newspapers, published reports and secondary academic literature. Challenging those theoretical perspectives that downplay the direct influence of large business enterprises over public policy, this dissertation argues that the mining industry has exercised a predominant influence over the government of Ontarios public policies. While the industry disposes of several political resources that privilege it in relation to its opponents, two in particular deserve special attention: First, minings commanding economic presence in the provincial North where alternative investment opportunities are generally absent, and second, the industrys deep-seated linkages with the provincial mining ministry in terms of personnel and ideology. In sum, the mining industrys structural power over the Northern economy together with its close working relations with the provincial ministry of mines have rendered provincial policymakers particularly vulnerable to the industrys lobbying, allowing the industry to play a predominant, though not monolithic, role in shaping provincial public policy.

Uncertain Future, Unsettled Present? Everyday Geographies of Precarious Immigration Status in Toronto, Canada - Dennler, Kathryn Elizabeth (York University, 2020)
Increasing processing times for immigration applications and increasing numbers of people admitted on temporary visas mean that more newcomers spend longer periods of time living in Canada with restricted rights and uncertain if they will be able to remain. This has contributed to an increase in precarious immigration status, which refers to a sense of insecurity caused by ones formal immigration status. The purpose of the dissertation is to examine how people are affected by living for prolonged periods of time with uncertainty about future residence and how these effects vary across space and time. The study, based on qualitative research with migrants in Toronto and people who work on migration issues, investigates how immigration status is performed in everyday life and how immigration status intersects with other social relations to produce distinctive affective textures of life in Toronto. The research shows that formal immigration status affects people differently depending on their migration motivations, capacities, and community support networks. Lack of reliable information about the time required to become eligible for permanent residence and application processing times make it more difficult for people to make decisions about how to orient themselves towards the future, the present, and the passage of time in ways that meet their needs. It identifies two salient temporal orientationssuspending or embracing engagement with everyday lifeeach of which comes with benefits and risks. Finally, the research suggests that contemporary practices of immigration control can lead to an internalization of discourses that construct people with precarious immigration status as unworthy of membership in Canadian society. Participants sought to undermine these discourses through narrative redefinition of themselves as people who have something to contribute but are stopped from doing so. I find that this resistance is necessary to peoples ability to persist, yet it has a limited effect on the harm done. The research findings contribute to scholarly understandings of formal immigration status and the slow violence of living with precarious immigration status.

Le Conseil général de la CEQ et l’arrimage de l’éducation à la souveraineté du Québec, 1990-1995. - Derradji, Fabrice (Université de Montréal, 2020)
Notre doctorat est une recherche sur l’histoire du syndicalisme enseignant au Québec durant la première moitié des années 1990. Plus précisément, du Congrès de la Centrale des enseignants du Québec (CEQ) de juin 1990 à la convocation par le ministre de l’Éducation du gouvernement Parizeau des États généraux sur l’éducation en mars 1995. Notre recherche s’efforce de poser des jalons pour une première histoire critique du syndicalisme des enseignants à construire dans son rapport à l’histoire de l’éducation selon un constat initial que la première est sous-évaluée, voire largement invisible dans divers champs des sciences humaines et sociales (Relations industrielles, sociologie et histoire). La CEQ est la centrale syndicale des fédérations et des syndicats locaux représentant des enseignantes et des enseignants du Québec (des secteurs primaire, secondaire, collégial et même universitaire) et des professionnels de l’enseignement (animateurs de pastorale à l’époque). L’organe décisionnel de la CEQ est le Congrès national qui se réunit tous les deux ans ; l’application des décisions du Congrès se fait à la fois par le Bureau national (Conseil exécutif à partir de juin 1992) et le Conseil général des délégués de toutes les fédérations et de tous les syndicats locaux affiliés à la Centrale. Cette agora syndicale, qui se réunit six fois par année, est le cœur de la vie démocratique, tumultueuse, de la Centrale syndicale et étudie tous les rapports, les documents, les analyses, etc., qui lui sont soumis par le Bureau national / Conseil exécutif, l’unité de recherche de la CEQ ou divers comités. Dans un premier temps, notre thèse aborde le fait que le syndicalisme enseignant québécois est un objet historique inachevé et inabouti. Notre démarche tente de répondre à ce lien problématique entre historiographie et histoire. Puis, elle propose de nouveaux jalons pour une étude critique de cette histoire, notamment sur l’échec de la première tentative d’arrimage syndical de l’éducation à la souveraineté du Québec de 1977 à 1984. Mais alors, comment une centrale syndicale a-t-elle pu évoluer d’une opposition d’inspiration marxiste à toute tentative de réforme imposée de l’éducation et à un projet de souveraineté considéré comme conservateur et « capitaliste » portée par le PQ en 1977-1985 à iii une proposition d’une réforme globale, néolibérale, de l’éducation et un soutien à une souveraineté « sociale-démocrate » portée par le même parti politique en 1994-1995 ? Pour expliquer et comprendre ce paradoxe historique, nous allons étudier les nouvelles orientations stratégiques de la CEQ à partir du Congrès de juin 1990. Puis, dans un second temps, à partir d’archives syndicales – les procès-verbaux des réunions des délégués syndicaux au Conseil général de la CEQ –, notre étude historique porte sur le second arrimage de l’éducation fait par la Centrale à la conquête de la souveraineté du Québec, et particulièrement le rôle que joua le Conseil général des délégués syndicaux quant à la définition de quatre positions : 1) la question de la déconfessionnalisation, puis de la laïcité du système éducatif québécois ; 2) l’élaboration de la politique d’éducation interculturelle ; 3) les enjeux politiques et stratégiques autour de la définition de la souveraineté du Québec ; 4) le tournant participatif et la proposition d’une réforme globale de l’éducation au Québec. Enfin, notre recherche historique nous amène à décrire les mémoires syndicales enseignantes qui font de la CEQ une centrale syndicale si particulière dans l’histoire du mouvement ouvrier québécois.

“The CCF Is Not a ‘Class’ Party”: Labour, Politics, and Their Unification at the Lakehead, 1944-1963 - Duplessis, Nicholas James (Lakehead University, 2020)
This study analyzes the new sophistication of the organized labour movement and labour’s relationship to politics in a period of rapid change for the Lakehead. ““The CCF is not a Class Party”” argues that, between 1944 and 1963, the organized labour movement and the Cooperative Commonwealth Federation (CCF) at the Lakehead underwent parallel structural developments against the backdrop of conservative social forces in the postwar period that, by the end of the 1950s, necessitated a merger of the two formally distinct entities. The amalgamation of labour and politics, resulting in the formation of the New Democratic Party (NDP), is best examined through the political career of Douglas Fisher, who first represented the CCF and, later, the NDP in Port Arthur. The debate surrounding the ‘New Party’ idea in the late 1950s at the Lakehead is reflective of the uneasy relationship between labour and politics that had formed throughout the postwar period.

Work and Worth: A Contested History of Labour and Value in Toronto’s Public Libraries - Frederiksen, Lia (University of Toronto, 2020)
Public libraries are often thought of as inherently democratic institutions where the provision of informational resources supports social inclusion and civic participation. Inspired by a recent citywide conflict over potential library closures in Toronto, Canada, this dissertation investigates a more contested history than conventional interpretations have often permitted by revealing a series of conflicts over public library buildings, budgets, and governance across more than a century. The main argument is that understanding this history requires an account of the overall work done to make and remake these spaces into what they are today, as a way of understanding of what these spaces may soon become. This argument illustrates how the perceived worth of providing public library service, whether or not it is accounted for in monetary terms, can be seen as socially constructed and politically contested. To make this argument, I draw mainly from feminist theorizations of work, which broaden this category to encompass productive waged labour along with paid and unpaid reproductive labour coded as ‘nonwork’ or ‘unproductive’, and geographers’ insights on the contested social production of space. In so doing, this dissertation aims for a critical re-thinking of what these spaces mean for daily urban life.

"Ni Rome, ni Moscou" : l'itinéraire des militants communistes libertaires de langue française à Montréal pendant l'entre-deux-guerres - Houle-Courcelles, Mathieu (Laval et Université Paris, 2020)
Cette thèse retrace l’itinéraire collectif d’un groupe de militants communistes libertaires de langue française pendant l’entre-deux-guerres à Montréal rassemblés autour d’Albert Saint-Martin (1865-1947). Figure importante du mouvement ouvrier au Québec, l’itinéraire politique de Saint-Martin est multiforme : on le retrouve associé au Parti socialiste du Canada, à la One Big Union, au Parti socialiste (communiste), à la Ligue des sanstravail, à l’Association révolutionnaire Spartakus, à l’Université ouvrière, à l’Association humanitaire, à la Ligue du Réveil féminin et à de nombreuses coopératives de consommation et de production. Saint-Martin est entouré de camarades provenant de divers horizons politiques. Notre thèse nous a permis d’identifier plus de 300 individus ayant pris part à des activités militantes à ses côtés. À travers l’analyse croisée de leurs parcours individuels, nous cherchons à mieux comprendre les modalités de leur engagement collectif avant, pendant et après la Première Guerre mondiale, leur représentation de la société idéale et les moyens d’y parvenir, la nature et la diversité de leurs liens de sociabilité, les territoires où se déploient leurs réseaux, la fréquence et les thèmes de leurs réunions de même que les symboles et les rituels qui y sont rattachés. Nous faisons l’hypothèse que celles et ceux qui participent aux activités de ce milieu partagent une même culture révolutionnaire articulée autour des notions de communisme, d’anticapitalisme, d’anticléricalisme et d’internationalisme, débouchant sur une critique des institutions autoritaires : l'État, l’Église catholique, la propriété privée, l’armée, le mariage, etc. Les stratégies d’émancipation individuelle et collective mises de l’avant par ces militants et ces militantes reposent sur l’éducation et l'action directe. C’est cet ensemble de principes théoriques, stratégiques et tactiques que nous regroupons sous le terme de communisme libertaire.
https://cha-shc.ca/prize-winner/mathieu-houle-courcelles/

Making Prison Work: Prison Labour and Resistance in Canada - House, Jordan Lorne (York University, 2020)
This dissertation examines prisoner-worker organizing in Canada by considering three case studies in detail: first, the successful unionization of an experimental privately managed abattoir at the Guelph Correctional Centre, a provincial jail in Ontario, in 1977; second, efforts by federal prisoners to unionize, with a particular focus on the efforts by the Prisoners Union Committee in 1975 and the Canadian Prisoners Labour Confederation, between 2010-2015, and; third, the nation-wide federal prison strike in response to prisoner wage cuts in 2013. Through these cases, this study examines the similarities and differences between prisoner-workers and their non-incarcerated counterparts, and considers the methods and motivations of prisoner organizers, as well as the substantial legal and organizational barriers that Canadian prisoners face in their organizing efforts. Working prisoners are one of many groups who labour on the margins of society and the economy, and who have been largely overlooked or dismissed by both scholars of work and labour and the labour movement. This study seeks to expand conventional definitions of who is a workerand what constitutes the working classby demonstrating ways that prisoners have asserted their rights as workers and the legitimacy of their organizations and struggles. Through these struggles, which have been conceptualized not only as economic, but also as political struggles, prisoners have contested their state of privation and laid claim to new sets of rights. At their most successful, the organizing efforts of working prisoners have resulted in not only improvements to their working lives, but also expanded rights and freedoms in relation to their incarceration.

“Just Go to Work”: Gendered Harassment in Resource Extraction Work in Canada - Kelly, Griffin (University of Alberta, 2020)
This Master’s thesis examines tradeswomen’s experiences of and responses to gendered harassment at camp-based work in resource extraction industries in western Canada. This study predominantly features women working in the Alberta oil sands industry. Gendered harassment at work has been identified as a major issue in recent years (Curtis et al., 2018; Denissen, 2010; Wade & Jones, 2019) and this study aims to better understand tradeswomen’s day-to-day experiences of harassment in work camps. I utilize constructivist grounded theory methodology and critical feminist geography as the theoretical framework for the project. I find that tradeswomen employ a wide range of affective, material, and social strategies to manage harassment. I introduce two concepts, “just go to work” (JGTW) and “me vs. other girls,” to illuminate these strategies for self-preservation in the masculine occupational culture of work. This is labour that tradeswomen must perform in addition to their demanding work duties and schedules. JGTW demonstrates how gendered harassment is embedded into the masculinist culture of work of the trades. This study begins to address this gap in scholarly literature to capture the shifting cultural context of the oil sands industry and identifies new areas for future research.

Drowned: Anishinabek Economies and Resistance to Hydroelectric Development -in the Winnipeg River Drainage Basin, 1873-1975 - Luby, Brittany Alexandra (York University, 2020)
In 1893 the Keewatin Lumber and Power Company planned the first hydroelectric generating station on the north shore of Lake of the Woods (near present-day Kenora, Ontario). Approximately fifty years later, federal officials seeking employment for Canadian veterans turned to Northwestern Ontario and its underutilized water resources, envisioning a manufacturing hub on the Precambrian Shield. Between 1950 and 1958, the Hydroelectric Power Commission of Ontario remodeled the Winnipeg River drainage basin to produce power for federally-sanctioned peacetime industries, namely pulp and paper production. To redesign the Winnipeg River drainage basin, however, hydro officials needed to encroach on Anishinabek lands: both federally-recognized reserves and unrecognized, but heavily occupied, ancestral territories. This dissertation tells the story of how Anishinabek families used a diverse array of strategies adaptation, cooperation, and passive resistance to manage environmental change caused by Whitedog Falls Generating Station. Anishinabek families worked to stabilize their communities in an era of imposed environmental and economic change. Historians have long argued that hydroelectric development is necessarily at odds with Indigenous culture and subsistence economies. This dissertation provides a counter-narrative, arguing that cultural and economic damage, although linked to environmental damage, correlated more strongly with Anishinabek exclusion from resource negotiations. Moreover, this work complicates historical representations of a uniform Indigenous response to development. Given limited negotiations between the Hydro-Electric Power Commission and local First Nations, Anishinabek families did not respond to industrial incursions with one representative voice. The process of development itself, I argue, prevented a unified community response. As a result, Anishinabek communities fractured in response to hydroelectric development.

Serving Each Other: Sharing Economies and Affective Labour in Montreal’s Kiki Scene - Lundy, Jess D. (Jessica Dawn) (Carleton University, 2020)
Against a tense socio-political backdrop of white supremacy, intensifying pressures of neoliberal fiscal austerity, and queer necropolitics, this thesis addresses performance-based activist forms of place-making for urban-based queer, trans, and gender nonconforming communities of colour. Using participant observation and qualitative interviews with pioneering members of Montréal's Kiki scene and Ottawa's emerging Waacking community and interpreting my findings through the theoretical lens of queer of colour theory, critical whiteness studies, queer Latinx performance studies and Chicana feminism, I argue that Kiki subculture, which is maintained by pedagogical processes of 'each one, teach one', is instrumental in facilitating i) life-affirming queer kinship bonds, (ii) alternative ways to simultaneously embody and celebrate non-normative gender expression with Black, Asian, and Latinx identity, iii) non-capitalist economies of sharing, and iv) hopeful strategies of everyday community activism and resilience to appropriative processes during economic insecurity and necropolitical turmoil.

Just a Farmwife?: An Intergenerational, Intersectional Study of Women’s Labour on Southern Alberta’s Dutch Reformed Family Farms, 1950–2019 - Martens, Shelby Blair (University of New Brunswick, 2020)
Through two-part intergenerational oral histories, this thesis explores the intersections of labour, gender, and lived religion in the lives of twelve Southern Alberta, Dutch Reformed women from family farms from the 1950s to 2019. By focusing on the broader lived experience of the women interviewed, and not just their physical labour on the farm, this thesis argues that women’s roles on the family farm were crucial, while complicating the narrative of farm women’s roles to show their multiple and often conflicting identities.

Harms of Criminalization of Sex Work: How End-Demand Legislation and Immigration Policy Shape Labour, Health and Rights Among Im/Migrant and Indoor Sex Workers in Canada - McBride, Bronwyn (University of British Columbia, 2020)
Background and objectives: Globally, sex workers experience labour rights abuses, disproportionate burdens of workplace violence, and restrictions on safer ways of working (i.e., collectively and in indoor venues) due to criminalization. These inequities are often exacerbated among im/migrant sex workers, who may additionally face precarious legal status, restrictive immigration policies and racialized policing. Despite implementation of “end-demand” legislation (legal models aimed at ending clients’ demand for sexual services) in dozens of countries, little empirical research has explored how end-demand laws impact sex workers’ labour conditions. This dissertation sought to explore how end-demand laws and prohibitive immigration policy impact labour conditions, health and rights among im/migrant and indoor sex workers in Vancouver. Methods: This dissertation drew on quantitative and qualitative data collected from AESHA (An Evaluation of Sex Workers’ Health Access), a community-based open prospective cohort of 900+ women sex workers across Vancouver, Canada, who complete bi-annual interviewer-administered questionnaires and voluntary sexual health testing. Mixed methods (explanatory and confounder bivariate and multivariable logistic regression analyses; interrupted time series; coding of semi-structured interview data) were used to elucidate the impacts of end-demand laws and resulting law enforcement practices on indoor and im/migrant sex workers’ labour environments. Results: This dissertation found that end-demand legislation in Canada failed to improve sex workers’ access to justice, restricted access to supportive third parties and safer indoor venues, heightened the vulnerability of sex work venues to violence, and limited access to occupational health resources (condoms, community-led services); with negative implications exacerbated among im/migrant sex workers. Conclusion: These findings extend limited existing research on the impacts of end-demand legislation, and demonstrate that end-demand criminalization reproduces the harms of full criminalization models. These results have important implications for legislative, policy, and law enforcement reforms towards enabling safe labour environments among im/migrant and indoor sex workers. This dissertation calls for the decriminalization of sex work; removal of prohibitions on im/migrant sex work; sensitivity and anti-stigma trainings among authorities; dedicated efforts to address systemic racism in sex work policing; promoting rights-based municipal occupational health standards; and increasing support for sex worker-led outreach; to promote sex workers’ labour and human rights.

Connected by a Thread: Stories of Migration and Labour in Sara Angelucci’s Piece Work - Montpetit, Chiara (Concordia University, 2020)
This thesis is a critical analysis of the multimedia project Piece Work (2017) by Toronto-based, Italian Canadian artist Sara Angelucci (b. 1962). Focusing on Coppley Apparel, a garment factory in Hamilton, Ontario, the project explores the process of making business suits through the digital collage Coppley Patterns and the photographic series Mano d’Oro. The sound installation A Sewers’ Chorus features the voices of the garment workers who recall positive and negative memories of their work experiences and personal histories, while the video installation Suit Elevator depicts the business suit in its final form. The majority of Coppley Apparel’s employees are women from non-white racialized groups. Deploying an intersectional feminist approach, this thesis argues that Piece Work reveals the complex lives of these factory workers from immigrant backgrounds in ways that speak against persisting discourses and practices of racialized and gendered labour in the garment industry. It begins by providing an overview of the history of the Coppley Apparel factory in relation to the history of migrant garment factory workers in Hamilton, and the broader history of racialized and gendered factory labour in the city. This thesis also acts as a record of the migration story of Nina Acciaroli, the artist’s mother, whose first job in Canada was at Coppley Apparel. It then examines A Sewers’ Chorus and its use of oral history, providing a discussion of the different stories shared by the interviewees, which range from happy childhood memories and nostalgic flashbacks to accounts of traumatic experiences. The thesis provides a comprehensive discussion of the process of making Piece Work, contextualizing it within Angelucci’s larger artistic practice of incorporating voices in the exploration of her family’s immigrant experience. Ultimately, Piece Work recognizes the employees of Coppley Apparel as people with singular voices and unique experiences and highlights their agency by including the complexity of their voices and identities as women, garment workers, racialized minorities, and contributing members of Canadian society.

Organizing Canadian Theatre Designers: The Intersection of Creative and Precarious Labour - Moore, Conor (Simon Fraser University, 2020)
Canadian theatre designers share many similarities with other freelance, creative workers in Canada. The conditions of precarity that define their working relationships are similar to those that affect workers in other sectors, such as film, music, television, and visual arts. This thesis begins by examining the existing literatures and research concerning creative and precarious work, primarily in Canada, but also internationally. Drawing on in-depth interviews of 55 designers from within the relatively small community of Canadian theatre designers, approximately 500-700 workers, I examine the working conditions that designers find challenging and seek suggestions for how they can be improved. Additionally, I explore the different models that designers have used to organize in Canada, Quebec, and the United States. By comparing these models with the interviews from designers, I conclude that the best way for Canadian designers to improve their working conditions is to build a closer relationship with IATSE [International Alliance of Theatrical Stage Employees], the union that represents stagehands and technicians. Finally, I identify some questions for further exploration, including the tension between artistic and worker identities, while also touching on the present circumstances of the Covid-19 crisis and the current conversations concerning racism and white supremacy within Canadian society.

Beyond the Barbed Wire: POW Labour Projects in Canada during the Second World War - O'Hagan, Michael (Western University, 2020)
This dissertation examines Canada’s program to employ prisoners of war (POWs) in Canada during the Second World War as a means of understanding how labour projects and the communities and natural environment in which they occurred shaped the POWs’ wartime experiences. The use of POW labourers, including civilian internees, enemy merchant seamen, and combatant prisoners, occurred in response to a nationwide labour shortage. Between May 1943 and November 1946, there were almost 300 small, isolated labour projects across the country employing, at its peak, over 14,000 POWs. Most prisoners were employed in either logging or agriculture, work that not only provided them with relative freedom, but offered prisoners unprecedented contact with Canada and its people. Work would therefore not only boost production but, it was hoped, instil POWs with Canadian mores and values through interaction with guards, civilians, and the natural environment. Rather than attempt a narrative encompassing almost 300 labour projects, this dissertation examines POW labour through a series of five case studies. The first examines prisoners cutting fuelwood in Manitoba’s Riding Mountain National Park while the second and third examine POWs cutting pulpwood in Northwestern Ontario for the Ontario-Minnesota Pulp & Paper Co. and Abitibi Power & Paper Co., respectively. The fourth case study examines POWs employed by Donnell & Mudge in its tannery in New Toronto, Ontario and the fifth examines the practice of employing POWs in farm work in Alberta, Saskatchewan, Manitoba, Ontario, and Quebec. Through these case studies, this dissertation examines how how internment officials employed remote parts of Canada as a physical boundary to prevent escape attempts, while also using it as a space to provide POWs with relative freedom as an inducement to work, and how work challenged definitions of who or what was the “enemy”. With significantly more freedom than the typical internee, POWs interacted with civilians and guards on a more familiar level, resulting in illicit fraternizations and relationships between POWs and Canadians. Although such fraternization also triggered considerable protest, these interactions reveal a great deal regarding POWs’ opinions of and attitudes towards Canada and its people as well as Canadian attitudes towards POWs.

The Academic Librarian as the Subaltern: An Institutional Ethnography of a Feminized Profession - Revitt, Eva Justyna (University of Alberta, 2020)
I locate this study within the context of my own work and experiences as an academic librarian and the disconnect that I have often felt between what I consider my role and the value of my work to be versus the perception and understanding of that role, the work, and its value by others. Overwhelmingly, librarians working at Canadian universities are considered academic staff, if not faculty. However, the role and fit of the academic librarian within the academic enterprise is overshadowed and frequently misunderstood. As the subaltern, librarians’ expertise and contribution to the university’s academic mission is often sidelined: the nature of the work too frequently viewed through an organizational rather than an academic lens and characterized as preoccupied with a structured set of regularized responsibilities. The goal of this study is to make visible the processes that shape the work experiences of academic librarians such as they are. Two research questions served as the impetus for this study: How is it that the academic librarian’s lesser status is the ideal at Canadian universities? What are the social processes that shape this ideal? This study is informed by the epistemological, ontological, and methodological assumptions of institutional ethnography: a research approach developed by the Canadian social theorist and sociologist, Dorothy Smith. Institutional ethnography considers the everyday, lived experiences of people as the research problematic—a term used by Smith to focus the inquiry on the actual, social, and active world as it is lived and experienced by people. An institutional ethnography progresses through layers, in this case the progression is from the academic librarian, to the library, to the institution, and beyond, to reveal how power structures external to the local setting influence daily life. To understand how the everyday world is put together so that things happen as they do, the focus of the investigation is on individual experiences and what people are doing relationally. However, in institutional ethnography the actions and experiences of people within a particular setting are not regarded as representative. Rather, the local experience is regarded as a window into the role of power. It is a politically charged and activist type of scholarship. Because institutional ethnography is concerned with explicating the actual rather than formulating or advancing the theoretical, the emphasis is on discovery rather than hypothesis testing. The findings of this study reveal how the value of librarians’ work is socially constructed and based on work that is perceived as women’s work; how the work of librarians is organized as library work rather than academic work; how accreditation bodies and the professions privilege the library over the librarian; and how institutional policies and practices position the librarian as academic on the margins of the academy. These social processes reveal how things come about so that librarians’ experiences as academic staff are such as they are. However, it is ideologies that help us understand why things are the way they are. I propose that two ideological codes—women’s work and the library—permeate our social consciousness, including speech, text, and talk, and infuse librarians’ work with particularizing characteristics. Ultimately, the findings of this study tie librarians’ work experiences to the necessary and gendered exploitation of labour that happens within a capitalist mode of production.

Seam Stress: Garment Work and Gendered Labour Struggle in 1980s Montreal - Siaw, Leona (Concordia University, 2020)
Montreal’s garment industry was the largest in Canada until most of its factories closed or relocated in the 1980s and 1990s, but it did not go out quietly. Staring down the barrel of rapid, state-sanctioned deindustrialization, 9,500 members of the Quebec ILGWU, most of them immigrant women, launched an industry-wide strike in August of 1983, the first in 43 years, as well as the last. Using the strike as a springboard, this thesis combines oral history interviews and archival material with historical, geographical, and feminist literatures to understand how women workers experienced and contested garment deindustrialization in 1980s Montreal. The result is a graphic novel about garment work and feminist labour struggle, for public consumption. This thesis adds much-needed female perspective to a growing body of work around deindustrialization and its contestation within history and geography. Conceptually and politically, it seeks to recast the Mile End and Mile-Ex as a site of feminist, working-class struggle, placing gentrification in conversation with deindustrialization while offering a primer on place-based labour organizing during a time of unprecedented capital mobility.

Theorizing Precarization and Racialization as Social Determinants of Health: A Case Study Investigating Work in Long-Term Residential Care - Syed, Iffath Unissa (York University, 2020)
This thesis uses anti-racist and feminist political economy of health perspectives that intersect with immigrant status, in order to analyze the findings from a single-case study investigating the social determinants of health and work precarization in a residential long-term care (LTC) facility in Toronto, Ontario. Throughout this dissertation, I use mixed methods case study to investigate social, political, and economic implications in the lives of health care workers. Observation, interview, and survey methods were utilized to investigate workers health in relation to the precarization of work. Specifically, I used the concept of precarization as a lens to track the ways in which work relations impact the other social determinants of health. The main areas of focus include the intersections of gender, work, and occupational health with race, immigrant status, and culture; the ways in which precarization affects employees in this specific health care sector; the implications of precarization in the health and wellbeing of workers and their families; the role of (un)paid care work and social support provided by family members; and the exercise of strength, resilience, resistance, agency, and coping strategies. Broadly, I will argue that precarization in LTC is an increasingly experienced phenomenon, and that various levels of precarization are experienced by particular workers who are women, racialized persons, and immigrants. This study contributes to our understanding of racialization as a social determinant of health, and analyzes the health impacts of workplace inequality through the lens of precarization. The study makes the case for closer attention to racism and precarity both on and as social determinants of health.

Mapping Ruling Relations Through Homelessness Organizing - Withers, A. J. (York University, 2020)
Poor peoples organizing can be effective even in periods of neoliberal retrenchment. This dissertation examines ruling relations and the social relations of struggle from the standpoint of the Ontario Coalition Against Poverty (OCAP) in Toronto, Ontario, Canada. With political activist ethnography as my central theoretical framework and methodological approach, I conducted field research, interviews and textual analysis of City and organizational documents. Focusing on OCAPs homelessness campaigns, I examine the social relations of struggle in three campaigns in Toronto: a campaign to stop the criminalization of homeless people in a public park by private security, a campaign to increase access to a social assistance benefit for people in emergency housing need, and a campaign to increase the number and improve the conditions of emergency shelter beds. My research demonstrates the active and ongoing research and theorization that anti-poverty activists engage in as well as the practices of delegitimization, excluding critique, testimonial injustice and epistemic violence that ruling relations engage in to counter activist research and theory. Some of this research and theory has regarded both Housing First policy and philosophy and Torontos emergency shelter system which OCAP, homeless people and other advocates have been decrying as unjust and inept for years. This dissertation explicates some of the ways that the City works to delegitimize its challengers and demonstrates the validity of many of the longstanding critiques of the ruling regime. While the City of Toronto has worked to contain homelessness organizing in Toronto, and deployed numerous demobilization tactics to do so, each campaign was fully or partially successful. Full or partial victories were secured by anti-poverty activists through the use (or threat) of direct action tactics.

Extracting Views About the Environment: Oilfield Workers’ Understandings of Climate Issues in Moose Mountain, Saskatchewan - Adams, Shelby B. (Royal Roads University, 2019)
The purpose of this research was to describe oilfield workers in the Moose Mountain Provincial Park area in southeastern Saskatchewan views on climate change. This qualitative study, inspired by Grounded Theory, utilized fifteen, semi-structured interviews to analyze participants’ perspectives and experiences. For this research, climate change means, “a change of climate which is attributed directly or indirectly to human activity and which is in addition to natural climate variability” (IPCC, 2014). This study has three main findings. First, participants have robust “sense of place” attachment that fosters environmental stewardship toward the Moose Mountain area. Second, participants hold conflicted understandings of climate change that alternate between the adoption of climate skepticism and acceptance of scientific consensus regarding anthropogenic climate change. Finally, this study demonstrates the importance of engaging in conversations with oil workers to facilitate a pluralistic narrative and navigate multiple worldviews to create understanding of a controversial topic in Saskatchewan.

Doing What ‘Works Best’: Exploring the Narratives of Mothers Who Work as Strippers - Annett, Michelle Lesley (Brock University, 2019)
Despite a large body of research exploring the experiences of working mothers today, there is little literature focusing on mothers who take part in stigmatized and unconventional forms of paid labour. Taking up this line of inquiry, my MA thesis project explores both micro and macro-level understandings of the narrated experiences of four women in Canada, who are both mothers and exotic dancers, with the overarching question: ‘how do these women navigate and negotiate their socially constructed identities and practices as both mothers and sex workers?’. This thesis is informed by feminist methodologies and a broad array of literatures on social reproduction, social surveillance of mothering practices, the intensification of mothering, women working in the sex industry, and occupational stigma of exotic dancing. My research consisted of four semi-structured phone interviews with women in Canada (all in the province of Ontario) who have (either currently or in the past) navigated both roles of mothering and stripping simultaneously. Through my interviews, I explored how the women in my study negotiated the work of social reproduction, the forms of support they had access to, and the barriers they have faced. My findings illuminate that due to limited access to affordable services in Canada, the mothers I interviewed rely on informal assistance from their key supports to provide necessary care work that the mothers could not fulfill due to the responsibilities of their paid work. Mothers also stress the necessity of managing their occupational stigma to comply with dominant ideologies of maternal caregiving by constructing personal communities and adopting techniques of secrecy and trust in order to enhance their ability to combine paid work and unpaid care. Overall my MA thesis offers insight into experiences, supports, and constraints that women face as they navigate the demands of paid labour, domestic work and unpaid caregiving in stigmatized and precarious conditions.

Arrival of the Fittest: German POWs in Ontario during the Second World War - Bailey, Jordyn (Western University, 2019)
Over 35,000,000 soldiers, sailors and aviators, statistically one in three combatants, were taken prisoner during the Second World War. Some 35,000 of these prisoners were members of the German army, navy and air force, imprisoned in twenty-five internment compounds and 300 small, isolated labour camps across Canada. Once on Canadian soil, German POWs were treated with remarkable hospitality in lieu of their status as the “Nazi” enemy. Canada’s excellent treatment of German POWs was a product of many things: a desire to adhere to the Geneva Convention; concern for the well-being of Canadian and other Allied POWs in German hands; and the discovery that German POWs often made valuable workers, for which there was a great need during the war. It was also a product of racism, expressed in numerous actions, suggesting a willingness to perceive German POWs as potential members of society - a willingness not extended to German-Jewish civilian internees or even to Japanese-Canadians who were already citizens.

Like a Virgil: Georgic Ontologies of Agrarian Work in Canadian Literature - Baker, Jennifer (University of Ottawa, 2019)
In this dissertation, I argue that two dominant perspectives on farming in Canada—the technoscientific capitalist perspective on modern industrial farming and the popular vision of hard-won survival on the family farm—both draw on narrative and aesthetic strategies that have deep roots in distinct, but related variations of the georgic tradition, which arrived in Canada in the eighteenth century and continues to shape literary representations and material practices today. Critics of Canadian literature have tended to subsume the georgic under the category of pastoral, but I argue that the georgic is a separate and more useful category for understanding the complex myths and realities of agricultural production in Canada precisely because it is a literary genre that focuses on the labour of farming and because it constitutes a complex and multi-generic discourse which both promotes and enables critique of dominant agricultural practices. I argue that, despite its sublimation beneath the pastoral, the georgic mode has also been an important cultural nexus in Canadian literature and culture, and that it constitutes a set of conventions that have become so commonplace in writing that deals with agricultural labour and its related issues in Canada that they have come to seem both inevitable and natural within the Canadian cultural tradition, even if they have not been explicitly named as georgic. By analyzing a variety of texts such as Oliver Goldmith’s The Rising Village, Isabella Valancy Crawford’s Malcolm’s Katie, Susanna Moodie’s Roughing It in the Bush, Frederick Philip Grove’s Settlers of the Marsh, Martha Ostenso’s Wild Geese, Al Purdy’s In Search of Owen Roblin, Robert Kroetsch’s “The Ledger,” Christian Bok’s Xenotext, Rita Wong’s Forage, and Phil Hall’s Amanuensis, I recontextualize Canadian writing that deals with agrarian work within two distinct but related georgic traditions. As Raymond Williams and others have shown, the georgic’s inclusion of both pastoralizing myths and material realities makes it useful for exploring ecological questions. The georgic is often understood in terms of what Karen O’Brien has called the imperial georgic mode, which involves a technocratic, imperialist, capitalist approach to agriculture, and which helped theorize and justify imperial expansion and the technological domination of nature. But as ecocritics like David Fairer, Margaret Ronda, and Kevin Goodman have argued, the georgic’s concern with the contingency and precariousness of human relationships with nonhuman systems also made it a productive site for imagining alternatives to imperial ways of organizing social and ecological relations. Ronda calls this more ecologically-focused and adaptable georgic the disenchanted georgic, but I call it the precarious georgic because of the way it enables engagement with what Anna Tsing calls precarity. Precarity, as Tsing explains, describes life without the promise of mastery or stability, which is a condition that leaves us in a state of being radically dependent on other beings for survival. “The challenge for thinking with precarity,” she writes, “is to understand the ways projects for making scalability have transformed landscape and society, while seeing also where scalability fails—and where nonscalable ecological and economic relations erupt” (42). By tracing the interplay between imperial and precarious georgic modes in Canadian texts that have mistakenly been read as pastoral—from Moodie’s settler georgic to the queer gothic georgic of Ostenso’s Wild Geese to the provisional and object-oriented georgics of Robert Kroetsch and Phil Hall—I argue that the precarious georgic strain has always engaged in this process of thinking with precarity, and that it holds the potential for providing space to re-imagine our ecological relations.

'To Waffle to the Left:' The Waffle, the New Democratic Party, and Canada's New Left during the Long Sixties - Blocker, David (Western University, 2019)
The Sixties were time of conflict and change in Canada and beyond. Radical social movements and countercultures challenged the conservatism of the preceding decade, rejected traditional forms of politics, and demanded an alternative based on the principles of social justice, individual freedom and an end to oppression on all fronts. Yet in Canada a unique political movement emerged which embraced these principles but proposed that New Left social movements – the student and anti-war movements, the women’s liberation movement and Canadian nationalists – could bring about radical political change not only through street protests and sit-ins, but also through participation in electoral politics. The Waffle movement, which formed around the “Manifesto for an Independent and Socialist Canada” and challenged the leadership of the New Democratic Party (NDP) from 1969 to 1973, represents a dynamic convergence of many of the social movements that comprised the New Left in Canada. The Waffle argued that the NDP should promote socialist measures to combat American economic domination and ensure Canadian independence while simultaneously engaging with extra-parliamentary struggles. NDP and trade-union leaders, reluctant to adopt such a radical approach, expelled the Waffle from the Ontario NDP in 1972. Despite its short life-span, the Waffle had a considerable influence on Canadian politics and the issues that it raised – Canadian economic dependency, Quebec’s right to self-determination, women’s equality, and the decline of the manufacturing sector, among others – continue to resonate to this day. Furthermore, the Waffle’s impact on Canadian nationalism and its legacy in the NDP, labour and women’s movements, radical left and academia remain contested. The Waffle’s successes and failures represent a potentially revealing perspective on Canadian politics and society during a period of rapid social change, the Sixties. While the existing historiography has sketched the outlines of the Waffle’s history, the focus overall has been limited to analyses of internal leadership disputes and the experience of the Ontario Waffle in particular. Abundant research materials now exist to support a wider and more intensive examination. Through an analysis of the Waffle, focusing on grassroots activists as well as the movement’s leadership, this dissertation demonstrates important connections between the Waffle and other New Left social movements. This interconnectivity is particularly significant, as it indicates that the Waffle occupied a unique place in the international New Left, specifically a convergence of social movements which sought to engage with electoral politics through an existing political party, the NDP. The dissertation also revises the movement/party dichotomy which has dominated much of the Waffle/NDP historiography. Finally, my study of the Waffle, a group active from 1969-75, indicates the flaws of applying a declension narrative to the Canadian Sixties, instead demonstrating the value of a “long Sixties” approach. As the clock ticked down on the 1960s, the Canadian New Left neither died nor retreated into cynicism nor lashed out in violence. Instead, its diverse elements, led by the Waffle, nurtured the wild dream of redirecting and leading to triumph an established political party.

Transnational Migration and Social Reproduction: Filipino Hotel Workers in Rural Manitoba - Bryan, Catherine (Dalhousie University, 2019)
At the intersection of three highways, the Douglas Hotel, in Manitoba’s central-west, is a place to stop for a coffee, a meal, or a night’s accommodation. Like elsewhere on the Canadian prairies, the daily labour required of these services falls largely to a migrant workforce. Bringing together historic political economy with feminist political economy, I draw on the presence of this workforce, comprised of 71 Filipino service and hospitality workers, in Douglas as an entry point into an extended exploration of the workings of social reproduction under globalized capitalism historically and at the beginning of the 21st Century. Sensitive to the transnationality that characterizes the lives of these workers, this multi-sited ethnographic study reads the details of everyday life in Manitoba and the Philippines through the historic and present-day political economy of each site. Offering this parallel yet integrated account, I highlight the variability of migrant experience in Canada at the sub-national level, as well as the ways in which receiving-states and private enterprise collaborate in the creation of labour markets. Low-wage and low–status, the labour market in question demands a kind of corporate, commodified care work that ensures the bodily reproduction of the Hotel’s guests and the material reproduction of the Hotel itself. Following from the objectives of their migration, the labour these workers perform at the Hotel also supports the survival and well-being of family in the Philippines. However, in addition to ensuring the material reproduction of non-migrant kin, through their use of digital communication technology and social media, these migrants contribute to the reproduction of migrant subjectivities, and subsequently, respond to the needs of global capital and the Philippine state. Thus, identifying the various, scaled forms of social reproduction in which the Hotel’s migrant workers participate, this thesis offers a multi-faceted, transnational account of reproduction, incorporating migrants, their families, their employer, and multiple state players. While not reproductive as conventionally defined, their labour at the Hotel provides insight into the patterning and re-patterning of social reproduction, and its associated labour, under global capital. Moreover, it demonstrates the centrality of those processes to operations of capitalism.
Accepted: 2019-11-28T16:51:31Z

“Mr. Big Wood or Sawdust?”: Joseph R. Smallwood and the 1959 IWA Strike in Central Newfoundland - Campbell, Dana (Dalhousie University, 2019)
Joseph R. Smallwood was, for lack of a better term, a Newfoundlander for Newfoundland. Or so, that is how he portrayed himself. Under the first ten years of Confederation, Smallwood pushed a program of rapid industrialization. This program was largely unsuccessful. So, when the IWA [International Woodworkers of America] declared a strike on the Anglo-Newfoundland Development Company in January 1959, which posed a significant threat to the province’s most prosperous industry (pulp and paper), Smallwood leapt into action. Rather than support the loggers’ elected union, he banned the IWA in favour of a provincial union that was to be run by Max Lane, President of the Fishermen’s Federation. Utilizing key documents from the Smallwood Collections at Archives and Special Collections, Queen Elizabeth II Library, Memorial University, this thesis examines the factors that led up to this decision, its outcome and ultimately, and why Smallwood chose to do what he did.
Accepted: 2019-08-27T13:49:18Z

The Rise and Decline of the Cooperative Commonwealth Federation in Ontario and Quebec during World War II, 1939-1945 - Deshaies, Charles A. (University of Maine, 2019)
The Cooperative Commonwealth Federation (CCF) was one of the most influential political parties in Canadian History. Without doubt, from a social welfare perspective, the CCF helped Canada build and develop an extensive social welfare system across Canada. The CCF’s major contributions to Canadian social welfare policy during the critical years following the Great Depression has been justly credited to the party. This was especially true during the Second World War when the federal Liberal government of Mackenzie King adroitly borrowed CCF policy planks to remove the harsh edges of capitalism and put Canada on the path to a modern welfare state. Despite the party’s success in shifting the role of the state in society, electoral triumphs proved more difficult for the CCF to obtain. On the federal level, there has been a great deal of discussion about the third-party status of the CCF. One of the objectives of this paper is to indicate that such a role was not pre-ordained for Canada’s democratic socialist group. From 1942 to 1944, it appeared that the CCF was a significant electoral threat to the monopoly of the Conservative and Liberal parties. Ultimately, the party fell short of ending the dominance of the traditional governing bodies. The failure of the CCF to break through with the Canadian voting public is often blamed on the underwhelming performance of the party in the two most populous provinces: Ontario and Quebec. This work explores the efforts put forth by the party to expand the CCF beyond its Western base of support and shows how both provinces were inhospitable to the CCF prior to World War II. In addition, evidence is presented that clearly demonstrates that the CCF in Ontario and Quebec often hindered its own efforts to grow the movement. Horrid organization, non-existent leadership, and serious divisions within the party all helped to contribute to the anemic state of the CCF in Canada’s two largest provinces. These problems were compounded by thinly-veiled racism towards members of the French-Canadian community in Quebec. However, by 1942, the Ontario CCF addressed these issues and became a force to be reckoned with in the province. Attempts were made to incorporate this model into the Quebec branch of the party. The Quebec CCF made some in-roads in expanding their small base on the Island of Montreal. Despite these advances, the party failed to break through in the predominately French-speaking province. The 1945 Ontario and federal elections stemmed the tide of CCF momentum. From that point, the party was relegated to a permanent third-party status at the federal level. In Ontario, the party maintained a substantial degree of public support and would play a role in maintaining the three-party political system in that province. The Quebec CCF could make no such boast. The party’s weak support ensured they would remain on the fringes of Quebec politics during the remainder of the party’s days. While numerous factors are often credited with dooming the CCF in Quebec (opposition from the Roman Catholic Church, the centralizing nature of CCF policy, and media disdain), the available evidence indicates the party failed to address persistent concerns over leadership and organization.

The Transnational Making of Ontario Tobacco Labour, 1925-1990 - Dunsworth, Edward Ira (University of Toronto, 2019)
This dissertation explores the transformations in tobacco farm labour in Ontario from approximately 1925 to 1990, advancing a significant reinterpretation of the histories of agricultural labour and guestworker programs in Canada. Contrary to portrayals of Canadian agriculture as permanently plagued by labour shortage, this case study demonstrates the heterogeneity of the sector, which included not only labour-starved growers but also farmers like those in tobacco whose high profits enabled them to attract a diverse range of harvest workers each year. Indeed, for much of the 20th century, Ontario’s tobacco sector, located primarily in Norfolk County and the surrounding areas, was the premier destination for seasonal farmworkers in Canada. In the sector’s early decades, tobacco workers enjoyed significant freedom of movement, unusual opportunities for social mobility, and a vibrant culture of worker organization and resistance. However, the opportunities in Ontario tobacco were never equally available to all prospective workers, and incorporation into the sector was always marked by patterns of inclusion and exclusion. For those workers who could gain access to the tobacco labour market, the benefits of working in tobacco steadily declined over the 20th century. By the 1980s, the sector no longer offered opportunities for social mobility and the possibilities of worker organization were greatly constrained. Guestworkers from the Caribbean and Mexico found their labour and geographic mobility much more tightly restricted than any previous or contemporary groups of tobacco workers. These transformations were complex and the result of many contingent factors (in both Canada and migrant-sending countries), including: political economic trends; ideologies of race and gender; the actions of employers, local communities, and workers themselves; and the efforts of multiple levels of the state to exert greater control over tobacco farm labour. The thesis pays particular attention to the transnational dynamics of labour migration systems, guestworker program structures, and worker resistance. By historicizing farm labour in a single crop and single region over approximately seven decades, the dissertation demonstrates that farm labour is not by definition a station of poverty and extreme exploitation, but instead is made so by historical processes.
https://cha-shc.ca/prize-winner/edward-dunsworth/

Re-Assessing Caregiver Migration Programs and Policies in Canada - Eldeib, Isabella (Toronto Metropolitan University, 2019)
Caregiver migration programs and policies in Canada have undergone numerous changes since the implementation of the Live-in Caregiver Program (LCP) in 1992. Although changes made by the Canadian government between 1992 and 2020 claimed to “support” migrant caregivers, many caregivers continue to face precarious conditions. The purpose of this Major Research Paper is to argue that caregiver migration programs and policies need to be reassessed and challenged as they continue to embody problematic labour practices that render migrant caregivers vulnerable. Broadly, this research brings literature on racism, sexism and colonialism into one conversation in order to better understand the root causes of inequality faced by migrant caregivers in Canada. The significance of this work lies in its provision of a contemporary understanding of caregiver migration, especially in light of a global pandemic, in order to advocate for policy amendments that will genuinely support migrant caregivers and lead to the elimination of exploitative care labour practices.

Precarious Work, Gender Roles, and the Use of Work-Life Balance Programs in Academia - Enoh, Eno Ibok Jackson (University of Lethbridge, Dhillon School of Business, 2019)
This thesis examined the experiences of contract academic staff (CAS) regarding their use of work-life balance programs (WLBPs). As precarious employees, CAS are subject to work conditions that put them in a bind between surviving as precarious workers and meeting the demands of their work and family lives. As such, a clearer picture of how such highly-skilled professionals utilize WLBPs to achieve WLB is required. Adopting the phenomenology qualitative research approach, I used NVivo to analyze the data obtained from in-depth, semi-structured interviews conducted with ten research participants. Four themes emerged: precarious work, support and performance, gendered aspects of academia, and precarious workers’ use of WLBPs. Results showed that male and female CAS adopted similar WLBPs as boundary management strategies to integrate and/or separate their work and family obligations. The limitations and implications of the research for theory and practice were discussed and recommendations were made for future research.
Accepted: 2020-02-21T18:45:59Z

“Farmworkers Zindabad!”: Community Unionism and the Canadian Farmworkers’ Union, 1978-1986 - Fast, Nicholas (Simon Fraser University, 2019)
At a meeting of the Farmworkers’ Organizing Committee (FWOC) on 6 April 1980, the FWOC officially became the Canadian Farmworkers’ Union (CFU) with the goal of providing better legal protection, immigration services, and overall improved safety standards for South Asian farm workers in the Lower Mainland. The CFU was unable to reach financial autonomy on their own and with a perpetual shortage of dues and heavy reliance on outside support, the CFU affiliated with the larger Canadian Labour Congress (CLC) in 1981. The CFU’s community unionism was unique and suited for their members’ needs but complicated their relationship with the CLC’s vision of a labour movement dominated by business unionism. This thesis demonstrates the CFU’s importance to Canadian labour historiography and provides valuable lessons for those who want to organize in an increasingly neo-liberal dominant society.

Working on Keeping it Together: Exploring the Lived Experience of Precarious Employment in Rural Ontario - Gaspard, Valencia (University of Guelph, 2019)
Precarious employment is often experienced as contract work, involuntary part-time work, low wage work, and self-employment. There is a well-developed body of literature pointing to negative health, economic, and social impacts related to precarious employment in urban centres, while little consideration has been given to the particularities that may make a rural precarious employment experience different. The goal of this exploratory research project is to understand the experience of being precariously employed in rural Ontario. Nineteen unstructured individual interviews with rural Ontarians experiencing rural precarious employment were conducted. The phenomenon of rural precarious employment was distinguished by five themes (financial, health, self-view, social, and system) emergent through phenomenology. The phenomenon encompassed experiences of poverty, decreased health, negative self-views, social struggles, and marginalization from support public systems. Unpacking precarious employment in rural Ontario from the experience of workers has significance for both rural scholars and policy makers. Rural scholars benefit from a better understanding of precarious employment as an experience in rural areas, and the addition of lived rural experiences to the precarious employment literature advances the understanding of urban bias in scholarship. This research provides provincial policy makers the opportunity to craft rural focused employment policy and better understand how services can support rural precarious employees.

That '70s Strike Support: Labour, Feminism, and the Left in Three Ontario Strikes, 1972-1979 - Godden, Mason (Trent University, 2019)
This thesis examines three Ontario strikes during the 1970s: the Dare Foods, Ltd. strike in Kitchener, Ontario, 1972-1973; the Puretex Knitting Company strike in Toronto, 1978-1979; and the Inco strike in Sudbury, 1978-1979. These strikes highlight gender issues in the Canadian food production, textile, and mining industries in the 1970s, industries that were all markedly different in size and purpose, yet equally oppressive towards working women for different reasons, largely based on the regional character of each city the strikes took place in. In Kitchener, the women's movement worked closely with the Dare union local and the left to mobilize against the company and grappled with the difficulties of framing women's inequality within the labour movement. At Puretex, immigrant women workers were subject to electronic surveillance as a form of worker control, and a left-wing nationalist union needed to look outside of the Canadian Labour Congress (CLC) for allies in strike action. At Inco, an autonomous women's group formed separate from the United Steelworkers of America (USWA) but struggled to overcome a negative perception of women's labour activism in Sudbury. Ultimately, these strikes garnered a wide variety of support from working women and feminist groups, who often built or had pre-existing relationships with Canadian and American trade unions as well as the left-wing milieu of the 1970s. This thesis uses these strikes as case studies to argue that despite the complicated and at times uneven relationship between feminism, labour, and the left in the 1970s, feminist and left-wing strike support was crucial in sustaining rank-and-file militancy throughout the decade and stimulating activist careers for women in the feminist movement, in unions, and on the left.

“When Blue Is Green”: Towards a History of Workers as Environmentalists in British Columbia and Beyond - Harter, John (Simon Fraser University, 2019)
This dissertation examines the history of working-class environmentalism. It investigates the relationship between work and the environment and between workers and environmentalists. It presents five case studies that focus on the relationship between workers and the environment in British Columbia from the 1930s to the present, with particular emphasis on the forestry industry. Each case study examines how the interests of workers both intersect and conflict with the interests of environmentalists and how this intersection of interests presented itself throughout the twentieth and twenty-first centuries. Additionally, this dissertation examines how the working class has historically been constructed as the adversary of nature or wilderness and aims to explore how the working class, resource workers in particular, have come to symbolize that adversarial relationship. As well, it hopes to answer more epistemological questions about why working class environmentalism has not entered our lexicon and how lacking a sense of the working-class environmentalist serves to shape a discourse in which the history of worker environmentalism has been largely passed over. This study also explores how the collective memory of environmentalism has been constructed to exclude notions of class, and thus how environmentalism and the working class have been constructed as mutually exclusive categories. While this dissertation explores the exclusion of working class environmentalism it also attempts to write the worker-environmentalist back into history and show how teaching working class and labour history can help remedy this exclusion.

Proletarian Publics: Leftist and Labour Print in Canada, 1930-1939 - Hasenbank, Andrea Grace (University of Alberta, 2019)
his thesis examines a selection of print materials from the radical and Communist-affiliated Left in the 1930s, a group and time period that are often passed over in assessments of Canadian literature. While similar texts have been studied in the context of legal evidence or political propaganda, they have rarely been considered as print objects in themselves, operating within a network of production, circulation, and response alongside other literary and non-literary media. In looking at the 1930s, a moment when the project of Canada was acutely challenged by the political and economic forces of the Great Depression, I see an equal challenge to scholars and critics by writers and readers struggling to organize from below. By considering examples of Canadian proletarian print from different points along the communication cycle, this project seeks to connect the imaginary aspirations and rhetorical strategies of these texts to the material contexts of their producers and readers. Chapter One addresses the existing gap in Canadian literary history, which maintains a liberal orientation throughout its associated institutions, approaches and subjects; this orientation has been upheld through political and legal structures hostile to proletarian movements. This chapter discusses Ronald Liversedge’s Recollections of the On-to-Ottawa Trek as a text that highlights and crosses such institutional boundaries. Chapter Two takes up the methods of book history, using the example of the “Worker’s Pamphlet Series” to discuss expanding this approach to include material such as pamphlets, periodicals, and manifestos as part of an explicit class analysis. Chapter Three analyzes the self-reflexive circulation of proletarian print in the restrictive legal environment created by Section 98 of the Criminal Code through materials produced by the Canadian Labour Defense League. Chapter Four examines surveillant readings and misreadings as they intercept proletarian print, using the Edmonton Hunger March and the subsequent pamphlet “The Alberta Hunger-March.” By mapping locations associated with this event and with the print economy in 1932 Edmonton, Chapter Five considers the formation of proletarian publics as highly localized interpretive communities, and how the application of tools such as GIS mapping might further re-center readers’ material lives in the analysis of print culture. As a whole, this dissertation demonstrates how the methods of analysis and historicization offered by book history can and should be applied to bring proletarian print and readers into conversation with the wider patterns of Canadian writing through the twentieth century. This is a necessary confrontation: as the study of Canadian literature begins to acknowledge the construction and contestation of our national myths, it must also avow the lasting political consequences for those who have been excluded.

Design in Motion: The Everyday Object and the Global Division of Design Labour - Hodson, Elise (York University, 2019)
The practice of design has become obscured by global networks of production, circulation, and consumption. Traditional design studies tend to focus on high-profile products, presenting heroic designers as the primary authors of works of design. This approach is inadequate for understanding design in the late-twentieth and early twenty-first centuries. Contemporary design is better understood as an iterative and distributed process of give-and-take among actors, human and non-human, including people, tools, places, and ideas. It is a process that is influenced by conditions along the commodity chain that fall outside of the designers traditionally recognized sphere. This research demonstrates that commonly held conceptions of designers as sole authors and of design work as a largely intellectual, creative activity distanced from manufacturing, misrepresent the real practices and relations of design labour in the current global economy. Two object ethnographies follow the production, circulation, and consumption of everyday, mass-produced goods: the Vanessa steel-toe boot by Mellow Walk and the Non Stop flatware by Gourmet Settings. These case studies map networks of design labour across continents, countries, cities, and generations. Primary research includes 18 interviews, observations of environments and practices, and the analysis of material evidence. This process reveals actors whose contributions have typically been omitted from design history, and describes practices of design that contest traditional depictions of designers, design work, and evidence thereof. This research contributes a fuller and more accurate understanding of the range of creative labour and labourers involved in the design and development of goods for global markets while challenging the view of these goods as placeless and culture-free. I respond to the call by design historians to extend the scope of designs histories beyond the West, and I build on the work of design and creativity scholars who identify design thinking outside of recognized design roles. My work challenges established hierarchies of design, including who is permitted to design, which countries are perceived as superior sources of design and manufacturing expertise, and the hand-head dichotomy that underwrites how we think about design and that has been entrenched in traditional conceptions of manufacturing and the global division of labour. Understanding how the work of design is distributed and how it has changed in response to globalization gives insight into the politics of production and consumption.

The Making and Reproduction of Male Working-Class Identity in a Mining Town - King, Adam D.K. (York University, 2019)
This dissertation is a study of working-class identity and subjectivity among a sample of male nickel miners in Sudbury, Ontario. Recent foreign takeovers of mining firms and a protracted strike at Vale-Inco in 2009-2010 motivate this dissertation's new look at class relations and subjectivity in one of Canadas most historically significant regions of working-class organization. This study understands these recent events as part of a set of decades long economic processes that have transformed workers lives in and outside work. It explores how the form that trade unionism took in the post-WWII period has shaped class relations and class identity among male nickel miners in Sudbury. The dissertation asks: how have class subjectivity and socioeconomic change interacted over this history? After first analyzing the political economy of mining in the Sudbury Basin, the dissertation traces the formation of historically situated class subjectivities. In it, I examine how the postwar compromise between capital and labour influenced unionization and class identity among male workers at the mines. I then inquire into how industrial restructuring and job loss, the rise of new managerial strategies and neoliberal governance, and the growth of precarious, contract labour have transformed both the material contexts of workers lives and their practices of reproducing their identities as members of a working class. To form the central arguments of the dissertation, I draw on 26 oral history interviews with current and retired workers, and organize their narratives into three thematic areas of class identity: first, issues of work and the labour process; second, themes of place, space, and belonging in the formation of class identities; and third, how historical memory and generational conflict influence class. Within and across these thematic areas I show how material conditions and workers own practices of identity formation interact, adjust, and at times, contradict. I argue that the postwar class compromise between labour and capital contributed to a resilient form of working-class subjectivity among workers that is reproduced by local processes of social remembering and class reproduction. Yet, industrial restructuring, the growth of precarious employment, and the internationalization of ownership and management at the mines challenge the efficacy of this historical subjectivity. By studying unionized workers who are confronting profound industrial change, this dissertation raises questions about how the making of male working-class identity limited broader processes of class formation, as well as how we understand class and class formation in the global economy at a time when labour movements face growing structural challenges.

Teacher Unions in the Public Sphere: Strategies Intended to Influence Public Opinion - Maharaj, Sachin (University of Toronto, Ontario Institute for Studies in Education, 2019)
This study explores how teacher unions in British Columbia and Ontario attempted to influence public opinion during periods of labour conflict between 2001 and 2016. A comparative case analysis was conducted based on eight interviews with members of the British Columbia Teachers Federation, six interviews with members of the Elementary Teachers’ Federation of Ontario, as well as documents from each union. In addition, newspaper items published in each province during the conflict period were collected. The unions’ efforts were analyzed through the framework of Habermas’ concepts of the public sphere and validity claims. Findings indicate that both unions had active public relations strategies designed to influence media coverage and discourse in the public sphere. However, most of their efforts were focused on influencing the public sphere indirectly, by using tactics that are not traditionally considered part of public relations strategies. While the unions’ efforts were similar in nature, the impact that these efforts had on influencing public opinion and producing policy change varied substantially. I argue that a combination of historical and political differences, mediated through a validity claims framework, helps explain this variation.
Accepted: 2019-11-14T15:00:17Z

The Labour Feminism Takes: Tracing Intersectional Politics in 1980s Canadian Feminist Periodicals - McKenna, Emma (McMaster University, 2019)
This dissertation turns to recent feminist history of the 1980s to consider feminism’s relationship to class, economics, and labour. Challenging the idea that feminism is an inclusive project, I look at how feminist ideology produces commonsense forms of racism, classism, and sexual normativity. To demonstrate this argument, I evaluate two important moments in 1980s Canadian feminism: the development of feminist political economy and the debates of the feminist sex wars. In tracing the ways in which these histories unfold to value some feminist subjects more than others, I show how feminist narratives appear cohesive through quotidian practices of exclusion. I claim that the resistance of marginalized subjects is integral to these narratives, particularly when this resistance has been made to appear invisible or absent. I first turn to feminist political economy to show how a white feminist discourse about gendered domestic labour emerged while simultaneously omitting analyses of the experiences of women of colour and migrant domestic labourers. This white feminist discourse is imbued with commonsense racism, and imagines migrant domestic workers as located elsewhere to feminism. Subsequently, I examine how the feminist sex wars pursued a line of inquiry into sexuality that privileged a framework of danger. Feminist theorizing of violence against women as intrinsic to prostitution and pornography had dire consequences for understanding sex work and the diverse women employed in the industry. In promoting a white, middle-class perspective on sexuality, feminists appropriated sex workers’ experiences of violence and sought state support for abolishing commercial sexuality, in turn contributing to the heightened state surveillance of sexual minorities. In looking to and for marginalized women’s experiences within an archive of women’s publishing, this project insists on the integral place of sex workers and migrant domestic workers within Canadian feminist labour histories.

Precarious Work, "Harmonizing down" and Economic Anxiety: Implications for Citizenship and Society - McKnight, Zoe Amanda (Carleton University, 2019)
This paper examines precarious work, its historical origins and certain social consequences. I use the 2015 Canadian Election Study to analyze the relationship between work-related insecurity and economic anxiety with voting, non-voting political behaviour and attitudes toward equity-seeking groups. I propose a theory of "harmonizing down", in which workers who were once able to access the benefits and status of the standard employment relationship have generally seen their opportunities for stable and secure work decline. This has resulted in economic anxiety for most workers. Results were mixed, suggesting that broad generalizations around economic anxiety are problematic. Insecurity and anxiety may reduce the likelihood of voting but may increase non-voting participation. Some aspects of insecurity and anxiety were related to negative attitudes toward equity-seeking groups, but the relationship is not clear. Gender and political party identity influence these attitudes.

Books and Broomsticks: Prairie Indigenous Female Domestic Workers and the Canadian Outing System, 1888-1901 - Nason, Sarah Faye (University of Calgary, 2019)
This thesis discusses the Canadian outing system, a direct feature of industrial schools in the prairie west prominent in the late nineteenth century. Seen as an extension of the school’s vocational training, the outing system became an outlet with which the Canadian federal government’s Department of Indian Affairs (DIA) could integrate into the lower ranks of Euro-Canadian society young Indigenous girls in a hierarchical system of labour. By examining the roles and education of Indigenous female youth in the industrial school system in the Canadian prairies, this study illuminates how, in the name of assimilation, the DIA implemented the outing system. This thesis highlights how young Indigenous women were compelled to work in homes that exemplified settler values, taking on strenuous labour in environments where attitudes of race and class dimensions were prominent. By drawing from 1901 census data and looking at the settler homes, farms, and establishments in which they worked, this thesis provides an important glimpse into the early history of domestic work for Indigenous women and girls in western Canada and offers insights into the very nature of settler colonialism in early Canadian national history.

The Customer is Always Right: Violence Against LGBTQ2S+ Service Workers in Windsor and Sudbury, Ontario - Owens, Benjamin (McMaster University, 2019)
Previous research has indicated the prevalence of customer violence towards workers in the service sector, but few studies have looked at the impacts of this violence for LGBTQ2S+ workers. Drawing from survey results (n=208) and interviews (n=11) with LGBTQ2S+ service sector workers in Windsor and Sudbury, Ontario, this thesis explores the rates and experiences of customer violence for these workers, using chi-square analyses to identify relationships between customer violence and independent variables related to workers’ identity and workplace. Further analysis was conducted on qualitative interview data to understand how this violence was experienced, as well as how workers resisted and perceived management’s response. Customer violence was found to be widespread among survey and interview participants, with participants who were racialized as non-white, union members, and in precarious work situations reporting higher levels of violence. Interviews also showed how participants often resisted customer violence through individual means, and perceived support from management to be lacking and contingent upon economic motivations.

"No Somos Maquinas" (We Aren't Machines): Emotional Dimensions of Precarious Labour in the Seasonal Agricultural Worker Program - Pennell, Elena (Simon Fraser University, 2019)
This study concerns the social and emotional dimensions of Mexican migrant workers’ temporary labour migration experience as they relate to precarity and unfreedom within the Seasonal Agricultural Worker Program (SAWP). My principle inquiry centers around understanding migrant workers’ subjective and emotional experiences of being away from home and family. This study makes the case that migration and family separation, as requirements of SAWP employment, are precarious labour conditions that result overwhelmingly in distressing emotional experiences that go unseen in workers’ daily lives. I draw on a deeply qualitative methodological approach and theories of precarity, emotion and practice to explore the ways that SAWP workers navigate their labour migration experience through a series of practices in their daily lives. I conclude by sharing my participants’ recommendations for a more dignified and humanized labour experience and with their insistence that they are not maquinas (machines).

Working with an Accent: The Aesthetic Labour of International Teaching Assistants in Ontario Universities - Ramjattan, Vijay Anil (University of Toronto, Ontario Institute for Studies in Education, 2019)
International teaching assistants (ITAs) in North American English-medium universities often work with an accent. In one sense, to work with an accent entails doing one’s work while having an aural stigma. This is due to the increased likelihood that students and other university stakeholders perceive ITAs’ foreign-accented English as difficult to understand. The purported problem of their foreign accents can thus create additional facets in working with an accent such as working with the idea of how to change an accent and performing (around) it in order to be viewed as effective workers. All of this work can be considered a type of aesthetic labour in that ITAs need to develop the right sound for their professional duties. Based on a narrative inquiry of the experiences of 14 ITAs working in various universities in Ontario, Canada, this thesis explores how they conceptualize and execute aesthetic labour. Specifically, it details their perceptions of a satisfactory aural aesthetic for work as well as the extent to which they incorporate this aesthetic in discussions about their professional practices. Regarding the first research objective, the ITAs understood a satisfactory accent in linguistic, racial, and professional terms. Indeed, an accent could sound “native” or “nonnative,” become “whitened” or remain racialized, and match or not match one’s work (environment). In terms of taking up these perceptions in their professional practices, which took the general form of working on or around an accent, the ITAs’ prior views on aural aesthetics were upheld and/or tempered by contextual factors in their universities. On the immediate level, the above findings provide suggestions for changes to existing forms of ITA training, which tend to ignore the knowledge of ITAs and fail to prepare them to effectively communicate according to the specificities of their work environments. More broadly, the findings are useful in highlighting how accents are not stable individual traits, but rather, malleable tools that help workers negotiate intercultural encounters in a range of professional settings. Therefore, this study counters research that frames the ITA accent as an inherent problem needing to be rectified for a homogeneous audience.
Accepted: 2019-11-14T18:00:37Z

Deportability, Labour and Health in Canada’s Late Capitalism - Rivas-Sánchez, Hector Eloy (Carleton University, 2019)
This dissertation explores the political economy of the physical and mental illnesses that the migrant workers experience while living and working under conditions of illegality in Canada's late capitalism. The dissertation is divided into three parts. The first part locates four social determinants of health underpinning the structural vulnerability to which the Latin American undocumented workers are subjected in this particular context. The second part describes the mental and physical health illnesses that the undocumented workers develop while living and working in Canada without authorization, according to the type of industry they work in (1.—Multinational Corporations, 2.—Medium-size local industries and 3.—Underground workers' cooperatives) and to the type of work they do. The empirical evidence illustrates that the undocumented immigrants who work for medium-size local enterprises, those who have been affected by deportability and deportation, as well as those who lost their legal status after being engaged in refugee claimant applications, are more likely to develop the most dramatic forms of physical and mental health diseases, all linked to what is called here "short- term historical trauma." In contrast, undocumented workers who work for underground workers' cooperatives are more likely to report better physical and mental health outcomes. Cooperative labour, free time and social solidarity make this possible. Overall, this thesis indicates that –as explored in part three– under the social conditions organized by late capitalism, social solidarity and engagement in non-waged cooperative labour constitute social mechanisms by which undocumented migrants can access to forms of refuge, care, solidarity and social recognition that partially emancipate them from illnesses, suffering and social death. This thesis is based on an ethnographic work that I carried out over 24 months in Montreal. During that period of time, I worked side by side with Latin American undocumented workers in slaughterhouses and meatpacking factories, construction and home renovation companies, employment agencies, and as industrial cleaner for multinational corporations, spaces where I carried out direct empirical observation in the points of production and conducted 47 in-depth interviews on illegality, labor and health. I also conducted ethnographic work in hospitals and deportation centers.

Activism, Popular Education and Knowledge Production Against Temporary Employment Agency Exploitation of Im/Migrant Workers in Montreal - Salamanca Cardona, Manuel (McGill University, 2019)
This thesis examines two intimately related topics. First, it analyzes the practices of temporary employment agencies and employers in using the vulnerabilities of migrant and immigrant workers across different precarious labour sectors in Montreal. Second, it aims to understand the knowledge production, learning and non-formal education linked to action that occur in the course of organizing im/migrant agency workers by the Immigrant Workers Centre (IWC) and the Temporary Agency Workers Association (TAWA). The discussion of agencies is located in a broader context of the global and Canadian neoliberal model which includes attending to racism and racialization, flexible labour and labour deregulation, labour precarity, the defensive position of trade unions, austerity and immigration policies. The study uses longitudinal research and interviews with 42 im/migrant agency workers in precarious jobs, as well as interviews with IWC and TAWA activists and members. It employs an ethnographic and activist approach informed by Global Ethnography and the Extended Case Method. The analysis entailed the description of local experiences of im/migrant agency workers and the ways that agencies manage their vulnerabilities to optimize labour exploitation. It relates IWC and TAWA organizing processes to the growing activity and importance of workers' centres as alternative organizations to traditional trade unionism. The study found that systematic violations of im/migrants' labour rights through agencies also impact their private lives. It argues that the Canadian and Quebec states are complicit in structuring this super-exploitation through their immigration policies and their disengagement from the conditions of im/migrants in the labour market. In response, the IWC and the TAWA have developed an organizing model for agency workers based on five pillars: community organizing, knowledge production, popular education, and leadership development. This includes provision of services infused with education for collective action, arts-based activism, and diverse ways of spreading information and knowledge. Participation in bigger campaigns and partnership with engaged academics has also resulted in important strategies leading to the IWC and the TAWA organizing workers and making visible the problems associated with agencies.
OCLC: 1117447052
Keywords: Academic Dissertation; Academic theses; Integrated Studies in Education; Thèses et écrits académiques

Identity, Employment, and Inequality: An Examination of Immigrants with Disabilities - Sayin, Kutadgu Firat (McMaster University, 2019)
Most extant studies on the relationship between workforce diversity and employment inequalities focus on the impact of a single disadvantaged identity on a single employment outcome such as pay or promotion at the organizational level. Thus, the relation between workers’ multiple identities and different dimensions of employment inequalities within the broader social context remains unclear. The goal of this thesis is to start filling this gap. I start with developing a multilevel model of employment inequalities for workers with multiple identities by integrating the social identity theory, double jeopardy hypothesis, intergroup contact theory, and theory of minority group threat. I test this model with two empirical studies using Statistics Canada’s nationally representative Canadian Survey on Disability (2012) linked with the National Household Survey (2011). Labour force participation, employment, and employment income are the dependent variables of this thesis. I examine the intersection of immigrant and disability identity dimensions by focusing on immigrants with disabilities (IwD) as compared to immigrants with no disabilities, Canadian-born with disabilities, and Canadian-born with no disabilities. Study 1 demonstrates that while immigrant and disability identities are independently negatively associated with employment and employment income, having both identities simultaneously has a positive effect on employment and employment income. Furthermore, with the increase of the residential area diversity (RAD), which is determined by the number of immigrants and people with disabilities in a community, IwD’s likelihood of employment increases but employment income decreases. Study 2 shows that the proportion of immigrants in a residential area (RA) is negatively associated with the likelihood of being in the labour force for IwD. Furthermore, perceived work discrimination is negatively associated with labour force participation for IwD. Moreover, perceived work discrimination mediates the relationship between the proportion of immigrants in an RA and labour force participation for IwD. This thesis contributes to theory by (i) developing a multi-level theoretical framework that demonstrate the complex relationship between individuals with multiple identities, organizations, and society, (ii) extending the intergroup contact theory and the theory of minority threat using empirical evidence from individuals with multiple identities rather than focusing on a single identity, (iii) examining multiple employment outcomes at once and demonstrating how employment outcomes might differ based on intersecting identities, and (iv) demonstrating the impact of societal context by incorporating RAD into analysis and showing how the employment outcomes of individuals with multiple identities differ by where they reside. I discuss practical implications of the findings for workers, employers, policymakers, and society.

"The world outside these walls": Toronto's Provincial Lunatic Asylum in Context, 1830-1882 - Smith, Maximilian Samuel (York University, 2019)
This dissertation explores the place of Torontos Provincial Lunatic Asylum within the broader social, cultural, and political landscape of nineteenth-century Ontario (Upper Canada). The development of the asylum in Upper Canada was one part of a broader institutional reform movement intended to codify, segregate, and rehabilitate the provinces criminals, lunatics, and other social deviants. I argue that the lunatic asylum was fundamentally shaped by its place within this broader institutional suite. At once a medical, political, and social space, the asylum was mobilized by various individuals and associations to serve a variety of interests. The Provincial Lunatic Asylum was a liminal institution. Its value as a resource for the growing Upper Canadian medical profession, its place within entrenched systems of partisan patronage, and its status as a charitable public institution ensured that the fate of the lunatic asylum was tied to the life of the province. By situating the asylum within its broader social, political, and cultural contexts, this study enhances our understanding of the role of public institutions like the asylum in the early formation of the Canadian state. Moreover, this study sheds light on the intricate connections between lunacy care and the everyday life of Upper Canadians from many social and cultural backgrounds. It is a study not only of the role of the asylum in the development of a nation, but also the fundamental role of the local and transnational contexts of mid-nineteenth-century Upper Canada on the development of a peculiarly Canadian asylum. This is the story of both an institution and the world outside its walls, spanning a range of topics including the professionalization of medicine, the birth of a political culture, the institutional development of Upper Canada and Toronto, working- and middle-class labour, and the experiences of ordinary Upper Canadians living with lunacy.

Troubling the Teacher Diversity Gap: The Perpetuation of Whiteness Through Practices of Bias Free Hiring in Ontario School Boards - Abawi, Zuhra Elizabeth (University of Toronto, Ontario Institute for Studies in Education, 2018)
Teaching staff in Ontario schools do not reflect the increasing diversity of the students who occupy Ontario classrooms today. School boards across Ontario have come under considerable scrutiny regarding the lack of diverse teacher representation that adequately reflects Ontario’s demographic composition (Childs et al., 2010; Ryan, et al., 2009; Turner, 2015). This thesis addresses the Ontario teacher diversity gap (James Turner, 2017; Turner 2015; Turner, 2014; Ryan, et al., 2009) in relation to provincial equity and inclusive educational policies, which have been created to address the dominance of white teachers in publicly-funded education in Ontario. However, findings from the research indicate that these policies have not had the desired results, and in some ways have contributed to perpetuating the status quo, and the ongoing overrepresentation of white teachers in schools. The thesis furthermore addressed the notion of bias-free hiring (Fine Handlesman, 2012; Hassouneh, 2013) practices through narratives of Ontario teachers themselves. The predominant assumption of bias-free hiring is that one can divorce themselves from their unconscious biases and preconceptions of groups who are dissimilar to them in order to recruit the so-called “most qualified applicant”. The narrative of the “most qualified applicant” is a term invoked when racialized people seek access to employment opportunities. School administrators have great influence on who is hired; therefore it is important for administrators to interrogate their own social locations and positions of power, and unconscious bias in terms of how they recruit teachers. Findings from the research indicate that teachers from racialized groups have different experiences when seeking employment as teachers in publicly-funded school boards in Ontario. In response to this the EHT Equity Hiring Toolkit for Ontario School Administrators has been developed to support school administrators to recruit more diverse teachers. The EHT provides a framework for school administrators to engage in antiracist praxis and action, by examining their social location, and ways that their positionality impacts the hiring decisions they make. School administrators can use the creation of the Toolkit based on the findings of the data that emerged from the research as a Creative Professional Activity (CPA). I consider this to be my contribution to the field of social justice education and leadership.

Les grèves de la Shmata, 1934-1937: étude des contradictions de genres, d'ethnicités et de classes dans le mouvement ouvrier juif à Montréal - Alatorre, Florian (Université du Québec à Montréal, 2018)
Les grèves générales de la robe déclenchées en août 1934 et en avril 1937 marquent un épisode de solidarité entre ouvrier.ères juif.ves et travailleuses canadiennes-françaises jusqu'alors sans précédent. Si quelques grèves avaient déjà réuni piqueteuses juives et canadiennes-françaises dans les années 1920, aucun de ces conflits de travail n'avait connu cette ampleur. Souvent isolées à une seule fabrique de vêtements, ces grèves étaient de taille plus modeste, tant par la durée du conflit que par le nombre de grévistes qu'elles comprenaient. La grève de 1934 organisée par l'IUNTW rassembla dès son déclenchement 4 000 piqueteur.ses, interrompit l'activité de 90 établissements, et totalisa en tout 45 000 journées de travail perdues. La grève de 1937 qui s'inscrivit dans la continuité de l'organisation des ouvrières de la robe entamée par la grève de 1934, rassembla plus de 5 000 grévistes et couta 55 000 journées de travail perdues à l'industrie montréalaise de la robe. Le présent mémoire explore les grèves générales des ouvrier.ères de la robe qui s'enclenchèrent au cours de la décennie 1930 à Montréal. Opposant un prolétariat canadien-français et juif à des manufacturiers pour la majorité eux-aussi juifs, ces grèves s'inscrivent dans le phénomène plus vaste d'un mouvement ouvrier juif canadien. L'expérience de ces conflits de travail est parcourue par de multiples tensions. Le prolétariat de l'aiguille est traversé par de multiples contradictions où s'entrelacent plusieurs axes de hiérarchisation qui fragmentent la force de travail. Conséquemment, ce mémoire se penche plus précisément sur les rapports de pouvoir et les axes hiérarchiques qui structurent à la fois la production, mais aussi la lutte syndicale, plus précisément autour des rapports de genres, de classes et d'ethnicité sur le plancher de l'usine et à l'intérieur des organisations syndicales. Ce mémoire cherche à comprendre comment l'articulation des relations de genres, d'ethnicité et de classes module l'expérience de la lutte ouvrière dans le cas précis du mouvement ouvrier juif montréalais dans le secteur de la robe, au cours de la décennie 1930 et comment dans un prolétariat fragmenté sur une multiplicité d'axes hiérarchiques ont pu se construire des alliances et des moments forts de solidarité au sein de grèves et de luttes ouvrières.
OCLC: 1077271412
Keywords: 1900-1999; Academic Dissertation; Academic theses; Années trente (Vingtième siècle); Clothing workers Labor unions; Grèves et lock-out Vêtements Industrie et commerce Québec (Province) Montréal Histoire 20e siècle; History; Labor movement Québec (Province) Montréal Religious aspects Judaism; Labor movement Religious aspects Judaism; Mouvement ouvrier Québec (Province) Montréal Aspect religieux Judaïsme; Nineteen thirties; Québec Montréal; Strikes and lockouts Clothing trade; Strikes and lockouts Clothing trade Québec (Province) Montréal History 20th century; Syndicalism; Syndicalisme; Thèses et écrits académiques; Travailleurs du vêtement Syndicats

Struggling for a New Left: The New Tendency, Autonomist Marxism, and Rank-and-File Organizing in Windsor, Ontario during the 1970s - Antaya, Sean (Trent University, 2018)
This study examines the emergence of the New Left organization, The New Tendency, in Windsor, Ontario during the 1970s. The New Tendency, which developed in a number of Ontario cities, represents one articulation of the Canadian New Left's turn towards working-class organizing in the early 1970s after the student movement's dissolution in the late 1960s. Influenced by dissident Marxist theorists associated with the Johnson-Forest Tendency and Italian workerism, The New Tendency sought to create alternative forms of working-class organizing that existed outside of, and often in direct opposition to, both the mainstream labour movement and Old Left organizations such as the Communist Party and the New Democratic Party. After examining the roots of the organization and the important legacies of class struggle in Windsor, the thesis explores how The New Tendency contributed to working-class self activity on the shop-floor of Windsor's auto factories and in the community more broadly. However, this New Left mobilization was also hampered by inner-group sectarianism and a rapidly changing economic context. Ultimately, the challenges that coincided with The New Tendency's emergence in the 1970s led to its dissolution. While short-lived, the history of the Windsor branch of The New Tendency helps provide valuable insight into the trajectory of the Canadian New Left and working-class struggle in the 1970s, highlighting experiences that have too often been overlooked in previous scholarship. Furthermore, this study illustrates the transnational development of New Left ideas and organizations by examining The New Tendency's close connections to comparable groups active in manufacturing cities in Europe and the United States; such international relationships and exchanges were vital to the evolution of autonomist Marxism around the world. Finally, the Windsor New Tendency's history is an important case study of the New Left's attempts to reckon with a transitional moment for global capitalism, as the group's experiences coincided with the Fordist accord's death throes and the beginning of neoliberalism's ascendancy.
https://cha-shc.ca/prize-winner/sean-antaya/

Hone the Means of Production: Craft Antagonism and Domination in the Journalistic Labour Process of Freelance Writers - Bertuzzi, Robert (Western University, 2018)
The works of Karl Marx have been central to the formation of a body of critical communication scholarship in Canada. But as Nicole S. Cohen adeptly shows, the influence of Marx’s thought has been absent, mostly, as it relates to questions involving cultural labourers. Of particular interest to her is Marx’s formulation concerning exploitation and its relationship to the field of journalism as it affects freelance writers. This dissertation extends the notion of a “missing Marx” by incorporating other concepts from his oeuvre. His writings on alienation help to address one of two major research questions posed in this dissertation. The first being: why is it that freelance writers in Canada are willing to work for such low levels of remuneration? Historically, a dichotomous rendering has prevailed as to whether exploitation or alienation provides a better explanatory framework for understanding the experiences of workers—in this case, freelance writers. One of the aims of this work is to bring alienation and exploitation into conversation with one another. This requires an analytical investigation of the journalistic labour process. Ideas of craft have helped shape identity and understandings of work in the journalistic field over a few centuries now. This understanding segues into the second research question: at this juncture of deepening capitalist crises, and subsequent renewed interest in craft modes of production, what relevance do these forces have in the lives of contemporary freelance writers? This dissertation addresses both of the above research questions as well as the aforementioned phenomenon through interviews of Canadian freelance writers in the spirit of Marx’s workers’ inquiry. These 25 interviews in combination with documentary analysis of the historically changing conditions of journalism explore the pertinence of the field’s craft sensibility upon its freelance workforce under circumstances of intensifying alienation. Statements from informants reveal the craft dimensions of the labour process as both a source of domination and of resistance as well as playing a possible future role in the enactment of broader class struggles.

Precarious Professionals: Non-Tenure-Track Faculty in Southern Ontario Universities - Birdsell Bauer, Louise (University of Toronto, 2018)
While precarious work is a phenomenon often associated with non-professional workers, the emerging case of non-tenure-track faculty (NTTF) calls for a new framework building on scholarship on both precarious work and the professions. An in-depth case study of NTTF in southern Ontario shows how a new phenomenon of ‘precarious professionals’ is emerging. Drawing on sixty semi-structured interviews with faculty members, university administrators and union representatives across southern Ontario, I analyze workers’ experiences in temporary contract work in the academic profession, and their views on the way certain types of professional work are valued. Building off previous literature on precarious work, gender and work, and professional work, this thesis defines precarious professionals as highly skilled workers who do professional work that is valued and devalued along lines of gender. Their experiences in temporary contract work marginalize them economically and professionally in complex and compounding ways that trap them between identifying as precarious workers and as professionals. Union organizers and activists draw on a two-pronged approach that addresses both dimensions of precarious worker and professional identities. This thesis shows variation in workers’ experiences, suggesting that not all temporary contract workers become precarious professionals, and shows how that variation can be explained.

Industrial Island - African-Caribbean Migration to Cape Breton Canada, 1900-1930 - Bonner, Claudine (Dalhousie University, 2018)
The late 19th and early 20th centuries evidenced extreme changes in industry and urbanization which fueled the movement of people worldwide. Included in this movement was an African Diaspora migration up and out of the Caribbean Basin and into the United States and elsewhere, as people sought to escape economic hardships within the region. Some took the opportunity to make their way to Sydney, Nova Scotia, where they labored for the Dominion Iron and Steel Company. The story of their migration to Cape Breton is of interest because they have remained a footnote in Canadian migration history. This thesis offers an opportunity to look at the lived experiences of these African Caribbean migrants and the community they created in Whitney Pier. This community served to spread notions of racial uplift and Black nationalism, evidenced by its involvement in the then growing Garvey movement.
Accepted: 2018-05-03T11:49:31Z

Diaspora Solidarities: Refugees, Human Rights, and the Jewish Labour Committee of Canada, 1936-1967 - Chanco, Christopher John Jacobi (York University, 2018)
This transnational history of the Jewish Labour Committee of Canada (JLC) retraces the organisations narratives, networks, and practices of diaspora solidarity, from the moment of its establishment and into the post-war period. The JLCs activists refracted their solidarities through the lens of a diasporic Jewish identity. At a time when Canada imposed strong barriers against refugees, the JLC worked to send aid to the anti-fascist resistance in Europe while participating in a series of immigration schemes to bring Jews from displaced persons camps over to Canada. It was in this unique moment that the JLC could also launch pioneering human rights and anti-racism campaigns within the labour movement. Representing one section of the organised Jewish community in Canada, the JLC proved a critical part of the transformation of the countrys treatment of refugees and minorities in the following decades.

Faculty Narratives of Disability in Academic Work - Dolan, Vera Lúcia Brandão (University of Toronto, Ontario Institute for Studies in Education, 2018)
In the neoliberal academy, professors who disclose any form of impairment risk raising concerns about their fitness to perform their jobs. Academics are expected to deliver highly measurable outcomes from their work in order to build a positive reputation among their peers. But given the negativity that typically characterizes the disability discourse in Western cultures, it is all too easy for the scholarly community to infer that differentness equates to ineptness. Thus, individualist and ableist discourses are central to the discussion of power relations and care of the self in the contemporary academy. The focus of this doctoral thesis is “diversable” professors performing under neoliberal academic regimes. The term “diversability” is used to designate people with disabilities—particularly of an invisible nature—while debunking the fallacious connotation of incompetence habitually attached to their differentness. Combining self-narrative and postmodern-grounded theory, this study derives valuable insights from the stories of 16 professors, both tenured and untenured, who reveal how they navigate disability, as well as the intersecting dimensions of differentness attached to their self-identities. The findings suggest that diversable professors, in spite of an academic environment embedded in disability avoidance—and the usual structural contingencies that can prevent scholars from fully demonstrating their value—can present counter-narratives that include positive constructions of self-identity as good teachers, researchers and advocates for social justice. This research also uncovers inadequacies in the academy itself—but not without a message of hope for remedial change.

Imagined Communities of 'Whiteness': Racial-Nationalist Origins of Settler-State Formation in Argentina and Canada, 1840-1914 - Evans, Jessica Jacqueline (York University, 2018)
This dissertation sits at the intersection of critical international political economy and a decolonizing, anti-racist approach to empirical political science. Specifically, I examine how liberal state forms are presupposed by and premised upon illiberal practices of sorting, policing, and defining populations. Rather than view such practices as anomalous to the modern state form, I view them as productive. I depart from the dominant literature in this field of study (postcolonial theory) with a typical focus on discursive and local practices, and instead advance a defense of Marxism rooted in an examination of the material practices of states responding to global political-economic pressures. This analytical and methodological focus stems from an engagement with the theoretical and empirical work conducted through Political Marxism, and through an engagement with the concept of uneven and combined development. I compare instances of racialized nation-building from the nineteenth century, focusing on the ways in which the creation of racialized hierarchies of belonging were seminal to the production of liberal state capacity and legitimacy. I examine the cases of Canada and Argentina to explore how the dispossession and management of indigenous peoples served to foment vast networks of bureaucratic, fiduciary, and coercive state capacities. Such capacities were necessary in the project of constructing competitive liberal economies to respond to pressures generated by an emergent global market in agricultural goods. This work sheds new light on the role of race and racialization in the formation of the nation-state system, while responding to and contesting common assumptions about the legal equality assumed to underpin Western nationalism(s).

The Institutional Organization of Black Female Child Protection Workers’ (Re)construction of their Role as Carers in Child Protection: An Institutional Ethnographic Inquiry - Goary, Woyengi (University of Toronto, 2018)
This institutional ethnographic study explores the coordinated processes that organize Black female child protection workers’ (re)construction of their role as carers in the Ontario child protection system. This examination occurs within the backdrop of colonialism and shifting and unequal power relations in Canada. Absent from social work research is an understanding of the complex sequences of actions in every day child protection activities that authorize colonial ideologies and practices and the impact of Black female child protection workers’ negotiation of this context on their well-being. This study’s informant sample includes 9 Black female child protection workers currently employed at a child protection institution in Ontario. Data was collected from semi-structured interviews and textual analysis. The findings revealed colonialism in the child protection system is maintained through institutional patterns of exclusion and acts of dissimulation in the institutional discourse and practice. In response, Black female child protection workers resist colonial practices through their injection of acts of caring into their work. At the same time, their constant experiences of structural violence lead to institutional trauma. This research highlights a contradiction within the social work framework; the overt espousal of human rights and social justice as ethical priorities, while covertly maintaining colonialism in the child protection system, specifically towards Black female child protection workers and their communities. The findings advance social work knowledge by offering a way to identify the existence and the impact of the colonial context on Black female child protection workers as well as map out the sequences of actions or inactions that embed colonial ideologies and practices in the child protection system.
Accepted: 2018-07-18T19:03:41Z

Anarchism and the Working Class: The Union of Russian Workers in the North American Labor Movement - Grueter, Mark (Simon Fraser University, 2018)
Thousands of Russian anarchist immigrants, organized by the Union of Russian Workers (URW), took part in a surging union movement and strike wave that broke out across North America in the 1910s. However, they have received scant attention from historians, and no account of the URW exists. My dissertation fills in this gap by detailing the activity of the URW against the background of the rising labor movement, and it considers the question of anarchism's relationship to the working class. Historians have traditionally situated anarchism outside of the labor movement, yet the Russian anarchists in North America joined both radical and mainstream unions, and URW leaders recruited migrants explicitly by appealing to their class interests as foreign workers exploited by American capitalism. The study highlights the anarchists’ involvement in labor organizing, and it centers their perspectives to help narrate a history of the period. It first traces a history of the international anarchist movement along with migration patterns to North America in order to contextualize the research and shed light on the origins of the URW and why their story matters. Utilizing anarchist publications, local English-language newspapers, government surveillance files, and archival materials, the study finds that URW members made a wide array of contributions to the emerging industrial union movement in the United States and developed a critique of American capitalism that ranged beyond the immediate strikes. It argues that alongside the Industrial Workers of the World, the URW helped to push labor to the left and prepare the ground for the rise of major industrial unions with socialist leanings in the 1930s. Simultaneously, the study shows how the URW harnessed its strength in North America to make substantial material contributions to the anarchist movement in Russia, in the lead up to the 1917 revolution, while developing an anti-Bolshevik critique also echoed by subsequent movements on the left. By locating Russian anarchism and the URW in the labor movement, this study challenges historiographical claims which deny anarchism's working-class character. Thus, it contributes to a growing body of newer research which finds the anarchist movement rooted in labor and working-class organizing.

Industrial Stagecraft: Tooling and Cultural Production - Hambleton, Jennifer (Western University, 2018)
The tooling of theatrical spectacle requires collaboration between stagecraft technicians and designers in an increasingly globalized and standardized manufacturing process. While hand skills are still used and remain useful, digital fabrication and other tools are now incorporated in labour processes in scenery manufacturing workshops, altering collaborative work in complex ways. This thesis is an inquiry into the epistemological role of software and digital fabrication tools in stagecraft practices and explores how the politics of craft labour intersect with material practices in media production labour. The technical aspects of the fabrication of theatrical spectacles and display environments, the way objects are used to think, and the ways tools mediate practices suggest how tacit knowledge is produced and reproduced in scenery manufacturing workshops that build theatrical sets and corporate display environments. The articles in this thesis draw from case study research of a community of craft technicians who work in the industry of theatrical display in southern Ontario, Canada. Each of the four articles focuses on different facets of this case study. The technician’s work in labour processes in scenery workshops is compared to repair and bricolage. Autonomy or self-determination over tasks in the workshop sites is explored in its material and embodied sense. The collaboration between the designer and scenic artist is mediated with digital media and this complicates established occupational roles. A case of collective organizing exemplifies the individualistic/collective dichotomy of craft labour. Using an inductive approach, the empirical research for this community case study was accomplished with participant observation and semistructured interviewing. My analysis of interview transcripts and interpretation of field data utilizes an autoethnographic methodology to reflect on and draw from my past work experience in theatre production labour as a builder and scenic artist. In this integrated article thesis, I consider how material practices constitute culture in media production labour.

Patterns of Protest: Property, Social Movements, and the Law in British Columbia - Isitt, Benjamin (University of Victoria, 2018)
Embracing a spatial and historical lens and the insights of critical legal theory, this dissertation maps the patterns of protest and the law in modern British Columbia―the social relations of adjudication—the changing ways in which conflict between private property rights and customary rights invoked by social movement actors has been contested and adjudicated in public spaces and legal arenas. From labour strikes in the Vancouver Island coal mines a century ago, to more recent protests by First Nations, environmentalists, pro- and anti-abortion activists, and urban “poor peoples’” movements, social movement actors have asserted customary rights to property through the control or appropriation of space. Owners and managers of property have responded by enlisting an array of legal remedies and an army of legal actors—lawyers, judges, police, parliaments, and soldiers—to restore control over space and assert private property rights. For most of the past century, conventional private property claims trumped the customary claims of social movements in the legal arena, provoking crises of legal legitimacy where social movement actors questioned the impartiality of judges and the fairness of adjudicative procedures. Remedies and legal technologies asserted by company lawyers, awarded by judges, and enforced by police and soldiers were often severe―from Criminal Code proscriptions against riotous assembly and deployment of military force, to the equitable remedy of the injunction and lengthy prison sentences following criminal contempt proceedings. But this pattern shows signs of change in recent years, driven by three major trends in British Columbia and Canadian law: (1) the effective assertion of indigenous customary rights; (2) growing recognition of the importance of human rights in democratic societies, particularly in the context of the Canadian Charter of Rights and Freedoms; and (3) changes in the composition of the legal profession and judiciary. This changing legal landscape has created a new and evolving legal space, where property claims are increasingly treated as contingent rather than absolute and where the rights of one party are increasingly balanced by customary rights, interests, and aspirations of others. Consequently, we are seeing a trend toward the dilution of legal remedies traditionally available to the powerful, creating space for the assertion of non-conventional property claims and the emergence of new patterns of power relations.

The Role of Empowerment on the Relationship between Flexible Work Arrangements, Work-Life Balance, and Job Satisfaction in the Canadian Public Sector - Marzi, Elham (University of Toronto, 2018)
Some studies have shown strong support for positive outcomes related to flexible work arrangements such as improved performance and productivity (Bloom, Liang, Roberts, Ying, 2015; Laschinger, Finegan, Shamian, Wilk, 2001; Laschinger, Leiter, Day, Gilin, 2009), while others have found detrimental effects including negative impacts on managing and separating work, life, and family demands (Cohen Single, 2001; Yuile, Chang, Gudmundsson, Sawang 2012). The typical approach to studying flexible work arrangements is to examine outcomes at the individual level among employees, assessing the relationship with performance and work-life, or work-family balance. This study examined the relationship between flexible work arrangements and job attitudes and work-life balance, simultaneously at both the individual and organizational unit level of analysis in the Federal public sector in Canada. The data is from responses captured five times over the span of 12 years within the public-sector workforce. The findings provide further contributions to the body of research on the job demands-resources model (Bakker Demrouti, 2007) and support the idea that some types of flexible work arrangements are positively related to work-life balance and job satisfaction, while also being positively mediated by structural empowerment of employees. These findings hold both at the individual and organizational level. Certain flexible work arrangements, namely flextime and telework, show consistent and positive relationships with work-life balance at both the individual and organizational unit level. Compressed work weeks, and income averaging, however, show signs of negative relationships and require further study. A critical finding of this study is that empowerment consistently fosters improved work-life balance and job satisfaction, providing strong evidence for practitioners to prioritize employee structural empowerment as part of strategic human resource plans.
Accepted: 2019-07-10T04:00:38Z

Conceptualization, Measurement, and Association of Underemployment to Mental Health Inequities between Immigrant and Canadian-born Labour Force Participants - Mawani, Farah N. (University of Toronto, 2018)
This thesis aims to increase understanding of the association of underemployment (unemployment or overqualification) to mental health inequities between immigrant and Canadian-born labour force participants. The first paper provides a theoretical framework to guide design, analyses and interpretation of findings for this thesis, and future research on social determinants of mental health inequities. The second paper uses the Canadian Community Health Survey (CCHS) Cycle 1.2 to assess the construct validity of self-rated mental health (SRMH) for the overall population, and sub-groups by immigrant status and sex. Positive associations between SRMH and a comprehensive array of mental morbidity measures were large and consistent, but a sizeable percentage of respondents with mental morbidity did not rate their mental health as fair/poor. SRMH is useful for assessing social determinants of inequities in general mental health, but not specific mental health morbidities. The third paper uses CCHS Cycle 2.1 (2003) to examine the association of underemployment to fair/poor self-rated mental health (SRMH) in: 1. labour force participants (18-64 yrs) in Canada, and 2. between a. immigrants vs. Canadian-born labour force participants, and b. recent immigrant (< 10 years in Canada) vs. long-term immigrant (³ 10 years in Canada) labour force participants. Underemployment was positively associated with fair/poor SRMH for labour force participants. There was a significant positive association of overqualification to fair/poor SRMH for immigrant (AOR 1.63), but not for Canadian-born labour force participants (AOR 1.03), and differences between the groups were significant (p<0.05). Unemployment had a higher magnitude of association (AOR 3.41) than overqualification (AOR 1.52) to fair/poor SRMH for long-term immigrants, while overqualification had a higher magnitude of association (AOR 2.04) than unemployment (AOR 1.15) to fair/poor SRMH for recent immigrants arriving between 1993-2003. For recent immigrants, the associations of unemployment and overqualification to fair/poor SRMH were not statistically significant (p<0.05). Though differences between groups did not achieve statistical significance (p<0.05), differences may have practical importance....

Home and Away: Circular Migration, Mobile Technology, and Changing Perceptions of Home and Community in Deindustrial Cape Breton - McIntyre, Mark (University of Victoria, 2018)
This thesis engages deindustrialization as a lived process and applies the concepts of precarity as they relate to communities navigating processes of deindustrialization. Through ethnographic interviews and participant observation research conducted over the summer of 2017 I examine the lived experiences of circular migrant labourers and their significant others, who live in the former coal town of Glace Bay, Nova Scotia, Canada, as they engage in strategies to keep their families in the community. I explore the continuities of industrialization, deindustrialization and labour; the history of work in the region; the present sacrifices that families make to stay in the communities; why families stay; and what they circular migrant labourers and their significant others imagine the future of the region will look like as they raise their children there. Further, as circular migrant labourers are away from home and their families for significant amounts of time, often at irregular schedules, I ask about the strategies that labourers and their families use to eke out a living in a marginalized community. I ask participants what it is like to have to leave the community for work; what it is like to stay behind while your significant other is away for work; what is it like to be home together; and what strategies are used to keep in touch. One such strategy is the use of internet communication technologies to negotiate physical and social distance. However, these technologies do not always necessarily make up for time spent away from loved ones.

Days of Action: Ontario's Extra-Parliamentary Opposition to the Common Sense Revolution, 1995-1998 - Nesbitt, Douglas (Queen's University, 2018)
From 1995 to 1998, Ontario was the site of a sustained political and industrial conflict between the provincial government of Premier Mike Harris and a loosely-coordinated protest movement of labour unions, community organizations, and activist groups. The struggle was aimed at the defeating the “Common Sense Revolution,” a sweeping neoliberal program advanced by the Progressive Conservative Party of Ontario. The program designed to renovate the state, rationalize the social safety net, repeal barriers to capital accumulation, and decisively weaken the strength of organized labour. What became a union-led extra-parliamentary opposition drew in large sections of the population often aligned with a political culture of statist collectivism encompassing both social democracy and “Red Toryism”. The movement emerged at a time when the two major parties aligned with such ideas embraced neoliberal policies. Under the leadership of Mike Harris, the Red Tories were pushed out of the Ontario Progressive Conservatives in the early 1990s. Meanwhile, the one-term New Democratic government of 1990-95 made a decisive turn towards neoliberal austerity amidst a catastrophic recession, declining federal transfers, and employer hostility. Through the union-led “Days of Action” of large political strikes, mass demonstrations, and numerous militant protests, the implementation of the Common Sense Revolution was slowed and weakened and the government’s popularity greatly diminished. However, the province’s union leadership was deeply divided over loyalties to the New Democratic Party following its turn to neoliberal austerity. One union leadership faction opposed the Days of Action while the other proved unwilling to escalate the scale of industrial disruption against the Common Sense Revolution. The crisis led to an open factional dispute within organized labour that culminated in the formal suspension of the political strikes in the summer of 1998. The outcome was an unprecedented political defeat for the labour-led forces defending an expansive redistributive welfare state, and a retreat by organized labour from extra-parliamentary political strategies in favour of electoralism. The government managed to regain support before winning re-election in 1999. The end of the Days of Action marked the political triumph of neoliberal restructuring and permanent austerity, and the crafting of a new political and economic common sense that has endured in Ontario to this day.

La position des centrales syndicales et des organisations patronales à l'égard de l'immigration au Québec, de 1965 à 1995 - Provost-Turgeon, Florence (Université de Montréal, 2018)
Ce mémoire porte sur l’immigration au Québec en comparant le point de vue des principales organisations représentant le monde patronal et le monde syndical de l965 à 1995. Les instances étudiées sont, du côté patronal : le Conseil du patronat du Québec (CPQ) et la Chambre de commerce du district de Montréal (CCDM). Du côté syndical, nous analysons le discours des principales centrales, soit la Confédération des syndicats nationaux (CSN), la Fédération des travailleurs du Québec (FTQ) et la Centrale de l’enseignement du Québec (CEQ). Avec l'augmentation constante du nombre d'immigrants et la diversification de leurs origines, la période étudiée se caractérise par la volonté du gouvernement québécois de prendre en charge les politiques d’immigration et d’intégration des immigrants à la société québécoise. Désireux d'intervenir conjointement avec le gouvernement fédéral, il crée, en 1968, un ministère de l'Immigration. Tout au long de la période étudiée, des négociations entre les deux paliers de gouvernement se traduisent par des ententes qui définissent la marge de manoeuvre de l'État québécois et guident ses actions en matière d'immigration et d'intégration. Au cours des années 1980, l'État québécois se dote d'une politique d'intégration et d'encadrement des immigrants qu’il qualifie d’interculturalisme, destinée à promouvoir la reconnaissance de la pluralité ethnoculturelle et l'adhésion de tous les citoyens à la langue française. En participant aux consultations publiques du gouvernement et en présentant des réclamations, les organisations patronales et syndicales tentent d'influencer les politiques d'immigration. Chaque instance développe une manière particulière d’analyser les questions liées à l’immigration. Dans une large mesure, leurs discours se rejoignent sur l’idée que le gouvernement du Québec prenne en charge le domaine de l’immigration et sur l’apport bénéfique des immigrants pour la société québécoise. Bien souvent cependant, elles s’opposent sur les normes de sélection et sur la manière de mettre en application les politiques d’immigration.
https://doi.org/1866/20151

De l'universel au particulier : les luttes en faveur des droits humains au Québec, de l'après-guerre à la Révolution tranquille - Rainville, Paul-Étienne (Université du Québec à Trois-Rivières, 2018)
Notre thèse porte sur l' histoire du militantisme en faveur des droits humains au Québec, de la fm de la Deuxième Guerre mondiale aux premières années de la Révolution tranquille. Elle s'appuie sur une analyse comparative des discours et des revendications portés par quatre organisations issues du mouvement syndical (la Fédération des travailleurs du Québec et la Confédération des travailleurs catholiques du Canada), de la communauté juive (le Congrès juif canadien) et du mouvement étudiant francophone montréalais (l'Association générale des étudiants de l' Université de Montréal). À travers ces quatre études de cas, nous mettons en lumière le rôle déterminant des organisations non gouvernementales et des groupes et individus victimes d'atteintes à leurs droits dans les processus de réappropriation, d'internalisation et de diffusion des idéaux des droits humains à l'échelle locale et nationale. En exposant les similitudes et les spécificités des trajectoires de ces organisations, de même que l'étendue de leurs réseaux d'alliances, nous démontrons que le discours des droits humains s'est érigé comme un important instrument de mobilisation, de contestation et de changement social pour les principaux groupes et mouvements sociaux actifs au Québec dans les deux décennies suivant la Seconde Guerre mondiale. Fondée sur une approche multiscalaire, notre recherche porte une attention particulière aux réseaux transnationaux dans lesquels s' inscrivent les acteurs que nous étudions et aux enjeux internationaux qui influencent leur combat pour la reconnaissance de droits humains à l' échelle locale, nationale, régionale et mondiale. À partir de cette dialectique globale-locale, nous démontrons l'impact déterminant du mouvement international des droits humains sur l'évolution des débats qui agitent la société québécoise, mais aussi le rôle structurant du contexte local, marqué par le passage de la période dite de la « Grande noirceur» à celle de la Révolution tranquille au Québec. Sur le plan théorique, notre étude explore la manière dont les identités et les rapports de pouvoirs ethniques, de classe, d'âge et de genre contribuent à orienter les discours, les revendications et les stratégies des militants qui se revendiquent de l'idéal universaliste des droits humains. En nous inspirant des approches discursive, délibérative et socioconstructiviste, nous montrons que ces droits ne constituent pas un idéal abstrait et universel qui serait par essence désintéressé. Ils apparaissent en effet, sur le plan empirique, comme une catégorie discursive socialement construite et historiquement contingente, qui peut être mobilisée, négociée ou contestée par les acteurs sociaux en fonction de leurs idéologies, de leurs intérêts, de leurs stratégies et de leurs propres conceptions du juste et de l'injuste. Enfm, en envisageant ces droits dans leur dimension formelle (les normes établies par l' État, le droit et la loi) et identitaire (la reconnaissance d' identités sociales et citoyennes), nous mettons en lumière la dialectique entre universalisme et particularisme qui est à l'oeuvre dans l'universalisationconcrète de l' idéal des droits humains.

Journalists Organize the Thomson Newspaper Chain: A Labour Union Standpoint to News Organizations - Salamon, Errol (McGill University, 2018)
In this dissertation, I outline a history of the labour union organizing efforts of journalists at the Thomson Newspapers chain in Canada from 1963 to 1995. Such organizing efforts provide an entry point into examining control over employment conditions in the newspaper industry. To undertake this study, I develop an analytical framework that I call a “labour union standpoint to news organizations” and a “labour union standpoint methodology.” I conduct a historical and labour union standpoint analysis of nine labour organizing campaigns, situating them within their broader political, economic, and social-historical contexts. I draw on union archival documents, newspaper content, corporate and government documents, and a critical review of the published body of literature. Between 1963 and 1995, Thomson adopted a long-term strategy of vertical growth, expanding from radio broadcasting and newspapers into other media. The corporation also adopted a strategy of horizontal growth, building a newspaper chain through acquisitions, and typically obtained a monopoly or oligopoly in the markets in which it operated. Thomson consistently had double-digit profit margins and was among the “big three” newspaper chains in Canada with regard to number of daily newspapers owned, share of total daily newspaper circulation, or share of total revenues. In response, Thomson journalists organized labour unions to protect their employment conditions. Accordingly, I consider the labour organizing tactics that journalists’ unions adopted to “bite back” at the corporation and the communication tools that they used to facilitate those tactics.My analysis reveals that journalists’ unions contested and negotiated control over employment conditions within news organizations. The outcomes of union organizing efforts were contingent upon the local circumstances of the journalists, unions, and management at a particular newspaper within the chain. While journalists’ union organizing campaigns were sometimes unsuccessful, journalists were more successful when they focused on building bridges with community members rather than developing communication tools such as strike newspapers. Some journalists’ unions challenged the established social relations and advanced social transformation by mobilizing massive community support, connecting their workplace struggles to broader social issues, and creating publicity campaigns to communicate these struggles to the public.
Keywords: Art History and Communications Studies

Practicing Precarity: The Contested Politics of Work Experience in Cultural Industries - Sarjeant, Elizabeth Anne (Simon Fraser University, 2018)
Over the past decade in Canada, student work has become a topic of public criticism, legal action, academic research, and labour activism. Cultural industry employers’ use of unpaid, low-paid, and flexibilized labour in the form of internships and other kinds of ‘work experience’ raises questions about the future of work in already precarious fields such as news production, advertising, television, and film. Against the backdrop of neoliberal processes still shaping universities and labour markets, the student worker emerges as a strategic figure in the contested politics of cultural work. This thesis offers a theoretical and empirical investigation of the dominant discourse and counter-discourse through which work experience is constructed, legitimized, critiqued, and re-visioned. Drawing on autonomist Marxist theory, critical philosophies of education, and feminist political economy, I situate cultural work experience as a discursive site where struggles over knowledge production and labour rights become visible and urgent.

How Do Expectations Influence Labour Supply? Evidence from Framed Field Experiments - Stockley, Lisa Marie (University of Toronto, 2018)
Models of reference dependence have improved the connection between economic theory and documented labour supply behaviour. In particular, the Kőszegi and Rabin (2006, 2007, 2009) [hereafter "KR"] theory of expectation based reference dependent preferences appears to be a disciplined way to unify the conflicting wage elasticity estimates, and recent laboratory and natural experiments suggest this theory may work in practice as well. I take this theory to the field in a pair of laboratory-like experiments designed to test if expectations determine the effort of a group of impoverished individuals involved in piece-rate work in Northeast Brazil. I use Abeler, Falk, Goette, and Huffman's (2011) experimental mechanism, which is a clear test of KR preferences in effort provision, in two experiments: first to test if rational expectations act as a reference point that influences effort, and second to test if adaptive expectations act as a reference point that influences effort. In both experiments, I find that although people do not behave in accordance with KR preferences, they do not behave as though they make their decisions following canonical lines either. I then outline a speculative rationale for the observed behaviour in these experiments—the adaptive heuristic of regret matching—where workers are able to evaluate their ex-post feelings of regret, even if they do not know the source of those feelings, to optimize behaviour going forward.

Health, Labour, and the Environment: A Social Economic Analysis - Tumpane, Sara Kathleen (York University, 2018)
In this dissertation, I explore several social economic topics, including health, labour, and the environment. Although the chapters of this dissertation explore diverse subjects, the overall theme is to analyze important social issues and their policy implications. I made use of a variety of rich datasets, as well as employing various econometric analyses, often supported by a theoretical model, to examine the research topics identified in each chapter. In Chapter 1, I explore a 1997 policy change, which altered eligibility requirements for Disability Insurance (DI). While DI in Canada provides income support to millions, it has also been criticized for creating a disincentive for labour force participation. The 1997 change affected some Canadians, but not others, creating a natural experiment setting in which to explore this policy. I found that, following the tightening of eligibility requirements, relative labour force participation for women did increase, but their level of employment did not. There was little effect for men. This distinction between labour force participation and employment is a crucial one in this context: it indicates that what may appear to be individuals returning to work after not being eligible for DI may instead be individuals returning to the labour force, but unable to find suitable employment. In Chapter 2, I examine whether searching for health information on the internet acts as a complement or substitute for the demand for information from physicians (proxied by physician visits). I found that the effect on physician-based information hinged on an individuals prior trust in the formal medical sector: those with high prior trust tended to use health information searching on the internet as a complement for physician visits, whereas, those with low prior trust substituted away from physician visits in favour of information found online. The results were very similar when a telehealth program was examined instead of internet-based information. Further, those who were online health information searchers also tended to be more likely to use a telehealth program. This is a reassuring result, as it may mean that those who substituted out of the formal medical sector, in favour of health online information, may also be using the more quality-controlled telehealth programs. In Chapter 3, I explore how attitudes towards the environment affect behaviours in five key areas of environmental-related household consumption: waste generation and recycling, energy use, organic food consumption, personal transport, and water use. Prior studies have not examined these areas together, often due to data restrictions, and not in the context of environmental attitudes. Using a modelling procedure that allows for the errors in these five areas to be correlated, I found that attitudes were often a more significant predictor of ones behaviour than the financially driven policy implemented in the area.

Everyday Landscapes: Picturing Places of Labour, Leisure, and Industry in Quebec's Eastern Townships, 1900-2015 - Beaudoin, Caroline (Concordia University, 2017)
Focusing on the Eastern Townships area of Quebec, this dissertation attends to the complex values that can be assigned to landscape as visual representation, and to landscape as place. The case-studies, beginning at the turn of the 20th-century, consider landscape in relation to a broad network of social relations and cultural meanings. Section I of the thesis starts by examining paintings and illustrations of loggers by F.S. Coburn as a way to address the logging industry in the Eastern Townships, and to consider the presence or absence of labour in landscape representation. Section II concentrates on early 20th-century postcards of towns, sites of leisure and asbestos mines in the region. I approach these postcards as modern material agents that articulate the everydayness of landscape and place through their imagery, as well as through their usage. Section III comes up to the present day through a discussion of an eco-park in Magog that negotiates the tension between ecological activism and eco-tourism, as the Eastern Townships struggles to achieve a post-industrial identity. Organized into three chronological and overlapping sections that span 115 years of one region's history, the thesis develops an approach to landscape that is both art-historical and interdisciplinary. This study builds on recent scholarship within Canadian art history that challenges the association of landscape art with a myth about the country’s uninhabited wilderness; the region's landscapes studied here are inhabited, and imbued with rural, industrial and bilingual histories. The visual culture methodology deployed here means that canonical modes of artistic landscape representations are addressed relative to landscape images circulating on postcards, newspaper and book illustrations, documentary photographs, a labour recruitment booklet and an ecopark's website for example. The theoretical and scholarly foundation of this thesis has been constructed by drawing on discussions of landscape by art historians, but also by sociologists, geographers, anthropologists, and philosophers. It is this interdisciplinary breadth that allows landscapes to be regarded as sites of everyday human interactions, that inevitably intersect with collective, commercial and political motives, and with cultural ideals, interests, and values. The writings of Henri Lefebvre on the value of the everyday have been important for this thesis, as has his critique of capitalist practices of labour and leisure. Another key author is Félix Guattari who was also highly critical of capitalism, while turning his attention to the state of the world's post-industrial ecology. Likewise, this thesis calls attention to the role of capitalist initiatives in the production of everyday landscapes. This analysis of diverse landscape images is meant to shed light on the Eastern Townships' complex identity as it transitions from a former industrial modern era to its current post-industrial phase. This thesis asks what the term landscape has come to imply measured against social tensions relating to class differences, or economic and environmental imperatives, and how its range of meanings can encompass territory, property, picture, place, and environment.
See also this summary: https://quescren.concordia.ca/en/search?page-len=1&sort=score&page=65&all=labour

Reds in Beds: The Communist Party of Canada and the Politics of Reproduction, 1920-1970 - Beswick, Lorne (Queen's University, 2017)
In the early twentieth-century, the Communist Party of Canada (CPC) initially hesitated to discuss the politics of reproduction as a means of easing material inequity for women and men of the working class. Nevertheless, over five decades, this topic appeared often in the CPCs official and unofficial publications, illustrating a sustained interest in the taboo subject. My thesis draws upon archival materials, communist and mainstream newspapers, and medical periodicals to survey contemporary opinions of birth control, abortion, eugenics, juvenile delinquency, venereal disease, and state medicine. Using the lens of left-politics, these topics are contextualized with reference to the extant literature on the histories of politics, sex, reproduction, labour, and medicine in Canada and beyond. Far from being confined to a few secretive individuals, the militant left engaged a dense network of activists who took stock of the social as well as physical reproduction of the nation. Often their interests appeared indistinguishable from the mainstream, and occasionally overlapped with those of their right-leaning opponents. The CPC unfailingly argued for an understanding of sex and reproduction that reflected its Marxist worldview. Some multi-generational discussions were so durable that they would outlast and outgrow the militant left to emerge within the rhetoric of a multitude of Canadian liberation groups by the late sixties and early seventies. I argue that investigation of the politics underwriting the ideas of the CPC and its ideology of a healthy, socialized body politic, elucidates complexities in the formation of mainstream Canadian approaches to sex, reproduction, and health.

The Workers’ War: The Character of Class Struggle in World War II - Bjorge, Mikhail (Queen's University, 2017)
This dissertation explores the nature of workers’ self-activity during World War II and the ensuing responses to these actions by the state and capital. A close examination of wartime strikes demonstrates that top-down efforts by unions to operate within normative industrial relations were generally failures. Far more likely to be effective were democratic strikes, generally illegal, called from the shopfloor. The Workers’ War further illustrates that while the government passed incredibly coercive legislation to control labour, such legislation failed to have a significant impact. Even where it was most influential and targeted it was eventually beaten through direct action. Even Japanese Canadian forced labour in work camps with armed guards, undertook effective strikes. Largely interested in institutional and legislative changes, the unions, far from being a militant force, spent much of their energy trying to stop or curtail strikes. This thesis contends that the concretion of industrial legality in Canada was imposed to control effective action. Rather than breaking unions of their militancy, the dearth of a state terror apparatus necessitated the creation of compulsory bargaining legislation. First, it argues that the creation of the modern industrial relations regime that forms the foundation for modern labour law was the result of effective workers’ action rather than militant unions. It further shows that the repressive apparatus of the state was unable to control workers, necessitating a structural adjustment. In a larger sense, this thesis argues that this story is at the centre of the history of capitalism in Canada. The imposition of capitalist social relations on the geographies that become Canada had the transformation of land into capital via labour at the very core of its project. Controlling labour was a central concern, and the manner in which labour relations were consolidated was a reflection of a negotiation between labour, capital, and state- a manifestly unequal negotiation that largely failed to reflect the interests of workers.

Understanding the Neoliberalization of Education Through Spaces of Labour Autonomy - Bocking, Paul (York University, 2017)
In recent years K-12 school systems from New York to Mexico City to Toronto, serving vastly divergent students and communities, have been subject to strikingly similar waves of neoliberal policies by governments. A key manifestation has been the de-professionalization or deskilling of teachers. Organized labours response has been highly uneven geographically. Professional autonomy means a capacity and freedom of teachers to exercise their judgement in interpreting broad curriculum guidelines, into their day to day classroom activities. It is the primary obstacle to the further neoliberalization of education. The expansion of standardized instructional and evaluative techniques and technologies are necessary for opening new markets within schools and for weakening the collective power of teachers and their unions. Their proponents are limited by the existence of the classroom as a space of labour autonomy, run by experienced and highly educated teachers. Recognizing the significant crossover of policy at the North American scale alongside significant economic and political linkages, this dissertation centres on case studies in three cities, New York, Mexico City and Toronto. This dissertation assesses challenges to teachers professional autonomy from 2001 to 2016 across five dimensions of comparison. First are changes in governance, namely the centralization of authority, often legitimized by mobilizing policies from elsewhere. Second are policies which have shifted workplace power relations between principals and teachers, as with School Based Management programs that download budgetary, discipline and dismissal practices to school administrators. Third are the effect of standardized testing of students and teachers on the latters capacity to exercise professional judgement in the classroom through designing unique lesson plans, pedagogy and evaluation. Fourth is the creation of school choice for schools competing for enrolment and thereby funding, which has tended to perpetuate class and racial segregation. Finally, the ability of teachers unions to construct a multi scalar strategy is considered, including alliances with parents, communities and other sectors of labour. This dissertation concludes with recommendations for how teachers unions could respond to the challenge to professional autonomy with a stronger engagement on teacher practice and professional self-regulation.

Harvest Histories: A Social History of Mexican Farm Labour in Canada since 1974 - Calnitsky, Naomi (Carleton University, 2017)
While concerns and debates about an increased presence of non-citizen guest workers in agriculture in Canada have only more recently begun to enter the public arena, this dissertation probes how migrant agricultural workers have occupied a longer and more complex place in Canadian history than most Canadians may approximate. It explores the historical precedents of seasonal farm labour in Canada through the lens of the interior or the personal on the one hand, through an oral history approach, and the external or the structural on the other, in dialogue with existing scholarship and through a critical assessment of the archive. Specifically, it considers the evolution of seasonal farm work in Manitoba and British Columbia, and traces the eventual rise of an “offshore” labour scheme as a dominant model for agriculture at a national scale. Taking 1974 as a point of departure for the study of circular farm labour migration between Mexico and Canada, the study revisits questions surrounding Canadian views of what constitutes the ideal or injurious migrant worker, to ask critical questions about how managed farm labour migration schemes evolved in Canadian history. In addition, the dissertation explores how Mexican farm workers’ migration to Canada since 1974 formed a part of a wider and extended world of Mexican migration, and seeks to record and celebrate Mexican contributions to modern Canadian agriculture in historical contexts involving diverse actors. In exploring the contexts that have driven Mexican out-migration and transnational integration, it bridges oral accounts with a broader history that sets Mexican northward migration in hemispheric context. It reads agricultural migration upon various planes, including corporeality, experience, identity, masculinity, legality, “contra-modernity,” and the management of mobilities.

The Impact of a Living Wage from the Perspectives of Workers - Cameron, Melissa (McMaster University, 2017)
The focus of this research is the economic, social and health impacts of a living wage for employees in Ontario who were previously earning less than a living wage. The living wage is a calculation based on how much it costs for a family to live in a specific region. The rise of living wage campaigns is a response to the prevalence of low wage work. This research explains the significance of a living wage from the perspectives of workers compared to current research which concentrates on labour market impacts and how this policy affects businesses. Lived experience is emphasized as an important type of knowledge by including the voices of workers through qualitative interviews. Their experiences highlight how low-income and precarious work can affect workers’ lives and how the living wage addresses these problems. Their experiences also demonstrate how a living wage is a vast improvement from the minimum wage but also reveal the shortfalls of the current living wage framework. Overall, the living wage has a significant impact on the economic, social and health aspects of living wage workers, but falls short as an all-encompassing solution for achieving a decent standard of work. Issues such as unaffordable housing, high tuition costs, lack of job opportunities for young workers and precarious work all contribute to an insufficient living wage. These types of social policies from governments and decent work provided by employers need to assist the living wage in achieving a good standard of living for all workers.

Race, Labour, and The Architecture of White Jobs: Chinese Labour in British Columbia’s Salmon Canning Industry, 1871-1941 - Eeg, Devin Ainsworth (University of British Columbia, 2017)
Chinese migrant workers in North America have typically been regarded in two ways by historians: either as competitive threats to white workers, or as workers isolated within ethnic niches. Few scholars have examined cases where Chinese workers complemented or supported the labour of others. This thesis looks at Chinese labour in British Columbia’s salmon canning industry between 1871 and 1941, arguing that Chinese workers were foundational to white fishing jobs in the province. Drawing on company records, Government reports, newspapers, and oral interviews, I examine Chinese manual labour, labour politics, and wages as three areas where Chinese workers upheld the labour of fishers in a nominally “white” industry. As such, this thesis offers a different outlook on the structural entanglement of race and labour in British Columbia in the seventy years after the province joined the Canadian Confederation.

White Nepotism: Interrogating "Corporate Culture" in the Toronto Census Metropolitan Area Labour Market - Fraschetti, Michael Steven (York University, 2017)
This research project examines systemic forms of racism that limit the employment chances of racialized workers in the Toronto Census Metropolitan Area (CMA) labour market. Through a situated analysis of racialized workers, institutional actors, and public policies, I explore the nuances of racialized individuals encounters with discriminatory hiring practices and job promotion procedures that exist in the labour market. Through the perspectives of racialized workers lived experiences, and by bringing into question the employment practices of hiring managers and human resource personnel, this project addresses the following key questions: 1) How do racialized workers negotiate their movement through places of employment in the Toronto CMA? 2) How might we understand the operation of racism in hiring practices and what are the mechanisms under which it remains institutionally entrenched? This research critiques the organizational cultures of private companies that are configured as spaces of whiteness.

Diamonds are Forever: A Decolonizing, Feminist Approach to Diamond Mining in Yellowknife, Northwest Territories - Hall, Rebecca Jane (York University, 2017)
This dissertation examines the impact of the development of diamond mines in the Yellowknife region, Northwest Territories (NWT), asking two questions: how has the diamond-mining regime affected the gendered social relations in the regional racialized mixed economy? And, how can violence against Indigenous women living in the region be situated in the context of structural shifts in the mixed economy? The analysis developed in response to these questions is informed by a theorization of the mixed economy as a dynamic set of social relations characterized by tension between the temporal imperatives of capitalist production and the place-based imperatives of subsistence. Taking a decolonizing, feminist political economy (FPE) approach, this dissertation responded to these questions by drawing on documentary analysis, interviews, and talking circles to examine the often invisibilized labour performed by Indigenous women that reproduces the mixed economy. The central contention is that the diamond-mining regime represents a new imposition upon daily and intergenerational social reproduction performed by Indigenous women, an imposition that is sometimes violent, and that is met with resistance. The dissertation unfolds in six substantive chapters. Building on a theoretical and historical grounding offered in chapters one and two, chapters three-five draw on field research to examine shifts in local relations of capitalist production, social reproduction, and subsistence production. The analysis reveals that the Fly-In-Fly-Out (FIFO) diamond-mining regime, itself a spatial articulation of the capitalist separation between (masculinized) capitalist production and (feminized) social reproduction, introduces, or, in some cases, intensifies a nuclear male-breadwinner/female-caregiver structure. Woven through this analysis is an examination of the relationship between structural and embodied violence. Indeed, the structural shifts imposed by the diamond-mining regime characterized in this dissertation as structural violence contribute to Indigenous womens experiences of embodied violence in the Yellowknife region. At the same time, Indigenous women meet these shifts with decolonizing resistance in the form of the day-to-day labours they perform to reproduce the place-based social relations of the mixed economy.

Achieving Equality for Women in Labour and Employment – A Comparative Study of Colombia and Canada - Hernandez, Lina (Western, 2017)
The primary focus of this thesis is to analyze and compare the legal systems enacted to protect working women in Colombia and Canada. This thesis focuses on: the protection of maternity and parental rights; the principle of equal pay for work of equal value; and discrimination in employment (including harassment). This research argues that the legislative and judicial changes made in each country to protect working women have not led to substantive equality for working women. This thesis also argues that there is a gap between international and national standards, thus a law reform is appropriate and needed in both the Canadian and Colombian legal systems to bridge the gap and achieve equality for women in employment. Overall, this thesis provides a holistic understanding of two different legal systems in two different countries, both State parties to important International Labour Organization (ILO) and United Nations Organization (UN) treaties and with the same international goal of attaining equality for women in employment.

"Keeping the Kids out of Trouble": Extra-Domestic Labour and Social Reproduction in Toronto's Regent Park, 1959-2012 - James, Ryan Kristopher (York University, 2017)
This dissertation is an historical ethnography of social reproduction in Regent Park, Canada's first public housing project. Built from 1948 to 1959 as part of a modernist slum clearance initiative, Regent Park was deemed a failure soon after it opened and was then stigmatised for decades thereafter, both for being a working-class enclave and for epitomising an outdated approach to city planning. A second redevelopment began in 2005, whereby the project is being demolished and rebuilt as a mix of subsidised and market housing, retail space, and other amenities. Despite its enduring stigmatisation, however, many current and former residents retain positive memories of Regent Park. Participants in this study tended to refer to it as a community, indicating senses of shared ownership and belonging that residents themselves built in everyday life. This dissertation emphasises the capacity of working-class people to build and maintain community on their own terms, and in spite of multiple and intersecting constraints. To theorise community-building, I begin from the concept of social reproduction: the work of maintaining and replenishing stable living conditions, both day-to-day and across generations. Much of this work is domestic labour unpaid tasks done inside the household such as cooking, cleaning, and raising children. In Regent Park, social reproduction demanded even more of residents: the stability of households was often threatened by dangers and challenges unique to life in a stigmatised housing project, and it was largely left up to residents themselves to redress these. To account for the considerable effort this involved, I propose a concept adjacent to domestic labour that I call extra-domestic labour: unpaid work done outside the household, usually through informal collaboration among members of different households, that is necessary for social reproduction. Extra-domestic labour built community and fostered a territorial solidarity that, I argue, is the primary means through which Regent Parkers developed class consciousness. This was often expressed through emic class categories, which were defined in relation to the locality more so than the workplace, and through which people interpreted their position in the wider social order.

‘A Matter of Principal’: Female Involvement in Politics and Labour at the Lakehead, 1903-1918 - Kirker, Jenna (Lakehead University, 2017)
[This thesis] is an analysis of the role women played in the social, political, and labouring sphere at the Canadian Lakehead (comprised of the twin cities of Port Arthur and Fort William, Ontario – present day Thunder Bay) during the early twentieth century. Through an analysis of the involvement of women in the workforce, strikes, and political organizations, it contends that a parallel narrative of female involvement in the Lakehead’s labouring history exists between 1903 and 1918. During this period, women were involved in advocating for, and giving a voice to, both themselves and their sex in a largely male dominated area and era of influence.

‘Camp Syndrome?’ Exploring Frontier Masculinity in Alberta’s Oil Production Culture: Oil Worker and Sex Worker Perspectives - Landry, Kassandra M. (University of Alberta, 2017)
Research shows that the sex trade flourishes in oil rich regions and economies. However, the connection between these two industries has not been widely studied despite how studies often acknowledge that oil industry workers purchase sexual services. This thesis, therefore, explores how the oil production culture contributes to oil industry workers purchasing sexual services. This research project aims to explore answers to the following research questions: 1) How does the oil production culture contribute to oil industry workers purchasing sexual services; 2) What economic and social aspects of the oil production culture contribute to oil industry workers purchasing sexual services; and 3) What can we learn about the sex trade and the oil industry when using a feminist lens? In addition, this research project draws from literature on masculinity, Messerschmidt’s theoretical work on masculinity, and feminist theory. I used a qualitative exploratory methodology to answer the research questions. In total, I conducted 11 semi-structured interviews, including five oil industry workers and six indoor sex workers. My major findings suggest that there is a strong economic connection between the oil industry and sex trade, as well as that negative views of women, the objectification of women, and the normalization of purchasing sex, are all pervasive aspects of the oil production culture. However, the negative treatment of women within the oil industry seems to be context specific to the oil production culture insofar as I also found there are no significant differences in sex workers’ interactions with oil industry worker clients compared to non-oil industry worker clients. I conclude that the frontier masculinity found in the oil production culture is an expression of masculinity specific to the context of the oil industry. This thesis, then, offers contributions on three main topics: what it is like working in the oil industry; the lifestyle and culture of the oil industry; and the connection Alberta’s oil industry has to indoor sex work.

Making Histories and Narrating Things: Histories of Handmade Objects in Two Indigenous Communities - MacDonald, Katya Claire (University of Saskatchewan, 2017)
Building on and deepening my existing community-engaged research relationships with community members in Sliammon, B.C. and Ile-a-la-Crosse, SK, this dissertation is, as I described it to community members, a history of handmade items. At the intersection of economic change, changing colonialist policy, ideas about tradition, and Indigenous political interests that has taken place in Indigenous communities in the latter half of the twentieth century, seemingly local or domestic objects in fact highlight complexities within and beyond communities over time. The role of objects was shaped – in conflicting or paradoxical ways – by newcomer institutions that sought to define Indigenous people and their activities in constrained ways. Yet for community members, the processes and products of making things became ways to define and historicize tradition itself. These two themes – objects in families and communities, and objects in newcomer institutions – provide the overarching structure for this dissertation. People in both communities have shared in parallel processes of using and co-opting colonizing influences not only to make a living for themselves within those contexts, but also, through their involvement in “making things,” to make explicit statements about the significance of histories and historical interpretation in community changes. This dissertation, and the individual and collective experiences of making things portrayed within it, are a means of discussing how labour, gender, and tradition have been mobilized in Ile-a-la-Crosse and Sliammon in the twentieth century, and especially from the 1930s and onwards to respond to contemporary realities. Because the communities I have worked with are very different places from each other – a small, west coast First Nation and a predominantly Metis municipality in northwestern Saskatchewan – this work is intentionally not comparative. Rather, I use these two case studies to follow how community members have interpreted their histories through processes of making tangible “things,” depending on local historical circumstances. I consider the changing ways that community members have responded to and worked within colonial intervention. First and foremost, though, by making things, they sought to address their own economic, social, and political concerns. Changes in processes of making and interpreting handmade items help to illuminate how community members envisioned objects in their communities, not only as practical items or symbols of cultures or histories, but also as ways to describe the shifting significance of tradition for making sociopolitical arguments illustrated by the objects themselves.

De la grève de l'amiante au lobby pro-chrysotile : la question de l'amiante chez les syndicats québécois de l'amiante, 1973-1983 - Marier, Micheline (Université de Montréal, 2017)
Au début des années 1970, les travailleurs de l'amiante de Thetford Mines et d'Asbestos ont entrepris un combat pour assainir leurs milieux de travail et leurs villes, dans lesquelles les mines étaient imbriquées. À Thetford Mines, ils ont mené une longue grève de sept mois et demi qui a conduit à la mise sur pied du Comité d'étude sur la salubrité dans l'industrie de l'amiante, puis, avec l'élection du jeune Parti québécois, à la Loi sur la santé et la sécurité du travail qui introduisait les principes de l'élimination des dangers à la source et de la participation des travailleurs à son application. La crédibilité de leurs syndicats s'en trouvait renforcée. Mais bientôt la montée d'un mouvement international visant à bannir l'amiante et la crise économique du début des années 1980 allaient porter un dur coup à l'industrie et entrainer un déclin que rien ne pourrait arrêter. Les travailleurs miniers, qui s'étaient unis contre leurs employeurs et parfois contre l'État dans leur combat pour la santé, s'allièrent dès lors à leurs entreprises et aux pouvoirs publics pour promouvoir le minéral et tenter de préserver leurs emplois et la vitalité de leurs régions. Ils n'ont jamais envisagé l'arrêt de la production d'amiante car ils ont toujours considéré qu'il est possible d'en maitriser les risques et ils défendirent bec et ongles leur produit en arguant du caractère sécuritaire de ses utilisations modernes, malgré un consensus international grandissant à l'encontre de cette thèse.
https://doi.org/1866/18334

Rogues Among Rebels: Entanglements between Irish Catholics and the Fishermen’s Protective Union of Newfoundland - O'Flaherty, Liam Michael (Simon Fraser University, 2017)
This thesis explores the relationship between Newfoundland’s Irish Catholics and the largely English-Protestant backed Fishermen’s Protective Union (FPU) in the early twentieth century. The rise of the FPU ushered in a new era of class politics. But fishermen were divided in their support for the union; Irish-Catholic fishermen have long been seen as at the periphery—or entirely outside—of the FPU’s fold. Appeals to ethno-religious unity among Irish Catholics contributed to their ambivalence about or opposition to the union. Yet, many Irish Catholics chose to support the FPU. In fact, the historical record shows Irish Catholics demonstrating a range of attitudes towards the union: some joined and remained, some joined and then left, and others rejected the union altogether. Far from being beholden to the whims of clerics, political elites, or the structural dictates of the economy and of region, Irish-Catholic fishermen made their own decisions about membership. Nevertheless, the pressures of class and ethno-religious solidarities mediated their decisions to engage with the union. This thesis uses a combination of newspaper sources, church correspondence, oral histories, censuses, and election data to unearth the history of Irish Catholics’ complex relationship with the FPU, and argues that this relationship is an example of the entanglements of ethnicity and class in pre-Confederation Newfoundland.

The Effect of Lack of Citizenship on the Wages of Low-Skilled Non-Permanent Resident Workers in Canada - Palacio, Nelson Mauricio (Ryerson University, 2017)
This dissertation explores the effects of lack of citizenship on the wages of low-skilled Non-Permanent Residents (NPRs) in Canada—a category that includes temporary foreign workers, refugee claimants, and people with temporary resident visas on humanitarian grounds. The dissertation uses the 2006 census and quantitative methods (cross-tabulation and regression analysis) to evaluate wage differences between low-skilled workers without citizenship and low-skilled workers with citizenship or permanent resident status. Differences are calculated at the industry sector level and occupation level. The analysis further considers a set of intrinsic characteristics of low-skilled workers (including sex, level of education, official language ability and country of birth) and their occupations (provincial location, rural/urban setting). Empirically, this dissertation confirms that there is a penalty attached to lack of citizenship for low-skilled workers. In absolute terms, low-skilled NPRs earn low wages. In relative terms, these NPRs earn less than both the Canadian-born and immigrants low-skilled workers employed in the same occupations. Among low-skilled NPRs themselves, the Canadian labour market exhibits a hierarchy of wages and labour experiences on the lines of workers' country of birth, province of residence, and rural/urban place of work. Among low–skilled workers born in the same country, wages improve when either citizenship or the rights attached to permanent residence are acquired. From a policy perspective, the dissertation identifies the policy origins and drivers of low wages among low-skilled non-citizens. The thesis makes the case for the relevance of quantitative outcomes analyzed through a critical social lens. From a theoretical perspective too, the dissertation also shows how the state as a biased broker (towards capital) facilitates the implementation of non-citizenship as a means to accessing cheap labour.

Racial Extractivism: Neoliberal White Settler Colonialism and Tar Sands Extraction - Preston, Jennifer Lauren (York University, 2017)
This dissertation traces the reoccurrence of logics which attempt to justify white settler occupation and the extraction, theft and harm of Indigenous lands and life in the Athabasca region and in relation to the extraction, transportation and marketing of bitumen. By tracing the entrenchment of notions of white entitlement to land and life in this context, the repetitiveness of normalized epistemic and ontological colonial violence comes into view as just as much a part of the contemporary neoliberal moment as it was during the founding of the nation-state. The Athabasca region is home to the worlds second largest deposit of oil and is being aggressively extracted despite being an unconventional oil source that requires massive amounts of energy, water, toxic chemicals and irreversible environmental damage to extract. Herein, historical narratives of empire and nation-building are examined and linked to extractive industries over time, first within a colonial mercantilist economy, then within a capitalist economic structure and finally within the contemporary neoliberal context. The relationships between private capital and the white settler government are explored as deeply interconnected and as mutually involved in the creation and maintenance of normalized white settler colonialism. Furthermore, the dissertation examines the extractive practices of white settler colonialism as always already informed by logics of white supremacy, and develops the concept of racial extractivism as a theoretical lens through which race, racism and racialization as well as colonialism may be centered in studies of resource extraction and nation-state building. Influenced by Cedric Robinsons (1983) theorization of racial capitalism, racial extractivism contributes to studies of political economy, settler colonialism, and to cultural studies and is utilized in analyzing the more regionally specific context of tar sands extraction and the contemporary discursive strategies supporting it and marketing it domestically and internationally. Lastly, the project examines neoliberalism and the securitization of the industry and attempts to think about racial extractivism intersectionally, as white settler state power combines with the forces of private oil and gas companies to discursively and affectively normalize ongoing colonial violence.

Russell: Government, Labour, and Business Progressivism in a Canadian War Industry, 1899-1920 - Pritchard, Kyle (University of Guelph, 2017)
In May 1919, businessman and former munitions manufacturer Thomas Russell was brought before the Royal Commission on Industrial Relations (Mathers Commission) to provide insight into the largest collection of strikes in Canadian history. Russell was one of Canada’s pioneering automakers, first employed as general manager of the Canada Cycle and Motor Co. (CCM) and later as vice-president when the company was reorganized to become the Russell Motor Car Co. (RMCC). Russell had been actively engaged in business and political discourse for nearly two decades and played a leading role in implementing industrial reforms during the First World War. The RMCC became the largest private producer of shell fuses in Canada and employed one of the country’s largest female workforces. While these progressive reforms increased the productivity and profitability of munitions manufacturers, they had been implemented with little regard to their dramatic transformation of wartime labour conditions. As the war came to a close, Russell suspended his seemingly “progressive” program in favour of protecting his companies’ enormous late war profits. When asked what he believed to be the cause of labour unrest, he told the Mathers Commission that the strikes were not the fault of employers’ wartime industrial policies, but rather an unavoidable “natural desire for betterment” among dissatisfied workers and the unemployed. Contrary to Russell’s testimony, employers were very much responsible. This project explores the origins of progressive ideals in Canadian business at the turn of the 20th century and their impact on industrial reform during the First World War. As war manufacturers, business progressives failed to address the devastation their industries caused in the post-war period. Their post-war factory closures and reluctance to compromise with the growing labour movement substantially contributed to the outbreak of the 1919 labour revolt and fueled future advocacy for government intervention in the Canadian economy.

Claiming the Road: Intersectional Mobilities and Unfreedom among Migrant Farmworkers in Canada - Reid-Musson, Emily R. (University of Toronto, 2017)
This study considers the travel patterns, practices and conditions that shape how migrant farmworkers circulate in rural southwestern Ontario. While migrants in Canada’s Seasonal Agricultural Worker Program (SAWP) do not exercise occupational mobility and are housed in employer-provided accommodations, they are otherwise legally entitled to circulate freely in Canada. In practical terms, however, most experience significant mobility barriers. The study investigates the mechanisms by which migrant farmworkers are confined and immobilized to farm spaces on systemic levels, contributing to a vein of research on the immobilities that pervade everyday life for transnational, low-wage labour migrants. I show how localized mobility controls placed around migrants as well as inadequate transportation create a “mobility fix” for farm operators and state actors. Technologies of confinement that immobilize migrant farmworkers are justified through racial and sexual ideologies about migrants being a threatening presence in rural Canada, while permitting high levels of value to be extracted from migrants’ labour. The dissertation is organized as three empirical journal articles which are preceded by a chapter on research methods. In the first article I document how a purported problem with transient farm labour migration to Ontario from Quebec and Atlantic Canada was constructed in the 1960’s and 1970’s. In response, the Canadian government devised the SAWP as an institutional mechanism to undercut transnational migrants’ constitutional and practical mobility rights, rights that transients harnessed. This chapter reveals how enacting controls around migrants’ local mobilities has been crucial to the “making” of migrant agricultural workforces in Canada. In the second article I identify how systemic immobilities for SAWP workers are enacted by Canadian family farm operators. I show how Canadian family farms benefit from high levels of personal and intimate interaction with SAWP employees. I identify how operators impose high limitations and constraints as to when, where, and how migrants can travel beyond formal work hours. Finally, the third article examines how migrants have forged bicycling geographies in rural places and how migrant bicyclists are perceived in Canadian communities. Migrants are more vulnerable as bicyclists, do not bike out of choice, and have become subjects of bike safety education. I argue that racial and economic forms of exploitation as well as socio-spatial exclusions inflect actually existing bicycling geographies.

Class Struggle, the Communist Party, and the Popular Front in Canada, 1935-1939 - Schoots-McAlpine, Martin (Trent University, 2017)
This thesis is an attempt to provide a critical history of the Communist Party of Canada (CPC) during the Popular Front era, roughly November 1935 to September 1939. This study contains a detailed examination of the various stages of the Popular Front in Canada (the united front, the height of the Popular Front, and the Democratic front), with special attention paid to the CPC’s activities in: the youth movement, the labour movement, the unemployed movement, the peace movement, and the anti-fascist movement. From this I conclude that the implementation of the Popular Front, the transformation of the CPC from a revolutionary party to a bourgeois party, was not a smooth process, but instead was punctuated and resisted by elements within the CPC in what can be considered a process of class struggle internal to the CPC itself.
Keywords: Canada; Communism; Great Depression; Labour; Popular Front; Social sciences; Socialism

A Critical Literature Review of the Impact of Precarious Work on the Mental Health of Immigrant Women in Canada - Umaigba, Karina (York University, 2017)
This critical review draws on existing literature on the discourse of precarious work within the Canadian nation-state. The goal of this research work is to critically examine the impact of precarious work on the lives, well-being and mental health of immigrants with a specific focus on immigrant women. Given that most research works have been mainly focused on the way in which precarious work creates health inequalities, this paper aims to throw light on the way in which precarious work can affect mental health. Also, the paper will examine the Canadian public policy response to this issue. The paper argues that Canada’s policy response is a reflection of the dominant political ideology within this nation-state. The dominant political ideology of neoliberalism seeks to justify minimal state intervention in policies that directly affect health and more broadly citizen’s life. The following principal questions will guide this critical review. 1) Why are immigrants, particularly immigrant women of color disproportionately situated in precarious forms of labour within the Canadian nation-state? 2) How does precarious work affect the mental health of immigrant women? 3) How and to what extent has capitalism and neoliberalism within the Canadian nation-state helped to perpetuate precarious working conditions for racialized immigrant women? By interrogating Canada’s neoliberal policy agenda as it affects immigrants through entrenched legislations of immigrant classes, the primary goal of this paper is to advance the construction that immigrants/migrants exist for economic exploitation and gain. The main theoretical framework that will guide this analysis is based on a post-colonial feminist scholarship that analyzes how inequities grounded on gender, race, class, and migratory status intersect to create complex and diverse labour market results for racialized immigrant women in Canada. A common theme that emerged throughout the critical review of several scholarly and grey literatures is that more women than men are situated in precarious work, and of those women in precarious forms of employment, women who identified as members of a visible minority group were even more disproportionately situated in precarious forms of work. Also, it was observed that the Canadian nation-state has to date failed to respond appropriately to this social and economic situation. Since employment and working conditions, unemployment and employment security – described as some of the most crucial social determinants of health – are significantly correlated to income and its security, allowing precarious work has only served to reinforce high-levels of income inequality, income insecurity and poverty within Canada.

Divided Loyalties: A Study of a Communist-Led Trade Union’s Struggle For Survival in Trail, British Columbia, 1943-1955 - Verzuh, Ronald William (Simon Fraser University, 2017)
[E]xamines a Communist union’s struggle to survive in the post-Second World War environment of anti-Communism and anti-trade unionism that marked one of the most violent periods in the history of the Canadian labour movement. In 1943, Local 480 of the International Union of Mine, Mill and Smelter Workers in Trail, British Columbia, was nearing the end of a six-year battle for certification as the legal bargaining agent for about 4,000 smelter workers. After it achieved that goal the following year and for the next decade, it faced new battles with the employer, the powerful Consolidated Mining and Smelting Company of Canada (CM&S) with its paternalistic president S.G. Blaylock. The local also faced an array of other opponents: a workforce suspicious of a Red-tainted union with a radical past, a company union that had been established by Blaylock after the First World War, a company-loyal newspaper, and a divided community situated in the rural West Kootenay district near the Canada- United States border. Among the local’s most vigorous adversaries were the local churches, the federal government with its secret service police, and the Canadian Congress of Labour (CCL). By the 1950s, it had been purged from the CCL, shunned by the Cooperative Commonwealth Federation (CCF), and victimized by cold warriors bent on its destruction. To survive it needed to win the support of a substantially immigrant workforce with a strong alternative culture to the dominant Anglo-Saxon one. It had to address the concerns of the hundreds, perhaps thousands, of women war workers who had been hired at lower wages to replace enlisted men. And it fell into the middle of an ideological clash between the region’s two dominant left-wing political parties. Its greatest strength and potential weakness was an unabashed Stalinist named Harvey Murphy. He had been a fugitive from justice and was incarcerated in a war-time internment camp as a threat to national security, but he became an influential leader of the provincial labour movement and an outspoken advocate of workers’ rights who was hated by some and respected by others. “Divided Loyalties” begins with a victory, but Local 480’s survival for the duration of the twelve-year period of this study was far from assured.

"Something to Just Hold On To": Occasional Teaching and Collaborative Inquiry in Precarious Times - Walkland, Tyler Andrew (University of Toronto, Ontario Institute for Studies in Education, 2017)
This thesis is the product of a collaborative inquiry involving six occasional teachers, myself included, who came together over five months to share our experiences of navigating a teacher labour market ruled by teacher surplus, job shortages, and increasing employment precarity. Together we took an inquiry stance on occasional teaching (Cochran-Smith Lytle, 2009) and explored the consequences of precarious teacher employment for teaching, learning, working, and living. Here I document the myriad ways precariousness shapes not only our career trajectories but also our everyday experiences of practice, our professional identities as educators, and our engagement in political action and institutional change efforts. I also offer specific processes and interventions that mitigate the risks of long-term employment precarity for teaching and learning. Throughout, I rely on my participantsâ words as well as my own to tell a story about our work, what it means to us, and why it matters.

Temporary Employment Agencies in Ontario: Experiences of South Asian Immigrant Women - Aujla, Navneet (York University, 2016)
Informed by the feminist political economy perspective (FPE), this study examines the experiences of recent South Asian immigrant women working through temporary employment agencies in Ontario, paying particular attention to how social factors such as gender, race and immigrant status shape these experiences. As FPE pays attention to the interconnection between family, state and market, the study examines how women experience precariousness at work, within the household, and trying to settle and integrate. Based on analysis of twelve qualitative interviews and observations as a participant-researcher, findings indicate that recent South Asian immigrant women are funneled into agency work due to a variety of structural barriers, and that the lack of rights associated with agency work leaves them particularly vulnerable to exploitation and poverty. As such, it is proposed that changes must address a lack of security and enforcement of employment standards, and barriers to employment for women and recent immigrants.

La Babylone des marins : Marins hauturiers à Montréal 1851-1896 - Bélisle-Desmeules, David (Université de Montréal, 2016)
Le port de Montréal connaît un essor considérable dans la seconde moitié du 19e siècle. Des travaux de dragages en font une destination importante pour les navires transatlantiques qui visitent le port durant la saison de navigation. Ainsi, de mai à novembre, un grand nombre de marins qui œuvraient sur ces navires faisaient escale en ville. Cet essai s’intéressera à ces marins hauturiers de la marine marchande, qui représentent durant leur passage dans la métropole un groupe distinct tenu aux bords de la société coloniale montréalaise, durant leur passage dans la métropole. Les marins, physiquement présents au cœur même de la cité, sont pourtant considérés comme des êtres périphériques, attirant l’attention de la presse et de l’opinion surtout lorsqu’ils transgressaient les normes sociales. Nous décrirons une partie de leur activité à terre à partir de trois lieux du front portuaire que sont les bassins du port, témoins de noyades et de sauvetages, les quais adjacents, où le vol de marchandises est monnaie courante, et finalement la taverne du bord de l’eau, où les marins vont boire. Leurs comportements liminaux comme la consommation abusive d’alcool et la bagarre ainsi que leur proximité avec les classes laborieuses indigènes, font d’eux des suspects facilement amalgamés aux « classes dangereuses ». Les marins posent un défi à la bonne marche du commerce maritime. Ils forment un groupe hautement surveillé par les autorités. Une force spéciale, la Montreal Water Police, est d’ailleurs mise sur pied à cet effet le temps de la saison de navigation. En effet, les conflits que les matelots entretenaient avec leur capitaine, qui se soldaient parfois par des désertions ou des procès minaient la bonne marche des affaires. Cependant, les autorités tentèrent tout au long de la période de policer le marché de l’emploi maritime, volatil et violent, géré par un groupe d’embaucheurs (crimps), intermédiaires interlopes dont les marins sont à la fois les bénéficiaires et les victimes. Finalement, on avancera que, durant la seconde moitié du 19e siècle, la présence des marins a fait du front portuaire de Montréal un lieu qui s’apparente à un sailortown, espace à la fois physique et symbolique où s’exprime la culture maritime à terre.

Competition or Liberation? Implications of Labour Automation in the Context of Cognitive Capitalism - Burgess, Russell (Carleton University, 2016)
Technologies in the first half of 21st century are developing new abilities to perform autonomously and compete with humans directly in more and more tasks, opening up the future possibility of increasing labour substitution. Using the theory of Cognitive Capitalism to examine advanced economies as the most recent form of capitalism shows that in the modern economy work is increasingly central to the lives of individuals due to new cognitive labour which requires more worker engagement than industrial labour. This requirement has strengthened the direct coercive mechanisms of the increasingly precarious wage relationship and weakened alternate income sources. This dissertation argues that automation in this context could be harmful to individuals required to depend on work to survive and evaluates three policy options against the goal of freeing individuals from this institutional constraint to work so that they can continue to fully and freely participate in society if widespread automation occurs.

Invisible Worker(s), Invisible Hazards: An Examination of Psychological and Physical Safety Amongst Frontline Workers in Long-term Residential Care Facilities in the 'New' Global Economy - Campbell, Andrea Lynn (York University, 2016)
Research has consistently demonstrated that the long-term residential care (LTRC) frontline workforce encounters a range of serious health and safety hazards and risks that result in physical and psychological injury, illness, absenteeism, and related costs. Using the lens of feminist political economy, this dissertation explores the risks workers encounter on the frontlines of LTRC, how these workplace risks are shaped by broader social, economic, political, and historical factors, as well as the ways frontline workers resist, challenge, or shape the conditions of their work in this setting. My analysis of primary data is informed by interviews with 17 frontline workers working within for-profit, non-profit, and municipal LTRC facilities within Ontario and 2 key informants. Restructuring and reform of health and social care services under neoliberalism have profoundly transformed the character, funding, organization, and delivery of LTRC. These changes have serious implications for workforce configurations, the conditions of work and care, workplace health and safety, worker control over their labour, and capacities for worker resistance to the conditions of their work. Within the LTRC organizational hierarchy, frontline workers are of marginal status. The frontline workforce is composed predominately of women and increasingly marginalized immigrants and racialized groups, whose care labour on the frontlines is often naturalized, undervalued, and treated as unskilled and safe. This research provides evidence that restructuring and work reorganization processes, policies, and practices constitute a form of structural violence, which contribute to, intensify, and/or give rise to new sources of struggle, inequity, risk, violence, alienation, and exploitation on the everyday/everynight frontlines of LTRC.

Creative Management: Disciplining the Neoliberal Worker - Cruz, Trent (Western University, 2016)
This integrated article dissertation examines some of the new managerial practices that have emerged to handle cognitive capitalism’s ongoing need for creative, flexible labour power. The three articles included in this dissertation offer a glimpse into the widespread processes employed by management to regulate and discipline a workforce that must also be granted a degree of relative flexibility, creativity, and autonomy in order to be effective under post-Fordist conditions of production. The first chapter looks at the emergence of corporate improvisational training at the turn of the twenty-first century as an attempt to cultivate flexible and innovative workers, a move that ultimately succumbs to what Andre Spicer (2013) calls “organizational bullshit”—the deployment of cynical and self-serving discourse that functions to build confidence and legitimacy within workplaces where a clear sense of occupational purpose is lacking. Chapter two explores the recent trend of workplace mindfulness as a specific element of the now-prevalent 'wellness' discourses, which inevitably work to align workers' personal values with those of their employer. The final chapter involves an analysis of the working conditions of voice-over and motion capture actors in the video game industry and the processes of rationalization and neo-taylorization to which they are subjected.

Labour, Heritage, and the Politics of Difference: Working Class History Museums in the Changing City - DesRoches, Davina Marie (Queen's University, 2016)
As a contemporary communications medium, the museum has undergone significant reinvention and reorientation of purpose within the past several decades. While the late twentieth century saw the rise of a fundamental reimagining of the museum as a visitor-oriented space where questions of representation, ownership, and voice were of paramount concern, the early twenty-first century has seen a repositioning of museums as market actors with a role to play in the economic aspects of social life. This dissertation probes the growing disconnect between the rhetoric and practices enacted under the auspices of new museology and the ascendancy of corporatized values, interests, and operational forms in museum praxis. It is specifically concerned with working class history museums located in postindustrial urban environments, and seeks to explore and consider some of the inherent tensions in representing labour struggles and working class heritage in gentrifying, capitalist cities. The dissertation reveals that working class history museums face immense challenges in trying to reconcile being socially progressive and class-oriented while also maintaining relevance and success in gentrifying areas. It argues that these museums are embedded within political economic structures of power, and thus face considerable limitations in their efforts to act as meaningful sites of political or ideological contestation. Furthermore, by subscribing to the supposition that heritage resources can be used to spur gentrification and economic development, museums may unwittingly reinforce elite reimaginings of the urban environment. Three case studies are examined: the People’s Palace, a public museum in Glasgow, Scotland; New York City’s Lower East Side Tenement Museum; and finally, the Écomusée du Fier Monde, a small community museum located in the Centre-Sud neighbourhood of Montréal, Canada.

Mental Health in the Workplace: Unions' Role in Identifying and Combating Psychosocial Hazards - Edelson, Miriam Karin (University of Toronto, Ontario Institute for Studies in Education, 2016)
The world of paid work has shifted extraordinarily in the last several decades. Globalization, technology, lean production, the intensification of work, mergers and reorganizations and precarious work have all meant a toughening of the conditions for workers. Unions organize in these conditions, confronting issues of concern to workers. Very little has been written about the role unions play in trying to protect the psychological health of their members. The major question of this thesis is whether unions are identifying and combating psychosocial hazards in the workplace. The thesis adds to knowledge on this subject by analyzing two data sets. First I conduct an analysis of grey literature on the Internet about psychological health and safety concerns. Second, I explore a series of questions with union health and safety experts representing every major Canadian union from each sector of the economy. The questions probe how unions are dealing with psychosocial risks in the workplace, how unions are organizing resistance and building solidarity. My inquiry also explores the issue of how unions deal with return-to-work for workers who have been absent for mental health reasons. I am not a neutral observer: I write from the standpoint of workers. My work has a practical utility to the degree that it can be directly applied to these real life problems facing health and safety practitioners. It attempts to theorize that which these union specialists should do. It also tries to anticipate some practical problems they may need to solve in future as a result of current health and safety practices. I observe real life phenomena and develop theory around them. One of these is that unions resist employer restraints and power and in so doing bump up against managementsâ right to control production and dictate work organization. In this thesis, I show the fledgling ways in which unions are challenging managementsâ typical rights in the interests of better working conditions. I give evidence of three promising practices that unions are adopting and propose that these may be adapted further for initiatives in other sectors. I argue that workersâ psychological health is one potential winner of these strategies. I also propose that union representatives be educated to deal more empathically with members that are absent for reasons of psychological ill health, in advocating for them when they return and by building solidarity among co-workers.
Accepted: 2017-03-27T23:00:16Z

The Seeds of Divergence: The Economy of French North America, 1688 to 1760 - Geloso, Vincent (London School of Economics and Political Science, 2016)
Generally, Canada has been ignored in the literature on the colonial origins of divergence with most of the attention going to the United States. Late nineteenth century estimates of income per capita show that Canada was relatively poorer than the United States and that within Canada, the French and Catholic population of Quebec was considerably poorer. Was this gap long standing? Some evidence has been advanced for earlier periods, but it is quite limited and not well-suited for comparison with other societies. This thesis aims to contribute both to Canadian economic history and to comparative work on inequality across nations during the early modern period. With the use of novel prices and wages from Quebec—which was then the largest settlement in Canada and under French rule—a price index, a series of real wages and a measurement of Gross Domestic Product (GDP) are constructed. They are used to shed light both on the course of economic development until the French were defeated by the British in 1760 and on standards of living in that colony relative to the mother country, France, as well as the American colonies. The work is divided into three components. The first component relates to the construction of a price index. The absence of such an index has been a thorn in the side of Canadian historians as it has limited the ability of historians to obtain real values of wages, output and living standards. This index shows that prices did not follow any trend and remained at a stable level. However, there were episodes of wide swings—mostly due to wars and the monetary experiment of playing card money. The creation of this index lays the foundation of the next component. The second component constructs a standardized real wage series in the form of welfare ratios (a consumption basket divided by nominal wage rate multiplied by length of work year) to compare Canada with France, England and Colonial America. Two measures are derived. The first relies on a “bare bones” definition of consumption with a large share of land-intensive goods. This measure indicates that Canada was poorer than England and Colonial America and not appreciably richer than France. However, this measure overestimates the relative position of Canada to the Old World because of the strong presence of land-intensive goods. A second measure is created using a “respectable” definition of consumption in which the basket includes a larger share of manufactured goods and capital-intensive goods. This second basket better reflects differences in living standards since the abundance of land in Canada (and Colonial America) made it easy to achieve bare subsistence, but the scarcity of capital and skilled labor made the consumption of luxuries and manufactured goods (clothing, lighting, imported goods) highly expensive. With this measure, the advantage of New France over France evaporates and turns slightly negative. In comparison with Britain and Colonial America, the gap widens appreciably. This element is the most important for future research. By showing a reversal because of a shift to a different type of basket, it shows that Old World and New World comparisons are very sensitive to how we measure the cost of living. Furthermore, there are no sustained improvements in living standards over the period regardless of the measure used. Gaps in living standards observed later in the nineteenth century existed as far back as the seventeenth century. In a wider American perspective that includes the Spanish colonies, Canada fares better. The third component computes a new series for Gross Domestic Product (GDP). This is to avoid problems associated with using real wages in the form of welfare ratios which assume a constant labor supply. This assumption is hard to defend in the case of Colonial Canada as there were many signs of increasing industriousness during the eighteenth and nineteenth centuries. The GDP series suggest no long-run trend in living standards (from 1688 to circa 1765). The long peace era of 1713 to 1740 was marked by modest economic growth which offset a steady decline that had started in 1688, but by 1760 (as a result of constant warfare) living standards had sunk below their 1688 levels. These developments are accompanied by observations that suggest that other indicators of living standard declined. The flat-lining of incomes is accompanied by substantial increases in the amount of time worked, rising mortality and rising infant mortality. In addition, comparisons of incomes with the American colonies confirm the results obtained with wages— Canada was considerably poorer. At the end, a long conclusion is provides an exploratory discussion of why Canada would have diverged early on. In structural terms, it is argued that the French colony was plagued by the problem of a small population which prohibited the existence of scale effects. In combination with the fact that it was dispersed throughout the territory, the small population of New France limited the scope for specialization and economies of scale. However, this problem was in part created, and in part aggravated, by institutional factors like seigneurial tenure. The colonial origins of French America’s divergence from the rest of North America are thus partly institutional.

L’usage par les travailleurs étrangers temporaires des ressources proposées par le droit du travail : une contribution aux études portant sur l’effectivité du droit - Gesualdi-Fecteau, Dalia (Université de Montréal, 2016)
Au Canada, le nombre de travailleurs étrangers temporaires est en forte hausse et ce, depuis 2003. Les travailleurs étrangers temporaires ne disposent ni de la citoyenneté politique, ni de la résidence permanente; leur mobilité professionnelle est restreinte et leur durée de séjour est limitée et prédéterminée. Sur le plan formel, ces travailleurs bénéficient des protections prévues par le droit du travail nonobstant leur statut migratoire. Toutefois, plusieurs travaux ont démontré que les travailleurs étrangers temporaires occupant des emplois qui requièrent un niveau réduit de formation sont généralement moins enclins à dénoncer la violation de leurs droits au travail. Le droit du travail constitue-t-il un rempart utile pour ces travailleurs? À l’aide d’une méthodologie mixte impliquant notamment une enquête de terrain auprès des acteurs-clé, la présente thèse poursuit deux objectifs distincts. Sur le plan empirique, elle permet de mettre en lumière l’incidence du système d’emploi singulier dans lequel s’insèrent les travailleurs étrangers temporaires sur leur usage des ressources proposées par le droit du travail. Le recours à ces ressources n’est pas contingent et prédéterminé; il est inextricablement lié aux opportunités et aux contraintes avec lesquelles ces travailleurs composent. Cette recherche révèle également que les stratégies échafaudées par différents acteurs qui ne sont pas, sur le plan juridique, des parties au rapport salarial, ont une incidence significative sur l’usage du droit par ses destinataires ; leur impact dépend largement du pouvoir dont ces acteurs disposent dans le système d’emploi. Sur le plan théorique, cette thèse s’inscrit dans le champ plus large des études portant sur l’effectivité du droit; elle propose de distinguer entre l’étude des effets du droit et l’analyse de son usage. Elle présente, à cette fin, un cadre analytique permettant de saisir le rapport qu’entretiennent les destinataires avec le droit.
https://doi.org/1866/13502

Geopolitics, State-Formation and Economic Development in Quebec and Ontario - Gheller, Frantz (York University, 2016)
This dissertation challenges the prevailing periodization of Quebec and Ontario’s economic development in Canadian historiography by contrasting the specificity of capitalist social relations with the non-capitalist forms of social reproduction belonging to French Canadian peasants and Upper Canadian farmers in the colonial period. With a few notable exceptions, existing historical interpretations assume that capitalism was there, at least in embryo, from the colony’s very beginning in the guise of the fur trade, manufacturing, or a local bourgeoisie. By contrast, this thesis brings together, through a comparative perspective, different pieces of the interconnected histories of France, Britain, the United States, Ontario, and Quebec in order to show that capitalism did not arrive on the shores of the St. Lawrence River with the first settlers. The dissertation also brings together pieces of the uneven intra-regional histories of these regions, and provides a general reflection on how to systematically integrate the geopolitical dimension of social change into historical sociology, political economy, and comparative politics. As such, the question with which the thesis is concerned is not exclusively that of the transition to capitalism in Quebec or in Ontario, but more broadly the interrelated questions of state-formation and ‘late development’ in north-eastern North America. One of the main findings of the dissertation is that only with the development of industrial capitalism in the north-eastern United States were the conditions for the emergence of capital-intensive types of agriculture in rural areas of Quebec and Ontario put in place. American breakthroughs toward industrial capitalism irrevocably transformed the system-wide conditions under which subsequent agricultural evolution took place in neighbouring regions, generating a new geopolitical configuration in which customary peasant production continued to persist in Quebec alongside petty-commodity farmers in Upper Canada and the development of industrial capitalism in urban areas such as Montreal. These findings bring to the fore the need to directly address the ‘peasant question’ in order to understand the impact of the continued existence of a large peasantry on state-formation and the long-term economic development of Quebec during the period when industrial capitalism was emerging as a dominant feature of the North American economy.

Race, Labour, and the Postmodern Plantation: Jamaican Migrant Farmworkers in Canada's Seasonal Agricultural Worker Program - Hjalmarson, Kirsten Elise (University of British Columbia, 2016)
This ethnographic thesis project critically examines the experiences of Jamaican migrant farmworkers employed in the Okanagan Valley, British Columbia via the Seasonal Agricultural Worker Program (SAWP). First introduced in 1966, the SAWP is the oldest and longest-standing labour migration regime in Canada and the principal agricultural stream of the federal Temporary Foreign Worker Program. Drawing upon the salient work of numerous activists and scholars who have contended that the SAWP facilitates a form of transnational indentureship by bonding migrant workers to their employers, I argue that the SAWP farm site constitutes a peculiar and totalizing institution that capitalizes on the unfreedom of black labour. I apply critical race theory to situate workers’ experiences of surveillance, immobilization, and hyper-exploitation in addition to their characterization of farm life as “prison life” within a postslavery context. I conclude that only by acknowledging the role of racism and its relationship to the border can we ever hope to truly achieve justice for migrant farmworkers in Canada.

Athletic Labour, Spectatorship, and Social Reproduction in the World of Professional Hockey - Kalman-Lamb, Nathan (York University, 2016)
Existing literature in the sociology of sport largely omits any discussion of the relation between the spectator and athlete in professional and high performance sport. This dissertation explores that relation, demonstrating that exploitation in athletic labour and the enduring allure of sport as spectacle are inextricably linked as part of a broader political economy. The labour of professional athletes is theorized as a form of social reproductive labour that offers affective/subjective renewal for fans. Spectators who experience isolation and alienation in their day-to-day lives as capitalist subjects come to sport seeking a sense of meaning, connection, and community. Athletic labour in professional sport provides this to them and enables them to continue to function as productive capitalist subjects by serving as an armature upon which an imagined athletic community of fans can be built. However, for social reproduction to occur for fans, athletes must sacrifice their bodies completely in the performance of their labour. It is only through this sacrifice that the imagined athletic community becomes concretized as something tangible and real and spectators become willing to spend their money on sports fandom. This theoretical understanding of athletic labour and spectatorship is explored through semi-structured qualitative interviews with eight former professional hockey players and eight spectators of sport. The testimony of former players consistently links the political economy of professional sport and the harm and exploitation they experienced in the course of their work. The testimony of spectators, on the other hand, typically fails to acknowledge that the meaning and pleasure derived from watching professional sport is predicated on the destruction of athletic bodies. This study ultimately suggests that a form of alienation exists between athletes and spectators. The spectator grasps for an elusive sense of community within a society structured to deny that form of connection by placing vicarious investment in the bodies of athletes. Yet, this act of investment instrumentalizes and commodifies the athlete. Athletes understand this process as it occurs because it denies them their humanity by transforming them into something both more (the heroic vessel) and less (the abject failure) than human.
Keywords: Exploitation; Hockey; Imagined community; Injury; Interviews; Labor; Labour; Labour relations; Marxism; Masculinity; Political economy; Qualitative methodology; Social reproduction; Social theory; Spectatorship; Sport

Principles and Processes for Food Sovereignty: An Evaluation of the Blueberry Sector in British Columbia - Klassen, Susanna (Susanna Elsie) (University of British Columbia, 2016)
As a concept that has increasingly been invoked in discussions of social and political food systems dynamics, food sovereignty calls for the holistic consideration of human and ecological aspects of agricultural systems with a focus on power and political dynamics. We investigated an export-oriented agricultural production system as a case study to understand how and to what extent food sovereignty principles can be enacted in the context of agriculture in the Global North. The blueberry industry in British Columbia, Canada, is socially and economically significant within a regional food system, and is globally integrated through export and trade. This study employs the framework of food sovereignty by drawing on principles of equity, empowerment and ecology as a methodological tool for assessing food systems, and examines how local producers in the BC blueberry industry are responding to pressures, constraints and opportunities in the global food system. I identified and operationalized key principles and processes for food sovereignty in the form of indicators. I conducted 33 structured interviews with blueberry growers representing a range of scales and modes of production. Significant themes and dynamics related to food sovereignty discussed by growers were: high demands for seasonal labour leading to mechanization; blueberry production as a means to attain a farming lifestyle while supplementing with significant off-farm income; and a perceived lack of power among growers relative to other actors in the food system. Participants expressed reduced decision autonomy through resource constraints and economic pressures. The combination of economic forces and social dynamics that have most growers locked into an industrial production cycle represent a barrier to achieving food sovereignty principles. On the other hand, there were several important institutions in the industry that support and empower growers through democratic participation opportunities, knowledge translation, and field expertise. A significant re-orientation of food systems governance and policy combined with economic re-structuring and social empowerment mechanisms would be needed to approach the realization of food sovereignty principles in the BC food system.

Deindustrialization on the Periphery: An Oral History of Sydney Steel, 1945-2001 - MacKinnon, Lachlan (Concordia University, 2016)
This thesis is an historical examination of the multi-layered processes of deindustrialization in Sydney, Nova Scotia. The history of a steel plant formerly located in the centre of the city is used as a case study through which the mechanisms of deindustrialization are fully explored. In 1967, the provincial government of Nova Scotia nationalized the Sydney Works. This marks a significant divergence from previous studies of deindustrialization, which have traditionally focused on the wave of industrial closures in the North American heartland during the 1970s and 1980s. Framed by oral history accounts of former steelworkers, this dissertation reveals the combined impact of Canadian regionalism, political economy, and working-class cultures of resistance on local experiences of industrial decline. This represents a synthesis between the econo-political historiography of deindustrialization favoured in the 1980s and the cultural/representational approaches of the 1990s and 2000s. The title, “Deindustrialization on the Periphery,” speaks to the specific national and regional contexts that frame the decline of Sydney Steel. The longue durée of economic change on the rural resource frontier has been understudied. In Cape Breton, the devastation wrought by the end of industry has roots that stretch back to the early 20th century. Tracing these through the use of Harold Innis’ “staples trap,” my thesis reveals how deindustrialization stretches from decades before closure to the years after a mine, mill, or factory are shuttered for the last time. Workers and other residents in Sydney continue to face the bodily aftermath of workplace injury, occupational, and environmental illness long after the structures of the plant have been demolished. But so, too, have experiences of working at the mill and living in the neighbourhoods that surrounded its gates created particular forms of culture, solidarity, and identity. My research is more than a eulogy for a defunct steel town. It seeks to expose the tensions between different forms of memory and experience, and to examine how the industrial past remains inextricably connected to the “post-industrial” present.
https://cha-shc.ca/prize-winner/lachlan-mackinnon/

Up-Rooted Lives, Deep-Rooted Memories: Stress and Resilience Among Jamaican Agricultural Workers in Southern Ontario - Mayell, Stephanie (McMaster University, 2016)
The Seasonal Agricultural Worker Program (SAWP) is a transnational labour agreement between Canada, Mexico, and various Caribbean countries that brings thousands of Jamaican migrant workers to Canada each year to work on farms. This thesis explores Jamaican SAWP workers’ experiences of stress in Ontario, and situates these experiences within a system of power and international inequality. When describing their experiences of stress and suffering in Ontario, many Jamaican workers drew analogies between historic and modern slavery under the SAWP. However, stress discourses also inspired workers to emphasise their resilience, and many workers gave equal attention to explaining their inherent strength as “Jamaicans”, which they associate with national independence and the history of slavery. In this way, I suggest stress discourses are sites of flexibility and resilience for Jamaican workers, and this thesis presents the foremost cultural, political, and historical factors that support Jamaican workers’ resilience in Ontario. Moreover, the predominant coping strategies workers employ in Ontario will be explored within the context of their restricted agency under the SAWP. This thesis concludes with a discussion of stress as an expression of subjectivity that is characterised by strength, faith, and the history of slavery.

Dressing Down Migrant Sex Work: The Global Anti-Trafficking Regime, Legal Employment Rights, and Canada’s Temporary Foreign Worker Program - Montiel, Vasti (Toronto Metropolitan University, 2016)
This paper analyzes the contemporary global anti-trafficking regime and discusses the destructive influence this regime has had on the lives of migrant sex workers. Through the use of public documents and academic literature, I deconstruct the global anti-trafficking discourses and argue in favour of more viable rights-based solutions (e.g., labour rights, immigration rights, and sexual rights) for combating human trafficking. Within this analysis, I explore the Canadian government’s gradual commitment to combat human trafficking through the gradual discontinuation of the exotic dancer visa, and eventual implementation of the migrant sex worker ban. In formalizing its commitment to combating trafficking, the Canadian government has implemented restrictive policy measures terminating migrant women’s ability to legally access the Canadian sex industry. While this type of employment was problematic in many ways, the Canadian government should have addressed these issues through rights-based policy initiatives instead of prohibiting access as part of its anti-trafficking campaign

Towards Transformative Solidarities: Wars of Position in the Making of Labour Internationalism in Canada - Nastovski, Katherine Slavka (York University, 2016)
Within the broad debates about neoliberalism, neoliberal globalization and the declining power of unions in the Global North, there has been renewed interest in the possibilities of international and transnational labour solidarity, coordination and action. Drawing from Rebecca Johns (1998) distinction between transformative and accommodationist forms of international labour solidarity I argue that we need to critically assess how these practices challenge or reinforce global divisions of labour born of the historical development of capitalism. To this end, this study provides an analysis of the dialectical relationship between the dominant practices of labour internationalism that emerged within the organized labour movement in Canada during the Cold War. I examine both the challenges to and possibilities for building transformative forms of international labour solidarity today. Challenges include the philosophies of social partnership, racism, white supremacy and nationalism that informed the labour imperialism and accommodationist solidarities of the institutionalized internationalism in this period. I argue that the brand of social democratic anti-communism that characterized this institutionalized labour internationalism was shaped by the wars of position over worker justice happening on the national level and internationally between unions, but also by ideas of race and nation. I outline the lessons from these practices by focusing on four cases: Kenya, Southeast Asia, The Caribbean and Palestine. Finally, I assess the grassroots labour solidarity that re-emerged inside the labour movement with the rise of the New Left. I argue that the model of international solidarity they built, called worker-to-worker, arose from the goals and strategies of class struggle unionism and constitutes an example of transformative solidarity that can inform discussions about organizing international soldiarity today. Rooted in anti-racist Marxist feminist theory, my historical sociological analysis draws from both archival research and interviews with union leaders, activists and staff. I make sense of the solidarities that determined these practices by exploring the terrain of class consciousness in which they were formed. Situating my analysis within the social and political contours of class formation in Canada and internationally, I pay particular attention to how these practices of labour internationalism intersect with issues of race, gender, nation and class struggle, and how racialized and gendered class formation in Canada has influenced ideas of worker justice and responses to imperialism, colonialism and national borders.

Les nouvelles formes de servitude et le rôle du droit : le cas de la privation de mobilité des travailleurs agricoles migrants au Canada - Ollivier-Gobeil, Jeanne (Université du Québec à Montréal, 2016)
Depuis le milieu des années 1960, le gouvernement canadien organise la migration temporaire de travailleurs agricoles originaires principalement des Caraïbes et d'Amérique centrale, via deux principaux programmes, soit le Programme des travailleurs agricoles saisonniers (PTAS) et le Volet agricole du Programme des travailleurs étrangers temporaires. Ces programmes ont permis de faire venir au Canada près de 42 530 travailleurs agricoles temporaires en 2013, dont 9760 au Québec seulement. Le PTAS et le Volet agricole soulèvent toutefois les critiques de plusieurs organisations et chercheurs. Une caractéristique commune centrale de ces programmes est particulièrement décriée, à savoir l'assignation des travailleurs à un employeur unique et à un emploi spécifique, puisque celle-ci aurait pour effet de priver les travailleurs de leur mobilité sur le marché du travail. En ce sens, il est notamment reproché à ces programmes de perpétuer des formes de travail non libre, alors que les travailleurs ne peuvent circuler librement sur le marché du travail. Dans la continuité de ces travaux critiques, ce projet de recherche se propose d'examiner le rôle de cette disposition juridique comme mécanisme de privation de la mobilité des travailleurs. Plus précisément, l'objectif de ce mémoire est d'analyser le rôle double du droit, d'une part, dans la production et l'encadrement de ces formes de travail non libre, et d'autre part, dans la possible contestation de celles-ci. Pour ce faire, nous nous appuierons tant sur analyse à la fois théorique et historique, que sur une vaste enquête de terrain. Cette enquête s'inscrit dans un projet de recherche plus large - dirigé par le professeur Martin Gallié - ayant permis de réaliser près de cent entretiens avec des travailleurs du PTAS et du Volet agricole de la région de Saint-Rémi, au Québec.

Job Displacement and the Implications for Job Quality: An Investigation of the Job Transition Process for Public Sector Workers in Scotland, Uk and Ontario, Canada During the Great Recession - Pascoe-Deslauriers, Rachelle M. (University of Strathclyde, 2016)
This thesis conceptualises the job transition as a continuous process in the context of organisational downsizing and restructuring. It argues that the policy and research related to re-employment following job loss, organisational downsizing and relevant labour market interventions remains disconnected from, and hence underemphasises, the sequential and cumulative nature of the transition process while also focussing disproportionately on modifying individual behaviour and action. This study explores the intersection and overlap in factors, actions and decisions made by actors in each part of the transition process to better understand the dynamic nature of job transition and its implications for re-employment and future job quality. This research considers job transition from two forms of displacement – job displacement and worker displacement. It comprises a cross-national comparative study of displacement from public sector work in Ontario, Canada and Scotland, UK. Forty expert and stakeholder interviews were carried out addressing different aspects of job transition, targeting academic and policy experts, employers/senior managers, union representatives and labour market programme service providers. Furthermore, 38 semi-structured work history interviews were conducted with displaced workers along with a follow-up survey. This research argues that downsizing policy and labour market interventions appear to view any job as a better outcome than redundancy. Where organisational policies maintain employment, the emphasis is on maintaining extrinsic features of work. Through practices like salary protection and lateral transfers, good quality work beyond equivalent remuneration is a bi-product rather that a central consideration. The study finds that individuals, faced with particular processes and limited information, modify their behaviour to protect valued aspects of work including, but not limited to, extrinsic job factors. Conceptually, this research contributes to knowledge on job loss and re-employment, organisational downsizing practice and job quality. Empirically, it contributes to debates on public sector restructuring following the Great Recession of 2008.

Insights into Nurses’ Work: Exploring Relationships among Work Attitudes Work-related Behaviours - Perreira, Tyrone (University of Toronto, Institute of Health Policy, Management and Evaluation, 2016)
Work motivation has been associated with work productivity. In health care, low motivation levels are associated with low productivity and linked to poor performance, decreased patient safety, and overall poor quality care. Hence the importance, ascribed in the literature, to clearly identifying the relationships between and among factors associated with work motivation, including work attitudes, and behaviours linked to work performance such as extra-role behaviours. Despite their importance to performance in health care, these relationships are understudied and poorly understood. The purpose of this study is to better understand work attitudes and their relationships to one another and to extra-role behaviours amongst nurses working in hospitals, the community, and long-term care settings in Ontario. This study comprises two stages: first, a scoping review focused on identifying individual-, unit-level, and organization-level characteristics that influence work motivation in health service organizations. The findings from the scoping review, augmented by a more in-depth review of the literature, aided in the development of a conceptual framework that guided the second stage of the study, to examine relationships amongst a specific set of nurses’ work attitudes - including perceptions of organizational justice, perceived organizational support, and affective commitment - and extra-role behaviours – specifically, organizational citizenship behaviours - in Ontario health care settings. In the second stage of the study, a survey was developed and administered to frontline nurses actively working in hospitals, the community, and long-term care settings in Ontario. Relationships amongst the constructs of interest were examined using structural equation modeling and path analysis. Examining the relationships of these concepts in a single model is novel, and offers insights regarding their complexity. The analyses further suggest that prior studies may be under-nuanced, and approaches to conceptualizing the concepts of perceived organizational justice and affective commitment in particular may have led to erroneous conclusions regarding their associations with perceived organizational support and organizational citizenship behaviours. This study further addresses four significant gaps previously identified in the work motivation and work behaviour literature: (1) how affective commitment relates to behavioural efforts, specifically organizational citizenship behaviours; (2) utilization of reliable and validated instruments to study work motivation; (3) use of a sufficiently large sample to have empirical support for generalizability; and (4) examination of these phenomena, among nurses, across diverse health care settings.

Reaching Gold Mountain: Diasporic Labour Narratives in Chinese Canadian Literature and Film - Phung, Malissa (McMaster University, 2016)
This project provides a coalitional reading of Chinese Canadian literature, film, and history based on an allegorical framework of Asian-Indigenous relationalities. It tracks how Chinese labour stories set during the period of Chinese exclusion can not only leverage national belonging for Chinese settlers but also be reread for a different sense of belonging that remains attentive to other exclusions made natural by settler colonial discourses and institutional structures, that is, the disavowal of Indigenous presence and claims to sovereignty and autochthony. It contributes to important discussions about the experiences of racism and oppression that typically privilege the relations and tensions of diasporic and Indigenous communities but hardly with each other. What is more, this study aligns with a recent surge of interest in investigating Asian-Indigenous relations in Asian Canadian, Asian American, and Asian diaspora studies. The political investments driving this project show a deep commitment to anti-racist and decolonial advocacy. By examining how Chinese cultural workers in Canada have tried to do justice to the Head Tax generation’s experiences of racial exclusion and intersectional oppressions in fiction, non-fiction, graphic non-fiction, and documentaries, it asks whether there are ways to ethically assert an excluded and marginalized Chinese presence in the context of the settler colonial state. By doing justice to the exclusion of Chinese settlers in the national imaginary, do Chinese cultural workers as a result perform an injustice to the originary presence of Indigenous peoples? This thesis re-examines the anti-racist imperative that frames Chinese labour stories set during the period of Chinese exclusion in Canada: by exploring whether social justice projects by racially marginalized communities can simultaneously re-assert an excluded racialized presence and honour their treaty rights and responsibilities, it works to apprehend the colonial positionality of the Chinese diaspora within the Canadian settler state.

Temporary Foreign Workers in British Columbia: Unfree Labour and the Rise of Unscrupulous Recruitment Practices - Rodgers, Alexandra Ellen (Simon Fraser University, 2016)
The political and economic processes of neoliberalization have led to the intensification of worker exploitation. In Canada, Temporary Foreign Workers (TFWs) who enter through the Low-waged Streams of the Temporary Foreign Worker Program (TFWP) are amongst the most vulnerable to abuse and exploitation. This thesis uses theories on unfree labour, state transformation, and anti-racism, along with data generated through qualitative research, to examine the state legislated exploitation of TFWs in British Columbia. I argue that the unscrupulous recruitment of TFWs into British Columbia is the functional process through which labour flexibility and unfreedom is achieved within the larger project of neoliberalization. I conclude by considering how regulatory reform of labour markets can be used in conjunction with anti-racist and anti-imperialist political demands that aim to challenge the functional processes of neoliberalization.

A "Minor League Equivalent to the Eiffel Tower and the Empire State Building": Vancouver's Penthouse Nightclub - Shearman, Mary (Simon Fraser University, 2016)
The Penthouse is rumoured to be the oldest continuously operating nightclub in the land we now know as Canada and is without a doubt the oldest exotic nightclub. Owned and operated by an Italian family who emigrated to Vancouver, British Columbia, The Penthouse has survived numerous waves of moral crackdown in the city as well as many offers to buy the prime location in the face of aggressive development. A staggering number of nightclubs in Vancouver, exotic or otherwise, have not shared the same fate. Through conducting an institutional history of The Penthouse I locate it within changing local politics related to feminist activism, policing, and the sex industry as well as larger shifts in cultural attitudes towards sexual labour and sex workers' bodies. Further I assemble a social history of the dancers, looking at their experiences in the club and their perception of the intersections between feminism, identity, performance, and sex. Feminist theory, women's and gender history, and performance studies inform this multi-method project, which includes results and analysis from archival research and oral history interviews conducted with dancers employed at the club from 1978-2012. Overwhelmingly, the narrators reflected on their time as dancers as valuable to their lives in a myriad of ways, including helping to foster healthy relationships with their bodies and sexualities. Nevertheless most felt that the stigma they faced as sexual labourers impacted their lives in a negative way and was in conflict with the way they experienced their work themselves. This ongoing stigma was often a driving force for abandoning striptease for more 'square' or respectable work. Others continue to work in the sex industry. Eleven dancers shared their stories for this project, as did one member of the serving staff at The Penthouse, booking agent Randy Knowlan, and current owner/operator Danny Filippone. These stories offer a history of the Penthouse which places it as a central part of Vancouver's history. At a time when conventional striptease seems to be in decline and other facets of the sex industry seem to be under attack by new forms of criminal regulation, the interviews with dancers, staff, and the owner/operator suggest that future possibilities for Vancouver's contemporary striptease communities might lie in the evolving local neo-burlesque scene.
OCLC: 1125387295

Union Organizing in the Canadian Banking Industry, 1940-1980 - Smith, Julia Maureen (Trent University, 2016)
In this dissertation, I examine union organizing in the Canadian banking industry between 1940 and 1980. By demonstrating that bank workers consistently sought to unionize throughout the twentieth century, I challenge claims that bank employees and other private sector white-collar workers have low rates of unionization because they are not interested in unions or suffer from false consciousness. This research also suggests, however, that many bank workers saw themselves as different from blue-collar industrial workers; the lived reality of bank work as precarious, poorly paid, and rife with gender inequality intersected with ideas about professionalism and aspirations of advancing up the career ladder. Banks, unions, and workers drew on these ideas and experiences in their arguments for and against unionization. I also look at why previous organizing efforts did not establish a strong union presence in the banking industry. Most of these attempts failed, I argue, due to several key issues, including the banks’ anti-union activity, federal and provincial labour board decisions, and labour movement disputes over ideology, jurisdiction, and strategy. The banks consistently opposed unionization and used a variety of tactics to thwart union organizing, both overtly and covertly. The state, in the form of labour legislation and labour boards, provided unions and workers with some means by which to compel the banks to recognize unions, negotiate contracts, and deal with employee grievances; however, state action and inaction more often worked to undermine union organizing. The attitudes and strategies of high-ranking labour movement officials also shaped the outcome of union drives in the banks. Between 1940 and 1980, the mostly male labour leadership repeatedly used top-down organizing strategies and appointed male organizers with no experience of bank work to oversee union drives in a sector with an increasingly feminized workforce; labour leaders’ inability or unwillingness to reflect on this approach and to support grassroots campaigns and alternative strategies hindered bank union organizing. I thus highlight the intersection of gender and class and reveal how these factors have historically shaped the labour movement bureaucracy, union organizing, and the relationship between labour and the state. Author Keywords: banks, gender, labour bureaucracy, trade unions, union organizing, white-collar workers.
https://cha-shc.ca/prize-winner/julia-smith/

Precarious Work in Montreal: Women, Urban Space, and Time - Teeple Hopkins, Carmen (University of Toronto, 2016)
This dissertation examines the impact of precarious work on women in Montreal. Precariousness is increasingly common in Quebec, where women are overrepresented in part-time, temporary, and self-employed work. Based on three years of fieldwork, the thesis argues that while many women experience precariousness in the labour market, they do not experience it in the same ways. The neighbourhoods in which women live significantly shape their lives at work and home. Building critically on the literature on precariousness and social class, my research theorizes precarious workers as members of the working class, not as a marginalized social class outside it. Specifically, the dissertation asks how urban space influences precarious work and how time pressures impact experiences of work and home. First, while noting that precarious workers across industries (e.g. art, teaching, service) face housing pressures similar to those experienced by other members of the working class, the research shows that precarious women workers living in central neighbourhoods are especially at risk of being displaced by the middle-class. Second, the project brings important attention to paid and unpaid domestic work. Most research in the field of “time-use” at work focuses on sectors outside the home, even though women have long performed unwaged housework and many women continue to undertake paid employment or self-employment in the home. The dissertation demonstrates the ways in which women’s workloads have increased in the sphere of the home, diminishing their physical health and rendering them more precarious. Third, with reference to women who continue to perform large amounts of unpaid work, the research considers the relevance of historical and contemporary debates around the relationship between paid and unpaid labour, illustrating how women’s wages are negatively impacted by this unpaid work. This dissertation brings together the social dimensions of gender, race, social class, and urban space. In so doing, the project contributes a multi-scalar analysis to antiracist feminist political economy and reaffirms the importance of social class within feminist geography. Bridging these two broader traditions – political economy and economic geography – the project provides a critical framework for understanding the specificities of precarious work for women in Montreal.

"Comrades! I Am Far from You, but I Am with You!": Ukrainian Working Women, Transnationalism, and the Soviet Cultural Revolution in Winnipeg, 1928 - Vargscarr, Karolya (University of Manitoba, 2016)
Using local primary sources, this work answers two questions. Firstly, is there a transnational political connection, reflected ideologically or materially, between the readership of Robitnytsia in Winnipeg and the Soviet Union in 1928? Secondly, what are the interests of the readership of Robitnytsia, as reflected in the Letters section? The answers to these questions are relevant to social historians because their focus is on content generated by the female readership of the journal, not the content generated by the male activists and political leaders who both contributed to and edited it. This work also highlights the value of Robitnytsia as a historical source of Canada, labour, gender, women's, and transnational histories; one that has been under-utilized to date and is readily available to researchers in Winnipeg and other cities across Canada. To evaluate and provide an analysis of Robitnytsia as a source of primary evidence, a brief introduction to the ULFTA, Robitnytsia, and the Soviet Cultural Revolution is helpful to the reader. After addressing the relevant historiography, the three chapters that follow provide analysis and the relevant context for the source work, including photographs and illustrations from the journal. Photographs featured on the covers of Robitnytsia provide insight into the imagery of the journal, as well as to the rhetoric associated with well-known images and icons within the working class Ukrainian community in Winnipeg. Discovering the answer to the second question posed in this work was straightforward, as the priorities and interests of the working women in Winnipeg were highly localized and specific, including recognizable and accessible priorities to even those readers who are not familiar with the work of the ULFTA. These interests included basic literacy, education, labour organization, and participation in political and social activities. The evidence regarding a transnational link to the Soviet Union, the first question of this work, was even more clear: at the grassroots level, there was no such transnational link between the Ukrainian Left in Winnipeg and the Soviet Union in 1928. –From Introduction

Accumulating Cares: Women, Whiteness, and the Affective Labour of Responsible Reproduction in Neoliberal Times - Watson, Amanda (University of Ottawa, 2016)
This thesis examines contemporary popular and news media representation of motherhood and labour in Canada and the United States. I explore what texts about motherhood and maternal labour suggest about gendered responsibilities to citizenship in neoliberal conditions. Building on important feminist research in the fields of citizenship, care, and the welfare state, I ask how are mothers being socially responsibilized toward multiple forms of labour simultaneously and to what effect? By engaging feminist theories of citizenship and bridging this field with feminist theories of science, media, and affect, I demonstrate how, under neoliberal conditions and in precarious circumstances, the ways in which women appear to juggle their commitments to paid and unpaid labour, determines how mainstream discourses reflect their value as citizens. This dissertation uses feminist critical discourse analysis to assess how, as women are responsibilized toward unpaid intimate work in newly empirical ways at the same time that they are encouraged to pursue career success in full-time paid employment, contemporary women in Canada and the United States are encouraged to rise above welfare retrenchment and inadequate provision by juggling “it all.” My thesis is an intersectional feminist project that interrogates questions of gendered citizenship and maternal affect, and I join feminist political theorists in applying pressure to the field of citizenship studies to centre reproduction in discussion of gendered welfare.

Green Jobs: An Alternative to Neoliberalism? Recycling in Buenos Aires, Argentina and Toronto, Canada - Yap, Lilian (York University, 2016)
In recent years, environmental organizations and labour unions have begun to more seriously campaign for the promotion of green jobs as a way to address the twin problems of climate change and economic stagnation, particularly in the aftermath of the financial crisis of 2008. They variously suggest that green jobs will be created through increased investment in green sectors; for some, this requires public investment and the adoption of a Green New Deal (GND) policy orientation, while for others this requires only increased private investment in green industries. The former emphasize that since green sectors are more labour-intensive than traditional industries, investment in green infrastructure could thus generate comparatively more employment per dollar invested. At the heart of these proposals is the proposition that capitalist economic growth could be made consistent with social and ecological justice. This dissertation is a critical engagement with the propositions of the green jobs campaign through the concrete examination of two diverse cases of residential (i.e. post-consumer) recycling, a quintessentially green sector, in Buenos Aires and Toronto. Defining recycling as the (global) production of value from waste, the analysis pays particular attention to both the labour process and historical development of recycling. Through a combination of qualitative document analysis, archival research, and qualitative interviews, this thesis argues that purely market-coordinated recycling is not able to simultaneously deliver large-scale employment creation and improved socio-ecological outcomes because of the inherent tension between labour intensiveness and methods of increasing productivity. This tension, in turn, is rooted in the distributive conflict characteristic of capitalist production, the resolution of which requires increased economic growth. From an ecological perspective, then, this is simply a deferment of the problem. In line with proponents of the Green New Deal, this dissertation argues that mediation of this tension in a direction favourable to both ecological and social concerns requires collective intervention. However, going beyond the Green New Deal, it concludes that commitment to social and ecological justice requires moving in the direction of decommodified, cooperative production and collective consumption.

No Hobo is an Island: Power and Political Culture in the Federal Work Relief Camps in British Columbia, 1932-1935 - Adolph, Neal Robert (Simon Fraser University, 2015)
This thesis explores the political experience of men in the Department of National Defence’s work relief camps in British Columbia from 1932 to 1935, when single, homeless, unemployed, and physically fit men accessed government unemployment relief living and working according to the administration’s policies. In these camps the men found a government administration eager to teach them work discipline, a collection of charities and private groups that promoted an ideal of the working class man in troubled economic times, and organizers with the Relief Camp Workers’ Union attempting to shape strikes that challenged government authority. In this thesis I argue that the unemployed vacillated between these different influences to challenge the government’s palliative relief while also ensuring that they maintained access to relief for as long as possible. This was accomplished by shaping multi-faceted relationships with the government, the union, private charities, and fellow campers.

Pierre Trudeau, Organized Labour, and the Canadian Social Democratic Left, 1945-2000 - Aivalis, Christo (Queen's University, 2015)
This dissertation examines Pierre Elliott Trudeau’s relationship with labour unions and the Cooperative Commonwealth Federation-New Democratic Party of Canada from 1945 to 2000. Trudeau was an extremely influential historical figure, both as prime minister (1968-1984), but also before his entry into formal politics, when he traveled and studied around the world, became deeply influenced by leftist movements and intellectuals, and sought to modernize Quebec, which in his view was falling behind English Canada in terms of technological, social, and democratic development. In essence, Trudeau sought to forge a liberal democracy he thought absent in Quebec, and found his staunchest allies to be trade unionists and socialists. In the end, however, Trudeau largely abandoned those movements because he felt winning liberal freedoms required the shelving of socialist objectives. This would, in turn, be his justification for joining the Liberal Party in 1965. As Prime Minister, Trudeau opposed the objectives and philosophies of his former left allies, even as he maintained his image as a progressive. So while many saw his Just Society, his approach to public and Canadian ownership of energy, his New Society, and his Charter of Rights and Freedoms as left-wing initiatives, I argue that Trudeau’s actions were undertaken not to challenge capitalism, but to strengthen it, primarily through the empowerment of business and the disempowerment of unions and the economically-disenfranchised. Ultimately, this dissertation asserts that Trudeau cannot be classified as a socialist, but must be seen as a liberal preoccupied, not with liberty and equality, but with the continued pre-eminence of capitalist property relations.
OCLC: 914902645
Keywords: Canadian Labour Congress; Charter of Rights and Freedoms; Cooperative Commonwealth Federation; Foreign Investment Review Agency; Liberalism; National Energy Program; New Democratic Party; Organized Labour; Pierre Elliott Trudeau; Quiet Revolution; Socialism; Thesis; Wage and Price Controls

Parcours de travail aux marges de l'emploi - Récits du salariat domestique, Québec, deuxième moitié du XXe siècle - Charron, Catherine (Université Laval, 2015)
Cette thèse porte sur les figures contemporaines du salariat domestique ainsi que les principales évolutions de ce secteur d’activités dans la deuxième moitié du XXe siècle à Québec. Les récits de vie d’une trentaine de femmes ayant expérimenté diverses formes de travail domestique rémunéré constituent la base empirique de cette étude. Durant cette période historique marquée par l’accroissement spectaculaire de la main-d’œuvre féminine, de même que par le déclin du fordisme et la polarisation du marché du travail, le secteur domestique se diversifie. Les nouvelles formes de service domestique s’inscrivent dans la continuité historique ― notamment en regard de la personnalisation et de la naturalisation du rapport de travail, qui ont maintenu ce secteur à l’écart de la norme salariale depuis le XIXe siècle ―, tout en participant pleinement à la construction de nouveaux régimes d’inégalités de classe, de race et de genre autour de la division du travail dans la société québécoise contemporaine. Les récits de vie témoignent de l’indissociabilité des formes rémunérées et non rémunérées de travail domestique, et de leur caractère structurant dans la construction du rapport des femmes de milieux populaires au travail, à l’emploi et à la famille. De l’apprentissage du service domestique comme mode de socialisation des filles à la permanence domestique assurée par les femmes à toutes les étapes de leur vie familiale, les réseaux féminins familiaux et communautaires tissent la toile de toute une économie des échanges domestiques, sur un continuum entre entraide et emploi. Au cours des dernières décennies du XXe siècle, divers mécanismes se mettent en branle pour créer un bassin de main-d’œuvre domestique, dont certains sont directement liés à l’institution patriarcale du mariage, et concernent les femmes divorcées ou celles qui ont connu une longue absence du marché du travail. L’univers des petits boulots domestiques apparaît comme une sorte d’archipel où sont refoulées des femmes exclues du marché de l’emploi formel. Au sein de cette nébuleuse des emplois domestiques, les dynamiques de professionnalisation, d’institutionnalisation et de segmentation s’articulent autour de la frontière entre service et servitude, laquelle nourrit les pratiques et les représentations dans ces métiers où l’héritage ancillaire fait figure de spectre.
https://core.ac.uk/download/pdf/442640565.pdf

Three Essays on Legal Issues Impacting the Employment Relationship in Canada - Curran, Bruce John (University of Toronto, 2015)
The first of three papers helps resolve the substantial debate about the impact of Honda v. Keays, a 2008 Supreme Court of Canada decision modifying the principles for compensating employees for improper employer conduct during dismissal (called “moral damages”). I performed content analysis on all relevant Canadian cases in the four years after Honda and an equivalent period before Honda and then used a tobit model to test legal scholars’ and lawyers’ predictions. I find that moral damages are less probable after Honda. Furthermore, the size of awards is smaller in those cases where moral damages are granted, partly because certain levels of employer misconduct now produce lower damages. However, I also find that, since Honda, high levels of mental distress are compensated more richly. The second paper is motivated by the absence of recent studies that investigate delay in grievance arbitration, despite increasing concerns being voiced about the issue. I performed content analysis on a random sample of about 400 Ontario arbitration awards, and then used a proportional hazards model to examine the extent of delay and its determinants. Consistent with common perception, the results suggest that delay has become a worse problem over the past two decades. I find that certain legalistic factors and the expanded jurisdiction of arbitrators over specific types of issues are associated with delay. The results also show that certain dispute resolution procedures are related to decreased delay, and this suggests some practical solutions. Prompted by a recent series of Supreme Court of Canada (SCC) decisions on freedom of association (FOA) in the labour context, the third paper critically examines the Canadian jurisprudence. The state of this law in Canada has been roundly criticized by various prominent labour law academics. This paper relies on Sheldon Leader’s theory of FOA to argue that the SCC should have interpreted s. 2(d) of the Charter as protecting collective bargaining and striking as independent rights, rather than as rights necessary for the realization of the FOA. Having done so would have yielded jurisprudence that was more consistent and coherent.

Designing Names: Requisite Identity Labour for Migrants' Be(long)ing in Ontario - Dechief, Diane Yvonne (University of Toronto, 2015)
This dissertation responds to the question of why people who immigrate to Ontario, Canada frequently choose to use their personal names in altered forms. Between May and December 2010, I engaged in semi-structured interviews with twenty-three people who, while living in Ontario, experienced name challenges ranging from persistent, repetitive misspellings and mispronunciations of their original names to cases of significant name alterations on residency documents, and even to situations of exclusion and discrimination. Drawing on critical perspectives from literature on identity and performativity, science and technology studies, race and immigration, affect, and onomastics (the study of names), I establish that name challenges are a form of "identity labour" required of many people who immigrate to Ontario. I also describe how individuals' identity labour changes over time. In response to name challenges, and the need to balance between their sometimes-simultaneous audiences, participants design their names for life in Ontario–by deciding which audiences to privilege, they choose where they want to belong, and how their names should be.

Jeunes et syndicalisme : une intégration réussie? Analyse comparative de deux organisations syndicales du Québec - Durand-Allard, Marc-Antoine (Université de Montréal, 2015)
Cette recherche dresse un portrait de la situation de la relève syndicale au Québec et des tentatives des organisations syndicales pour stimuler la participation de leurs membres de moins de 30 ans. Elle brosse d’abord un aperçu des habitudes sociales, des valeurs et des caractéristiques en emploi des jeunes. Elle nuance et recadre ensuite la problématique des jeunes en ce qui concerne l’identité collective qu’ils partagent instinctivement et les modalités de socialisation à l’interne façonnant leur participation. Cette recherche remet en question la fenêtre de recrutement estimée où les jeunes seraient en mesure d’entâmer leur participation dans les structures syndicales. Au demeurant, elle décrit l’ampleur des innovations syndicales destinées à stimuler la participation des jeunes et démystifie le mandat de l’une d’elle, les comités jeunes, qui peuvent agir à la fois comme porte-parole de leur organisation, comme la voix des jeunes membres et comme pépinière de la relève syndicale. Les données empiriques utilisées pour ce mémoire proviennent d’une vingtaine de groupes de discussion et de huit entretiens semi-dirigés (n=228), tenus dans deux organisations syndicales d’importance au Québec, disposant d’un comité jeunes et organisés par les chercheures d’un projet de recherche plus vaste sur la participation syndicale des jeunes. Nos résultats démontrent en premier lieu une identité collective construite autour de la précarité et des injustices perçues par les nouveaux travailleurs. L’âge ne serait pas significatif dans la construction de l’identité des jeunes qui semblent en phase de conquérir leur identité. En second lieu, le cadre strict de plusieurs modalités de socialisation avait un effet inhibiteur sur la participation, favorisait des relations d’échanges instrumentales et ne tenait pas compte de la sensibilité de cette nouvelle génération pour les interactions réciproques avec leurs représentants syndicaux. Nous avons aussi observé une utilisation limitée des nouvelles technologies, qui présentent des potentialités intéressantes en matière de transfert des connaissances de surcroît. Par ailleurs, nos résultats à l’égard de l’identité collective observée et de la durée du processus de socialisation soulèvent des questionnements sur la pertinence même des structures jeunes dans leurs paramètres actuels. Le parcours d’un jeune vers la militance syndicale apparaît plus tardif qu’escompté. Plus encore, la problématique jeunes met en lumière les tensions intrinsèques au mouvement syndical quant à la libre négociation sociale des intérêts défendus et du consensus interne nécessaire à leur légitimité.
https://doi.org/1866/11644

Capitalism on Trial: Section 98, the Communist Party of Canada and the Battle for Legality in the Interwar Period - Eaton, Campbell Scott (Simon Fraser University, 2015)
In 1919, the Canadian state enacted a law that criminalized the advocacy of radical politics. Section 98, as it became, was broad in its terminology, and carried a maximum punishment of twenty years imprisonment. In 1931, the state utilized the law against eight leaders of the Communist Party of Canada in an attempt to declare the organization to be illegal in Canada. The party, however, did not crumble under pressure. At trial, the accused were able to use the courtroom as a forum to protest the legality of the law; after the leaders were convicted, the party campaigned tirelessly for the release of their comrades, and for the repeal of Section 98. The party was successfully able to use its repression to forward its political agenda. This thesis explores how the party navigated Canada’s legal system in order to realize its political goals.

The City and the Reds: Leftism, the Civic Politics of Order, and a Contested Modernity in Montreal, 1929-1947 - Elie, Christine (Queen's University, 2015)
From 1929 to 1947 the city of Montreal was renegotiating the boundaries of belonging. This dissertation examines the relationship between the left and the city during this period of crisis. Attempts to impose order on the chaos of the period – from deportation to an all-out war on leftism – serve as valuable fault-lines in notions of citizenship and exclusion. Reinterpreting Montreal’s history in this period through Zygmunt Bauman’s conception of cultural modernity, this study challenges notions of Montreal’s left as lacklustre. It also probes the contours of municipal and clerical definitions of ‘Montrealer.’ Complicating existing scholarship on Montreal’s left as compliant, this dissertation broadens the definition of leftism and recasts leftists as resistant to state and clerical repression – not as passive victims of Montreal’s Grande Noirceur but as active participants in modern planning for the future of the city. Modernity is the common thread that weaves this dissertation together. This study opens with the Catholic Church – exemplified here by the École sociale populaire – as it attempts to redefine belonging in opposition to the radical left. It turns to the City of Montreal’s attempts to purge ambivalence through mass deportation campaigns that treated the unemployed and the foreign-born as outsiders to modern Montreal. It then examines a series of vigorous left moments as case studies of repression and resistance: Albert Saint-Martin’s Université ouvirère, the sedition trials of the 1930s, the Canadian Youth Congress, the Padlock Act, the War Measures Act, and Henri Gagnon’s Ligue des vétérans sans-logis. In so doing, this study argues that Montreal’s leftists, though cast as enemies by the state, contested their status as ‘outsiders’ by engaging with modernity on their own terms. While there were crushing defeats, there were also significant victories. In these diffuse, linguistically diverse communities, we find Montreal’s left developing an alternative vision of the city. Moments of convergence between Montreal’s French-Canadian students and the Anglophone-dominated Communist Party of Canada bear witness to the power of the left to challenge state-sanctioned repression. These leftists saw themselves as part of a larger global movement for change, peace, and a better tomorrow – one which concentrated on challenging narrow notions of belonging in Montreal.

Rethinking Unions: Contradiction, Leadership, Narratives and the Case of UFCW Local 401 - Foster, Jason (Saint Mary's University, 2015)
Over the past 20 years, the Alberta-based United Food and Commercial Workers Local 401 have revitalized their union through organizing diverse groups of workers in hard-to-organize occupations, increasing involvement in political and community matters and adopting innovative organizing and representation strategies. They have done so with a stable leadership that exhibits autocratic and populist tendencies. The apparent contradictions of autocratic structures and innovative reforms are difficult to explain using existing explanations of union renewal and concepts of union forms. This in-depth study examines Local 401 in an effort to explain the unexpected patterns. Using a variety of methods, including Critical Narrative Analysis, the study reveals that unions may be more fluid and dynamic than the existing literature acknowledges. The study concludes the business union-social union duality common in industrial relations theory needs to be replaced by a more flexible, more multi-layered conceptualization of union behaviour. Unions exhibit elements of both social and business unionism at the same time because they are organizations created at the intersection between structure and action and are always in flux. The study also highlights a possible third path for union renewal, coined “accidental revitalization”, where local-initiated renewal can occur without planned intention and within a context of stable local leadership. Third, the study explores the role narratives play in resolving apparent contradictions in union behaviour by constructing internal logics and how narratives contribute to the production and re-production of power dynamics within unions.

“Columns of the House” and Proud Workers: Greek Immigrant Women in Vancouver, 1954-1975 - Kalogeropoulou, Maria (Simon Fraser University, 2015)
In this thesis, I study the experiences of eight first-generation Greek immigrant women who moved to Vancouver between 1954 and 1975 by listening to and contextualizing their oral life histories. Looking at their lives before they immigrated, I explore how these women’s gender experiences were very much shaped by religion, class, and rural vis-à=vis urban locations in Greece. I also demonstrate that many exercised agency in this patriarchal culture, and that they were part of the decision-making process that led to immigration in search of a better life. After they immigrated to Vancouver, these women played an active part in supporting their families’ wellbeing, and some also contributed outside the household, offering their assistance to Greek communal organizations. Differences in class and working careers resulted in different narratives about immigration experiences, although the ideal of the kali noikokyra (good housewife) was consistent in their perceptions of proper Greek womanhood. Middle-class and working-class women also had different attitudes towards charitable work, religion, and the Greek community organizations. Both, however, actively contributed to the survival and settlement of Greek immigrant families in Canada. Overall, this thesis examines how gender, class, ethnicity, and religion affected Greek women’s identities before and after they immigrated in postwar period, and how their experiences of immigration altered their perspectives on the place of women in Greek families.

The Perils of Home: Race, Gender, and Labor on the Pacific Frontier - Kim, Jason Ulim (University of California, Berkeley, 2015)
In the early twentieth century, Chinese men and white women often worked in close proximity to each other in various intimate settings in the North American West— from the kitchens of upper class homes to the noisy cafés of the city. However, little has been said in the scholarship on the social and political significance of these encounters. Instead, this study centers on the different and connected ways in which intimacy shaped the North American West in the early twentieth century. As such, this work makes central and transparent the connections between the expansion of white women’s political and economic rights and efforts to exclude the Chinese in British Columbia and California. Thus, this study asks: How were changes in the status of white women and shifting notions of domesticity related to debates about Chinese labor and migration? Conversely, to what extent was the anti-Oriental movement and its calls for exclusionary measures informed and shaped by debates about gender roles? Last, how might a transnational analysis of these intersecting debates deepen our understanding of how such controversies shaped Vancouver and San Francisco as frontiers and gateways for Chinese labor migration and white settlement? If both Western Canada and the United States were primary sites for Asian labor migration and white settlement, did intimacy and affective labor play out differently in these two contexts?By using primary source documents to analyze two murder cases involving Chinese servants and two legislative efforts regarding affective labor in the distinct but connected contexts of Western Canada and the United States, this study shows how white women and Chinese men working together in intimate settings became increasingly scrutinized and subject to rampant social commentary and governmental intervention as racial, sexual, and class tensions flared.

Legitimating the “Fiasco”: Canadian State Justifications of CORCAN Prison Labour - Kleuskens, Shanisse (Université d'Ottawa / University of Ottawa, 2015)
Since Kingston Penitentiary’s opening in 1835, prison labour has been an integral part of Canada’s penal history. With purported goals such as deterrence, rehabilitation, reintegration, and providing sustenance to the state, the practice of coercing or forcing a prisoner to work while serving a sentence of incarceration was further embedded in the penal landscape in 1980 with the inception of CORCAN, the Correctional Service of Canada’s prison labour program. Despite critiques of the prison as “a fiasco in terms of its own purposes” (Mathiesen, 2006, p. 141), prison labour continues as a mechanism of the state’s penal apparatus. Drawing on political economy of punishment and penal abolitionism literature, this study reveals and disrupts official discourses used to justify and perpetuate this modern form of slavery in Canada. Through a content analysis of 33 Solicitor General of Canada and CORCAN annual reports, I demonstrate how CORCAN’s prison labour program is legitimated as a “positive reform” (Mathiesen, 1974, p. 202) of Canada’s penal system, beneficial to the reintegration of prisoners into society, communities, and the needs of the Canadian state and economy. Underneath this benevolent mask such representations are found to reproduce neoliberal capitalism as the hegemonic form of economic organization, construing prisoners and prison labour as solutions to the gaps and shifts in the national economy and labour market. After outlining these contributions, I suggest ways that future research can reveal and discredit penal ‘solutions’ such as prison labour to eradicate the penal system as a means to address the harms inherent in our social and economic systems.

Unionization at Justice Canada: A Case Study - Kowalsky, Andrij Roman (York University, Osgoode Hall, 2015)
In April 2005, non-management lawyers working at the federal Department of Justice Canada (DOJ) were recognized by the Public Service Labour Relations Act (PSLRA) as employees. This dissertation explores DOJ lawyers unionizing by addressing two research questions: (1) what led DOJ lawyers to unionize with the Association of Justice Counsel (AJC)? and (2) what was the AJC’s experience in negotiating a first collective agreement? The dissertation is organized using a conventional structure. The literature review presented in Chapter 2 maps the academic study of lawyer unionization. Chapter 3 elaborates on the dissertation’s research design as a case study. Chapter 4 explains DOJ lawyers’ exclusion from the Public Service Staff Relations Act, the DOJ’s administration of the individual employment relationship, and introduces the Legal Officers’ Advisory Committee (LOAC). Chapter 5 provides a historical analysis of events leading to LOAC becoming the AJC. The chapter describes how redressing an exclusive wage premium known as the “Toronto differential” helped LOAC generate employee support for forming the AJC as a professional association, and, later, campaigning for union recognition under the PSLRA. Chapter 6 presents the AJC’s negotiation and completion of a first labour agreement. Chapter 7 concludes the work. Findings from the seven chapters are synthesized into a descriptive theory that addresses the two research questions. Its thesis is that DOJ lawyers’ desire for workplace representation and improved wages, executive level support from the DOJ, and introduction of the PSLRA facilitated the creation and development of the AJC into a vehicle that directed the unionization process. The argument further holds that the AJC negotiated a first collective agreement with an employer who engaged in hard bargaining that resulted in deadlocked negotiations, but was conduct, nonetheless, the courts determined had allowed the AJC a meaningful process of collective bargaining prior to the imposition of wage-restraint legislation. The dissertation’s findings: (1) detail the establishment of a new professional union in Canada’s federal public service; (2) confirm the relevance of the processual model for understanding DOJ lawyers unionizing; and (3) suggest that litigation challenging legislation remains unpredictable despite jurisprudence that protects the process of collective bargaining.
Keywords: Association of Justice Counsel; Collective bargaining; Department of Justice Canada; Department of Justice Canada lawyers; Labor relations; Law; Social research; Unionization; case study

An Organizational Study of Mental Health in the Workplace - Malachowski, Cindy (University of Toronto, Graduate Department of Rehabilitation Science, 2015)
Workplace mental health is becoming of increasing importance, in part due to the rising social and economic costs of mental health issues in the workplace. Little is known about how the experience of workers with mental health issues is actively produced through their participation in workplace procedures and associated supports. The purpose of this research is to better understand how employees actively engage in institutional practices and associated social relations that ultimately coordinate and produce their workplace experience. Using institutional ethnography, I take up the standpoint of the employee living with mental health issues to explore the coordinating relations associated with workplace mental health. This approach sheds light on how employees' experiences are socially produced and coordinated across and between institutional processes and practices. Data collection included over 140 hours of ethnographic observations, the analysis of associated texts and documents, and interviews that were conducted with 17 informants. This research details some of the challenges experienced by one novice health science researcher while conducting ethnographic research, and provides techniques for addressing personal and professional boundaries, negotiating ethical dilemmas, and reconciling the emotional experience of transitioning back and forth between being an `outsider' and `insider'. In addition to these insights, the findings explicate the social relations and institutional processes that coordinate sick time utilization for workers experiencing mental health issues. We revealed that employee's work of managing workplace absence management programs while negotiating episodes of mental ill health was perceived as overwhelming, unfair, and even punitive. Employees would require formal and informal respite from work, and would often utilized vacation time when unwell in order to avoid institutional processes all together. The biomedical focus of the absence management program created uncertainty about what constitutes a bona fide illness, and caused managers to come to know their work activities as distinctively separate from the work of healthcare practitioners. This research contributes to the literature by highlighting how tensions are created through textually coordinated work activities within and between the corporate and healthcare sector. These insights are important in establishing where and how to enact change from the standpoint of the worker.
Keywords: Institutional ethnography; Mental health; Mental illness; Social organization; Stigma; Workplace

"If You Want Blood": Violence at Work in the North American Auto Industry, 1960-1980 - Milloy, Jeremy Strachan (Simon Fraser University, 2015)
Violence in the workplace has attracted widespread scholarly and media attention in the United States and Canada since the 1980s. Governments and corporations on both sides of the border have identified this violence as a serious problem affecting the health and safety of workers. However, there is still much that is unknown about workplace violence. Is the problem of workplace violence more serious than it was today? How has it changed over time? What are the factors that have produced violence at work? How have workers, management, and governments defined violence at work? How have they approached the problem? This dissertation historicizes the phenomenon of workplace violence, investigating on-the-job violence in the North American automotive industry between 1960-1980. It embeds violence at work in its economic, political, and cultural contexts and investigates how violence shaped the North American workplace and identities of class, gender, and race on the job. A comparative, transnational approach is central to this study. If we seek to understand the structural factors causing workplace violence, the national context cannot be ignored. This is especially true when considering the US and Canada, two countries which are extraordinarily integrated economically but often contrasted socially and culturally. My research has uncovered a significant history of violence in the automotive workplaces of Detroit and Windsor, and shows that national and local contexts were crucial in determining the level of violence. Violence was a regular element of shop-floor culture and workplace conflict in both countries, but was different in each. In Detroit, violence at work reached epidemic levels and was a major factor in the crisis that gripped the city's auto plants in the 1960s and 1970s. This was not the case in Windsor. Yet in both cities workplace violence became a major concern outside the factory when work-related murders seized national headlines and challenged citizens to understand these tragedies. The thesis demonstrates that, though the patterns and levels of violence were different in each place, violence was no aberration, no freak occurrence, but an ongoing phenomenon that influenced the labour process and workplace culture in both Detroit and Windsor.
https://cha-shc.ca/prize-winner/jeremy-milloy/

State Repression and Political Deportation in Canada, 1919-1936 - Molinaro, Dennis (University of Toronto, 2015)
Section 98 of the Criminal Code of Canada was in force from1919 to 1936. The dissertation traces the way in which Canada incorporated emergency law, created during the First World War under the War Measures Act, into the Criminal Code as Section 98 after the war to combat political radicalism from 1919 to 1936. In contrast to existing scholarship, this work not only explains how a liberal democracy like Canada can legally use emergency legislation outside of a state of emergency through a process of `normalization' but it also examines the effects of such laws on their human targets through case studies of criminal trials and deportation hearings. Targets included political activists, immigrants and women. It makes contributions to Canada's legal, immigration, labour and intelligence history. The study also examines the international influences on Canadian policy makers in creating such laws and the complex international identities of the transnational activists at whom these laws were often directed. The work examines how culture played a crucial role in underpinning the intelligence cycle that led to the prosecution of leading Communist Party of Canada (CPC) members. It also complicates our understanding of the CPC during Moscow's `Third Period.' It was a party that both marginalized and welcomed immigrant workers. The dissertation provides an in-depth examination of the trial of Rex v. Buck et al and the ways in which political ideology was interpreted by the court as a criminal act. It examines cases of deportation that resulted from the trial, such as the case of the `Halifax Ten,' and traces what happened to the deportees after their deportation making use of Finnish, Polish, Croatian, and German primary sources. In addition, this work demonstrates how the communist led organization, the Canadian Labour Defense League (CLDL) initiated Canada's civil rights movement by joining with moderate leftists during the `Third Period,' and before the Communist International's shift to the `United Front' policy, to repeal Section 98. It demonstrates how the normalization of emergency law continued after Section 98's repeal when its core elements were retained and folded into Canada's sedition laws where it remains today.
Keywords: Section 98; communism; deportation; national security; state of emergency; state of exception

Life on the Line: Indigenous Women Cannery Workers' Experiences of Precarious Work - Morgan, Norma Jean (University of British Columbia, 2015)
This dissertation examines the experiences of Indigenous women engaged in precarious and seasonal salmon cannery work. The dissertation argues that to grasp the nature of the women's work, which is exceedingly precarious, it is necessary to consider how it is shaped by a host of social, political, environmental and economic forces. In particular, the dissertation illustrates how provincial and Canadian neoliberal policies that developed during the past few decades have amplified the vulnerable status of Indigenous women cannery workers. Neoliberal discourses of active (worthy) and passive (unworthy) citizens embedded in social policies powerfully shape qualification requirements to programs such as Employment Insurance and Income Assistance while individualizing social inequalities experienced by Indigenous women. The dissertation employs both decolonizing and feminist methodologies to examine the everyday experiences of Indigenous women and to map out the social relations that shape their experience as precarious workers. Overall the dissertation contributes to making Indigenous women worker's lives more visible, to showing their significance in the salmon canning industry, to highlighting how their precarious labour undermines their well being and that of their families, and to demonstrating their resilience in the face of major obstacles.

What's Love Got to Do with It?!: Teaching as a 'Labour of Love' and Ontario's 2012-13 Labour Disputes. - Nadon, Jaclyn (Queen's University, 2015)
The following entails a “historico-critical” (Foucault [1984] 2010:46) analysis of the connection between teaching and love encapsulated in public, political and media discourses during the 2012-13 education labour disputes in Ontario, Canada. Examining the history of teaching as a ‘feminized’ profession within a capitalist, patriarchal, settler-colonial state, I suggest that discourses constituting teachers as selfless carers are intimately linked to visions of motherhood and white supremacy. Furthermore, I suggest that the concept of selfless love operates as a tool for depoliticization, used primarily against women and others within a society subsumed by neoliberal rhetoric. Ultimately, thinking outside of and working against this conception of love as something inherently selfless can help us elaborate a more egalitarian vision of love which values both autonomy and collectivity through an acknowledgement of Levinasian selfhood.

Discourses of Teacher Professionalism: A Study of Union-Active Teachers - Osmond-Johnson, Pamela (University of Toronto, Ontario Institute for Studies in Education, 2015)
This study presents a qualitative cross-case analysis of the discourses of teacher professionalism amongst union active teachers in the Canadian provinces of Alberta and Ontario. Data collection included interviews with 11 members of the Elementary Teachers’ Federation of Ontario and 13 members from the Alberta Teachers’ Association, which were grounded in a document analysis of various reports, member magazines, news articles, and press releases dating back to the 1990s. The study reveals a triad of influences on the professionalism discourses of union-active teachers: engagement in teacher associations, the larger policy environment, and teacher agency. More specifically, participants’ inner drive to affect change, coupled with the capacity building experiences gained through their teacher association, saw many participants enacting and espousing discourses that positioned teachers as learners, leaders, advocates, and autonomous experts. That being said, member discourses were also impacted by the organizational priorities of their teacher associations and the extent to which the associations had been able to sway discourses within the larger policy environment to be supportive of teachers. These discursive influences are not static, however, nor are they mutually exclusive. Rather, a complex, mutually reinforcing relationship exists between these elements that change over time as teachers, their unions, and governments respond to each other in new and evolving ways. This results in discourses of teacher professionalism “from within” and “from without” that are more akin to two sides of the same coin than they are to the juxtaposed manner which they are often conceived of. In this way the study illustrates the power of teachers and their unions to alter the balance between democratic discourses which position teachers as advocates, agents, and policy actors; and neoliberal portrayals of teachers as the objects of educational reform.
Keywords: Discourse; Educational policy; Neoliberalism; Teacher professionalism; Teacher unions

Partial Histories: Constituting a Conflict between Women's Equality Rights and Indigenous Sovereignty in Canada - Painter, Genevieve (University of California, Berkeley, 2015)
This dissertation is a history of an idea, a retelling of a simple story about an idea as a complicated one, and an explanation of the effects of believing the simple story. From 1869 to 1985, to be an Indian in the eyes of the Canadian state—to be a “status Indian”—a person had to have a status Indian father. The Canadian government registered a population of Indigenous people as status Indians and decided that Indian status passed along the male line. If an Indian man married a non-Indian woman, his wife gained status and their children were status Indians. In contrast, if a status Indian woman married a non-Indian man, she lost her Indian status, and her children were not status Indians. This rule exiled women from their families of birth and tore them from the political fabric of their communities. The Indian status system is a keystone in Canada’s colonizing governance of Indigenous life. The rules in the Indian Act for the transmission of Indian status came under heavy criticism and, in 1985, the federal government amended the law. Because the 1985 amendments perpetuated sex discrimination by conferring an advantage to those who traced Indian status along the male line, the rules for Indian status were the object of decades of subsequent campaigning and litigation. In 2008 and 2015, landmark judgments in McIvor and Descheneaux declared the rules to be in breach of the gender equality guarantees in Canada’s Charter of Rights and Freedoms. In overturning the Indian Act’s status rules, the courts have relied on the government’s explanation of the history of these rules. The legislative history told by the government mirrors commonly held views about the history of the 1985 amendments to the Indian Act. According to this canonical history, the core explanation for the Indian Act amendments is a tension between individual rights to gender equality and collective rights to Indigenous self-governance, embodied in a conflict between Indigenous women and Indigenous communities (often represented by male Indigenous leaders). According to the canonical history, the opposition between these groups yielded an intractable political stalemate—a Gordian political knot that could only be sliced by the equality rights offered in constitutional and international human rights law. This dissertation unseats the canonical history by advancing an alternative account, one with both a wider aperture on the political and social context and a sharper focus on detail, complexity, and contingency. The dissertation asks how individual equality rights and Indigenous self-governance became juxtaposed to one another in a relationship of tension and dichotomous opposition and explains the discursive, political, and social forces that came together to create this idea of opposition. It situates the history of the Indian Act amendments in the context of negotiations for the re-founding of Canadian sovereignty and the passage of the Charter of Rights and Freedoms, Indigenous demands for recognition as a third order of government in Canada’s federal state, changing understandings of equality in Canadian law, and shifts in the categorization of the problem of Indian women’s loss of status as a political, social, or cultural problem. It traces the role of Indigenous political organizations, Indigenous women’s political organizations, and the white-led women’s movement in shaping the debate. It tracks how an issue transformed from a political problem into a question of fundamental rights. Debates about amending the Indian Act showed a consensus among Indigenous people about the importance of Indigenous self-governance and the need to end sex discrimination in the Indian Act. Conflict among Indigenous groups arose about the mechanisms for recognizing Indigenous self-governance and the definition of self-governing polities. Rather than a pitched battle among Indigenous people, the central threads running throughout the history of reforms to the Indian Act are the federal government’s steadfast refusal to recognize inherent Indigenous self-governance and a desire to limit government spending on status Indians, all in service of a project of constructing and defending Canadian sovereignty. The dissertation exposes the government’s share of responsibility in creating a conflict between gender equality rights and Indigenous self-governance. It reveals the law’s hand in shaping the discourses of rights through which this idea of tension became articulated, labeling those rights as fundamental, pitting those rights against one another as intrinsically opposed, and then balancing them in the name of justice and fairness. In contemporary litigation over the Indian Act, the Canadian government deploys a story about competing interests of Indigenous women and Indigenous communities as a justification for continued discrimination in the Indian Act. (Abridged abstract)
Keywords: Canada; Constitutional law; Human rights; Rhetoric; Settler colonialism; Social movements; Social sciences

Bunkhouse Drama: An Examination of Control and Agency among Migrant Farm Workers in Ontario, Canada - Perry, Joseph Adam (University of Toronto, Ontario Institute for Studies in Education, 2015)
This thesis examines workers' experiences of control and agency at the micro-political level of the dormitory/workplace in the context of Canada's Seasonal Agricultural Workers Program (SAWP). I ask: 1) How are individual migrant workers responding to workplace and (im)migration policies and practices that aim to produce a flexible and compliant workforce; and 2) what forms of creative research strategies are best suited to documenting and examining the private, largely hidden lives of migrant farm workers? The thesis sheds light on the daily forms of resilience, opposition and survival among an entrenched, yet largely hidden workforce on the margins of Canada's labour market. I conducted my fieldwork in the town of Leamington, Ontario, a well-established hub of Canada's greenhouse industry, and as such a significant terminus for SAWP workers. In order to fully engage workers in the research process, I incorporated a qualitative, embodied, active and participatory approach to research grounded in life history, personal narrative, and drama-based methods. Through my interactions with workers I explore in detail how colonial attitudes operate alongside Canada's official policy of multiculturalism in the context of migration and employment among `low-skilled' guest workers. Throughout the thesis I examine workers' stories through the conceptual lenses of worker agency, workplace relations and worker emancipation. My research reveals that in tightly controlled and surveilled workplace environments workers learn to be intensely competitive and to distrust each other as a means of survival, resulting in a deep sense of isolation among workers, thus stifling potential opportunities for building group solidarity. However, I found that workers' participation in non-work related activities during leisure hours produced small breaches in the accepted norms of control, offering potentially rich opportunities for critical reflection and dialogue. I argue that an analysis of complex and even contradictory worker subjectivities that are developed and performed in everyday life among Canada's SAWP workers offers a more nuanced understanding of worker solidarities, collective social movements and the potential for labour education at the margins of Canada's labour market.

Flexible Work Arrangements and Co-Worker Perceptions: The Relationship Between Values, Job Satisfaction and Organizational Commitment - Pitek, Joanna Marie (University of Toronto, 2015)
This dissertation explored the relationship between individual-level value differences and workplace attitudes. Using data from a sample of Canadian workers whose co-workers were currently using flexible work arrangements, the relationship between allocentrism and workers' job satisfaction and organizational commitment was explored. A workplace-allocentrism scale was developed and validated. The scale showed adequate validity and reliability and thus was used in the main study. The Co-Worker Model was developed and tested on a sample of adults in Canada who work in organizations where flexible work arrangements are used. Data were collected from an online research panel and then tested using structural equation modeling. The results indicate that allocentric value orientations were positively related to reported organizational commitment, mediated by job satisfaction. This study sheds light on the importance of understanding individual-level value differences when examining the effectiveness and/or ineffectiveness of organizational policies and practices.

Examining the Delineation of Jurisdiction Between Human Rights and Labour Arbitration After Figliola and Penner - Regan, Anne Elizabeth (University of Toronto, 2015)
There has been a long-time debate over whether issues conclusively decided at labour arbitration should be subject to a subsequent proceeding before a human rights tribunal. The author examines Supreme Court of Canada decisions dealing with re-litigation of issues before multiple decision-makers, and demonstrates how they are interpreted by the human rights tribunal. This paper identifies principles from cases before other decision-makers that can be applied to the problem of shared jurisdiction between labour arbitration and human rights.

Housework and Social Subversion: Wages, Housework, and Feminist Activism in 1970s Italy and Canada - Rousseau, Christina Adelina (York University, 2015)
My dissertation, Housework and Social Subversion: Wages, Housework, and Feminist Activism in 1970s Italy and Canada, presents a history of the Wages for Housework movements in Italy and Canada (1972-1978), looking at the parallel development of autonomist feminist politics in these locations. Based on a series of interviews with feminists involved in the movement, my dissertation highlights the significant political value in the way the groups theoretical perspective influenced our current understanding of social reproduction. Social reproduction refers to the unpaid activities associated with family and societal maintenance procreation, socialization, and nurturance as well as paid work in social sectors such as health care, education, childcare, and social services. In the context of Wages for Housework, my dissertation re-examines the movements understandings of wages, housework, and the gendered relations of production in the home. In critiquing the capitalist, patriarchal, imperialist nuclear family, they re-conceptualized wages and housework in a way that allowed for the uncovering of the most hidden aspect of housework: emotional labour and care. Looking at the parallel development of Wages for Housework movements in Italy and Canada, I also highlight the emergence of similar tensions regarding the demand for wages and the role of the working class housewife in their analyses. As Nicole Cox and Silvia Federici wrote, Our power as women begins with the social struggle for the wage, not to be let into the wage relation (for we were never out of it) but to be le out of it, for every sector of the working class to be left out of it (1975, 11). In light of the continued pervasiveness of care as work, this dissertation contributes to building a better understanding of social reproduction in a global context.

Job Developers in Transition: A Study of Informal and Nonformal Job Skills Training of Job Developers in Nonprofit Organizations in Ontario - Savia, Roy Della (University of Toronto, 2015)
Job Developers have complex and demanding jobs that require balancing the needs of organizations, employers, and job seekers. Job Developers must meet new employers and potential employees every day, earn their trust, and learn their needs. A common role Job Developers play is helping people find jobs and helping employers find employees. Job Developers attempt to learn what employers and job seekers need and what each can offer to match the right applicants to the right employers.Competent Job Developers must have organization, research, marketing, selling, communication, and negotiation skills. Job development has become a high growth occupation. Because the nature of their jobs changes constantly, Job Developers must also stays updated on employment trends and labor market information. While these changes provide opportunities for practitioners to expand their roles, they also impose increased demands and challenges to build their skills and capacity to perform their jobs. The job developer profession (also known as employment specialist) is a recently new concept in the nonprofit sector. Job Developers' potential as advocates for the unemployed, those with disabilities, and new immigrants is fundamental in today's competitive job market and in the context of equitable opportunity for employment. Informal and nonformal learning are well-recognized and well-used in the job development field. Job Developers rely on informal and nonformal learning for professional development and occupational autonomy.

Remembering the Civil Service: Work and Life Stories of Indigenous Labourers in the Canadian Federal Civil Service - Seguin, Alisha (Carleton University, 2015)
This thesis examines the life stories of six Indigenous civil servants who worked in the Canadian federal public service from the late 1960s until today. To contextualize these lived experiences, this thesis also explores the development of a culture of merit, representation, and employment equity within the federal civil service in the twentieth century. Stories of work were provided within the frame of larger life stories, allowing narrators to speak to both their perceptions of the civil service as an employer and also the role and meaning of this work within their lives. As a result, this thesis argues that the complexity of individual experiences, identity formation, and memory make it difficult to generalize about “the Indigenous civil servant” in any meaningful way. Relatedly, this thesis also emphasizes both the enriching possibilities and the unique challenges of conducting life story oral interviews and “sharing authority” in collaborative research projects.

The Worker and the War Machine - Smith, Autumn Danielle MacKenzie (York University, 2015)
This paper aims to discover the theatrical relationship between the working class and the factory of war. In that, it strives to prove that the lower income labourer is the cog of the machine: a nameless entity with an inescapable destiny. Through the paper and the subsequent production of Oh, What A Lovely War! I intend to give a voice to the worker and will struggle with my own blue collar identity, just as Joan Littlewood did in years past. This production and paper therefore is one of self-discovery and acceptance. In addition, it aims to prove that without the heroic efforts of the laboring class, there would be no war, as the cowardice of capitalism would fall without its soldiers.
Keywords: Directing; Factory; Games; In-Yer-Face; Joan Littlewood; Labourer; London; Machines; Pierrot; Theatre; Theatre Workshop; Working Class; World War I

A Community in Conflict: The Crowsnest Pass' 1932 Coal Strike - Stace, Trevor I. E. (University of Alberta, 2015)
In 1932, coal miners inside of Alberta's Crowsnest Pass struck for 195 days over working conditions. I use a multi-perspective approach and found my analysis on the basis of community to increase our understanding on industrial disputes. I explore the strike from the viewpoint of coal operators, miners, union organizers, women, the RCMP, and other residents inside the region to contextualize the experience of the strike. By using the starting point of community, I add to the ‘labour versus capital’ paradigm often employed in writings on industrial disputes. The Mine Workers Union of Canada represented the striking miners but it became clear that community consensus to support for the union was never reached. Resistance against the union formed on several fronts and often pitted strike supporters against those who disagreed. The strike is a reminder that tensions not only existed between classes but also within classes.

Standing up, Fighting Back: Fostering Collective Action in CUPE New Brunswick, 1963-1993 - Vinh-Doyle, William (University of New Brunswick, 2015)
The emergence of the Canadian Union of Public Employees (CUPE) in the 1970s as the largest union in Canada was a major development in Canadian labour history and the result of extensive efforts to organize unorganized civil servants and public employees. Public sector union growth has often been thought to have differed fundamentally from the experience of private sector unions, on the grounds that union rights were extended to public sector workers without struggle. The history of CUPE New Brunswick, established in 1963, and its predecessor unions in the 1950s demonstrates the complex struggles of civil servants and public employees to acquire and then to apply collective bargaining rights in the province of New Brunswick. While the enactment of the Public Service Labour Relations Act (PSLRA) in 1968 provided a legal means for civil servants to join a union and bargain collectively, public sector workers continued to struggle for improved wages and working conditions throughout the 1970s and 1980s. These conflicts, which drew on both membership mobilization and legal strategies, are shown in detail in the experience of CUPE members in Local 963, New Brunswick Liquor Store Workers, and Local 1252, New Brunswick Council of Hospital Unions, the umbrella organization representing hospital support workers. While locals within CUPE New Brunswick worked independently of one another, the more than 200 CUPE locals in the province joined together in 1992 to resist measures introduced by the provincial Liberal government. While this was essentially a defensive struggle to protect existing rights, it also represented a challenge to the emerging policies of neo-liberalism and a culmination of a tradition of collective action within the union.

Labour Law and Triangular Employment Growth - Bartkiw, Timothy John (York University, Osgoode Hall, 2014)
This thesis is concerned with understanding the relationship between labour law and triangular employment growth, and particularly in "staffing services" contexts. A review of alternative explanations for growth in triangular employment within three theoretical paradigm (neoclassical, institutionalist, and critical) illustrates the theoretical space for conceiving of a relationship between the particularities of labour law and triangular employment growth. To this end, the thesis develops the concept of a regulatory differential, or ways in which a legal regime may produce differential regulatory effects as between direct and triangular forms of employment. A typology of regulatory differentials is outlined. Further, a discussion of the relationship between these differentials and employer-status rules is provided, and it is suggested that the logic of the framework may helpfully inform analysis of triangular employment growth within a given jurisdiction, as well as comparative analysis of this phenomenon. The theoretical framework is then applied towards examining diverging growth rates in triangular employment as between Canada and the U.S. Legal analysis examining two key sub-fields of labour suggests that the presence (and expansion) of key regulatory differentials in the U.S., absent in Canada, may help explain the observed patterns of triangular employment growth in these countries.

Precarious Life, Work and Culture; Fields of Power: The Canadian Farmworkers Union - Berggold, Craig Josef Condy (Queen's University, 2014)
The contemporary precarious condition, ‘precarity,’ in life, work and culture parallels transformations in national and global economies, in part through the rise of immaterial production. Precarity has led to destabilization and reconfiguration of a class /class system and the creation of a new majority precarious class including domestic and farm workers, academic workers, care givers, part-timers and more. The thesis identifies how a historical moment of the Canadian Farmworkers Union (1979-1999) experienced marginal social protection, racial discrimination, limited legal rights, short-term contracts, vulnerable working conditions and precarious life without health care. The transnational lessons of the CFU include a better understanding organizing precarious citizens today — including what has not worked; importance of visual cultural analysis and counter-visuality to inform resistance. Theories of immaterial labour; porousness of international borders; lack of social protections; shorter career cycles; challenges to traditional craft unions; shift in social values as citizens organize across sectors, geographies and borders; and, migrant experiences as central to the experience of precarity. Confronted with the difficult task of re-imagining old ‘modernist’ visions of ‘class,’ ‘people,’ ‘nation-states’ and many established perspectives of resistance that have been stalemated. The thesis also includes a short survey of visual cultural expressions from twenty-first century precarious citizen groups. [This] The Master of Arts - Cultural Studies major project includes a 96-page illustrated history book entitled "Fields of Power: The Canadian Farmworkers Union," with photographs and text by [the author].

Irreconcilable Differences: The Corporatization of Canadian Universities - Brownlee, Jamie Kyle (Carleton University, 2014)
To date, there has yet to be a comprehensive national study of university corporatization in Canada. This study addresses this gap by reviewing the empirical basis, history, root causes and evolution of the transformation of higher education in Canada that has taken place over the past four decades. In this research, “corporatization” is used to refer to the process and resulting outcomes of the ascendance of business interests, values and models in the university system. Throughout the study, my two primary questions of interest are: (i) how has the corporatization of Canadian universities taken shape?; and (ii) what are the consequences of this restructuring both for higher education and society at large? The study begins with a brief historical review of the relationship between education and various sources of power, as well as some of the competing perspectives that have been used to explain university restructuring. I then review the main manifestations of the corporatization process, beginning with a detailed analysis of the casualization of academic labour. Drawing on a new and unique dataset collected through access to information requests, I provide a detailed account of the rise in the number of part-time and full-time contractually limited appointments in a number of Ontario institutions and discuss some of the impacts of this change. Subsequent chapters focus on the changing role of students (as consumers) in corporatized university spaces as well as changes in tuition and debt rates in Canada; how corporate management styles and practices have infiltrated university governance and programmatic and curriculum decisions; and the impact of corporate and commercial influences on academic research. Taken together, this evidence demonstrates that many of the defining characteristics of the public university are currently under threat, particularly its systems of governance, academic freedom, and its approach to teaching and research. Moreover, I argue that there are irreconcilable differences between university and corporate institutions. The study concludes with a discussion of the fact that acts of resistance need to go beyond calling for new regulations within the current environment and seek more radical measures, given the fundamental incompatibility between these types of institutions.

Workplace Harassment: A Cross-Jurisdictional Comparative Analysis of Legislative Responses to this Workplace Phenomenon in Canada - Carr, Kayla Alice (York University, Osgoode Hall, 2014)
This thesis investigates different statutory models Canadian legislatures have enacted to address workplace harassment. It adopts a qualitative, comparative case study approach, providing an in-depth comparative analysis of legislation from Québec, Saskatchewan, Ontario, Manitoba and British Columbia. Through this analysis, this thesis outlines the ways in which workplace harassment has been regulated in Canada, why that model was adopted by the jurisdiction and how that model measures against other models for legislating workplace harassment. Through an examination of existing literature relating to workplace harassment stemming from three theoretical paradigms and an analysis of a model legislative framework, this thesis creates a tool for scholars and lawmakers to use for future research and enactments of workplace harassment legislation. Overall, this thesis demonstrates that the varying and complex nature of the enacted legislation in the aforementioned Canadian jurisdictions leaves room for improvement for future enactments and amendments of workplace harassment legislation.

Re-Conceptualizing "Contributing" Homelessness and Unpaid Labour in a Neo-Liberal Climate - Choy, Mary Rebecca (York University, 2014)
The goal of this research was to challenge notions of “contributing” in active citizen discourse. This was done by exploring how individuals experiencing homelessness give back to their communities while surviving through social exclusion and life on the streets. Twelve semi-structured interviews were conducted with individuals who experienced homelessness between the ages of 40-64. This research found that respondents gave back to others through various forms of labour in ways that were mutually beneficial. Contributing to the well being of others helped respondents to cope with homelessness by gaining opportunities, resources, information, networks and developing a sense of well being, confidence or support. The findings suggest a need to re-conceptualize “contributing” in ways that recognize alternative forms of citizenship activities and participation. By doing so, all people, including people without homes, can be recognized as contributing citizens in their communities.
Keywords: Contributions; Feminist political economy; Homelessness; Labour; Marginalization; Neo-liberalism; Poverty; Reciprocity; Social; Social exclusion; Social reproduction; Social research; Social work; Sociology; Unpaid labour; Volunteerism

The Female Job Ghetto: Women’s Voices on Occupational Gender Segregation in Unionized Ontario Grocery Stores - Davies, Claire (University of Guelph, 2014)
This thesis adopts a socialist feminist perspective to explore women’s experiences with occupational gender segregation in unionized grocery stores across Southwestern Ontario. The thesis draws conclusions about the devaluation of women’s labour and how this devaluation impacts their economic and social status. Socialization theory and human capital theory, as well as explanations based on biology, are critiqued in this thesis, as these explanations do not fully account for occupational gender segregation. The results of this study suggest that occupational gender segregation is deeply entrenched in unionized grocery stores and the trend towards increasing profit by replacing full-time labourers with part-time labourers is further exacerbating the marginalization of women in paid labour. It is concluded that women’s labour has been steadily devalued and that class and patriarchy severally limit women’s overall upward mobility by concentrating women in highly gendered part-time low skilled jobs in grocery stores.

The Institutionalisation of Regional Integration in North America - Farías Pelcastre, Iván (University of Birmingham, 2014)
Current studies of regional integration in North America claim that this process is limited to the entering of intergovernmental agreements that aim to expand and enhance crossborder flows of goods and capitals between Mexico, Canada and the US. Such studies claim that the political effects of the process on nation-states are limited and constrained by the decisions of the national governments. In contrast, this thesis argues that the actions of transnational actors have increased the policy interdependence between the three countries in the arenas of environmental protection, labour cooperation and protection of foreign direct investment. Transnational actors have used, applied and interpreted the rules originally created by the intergovernmental agreements –NAFTA, NAAEC, BECA and NAALC– and have subsequently demanded additional and improved rules. Regional institutions have in turn responded to these demands by supplying new and improved regional rules. In doing so, transnational actors and regional institutions have furthered the policy interdependence between the three countries. This phenomenon, known in other contexts as institutionalisation, demonstrates that the process of regional integration in North America is more substantial than previous studies claim. In addition, it illustrates the relevance of the theories of Liberal Intergovernmentalism and Supranational Governance to the analysis of the emergence and development of the North American integration process.

"Outside Agitators and Ungrateful Kids": The Making of the Working Class in Rural Newfoundland - Fournie, Mitchell S. (Memorial University of Newfoundland, 2014)
The 1971 Burgeo strike was a central moment in the development of working-class consciousness in Newfoundland. Combining archival sources with the author‘s own field interviews, this thesis illustrates how the development of industrial production during the two and a half decades after the Second World War generated a corresponding shift in the society and culture of rural Newfoundland. The resulting narrative demonstrates a model of class formation in the "industrial villages" of outport Newfoundland.

"Hire the Handicapped!": Disability Rights, Economic Integration and Working Lives in Toronto, Ontario, 1962-2005 - Galer, Dustin (University of Toronto, 2014)
This dissertation argues that work significantly shaped the experience of disability during this period. Barriers to mainstream employment opportunities gave rise to multiple disability movements that challenged the social and economic framework which marginalized generations of people with disabilities. Using a critical analysis of disability in archival records, personal collections, government publications and a series of interviews, I demonstrate how demands for greater access among disabled people to paid employment stimulated the development of a new discourse of disability in Canada. Including disability as a variable in historical research reveals how family advocates helped people living in institutions move out into the community and rehabilitation professionals played an increasingly critical role in the lives of working-age adults with disabilities, civil rights activists crafted a new consumer-led vision of social and economic integration. Separated by different philosophies and bases of support, disability activists and allies found a common purpose in their pursuit of economic integration. The focus on employment issues among increasingly influential disability activists during this period prompted responses from three key players in the Canadian labour market. Employers embraced the rhetoric and values of disability rights but operated according to a different set of business principles and social attitudes that inhibited the realization of equity and a ‘level playing field.’ Governments facilitated the development of a progressive discourse of disability and work, but ultimately recoiled from disability activism to suit emergent political priorities. Labour organizations similarly engaged disability activists, but did so cautiously, with union support largely contingent upon the satisfaction of traditional union business first and foremost. As disability activists and their allies railed against systematic discrimination, people with disabilities lived and worked in the community, confronting barriers and creating their own circles of awareness in the workplace. Just as multiple sites of disability activism found resolution in the sphere of labour, the redefinition of disability during this period reflected a shared project involving collective and individual action.

Bringing Labor Back In: Varieties of Unionism and the Evolution of Employment Protection and Unemployment Benefits in the Rich Democracies - Gordon, Joshua (University of Toronto, 2014)
This thesis looks at the politics of labor market policy in the postwar period in the advanced industrialized democracies. Specifically, the dissertation seeks to explain stark cross-national differences in unemployment benefit systems and employment protection legislation. The theory advanced in this thesis emphasizes significant differences in union organization across the rich democracies. This view, “Varieties of Unionism”, shows how the varying political capacities and policy preferences of labor movements explain most of the cross-national policy differences. In particular, the research points to union movements’ ideological traditions and varying rates of union density, union centralization, and involvement in unemployment benefit administration as crucial explanatory forces. Each feature of union movements captures an important part of why they might choose to advocate on behalf of the unemployed and to their differential ability to have those policy preferences realized, as well as indicating the kinds of preferences they will have for employment protection legislation. In the case of policies directed at the unemployed (or so-called labor market ‘Outsiders’), these insights lead to the construction of an index of “Outsider-oriented Unionism”, which correlates very closely to cross-national variations in unemployment benefit generosity as well as to active labor market policy spending. The thesis also introduces a new fourfold typology of unionism that helps to explain the different combinations of employment protection legislation and ‘Outsider policy’ generosity that exist among the rich democracies, or labor market policy ‘regimes’. The thesis makes this argument with multiple regression analysis of fifteen rich democracies and with detailed historical case studies of Britain, The Netherlands, and Sweden. In making this case, the thesis strongly challenges the explanations of labor market policy put forward by the Varieties of Capitalism literature and Insider-Outsider theory. In addition, the thesis reformulates the traditional Power Resource view by introducing a more rigorous theory of labor movements’ policy preferences and thereby qualifies recent statements that have emphasized partisanship almost alone. Most broadly, the theory challenges the “individualist turn” in recent comparative political economy scholarship and suggests that the field needs to return its gaze far more toward organized interests.

The Impact of Informal Caregiving Intensity on Labour Market Outcomes - Jacobs, Josephine Christina (University of Toronto, Institute of Health Policy, Management and Evaluation, 2014)
Most OECD countries have introduced policies shifting health care into community settings. These policies rely on informal caregivers to provide care to disabled or ill family and friends. At the same time, there are policies in place promoting labour market retention. To better understand how caregiving and labour policies may interact to affect the available pool of caregivers and labour force participants, we need more evidence about how informal caregiving is related to labour market outcomes. We explore this issue through three empirical studies, with a focus on caregivers who provide significant amounts of weekly care (i.e. intensive caregivers).The first study uses the Canadian cross-sectional General Social Survey to determine whether providing informal care is associated with various labour market states. We find that intense caregiving is associated with being fully retired for men and women. High intensity caregivers are also more likely to be retired before age 65. In the second study, we use the American National Longitudinal Survey of Mature Women and control for time-invariant heterogeneity and time-varying sources of bias amongst retirement-aged women. We find that women who provide at least 20 hours of informal care per week are 3 percentage points more likely to retire relative to other women, which supports the idea that intensive caregiving may cause women to retire. Finally, given changes in the policy, demographic, and cultural contexts, we use the American National Longitudinal Surveys of Young and Mature Women to explore whether labour market penalties have changed over time. Following two cohorts of pre-retirement aged women, we find that intensive informal caregiving is negatively associated with labour force participation for both pre-Baby Boomers and Baby Boomers. The caregiving effects are not significantly different across cohorts, implying that, despite the introduction of offsetting policies, labour market penalties for caregivers have persisted.

Rules of Disengagement: 'Low Skill' Migrant Workers, Law and the Social Dimensions of Exclusionary Inclusion - Jowett, Brendan Breckman (York University, Osgoode Hall, 2014)
This thesis interrogates social exclusion among migrant workers under the NOC C & D (“low skill”) occupational stream of Canada’s Temporary Foreign Worker Program, a relatively new, fast-growing, and highly diverse stream which brings migrant workers into industry sectors and social settings where they were never seen before. The author develops a framework for understanding law’s role in producing social exclusion, and applies it to ethnographic data collected through interviews with migrant justice advocates and migrant workers in Brandon, Manitoba. This thesis ultimately establishes that migrant workers need not face spatial separation, discrimination from the community, or a historically gendered and racialized labour context in order to experience social exclusion; the author argues that social exclusion is legally constructed and that the legal framework of this program itself presents barriers to migrants’ full participation in the life of the communities in which they live and work.

Mapping the Division of Labour in Long-Term Residential Care Across Jurisdictions - Laxer, Katherine Erika (York University, 2014)
Despite the international emphasis on care in private homes, the demand for long-term residential care is rising given the growing number of older persons and those living with severe disabilities. Rising acuity levels of residents have resulted in calls for more training for care providers and concerns have been raised about the supply of workers, drawing attention to the working conditions, pay, benefits and status attached to work in long-term residential care. This industry is a link in the international care chain, with wealthy countries seeking workers from poorer countries. Yet, cross-national data sources provide limited information on the long-term residential care labour force, reflecting the value attached to the sector and the level of concern about the well-being of the labour force. Data that are available indicate that care is prioritized, divided and measured in different ways in different contexts and that there are varying degrees of precariousness experienced by workers. The evidence from the data also suggests that the public not-for-profit sector and unionization are critical shelters for the mostly women providers. Using a feminist political economy approach, this thesis outlines data available from statistical sources in Europe and North America with a case examination of four countries: Canada, the United States, the United Kingdom and Sweden. It critically maps the comparative data on the supply of labour in this industry of health and social care, as well as on their locations and relations. It illustrates the extent to which the framing of care in conventional terms, influenced by both neoliberal and medical notions of care, limits the statistical infrastructure in terms of its capacity to adequately measure workforces involved in long-term residential care and to provide a basis for addressing the continuing supply of labour in this sector.

Disability, Underemployment and Social Change - Lee, Susan Sau-Yee (University of Toronto, 2014)
Informed by the disciplines of disability studies and interpretive sociology, and using the social model of disability and the collective identity model, this dissertation pursues an investigation of underemployment. Underemployment, conceptualized as the underutilized skills and knowledge of the employed and unemployed, occurs at higher levels amongst disabled persons than among non-disabled people (Canada, 2009). Semi-structured interviews with 14 underemployed disabled people conducted, to investigate the experiences of disabled persons who worked in the fields of education, computer, healthcare, fitness, environment, travel, social work, government and non-government agencies. In addition, Canadian social policies were analyzed to address the research questions: 1) How do disabled workers understand and address experiences of underemployment? 2) How do organizations and social policies account for underemployment amongst disabled persons? 3) How can practices which acknowledge and enhance collective identity be used to address underemployment and advance the disability movement? 4) How can underemployment amongst disabled persons be addressed at the organizational level? The texts of these narratives and Canadian social policies were analyzed using a critical interpretative textual analysis approach. The analysis demonstrates the depths of the negative consequences of high levels of underemployment resulting from structural, environmental and attitudinal barriers. Such consequences include lack of opportunities for recognition, compensation, promotion, accommodations, and career fulfillment, as well as poor mental, physical, emotional and social health. This research study is unique as it reveals the struggles that disabled persons experienced in work contexts, their narratives of resistance, and their recommendations for socio-political change to build more inclusive work environments

“Go to Work on Monday One More Time”: An Analysis of the Compensation Process for Occupational Disease at General Electric in Peterborough - Luckhardt, Natasha (McMaster University, 2014)
This paper provides a historical, socioeconomic and political analysis of the compensation claims process for former General Electric workers in Peterborough. To provide context to the issue, the literature analyzes the evolution of the compensation process, the history of asbestos and occupational cancer in Canada and more specifically, Ontario, chemical causation considerations and the government and large industry’s participation in these issues. In order to examine the complexity of the compensation process in Peterborough, the key players involved in the process were interviewed and include representatives from CAW/Unifor, Occupational Health Clinic for Ontario Workers (OHCOW), OWA (Office of the Worker Advisor), Workplace Safety and Insurance Board (WSIB), Occupational and Environmental Health Coalition of Peterborough (O&EHC-P), as well as former workers and their families. The testimonials deliver insight on issues such as the range of asbestos and chemicals used in the plant, the lack of causation data to support workers’ claims, the use and abuse of science in the process, the socioeconomic relevancy of GE in Peterborough, the environmental devastation created by the manufacturing industry in the city and the tensions between the intended and applied responsibilities of the key players. The overall findings were that the workers feel invisible to the major players involved, ignored by the community and overwhelmed by the system. To provide a deeper understanding of these issues, there are three groups of case studies examined: the compensated, the uncompensated and the families. The recommendations include a need for a concerted effort by all key players to ensure the workers’ right to a fair and just compensation process, enhanced education within the community on occupational health and safety, legislation reform, increased causation data, community mobilization efforts and environmental studies examining the water, air and soil in Peterborough and surrounding areas.

Unemployed Women in Neo-Liberal Canada: An Intersectional Analysis of Social Well-Being - Nichols, Leslie J. (Ryerson University, 2014)
This study explores the lived experiences of unemployed women in neo-liberal Canada, through interviews with a diverse sample of participants between the ages of 25 and 40 from the cities of Toronto and Halifax. The results were analyzed using intersectional and grounded theory. The study resulted in four main findings. First, the study builds on intersectional methodology by McCall (2005) and Hancock (2007) to indicate the significance of context-specify and fluidity of identities. The significance of intersectionality theory is that there is not one salient identity; rather the impacts of identities are context dependent. Second, the neo-liberal erosion of the state infrastructure is manifested in a paucity of supports for unemployed workers. The unemployed woman workers do not only have to face a lack of adequate support when they become unemployed but they also do not have adequate support in other aspects of their lives including child care, retraining, health care and labour market supports while employed. Thus, many women do not have access to adequate living conditions without reliance on a male partner. Third, the health of the women was negatively affected, whether precariously employed or unemployed. They have insecurity around not being able to plan their future, and living on limited money and poor health care benefits. Finally, regional economic differences may be disappearing while all EI measures are brought towards the lowest common denominator. Thus, neo-liberal labour market policies put women, and particularly women with intersectional identities, in jeopardy. This study makes four policy recommendations: (1) to create social policies that address intersectional identities to allow women a real choice in facing competing demands of wage work and dependent care; (2) to create policies to curb the impacts of precarious employment; (3) to create EI policies not bound by regions but to the needs of the labour market including the growth of precarity; and (4) in the interim, to introduce extended health benefits to improve the situation of unemployed and precariously employed workers.
Keywords: Gender-based analysis – Canada; Social justice – Canada; Unemployed women workers – Canada – Social aspects; Unemployed women workers – Canada – Social conditions; Unemployed women workers – Services for – Canada; Unemployment insurance – Government policy – Canada – Evaluation; Women – Employment – Canada

Class Struggle and Solidarity in Neo-Liberal Times: The 1986 Gainers Strike - Samoil, Andrea (Trent University, 2014)
The lengthy and raucous 1986 Gainers meatpacking plant strike in Edmonton, Alberta was one of the most important events in recent Alberta labour history. In the midst of the economic crisis of the 1980s and the rise of neo-liberal ideas, the strike marked a backlash by both the labour movement and ordinary citizens against attacks on workers and unions. Characterized by widely covered picket line violence, repressive police and court actions, and government unresponsiveness, the strike generated massive solidarity within and beyond the labour movement. This solidarity originated in a rejection of the neo-liberal new reality of Alberta typified by high unemployment, anti-union laws and practices, and lack of government welfare support, and it generated a provincial change the law campaign, national boycott, and rising class consciousness. The working class mobilization during the Gainers strike was a watershed for the Alberta labour movement.
Keywords: Alberta federation of labour; Gainers strike; Neo-liberalism; Social sciences; Solidarity; Working class

Immigrant Women and their Work in the Informal Economy in Toronto: Impacts and the Potential for Critical Transformations - Santhosh Thomas, Agnes (University of Toronto, Ontario Institute for Studies in Education, 2014)
This research examines the everyday experiences of immigrant women working informally in the City of Toronto (Canada). The study is based on analysis of original in depth interview (n = 27) and focus group data (n = 19). The thesis begins from the belief that the choice of highly educated immigrant women, with and without professional work experiences from their home countries, to do informal work in Canada is part of a fact that they are going through a particularly intensive process of change. With special attention to the potential for critical transformative learning (e.g. Mezirow; Freire) - how this change is produced, experienced, and addressed is the key focus in this study. The study considers three avenues of experience potentially influencing change in the lives of immigrant women post-immigration: i) the ways of knowing, frames of reference, and worldviews of these women as shaped by the complex relationship between their private (e.g. as mothers and wives) and public (e.g. as community members and informal product/service workers) lives; ii) the various economic and cultural relations and shifting locations that mediate how the individual makes choices regarding (formal and/or informal) work activities; and, iii) the social relations shaping the changing experiences and interpretations of interlocking systems of power relations involving gender, race, class and disability.Agentive participation and learning in the context of economic participation are key in understanding women's choices, experiences, and outcomes in the context of their work and life experiences in Canada. This study reveals the multidimensional, often contradictory, processes of change that individuals in marginalized situations post-immigration go through and their awareness of and influence over these change processes. The analysis suggests a multilayered process that supports and sometimes inhibits the creation of a new foundation for various types of transformative learning trajectories; one that keeps the loose threads together and moves people towards and along a path they individually or collectively choose to follow in order to find meaning and realize positive change.

The Making of a Labour Activist: James W. Orr, Saint John, New Brunswick, 1936-2009 - Stairs, Ryan (University of New Brunswick, 2014)
James W. Orr (1936-2009) was one of a number of rank-and-file labour militants in the city of Saint John, New Brunswick who bore witness to, and had some hand in, a number of upheavals in the local labour movement. Growing up in a working-class neighborhood in west Saint John, he came of age at the time of the momentous Canadian Seamen’s Union strike of 1949, which had a permanent impact on his outlook. Leaving school at sixteen to work for the Canadian Pacific Railway, he then joined the navy before going on to become a lifelong union man on the docks. As a member of Local 1764, International Longshoremen’s Association, he helped lead the 1974 strike against the Maritime Employers’ Association. He was one of the organizers of the 1976 Saint John General Strike on 14 October against the federal government’s wage controls. Orr was also a key organizer of the 1979 NO CANDU campaign that closed the port in support of civil rights for workers in Argentina. Within the ILA, he helped open union membership for non-union workers on the docks, an effort that cost him his position as a union officer; however, the influx of new blood rejuvenated the ILA and reoriented it in the direction of social unionism. Local 273 went on to replace the archaic shape-up system with a dispatch system while also struggling against the bureaucracy of the international union and for the autonomy of Canadian locals. The object of this study is to rescue Jimmy, or “the Bear” as he was affectionately called, from what the influential social historian E.J. Hobsbawm describes as “the anonymity of the local militant.” This study relies heavily upon oral history, including two interviews completed before Orr’s death, and his personal papers deposited at the Provincial Archives of New Brunswick.

The Relationship Between a Strategic Approach to Quality and Employee Happiness - Stoehr, A. (University of the West of England, Bristol, 2014)
This research explores the relationship between a strategic approach to quality management in Canadian organizations and employee measures of happiness. In particular, it investigates how a strategic approach to quality management impacts on employee satisfaction, engagement, and morale. Understanding the relationships between a strategic approach to quality management and employee measures of happiness helps companies, policy-makers, and academia. Companies can use the conclusions to decide on the value of a quality management system as it relates to employees. The findings provide answers to employees, management, and labour unions that need to understand the impact a strategic approach to quality will have on them. Policy-makers can use the findings to set the agenda for closing Canada’s productivity gap. Knowledge of this research can support policy-maker decisions to simplify the process for implementing a strategic approach to quality, realizing the benefits for participating organizations and employees at those organizations. This research helps academia fill two major gaps in the literature: First, the impact that the implementation of a strategic quality approach has on employee happiness (namely satisfaction, engagement, and morale). The second is the focus on Canadian organizations. There are relatively few studies that investigate a strategic approach to quality that focus on Canadian companies. Much of the research related to strategic quality employs data from American, Asian, Australian, and European organizations whereas this research uses data from exclusively Canadian organizations. This is the only academic research (to the knowledge of the researcher) that uses original Canada Awards for Excellence recipient results to draw conclusions. In this research, organizations with a strategic approach to quality (Canada Awards for Excellence recipients) are compared with similar size organizations with no defined approach to quality (non-winners). A 66-question survey was used with 591 respondents representing 58.68% response rate from 12 Canadian organizations. The participating organizations were a mix of small and medium size organizations ranging in size from 5 employees to 400 employees in both the service and manufacturing sectors. The survey respondents included 315 from Canada Award for Excellence winners and 276 from non-winners. Of the 12 organizations studied, five are Canada Award for Excellence winners and seven of them are non-winners. The research provides evidence that organizations taking a strategic approach to quality have a positive impact on the employees of that organization. The research has found significant connections between an organization’s level of strategic quality and the effect on employees in terms of morale, engagement, and satisfaction. The survey alongside focus group analysis shows that there is a clear relationship between strategic quality and employee measures of happiness. The findings indicate that the impact of implementing quality is positive and results in benefits for both the organization as a whole and the individual employee. Significant differences are noted between Canada Award for Excellence winners and non-winners.

Captains of Industry Crewing the Ship of State: Dollar-a-Year Men and Industrial Mobilization in WWII Canada, 1939-1942 - Stuart, Jeremy (University of Calgary, 2014)
[E]xamines the role and influence of Canadian manufacturers and executives working for the Canadian government, known as the dollar-a-year men, in mobilizing the Canadian economy for war production. Based chiefly on primary source research this thesis examines contracting methods, the bureaucratic structure of the Department of Munitions and Supply, and the degree to which the Department reacted to events. This thesis demonstrates that the dollar-a-year men's strategy for industrial mobilization was initially focused on maximizing production at almost any cost, and only started focusing on cost efficiency in late 1942 and early 1943. It is also demonstrated that the current historiography is lacking and that C.D. Howe played a far different role than the historiography describes.
Keywords: Department of munitions and supply; Dollar-a-year men; Howe; C. D. (Clarence Decatur); 1886-1960

Working-Class Anguish and Revolutionary Indignation: The Making of Radical and Socialist Unemployment Movements in Canada, 1875-1928 - Thompson, David (Queen's University, 2014)
Taking a telescopic view of the multifaceted struggles of the workless prior to Black Tuesday challenges the myopic picture of the Great Depression as the sudden, unexpected eruption of unemployment protest. Out of all proportion to their size and political strength, radical unemployment agitators between 1875-1928 proved to be vital protagonists in forcing relief measures, thrusting socialist values into public discourse and inspiring working-class resistance during economic crises and at times when the labour movement was at its weakest. This dissertation examines hundreds of unemployment protests in urban centres across Canada during the 1872-1896 long depression, and the economic slumps of 1907-1909, 1912-1915 and 1921-1926. These protests and the organizations of the workless challenged three distinct but overlapping stages in the evolution of the liberal-capitalist state: producer, progressive, and authoritarian. Although always vulnerable and contingent, the mobilized workless responded with innovation to the evolution of liberal capitalism and, by gravitating towards the developing socialist alternative, gained greater coherence and uniformity as they moved from the local and spontaneous “les Misérables” (1875-1896) to an ad hoc “Organized Mob” (1907-1915) to a militant and sporadically nationally-organized “Unemployed Army” (1919-1935). This study contends that the persistence of a moral economy, the strategies of disruption, and working-class anguish and indignation were key resources for the radical and socialist organizers of the unemployed. Sensitive to the ways in which a culture of whiteness and masculinity often precluded greater solidarity amongst the workless, this dissertation also traces the ways unemployed diaspora socialists, socialist feminists and their allies encouraged a more diverse and inclusive movement. Far from reactionary or apathetic, the mobilized unemployed were every bit as important to the vitality of the left as unions or political parties – their struggles were crucial elements in the development of Canada’s earliest socialist experiments. Similarly, Canadian social policy history is unintelligible without an acknowledgment of the fundamental role that unemployment movements played in wresting concessions from the liberal order and as disruptive agents in the shaping of the welfare state.

Masculinity, Medicine and Mechanization: The Construction of Occupational Health in Northern Ontario - Wilde, Terence Peter (York University, 2014)
This dissertation examines workplace issues and events that shaped men’s health, and the healthcare services in support of them, in northern Ontario’s resource extraction industries. Between 1890 and 1925 there were important transformations in the hardrock mining sector including: technological innovations and refinements of the materials and devices used to extract ores; the healthcare mandated and legislatively prescribed but challenging to deliver to frontier workspaces; and how the complex interactions of the men, their work, their communities, wartime demands and collective bargaining combined to construct new definitions of masculinity. Using quantitative data from the Ontario Bureau of Mines on the numbers of annual accidents and fatalities, a clearer understanding emerges that reveals how workingmen’s bodies were understood over time. Together with newspaper accounts, the reports of coroners’ juries, personal papers, doctors’ memoirs and popular histories, the role of work and workplace conditions clarifies how health was managed or how it suffered as the exploitation of the provinces natural resources began in earnest. The impact of World War One caused a wholesale change in the scale and importance of the mines and the men that worked them. This was seen in their solidarity, strength and successful strike immediately after the war and in fewer accidents and fatalities. The pace of change, however, faded in the post-war era. The gains that were made were kept and men’s health and safety never again saw the alarming losses as those enumerated here.

Living the Dream: Precarious Labour in the Live Music Industry - Zendel, Adam Michael (University of Toronto, 2014)
This thesis explores the precarious nature of backstage work within the live music industry. Live music is replacing recorded music as the economic core of the music industry. Live music is a unique sector, in that it is valued for its ephemerality. Given the ephemerality of concerts, new frameworks are required to understand technical and logistical production of live music. Labour arrangements in live music reflect sweeping trends in the labour market. Backstage workers are employed in flexible, contract and contingent arrangements leading to precarious livelihoods. This thesis argues that labour precaritization in the live music industry is part of an accumulation strategy by suggesting that employers exploit the affective, emotive and cathartic nature of live music to reduce wages and extract surplus from workers. Essentially, workers are willing to accept a psychic wage in lieu a living wage. This arrangement can be called `lifestyle labour' in that workers are willing to accept lifestyle components as part of their wage.
Accepted: 2015-05-22T16:10:05Z

Aboriginal Dispossession and Proletarianization in Canadian Industrial Capitalism: Creating the Right Profile for the Labour Market - Bird, John Albert (University of Regina, 2013)
The central theme of this paper revolves around the dispossession of Aboriginal peoples (First Nations, Métis, and Inuit) from their traditional socio-economic means of production and their subsumption into the industrial-capitalist mode of production. The investigation is a hypothesis about the historical proletarianization process regarding Aboriginal peoples in Canada stemming from dispossession. The analysis utilizes a critical political economic approach primarily in regard the revolutionary power of private property relations as the competitive antithesis to traditional-subsistence economy relations. Positing the facts of Aboriginal proletarianization within a political economic framework is an addition to the critique of capital. The research of the paper is anchored within: the numbered treaty framework and its application, the disciplinary methods of residential schooling systems, assimilation into proletarian ethics, and contemporary statistics about Aboriginal cohorts within the Canadian labour market. The historical research provides evidence about Aboriginal socio-economic dispossession and the contemporary data provides evidence regarding present-day conclusions of the initial industrial-proletarianization processes. Keywords: numbered treaties, residential schools, Aboriginal labour, Aboriginal history, political economy, industrial capitalism, proletarian, Karl Marx.

L’évolution de la qualité d’emploi des immigrants du Canada par rapport aux natifs : une comparaison interprovinciale - Boulet, Maude (Université de Montréal, 2013)
Il est bien connu que les immigrants rencontrent plusieurs difficultés d’intégration dans le marché du travail canadien. Notamment, ils gagnent des salaires inférieurs aux natifs et ils sont plus susceptibles que ces derniers d’occuper des emplois précaires ou pour lesquels ils sont surqualifiés. Dans cette recherche, nous avons traité de ces trois problèmes sous l’angle de la qualité d’emploi. À partir des données des recensements de la population de 1991 à 2006, nous avons comparé l’évolution de la qualité d’emploi des immigrants et des natifs au Canada, mais aussi au Québec, en Ontario et en Colombie-Britannique. Ces comparaisons ont mis en évidence la hausse du retard de qualité d’emploi des immigrants par rapport aux natifs dans tous les lieux analysés, mais plus particulièrement au Québec. Le désavantage des immigrants persiste même lorsqu’on tient compte du capital humain, des caractéristiques démographiques et du taux de chômage à l’entrée dans le marché du travail. La scolarité, l’expérience professionnelle globale et les connaissances linguistiques améliorent la qualité d’emploi des immigrants et des natifs. Toutefois, lorsqu’on fait la distinction entre l’expérience de travail canadienne et l’expérience de travail étrangère, on s’aperçoit que ce dernier type d’expérience réduit la qualité d’emploi des immigrants. Dans ces circonstances, nous trouvons incohérent que le Canada et le Québec continuent à insister sur ce critère dans leur grille de sélection des travailleurs qualifiés. Pour valoriser les candidats les plus jeunes ayant peu d’expérience de travail dans leur pays d’origine, nous suggérons d’accroître l’importance accordée à l’âge dans ces grilles au détriment de l’expérience. Les jeunes, les étudiants étrangers et les travailleurs temporaires qui possèdent déjà une expérience de travail au Canada nous apparaissent comme des candidats à l’immigration par excellence. Par contre, les résultats obtenus à l’aide de la méthode de décomposition de Blinder-Oaxaca ont montré que l’écart de qualité d’emploi entre les immigrants et les natifs découle d’un traitement défavorable envers les immigrants dans le marché du travail. Cela signifie que les immigrants sont pénalisés au chapitre de la qualité d’emploi à la base, et ce, peu importe leurs caractéristiques. Dans ce contexte, la portée de tout ajustement aux grilles de sélection risque d’être limitée. Nous proposons donc d’agir également en aval du problème à l’aide des politiques d’aide à l’intégration des immigrants. Pour ce faire, une meilleure concertation entre les acteurs du marché du travail est nécessaire. Les ordres professionnels, le gouvernement, les employeurs et les immigrants eux-mêmes doivent s’engager afin d’établir des parcours accélérés pour la reconnaissance des compétences des nouveaux arrivants. Nos résultats indiquent aussi que le traitement défavorable à l’égard des immigrants dans le marché du travail est plus prononcé au Québec qu’en Ontario et en Colombie-Britannique. Il se peut que la société québécoise soit plus réfractaire à l’immigration vu son caractère francophone et minoritaire dans le reste de l’Amérique du Nord. Pourtant, le désir de protéger la langue française motive le Québec à s’impliquer activement en matière d’immigration depuis longtemps et la grille de sélection québécoise insiste déjà sur ce critère. D’ailleurs, près des deux tiers des nouveaux arrivants au Québec connaissent le français en 2011. It is well documented that immigrants face many difficulties in the Canadian labour market. Particularly, compared to native-born, they earn lower wages, occupy more precarious jobs and are often overqualified. In this research, we discuss these three issues in terms of job quality. Using the data from the 1991 to 2006 Canadian population censuses, we compare the trends in job quality of immigrants and native-born in Canada, Quebec, Ontario and British Columbia. These comparisons highlight the rising gap in job quality between immigrants and native-born in the four geographical areas, but especially in Quebec. This gap persists even after controlling human capital, demographic variables and unemployment rate at entry in the labour market. Overall, we found that education, work experience and language skills improve the job quality of immigrants and their native-born counterparts. However, when we separate Canadian and foreign work experience, we find that the latter type of experience reduces job quality of immigrants. In these circumstances, it is counterproductive that Canada and Quebec continue to insist on this criterion in the point systems. We also suggest increasing the importance of age in the point systems in order to encourage the admission of younger candidates with little or no foreign experience. Youth, foreign students and temporary workers who already have work experience in Canada appear to be ideal candidates for immigration. Nevertheless, using Blinder-Oaxaca decomposition method, we show that the job quality gap between immigrants and natives is mainly due to unfavourable treatment of immigrants in the labour market. This means that immigrants are penalized in terms of job quality regardless of their characteristics. In this context, the selection of the best candidates for immigration may produce a limited effect. We therefore suggest acting downstream with public policy to support employment integration of immigrants. To do so, a better coordination between all actors in the labour market is required. Professional orders, government, employers and immigrants must establish accelerated pathways of skills recognition for newcomers. In addition, our results indicate that the treatment of immigrants in the labour market is more problematic in Quebec compared to Ontario and British Columbia. It is likely that Quebec society is less open to immigration given its francophone character and its minority status in North America. Since the beginning, the desire to protect the French language motivates Quebec to be actively involved in immigration and the Quebec point system already emphasizes this criterion. Moreover, nearly two-thirds of newcomers to Quebec speak French in 2011.
https://doi.org/1866/10132

Solidarity by Association: The Unionization of Faculty, Academic Librarians and Support Staff at Carleton University (1973–1976) - Bufton, Martha Attridge (Carleton University, 2013)
In the mid-1970s, three employee groups at Carleton University changed campus labour relations dramatically: the professors and librarians who belonged to the Carleton University Academic Staff formed the first Ontario faculty union in June 1975; nine months later the Ontario Labour Relations Board certified the Carleton University Support Staff Association as the bargaining agent for the administrative and technical staff. The history of faculty labour action at Carleton has been told but not that of either academic librarians or support staff so this case of unionism provides a unique opportunity to compare their experiences. Working primarily with oral histories, I argue that status was critical to mobilizing labour action at Carleton. These employees—many of whom were women—wanted a fair workplace but deliberately chose an independent association over a trade union because such “solidarity by association” was compatible with their deeply held beliefs about their work and place on campus.
https://cha-shc.ca/prize-winner/martha-attridge-bufton/

Negotiating Precarious Cultural Work: Freelance Writers and Collective Organization in Media Industries - Cohen, Nicole S. (York University, 2013)
Commentary on freelance work in the cultural industries suggests that freelancers are autonomous "free agents" who enjoy fulfilling work and control over their careers. Yet empirical research demonstrates that freelance media work is becoming increasingly precarious. This dissertation is a case study of the working conditions of Canadian freelance writers, the political economic and cultural context in which they work, and their efforts to organize collectively to address challenges they face. The dissertation examines the underlying processes, practices, and power relations that shape the work of freelance writing to argue that freelancers' experiences flow directly from the capitalist logic of the corporate cultural industries in which they work. In this view, freelance writing has been transformed from being primarily a strategy of resisting salaried labour by journalists—an effort to gain some control over the terms of commodification of their labour power and autonomy over their craft—into a strategy for media firms to intensify exploitation of freelance writers' labour power through two primary strategies: the exploitation of unpaid labour time and control of copyright to writers' works. Drawing on Marxist political economic analysis, a survey of Canadian freelance writers, and interviews with freelance writers' unions and organizations, the dissertation examines how exploitation is obscured in freelance cultural work and how it can be confronted through collective organization. The dissertation examines Canadian freelance writers' current organizing efforts: a professional association, a union, and an agency-union hybrid, arguing that the models freelancers favour tend to reinforce notions of professionalism and a preference for service-based organizations, which has not given freelancers the power required to effectively defend themselves against corporations' changing business practices. The dissertation outlines the challenges writers' organizations need to overcome, not least freelance writers' ambivalence toward their status as workers. Finally, the dissertation foregrounds labour processes as central to understanding media, suggesting that continual downloading of the risks of journalistic labour onto precarious workers will have implications for the future of freelance writing as an occupation and the media content produced.
https://www.mqup.ca/writers–rights-products-9780773547964.php
Keywords: Communication and the arts; Social sciences

The Seasonal Agricultural Workers Program: Looking at Mexican Participation Through a Magnifying Glass - Cruz-Lopez, Irma Fabiola (University of Ottawa, 2013)
Mexican migrant workers have been coming to Canada since 1974 to work in agriculture as participants of the Seasonal Agricultural Workers Program (SAWP). Presently, Mexicans constitute the majority of SAWP workers. As well, Ontario is the main receiver of these workers followed by British Columbia and Quebec. Accordingly, the scope of this thesis mainly encompasses Mexican workers in Ontario. However, the thesis also includes Mexican SAWP workers in Quebec and British Columbia. This thesis reveals two main issues: (1) that all SAWP workers, particularly Mexican workers, lack key legal rights and protections relating to labour relations, employment, health and safety standards at the structural level of the SAWP; and at the federal, provincial, and international levels. (2) Even when they have rights under legislation relating to the above-mentioned subject matters, Mexicans, especially, lack the capacity to access them. Thus, they become 'unfree labourers' who are placed in a perpetual state of disadvantage, vulnerable to abuse and exploitation once in Canada.To describe the issues above, the thesis is divided into five chapters addressing the following: Chapter 1 presents the historical context behind the SAWP as well as the Mexican workers' circumstances that attract them to participate in the Program. Chapter 2 examines the applicable constitutional and federal framework for SAWP workers. In addition, it highlights key federal exclusions placed on them, which originate in the federal immigration and employment insurance legislation. Chapter 3 concludes that Ontario does not protect its agricultural workers from unfair treatment and exploitation in the workplace; rather, it perpetuates such practices. This reality is intensified for SAWP Mexican workers. Particularly, chapter 3 analyses a constitutional challenge to the Ontario legislation excluding agricultural worker from its labour relations regime; said challenge is based on ss. 2(d) and 15(1) of the Canadian Charter of Rights and Freedoms. Chapter 4 maintains that similarly to workers in Ontario, SAWP workers in Quebec and British Columbia also face extreme disadvantages due in great part to the lack of or limited legal protections. Finally, chapter 5 asserts that due to its implementation in the Canadian framework, international law is inadequate to protect domestic and SAWP workers' rights. While each chapter identifies tangible drawbacks or anomalies, which affect SAWP workers negatively, the thesis also provides recommendations to alleviate said weaknesses.
Keywords: Collective bargaining; Discrimination; Employment insurance; Equality; Foreign workers; Immigration; Mexican workers; Migrant workers; Social sciences

Finding Home: Geographical Links Between Paid and Unpaid Work for Transnational Care Workers in Toronto's Suburbs - D'Addario, Silvia (York University, 2013)
Contemporary migration has become increasingly transnational as migrants maintain linkages with their place of origin and, in many cases, with multiple places. Transnational practices and identities highlight the complex ways that contemporary immigrants negotiate home. This dissertation explores the ways in which transnational Filipina care workers construct home and a sense of belonging, here and elsewhere. In order to examine these experiences of belonging, I investigate the linkages between paid and unpaid work in various workplaces and places of residence. This research weaves together experiences of paid and unpaid work and the locations that (re)create their feminized, racialized and classed circumstances. To capture the intricacies of home for transnational Filipina care workers, I analyze the 2006 Canadian Census and Statistics Canada's Ethnic Diversity Survey. I elaborate on these data with in-depth interviews and focus groups with three groups of Filipinas: recent health care workers, recent live-in caregivers and well-established residents. The analysis takes place in the inner suburbs of Scarborough, ON and the outer suburbs of Markham, ON; two locations that are key immigrant reception zones. My methodology investigates how various qualitative and quantitative methods can be employed to better understand how the complex relations between paid and unpaid work in various places of residence and workplaces influence the construction of home for transnational care workers.
Keywords: Care workers; Filipina; Ontario; Paid work; Social sciences; Suburbs; Toronto; Transnational; Unpaid work

Three Essays in Labour Economics: An Application of Mixed Methods Research to Understanding of the Employment Status of Aboriginal Workers in Canada - Delic, Senada (Carleton University, 2013)
This thesis consists of three self-contained essays examining the link between Aboriginal identity and economic success in the Canadian labour market. The analytical approach encompasses mixed methods research, with two empirical tests and one qualitative inquiry. Both the neoclassical and institutional economics approaches to labour market analysis are considered, as discussed in the introduction to the thesis. Essay I employs monthly Labour Force Survey data and examines the difference in the impact of the 2008-2011 economic downturn on Aboriginal and non-Aboriginal workers. The main findings in this essay indicate that the economic downturn had a markedly more negative impact on Aboriginal than on non-Aboriginal workers. For one subgroup of Aboriginal workers - Métis - a large portion of the difference in the impact can be attributed to the difference in endowments while for the other subgroup of Aboriginal workers - North American Indian - only a small portion of the difference in the impact can be attributed to the difference in endowments, much remains unexplained. Essay II employs the 2006 Census and Aboriginal Peoples Survey data and examines the relative impact of various sources of capital – human, social and cultural – on the employment success of Aboriginal labour force participants living on-reserve, off-reserve, in urban and in rural areas across Canada. The single most important finding in this essay is that the predictions of human capital theory do not hold up when the associated empirical models are applied to different Aboriginal groups. Another important finding is that for some subgroups of Aboriginal population social capital and cultural factors are potentially important omitted variables in the associated equations. Essay III employs primary data collected from knowledgeable key informants working in the area of Aboriginal labour force development and investigates the role institutional and other constraints, not observable in the statistical information, play in the labour market experience of Aboriginal people. Findings here suggest that many paradoxes and puzzles that persist in the empirical literature can be better understood once the institutional arrangements related to the investment in human and other capital, the legacy of historical disadvantage, and the experience of workplace discrimination are taken into account.
Keywords: Aboriginal; Employment status; Human capital; Labor market discrimination; Recession; Social capital

La constitutionnalisation du droit de négociation collective : ses effets sur les régimes législatifs de représentation collective - Desjardins, Annick (Université de Montréal, 2013)
Dans un important arrêt rendu en 2007 dans l’affaire Health Services and Support, la Cour suprême du Canada a reconnu pour la première fois que la liberté d’association énoncée à la Charte canadienne des droits et libertés protégeait la «capacité des syndiqués d’engager des négociations collectives sur des problèmes reliés au milieu de travail». Pour conclure ainsi, la Cour trouve appui dans le droit international du travail. Avec cette décision, la Cour renverse sa position établie une vingtaine d’années plus tôt voulant que la négociation collective ne soit pas une activité bénéficiant d’une protection à titre de droit fondamental. Suite à ce changement de paradigme, nombre d’auteurs ont été d’avis que la constitutionnalisation du droit de négociation collective pourrait avoir des effets sur la validité de différentes mesures législatives et sur l’interprétation des lois encadrant les régimes de relations de travail. De plus, la négociation collective étant historiquement indissociable de la grève, il y avait tout lieu de croire que la protection de la Charte pourrait être étendue au droit de grève. Par la suite, en 2011, la Cour suprême a rendu la décision Fraser portant sur l’accès à un régime de représentation collective, précisant la portée du droit de négociation collective tel qu’envisagé dans Health Services. Le présent mémoire recense la jurisprudence qui a abordé la protection constitutionnelle de la négociation collective en droit public canadien et en droit privé québécois depuis l’arrêt Health Services afin d’identifier ses effets sur la validité des restrictions au droit de grève, sur la validité des restrictions au contenu des négociations et sur l’imposition de conditions de travail, sur la validité des exclusions de certaines catégories de travailleurs des régimes de représentation collective, et sur l’interprétation des dispositions de ces régimes. Les résultats de la recherche nous permettent de conclure que la constitutionnalisation du droit de négociation collective a engendré un certain volume de contestations de la part d’organisations syndicales. Ces procédures ont porté fruit dans des situations où l’atteinte aux droits était similaire aux précédents de la Cour suprême ainsi que dans un cas lié au droit de grève. Les effets plus vastes envisagés dans la recension de la littérature ne se sont pas matérialisés. Par ailleurs, nos résultats en droit privé indiquent que la constitutionnalisation du droit de grève n’a pas eu d’impact sur l’interprétation des régimes de relations industrielles. Enfin, le recours ou non au droit international par les tribunaux n’a pas d’effet sur nos résultats.
https://doi.org/1866/9965

Fragile Future: The Attack Against Public Services and Public Sector Unions in an Era of Austerity - Fanelli, Carlo (Carleton University, 2013)
This study is about the ongoing transformation of neoliberal public policy, precarious work, and public sector unions' struggles against demands for austerity. Situated in long-term historical perspective, I examine to what extent changes in the nature and content of government intervention, social welfare provision, and restructuring of the public sector are structurally-induced, the products of historical and contemporary circumstances, the result of mismanagement, or some combination of other factors. I argue that in addition to reducing the compass of social services, recent expenditure restraint measures have targeted unionized workers in order to lower wages and reduce benefits across the sector. Case studies include original analyses of striking workers at the Canadian Museum of Civilization Corporation, collective bargaining between teaching assistants and contract instructors and Carleton University, and striking civic workers at the city of Toronto. Together the cases break new ground in understanding how neoliberalism is being reconstructed and redeployed in light of the Great Recession and the consequences this has had on public sector workers and services. The three jurisdictions in this study - municipal, provincial, and federal - represent three scales of neoliberal restructuring in Canada. While all three governments have resorted to some form of austerity, the methods used to reduce the deficit and move toward balanced budgets have been differential and multifaceted. These include service delivery restructuring, increasing use of public-private-partnerships, privatization, new user-fees, and/or consumption taxes, as well as public sector worker layoffs, workplace intensification, and the selling of Crown assets. I contend that such measures seek to shift the burden of recession onto the public sector by reducing social services provisioning and seeking concessions from unionized public sector workers. In fact, the state has taken a leading role in narrowing the field of free collective bargaining, suspending trade union rights, and implementing an aggressive program of dispossession. Absent the collective capacities to stop let alone reverse these measures, public sector unions have reached an impasse. Unable to translate militancy into an alternative ideological perspective and a coherent political and economic program, they continue to desperately hang onto previous gains that look increasingly insecure and fragile. I argue that in order for unions to regain their once prominent role in the pursuit of social justice and workplace democracy, they will need to take the risks of organizing working class communities and fighting back while they still have some capacity to do so - else they risk continuing the decades-long labour impasse and union decline. In my view, this necessarily requires an explicitly anti-capitalist perspective, with the aim being to develop both alternative policies and an alternative politics rooted in the working class.
https://carleton.scholaris.ca/items/6a2ec30d-538a-46b4-9528-ecee8a9575e1
Keywords: Austerity; Labor Unions; Public sector unions; Public services; Social sciences

The Voices of Women Struggling to Manage Employment and Motherhood - Finer-Freedman, Judith (University of Toronto, Ontario Institute for Studies in Education, 2013)
The purpose of this study was to examine the perceptions of working women when they announce their pregnancies, take maternity leave, transition back to work, and utilize flexible work policies. Using a qualitative methodology, transcripts of in-depth interviews were analyzed utilizing a life history approach. Key findings of the study are that women perceive more negative responses to the announcement of their pregnancies than positive ones. In terms of maternity and parental leave policies, all the participants had access to these benefits. Women found issues with financial adequacy, administration, and duration of these policies. Mothers found that financial support from the Canadian government was inadequate to allow them to take the full duration of the 52-week maternity and parental leave for which they were eligible. In addition, employer “top-up” payments were limited and administrative details of maternity leave were often not discussed fully with pregnant workers. When women returned to work, they found that workplaces did not offer resources such as a phased-in return to work or personnel to help them re-engage with their prior work projects. Women discussed the challenges of managing their dual roles of worker and mother and found that managers and coworkers put them in a mommy mould which lessened the quality of their assignments. New mothers found that they had difficultly juggling their work and home responsibilities, finding time for themselves, and receiving increased domestic support from their spouses. While some workplaces offered women flexible workplace policies, not all mothers chose to access them as they found these policies often negatively impacted their career progression. Other issues were a lack of flexible workplace policy transparency, inconsistent manager support, and difficulty maintaining a flexible schedule. Findings have major implications for an improved response from managers upon pregnancy announcement, improved dialogue among employers about increasing “top up” maternity leave pay to new mothers, developing a formal transition plan for new mothers returning to the workplace, and expanding the use of flexible workplace policies.

The Din of Work: Broadcasting the Labour Movement at Price-Kénogami, 1977-1981 - Grosman, Jessica (Concordia University, 2013)
This study examines twenty radio programs created by the local CSN union at Price-Kénogami in the Saguenay, Quebec, on community radio station, CHOC FM. The program began during a period of profound change in the pulp and paper industry in Quebec that was marked by protracted labour conflict at this plant. The union envisaged a program that would inspire rank-and-file workers' labour activism and broadcast pro-labour news and information to the wider community. Yet if union executives hoped to insert working-class interests into the public sphere and carve out a space for class-based conversations about labour and social justice, their aspirations were never fully realized. Instead of broadening the circle of active union members and creating a class-based counter-public, the weekly CSN broadcasts became the exclusive reserve of union activists. Radio shows legitimized the actions of union executives and increased the latter’s sense of the union’s momentum. In mirroring Habermas’ conception of the public sphere, the CSN broadcasts privileged the voices of a selected few union executives. When the bitter strike of 1980-81 divided workers at Abitibi-Price (formerly Price-Kénogami), union radio hosts refused to even comment on the position of the dissidents. The CSN union broadcasts neither allowed for spirited internal debate nor did they help create effective channels through which to intervene in the public sphere. Rather, labour programming on CHOC remained an extension of the union, which seemed content with using the weekly broadcasts as an inward-looking space for self-reflection.

Not in Their Classrooms: Class Struggle and Union Strength in Ontario’s Elementary Teachers’ Unions, 1970–1998 - Hanson, Andy Bruce (Trent University, 2013)
This dissertation examines the rise of teachers’ union militancy in Ontario through a case study of the Federation of Women Teachers’ Associations of Ontario (FWTAO) and the Ontario Public School Teachers’ Federation (OPSTF) between 1970 and their amalgamation into the Elementary Teachers’ Federation of Ontario (ETFO) in 1998. It uses the archival records of the two unions, relevant legislation, media records, personal collections, and interviews to explore how these two professional organizations became politicized, militant labour unions able to engage with the state and the trustees of boards of education. The Introduction situates the public education project within nation building in a capitalist-democracy and outlines the theoretical influences informing the dissertation. Chapter 1 follows the two unions during the 1970s as they developed into labour unions. The 18 December 1973 one-day, province-wide, political strike achieved the right to strike and established a unique labour regime for teachers. Chapter 2 examines the advance of the unions during the 1980s as they developed labour militancy. At the same time, neo-liberalism was ascending and the post-war social accord was coming to an end resulting in attacks on unions and cuts to social programs. How gender affected the elementary teachers’ unions between 1970 and 1990 is developed in Chapter 3. The FWTAO campaigned for women’s equality on a platform of liberal feminism while the OPSTF followed a unionist path in an effort to convince women teachers to join them. Chapter 4 scrutinizes the effect of neo-liberal ideology on education during the 1990–1995 Bob Rae NDP government and the impact the Social Contract had on teachers. The development of teacher resistance to the neo-liberal state is explored in Chapter 5. Alliances with other labour organizations during the Days of Action campaign culminated in a two-week, province-wide strike in the fall of 1997 against the Mike Harris Conservative government. The Conclusion brings together the findings of the dissertationand suggests future research exploring teacher union strength in the Canadian context.

"Une grande union pour tous les travailleurs" : la One Big Union au Québec (1919-1929) - Houle-Courcelles, Mathieu (Université Laval, 2013)
La One Big Union (OBU) a marqué l’histoire du mouvement ouvrier au Canada. Associée au courant du syndicalisme industriel révolutionnaire, l’OBU s’est développée au Québec dès 1919, tout particulièrement à Montréal. Ce mémoire nous permettra mieux comprendre les stratégies d’implantation du syndicat dans la province jusqu’en 1929, en nous attardant sur ses objectifs et ses moyens d’action. Notre recherche mettra en lumière la culture politique de l’organisation et de ses militants, ses périodes d’avancées et de reculs, de même que ses rapports parfois conflictuels avec le reste du mouvement ouvrier.

Unionization of Agricultural Workers in British Columbia - Jensen, Heather (University of Victoria, 2013)
This thesis provides a multi-method – historical, quantitative, qualitative, and jurisprudential – socio-legal case study of the unionization of agricultural workers in British Columbia. Agricultural employees have access to the Labour Relations Code of British Columbia. A historical examination of exclusion of agricultural workers from labour relations legislation from 1937 to 1975 explores the rationale behind labour relations laws and the political context of the legislative exclusion. Next, economic aspects of BC’s agricultural sector are described, with a focus on employment characteristics and the regionalised nature of agricultural production. Finally, this thesis explains the legal aspects of an ongoing campaign by the United Food and Commercial Workers (UFCW) to unionize migrant and resident agricultural workers. The union organizing campaign shows how legal labour relations processes operate in relation to migrant workers in a sector with low rates of unionization and high rates of precarious and low-paid, dangerous work.

The Union Is the Message: Messenger Work and Messenger Organizing in the Same-Day Courier Sector - Lavin, David Oliver (York University, 2013)
Work in the same-day courier sector is a precarious form of employment. Workers in this sector are also treated as self-employed and hired as independent contractors. The relationship with the firm for which they work, however, is hardly distinguishable from an employment relationship. Messengers are among a growing number of workers in Canada who can be labeled as disguised employees. To explore the phenomenon of disguised employment, I use a case study approach informed by critical political economic theory and a purposive approach to labour and employment law to examine work in the same-day courier sector in Toronto with a focus on a subpopulation of workers in this sector: bike messengers. I examine the causes and consequences of self-employment in the same-day courier sector, analyze messengers' work and argue that their employment status entails misclassification. In an increasingly market-mediated society we are witnessing a proliferation of unprotected work relationships with disguised employment being one manifestation of this development. Fortunately, some unions are trying to organize workers in disguised employment relationships. In this dissertation, I also examine an attempt by the Canadian Union of Postal Workers to organize workers in Toronto's same-day courier sector. I explore the processes and implications of organizing disguised employees and examine how organizing these workers relates to and can inform the project of union renewal in Canada. Gaining employee status, however, is no guarantee of successful organizing. The same-day courier sector is highly competitive and is dominated by small, decentralized employers. Organizing in such a sector is a formidable task. Under the collective bargaining regime, unions have to organize workers workplace by workplace. However, this is proving to be ineffective in highly competitive sectors dominated by small employers, and organizing efforts will likely only result in limited success. As I argue, unions can develop innovative strategies and tactics to organize workers. However, with the many structural obstacles unions face, these strategies and tactics can often fall short of their goals. To facilitate unionization in the same-day courier sector, the collective bargaining regime needs to be overhauled to mandate, or at least promote, multi-employer bargaining.

Protection of Temporary Foreign Workers: The Case of Filipinos in Canada - Leung, Kwan Ho (Ryerson University, 2013)
Temporary foreign workers have been employed – or simply used – throughout history. Their plights have gained some attention across the globe in recent decades. Canada as a major receiving country of these workers and the Philippines as a prolific sending country of workers are selected as case studies to examine whether measures taken internationally, nationally and locally are adequate to protect these workers, especially those in low-skilled occupations. Based on prior research on the workers’ well-being, the answer is no in at least five areas: recruitment, matching of qualifications, abuse, housing, and family separation. Suggestions are made to address these specific areas. In addition, it is argued that, in order to protect the workers, civil society should also be involved and expanded rights should be given to the workers.

Unpacking "Alberta Beef": Class, Gender, and Culture in Edmonton Packinghouses During the Era of Nationall Pattern Bargaining, 1947-1979 - Loch-Drake, Cynthia Marie (York University, 2013)
The struggle to establish a progressive American-based industrial union, United Packinghouse Workers of America, in Edmonton's four major packinghouses during World War Two sparked the ""awakening"" of a social conscience in many workers who embraced the goals of strengthening the labour movement and promoting working-class political activism. The impact of this working-class community on electoral politics, however, was limited to a significant degree by notions of gender difference. The most successful politician to come out of an Alberta packinghouse was Ethel Wilson, a seamstress in the laundry department at Edmonton's Burns plant, who rose through municipal and provincial politics to become a cabinet minister in the anti-union Social Credit government of Ernest Manning, while a number of packing men were unable to achieve electoral success. Drawing on a wide array of sources, including oral interviews, union and government records, and newspapers, I argue that notions of gender difference intersected with class and ethnicity to handicap packing men and women in distinctive ways linked to a national system of pattern bargaining that gave them unprecedented trade union power during the decades following World War Two. During these years workers tended to support male leaders who could be aggressive, even bullying and dictatorial. This masculinist leadership style was most effective in confrontations with the powerful companies that comprised Canada's ""meat trust,"" particularly Canada Packers, and with the province's increasingly right-wing provincial government, but it often marginalized progressive voices in the union and excluded women almost entirely from the most powerful leadership positions. Conversely, in community politics, the aggressive image of packing masculinity was a liability that did not handicap Ethel Wilson, who was able to achieve success by downplaying her union credentials and trading on an image of respectable white Anglo-Canadian femininity.

Behind the Resume: Influences on the Educational and Employment Trajectories of 1.5 and Second Generation Filipino-Canadians in Vancouver - Mais, Julia Kathleen (York University, 2013)
Many Filipino immigrants have moved to Canada as professionals, with high levels of English fluency and education. However, first and second generation Filipino-Canadians are still relatively disadvantaged in the labour market. Despite these negative collective outcomes, individual trajectories differ greatly, with many individuals achieving high levels of education and desirable employment. My research examines how social surroundings can facilitate or impede pathways to post-secondary education and employment by shaping aspirations and providing connections to the labour market. The research also analyses how gendered childrearing approaches, employment aspirations, peer norms and available role models result in distinct gendered experiences. The study is based on semi-structured interviews with adult children of Filipino immigrants in the Vancouver area who have attended post-secondary education and are employed. It will explain how, in most cases, trajectories are strongly influenced by the social networks in the spaces of the home, neighbourhood, education system and the Philippines.
Keywords: British Columbia; Social sciences

Redefining “Enterprising Selves”: Exploring the “Negotiation” of South Asian Immigrant Women Working as Home-based Enclave Entrepreneurs - Maitra, Srabani (University of Toronto, Ontario Institute for Studies in Education, 2013)
This study examines the experiences of highly educated South Asian immigrant women working as home-based entrepreneurs within ethnic enclaves in Toronto, Canada. The importance of their work and experiences need to be understood in the context of two processes. On the one hand, there is the neoliberal hegemonic discourse of “enterprising self” that encourages individuals to become “productive”, self-responsible, citizen-subjects, without depending on state help or welfare to succeed in the labour market. On the other hand, there is the racialized and gendered labour market that systematically devalues the previous education and skills of non-white immigrants and pushes them towards jobs that are low-paid, temporary and precarious in nature. In the light of the above situations, I argue that in the process of setting up their home-based businesses, South Asian immigrant women in my study negotiate the barriers they experience in two ways. First, despite being inducted into different (re)training and (re)learning that aim to improve their deficiencies, they continue to believe in their abilities and resourcefulness, thereby challenging the “remedial” processes that try to locate lack in their abilities. Second, by negotiating gender ideologies within their families and drawing on community ties within enclaves they keep at check the individuating and achievement oriented ideology of neoliberalism. They, therefore, demonstrate how the values of an “enterprising self” can be based on collaboration and relationship rather than competition, profit or material success. The concept of “negotiation”, as employed in this thesis, denotes a form of agency different from the commonly perceived notions of agency as formal, large-scale, macro organization or resistance. Rather, the concept is based on how women resort to multiple, various and situational practices of conformity and contestation that often can blend into each other.

Mapping Social Relations of Older Workers' Employment: Using Institutional Ethnography to Explore the Meaning and Organization of Work, Health, and Safety of Aging Workers in the Home Support Sector - Mandville-Anstey, Sue Ann (Memorial University, 2013)
Demographic trends both provincially and nationally indicate increasing life expectancy and growing numbers of older adults living with chronic disease and disability. Human resource projections predict that Canada will need to double the number of formal home care workers in order to meet future demands. This demographic change has also resulted in increasing numbers of older adults choosing to remain engaged in the workforce past the traditional age time of retirement. Research on supportive services in the community has identified the issues and challenges of homecare but little has addressed the complex interplay of economic, political, and social factors that have resulted in the health and safety challenges associated with the work provided by home support workers. Using a method of inquiry called Institutional Ethnography, this research explored the meaning of work and health and safety considerations of workers over 50 years old who are providing home support services in Newfoundland. This exploration of health and safety needs and practices, work environments, as well as policies and government systems regulating the employment of workers can be summarized into three threads that describe the everyday work of these aging home support workers: Crossing Boundaries - More Than Just a Job; Making it Work in Unhealthy and Unsafe Work Environments; and Becoming a Home Support Worker: Experience, Orientation, and Training Necessary to do the Work. The findings suggest that decision making practices to engage in risk taking behaviour that impact health and safety in the workplace are influenced by the meaning of work as well as the emotional connections and close, personal relationships with clients. It is anticipated that this research may positively influence the health and safety of aging workers in this sector. This will be achieved through the recommendations for policy and practice that emerged from this research including the development and implementation of a risk assessment tool for home support workers, clear standards on education, orientation, and training, wage parity with the acute care sector, and more clarity on title, roles, and responsibilities of home support workers.

Law's Permissions, Law's Exclusions: Precarious Migration Status in Canada - Marsden, Sarah Grayce (University of British Columbia, 2013)
The number of people with less than permanent migration status in Canada has increased in recent decades. While such people often have social and economic ties to Canada, and live and work within its territory, they do not have legal permanent membership by way of permanent residence or citizenship, and experience differential access to legal rights and entitlements. This dissertation examines the role of migration status in the lives of people who identify themselves as having “uncertain” migration status. In this study, I draw on interviews with migrants and representatives of migrant-serving agencies as well as legal and policy texts, deploying Dorothy Smith’s institutional ethnography as a methodology to ground the dissertation both analytically and structurally in the interview data. This study enlarges the understanding of the nature and effects of migration status as it is enacted in local institutional sites. Using the construct of “precarious migration status” as a theoretical frame, I focus specifically on the nature and effects of precarious migration status. I explore the effect of precarious migration status on working life and on migrants’ interactions with state institutions governing health care, education, and income security. I conclude that precarious migration status has a deleterious effect on the employment relationship itself as well as access to worker protections, even though the law creates no formal barrier to such protections on the basis of status. With regard to social state, individuals with precarious status are often formally excluded in the text of the law as well as through various exclusionary policies and practices within local institutional sites. I conclude that institutional sites in which precarious migration status functions to exclude should be understood as forms of enforcement. I further conclude that human rights and anti-discrimination strategies through Charter and provincial human rights statutes, while valuable, are unlikely to improve inclusion for precarious migrants, while contestation of membership at the level of local institutions has greater potential to do so.
Graduate

The Vancouver Hunger March of 1932: Explaining a Third Period Success - Maxwell, Jean-Francois (University of New Brunswick, 2013)
On 25 February 1932 some 6000 protestors descended on Vancouver for a “Hunger March” organized by the Communist Party of Canada (CPC) to demonstrate for better conditions for workers, both employed and unemployed, across the nation. Although Hunger Marches were organized throughout Canada, Vancouver’s march was by far the largest and certainly the most successful. This study presents a thorough examination of the circumstances surrounding the Hunger March and explains what made the event such a unique success in this city. The event’s success derives from the Vancouver CPC ‘s ability to take advantage of the large mass of transients who came into the city in the early part of the Great Depression and then to funnel their discontent into mass agitation. The following study shows how the Hunger March is symbolic of the Vancouver CPC’s revolutionary pragmatism during the Third Period,

"That Indispensable Figment of the Legal Mind": The Contract of Employment at Common Law in Ontario, 1890-1979 - Mummé, Claire Isabel (York University, 2013)
“The relation between an employer and an isolated employee or worker is typically a relation between a bearer of power and one who is not a bearer of power. In its inception it is an act of submission, in its operation it is a condition of subordination, however much the submission and the subordination may be concealed by the indispensable figment of the legal mind known as the 'contract of employment'.” Otto Kahn-Freund , Labour and the Law (London: Stevens, 1977) This study examines the legal evolution of the common law of employment contracts in Ontario between the 1890s and the 1970s. It focuses on the changing relationship between notions of property and contract in employment, as visible through the judicial discourse of reported common law cases. I argue that between the 1890s and the end of the 1970s Ontario saw the emergence and consolidation of two different conceptual paradigms for regulating work at common law. The common law of employment contracts was framed and reframed over different eras of the 20th century through what the courts understood of the nature of the exchange between the parties, the property interests involved and the legal tools necessary to manage that exchange. Contrary to the traditional narrative in the field, the courts of Ontario first conceptualized employment as an exchange as of the turn of the 20th century. This first paradigm emerged in tandem with the province’s second industrial revolution, and sought to regulate the discretionary nature of white collar professional work. The second paradigm was entrenched in the 1960s and 1970s. It is over these years that workers in Standard Employment Relationships (SER) first began to bring employment-related claims to the common law courts, a few decades after it emerged as the paradigmatic form of work around which Ontario’s labour market and employment laws were fashioned over the mid-century. The basic premises of the SER, of long-term employment, job security and internal career advancement, fundamentally changed the psychosical and economic terms of employment. But faced with workers’ claims for recognition of these new terms in law, the courts instead chose to entrench a limited legal framework which denied job security as an enforceable contract term.
Keywords: Contract; Employment; Employment law; Labour history; Labour law; Labour relations; Law; Property in employment

Gender and the Games Industry: The Experiences of Female Game Workers - Newbery, Marsha (Simon Fraser University, 2013)
In the digital games industry women are statistical and cultural outliers. Using a cultural studies lens, this thesis examines the experiences of women game-makers in order to more deeply understand the attitudes of female game-workers, and to ascertain whether work in the male dominated gamed industry can be ‘good work’ for women. When compared to other cultural sectors, female game workers face unique barriers to sustaining careers in this high status industry. Gender stereotypes keep many women from fully participating in games industry culture which in turn discriminates against any worker who does not fit in to the ‘might is right’ mindset. Female game workers are getting mixed signals from an industry that appears to desire gender diversity in order to attract the growing ranks of female gamers, but is resistant to change sexist and discriminatory work practices that continue to alienate women.

Embodying and Resisting Labour Apartheid: Racism and Mexican Farm Workers in Canada's Seasonal Agricultural Workers Program - Paz Ramirez, Gabriela Adriana (University of British Columbia, 2013)
Contrary to government official discourses that present the Seasonal Agricultural Workers Program (SAWP) as a ‘human and just’ labour migration model, in this paper, the SAWP is presented as a migrant labour regime that functions as labour apartheid system of discipline and control, which is in place to satisfy the needs of capitalist development in the Canadian agricultural industry. By identifying the parallels and similarities of the differential treatment of Black migrant workers under South African apartheid with the differential treatment to which migrant farm workers are subjected under the SAWP, I explore how coercive migrant labour regimes of work function today in the context of heightened neoliberal hegemony and state multiculturalism. Through empirical evidences and theoretical claims, I identify main constitutive elements and forms of governance that cause workers to living and experiencing apartheid conditions; I explain how these forms of governance actually work on the ground, and how are they embodied, lived and contested by migrant farm workers participating in the program. I also delve in workers’ politics and their expressions of resistance and contestation to such system as they speak directly to the ways they experience apartheid conditions and the particular forms of how racism is inflicted over them. The SAWP presents an interesting opportunity to closely examine the ways in which colonialism works, how it is manifested today through labour and immigration schemes, and how these regimes are contested and challenged through migrant farm workers’ political subjectivities. In this respect, this paper paves the way for future movement-related research study of seasonal agricultural workers, which can generate collective insight and knowledge to support the organizing efforts of the precarious migrant workers in Canada.

Women, Work, and Family: Estimating Married Women's Status Achievement Over Their Careers - Reid, Sarah M. (University of Toronto, 2013)
My dissertation project examines women’s family lives, career trajectories, and status attainment. I draw on the concept of the work-family interface to highlight how work and families operate as contextual layers that cross-over in shaping definitions and appraisals of mothers as workers and workers as mothers. Utilizing data on married mothers’ complete working histories, I demonstrate that job exits due to motherhood negatively impact women’s occupational status attainment (SES), but I also show that women face penalties when changing jobs involuntarily and also due to personal reasons not tied to the maternal role. Importantly, in each instance, I demonstrate that these effects operate independently of the non-employment durations they engender, offering broad support for the status characteristics framework which points to the role of employer appraisals of women’s work commitment in shaping their SES outcomes. I also bring families back into the discussion of the work-family interface via the construction of a family-level framework that draws on mothers’, fathers’ and children’s attitudes about maternal employment as a platform for the development of discrete family configurations. I reveal a wide array of family attitude configurations that underscore that maternal employment continues to be contested moral terrain in some families while it is ii supported in others. In particular, I show that in egalitarian families—where maternal employment is not seen as a risk to ‘good’ mothering—mothers report more positive experiences of family and marital relations, less housework and more paid work, and higher earnings. I argue that family contexts represent an important yet understudied contextual reality that is more than the sum of individual views and which have unique consequences for women’s family lives and status trajectories.

Working Professionalism: Nursing in Western Canada, 1958-1977 - Scaia, Margaret Rose (University of Victoria, 2013)
Changes in women’s relationship to caring labour, and changes in societal attitudes towards women as nurses during the period when they became union members and aspiring professionals, are revealed in thirty-seven oral history interviews with women who became nurses between 1958, a pivotal time in the development of the publicly funded health care system, and 1977, when the last residential school of nursing closed in Calgary. This study challenges the historiography that suggests that nursing programs of nursing in the 1960s and early 1970s were sites of unusual social regulation, and that nursing was a career choice that women made because of a lack of other more challenging or rewarding alternatives. This study also challenges assumptions that women in nursing were unaffected by the feminist movements of the 1960s and 1970s and instead passively accepted a position of gendered subservience at home and in the workplace. Instead, I argue that nurses skilfully balanced work and other social responsibilities, primarily domestic caregiving, and also were active in unionization and professionalization in advance of other Canadian women workers. The ability of nurses to maintain a prominent position in health care, to advocate for the conditions needed to provide the best nursing care possible, while also fighting for improved working conditions and higher professional status is an impressive story of how women in these decades used gender, and class, as tools to enact social change. These efforts are all the more impressive when considered within the context of social opposition faced by nurses as they both resisted and conformed to expectations that their primary role was as wives and mothers. Nurses negotiated this challenging political terrain by framing their work in terms of its practical necessity and gendered suitability as women’s paid employment. In making these claims, I position nursing and nursing education as a form of women’s labour that exemplifies employed women’s struggles to promote fairer wages, better working conditions, and access to the full benefits of economic and social citizenship for all women. This challenge to the prevailing assessment of nursing during this period establishes the main thesis of this dissertation.
Keywords: Labour history; Nursing history

Knowledge, Organization and the Division of Labour: Evaluating the Knowledge Class in Canada - Scholtz, Antonie Edward (University of Toronto, Ontario Institute for Studies in Education, 2013)
This dissertation explores the claim that, in advanced capitalist countries like Canada, a powerful knowledge class is assuming increasing dominance within the social relations of production. Attached to such theories are claims of trends toward post-bureaucratic organizations, rising job complexity and autonomy, and increased power within operational and strategic decision-making processes. In my study I focus on Canadian “specialist” employees (professionals and semi-professionals) and managers. I present aggregated and disaggregated data from two Canadian surveys conducted in 1983 and 2004 and complement this with original interviews with information technology (IT) workers and engineers. I find a seeming paradox within the labour process of specialists and managers, with task-level autonomy declining even as job complexity and involvement in organizational decisions are rising. I provide evidence that imperatives for profit/cost effectiveness are leading to efforts to make specialist and managerial labour and knowledge more transparent, integrated, and manageable, but this is not the same as degradation or proletarianization. In contrast to my expectation, I find boundaries in the division of labour are durable despite this “socialization” of many labour processes. I argue that a specialist-and-managerial class (SMC) exists in Canada, and will continue to exist, though it is subordinate to and exploited by the capitalist elite even as it excludes and exploits the working class through occupational closure and credential barriers. The SMC is thus contradictory, internally heterogeneous and fraying at its borders, but simultaneously resilient. The resiliency comes via possession of specific strategic knowledge and consequent ability to secure rents and/or control specific organization assets via delegated authority. Resiliency is also structural, with management in many organizations retaining an interest in separating planning and design (“conception”), on the one hand, from process and completion (“execution”), on the other, in order to maximize efficiency and productivity through more centralized control.
Accepted: 2013-08-13T14:02:24Z

Vancouver Longshoremen, Resilient Solidarity and the 1935 Interruption: Company Unionism 1923-1945. - Smith, Roy Alfred (Simon Fraser University, 2013)
This thesis challenges the historiography that asserts the waterfront strike in Vancouver in 1935 was a failed militant surge by a new radical leadership in an otherwise twenty-year period of dormancy among the city's longshoremen. Using union documents, employer records, and interviews with workers, the thesis presents the entire company era, between 1923 and 1944, as a period of developing solidarity and resistance. In this context the 1935 strike and the union's leadership were a product of, not a radical departure from that continuity. The thesis shows that despite two lost strikes in 1923 and again in 1935, the administrative structures the employers established produced a resilient culture of solidarity that was in place before Partiament acted in 1944 to provide longshorement with the legal framework for union representation.

Intensified Work, Intensified Struggle: Solidarity Unionism and The Edmonton Postal Workers' Fight Against Forced Overtime - Thorn, Scott M. (McMaster University, 2013)
In February 2011, a wave of creative direct action swept across postal depots in the city of Edmonton which saw rank-and-file workers organizing outside of the channels of formal-legal unionism. Fighting against management’s imposition of compulsory overtime as a staffing measure, Letter Carriers and other “outside” postal workers relied on solidarity and resistance at the point of production in a successful campaign to put an end to this practice. The relevance of this particular struggle to the Canadian labour movement is twofold. First, the intensified workloads of Edmonton postal workers reflect a wider shift in the nature of employment relationships away from the existence of employer support as part of the rise of neoliberal capitalism. Second, the choice of workers to organize at a distance from the historically militant Canadian Union of Postal Workers reveals both the predicament facing labour of a highly restrictive formal labour relations system as well as an alternative path of resistance. For Edmonton postal workers, this path was forged in large part as a result of the influence of IWW dual-carder organizers and, more specifically, their introduction of a mode of union praxis known as solidarity unionism.

"Lest You Undermine Our Struggle": Sympathetic Action and the Canadian Charter of Rights and Freedoms - Vallance, Keir (University of Saskatchewan, 2013)
In this thesis I address the question of sympathetic action - action by one group of workers designed to aid another group of workers in their struggle with an employer, manifested most obviously through refusals by workers to cross a picket line - through the lens of the Canadian Charter of Rights and Freedoms. As the law currently stands in Canada, undertaking sympathetic action collectively is invariably illegal as it is considered an illegal "strike" under Canadian labour legislation. Further, workers who undertake sympathetic action - whether collectively or individually - can be subject to discipline or discharge by their employer. I argue that workers who undertake sympathetic action can have numerous motivations, ranging from economic self-interest to deeply-held political or moral beliefs (the latter manifested through the concept of "solidarity"), and that when those motivations include expressive or conscientious interests, sympathetic action should be entitled to protection by the fundamental freedoms of conscience, expression, and association found in section 2 of the Charter. I further argue that a each of these freedoms represents a different aspect of the inherent dignity and worth of an individual, and that a right to sympathetic action promotes both those freedoms and Charter values. Finally, I argue that a constitutional right to sympathetic action is a free-standing right that can exist even in the absence of a constitutional right to strike. This thesis reviews the current and historical state of Canadian law (in both the statutory labour relations regimes and in common law) regarding sympathetic action, the potential application of the Charter freedoms of conscience, expression, and association to sympathetic action, and finally options for reform that reduce or eliminate restrictions on sympathetic action and therefore make our labour relations system more in keeping with Charter values.

Serving the Fast Food Nation: Analyzing and Understanding Food Choice, BMI and Self-Perceived Weight in the Food Service Worker Population - Woodhall-Melnik, Julia R. (University of Waterloo, 2013)
Policymakers, politicians, and media outlets have declared an obesity epidemic. In doing so, they have named a variety of villains, including fast food. Despite the framing of fast food as being a leading contributor to weight gain and obesity, we have yet to understand the impact that fast food has on those who work with it every day. The purpose of this dissertation is to understand the food choices, BMIs, and self perceived weights of the food service worker population. Using Pierre Bourdieu‘s concepts of habitus and field, I investigate the role of the workplace and external cultural influences, such as the family, in navigating an obseogenic workplace environment that is centered on selling highly caloric food to the Canadian public in a quick and cost effective manner. The first stage of this research addresses the question: Are food service workers more likely to be overweight or obese and perceive themselves as being overweight compared to the general population? In order to do this, I analyzed secondary survey data from the Canadian Community Health Survey cycle 5.1 (2009-2010). I used logistic regression techniques to construct models that analyze the likelihood of having high BMIs and high self perceived weights in both the food service worker and general Canadian populations. In addition to this, I sought to understand the food choices that contribute to weight gain in fast food workers. To do this, I conducted forty semi-structured qualitative interviews with workers from a variety of fast food chains. The results of my research disprove my original hypothesis that food service workers are more likely to be overweight or obese because of their frequent exposure to fast food. Instead, I found that they are less likely to be overweight or obese than the general Canadian population. Additionally, they are also less likely to perceive themselves as being overweight or obese. Through the qualitative interviews, I found that these individuals participate in a process of regulation where they monitor their food intake at work. Additionally, I found that their consumption patterns stemmed from habitus generated through cultural exposures in other areas of their lives. Pierre Bourdieu (1984) argues that we develop habitus through meaningful cultural exposure. We use our habitus, or engrained dispositions, to navigate hierarchical spaces or fields. Through this research, I found that workers viewed their jobs as being temporary and their cultural consumption patterns did not seem to change from their exposures to their workplaces. The majority were part time students, working in this industry to pay for living expenses and tuition. For the most part, they were raised in middle class homes where their mothers prepared food for their families from scratch on a daily basis. Fast food was viewed as a special treat and not an item to consume on a regular basis. I conclude that the meaningful exposures we have to food and cultural norms throughout life are more important in determining our food choices than our exposure to fast food restaurants.
Keywords: BMI; Fast food work; Food choices; Habitus; Self-perceived weight

Working Natures: An Ethnography of Love, Labour, and Accumulation on the British Columbian Coast - Yard, Jaime Dianne (York University, 2013)
The primary question for investigation throughout this research is how the environmental knowledges of settler-colonists and their descendants have been formed through processes of work and dwelling in place. This dissertation results from over a year of fieldwork in an aging community where retired loggers, semi-retired fishermen, and retired exurban migrants are actively renegotiating the meanings of local places and natures as the local economy shifts from a base in logging and fishing to one in recreational and retirement real estate development. Through archival research, life history interviews and participant-observation with loggers, fishermen, exurban retirees and other long-term residents I explored the complications and contradictions inherent in learning to value nature through processes of transforming and intervening in ecological processes for economic ends. Writing against hard social constructivism I examine the ways in which the life cycles of fish and fish populations, the contingencies of weather, topography and currents, and, the physical form of the land are active elements in the formation of labour and settlement patterns in coastal British Columbia. As a contribution to the underdeveloped field of first world political ecology this work maps environmental knowledges and values developed in tense complicity with regimes of natural resource management and accumulation by dispossession. Central to this process is how people become agents of the commodification of nature and place in their everyday lives and work, and, how private property has become naturalized as a prerequisite to "protecting" self, nature, and community from precarity in the era of late capitalism. This dissertation tracks the various ways, both historically and in the present, that settlers and their descendants on the BC Coast have attempted to simultaneously make a living and make a home of an occupied place-the imperialist nostalgia and (neo)liberal white guilt endemic to the process.
Keywords: British Columbia; Commodification of nature; Environmental knowledge; Labor; Settler-colonists; Social sciences

Canadian Mining and Labour Struggles in Mexico: The Challenges of Union Organizing and the Weaknesses of Corporate Social Responsibility - Bocking, Paul G. (McMaster University, 2012)
Focusing on a case study of a union organizing effort at the La Platosa mine in northern Mexico from 2009-2012, this paper studies the challenges facing labour activism at Canadian mining companies in Mexico within the context of the North American Free Trade Agreement. The positions of the Mexican and the Canadian governments in relation to contemporary workers’ struggles in Mexico’s mining sector are considered, particularly the latter’s adoption of a ‘corporate social responsibility’ approach to addressing the activities of Canadian extractive firms abroad. By studying the outcome of the request for mediation filed by La Platosa miners with the Canadian government’s Extractive Sector CSR office in 2011 and evaluating the evolution of this government’s policy approach to extractive companies abroad since 2009, we find that CSR as practiced by the Canadian government has been ineffective at mitigating abusive practices by Canadian mining companies in Mexico and that an alternate outcome is not to be expected under existing policy structures. The relative strengths and weaknesses exhibited during labour organizing at the La Platosa mine are evaluated to find both locally specific and more broadly applicable strategies which could be applied to union renewal, both by workers employed under NAFTA’s transnational sector, and by the general labour movement.

A Loyalist Plantation in Nova Scotia, 1784-1800 - Cottreau-Robins, Catherine M. A. (Dalhousie University, 2012)
At the close of the American Revolution thousands of American Loyalists were forced into exile and made their way to British colonies beyond the United States. Most of the Loyalists landed in British North America, particularly the Maritimes. Along with the trauma and losses of the conflict, the Loyalists brought with them a way of doing things, an intense political history, and ideas concerning the imperial structure that framed their everyday lives. This dissertation is a study of the Loyalists. Specifically, it explores a prominent Loyalist and his journey from Massachusetts to Nova Scotia along with family members, servants, and labourers, including enslaved persons. A central objective of the dissertation is to illuminate the story of the enslaved and magnify their place in Nova Scotia’s eighteenth century colonial history narrative. The objective is addressed by adapting a holistic perspective that considers a single geography – the plantation. The holistic perspective, developed through an interdisciplinary methodology, explores the people, places and culture that formed the Loyalist plantation and were informed by it. The picture that emerges is one that puts into place the structure and organization of a Loyalist plantation in the late eighteenth century. This dissertation argues that an interdisciplinary approach is fundamental when exploring the subject of the plantation and its inhabitants in Nova Scotia. Through study of the slaveholder and the comparison of his plantation spaces, the dissertation argues for Loyalist continuity. Such continuity confirmed a slaveholding culture during the mass migration. Finally, this dissertation argues that the Loyalist period can be described as Nova Scotia’s Age of Slavery. The Loyalist migration represents an unprecedented arrival of enslaved persons to the province. Furthermore, the Loyalist migration represents the unprecedented arrival of a political and ideological framework that carried within it perceptions of race and seeds of discrimination that took root.
Accepted: 2012-09-05T17:57:01Z

Neoliberalising Immigration in Canada: The Pilot Project for Occupations Requiring Lower-Levels of Formal Training and the Expansion of Canada's Temporary Foreign Worker Program - Cragg, C. Andrew (Trent University, 2012)
There has been a significant expansion in Canada's Temporary Foreign Worker Program (TFWP) over the past ten years. The Pilot Project for Occupations Requiring Lower Levels of Formal Training (PPORLLFT), a sub program of the TFWP, has been leading this expansion. Drawing upon testimony given to the Parliamentary Standing Committee on Citizenship and Immigration, this thesis examines the development and expansion of the program, since its inception in 2002, and shows that it is connected to the ongoing process of neoliberalisation in Canada. One significant example of this connection is the program's support for increases in two-step immigration streams that involve employer sponsorship for successful transition to permanent residency; this increase represents a privatisation of citizenship decisions. More than this, the neoliberal aspects of the PPORLLFT have increased inequality and the ability of employers to have a more disciplined workforce. This has decreased the ability of working people to have influence in their workplace and over economic policy more generally.
Keywords: Immigration; Neoliberalism; Temporary Foreign Workers

Labour and Literature in the 'West Beyond the West' - Diotte, Mark Vincent (University of British Columbia, 2012)
The literature of British Columbia and the study of labour therein have been largely ignored in academic criticism. I address this deficiency by foregrounding labour in the prose literature of British Columbia as well as the significance of British Columbia literature itself. My introductory literature review demarcates the field, situates the authors and texts I take up, and points to the general importance of such a study. Chapter two begins by analyzing the male-dominant labour narrative in Bertrand Sinclair’s The Inverted Pyramid and Roderick Haig-Brown’s On the Highest Hill and Timber—each focused on the theme of logging. Rather than an overarching argument, the section on Sinclair addresses many concepts, including Pierre Bourdieu’s theory of fields, a connection between environmental conservationism and loggers, and a cooperative economic model that opposes capitalism. Likewise, in Haig-Brown I focus on his treatment of danger in the logging industry, the oft-forgotten history of Canada’s national parks, the way that language connects people to nature, and the presence of homosocial and homosexual relationships in logging. My project shifts in chapter three from logging to orcharding and from novels to three works of creative non-fiction by Harold Rhenisch:Out of the Interior: The Lost Country, Tom Thomson’s Shack, and The Wolves at Evelyn: Journeys through a Dark Century. Operating out of a site of tension and contradiction,Rhenisch resists what he sees as the dominant discourses in the Interior of British Columbia. In my fourth chapter I return to novels but move from a study of manual labour to white collar labour. Here the phrase “white collar” becomes an analytical lens to view labour stratification, exploitation, authorship, sexism, and agency in Douglas Coupland’s JPod, Robert Harlow’s Scann, and Jen Sookfong Lee’s the end of east. In chapter five, I conclude by using Daphne Marlatt’s novel Ana Historic as a way to reflect on the positions of chapters two through four. Marlatt’s criticism of male dominant conceptions of history and patriarchal systems of power illuminates the texts I have taken up and reveals possibilities for further analysis, debate, and discussion.

The Class Idea: Politics, Ideology, and Class Formation in the United States and Canada in the Twentieth Century - Eidlin, Barry (University of California, Berkeley, 2012)
Why are class politics more prevalent in Canada than in the U.S., even though the two countries share similar cultures, societies, and economies? Many view this crossborder distinction as a byproduct of longstanding differences in political cultures and institutions, but I find that it is actually a relatively recent divergence resulting from how the working class was politically incorporated in both countries before, during, and after World War II. My central argument is that in Canada, this incorporation process embedded "the class idea"–the idea of class as a salient, legitimate political category–more deeply in policies, institutions, and practices than in the U.S.Out of the social and political struggles of that period emerged two working class movements that, although bearing a surface resemblance, were organized along different logics. In Canada, the working class was incorporated as a class representative, whereas in the U.S. It was incorporated as an interest group. That difference in political incorporation enabled or constrained labor's legitimacy and organizational capacity in different ways in both countries. Canadian labor's role as a class representative legitimized it and expanded its organizational capacity, while U.S. labor's role as an interest group delegitimized it and undermined its organizational capacity.I show this through a detailed analysis of trajectories of labor movement strength in both countries over the course of the twentieth century, as measured by unionization rates, or union density. Starting from the observation that union density was very similar in both countries until the mid-1960s, then diverged, I first examine competing explanations for this divergence. Having illustrated their strengths and limitations, I then develop an argument showing how the divergence in working class organizational strength was the outcome of struggles for political incorporation.I identify two key moments that shaped these different processes of political incorporation. The first was the restructuring of party-class alliances in both countries in the 1930s and 40s, where U.S. labor decisively abandoned the project of building an independent working class party in favor of an alliance with the Democratic Party, at the same moment that Canadian labor forged an independent class alliance with progressive agrarian forces under the banner of the CCF. The second was differences in the effects of postwar Red scares on the relationship between labor and the left in both countries. While anti-Communism took its toll on working class movements in both countries, the labor-left alliance was severed in the U.S., but only strained in Canada. The outcome of these processes was a U.S. labor movement that conceived of itself more as an interest group representing a specific constituency within the Democratic Party, and a Canadian labor movement that conceived of itself more as a class representative with closer ties to a broader social movement.Differences in labor's political incorporation also shaped the formation and development of the regimes governing labor-management relations in both countries. The Canadian labor regime was created as a result of working class upsurge from below, whereas the U.S. labor regime was created as part of an elite reform project from above. This original difference influenced the organizing logics of each regime. Whereas the Canadian labor regime was organized around recognizing the existence of class conflict and seeking to mitigate it, the U.S. regime was organized around protecting workers' individual rights. Although this created a more interventionist Canadian system that restricted labor's scope of action in important ways, it also reinforced a collective, oppositional class identity vis-à-vis both employers and the state. Meanwhile, the U.S. system's focus on rights led to a stronger focus on legalistic proceduralism and imposing a formal equality between labor and management that obscured the power imbalance inherent in the employment relationship. Additionally, labor drew different lessons from these different processes of regime formation. Whereas Canadian labor learned the value of winning gains through disruptive mass mobilization, U.S. labor learned the value of winning gains through sympathetic politicians and favorable legal precedents.The combination of a more protective and institutionally stable labor regime and a labor movement more accustomed to winning gains through mass mobilization, Canadian labor was better positioned to defend itself than its U.S. counterpart when employers began a counter-offensive beginning in the late 1960s. While U.S. labor spiraled into decline, Canadian labor proved more resilient, leading to the divergence in union density rates.

Permanent Worker, Temporary Resident: Media Representations of Canada's Live-in Caregiver Program - Gilliland, Julia Sarah Jane (University of Victoria, 2012)
The Live-in Caregiver Program is a temporary foreign worker program that allows workers to come to Canada in order to labour as private caregivers for children, the elderly, and disabled individuals. This program allows caregivers to apply for permanent residency after the successful completion of 24 months of full time work. There are a number of scholars, advocacy groups, former caregivers, and other parties that have raised concerns about certain regulations of this program. For example, caregivers under this program have an employer-specific work permit, must live in the homes of the employers, and have no external monitoring of their work environments. Subsequently, the Live-in Caregiver Program has been seen as problematic because of the high number of abusive labour situations. This thesis is dedicated to an analysis of how the Canadian news print media represents the Live-in Caregiver Program. Although there has been much research done on migrant care work within Canada, and around the world, there are few studies on how the news media construct arguments that describe these transnational labour flows. The main topics that guided the research questions for this thesis were: temporary foreign worker programs; citizenship status; globalized, gendered, and racial stereotypes; the live-in regulation; employer specific work permits, and power relations in the labour relationship. This research was not geared to proving or disproving the main findings of key migrant domestic worker literature, rather it was focused on how these conclusions are interpreted, transferred and argued within a publically accessible format, Canadian news print media. This analysis revealed how journalists within Canadian news media construct important cultural narratives to persuade audiences to either reject the LCP as exploitative and problematic, or embrace it as economically beneficial.
Keywords: Social sciences

Harvesting Power and Subjugation: Canada's Seasonal Agricultural Workers Program in Historical Context - Glassco, Clare (Trent University, 2012)
This thesis explores the Canadian state's rationale for the creation and perpetuation of the Seasonal Agricultural Worker's Program (SAWP). Informed by and building on the writing of Canadian political economists, this thesis provides a composite history of the program from its creation in 1966 to its current-day incarnation. While many scholars have looked to neo-liberalism to analyze the program, SAWP existed long before the term entered the political lexicon and instead fits into a much longer history of racialized immigration and labour policies in Canada. Therefore, though we need to understand the changes wrought by neo-liberalism, we must also acknowledge the historical continuities inherent in SAWP: no matter who was in office, and what political ideology they subscribed to, migrant labour schemes have consistently been relied onto support the state's project of aiding the accumulation of wealth and filling the labour vacuum left behind by Canadians who gained safer, more secure, and more lucrative employment elsewhere.
Keywords: Social sciences

« Le jour du Seigneur vendu à l'encan » : regard sur la Commission d'enquête sur l'observance du dimanche dans les industries de pâtes et papiers du Québec (1964-1966) - Guillette, Bruno-Pierre (Université du Québec à Montréal, 2012)
Le Lord's Day Act interdit le travail le dimanche en 1906, mais autorise les travaux jugés nécessaires. Les compagnies papetières québécoises peuvent effectuer les travaux d'entretien et de nettoyage, mais ne peuvent pas produire le dimanche. L' industrie papetière exige la production continue et menace de freiner ses investissements au Québec si le gouvernement ne permet pas le fonctionnement des machines le dimanche. Le gouvernement Lesage instaure donc la Commission d'enquête sur l'observance du dimanche dans les usines de pâtes et papiers en 1964. Le jour du Seigneur fut essentiellement traité comme une question religieuse par les historiens, mais l'attachement pour la conservation du repos dominical déborde les questionnements sur le sécularisme ou la piété populaire. Cette commission instaurée pour régler un problème technique cache un profond conflit de valeurs entre les différents acteurs sociaux. Différentes façons de concevoir le bien commun et le progrès social y sont avancées. Aux séances de la commission, plusieurs groupes et individus font valoir leurs points de vue. Les représentants des compagnies papetières exigent unanimement la production le dimanche pour accroître la production. Pour les groupes religieux, la sanctification du dimanche est une manifestation collective vitale pour la cohésion de la famille, de la paroisse et de la société. Quant à eux, les travailleurs et leurs syndicats défendent l' idée d' un repos commun hebdomadaire et dénoncent le travail par rotation d'équipes. Les débats lors de la Commission Alleyn permettent de mettre en relief une confrontation culturelle à l' intérieur d'un rapport économique de production, tout en offrant un éclairage sur le bouleversement des nouveaux rapports sociaux en plein coeur de la Révolution tranquille.
https://cha-shc.ca/prize-winner/bruno-pierre-guillette/
Keywords: Alleyn; Commission d'enquête; Culture populaire; Dimanche; Temps de travail; Industrie papetière; Église; Religion; Repos dominical; Syndicat; Québec; Histoire.

Is Leisure Working? The State and the Gendered Regulation of Working Time and Leisure in Canada, 1950-2006 - Ignagni, Sandra (York University, 2012)
This dissertation examines the intersection of gender, employment law and public health policies through an analysis of the federal government's efforts to regulate the work/leisure relationship. The study asks how and why, despite over 50 years of state interventions to regulate leisure and healthy lifestyle, concerns about 'work-life balance' have surfaced in labour policy arenas in recent years. The study builds a feminist political economy framework for understanding changes in policy developments over time. I use the concepts of social reproduction and time- and work-discipline as lenses with which to probe the relationship between the changing temporal dimensions of paid and unpaid work and efforts to manage the new realities of the labour market through the institutions of the state. The dissertation considers how the changes in the gendered organization of social reproduction, the nature and regulation of employment, and the power of organized labour to advocate on behalf of workers have influenced the types of policies used to manage the work/life interface. The empirical dimension of this study traces the emergence of a framework for regulating social reproduction through state-led management of the work/life relationship. Following the evolution of such frameworks through federal policy debates, policy papers and program materials, I trace the continuities and changes in dominant leisure discourses and policy mechanisms through four phases of federal policy development: early fitness policies (pre-1960); ParticipACTION (1960 to early 1970s); employee fitness experiments (mid-1970s to 1990); and the Work/Life Balance Strategy (1990s to mid-2000s). The central argument put forward in this dissertation is that the gender- neutral and individualized framework for regulating the healthy reproduction of workers, developed in Canadian law and policy since the 1950s, has produced highly gendered outcomes through its failure to address the changing dynamics of work and family life. By continuing to uphold the notion of a worker 'unencumbered' by familial and household responsibilities, 'new' work-life balance policies exacerbate the tensions between paid and unpaid work and contribute to the ongoing marginalization of women in the labour market.
Keywords: Employment law; Gender; Leisure; Public health policies; Social sciences; Working

Pathways to Successful Economic Integration: The Dynamics of Low Income and Low Wages Among New Immigrants to Canada - Kaida, Risa Lisa (University of Toronto, 2012)
Contemporary research on immigrant economic integration identifies growing economic disadvantages faced by immigrants and probes sources of the disadvantages by focusing on immigrants' pre-migration and ascriptive characteristics. However, little empirical evaluation exists on how immigrants overcome their initial economic disadvantages over time. This dissertation departs from previous research by studying the roles of two post-migration factors - schooling (formal education and language training) and the employment of female spouses - in the exits from low wages and low family income (poverty) among recent immigrants. The analysis of the Longitudinal Survey of Immigrants to Canada (LSIC) - a three-wave survey of immigrants who arrived in Canada in 2000-2001 - produces three main findings. First, investing in host country formal education is beneficial for the economic advancement of new immigrants - especially highly educated ones. This finding confirms the role of skill upgrading programs for adult immigrants as an effective immigrant settlement policy, given that the majority of recent immigrants have postsecondary education but that their initial economic hardships are growing. Second, the benefits of English/French language lessons are real. This finding counters a common criticism that language lessons for adult new immigrants, which are often funded by the governments, are not helpful. Indeed, standard logistic regression analysis of the LSIC data shows that immigrants who enrolled in language lessons have no advantage in exiting poverty or low wages. However, the bivariate probit model demonstrates that this is because unmeasured characteristics of the language lesson participants confound the true benefit of language lessons. Third, this dissertation research highlights the role immigrant women play in lifting their families out of poverty when they work. This finding has an implication particularly for women of Arab and Middle Eastern origins as their notably lower labour force participation rates explain much of their high poverty rates.
Keywords: Demography; Economic integration; Ethnic and racial studies; Formal education; General; Immigrants; Language training; Low-income; Social sciences; Sociology; Spousal employment; Wages

L'Arsenal canadien: Les politiques canadiennes et la fabrication de munitions au Canada durant la Deuxième Guerre mondiale - Labbé, Pierrick (Université d'Ottawa, 2012)
Cette thèse propose une analyse de la production de munitions au Canada durant la Deuxième Guerre mondiale dans le but d'exposer les politiques mises de l'avant par le gouvernement canadien pour répondre aux exigences matérielles de la guerre. Afin de combler les besoins du ministère de la Défense et de ses alliés, le ministère des Munitions et Approvisionnements réussit un tour de force en transformant une industrie munitionnaire insignifiante en un vaste programme qui employait plus de 103 000 personnes à son apogée. L'analyse des politiques à l'origine de cette production montre que le gouvernement fédéral géra autant que possible sa contribution matérielle de manière à fournir une aide considérable à ses alliés tout en poursuivant ses objectifs de relance économique à long terme. Le Comité de guerre du Cabinet tenta également de limiter l'impact négatif de ses décisions sur la vie des Canadiens. La participation matérielle du Canada prit forme graduellement, restreinte par la volonté de limiter les dépenses militaires. Les projectiles ne figuraient pas parmi les priorités avant la chute de la France. À partir de l'automne 1940, les principaux ministères se montrèrent plus ouverts à la mise en place et au financement d'un vaste programme. Ils consolidèrent leur collaboration avec les gouvernements britannique et américain afin d'obtenir le soutien technique et financier nécessaire pour surpasser les faiblesses industrielles du pays, de manière à permettre une collaboration qui ne nuirait pas à long terme aux finances publiques. Ensuite, l'interventionnisme sans précédent pour stimuler ce secteur non traditionnel s'effectua, malgré l'ampleur des investissements, dans un esprit d'économie et mené par une volonté de ne pas disloquer inutilement les structures de l'économie civile. Le gouvernement misa sur une collaboration avec les entreprises compétentes qui dominaient déjà le marché. Les entrepreneurs jouèrent un rôle clé dans la stratégie fédérale de gestion des ressources humaines. L'élaboration d'une solution à la pénurie de travailleurs s'effectua autant que possible sans l'imposition de mesures coercitives, de manière à ne pas nuire à la relance de l'économie dans l'après-guerre et à ne pas saper le moral des citoyens. Le ministère des Munitions et Approvisionnements opta plutôt pour la mise en place d'un État-providence de guerre et d'un paternalisme industriel. Le secteur privé, appuyé par diverses initiatives du gouvernement fédéral, se devait d'imposer un encadrement strict du milieu de travail afin de maximiser la productivité, de diminuer l'absentéisme et de lutter contre les interruptions de production.
Keywords: Histoire de la Deuxieme Guerre mondiale; Histoire politique canadienne; Munitions; Social sciences; World War II

Topics in Canadian Aboriginal Earnings, Employment and Education: An Empirical Analysis - Lamb, Danielle Kathryn (University of Toronto, 2012)
This dissertation is divided into three main components that each relate to the socioeconomic wellbeing of Aboriginal peoples in the Canadian labour market. Specifically, using data from the master file of the Canadian census for the years 1996, 2001 and 2006, the first section examines the wage differential for various Aboriginal and non-Aboriginal groups, including a comparison of those living on-and-off-reserves. The study finds that, while a sizeable wage gap between Aboriginal and non-Aboriginal persons still exists, this disparity has narrowed over the three census periods for those living off-reserve. The Aboriginal-non-Aboriginal wage differential is largest among the on-reserve population and this gap has remained relatively constant over the three census periods considered in the study. The second study in the dissertation uses data from the master file of the Canadian Labour Force Survey for 2008 and 2009 to estimate the probability that an individual is a labour force participant, and, conditional on labour force participation, the probability that a respondent is unemployed, comparing several Aboriginal and non-Aboriginal groups. The results reveal that Aboriginal men and women have lower rates of labour force participation and higher rates or unemployment in both periods as compared to their non-Aboriginal counterparts. Aboriginal peoples were also disproportionately burdened by a slowdown in economic activity as measured by a change in the probability of unemployment moving from 2008 to 2009, as compared to non-Aboriginal people, who experienced a smaller increase in the probability of unemployment moving from a period of positive to negative economic growth. Finally, the third study examines the probability of high school dropout comparing Aboriginal peoples living on-and-off-reserve using data from the master file of the Aboriginal Peoples Survey for 2001. The findings reveal dramatically higher rates of dropout among Aboriginal people living on-reserve as compared to those living off-reserve. Limitations of all three studies as well as some possible directions of future research related to similar issues concerning Canada's Aboriginal population are discussed in the concluding chapter of the dissertation.
Keywords: Aboriginal peoples; Earnings; Education; Employment; Labor force activity; Social sciences; Unemployment

Labour Landmarks in Industrial Cape Breton, 1922-2011 - MacKinnon, Lachlan (University of New Brunswick, 2012)
Labour landmarks are memorial sites, commemorations, plaques, and burial sites that provide access to the themes and meanings of workers' past experiences. They are instrumental in enshrining workers' "public memories," which are the separate experiences of groups within society, within the larger "collective memory" of the community. A general exploration of the commemorative landscape reveals a number of themes and allows a detailed discussion of several labour landmarks. In the course of this research, 21 separate labour landmarks were identified in the communities of industrial Cape Breton. The majority of these monuments are dedicated to workers in the coal and steel industries. The 1980s saw an expansion in the frequency of labour commemorations, which indicates increased attention to the experiences of workers in Cape Breton. Two monuments in the community of New Waterford reveal the many layers of historical memory in the town. The first is dedicated to victims of the 1917 mine explosion, while the second commemorates the man killed during the 1925 strike. The explosion monument, unveiled in 1922, inserts the public memory of coal miners into the collective memory of New Waterford. The William Davis monument, dedicated in 1985, reveals an existing working-class consciousness in the town and merges individual and public memories of Davis while reflecting on a major event in the town's history. Another monument, dedicated to Sydney's steelworkers, now rests on the site of the former steel plant, and commemorates a century of experience. This memorial is used as an example of how one might "read" a labour landmark to access its themes and meanings, as well as to reach an understanding of the past experiences of workers.
http://labourlandmarks.weebly.com/labour-landmarks.html
Keywords: Social sciences

Rights of Temporary Foreign Workers in Canada - Macovei, Lidia (University of Alberta, 2012)
During the last decade, Canada experienced unequal economic growth. As result, the Canadian government expanded its Temporary Foreign Worker Program, which led to an essential change of its purpose, making it easier for employers to recruit temporary foreign workers for low-skilled jobs. In practice, TFWs are quite vulnerable without access to the same rights and privileges as Canadian citizens or permanent residents. The purpose of this thesis is to analyze whether the Canadian government respects the rights of TFWs through its domestic regulations and if such laws protect the rights of TFWs in practice. The thesis goal is to determine if the economic interest of the Canadian government and employers can be matched with international migrant rights' standards. It investigates international standards related to the protection of human rights, including covenants, international treaties, and human rights committees. This thesis also discusses similar programs governing TFWs in America, Germany, and Australia.
Keywords: Social sciences

Women in the Margins: Media Representations of Women's Labour in the Canadian Press, 1939-1945 - Moniz, Tracy (Ryerson University, 2012)
During the Second World War, women's participation in Canada's 'total war' effort meant increased domestic responsibilities, volunteering, enlisting in the armed forces, and joining the civilian workforce. Women's labour force participation more than doubled throughout the war, with more women working alongside and in place of men than ever before. This created a situation that could challenge the traditional sexual division of labour, and so women's labour became a subject for discussion in the public sphere. Through a comparative content analysis of the commercial and alternative (labour) press, this study examines representations of women's labour in wartime in the context of women's mobilization into the war effort through to subsequent demobilization near war's end. It first considers the theoretical and methodological issues involved in the historical study of news media and women and then offers original empirical research to demonstrate that when women's labour did emerge as a subject in the Canadian press, gender, not labour, was prioritized in the news. This was symbolically and systematically leveraged both within and across the commercial and alternative press, which reinforces stereotypical values about women and their labour and upheld the patriarchal status quo. In the end, while there were surface-level changes to the nature of women's paid labour during the war, the structures of female subordination and exploitation remained unchallenged despite women's massive mobilization into the workforce. By setting media representations against the wartime realities of women's labour told through archival records and secondary literature, this dissertation argues that news media generally presented a 'history ' of women's labour that did not reflect the lived reality or the political economic and social significance of women's labouring lives. This not only coloured how women's labour was represented in the news, but it can also shape the history that scholars construct from the newspaper. In contributing to feminist media and media history scholarship, this dissertation offers empirical evidence that challenges dominant ways of thinking about women's history in terms of the domestic sphere and furthers an understanding of women's wage labour as a provocation to such historical public-private divisions. This may, in turn, inspire histories that more fully and equitably capture women's experiences.
Keywords: Communication and the arts; Employment; Gender identity in mass media; Labor force; Media representations; Mobilization; Press; Social sciences; WORLD War; 1939-1945; Women workers; World War II

Race, Resistance and Co-Optation in the Canadian Labour Movement: Effecting an Equity Agenda like Race Matters - Nangwaya, Ajamu (University of Toronto, Ontario Institute for Studies in Education, 2012)
[Analyzes] the dialectic of co-optation/domestication and resistance as manifested in the experience of racialized Canadian trade unionists. The seven research participants are racialized rank-and-file members, elected or appointed leaders, retired trade unionists, as well as staff of trade unions and other labour organizations. In spite of the struggle of racialized peoples for racial justice or firm anti-racism policies and programmes in their labour unions, there is a dearth of research on the racialized trade union members against racism, the actual condition under which they struggle, the particular ways that union institutional structures domesticate these struggles, and/or the countervailing actions by racialized members to realize anti-racist organizational goals. While the overt and vulgar forms of racism is no longer the dominant mode of expression in today’s labour movement, its systemic and institutional presence is just as debilitating for racial trade union members. This research has uncovered the manner in which the electoral process and machinery, elected and appointed political positions, staff jobs and formal constituency groups, and affirmative action or equity representational structures in labour unions and other labour organizations are used as sites of domestication or co-optation of some racialized trade unionists by the White-led labour bureaucratic structures and the forces in defense of whiteness. However, racialized trade union members also participate in struggles to resist racist domination. Among some of tools used to advance anti-racism are the creation of support networks, transgressive challenges to the entrenched leadership through elections, formation of constituency advocacy outside of the structure of the union and discrete forms of resistance. The participants in the research shared their stories of the way that race and gender condition the experiences of racialized women in the labour movement. The racialized interviewees were critical of the inadequacy of labour education programmes in dealing effectively with racism and offer solutions to make them relevant to the racial justice agenda. This study of race, resistance and co-optation in the labour movement has made contributions to the fields of critical race theory, labour and critical race feminism and labour studies.
PhD

A Coal Miner's Shadow - Pelissero, Adam (Dalhousie University, 2012)
Light and shadow have the capacity to move us emotionally and create atmospheres that allow us to better understand stories. This thesis explores how light and shadow can propel the design of a music hall and museum space to commemorate the miners that lived and worked in the former industrial landscapes of Cape Breton, Nova Scotia, Canada.
Accepted: 2012-08-13T16:34:50Z

Hurrah Revolutionaries and Polish Patriots: The Polish Communist Movement in Canada, 1918-1950 - Polec, Patryk (University of Ottawa, 2012)
This thesis constitutes the first full-length study of Polish Communists in Canada, a group that provided a substantial segment of the countries [sic] socialist left in the early 20th century. It traces the roots of socialist support in Poland, its transplantation to Canada, the challenges it faced within an ethnic community heavily influenced by Catholicism, the complications caused by its links to the Comintern, and its changing strength and decline. It offers a deeper understanding of the ways in which the Communist party was able to appeal to certain ethnic groups, such as through cultural outreach, as well as its complicated and often arguably counter-productive relationship with the Comintern. It also furnishes important information on the efforts of the RCMP and Polish consulates to maintain control over the communists, as well as how generally improved material conditions among Poles, especially following the Second World War, along with the influence of the Cold War, accounted for a rapid decline in support. The thesis is primarily based on sources generated by the Polish Ministry of Foreign Affairs or, more precisely, by the Polish consulates in Winnipeg, Montreal and Ottawa. One the Canadian side, the thesis took advantage of RCMP records, Canadian security bulletins, immigration records and Polish-language newspapers printed in Canada. By utilizing these sources, this study not only analyses the interaction of the Polish Canadian communist movement with other segments of the Polish community in Canada, but it also moves beyond the introverted approach that has characterized most studies of ethnic organizations in Canada by placing the movement within a "Canadian" context to analyze its relations with the government, broader segments of Canadian society, and the Communist Party of Canada (CPC).
Keywords: Albert; Communist Party of Canada; Dutkiewicz; Ethnic Polish; Glos Pracy; Immigration; Kronika Tygodniowa; Labor radicalism; Morski; Polonia; Polskie Towarzystwo Ludowe; Royal Canadian Mounted Police (RCMP); Social sciences; Wladyslaw

How the Media View Public-Sector Workers: A Critical Discourse Analysis of a 2009 Municipal Workers' Strike in Windsor, Ontario - Reitsma, Travis G. (University of Windsor, 2012)
Research in the field of media coverage of organized labour has found that there often exist biases in the way in which unions and their workers are presented. With the ever increasing influence of both the media and neoliberal political and economic ideologies, the public image of organized labour has come under attack. This thesis seeks to expose another instance of this bias in the Windsor Star 's coverage of a 2009 municipal workers' strike in Windsor, Ontario, Canada; a public-sector strike. A detailed critical discourse analysis (CDA) was conducted on 480 texts regarding the strike in 2009. An anti-union bias was found especially throughout the coverage. This bias can be seen to have a detrimental effect on the image of public-sector workers which serves to further discredit them in their struggle against neoliberal power structures which seek to minimize their influence.
Keywords: Communication and the arts; Critical discourse analysis; Labor strikes; News bias; News coverage; Social sciences

Labour Force Participation and Health-related Quality of Life in People Living with HIV - Rueda, Sergio Ismael (University of Toronto, 2012)
This dissertation consists of four papers aimed at understanding the complex relationship between employment and health. One paper is a systematic review of the return to work literature, while the other three papers used secondary data from three cohorts of people with HIV to examine the association between employment and health-related quality of life. The systematic review looked at longitudinal studies that reported health outcomes associated with return to work in relation to other employment trajectories. This review supported the beneficial effect of return to work on health in a variety of populations, times, and settings, and also found evidence that poor health interferes with the prospects of returning to work. Two other papers looked at the association between employment and health-related quality of life in people with HIV; one paper used a cross-sectional sample of people with HIV, while the other paper used a longitudinal sample of men who have sex with men. These two studies found evidence to support the association between employment and both physical and mental health-related quality of life. They also found that employment had a stronger relationship with physical than mental health, suggesting an adaptation process to the experience of unemployment. Finally, another paper examined the cross-sectional association between job security and quality of life in men and women living with HIV. This study found that job security offered additional mental health quality of life benefits, over and above participation in employment alone, for men living with HIV. On the other hand, women benefited from the availability of work, but the perception of job security failed to offer additional health benefits. The current level of evidence on the relationship between work and health in HIV needs to be strengthened by further research to develop and support practical clinical and policy recommendations.

Solidarity Forever, Canadians Never: SAWP Workers in Canada - Russo, Robert Marc (University of British Columbia, 2012)
This doctoral thesis focuses on collective bargaining and temporary migrant workers within Canada participating in the Seasonal Agricultural Workers Program (SAWP). The intent is to analyze the range and efficacy of legal responses to the problems encountered by this community within Canada, focusing on the unionization of SAWP participants. The dissertation addresses the fundamentally legal relationship between unionization and SAWP workers in Canada. It takes an approach that considers both historical and legal considerations leading to the use of SAWP workers in Canada, and the eventual attempts at unionization. Recent legal developments in several Canadian provinces involving SAWP workers and efforts collective bargaining are analyzed. There is a comparison with similar efforts to unionize migrant workers in the United States, and of efforts to address violations of collective bargaining rights through international complaints as well as within the broader framework of international law. The conclusion reached is that within the current framework of provincial labour legislation and the current structure of the SAWP, collective bargaining alone represents an inadequate response to violations of SAWP workers’ workplace rights in Canada.
Keywords: Seasonal Agricultural Workers Program (SAWP)

No Quarter Required: Japanese Experiences and Media Distortions in the Steveston Fishers’ Strike of 1900 - Stielow, Timothy Mark (Simon Fraser University, 2012)
The brief histories of the Steveston Fishers’ Strike of 1900 are dominated by the arrival of the militia on 24 July and images of racialized violence between Japanese and white fishers. This thesis analyzes Japanese language sources and re-evaluates contemporary English language press reports to expand the strike narrative and demonstrate that Japanese fishers held significant negotiating power throughout the standoff. It argues that labeling Japanese as strikebreakers ignores their perspectives and goals in the labour dispute; however, this thesis also explains that there were important differences within the Japanese community and that to speak of a single Japanese perspective is to privilege individuals in positions of power who benefitted financially from fellow community members. It also demonstrates that by emphasizing tensions between groups of fishers, existing histories overlook the fact that the most violent acts of the month were done by the cannery owners through their connections with government.

The Social Organization of the Ontario Minimum Wage Campaign - Wilmot, Sheila (University of Toronto, Ontario Institute for Studies in Education, 2012)
My dissertation research is interdisciplinary in nature, at the nexus of three areas of scholarly work and actual practices: union renewal and non-unionized workers-rights organizing in Canada and the US; feminist, anti-racist Marxian approaches to class relations as being racialized, gendered and bureaucratic; and, the institutional ethnographic method of inquiry into social reality. My empirical focus is on the Ontario Minimum Wage Campaign (OMWC). The OMWC was a Toronto-based labour-community project to raise the minimum wage to $10 per hour. It was started in 2001 by Justice for Workers (J4W), was carried on by the Ontario Needs a Raise coalition (ONR) from 2003 to 2006, and was re-launched in 2007 by the Toronto and York Region Labour Council (TYRLC) in association with some community groups. The OMWC brought together across time and space activist groups, community agencies and labour organizations, all of whose volunteers, members, clients, educators, officials and staff were the agents and/or targets of the campaign. The apparent victory of the OMWC is quite contested. Local campaign realities were compartmentalized in numerous ways and OMWC involvement met different institutionally specific and coordinated needs. And while coalitions generally arise as vehicles to transcend such institutional separation, the campaign was challenged to materially bridge such compartmentalization. The fragmentation of reality amongst institutions and how it was managed in practice affected how collaboration, participation, and decision-making happened and appeared to have happened in organizing and educational activities. While there were at times transformative intentions, there was generally a pragmatic anti-racist organizing practice and effect. I contend that the complexity of contemporary society poses great challenges for the possibilities for human-agency based labour-community workers-rights organizing with a broad-based, political capacity for movement building orientation. I suggest that this is largely so because the social coordination of what we do and what we understand about what we do turns on at least three components of social reality: an institution-based organization of multi-layered social relations that is generally locally circumscribed but extralocally driven; a conditioned individually-driven orientation to meeting human needs; and an ideological orientation to both the content of ideas and thought, and the process of that reasoning.

National Holidays and Minority Festivals in Canadian Nation-Building - Zhu, Lianbi (University of Sheffield, 2012)
This study of Canadian national holidays examines their role as a complex and dynamic instrument of nation-building from 1867 to the early 2000s. It indentifies three phases of nation-building, labelled assimilation, transformation and multiculturalism. It takes the ideological change in Canada in 1971, namely the proclamation of Official Multiculturalism, as the momentous turning point which motivated the pioneering changes and creation of Canadian national holidays based on negotiations in the government and the interventions of varied ethnic groups, focusing on the relationship between the commemorative and recreational functions of these holidays. Specific holidays considered including Dominion Day (Canada Day), Labour Day, Victoria Day and Remembrance Day, as well as National Aboriginal Day, Canadian Multiculturalism Day and one minority festival – Chinese New Year. Counterparts in France and the United Kingdom are presented to contrast with Canadian practices, putting Canada in the global context of nation-building and decolonisation. It argues that debates surrounding national holidays are a good measure of underlying national ideology, which underwent a real change in Canada across the period studied.

The Sex Worker Rights Movement in Canada: Challenging the 'Prostitution Laws' - Beer, Sarah (University of Windsor, 2011)
The contemporary movement for sex workers' rights organizes around a range of international, national, and localized grievances. They are unified in their efforts to promote and protect sex workers' human and labour rights through the decriminalization and destigmatization of sex industry work. Within the context of social movement theory, literature on the sex worker rights movement has focused mainly on its failure to mobilize due to inadequate resources, small membership base, lack of sex worker leadership and absence of influential allies. In 2007, sex workers in Toronto, Ontario and in Vancouver, British Columbia, launched constitutional challenges to their respective Provincial Superior Courts to strike down Criminal Code of Canada provisions related to adult prostitution. The two court challenges are contrary to what would be predicted based on the extant literature on the sex worker rights movement. That literature supports a conclusion that due to marginalization, ambivalence toward their work, and feelings of inadequacy as political actors, sex workers lack the material and organizational strength to impact state regulation and alter social perceptions of sex work. This dissertation was based on a multi-site ethnographic study examining the processes by which constitutional challenges were initiated, the role of sex workers, and how the cases were perceived by the larger movement of sex worker rights activists in Canada. Drawing on primary and secondary data sources, including interviews with 26 movement activists, I examined constitutional litigation from the perspective of social movement theory, specifically considering the political opportunities, alliances, and resources necessary for these challenges to take place. This research demonstrates some tangible successes for the sex worker rights movement in Canada, despite ongoing social movement obstacles. The history of sex worker rights activism in Canada has produced sex worker-run organizations and political coalitions. These have garnered support from other organizations, researchers, cause lawyers and their teams, making it possible for sex workers, as individuals and via organizations, to mobilize legally against federal prostitution laws.

Permanently Precarious? Contingent Academic Faculty Members, Professional Identity and Institutional Change in Quebec Universities - Birdsell Bauer, Louise (Concordia University, 2011)
Universities across Canada are increasingly using contingent, or temporary instructors to teach undergraduate courses (Rajagopal 2002, Muzzin 2008, Lin 2006). Scholars have examined the marginalization of contingent academic faculty members in Canadian universities (Rajagopal 2002, Muzzin 2008). They have also critiqued the ways in which universities use contingent faculty to create surplus value and surplus labour (Rajagopal 2002, Bauder 2006), and support a “primary segment” (Bauder 2006) of the tenured and tenure-track professoriate. In this thesis, I examine the key issues faced by contingent academic faculty members, and how these issues impact on their professional identity. I also investigate into how the use of contingent faculty impacts on teaching practices in higher education. Through the analysis of Labour Force Survey data, I ascertain to what extent contingent academic labour has increased from 1998 to 2008, suggesting that full-time temporary labour is on the rise. I then analyze data gathered from twelve interviews with contingent academic faculty members at Quebec universities to explore how their working conditions and experiences have impacted on their professional identity and perceived quality of instruction. I suggest that professional identity among contingent faculty members is not as static as suggested by Rajagopal (2002) or Gappa and Leslie (1993) Using David Harvey’s (2005) concept of neoliberalism and Ulrich Beck’s (1992) concept of the flexibilization of labour under risk society, I situate the flexibilization of academic labour within the neoliberalization of the university, and also point to linkages between contingent academic labour and the commodification of higher education.

Deconstructing 'Hegemonic Feminism': The Emergence of 'Second Wave' Feminism in Canada (1965-1975) - Bragg, Bronwyn (University of Toronto, Ontario Institute for Studies in Education, 2011)
Drawing on a collection of interviews with Canadian feminists, this thesis explores the emergence of a ‘second wave’ of feminist organizing in Canada from 1965 to 1975. Using insights from poststructural feminism and critical race theory, I deconstruct the notion of ‘hegemonic feminism’ and examine how certain women came to inhabit a position of hegemony during the movement’s early years. I focus on key events in feminist organizing during the 1960s-1970s: The Royal Commission on the Status of Women and the founding of the National Action Committee on the Status of Women. Drawing on oral history interviews and a close reading of the report on the RCSW, I suggest that more nuanced approaches are needed to move beyond the binary thinking that inflects accounts of Canadian feminist history. I conclude with a series of feminist narratives which aim to complicate linear histories and offer an alternative reading of this movement.
Accepted: 2011-11-29T17:02:19Z

When the Injured Nurse Returns to Work: An Institutional Ethnography - Clune, Laurel Ann (University of Toronto, 2011)
Nursing is a high risk profession for injury. A Canadian survey reports many nurses are in poor physical and emotional health; they sustain more musculoskeletal and violence related injuries than other occupational groups. In Ontario, an injury management approach called Early Return to Work (RTW) requires injured workers, including nurses, to go back to work before full recovery. The Workplace Safety and Insurance Board cite this approach as beneficial to both the employer and employee. This study uses an institutional ethnographic approach to examine critically the RTW process from the standpoint of injured registered nurses. Through interviews and mapping activities with nurses, other health professionals and managers, a rendering of the social organization of hospital injury management emerges. The findings suggest that the implementation of RTW is complicated and difficult for nurses, their families and hospital employers. Injured nurses engage in significant amounts of domestic, rehabilitation and accommodation work in order to participate in the RTW process. When the returning nurse is unable to engage in full duties hospital operations become disorganized. Collective agreements and human resources procedures limit the participation of injured nurses in creative and/or new roles that could utilize their knowledge and skills. As a result, nurses are assigned to duties, which hamper them from returning to their pre-injury positions and cause their employment with the hospital to be reconsidered. The unsuccessful return of injured nurses to employment is counter to provincial retention initiatives, which seek to sustain an adequate cadre of nurses ready and able to care for the increasing health care needs of an aging population. Sites of change which could support and promote the successful return of these injured workers to nursing work are identified in this study.

“In an Equitable and Sympathetic Manner”: Alberta's Workmen's Compensation and the United Mine Workers of America, District 18's Welfare Fund - Devine, Jason Corey (University of Calgary, 2011)
This thesis is a study of the role of the United Mine Workers of America, District 18 in the development of Workmen's Compensation legislation in Alberta. It also an investigation into the creation of District 18's Welfare Fund in the post-war period and the fund's relationship to workers' compensation legislation. The miners initiated the movement for workers' compensation in Alberta and the first law in this regard was passed in 1908. After that year, District 18 continued to be prominent in working to improve the content and administration of the legislation as it affected miners and the Alberta working class. As a result of the insufficiency of workers' compensation, District 18 created a Welfare Fund. It was not designed to replace state-provided welfare, but to provide help to members where the law fell short. The fund, as such, was an exercise in working-class agency and mutual aid.

Constitutional Deradicalization of the Wagner Act Model:The Impact of B.C. Health Services and Fraser - Dobson, Tracey-Ann Alecia (University of Toronto, 2011)
For many years, workers petitioned the Supreme Court of Canada to intervene in labour relations to protect their collective bargaining rights. Finally, the Court answered the call, but the drastic changes made were not what workers expected. This thesis outlines the effect that the Court’s decision to intervene in labour relations had on the existing collective bargaining model. In making this determination, a historical analysis was done of the Court’s attitude towards using section 2(d) Freedom to Associate to protect collective bargaining, followed by a comparative analysis with United States jurisprudence to explain the effect of the Canadian decisions on the statutory provisions. The analysis revealed that the decisions had significantly weakened protections for workers’ rights, and provided the basis to conclude that the Supreme Court of Canada had used the Canadian Charter of Rights and Freedoms to deradicalize the existing collective bargaining model.

The Development of Working-Class Organic Intellectuals in the Canadian Black Left Tradition: Historical Roots and Contemporary Expressions, Future Directions - Harris, Christopher (University of Toronto, Ontario Institute for Studies in Education, 2011)
This thesis explores the revolutionary adult education learning dimensions in a Canadian Black anti-racist organization, which continues to be under-represented in the Canadian Adult Education literature on social movement learning. This case study draws on detailed reflection based on my own personal experience as a leader and member of the Black Action Defense Committee (BADC). The analysis demonstrates the limitations to the application of the Gramscian approach to radical adult education in the non-profit sector, I will refer to as the Non-Profit Industrial Complex (NPIC) drawing on recent research by INCITE Women of Colour! (2007). This study fills important gaps in the new fields of studies on the NPIC and its role in the cooptation of dissent, by offering the first Canadian study of a radical Black anti-racist organization currently experiencing this. This study fills an important gap in the social movement and adult education literature related to the legacy of Canadian Black Communism specifically on the Canadian left.

Working in the Creative Economy: The Spatial Dynamics of Employment Risk for Musicians in Toronto - Hracs, Brian Jennings (University of Toronto, 2011)
Over the past decade the introduction of MP3’s, file sharing networks and illegal downloading has fundamentally changed the music industry, structurally and spatially. In the wake of this restructuring it is now estimated that 95% of all musicians in Canada operate independently of record companies (Canadian Independent Recording Artist Association or ‘CIRAA’). Digital technologies afford independent musicians greater freedom and control over how and where they live and work. Although economic geographers have been quick to examine the impact of the so called ‘MP3 Crisis’ on record sales and the major record labels, little is known about how changes at the macro-scale affect the working lives of individual musicians in specific locations. As a result, this dissertation focuses on the employment experiences and spatial dynamics of independent musicians in Toronto. Drawing on sixty-five in-depth interviews with musicians and key informants in the music industry, the thesis documents the intersections between technology, work and space. In particular, the analysis highlights the ways in which the new creative and spatial freedoms, associated with independent music production, are accompanied by intensified competition and employment risk, which musicians experience in an increasingly individualized way. Surviving in the current marketplace requires independent musicians to perform a range of new tasks and exhibit a higher degree of professionalism. Accordingly, the research outlines some of the reasons why some musicians are rejecting and reworking traditional bohemian lifestyles, spatial patterns and risk mediation strategies. In particular, there is growing evidence of new forms of networking and of the increased importance of strategic collaborations between musicians and fashion designers. There are also signs that some musicians are relocating from the downtown core to the surrounding suburbs, and that musical talent is becoming redistributed across the city-region. Ultimately, this dissertation demonstrates the need for specialized policies to incubate and retain creative talent in an increasingly global and digital marketplace.
Accepted: 2011-02-17T21:27:29Z

Neither Temporary, Nor Permanent: The Precarious Employment Experiences of Refugee Claimants in Toronto - Jackson, Samantha (Ryerson/Toronto Metropolitan University, 2011)
While Canada’s immigration system is shaped primarily by the nation’s economic needs, refugee claimants’ motivations are, by nature, non-economic. Resultantly, refugee claimants are often portrayed as a drain on Canadian resources. Despite this however, refugee claimants’ employment experiences remain underrepresented in the literature. This study explores the employment experiences of refugee claimants in Toronto, and finds that claimants face distinct and unique barriers stemming from their precarious legal status. Additionally, as neither temporary workers nor permanent citizens, this study finds that refugee claimants perceive employment as an integrative expression of belonging and citizenship. Through the lens of refugeeness, this study traces the subjective employment trajectories of refugee claimants. Findings indicate that refugee claimants’ employability is shaped by real and ascribed barriers associated with their citizenship status, creating decidedly unique and often difficult employment experiences.

Unpaid Household Work: A Site of Learning for Women with Disabilities - Matthews, Ann (University of Toronto, Ontario Institute for Studies in Education, 2011)
This thesis explores women's learning in unpaid household work through the lenses of impairment and disability. Informal learning from this standpoint is a perspective that is not yet integrated into the adult learning literature. The impetus for the study came from dissatisfaction with the social undervaluing of unpaid housework and carework, and the largely unrecognized learning behind the work, which is predominantly done by women. Disability and impairment provide unique lenses for making visible what people learn and how they learn in this context. Those who have or acquire impairment in adulthood need to learn how to do things differently. For this study I have taken a segment of data from a 4-year, 4-phase project on Unpaid Housework and Lifelong Learning in which I participated. The participants in this segment are women and men with disabilities who took part in 2 focus groups (11 women), an on-line focus group (20 women), and individual interviews (10 women and 5 men). Learning is explored through three different themes: first, learning related to self-care; second, learning to accept the impaired body; and third, strategies and resources used in the learning process. Analysis of the data shows that the learning that happens through unpaid household work is multidimensional, fluid, and diverse. Learning is accomplished through a complex 4-dimensional process involving a blend of the body, mind, emotions, and the spiritual self. Furthermore, what participants learned and how they learned is influenced by the sociocultural context in which it takes place. Learning, when seen as a 4-dimensional process, provides a framework for challenging traditional Western cultural beliefs about what counts as learning and knowledge. Such beliefs have cultivated the viewpoint that learning is individualistic, cognitive, and based on reason. I contest these beliefs by disrupting the binaries that support them (e.g., mind vs. body, reason vs. emotion). Participants used both sides of the binaries in their learning processes, negating the oppositional and hierarchical categories they establish. The concepts in the binaries still exist but the relationship between them is not oppositional, nor is one concept privileged over another, either within or across binaries.

The Concept of Home Care Nursing Workload: Analysis and Significance - Mildon, Barbara (University of Toronto, 2011)
The concept of home care nursing workload has not been widely studied and no evidence was found that an analysis of the concept had been undertaken. Consequently, there was a knowledge gap regarding the definition and attributes for the concept of home care nursing workload as it is currently experienced. To address that gap, a descriptive, three-phase, mixed methods (quantitative and qualitative) study was conducted. In Phase One, Rodgers’ (2000) evolutionary method was used to analyze the concept of home care nursing workload based on the empirical literature. Phase Two was situated within the naturalistic inquiry paradigm and involved observation of ten home care registered nurses during their visits to 61 patients. In Phase three a questionnaire was administered to validate the draft definition and attributes for the concept of home care nursing workload. It was completed by 88 home care nursing experts from clinical practice, education, management and research. Qualitative findings were analyzed using inductive content analysis. Quantitative data were analyzed descriptively using SPSS. Data triangulation was used extensively within and between the study phases. Of 14 attributes in the phase three draft concept definition, respondents assigned the highest level of relevance to the attribute of cognitive effort and the lowest to physical effort. The final definition contained 20 attributes and includes the following excerpt: “Home care nursing workload is the totality of the cognitive, emotional and physical effort home care nurses expend to meet the expectations of all stakeholders in providing holistic, outcome directed and patient/family focused care within the context of a short or long-term therapeutic relationship.” Respondents reported high levels of agreement with the accuracy and completeness of the definition and the majority indicated the definition would be useful or very useful in their day-to-day work. The comprehensive concept exemplar that emerged from the study includes each of the identified attributes. The study findings provided evidence of the complexity and challenge inherent in quantitatively measuring home care nursing workload. Accordingly, implications of the findings are shared for the management and monitoring of workload and associated outcomes, as well as for nursing practice, education and research.

Mental Health Issues and Work: Institutional Practices of Silence in a Mental Healthcare Organization - Moll, Sandra (University of Toronto, 2011)
Over the past decade, mental illness in the workplace has become a key issue in the health and business communities, fueled in part by recognition of the high prevalence rates and significant costs for individuals and organizations. Although research in the field is starting to emerge, there are significant gaps in what is known, particularly with respect to the workplace context and its impact on workers. The overall objective of this study was to characterize, from a sociological perspective, the experiences of healthcare workers with mental health issues, and to account for how their experiences were shaped by the social relations of work. A qualitative approach, based on principles of institutional ethnography, guided exploration of the interactional, structural and discursive dimensions of work within a large mental health and addictions treatment facility. Data collection included in-depth interviews with twenty employees regarding their personal experiences with mental health issues, interviews with twelve workplace stakeholders regarding their interactions with workers, and a review of organizational texts related to health, illness and productivity. Analysis of the transcripts and texts was based on an institutional ethnography approach to mapping social processes; examining connections between local sites of experience and the social organization of work. The study findings revealed a critical disjuncture between the public mandate of advocacy, open dialogue, and support regarding mental health issues, and the private experience of workers which was characterized by silence, secrecy and inaction. Practices of silence were adopted by workers and workplace stakeholders across the organization, and were shaped by discursive forces related to stigma, staff-client boundaries, and responsibility to act. The silence had both positive and negative implications for the mental health of workers, as well as for relationships and productivity in the workplace. In accounting for the practices and production of silence, I argue that silence is complex, multi-dimensional, and embedded within the social relations of healthcare work. It serves to maintain institutional order. This conceptualization of silence challenges current beliefs and practices related to stigma, disclosure, early identification, support, and return to work for employees with mental health issues.

Racing Solidarity, Remaking Labour: Labour Renewal from a Decolonizing and Anti-racism Perspective - Ng, Winnie Wun Wun (University of Toronto, 2011)
The study examines how Aboriginal workers and workers of colour experience union solidarity and explores the necessary conditions for the remaking of solidarity and the renewal of the labour movement. Grounded in anti-colonial discursive framework, the study analyzes the cultures and practices of labour solidarity through the lived experiences of Aboriginal activist and activists of colour within the Canadian labour movement. Utilizing the research methodologies of participatory action research, arts-informed research and critical autobiography, the research draws on the richness of the participants’ collective experiences and visual images co-created during the inquiry. The study also relies on the researcher’s self-narrative as a long time labour activist as a key part of the embodied knowledge production and sense making of a movement that is under enormous challenges and internal competing tension exacerbated by the neoliberal agenda. The findings reveal sense of profound gap between what participants experience as daily practices of solidarity and what they envisioned. Through the research process, the study explores and demonstrates the importance and potential of a more holistic and integrative critical education approach on anti-racism and decolonization. The study proposes a pedagogical framework on solidarity building with four interlinking components – rediscovering, restoring, reimagining and reclaiming – as a way to make whole for many Aboriginal activists and activists of colour within the labour movement. The pedagogy of solidarity offers a transformative process for activists to build solidarity across constituencies in the pursuit of labour renewal and social justice movement building.
PhD

Women, Migration and Care Work: Filipino Health Care Aides in Canada - Novek, Sheila (University of Manitoba, 2011)
Personal care homes have become increasingly dependent on the employment of immigrant care workers. This qualitative study explored the high concentration of Filipino health care aides in personal care homes from their own perspectives, as well as that of policy stakeholders. In depth interviews were conducted with seven Filipino health care aides working in personal care homes in Winnipeg, Manitoba. Semi-structured interviews with policy stakeholders examined the policy context of the health care aide labour force. The study identified several factors that influenced the migration and employment of Filipino health care aides including: poverty and unemployment, migrant social networks, barriers in the labour market and financial incentives. The lack of regulations for health care aides sustained the flow of immigrant labour and enabled the expansion of social networks. Although their employment decisions were primarily based on financial need, health care aides valued their work and viewed themselves as critical care providers.

Women's Gendered Experiences of Rapid Resource Development in the Canadian North: New Opportunities or Old Challenges? - O'Shaughnessy, Sara (University of Alberta, 2011)
Rapid resource development in northern and rural Canada is leading to unprecedented social, political, economic and environmental changes in a number of communities. In particular, gendered identities and divisions of labour in northern Canadian communities are poised to be dramatically altered by increasing labour demands, shifting time-use patterns, and intensifying income inequalities. Through a feminist poststructuralist discourse analysis of print media coverage of gendered issues in Fort McMurray, and semi-structured interviews with thirty-two women working in either the male-dominated oil sector or the female-dominated social services sector, this dissertation examines how women in Fort McMurray, Alberta—the host community for the Athabasca oil sands—negotiate their identities and make sense of the opportunities and challenges associated with the recent oil boom. Drawing on materialist feminist and feminist poststructuralist theory, this dissertation first elaborates a comprehensive analytical framework for investigating gender in the context of natural resource extraction. This framework contends that gendered identities are inherently multiple, and divisions of labour are embedded in particular temporal and spatial contexts. Furthermore, this framework examines discursive and material contradictions in diverse gendered experiences of resource extraction in order to move beyond universalizing gendered interests and identities. Second, this dissertation examines how discursively constructed female subject positions in local and global print media over the past decade adopt a frame of frontier masculinity. I demonstrate that these subject positions become resources upon which women in Fort McMurray draw on to negotiate their identities in ways that perpetuate a sense of dependency and anomalousness. Finally, I explore how neoliberal discourses of individualism and meritocracy provide a potential site of resistance to hegemonic frontier masculinity in women’s narratives of their opportunities and challenges. However, I ultimately argue that neoliberal discourses and practices do not prove transformative of gendered identities and divisions of labour because women are only able to partially engage with neoliberal subjectivity, which neglects collective interests and wellbeing.

The Impact of Formative Work Experiences on the Psychological Contract: The Case of the Generation-X Knowledge Worker - Ormsbee, Floyd (Carleton University, 2011)
Organisations operating in today's market are facing an upcoming shift in workforce demographics. A majority of today's current workforce belong to the Baby Boomer generation (individuals born between 1946 and 1964). Many of these workers have already reached retirement age with many more reaching retirement age in the near future. The workers who are next in chronological line to fill the vacancies created by these departures belong to Generation X. There has been much speculation in the popular press concerning these workers, their work histories, and their workplace expectations. There has also been extensive study of the employment relationship (the psychological contract), a worker's assessment of that relationship, and the outcomes associated with it. However, there is no model directly tying worker experiences to the psychological contract and in turn outcomes of the psychological contract. This case study applied qualitative and quantitative methodologies to investigate the role work experiences play in the formation of the psychological contract with a present employer and the outcomes associated with it. Survey data were collected and in-depth personal interviews were completed with 66 Generation X middle level managers working for one of Canada's top employers competing in the knowledge sector. Findings suggest that several key work experiences in the labour market as well as experiences with a present employer are influential in perceptions of the relationship employees have with their employer, how they assess that relationship, and ultimately the outcomes of engagement and trust. The study concludes with: (1) a model illustrating the relationships between workers' experiences and the psychological contract process, and (2) a typology of worker types based on the effects of previous work experiences and perceptions of experiences with a current employer.
Keywords: Generation X; Psychology; Social sciences; Work experiences

The Role and Regulation of Private, For-Profit Employment Agencies in the British Columbia Labour Market and the Recruitment of Temporary Foreign Workers - Parrott, Daniel (University of Victoria, 2011)
My thesis examines the role and regulation of private, for-profit employment agencies in the British Columbia labour market with respect to the recruitment of temporary foreign workers. In it, I reviewed the historical origins of employment agency legislation in Canada. I go on to describe Canada’s Temporary Foreign Worker Program in connection with the transfer of federal immigration authority to the provinces. I also present a case study demonstrating how temporary foreign workers are recruited for the Live-in Caregiver Program in British Columbia, and use the study as a basis for comparing British Columbia’s employment agency legislation with the agency licensing regimes in the other Western Provinces. I conclude that Manitoba’s recent Worker Recruitment and Protection Act frames a best practice model for the protection of foreign workers during the recruitment process, and I encourage other provinces like British Columbia to develop and legislatively frame a similar set of best practices.

Organized Leadership for Equitable Change: Union-active Teachers Dedicated to Social Justice - Rottmann, Cynthia (University of Toronto, Ontario Institute for Studies in Education, 2011)
Historically, teachers’ unions have been some of the major organizational sites of social justice leadership in K-12 education (Kuehn, 2007; M. Murphy, 1990; Urban, 1982), but until the mid 1990s, the term “social justice unionism” (Peterson & Charney, 1999) had little currency in teacher union circles. The purpose of this qualitative case study was to examine the concept of social justice unionism in context. In particular, I asked how teacher union activists contributed and responded to the institutionalization of social justice in their organization. I used a critical constructionist (Ball, 1987; Berger & Luckmann, 1966; D. E. Smith, 1987) perspective to analyze 25 career history (Goodson, 1994) interviews with teachers, staff and elected officials affiliated with the British Columbia Teachers’ Federation between 1967 and 2007, and found that successive generations of union-involved activists dedicated to labour solidarity, feminism, multiculturalism, anti-colonialism and anti-homophobia used networks of like-minded colleagues to counter bureaucratic norms within their organization, the education system and society. A qualitative depiction of these changes suggests that they were layered, multi-dimensional and uneven. They played out on a contested, uphill gradient shaped, but not determined, by four factors: the organizational prioritization of teacher welfare over social justice; historically persistent micro-political struggles between two federation caucuses; the centralizing tendencies of union leadership in response to the provincial government’s centralization of educational authority; and broader ruling relations in Canadian society. Still, despite this uphill gradient, all activist networks left a durable trace on federation history. The major significance of this finding for critical theorists and social justice activists is a modestly hopeful alternative to the traditional conceptions of change embedded in organizational theory: revolution, evolution or despair.

Gifts of Rights?: A Legal History of Employment Pension Plans in Canada - Shilton, Elizabeth (University of Toronto, 2011)
This thesis explores the role played by law in the current breakdown of the employment pension system, focusing on the legal status of pension plans within the employment relationship, and on the way lawmakers have defined, shaped and enforced employee pension rights. It traces the legal status of employment pensions from their 19th Century characterization as gifts to reward employees for long and faithful service, to their current 21st Century construction as terms of the contract of employment. The thesis argues that Canadian lawmakers within all three legal regimes structuring rights and obligations within the employment relationship – the common law, collective bargaining law and statute law – have contributed significantly to the overall dysfunction of the system by cultivating both substantive and procedural legal rules that locate critical issues concerning the scope, design, durability and distribution of employee pension rights within the control of employers. Predictably, Canadian employers have used that control to shape pension plans to meet their distinct business needs, needs that frequently collide with worker needs and expectations for good pensions. Even in the heyday of the ‘Fordist’ work structures that fostered employment pension plans, the system delivered benefits very unequally, privileging the interest of elite workers who fit the ‘male breadwinner’ mould, and failing to provide adequate and secure pensions for the majority of Canadian workers. Changes in the organization of work in Canada, including trends towards more precarious work, will continue to exacerbate the problems inherent in the system, escalating its distributional inequalities. In the current round of pension law reform, Canada’s policy makers should abandon the effort to repair a system which is flawed at its core, and should instead seek a new foundation for pensions outside the employment relationship, a foundation which will not subordinate the pension interests of workers to the business interests of employers.

Activist Social Workers in Neoliberal Times: Who are We Becoming Now? - Smith, Kristin (University of Toronto, Ontario Institute for Studies in Education, 2011)
My thesis explores the knowledge, subjectivities and work performances that activist social workers bring to their practice in Ontario, Canada during a period of workplace restructuring that includes cuts to services, work intensification, increased surveillance and the evolving discourses of neoliberalism. A key aspect of my dissertation is the exploration of tensions between the attachments, desires and aspirations of the activist social work self and what that self must do every day to get by. I am interested in how it is that social workers produce and maintain their sense of identities – their integrity, ethics and responsibilities as activists – while also managing to navigate the contradictions of restructured workplaces. My aim is to understand not how power in the form of restructuring policies is imposed on people, but rather, how power acts through subjects who find themselves both implicated in, and struggling to resist neoliberal restructuring. My research lens draws on Michel Foucault’s ideas about governmentality and on feminist poststructural, critical race, and postcolonial theories. I use these theories to see neoliberal strategies of rule as working in diffuse ways through social and health service workplaces, encouraging service providers to see themselves as individualized and active subjects responsible for particular performances that enact specific types of change. My research findings reveal that activist social workers respond to neoliberal strategies of rule in multiple ways while constituting themselves through a variety of competing discourses that exist in their lives. Social workers subjectivities appear to be produced through a range of discourses drawn from their family histories, unique biographies and the intersections of socially produced distinctions that are based on gender, race, class, sexuality, age and nationalism. My dissertation traces some of the many ways that social workers position themselves within and beyond the changing context of neoliberalism. In doing so, my research reveals tentative pathways for building critical resistance practices and suggests future social welfare measures that are based on social justice and equity.

Calling for Resistance: The Political Economy of Indian and Canadian Call Centre Industries - Stevens, Andrew James Raymond (Queen's University, 2011)
Call centres have in the last three decades come to define the interaction between corporations, governments, and other institutions and their respective customers, citizens, and members. From telemarketing to tele-health services, to credit card assistance, and even emergency response systems, call centres function as a nexus mediating technologically enabled labour practices with the commodification of services. Because of the ubiquitous nature of the call centre in post-industrial capitalism, the banality of these interactions often overshadows the nature of work and labour in this now-global sector. Advances in telecommunication technologies and the globalization of management practices designed to oversee and maintain standardized labour processes have made call centre work an international phenomenon. Simultaneously, these developments have dislocated assumptions about the geographic and spatial seat of work in what is defined here as the new international division of knowledge labour. The offshoring and outsourcing of call centre employment, part of the larger information technology and information technology enabled services sectors, has become a growing practice amongst governments and corporations in their attempts at controlling costs. Leading offshore destinations for call centre work, such as Canada and India, emerged as prominent locations for call centre work for these reasons. While incredible advances in technology have permitted the use of distant and “offshore” labour forces, the grander reshaping of an international political economy of communications has allowed for the acceleration of these processes. New and established labour unions have responded to these changes in the global regimes of work by seeking to organize call centre workers. These efforts have been assisted by a range of forces, not least of which is the condition of work itself, but also attempts by global union federations to build a bridge between international unionism and local organizing campaigns in the Global South and Global North. Through an examination of trade union interventions in the call centre industries located in Canada and India, this dissertation contributes to research on post-industrial employment by using political economy as a juncture between development studies, critical communications, and labour studies.

The Aging Workforce: Addressing its Challenges Through Development of a Dignified Lives Approach to Equality - Alon, Pnina (University of Toronto, 2010)
Against the background of the global demographic shift towards an aging workforce and its impacts on the labour market and the economy in industrialized societies, this dissertation pinpoints six salient challenges for future litigation and policy-making in the area of labour and employment discrimination law. These include the global tendency towards abolishing mandatory retirement and increasing the eligibility age for pension benefits; legislative age-based distinctions; cost as a justification for age discrimination; performance appraisals of senior workers; and the duty to accommodate senior workers. At the core of each challenge lies a normative question regarding our conception of senior workers’ right to age equality, its importance and relative weight compared with other rights and interests. The aim of this dissertation is therefore to critically review the current understanding of this right and its moral and economic underpinning. Most notably, the dissertation contends that the prevailing conception of equality assessment (the Complete Lives Approach to equality), according to which equality should be assessed based on a comparison of the total share of resources obtained by individuals over a lifetime, has substantial implications for age discrimination discourse. As it uncovers the numerous difficulties with the complete lives approach, the dissertation develops an alternative: the Dignified Lives Approach to equality, according to which an individual should be treated with equal concern and respect, at any particular time and regardless of any comparison. The dissertation then articulates five essential principles founded in Dworkin’s notion of equal concern and respect: the principle of individual assessment, the principle of equal influence, the principle of sufficiency, the principle of social inclusion, and the principle of autonomy. When one of these principles is not respected at any particular time, a wrong is done, and the right to equality is violated. Next, the dissertation elucidates when and why unequal treatment of senior workers based on age does not respect each of these five principles and therefore constitutes unjust age discrimination. It demonstrates that senior workers’ right to age equality is a fundamental human right. Finally, it examines the above-mentioned challenges through the lens of the new Dignified Lives approach.

Railroad Crossings: The Transnational World of North America, 1850-1910 - Berkowitz, Christine Ann (University of Toronto, 2010)
The last quarter of the nineteenth century is often referred to as the “Golden Age” of railroad building. More track was laid in this period in North America than in any other period. The building of railroads was considered synonymous with nation building and economic progress. Railway workers were the single largest occupational group in the period and among the first workers to be employed by large-scale, corporately owned and bureaucratically managed organizations. While there is a rich historiography regarding the institutional and everyday lives of railway workers and the corporations that employed them, the unit of analysis has been primarily bounded by the nation. These national narratives leave out the north-south connections created by railroads that cut across geo-political boundaries and thus dramatically increasing the flows of people, goods and services between nations on the North American continent. Does the story change if viewed from a continental rather than national perspective? Railroad Crossings tells the story of the people and places along the route of the Grand Trunk Railroad of Canada between Montreal, Quebec and Portland, Maine and the Atchison, Topeka and Santa Fe Railroad (and later of the Southern Pacific) between Benson, Arizona and Guaymas, Sonora. The study first takes a comparative view of the cross-border railroad development followed by a consideration of emerging patterns and practices that suggest a broader continental continuity. The evidence demonstrates that this broader continental continuity flows from the application of a certain “railroad logic” or the impact of the essence of railroad operations that for reasons of safety and efficiency required the broad standardization of operating procedures that in many ways rendered place irrelevant.
Accepted: 2010-03-01T19:21:39Z

Speaking of Class in the Québec Labour Movement: Interpreting the Relationship Between Class and Identity in the Québec Labour Movement 1850-2010 - Bisaillon, Richard (Concordia University, 2010)
An examination of the recent and contemporary Québec labour union movement and its relationship with the nationalist cause might incline the observer to conclude that this powerful synthesis of what are in fact two separate sets of collective interests is a recent phenomenon sparked by Québec’s Quiet Revolution. In fact, these two aspects of collective and individual self and their expression through institutional forms have evolved together over the last two centuries. A further examination of the broader historical pattern demonstrates that aspects of shared linguistic and cultural identity have always at the very least qualified, and most often significantly muted expressions of working class interests and identity. In fact, save for a brief period from the Quiet Revolution to the first mandate of the Parti Québécois in 1976, working class collaboration with other class fractions in Québec ostensibly made in the greater interests of linguistic and cultural solidarity have generally cost the working classes a premium, while actually working to the benefit of other class partners. This historical pattern combined with the increasing influence of a neo-liberal ideological position within the Québec “state” leads to a certain conclusion: that there is an essential incompatibility between institutions calculated to represent working-class interests and movements founded upon a struggle for cultural recognition and the assertion of national interests. While the former seek the elimination or reduction of socio-economic differences, the latter seek only a cycling of dominant elites, resulting in the same dominant class relations under a different cultural elite fraction. –Author's abstract —————- An examination of Quebec labour unions and French Quebec's nationalist movement, which the author argues evolved together over a 200 year period. The author devotes one chapter to the "second wave of unionisation that washed over employees at Concordia University in the mid-1980s." During this period the university experienced the creation of approximately half a dozen unions over the span of a very few years in an institution that was comparatively lightly touched by the union experience previously. The author devotes another three chapters to the successive historical periods as they apply to the evolution of the labour movement in Quebec. One of these chapters deals with the first embryonic forms of working class representation couched within the context of "working men's associations," "benevolent societies" and the like, to genuine trade and labour unions after 1872 when the act of combination was decriminalised in Canada. Reference is made to English-speaking associations and societies during this early period, such as Quebec City's Ship Labourers' Benevolent Society, founded in 1857, by Irish workers. The author concludes with an examination of the cultural and linguistic divisions within Quebec's union movements. – Summary by Brendan O'Donnell, Bibliography on English-Speaking Quebec

Place aux individus : les itinéraires professionnels des travailleurs lors de la grève de Kirkland Lake, 1941-1942 - Blais, Sophie (Université Laurentienne, 2010)
Cette thèse de maîtrise retrace les parcours des travailleurs impliqués dans la grève des mines d'or de Kirkland Lake de 1941-1942. À partir de l'examen des fiches d'embauche et de service de la société aurifère la plus importante à Kirkland Lake, la mine Lake Shore, il a été possible de reconstituer, jour après jour, le déroulement du conflit, en y retraçant les va-et-vient précis de tous les travailleurs présents. À l'évidence, les itinéraires reconstitués des travailleurs sont multiples et divergents. Qu'il soit un employé de bureau ou un mineur, chaque travailleur a eu un parcours propre pendant la grève et a été susceptible de modifier à lui seul la tournure des événements, en adoptant, par exemple, des comportements non solidaires, ou en décidant de poursuivre la grève après sa fin officielle.

Mennonite Domestic Workers: Intersections of Gender, Ethnicity and Religion - Borger, Sandra Marie (Simon Fraser University, 2010)
The dominant representation of domestic work in the literature is quite negative, with uncaring employers, sexual, verbal, and physical abuse, and underpaid and overworked employees. However, the interviews conducted for this micro-study present an intriguingly different image. Young, immigrant Mennonite women who had come to Canada during the Second World War moved during the post-war period from their rural homes in the Fraser Valley, British Columbia, into the city of Vancouver. There, they were employed in domestic work and spent Thursday afternoons at the Maedchenheim, or girls’ home, with their peers. This thesis examines the disconnect between their accounts of domestic work and those of other domestics, with particular attention to how ethnoreligious understandings of gender, community, and survival informed my narrators’ memories and retellings of their experiences. It also explores whether the shift from a rural to an urban environment changed these women’s perceptions of their gender identity.

Mother Russia and the Socialist Fatherland: Women and the Communist Party of Canada, 1932-1941, with Specific Reference to the Activism of Dorothy Livesay and Jim Watts - Butler, Nancy Ellen (Queen's University, 2010)
This dissertation traces a shift in the Communist Party of Canada, from the 1929 to 1935 period of militant class struggle (generally known as the ‘Third Period’) to the 1935-1939 Popular Front Against Fascism, a period in which Communists argued for unity and cooperation with social democrats. The CPC’s appropriation and redeployment of bourgeois gender norms facilitated this shift by bolstering the CPC’s claims to political authority and legitimacy. ‘Woman’ and the gendered interests associated with women—such as peace and prices—became important in the CPC’s war against capitalism. What women represented symbolically, more than who and what women were themselves, became a key element of CPC politics in the Depression decade. Through a close examination of the cultural work of two prominent middle-class female members, Dorothy Livesay, poet, journalist and sometime organizer, and Eugenia (‘Jean’ or ‘Jim’) Watts, reporter, founder of the Theatre of Action, and patron of the Popular Front magazine New Frontier, this thesis utilizes the insights of queer theory, notably those of Eve Kosofsky Sedgwick and Judith Butler, not only to reconstruct both the background and consequences of the CPC’s construction of ‘woman’ in the 1930s, but also to explore the significance of the CPC’s strategic deployment of heteronormative ideas and ideals for these two prominent members of the Party.

Asbestos, Quebec: The Town, the Mineral, and the Local-Global Balance Between the Two - Horssen, Jessica van (University of Western Ontario, 2010)
From the late 19th to the late 20th century, the cities and industries of the world became increasingly reliant on fireproof materials made from asbestos. As asbestos was used more and more in building materials and household appliances, its harmful effect on human health, such as asbestosis, lung cancer and mesothelioma, became apparent. The dangers surrounding the mineral led to the collapse of the industry in the 1980s. While the market demand and medical rejection of asbestos were international, they were also experienced in the mining and processing communities at the core of the global industry. In the town of Asbestos, Quebec, home of the largest chrysotile asbestos mine in the world, we can see how this process of market boom and bust shaped a fierce local cultural identity. This dissertation examines the global asbestos industry from a local perspective, showing how the people of Asbestos, Quebec had international reach through the work they did and the industry they continue to support today. This thesis explores how the boundaries between humans and the environment were blurred in Asbestos as a strong cultural identity was created through the interaction between people and the natural world. This work advances our understanding of the interdependence of the local-global relationship between resource industries and international trade networks, illustrating the ways it shapes communities and how communities shape it. Bringing bodies of land, human bodies, and the body politic of Asbestos, Quebec into the history of the global asbestos trade helps demonstrate how this local cultural identity grew to influence national policy and global debates on commodity flows, occupational health, and environmental justice.
https://cha-shc.ca/prize-winner/jessica-johanna-van-horssen/

"A Useful Art": Artistic Labour and Social Justice in Canadian Poetry from 1789 to 1945 - Kelly, Erica Sue (University of Western Ontario, 2010)
Since well before the official endorsement of "peace, order and good government" in the British North America Act of 1867, Canada has understood itself as a peace keeping and socially-progressive collective. Both before and after the BNA Act, Canadian poets critiqued as well as celebrated this persistent national mythology, offering their poetry as social commentary and as impetus to change. This thesis considers the shifting understanding of the role of Canadian poets in shaping the nation and in establishing social justice. After tracing a history of theoretical understandings of social justice with specific attention to the arrival and evolution of such theory within Canada, the thesis reads poetry from before Confederation to the end of the Second World War in relation to its political and social moment. The first chapter investigates Canadian poetry from its beginnings to 1900, and through consideration of the poems of Alexander McLachlan, Isabella Valancy Crawford, Duncan Campbell Scott, and Archibald Lampman, among others, charts the persistent concern with what the historian Ian McKay calls "imagining otherwise;" that is, the desire to discover in Canada a place with the potential to envision alternatives, free from the hierarchies and injustices of the old world. These poets use the space of their work to reimagine labour and to explore the benefits of cooperation, and they persistently return to the role of the poet in crafting the just state they imagine. The second chapter turns to the Canadian modernist understanding of literary inheritance and re-creation Through a focus on F.R. Scott, the chapter considers the nation's artistic response to the Depression, as well as the influence of America's Federal One program, which extended employment to the nation's artists. The third chapter investigates modernist collectives in greater detail, reading the artistic and critical output of such artistic collaborations as Masses, Contemporary Verse, Preview and First Statement as challenges to the Canadian definition of artistic responsibility. Across the time periods considered, this thesis investigates ways in which poets balance idealism and pragmatism, commitments of form and content, and concern for the welfare of the individual and the wellbeing of the collective.
Keywords: Artistic labor; Language; Poetry; Social justice; literature and linguistics

Knowledge Management Processes in Growth-Oriented SMEs: An Atlantic Canadian Perspective - MacDonald, Harry Douglas (University of Stirling, 2010)
Competitive pressure and desire for success drive enterprises in general to involve in knowledge acquisition and dissemination activities that are becoming increasingly significant in the rapid changing and globalising economic world. In addition, with the increased mobility of information and the global labour force, knowledge and experience can be transferred instantaneously around the globe; thus, any advantage gained by one company can be eliminated by comparative improvements overnight. Therefore, the only comparative advantage a particular company will face will be its process of innovation – combining market and technology know-how with the resourceful talents of knowledgeable labour to solve a constant stream of competitive problems- and its ability to derive value from information. In this context, internal and external knowledge acquisition, intra-firm knowledge dissemination and management decisions taken in response to the significant information generated and subsequently filtered became the key factors of entrepreneurial success. This thesis explores how market orientation, learning orientation and entrepreneurial orientation systematically contribute to and are sources of competitive advantage in growth-oriented SMEs. The objective of this study was to investigate the likelihood of a growth-oriented enterprise established in Atlantic Canada to be involved in knowledge acquisition and dissemination activities and to succeed conditional on numerous internal and external factors. A ‘mixed-methods’ research approach was used in this study, comprised of: 1) a web-based questionnaire to study the knowledge management process and other aspects of entrepreneurial success and 2) ‘semi-structured’ interviews with a sample of the responding entrepreneurs. The findings suggest that knowledge management practices: external acquisition, intra-firm dissemination and responsiveness, do vary across the levels of entrepreneurial performance among the Atlantic Canadian SMEs investigated in the study. Having a market orientation and investing in human resources of the firm were found to be critical drivers of innovation leading to potential competitive advantage.

Québec City's Ship Carpenters, 1840 to 1893: Working Class Self-Organization on the Waterfront - Mathieu, Jean-Philip (University of Ottawa, 2010)
In the mid-nineteenth century, the construction of wooden sailing vessels became the single most important employer in Québec City. Thousands of people worked as shipwrights in the shipbuilding industry, but ship carpenters were the backbone of the trade. These workers displayed an extraordinary capacity for mobilization, being responsible for some of Canada's earliest labour organizations, starting in 1840 with the Société amicale et bienveillante des charpentiers de vaisseaux de Québec. This study demonstrates that ship carpenters' impressive capacity for organization was the result of the trade's remarkable ethnic homogeneity, as no less than 90% of ship carpenters were French Canadian, and most lived together in the working class suburb of Saint Roch. This homogeneity allowed ship carpenters to avoid the bitter internecine conflict that plagued the early labour movement, and allowed them to become part of the vanguard of the Canadian working class.
OCLC: 775058973

A Crisis of Commitment: Socialist Internationalism in British Columbia During the Great War - McCartney, Dale Michael (Simon Fraser University, 2010)
Historians who have examined the BC socialist and labour movement have generally overlooked the First World War period, assuming that the left uniformly opposed the war. In reality, close attention to archival sources and newspapers has revealed that the war created a crisis of commitment for BC leftists between their commitment to socialist internationalism and thus opposition to the war, and their support for the British Empire and the war it was engaged in. Eventually, the need for socialist internationalism to protect ethnic Canadian socialists led the BC Federation of Labour to elect a new anti-war leadership coalition. This coalition built several new organizations, including the Federated Labour Party and the One Big Union, as well as led the general strikes in Vancouver and Winnipeg in 1918 and 1919. This study is the first to demonstrate the central importance of socialist internationalism to the success of the post-war left.

Not Ashamed or Afraid: Portuguese Immigrant Women in Toronto's Cleaning Industry, 1950s-1995 - Miranda, Paula Susana Ferreira (York University, 2010)
Portuguese immigrant women occupied a niche in Toronto's cleaning industry, including both domestic and building cleaning, from the 1960s to the 1990s. This thesis examines the working and organizational experiences of Portuguese women in these sectors. Women's labour was crucial to the Portuguese immigrant family economy. Their workplace activism was framed by their positions as wives and mothers dedicated to the financial well-being of their families. They also acted as female immigrant workers seeking justice and dignity in the workplace. Portuguese immigrant women had an effect on larger Canadian society by positively shaping the domestic and building cleaning sectors, influencing unions and politicians to respond to the concerns of immigrant workers, as well as influencing the community work agenda of social service agencies. Portuguese immigrant women actively shaped the day domestic cleaning occupation, and made it more contractual, and less of a 'servant' experience by limiting tasks, reducing hours, increasing their wages, cultivating their 'expertise' in the occupation, as well as establishing more equitable relationships with employers. Conversely, Portuguese building cleaners were contract workers, which meant job insecurity, and low wages. Portuguese women attempted to improve their working lives in this sector by forging links with community activists, joining unions, and calling on the state to act in their interests. Their activism was aided by a new progressive community agency and labour context in the 1970s. Influenced by the Christian Left, and new ideas about consciousness-raising community work, social service workers created new programs, such as ' Cleaners' Action', to help immigrants mediate their encounters with dominant society. As a result, progressive unions became more interested in organizing in the cleaning industry. Through the lens of Portuguese women's workplace experiences, my dissertation provides insight into the period after the Second World War, including the expansion of the service industry, the modernization of domestic work, how the more conservative economic context of the 1970s and 1980s impacted immigrants in building cleaning, how unions became more responsive to immigrant and female workers, the rise of progressive community work, and of immigrant women's labour activism within this context.

The Politics of Capital: The Crisis and Transformation of Canada's Big Bourgeoisie, 1917-1947 - Nerbas, Don (University of New Brunswick, 2010)
This study examines the changing mentalité as well as the shifting accumulation and political strategies of Canada's big bourgeoisie during the transformative period from 1917 to 1947. Engaging literatures from a range of disciplines and subfields within history, the study pursues biographical case studies of five leading business and political figures from different regions and associated with different sectors of the economy. The group includes Howard P. Robinson (1874-1950), Charles Dunning (1885-1958), Sir Edward Beatty (1877-1943), Sam McLaughlin (1871-1972), and C.D. Howe (1886- 1960). In an era when American investment surpassed British investment for the first time and created a new dependency for the country's economic elite, the crisis of the old political economy of the National Policy period became apparent as business leaders and institutions struggled to maintain their economic and political power. This challenge became more pronounced with the onset of the Great Depression and the rise of social democratic and socialist alternatives, including a strong labour movement. For members of the economic elite whose residual worldview was associated with finance capital, compromise on key issues was difficult and some members questioned the efficacy of democratic governance in a time of economic crisis, but the eventual political defeat of this response cleared the way for ideological and political adjustments. The tendency of the scholarly literature to focus on the themes of economic dependency and political continuity in this period has concealed the more complex story told in this study: of finance capital's political failure and the eventual triumph of a form of managerial capitalism that accepted government intervention without ceding ideological ground.
Keywords: Bourgeoisie; Capital

Sisters in Toil: The Progressive Devaluation and Defeminization of Ontario Dairywomen's Work and Tools 1813-1914 - Quaile, Meredith Leigh (Memorial University, 2010)
In nineteenth and early-twentieth century Ontario, dairywomen toiled daily with cows and manure, sour milk and greasy butter, yet without improved apparatus, agricultural education, or male support. On the provincial family farm, milking, cream-separating, and butter-making chores included various time-consuming steps, physical labour, and an array of task-specific objects. This thesis analyses agriculture, and dairying in specific, as it began the transition from traditional to industrial, and consequently from female to male. – This dissertation touches on particular topics relevant to farmwomen's labour, including: agricultural education and improvement through science; public debate and perception surrounding gendered work; the government's role in promoting industrialization and thus defeminization; the concept of the dairyqueen in technological advertising; and, in particular, real farmwomen. These dairying 'sisters' include the well known, like Susanna Moodie and Catharine Parr Traill, Laura Rose, and Eliza Jones, and the unknown, such as Mary Newsam and the Hallen sisters, while focusing on Lamira Billings and her daughters Sabra and Sally. – This qualitative study reveals that by employing common dairy tools as a dominant, primary source, there are alternative perspectives from which to consider rural women's experiences. Analysis of material culture objects, like milking stools and pails, butter bowls and scotch hands, shallow separating pans and tin creamer cans, also allows for exploration of the tensions between projected male ideals and tangible female work - a question central to understanding gender and labour within a social history context. In addition to technologies, sources like The Farmer's Advocate, the photographs of Reuben Sallows, and early dairy advertisements, add to our understanding of the concerns surrounding dairywomen's labour during the period discussed. – Historians have suggested that dairy work was removed from the female sphere before the turn of the twentieth century in Ontario. Male agriculture authorities, scientific experts, and government officials, indeed initiated a conscious devaluation of farmwomen's work, oriented toward the defeminization of dairying. Rather than being removed from dairy work, however, Ontario's farmwomen continued separating cream and making butter between 1813 and 1914, habitually and simply equipped with their two hands, their mother's knowledge, and their grandmother's tools.

Clerical Workers: Acquiring the Skills to Meet Tacit Process Expectations Within a Context of Work Undervaluation and Job Fragility - Radsma, Johanna (University of Toronto, Ontario Institute for Studies in Education, 2010)
Since the late nineteenth century, clerical work has transformed from a small cluster of respected occupations dominated by men to a rapidly changing group of occupations 90 percent of which are held by women. Due to bureaucratization and the feminization of clerical work, clerical jobs are assumed to be routinized and simple, and clerical workers deemed easily replaceable. With further changes to the occupation caused by technology and globalization, clerical workers today have become increasingly vulnerable to unemployment, precarious employment and underemployment. In this research, an Ontario-wide survey with approximately 1200 respondents (including 120 clerical workers) and in-depth interviews with 23 Toronto clerical workers were combined to explore the employment situation of Ontario clerical workers. It is apparent that clerical workers are underemployed along all measured conventional dimensions of underemployment, including credential, performance and subjective as well as work permanence, salary levels and job opportunities. Relational practice is a largely unexamined aspect of clerical work that is often essentialized as a female trait and seldom recognized as skilled practice. In this dissertation, I argue that relational practice is critical to the successful performance of clerical roles and that relational practices are not innate but rather learned skills. I explore some ways in which clerical workers acquire these skills. I conclude by noting that recognizing and valuing relational skills will make the value of clerical workers more apparent to their employers, potentially reducing for clerical workers both their subjective sense of underemployment and their vulnerability to job loss.

Underemployment and Health-related Quality of Life - Raykov, Milosh M. (University of Toronto, Ontario Institute for Studies in Education, 2010)
Considering the increasing levels of unemployment and underemployment, and the limited evidence concerning the impact of underemployment on health, my study examines the relations between subjective, objective, and time-related underemployment and employees’ health-related quality of life, as manifested through self-rated health, activity limitations and work-related stress. The study compares an expanded model of work-health relations that, along with the factors addressed by control-demand, and social capital theories, includes characteristics of the physical work environment, and employees’ economic class. In addition to the commonly examined factors related to employment and health (control-demand and social capital), my study explores the impact of the work environment (hazards, discomfort and physical demands) and economic class to determine the specific effects of underemployment on an employee’s health-related quality of life. My main argument is that underemployment, in conjunction with lower economic class, higher exposure to a harmful work environment, lack of control over work, and lower social capital, contributes to increased work-related stress and diminishes health-related quality of life. The study applies a mixed methodological approach based on data from the Canadian Work and Lifelong Learning Survey and the US General Social Survey, and qualitative analysis of interviews from the Ontario Survey on Education-Job Requirements Matching. Evidence based on cross-sectional and qualitative data analysis provides consistent findings and confirms the main assumption that high levels of underemployment have a significant effect on employees’ health-related quality of life. The study shows that employees’ economic class, characteristics of work environment and control over work carry the highest associations with health-related quality of life, while underemployment has a significant additive association with health-related quality of life, most importantly with work-related stress.

Cities of Comrades: Urban Disasters and the Formation of the North American Progressive State - Remes, Jacob Aaron Carliner (Duke University, 2010)
A fire in Salem, Mass., in 1914 and an explosion in Halifax, N.S., in 1917 provide an opportunity to explore working-class institutions and organizations in the United States-Canada borderlands. In a historical moment in which the state greatly expanded its responsibility to give protection and rescue to its citizens, after these two disasters ordinary survivors preferred to depend on their friends, neighbors, and family members. This dissertation examines which institutions–including formal organizations like unions and fraternal societies as well as informal groups like families and neighborhoods–were most relevant and useful to working-class survivors. Families, neighbors, friends, and coworkers had patterns and traditions of self-help, informal order, and solidarity that they developed before crisis hit their cities. Those traditions were put to unusual purposes and extreme stress when the disasters happened. They were also challenged by new agents of the state, who were given extraordinary powers in the wake of the disasters. This dissertation describes how the working-class people who most directly experienced the disasters understood them and their cities starkly differently than the professionalized relief authorities. Using a wide array of sources–including government documents, published accounts, archived ephemeral, oral histories, photographs, newspapers in two languages, and the case files of the Halifax Relief Commission–the dissertation describes how elites imposed a progressive state on what they imagined to be a fractured and chaotic social landscape. It argues that "the people" for whom reformers claimed to speak had their own durable, alternative modes of support and rescue that they quickly and effectively mobilized in times of crisis, but which remained illegible to elites. By demonstrating the personal, ideological, political, and practical ties between New England and Nova Scotia and Quebec, it also emphasizes the importance of studying American and Canadian history together, not only comparatively but as a transnational, North American whole.
https://cha-shc.ca/prize-winner/jacob-aaron-carliner-remes/

Kitty Malloys and Rebel Girls: Representations of the Woman Worker in Vancouver’s Early 20th Century Mainstream and Radical Labour Newspapers - Schachtel, Kristin Michelle (Simon Fraser University, 2010)
Vancouver’s early twentieth century mainstream newspapers captured a feminine culture of the young woman worker caught in a moral paradox of naïveté and willing impropriety. Through images and narratives, the tumultuous social and economic changes of the day were rendered “class-based girl problems.” By contrast, radical labour newspapers represented women workers as “rebel girls” and valiant helpmates to the working class movement. This examination of images and narratives prompts consideration of how these class and gender discourses influenced real women workers. In particular, the telephone operators’ activism during Vancouver’s 1919 sympathetic strike demonstrates how women workers re-created discourses of class and gender in ways that brought greater control and meaning to their lives. While early twentieth century newspapers framed contemporary discourses of class and gender through images and narratives, they were unable to capture the resonance and pertinence of these discourses to the everyday lives of working women.

Making and Defending Intimate Spaces: White Waitresses Policed in Vancouver's Chinatown Cafes - Sia, Rosanne Amosovs (University of British Columbia, 2010)
In mid-1930s Vancouver, city authorities launched a campaign to ban white waitresses from Chinatown cafes. Canadian historians have overlooked this campaign because of the tendency to treat the Chinese in Canada as a separate history from working women and to focus on discourse analysis rather than experience. This obscures the importance of sexuality and cross-racial interaction to the lives of both Chinese “bachelors” and white working women in Canada. This paper shows how white waitresses, Chinese restaurant owners, and Chinese patrons created and defended a social space of cross-racial intimacies in Vancouver’s Chinatown cafes. By examining a variety of sources, including mainstream and labour newspapers, mayor’s and police records, oral histories, and Chinese-language newspapers, this paper considers the perspectives of the four groups involved in the campaign. City authorities constructed the cafes as immoral spaces, where white waitresses were enticed into prostitution by Chinese men. In the name of protecting white womanhood, they drew a gendered and racial line around Chinatown. Despite policies of racial and gender equality, labour organizations also viewed the campaign through this lens of morality. For the white waitresses and Chinese customers, on the other hand, these cafes opened up a social space to explore cross-racial intimacies. In the cafes, they flirted, formed friendships, and began sexual relationships. The Chinese “treated” the waitresses to dinner, gifts, or money in exchange for sexual intimacy. Some of these intimacies were purely functional, while others developed into relationships that fulfilled mutual interests, needs, and desires. Through these intimate practices, they created choices and opportunities not available outside of Chinatown. The ban forced the Chinese, and especially the white waitresses, to become self-reflective about their experience in the cafes. The Chinese condemned the ban as racial discrimination. Fifteen white waitresses marched on city hall, where they defended their rights as workers, their respectability, and their Chinese employers. The waitresses articulated why the Chinatown cafes held value in their lives and in Vancouver. They had lost their jobs and their reputations, but they took a political stand.

Who Cares? The Impact of Neoliberal Policies and New Organizational Methods on Child and Youth Workers - Altass, Patricia D. (University of Guelph, 2009)
Child and Youth Work is an emotionally demanding profession with an extremely high burnout rate. Previous research has shown that there are a variety of factors that contribute to high rates of burnout within this profession. This thesis begins by exploring topics related to stress, burnout, emotional labour and vicarious trauma, providing a context to understand the inherent issues and challenges faced by workers in this field. The prevailing beliefs and values underlying neoliberal policies resulting in funding restrictions within the social services are then considered in relation to the impact of these policies on experienced levels of worker stress and burnout with the residential care field. Lastly, this thesis looks at the introduction of new organizational methods, specifically Total Quality Management and New Public Management, as strategies implemented by agencies to cope with funding limitations, and the resulting impact on levels of stress and burnout of front line residential child care workers. In addition to the three key areas of focus, the role and impact of unions within residential treatment settings is considered as a potential avenue for positive change within these workplaces.

Farm-Level Impacts in Mexico of the Participation in Canada's Seasonal Agricultural Workers Program (CSWAP) - Carvajal, Lidia (University of Guelph, 2009)
In several parts of the world, the number of poor people in rural areas surpasses the capacity of agriculture to provide employment opportunities. The increasing role of off-farm income has highlighted the importance of rural migration, both within Mexico and to the United States (US) and Canada, as a vehicle for poverty reduction. A significant number of Mexican migrants are participating in guest worker programs, performing mainly agricultural activities. These programs allow Mexicans to enter the US and Canada through formal channels. Canada's Seasonal Agricultural Workers' Program (CSAWP) lets Mexican farmers enter Canada to work legally in agriculture, and participants in this Program send remittances home that are an important contribution to rural development. The main reasons to participate in guest worker programs relate to economic factors, such as the opportunity to earn a relatively high, stable income abroad and the lack of employment opportunities in Mexico, particularly in rural areas. The number of Mexican agricultural workers temporally migrating to Canada through CSAWP has increased significantly over time and now exceeds 12,000 annually. In Mexico, the program provides an estimated C$70 million in remittance income annually, mainly directed to rural and poorer regions. In these regions, this fungible income supports consumption activities and expenditures on family education. However, there are also investments in farming activities, in turn enhancing agrarian incomes. This research explores the impact of remittances on farm investments by migrant workers participating in CSAWP, which in turn impact farm income levels. The results highlight the extent to which temporary migrant labour to Canadian agriculture allows Mexican farmers to enhance their agricultural activities through increased farm investments, such as buying better seeds, fertilizer and farm equipment. The results show that, on the one hand, remittances can significantly enhance farm investments in Mexico that in turn increase farm incomes and, on the other, remittances increase non-farm incomes in Mexico, allowing farm migrants to expand their income portfolio. Hence, these results support the New Economics of Labour Migration (NELM) hypothesis that remittances relax the liquidity constraint in production/investment decisions. Furthermore, family labour availability counterbalances any temporary labour loss because of migration.
Keywords: Canada; Farm-level; Mexico; Seasonal Agricultural Workers Program; Social sciences

Benchmarking Carrots and Sticks: Developing a Model for the Evaluation of Work-Based Employment Programs - Castonguay, Julie (Hugo Sinzheimer Institute, University of Amsterdam, 2009)
Social benchmarking is an evaluation method in which the performance levels of different public social programs are compared, either relatively to each other or to an absolute value. The first part of this research discusses the use of social benchmarking for the evaluation of active labour market policies. This part also develops a social benchmark model, which can be used to assess the performance of active labour market policies in general, and work-based employment programs in specific. The second part of this research consists of the actual benchmarking of the work-based employment programs in five countries: Australia, Canada, the Netherlands, Switzerland and the United Kingdom.

Les jeunes migrants québécois dans les vallées fruitières de la Colombie-Britannique : ethnographie d'une forme de mobilité - Couture, Hugo (Laval, 2009)
Le groupe des jeunes voyageurs combinant le travail dans leur expérience de voyage constitue le segment du marché touristique mondial qui enregistre la croissance la plus importante cette dernière décennie. Certaines économies régionales dépendent de cette force de travail temporaire. C'est le cas de l'industrie agricole des vallées de l'Okanagan-Similkameen et de Creston en Colombie-Britannique qui accueille annuellement des milliers de migrant fruit pickers provenant majoritairement du Québec. Ce mémoire porte sur le quotidien de ces jeunes québécois et s'attarde à comprendre le sens qu'ils accordent à leurs projets de mobilité. Sur la base d'entretiens, je dégage l'imaginaire commun, les mythes, les idéaux et les représentations qui ont incité les jeunes à partir: Les résultats indiquent que ces jeunes inscrivent leur mouvement dans une double logique de quête et de fuite et que le sens attribué à l'expérience de vacances-travail diffère entre les nouveaux arrivants et ceux qui reviennent d'année en année.

Pour un syndicalisme de lutte de classe! : les groupes marxistes-léninistes et le mouvement syndical au Québec, 1972-1983 - Dubois-Campagna, Alexis (Université de Sherbrooke, 2009)
Dès la fin des années 1960, se développe une nouvelle tendance socialiste au Québec dans un contexte marqué par l'épuisement de la Révolution tranquille et par une ébullition idéologique sur la scène internationale. Dans ce climat politique, des groupuscules marxistes-léninistes (m-l) de tendance maoïste voient le jour au Québec, principalement dans la deuxième moitié des années 1970. Au même moment, sur le front syndical québécois, la lutte est intense entre travailleurs et employeurs. Les fronts communs de 1972 et 1975 et d'importantes grèves en font foi. De plus, de nombreux chefs syndicaux n'hésitent pas à s'attaquer directement au patronat et à l'État dans des discours clairement nourris par l'idéologie socialiste. Le radicalisme politique, même s'il n'est pas homogène et généralisé dans les centrales québécoises, s'impose de plus en plus dans les syndicats locaux comme dans les instances supérieures. C'est précisément les liens entre ces deux mondes, celui des groupuscules marxistes-léninistes et celui des centrales syndicales, qui nous intéressent. L'originalité de notre travail tient au fait qu'il lie les historiographies du marxisme-léninisme et du syndicalisme, ce qui représente un angle intéressant afin de renouveler la réflexion dans ces deux champs de recherche, certes très proches, mais malheureusement trop souvent étanches. À l'aide de diverses sources écrites, notamment les publications des organisations m-l et les archives des mêmes groupes, mais aussi d'entrevues menées par l'auteur avec d'anciens militants syndicaux, nous observons les relations entre les deux principaux groupuscules marxistes-léninistes, à savoir En Lutte! et la Ligue communiste (marxiste-léniniste) du Canada, et les centrales syndicales québécoises entre 1972 et 1983. Effectivement, il nous semble pertinent de mieux comprendre la nature des liens et des influences réciproques entre ces acteurs sociaux. L'objectif premier de cette recherche est de mettre en relief le militantisme des marxistes-léninistes au sein de ces institutions syndicales. En effet, la structure ouverte des syndicats, c'est-à-dire démocratique et accessible à tous les travailleurs syndiqués, a permis à un grand nombre de membres et sympathisants m-l de s'y intégrer et d'y faire valoir des positions d'extrême gauche. Et c'est justement le militantisme soutenu des m-l qui, contrastant avec celui beaucoup plus passif de l'ensemble des membres syndiqués, leur a permis d'influencer les positions et les stratégies des centrales syndicales, du moins de s'y faire entendre et de susciter des débats, particulièrement entre 1975 et 1980. Notre recherche sur cet aspect du militantisme syndical des marxistes-léninistes québécois éclaire des zones d'ombre de l'histoire politique récente de la province. De plus, cette étude amène une connaissance plus profonde de la place du radicalisme dans la culture politique québécoise et une meilleure compréhension du militantisme et de ses rouages. Afin d'atteindre nos objectifs, nous analysons d'abord le discours des marxistes-léninistes au sujet du monde syndical. Il sera notamment question des critiques sévères lancées contre les chefs syndicaux, ainsi que de la lutte idéologique qui secoue les différents groupes marxistes. Nous étudions ensuite les stratégies et les actions des m-l face aux syndicats, comme la volonté de se présenter à des postes électifs. Finalement, ce mémoire tente de mettre en lumière le militantisme m-l dans les différentes instances de la Confédération des syndicats nationaux, tout particulièrement le Conseil central de Montréal.

Trouble in Our Fields: Health and Human Rights Among Mexican and Caribbean Migrant Farm Workers in Canada - McLaughlin, Janet (University of Toronto, 2009)
For many years Canada has quietly rationalized importing temporary "low-skilled" migrant labour through managed migration programs to appease industries desiring cheap and flexible labour while avoiding extending citizenship rights to the workers. In an era of international human rights and global competitive markets, the Canadian Seasonal Agricultural Workers Program (SAWP) is often hailed as a "model" and "win-win" solution to migration and labour dilemmas, providing employers with a healthy, just-intime labour force and workers with various protections such as local labour standards, health care, and compensation. Tracing migrant workers' lives between Jamaica, Mexico and Canada (with a focus on Ontario's Niagara Region), this thesis assesses how their structural vulnerability as non-citizens effectively excludes them from many of the rights and norms otherwise expected in Canada. It analyzes how these exclusions are rationalized as permanent "exceptions" to the normal legal, social and political order, and how these infringements affect workers' lives, rights, and health. Employing critical medical anthropology, workers' health concerns are used as a lens through which to understand and explore the deeper "pathologies of power" and moral contradictions which underlie this system. Particular areas of focus include workers' occupational, sexual and reproductive, and mental and emotional health, as well as an assessment of their access to health care and compensation in Canada, Mexico and Jamaica. Working amidst perilous and demanding conditions, in communities where they remain socially and politically excluded, migrant workers in practice remain largely unprotected and their entitlements hard to secure, an enduring indictment of their exclusion from Canada's "imagined community." Yet the dynamics of this equation may be changing in light of the recent rise in social and political movements, in which citizenship and related rights have become subject to contestation and redefinition. In analyzing the various dynamics which underlie transnational migration, limit or extend migrants' rights, and influence the health of migrants across borders, this thesis explores crucial relationships between these themes. Further work is needed to measure these ongoing changes, and to address the myriad health concerns of migrants as they live and work across national borders.
Keywords: Canada; Caribbean; Farmworkers; Health; Health and environmental sciences; Human rights; Jamaica; Medical anthropology; Mexico; Migrant farm workers; Migrant workers; Migration; Seasonal Agricultural Workers Program; Social sciences; Temporary foreign workers; occupational health

State Strategy for Migration Management: Canada's Two Temporary Foreign Worker Programs, The Seasonal Agricultural Workers Program & The Live-in Caregiver Program - Reed, Austina J. (McMaster University, 2009)
This study applies an IPE approach to examine the economic conditions, motivations and interests which have driven the Canadian government and two sending countries, Mexico and the Philippines, to accept the terms and conditions of a regulatory framework encouraging short-term labour migration between them. The features of program development which underpin the Seasonal Agricultural Workers Program (SAWP) and the Live-in Caregiver Program (LCP) have not been compared side by side. Nor have the two programs been compared for the relationship that has developed over the years between the Canadian government and the two sending governments of Mexico and the Philippines. The study's core research question asks how the process of regulating cross-border labour migration works and how it is coordinated between two or more governments that form part of a migration system. An important research finding that emerges from the comparison is the categorization of different types of migration systems. I argue that the SAWP and LCP differ in how they are administered because relations between the various actors differ. Furthermore, what defines these relationships is the set of geopolitical and economic interests that each government carries when it negotiates the regulation of cross-border labour migration. Findings suggest that the geopolitical and economic imperative which has driven the SAWP's development is not the same for the LCP.

Collective Bargaining for New Brunswick Nurses by New Brunswick Nurses 1965-1969: In Unity There Is Strength - Reeves, Roxanne (University of New Brunswick, 2009)
New Brunswick nursing history is a little-known but significant story, and it helps us to understand women's paid work and how women organized to protect their interests in this occupation. While the profession's history demonstrates the importance of professional ideals, the New Brunswick, case also illuminates the struggle between these ideals and nurses' growing sense of dissatisfaction with wages and working conditions. In the mid-1960s in New Brunswick as elsewhere in Canada, nurses began to explore collective bargaining as a solution to poor wages and conditions and as a means to express concern for deteriorating patient care. This study examines the early stages of unionization among New Brunswick hospital nurses in 1965-1969. The evidence for this study is drawn from archival collections, interviews, newspapers, journals and secondary sources. Particular emphasis is placed on the pioneering efforts of the Social and Economic Welfare Committee (SEWC) of the New Brunswick Association of Registered Nurses (NBARN) and their efforts to educate members, lobby government, obtain outside expert advice and generally guide nurses towards a sense of collective identity that fostered a willingness to take collective action. By the end of the decade, nurses were included in a new Public Service Labour Relations Act, an outcome of the Royal Commission on Employer-Employee Relations in the Public Services (known as the Frankel Commission) which, among other features, greatly expanded the civil service and consequently the number of government employees with collective bargaining rights. Despite the fact that the new PSLRA had not yet been proclaimed, nurses in mid-1969 negotiated their first (if unofficial) collective agreement using the tactic of mass resignation to force a settlement. This thesis places the NBARN's early explorations of collective bargaining in the context of the political, economic and labour landscape of the 1960s.
Keywords: Health and environmental sciences; Social sciences

From Acculturation to Integration: The Political Participation of Montreal's Italian-Canadian Community in a Urban Context, 1945-1990 - Ricci, Amanda (Université de Montréal, 2009)
This thesis explores the political participation of the Montreal ltalian-Canadian community in an urban context, from 1945-1990. Concentrating on the local level, it examines the ltalian-Canadian contribution to municipal politics, the Quebec labour movement, mobilization with regards to the language debate, and' feminist activism. This historical account relies mainly upon the Montreal-based, Italian-language newspaper, Il Cittadino Canadese, as well as papers published by Italian-Canadian community organizations. The first chapter exammes the role ltalian immigrant elites played in the construction of a politicized ltalian-Canadian identity, as well as the establishment of numerous community institutions in the city. As a result of their efforts, several politicians of ltalian descent were elected to municipal government. Addressing the 1960 to 1977 years, the second chapter investigates the ltalian-Canadian contribution to Quebec's labour movement and language debate. Provoking the unification of the collectivity's institutions, the linguistic conflict solidified the Italian-Canadian identity, while it, also, paradoxically, led to internaI dissent and political heterogeneity amongst community members. The focus of Chapter 3, ltalian-Canadian feminist activism illustrates another form of political schism, when' a group of young students came together in 1978 to found the Centra Donne Italiane. Disassociated from the collectivity's mainstream institutions, ltalian feminists formed their own community,equally as politicized. As this thesis concludes, though originating with the language debate of the1960s and 1970s, the political heterogeneity present amongst Italian immigrants only heightened with time. With their basic needs met and a reasonable level of integration attained, Italian-Canadians, could afford both literally and figuratively, to distance themselves from the established cominunity leadership.
http://www.collectionscanada.gc.ca/obj/thesescanada/vol2/QMU/TC-QMU-7689.pdf

The Gendered Working of Class in Postindustrial, Service Sector Capitalism: The Emergence and Evolution of the British Columbia Nurses Union, 1976-1992. - Roth, Mark Andreas (Simon Fraser University, 2009)
This thesis explores the emergence and initial evolution of the British Columbia Nurses Union from 1976 to 1992. The thesis argues that class and gender framed interrelated processes of organizational change, labour action, and political consciousness for British Columbia’s nurses. These changes took place in the context of a historical struggle between professionalism and trade unionism in nursing, and during a turbulent and transformative era for western capitalism and the role of the capitalist state in the 1970s and 1980s. This thesis argues that class, as a socioeconomic relationship and as lived experience, was the driving force behind organizational, economic, and political change in the nursing occupation. This central assertion stands in sharp contrast to claims that class has ceased to be of socioeconomic or political importance in postindustrial, capitalist society.

A Study of the English Teachers’ Association of British Columbia, 1959-2000 - Saltel, Lonny Darlene (Simon Fraser University, 2009)
This study traces the efforts of British Columbia teachers as they endeavour to have increasing input into the educational policies of the Department of Education. It is grounded in a study of primary archival records and written in the form of an historical narrative. Primarily, I focus on the English Teachers' Association in B.C.: I trace its growth as a professional organization and follow its increasingly strident attempts to address the growing professional interests of English/Language Arts teachers in response to government policies, especially those affecting curriculum. Three main interrelated themes permeate the study: the professionalization of B.C. English/Language Arts teachers, the growth in the political power of teacher associations in B.C., and the effects of the B.C. government's changing educational policies in English/Language Arts classrooms. My study follows the English teachers' association from its beginning in 1959 when it was known as S.A.T.E., the Secondary Association of Teachers of English; during the years of 1971-1994 when it was called B.C.E.T.A. , the British Columbia English Teachers' Association; to its later years as B.C.T.E.L.A., the British Columbia Teachers of Engli sh Language Arts. The study reveals that as the decades pass, the association becomes increasingly persistent in its efforts not only to further the professional interests of English teachers but al so to provide input to the government on curricular decisions affecting Engli sh/Language Arts classrooms. It al so becomes increasingly persistent in its dealings with the government as their philosophies of education become more diverse.

Organizing the Unorganized: The Service, Office, and Retail Workers' Union of Canada (SORWUC), 1972-1986 - Smith, Julia Maureen (Simon Fraser University, 2009)
This thesis examines the Service, Office, and Retail Workers' Union of Canada (SORWUC), an independent, grassroots, socialist feminist union that organized unorganized workers in Canada in the 1970s and 1980s. It looks at SORWUC's role in Canadian labour history in general, and its efforts to organize unorganized workers in particular, focusing on SORWUC's efforts to organize workers at a pub and a restaurant in British Columbia. The central thesis of this work is that SORWUC's socialist feminist unionism and commitment to organizing unorganized workers positioned the union as radically different from much of the 1970s Canadian labour movement, and that this difference both helped and hindered the union in its efforts to organize the unorganized. By examining SORWUC from this neglected perspective, this thesis ultimately aims to demonstrate SORWUC's importance to the historiography of class and labour organizing in Canada.
https://cha-shc.ca/prize-winner/julia-maureen-smith/
Keywords: British Columbia; Canada; Labour Organizing; Labour Unions; Service Industry; Service; Office; and Retail Workers’ Union of Canada (SORWUC); Socialist Feminism

For Liberty, Bread, and Love: Annie Buller, Beckie Buhay, and the Forging of Communist Militant Femininity in Canada, 1918-1939 - Toews, Anne Frances (Simon Fraser University, 2009)
During the interwar years, friends Annie Buller and Beckie Buhay established careers with the Communist Party of Canada and forged a uniquely Communist militant femininity that led to their eventual canonization by the Party as ideal comrades. Using a biographical approach to women’s working-class history, this thesis examines these women’s significant contributions to the CPC’s political project as gendered work. It also demonstrates that although their representation of themselves as comrades was organized around their understanding of themselves as workers, it was shaped too by particularities of ethnicity, gender, and other factors that were all subsumed in the Party’s egalitarian rhetoric. Additionally, in exploring how their lifelong friendship supported their construction of Communist militant femininity, and thus enabled their work, this thesis contributes to a developing historiography of friendship that focusses on its work rather than its nature, and that is inclusive of the friendships of working-class women.
Keywords: Friendship; Labour College; communist; comrade; militant; woman question

Depression on the Frontline: An Examination of the Impact of Working Conditions and Life Stressors on Sex Workers, Stylists and Servers - Vallance, Katherine Jane (Victoria, 2009)
Changes to the global economy over the past few decades along with growing support for neo-liberal policies in Canada have led to an increase in precarious, low-wage frontline service work. These kinds of occupations often involve sustained interaction with clients and have high job demands, low job control and insufficient monetary reward. Further, many of these jobs also tend to be gendered (i.e., they involve a large degree of ‘emotional’ labour or care work that is predominantly carried out by female workers). Working conditions such as these can have a negative impact on the mental health of frontline service workers leading to psychological distress and depression. Chronic stress or cumulative stressful life events can also increase vulnerability to depression. While these stressors can be exacerbated by poor working conditions, they can also exist independently of them. Comparative research across two or more frontline service occupations, similar in broad strokes but differing in workplace characteristics, is especially needed to understand how structural and contextual factors in the workplace and over the life course interact to produce depression. This thesis presents data from my supervisor (Dr. Cecilia Benoit) and colleagues’ 4-wave longitudinal study entitled “Interactive service workers’ occupational health and safety and access to health services” (Benoit, Jansson, Leadbeater & McCarthy, 2005). This is a study of three types of frontline service jobs – two in the formal economy (hairstyling and food and beverage service) and one in the shadow/informal economy (sex industry). Results of this secondary analysis demonstrate that not only do working conditions have a significant impact on the mental health of frontline service workers but that stressful life events also have very strong explanatory power in understanding why certain workers experience depression more than others. The findings indicate that sex workers have the highest levels of depression, in comparison to stylists and servers. Yet sex workers report protective factors in their jobs, including higher comparative decision latitude, that contradict much of the current literature on sex work. The thesis concludes with policy recommendations and gives direction for further research in the area of frontline service work and depression.

Stories of Unionization: Four Teachers' Perspectives on Collective Bargaining in Two Canadian Private ESL Schools - Breshears, Sherry Diane (Simon Fraser University, 2008)
The private English language training industry in Canada has grown rapidly in recent years. While subject to influences of market competition, ESL schools have had little educational or labour regulation. This study presents life history interviews with four teachers who became involved in forming unions at their workplaces because of their experiences with just labour practices. The findings show that teachers sought union protection to deal with a pervasive sense of insecurity in their jobs. Through unions, they established clearer processes for dealing with such issues as the allocation of work and the resolution of grievances, a forum for communicating concerns to management, and a peer support structure. Additionally, these teachers have gained significant increases in salary and benefits. These narratives also show teachers, both individually and collectively, engaging in resistance as they confront the daily infringement of business priorities on their capacities to develop and practice as educators.

Watching Workers: A Critical Review of the Law Regarding Electronic Employee Monitoring in Non-Unionized Workplaces in Canada - Bueckert, Melanie R. (University of Manitoba, 2008)
This thesis addresses the topic of electronic employee monitoring in non-unionized workplaces in Canada. Electronic employee monitoring is defined as including (1) the use of electronic devices to review and evaluate employees’ performance; (2) ‘electronic surveillance’; and (3) employers’ use of computer forensics. Detailed consideration is given to a variety of technologies, including computer, internet and e-mail monitoring, location awareness technologies (such as global positioning systems and radio frequency identification), as well as biometrics, and the developing case law surrounding these innovations. Analogies are drawn to the jurisprudence developing with respect to unionized workplaces and under statutory unjust dismissal regimes. This analysis leads to the conclusion that legislative reform is necessary, either through(1) the creation of parallel private sector privacy regimes, such as those in British Columbia and Alberta, mirroring existing federal legislation; (2) amendments to existing employment standards legislation; or (3) the enactment of a stand-alone surveillance statute.

Commissioning Consent: An Investigation of the Royal Commission on the Relations of Labour and Capital, 1886-1889 - Cole, Stephen J. (Queen's University, 2008)
The 1880s were turbulent years in the Dominion. Under the auspices of the National Policy, Canada was in the midst of a social and political ‘transformation.’ The social and cultural aspects of this transformation became a source of public debate as the ‘Labour Question’ and the relations between labour and capital reached a high mark of political and economic significance. Waves of strikes and the emergence of large international labour organizations challenged many liberal Victorian ideas about a strictly limited state. Many looked upon the federal government as responsible not only for economic growth, but also for protection from the more pressing problems of industrial life. The Royal Commission on the Relations of Capital and Labour is a testament to not only the turbulent economic relations in late-Victorian Canada, but the emergence of the Canadian state’s active role in social relations. Its very title envisioned a dual role for the Canadian state: to “promote the material, social, intellectual and moral prosperity” of labouring men and women, and to improve and develop “the productive industries of the Dominion so as to advance and improve the trade and commerce of Canada.” However, this thesis argues that the Labour Commission was more subtly designed to enhance the prestige of the Canadian state and install Ottawa as an authority on, and mediator of, industrial relations in Canada. Attention to the formation, activities, and impact of the Labour Commission suggests that, rather than an exercise in addressing a mounting social polarization between “labour” and “capital,” the Commission lends insight into the emergence of a Canadian middle class. It was a carefully-constructed exercise in the assertion of middle-class cultural hegemony whereby such values and understandings as respectability, morality, manliness, worth and expertise were naturalized. In the process, the tension between labour and capital was diminished and in its place were developed visions of social reciprocity and mutual interest. It is in this way that the Labour Commission was an exercise in ‘commissioning consent:’ it placed oppositional voices and wrenching exposés about industrial life in a framework that worked to quell rather than stimulate far-reaching critiques of the established order. The Commission’s formation, methodology and language functioned like an industrial exhibition rather than a pointed social investigation. The evidence presents a thriving economy that had grown exponentially under a wise and paternal government. It also presented a vision of the Dominion whereby the disturbances that occurred between labour and capital could be handled within a conventional language of liberal politics. In addition, social and intellectual elites were fully ensconced in the formation and legitimization of these social and moral understandings. Because it was up to the state to select who would speak for labour and capital, the Commission’s message was not one of class polarization. Thus, exploring who became ‘labour’ and who ‘capital,’ and what sorts of things they said to each other, sheds light on to the emergent strategies of the Canadian state as it sought to understand and influence civil society. The Commission is an indication, even anticipation, of a more activist and energetic state.

Precariousness on the Menu: Restaurant Work and Labour Mobility Within the Low-Wage Service Industry in Kingston, Ontario - Denstedt, Mark James (Queen's University, 2008)
Precarious employment refers to forms of work characterized by limited job security, few employment benefits, lack of control over the labour process and low-wages. Restaurant work demonstrates a range of precarious forms of employment and reveals the complexity of issues that such jobs raise in the context of the regulation of the local labour market. This thesis analyses the nature of precarious employment in the restaurant industry in Kingston, Ontario. In particular, it seeks to understand how precarious employment is shaped by the structure and dynamics of the local labour market. The research highlights the role played by labour mobility, in shaping workers’ experiences of precarious work. Labour mobility refers to the movement of workers between different jobs and between different worksites within a structured local labour market as they seek to better their economic situation and generate a sustainable income for themselves. Through a discussion of labour mobility, this thesis seeks to contribute to a new lens through which the impacts of a precarious and flexible labour market can be better understood as they shape the lives of workers themselves. The objective of this study is to better understand the factors which shape the lived realities of precarious restaurant workers in one specific local labour market. The empirical analysis draws on data collected by Statistics Canada and interviews conducted with both employers and employees in local restaurants to analyze the structure of the local labour market and the nature of precarious employment. The research demonstrates that the restaurant industry in Kingston is comprised of three distinct submarkets, each of which appears to operate largely independently of one another. Interviews were conducted with employees and employers in the submarket located in downtown Kingston. Within this submarket the combined processes of labour market segmentation and labour mobility has a significant impact on workers experiences of precarious employment. By understanding the complex interaction of these two features within the labour market, we can begin to conceive of ways to address the issues associated with the precariously employed in the low-wage service industry.

A Crisis of Social Democracy: Organized Labour and the NDP in an Era of Neoliberalism - Fowler, Tim (Brock University, 2008)
The NDP was founded out of the ashes of the Co-Operative Commonwealth Federation to cooperate with the Canadian Labour Congress to become the 'political arm of organized labour' in Canada. The NDP has long claimed they are the party which represents the policy goals of organized labour in Canada: that the NDP alone will fight for trade union rights, and will fight for Canadian workers. Divergent Paths is an examination of the links between the labour movement and the NDP in an era ofneo-liberalism. Provincial NDP governments have become increasingly neoliberal in their ideological orientation, and have often proved to be no friend to the labour movement when they hold office. The Federal party has never held power, nor have they ever formed the Official Opposition. This thesis charts the progress of the federal NDP as they become more neoliberal from 1988 to 2006, and shows how this trend effects the links between the NDP and labour. Divergent Paths studies each federal election from 1988 to 2006, looking at the interactions between Labour and the NDP during these elections. Elections provide critical junctions to study discourse - party platforms, speeches, and other official documents can be used to examine discourse. Extensive newspaper searches were used to follow campaign events and policy speeches. Studying the party's discourse can be used to determine the ideological orientation of the party itself: the fact that the party's discourse has become neoliberal is a sure sign that the party itself is neoliberal. The NDP continues to drive towards the centre of the political spectrum in an attempt to gain multi-class support. The NDP seems more interested in gaining seats at any cost, rather then promoting the agenda of Labour. As the party attempts to open up to more multi-class support, Labour becomes increasingly marginalised in the party. A rift which arguably started well before the 1988 election was exacerbated during that election; labour encouraged the NDP to campaign solely on the issue of Free Trade, and the NDP did not. The 1993 election saw the rift between the two grow even further as the Federal NDP suffered major blowbacks from the actions of the Ontario NDP. The 1997 and 2000 elections saw the NDP make a deliberate move to the centre of the political spectrum which increasingly marginalised labour. In the 2004 election, Jack Layton made no attempt to move the party back to the left; and in 2006 the link between labour and the NDP was perhaps irreparably damaged when the CAW endorsed the Liberal party in a strategic voting strategy, and the CLC did not endorse the NDP. The NDP is no longer a reliable ally of organized labour. The Canadian labour movement must decide whether the NDP can be 'salvaged' or if the labour movement should end their alliance with the NDP and engage in a new political project.
Keywords: Social sciences

Racialized Immigrants In Canada’s Changing Labour Market: An Investigation Of The Effects Of Precarious Work On Black Caribbean Women - Hibbert, Maqueita (Ryerson University, 2008)
This research undertakes an examination of the employment opportunities and experiences of black Caribbean women in Canada, particularly within the context of the growing trend towards precarious jobs—casual, part-time and low paying—in the restructured Canadian labour market. The specific purview of this study is the labour history and employment experience of a representative group of black Caribbean women who work as Personal Support Workers in nursing homes across the Greater Toronto Area. A main concern of the study is to understand the ways in which precarious work affects these women’s settlement and integration experiences, particularly their ability to gain economic independence; this, in turn, affects a number of variables related to their, and others, perception regarding their status and place in Canada. By focusing on the case of Personal Support Workers, the study aims to shed light not only on the employment experiences of black Caribbean women in this sector but also to examine more closely the policies and employment practices that create labour market “niches” or labour “segregation” along racial and gender lines.

The Homeless and Reformers: Negotiating Progress in the Upper Streets of Halifax, 1890–1914 - Hood, David (Carleton University, 2008)
The extremely poor have often been cast as deviants or others, in both the past and the present. Historians of Atlantic Canada have used the idea of deviance as an acceptable approach to the poor and homeless of the past and tacitly encourage us to see the contemporary homeless as deviants. Victorian theorists such as Malthus and Mayhew pejoratively characterized the poor as an underclass. Contemporary writers have provided evidence that challenges the use of the concept in Canada. But it remains a powerful force within American sociology, which is able to cast its influence over Canadian historical writing. It is the contention of this research that it is possible to be true to the past, to reflect the warts and downfalls of the extremely poor and homeless who lived there, but at the same time recognize their efforts to follow prevailing norms and to empathize with their plight and in doing so generate at least the possibility of recognition and empathy in the present. Such recognition and empathy may be the keys to creating and maintaining humane solutions to poverty and homelessness. The examinations conducted by this research address an area of our past that has been largely overlooked. This research supplements broad historical surveys of social welfare legislation by examining social welfare policy in action at the local level. By positioning itself at the convergence of labour history and studies of poverty, and by demonstrating that the populations examined by these discrete areas of research are more alike than different, this research shows that labour history can be extended to include many of those who lived "rough" in the past. Through its approach this research hopes to encourage a view that can help to integrate the study of extreme poverty and homelessness into the mainstream of Canadian historiography.
Keywords: Halifax; Homeless; Nova Scotia; Progress; Reformers; Social sciences

When Red Meets Green: Perceptions of Environmental Change in the B.C. Communist Left, 1937-1978 - Martin, Eryk (University of Victoria, 2008)
From the 1940s to the 1970s the communist left in British Columbia used debates and perceptions of environmental change as a means to engage in a critique of capitalist society. In engaging in these debates, communists articulated a Marxist understanding of the connections between capitalism and environmental change. However, these articulations were heavily connected to broader occurrences that situated the communist left alongside a diverse group of social actors. Beginning in the 1940s the communist left situated their critique of provincial forest policy into a wider social debate over the management of forest resources. During the 1950s and 1960s, concerns over environmental change were transformed into debates over the effects of nuclear weapons and industrial pollution. From the late 1960s through to late 1970s elements of the communist left once again engaged with the environmental changes taking place in the forest sector, as renewed concerns developed over the status of the forest economy and the preservation of wilderness areas. To investigate the communist left’s perceptions and politicization of these issues this thesis focuses on the activities of communist controlled unions such as the International Woodworkers of America as well as the B.C. section of the Communist Party of Canada/Labour Progressive Party. In addition to these organizations, this thesis also follows the experiences of Erni Knott. As a woodworker, a founding member of the IWA, a member of the Communist Party, and an active environmentalist, Knott’s experiences highlight the complex way in which communist politics merged and conflicted with perceptions of environmental change.

Rural Businesses on Vancouver Island: Challenges and Opportunities - Siemens, Lynne Marie (University of Hertfordshire, 2008)
Many rural areas are undergoing structural changes as jobs in forestry, fishing, mining, agricultural and other natural resource-based industries decline. These communities, often based around these industries, are generally small and located some distance from urban areas. They are faced with decreasing population as residents and their families leave for jobs elsewhere. As a result, the communities and residents are looking for alternative ways to create employment and sustain themselves. Given the nature of these rural locations, many small businesses based there face challenges that are not generally experienced by enterprises in urban areas. Some communities are not accessible by paved road while others are not accessible by road at all, relying instead on water and air transportation. The business people in these areas often operate without standard business infrastructure, which can include telephone lines, broadband Internet, banking services and other items, and can have difficulty accessing supplies, customers, employees and other required materials. However, there has been relatively little research on the challenges facing rural businesses and the specific methods by which these owners mitigate these challenges. Understanding and addressing the challenges faced by these businesses becomes important in order to support and encourage economic growth and development in these rural communities. Building on this context, this research looks to answer the following questions: • Why do people start businesses in rural locations? • What type of businesses do they start? • What challenges do these rural businesses face? • How do owners respond to these challenges? Vancouver Island and the surrounding smaller islands in British Columbia, Canada serve as the research site. Given the exploratory nature of this research, an inductive approach has been selected with the use of case studies, interviews and grounded theory analysis. Purposeful sampling is used with the sample businesses meeting specific criteria, based on location, business size and definition of success. These businesses are interviewed at their locations to allow the researcher to experience the challenges associated with accessing the particular rural community. The interview topics are focused on the above research questions. There are several common characteristics among the sample owners and their businesses. The owners tend to be in-migrants who moved to the rural area for lifestyle reasons. They have started their business to provide an income, take advantage of a business opportunity, or both. Family members, particularly spouses, are actively involved in the business. In many cases, participants supplement their business income with other income sources to ensure business viability. Success is measured generally by personal and lifestyle goals, rather than financial criteria. The businesses face common challenges in terms of a limited local population base which impacts on market size and labour pool, rural location and access to urban centres, gaps in business and social services infrastructure and heavy time demands. The owners respond to these challenges in a variety of ways which includes the involvement of family, core business diversification, alternative income sources, long hours invested in the business and involvement with the community. To meet these challenges and devise their responses, the owners draw upon four key resources – their own skills and attitudes, their family, business and community. The resulting conceptual framework draws together these key resources and suggests that all four must be present to ensure success within a rural context. Each resource is comprised of several components which contribute to business success. The framework also integrates several resource-based theories, which consider the key resources either separately or in pairs, to create a holistic model. The conclusions focus on several key areas. This research contributes to the knowledge base on rural small businesses by creating a framework that draws directly from the experience of these owners and their objectives and motivations for their businesses. It reflects their internal focus and a concentration of the four resources that they access easily from within their domain. This research also suggests some possible roles for government which focus on its role in shaping the larger environment, particularly at the infrastructure level and human capital development. Finally, future research directions are recommended. This study considers a relatively unexplored topic and suggests ways for rural small businesses to address the challenges which they face. With this knowledge, individuals, businesses, communities and other interested organizations can work to achieve their economic development goals.

Les travailleurs miniers de l'Abitibi-Témiscamingue : la main-d'oeuvre de la mine Lamaque, 1948-1985 - Simard, David (Université de Montréal, 2008)
Ce mémoire porte sur les travailleurs de la mine Lamaque entre 1948 et 1985. À partir d’une étude approfondie des fichiers d’employés de l’entreprise, qui est l’une des plus riches mines d’or de l’histoire du Québec, nous analysons l’évolution de la main- d’œuvre sous les volets de la composition ethnique, de l’expérience dans le secteur minier ainsi que de la mobilité. Notre enquête révèle l’existence de deux périodes-clés autour desquelles on assiste à une transformation rapide de la main-d’œuvre: la période 1948-1960 est le théâtre d’un important processus d’homogénéisation des effectifs alors que les années 1967-1977 sont la scène d’un double processus de sédentarisation et de qualification de la main-d’œuvre. D’un groupe de travailleurs cosmopolites, peu expérimentés et très mobiles, il en ressort, au sortir de ces années, une main-d’œuvre nettement plus expérimentée, plus sédentaire et composée presque exclusivement de travailleurs canadien-français et, de surcroît, témiscabitibiens. Au-delà de ces transformations, notre mémoire comporte un bref aperçu de l’histoire de l’industrie aurifère québécoise et de la mine Lamaque, du « boom minier » des années 1930 à la grande relance de l’industrie au début des années 1980. De plus, nous portons une attention particulière aux travailleurs d’origine européenne qui forment, jusqu’à la fin des années 1960, une proportion appréciable de la main-d’œuvre. En plus de lever le voile sur la composition de ce groupe de travailleurs, notre étude révèle des similitudes insoupçonnées entre le contingent européen et canadien-français.
https://doi.org/1866/7681

Co-Opting Precariousness: Can Worker Cooperatives Be Alternatives to Precarious Employment for Marginalized Populations? A Case Study of Immigrant and Refugee Worker Cooperatives in Canada - Wilson, Amanda (McMaster University, 2008)
This thesis is an exploration into the potential for worker cooperatives to be conceptualized and experienced as an alternative to precarious employment for immigrants and refugees. It argues that current analysis and responses to precarious employment fail to fully address the root causes of precarious employment and fail to suggest what forms of alternative employment relations we should be striving to build. It is argued that by tracing the roots of precarious employment to the organization of work, the worker cooperative model can be seen as a potential solution to these root problems. This hypothesis is explored through two case studies of immigrant worker cooperatives, analyzing the employment experiences of several of its members. It concludes that workers cooperatives appear to provide alternatives in the areas of control, security and social capital and empowerment. However, more work is needed to support and facilitate the development and sustainability of cooperatives in order to improve in the areas of wages and formal benefits. Despite the challenges of worker cooperatives, the author argues that they remain an important tool, invoking a politics of the act that seeks to build alternative spaces of employment without relying on government or employers.

Workability of Intergovernmental Administrative Relations: A Comparison of Labour Market Policy in Post-Devolution Canada and the United Kingdom - Wood, Donna (University of Edinburgh, 2008)
This is a comparative study of intergovernmental relations in labour market policy in Canada and the United Kingdom (UK) between 1996 and 2006, the first phase of devolution in each country. The study focuses primarily on relations between the central government and a single sub-state in each country (Alberta in Canada and Scotland in the UK) and addresses three research questions: 1) to what extent were there differences in intergovernmental relations between the countries?2) what accounted for these differences? 3) what impact did these differences have on the character and workability of the intergovernmental relations system in each country? Workability was assessed based upon the degree to which trust ties developed between senior officials. The analysis concludes that the structure of the state, the structure of the policy domain, and the presence of two important accommodation mechanisms in the UK not found in Canada (the party system and the civil service) made intergovernmental relations in labour market policy in the two countries fundamentally different. In Canada, intergovernmental relations were multilateral, interprovincial and bilateral, whereas in the United Kingdom they were only bilateral. Despite devolution, the UK Government retained control of most policy levers, whereas in Canada devolution has limited federal control and influence and any notion of a national labour market system. Trust ties were enhanced by consistency between the key players, routinized engagement, reliability, honesty, respect, capacity and willingness to engage, and transparency. Although shared objectives made engagement easier, they were not a prerequisite for a positive relationship. Bilateral relationships that took place within the geographic boundaries of Alberta and Scotland were considered as positive and highly workable. Difficulties arose when relationships became multilateral or bilateral relations were managed at a distance. Despite devolution, multilateral relations in the historically conflicted labour market policy domain in Canada remained competitive, with a low degree of workability. Relationships with respect to disability and immigration issues were more positive. In the UK relationships in the welfare to work policy area were cooperative and highly workable. Relationships in skills and immigration did not fare as positively.

Skilled Trades' Work and Apprentice Training in the Manufacturing Industry with a Primary Focus on the Millwright Trade: An Inter-Generational Study - Wren, John Charles (University of Toronto, Ontario Institute for Studies in Education, 2008)
Technology has enabled management to utilize automation in the methods of production, and as such promoted a reduction in the use of traditional skills for traditional skilled trades' workers while narrower task specific apprenticeship training programmes promote the loss of trade knowledge traditionally passed from a trades' person to an apprentice in the manufacturing industry. The purpose of this intergenerational study is to trace the changing skill requirements affected by developing technologies in the manufacturing process focusing on the traditional skills of millwright trade, and associated skilled trades. To place in context the origins of the skilled trades' I have included brief histories of five skilled trades, to represent a selection of skilled trades' often closely connected through their work in the manufacturing industry; the millwright, electrician, welder, toolmaker and machinist. In an effort to also report the possible effects of technology on skilled trade labour from a tradesperson's perspective I have utilised my own experiences and incorporated anecdotal evidence from interviews with certified millwrights and apprentices that are either presently working in the trade, or have retired from the trade in Canada. Interviews with three generations of millwrights assisted in making comparisons of training and expectations of millwright work, together with changes in the control millwrights' exercise over the jobs they perform. The focus of the thesis is the possible effects of technological progress on the required skill sets of three generations skilled trades' with a primary focus on millwright skilled trades'. Restructuring and the utilization of new technologies has facilitated a reduction in the overall number of skilled trades' workers that were previously required when traditional skilled trades' personnel were utilised. Therefore, utilization of technology to lower production costs by modern industry is affecting social structure, in that, traditional opportunities for members of the working class, without the benefit of a university education, are restricted in their ability to obtain well paid jobs as skilled trades' personnel in the manufacturing industry. Thesis: Technology has enabled automation to be utilized by management in the methods of production, and as such promoted a reduction in discretion and control in the use of traditional skills for traditional skilled trades' workers while narrower task specific apprenticeship training programmes promote the loss of trade knowledge traditionally passed from a trades' person to an apprentice in the manufacturing industry.
Keywords: Apprentice training; Education; Manufacturing; Millwright; Skilled trades

La perception de la fête internationale des travailleurs dans les journaux canadiens entre 1906 et 1945 - Zombecki, François (Université du Québec à Montréal, 2008)
Le 1er mai 1906, les membres d'un éphémère parti socialiste canadien organisent à Montréal la première célébration de la fête internationale des travailleurs. Des centaines de personnes y défilent sous le drapeau rouge. L'événement se répète ensuite presque chaque année, et s'étend à la plupart des grandes villes du pays. L'histoire du mouvement socialiste / communiste au Canada et au Québec a certes été écrite, mais l'historiographie délaisse le sujet de sa fête annuelle. Pourtant, les journaux canadiens ont couvert l'événement, année après année, léguant aux générations suivantes une riche couverture. Celle-ci représente un outil utile, bien qu'imparfait, pour mieux saisir l'opinion de la population de l'époque à l'endroit des communistes. La présente recherche analyse plus de 400 articles de grands quotidiens pour sonder la perception des Canadiens, durant la première moitié du XXe siècle, quant au phénomène de la fête du 1er mai et au mouvement socialiste / communiste qui l'anime. Dans un premier temps, nos recherches présentent la couverture des journaux de plusieurs grandes villes canadiennes. Nous constatons alors d'importantes différences entre la perception des Canadiens français et celle des Canadiens anglais au Québec. Nous découvrons également une affinité particulière à Winnipeg -et même à Vancouver, dans une moindre mesure -pour le mouvement et sa fête. Le facteur ethnique explique en bonne partie tant les affinités de certaines communautés pour le mouvement, que la répulsion des Canadiens français. Dans un deuxième temps, à travers une approche chronologique plutôt que régionale, des facteurs conjoncturels et internationaux expliquent les fluctuations dans le ton des journaux entre 1906 et 1945. Ce travail de recherche jette la lumière sur une fête particulière, exclue du calendrier officiel nord américain et pourtant observée à travers la majeure partie du monde occidental. L'analyse de la couverture journalistique de l'événement permet de tirer d'intéressantes conclusions quant à la façon dont a été perçu le mouvement communiste canadien, au moment de son apogée.

A Proletarian Prometheus: Socialism, Ethnicity, and Revolution at the Lakehead, 1900-1935 - Beaulieu, Michel S. (Queen's University, 2007)
[Analyzes] various socialist organizations operating at the Canadian Lakehead (comprised of the twin cities of Port Arthur and Fort William, Ontario, now the present-day City of Thunder Bay, and their vicinity) during the first 35 years of the twentieth century. It contends that the circumstances and actions of Lakehead labour, especially those related to ideology, ethnicity, and personality, worked simultaneously to empower and to fetter workers in their struggles against the shackles of capitalism. The twentieth-century Lakehead never lacked for a population of enthusiastic, energetic and talented left-wingers. Yet, throughout this period the movement never truly solidified and took hold. Socialist organizations, organizers and organs came and went, leaving behind them an enduring legacy, yet paradoxically the sum of their efforts was cumulatively less than the immense sacrifices and energies they had poured into them. Between 1900 and 1935, the region's working-class politics was shaped by the interaction of ideas drawn from the much larger North Atlantic socialist world with the particularities of Lakehead society and culture. International frameworks of analysis and activism were of necessity reshaped and revised in a local context in which ethnic divisions complicated and even undermined the class identities upon which so many radical dreams and ambitions rested.
https://qspace.library.queensu.ca/bitstream/1974/1715/1/Beaulieu_Michel_S_200712_PhD.pdf
Keywords: 1900-1935; Canada; Communist Party of Canada; Ethnicity; Finns in Canada; Fort William; Ontario; Industrial Workers of the World; Labour history; Lakehead; Northwestern Ontario; One Big Union; Port Arthur; Ontario; Radicalism; Revolution; Social Democratic Party of Canada; Socialism; Socialist Party of Canada; Winnipeg general strike

La domesticité dans la colonie laurentienne au XVIIe siècle et au début du XVIIIe siècle (1640-1710) - Bessière, Arnaud (Université du Québec à Montréal et Université Paris IV - Sorbonne, 2007)
Cette thèse porte sur les domestiques au Canada entre 1640 et 1710. Recrutée en France ou dans la colonie, cette main-d'oeuvre, principalement masculine, est au service des paysans propriétaires et des communautés religieuses. Ses fonctions sont donc surtout liées à l'agriculture : défrichements, culture des terres, soin du bétail. Mais cela n'exclut pas des tâches comme le soin des malades et l'entretien ménager pour les communautés religieuses et les employeurs urbains plus fortunés. Au fil des ans, la composition du groupe se modifie : les domestiques sont de plus en plus d'origine canadienne et de plus en plus jeunes. Cette évolution est certes à rapprocher de la baisse du mouvement migratoire vers la colonie qui était en grande partie formé de domestiques. En plus d'analyser les modalités d'embauché, la thèse aborde la question des relations entre les maîtres et les domestiques et tente de cerner le devenir social du groupe dans la colonie.
https://cha-shc.ca/prize-winner/arnaud-bessiere/
Keywords: Canada; Domesticité; Domestique; Employeur; Engagé; Immigration; Main-d'œuvre; Maître; Nouvelle-France; Salaire; Servante; Serviteur; XVIIe siècle.

British Juvenile Immigrants in Canada 1868 to 1939: A Study of the Relationship Between Societal Changes and the Treatment of Home Children - Coombes, Brianna Leigh (Ryerson University, 2007)
This paper examines the history of the British juvenile immigrants, a group of over 100,000 children who arrived in Canada between 1868 and 1939 to work on farms or as domestic workers. There was both a pressing need within Canada for farm workers, and overcrowding in British cities, therefore conditions were right for a mutually beneficial labour exchange between the two nations. British philanthropists encouraged this movement and ensured its continued success over a seventy year period. The societal changes that occurred in Canada during the same period as a result of the reform movement are also traced within this historical examination. The increase in child welfare policies, and the subsequent attitudinal changes in the Canadian public also impacted how the home children were treated and viewed. Through this research, this neglected group of immigrants will be given a more prominent position in Canadian social and immigration history.

Chameleons, Chimeras and Shape-Shifters: The Production of Neoliberal Government in Ontario - Coulter, Kendra (University of Toronto, 2007)
Drawing on data from a sixteen-month ethnography of Queen’s Park, the provincial legislature of Ontario, this study analyses and critiques the evolving production of neoliberal government. The work of real social actors, primarily political workers and politicians, and their active ideological and material creation of government, is central to my focus on the neoliberal project of the Liberal government in Ontario. After charting the historical trajectory of neoliberalism internationally and in Canada, with a particular emphasis on the Third Way approach, Icentre on thedevelopment of neoliberal political culture and restructuring in Ontario. Then I provide an in-depth analysis of the production of the Liberal government, focusing on social and fiscal policies and policy-making, hegemonic gender and class politics, and political communications and spin. I conclude that, at one level, the Liberal chimera fused certain progressive practices and language with neoliberal policies and rhetoric. At the same time, significant and dangerous initiatives that interlocked the public and for-profit sector conceptually and materially were pursued. Thus, a more camouflaged form of deep neoliberal integration was produced.
OCLC: 664421107
Keywords: Academic Dissertation; Academic theses; Thèses et écrits académiques

Labour Goes to War: The CIO, the People's War, and the Construction of a "New Social Order," Toronto, 1939-1945 - Cuthbertson, Wendy Elizabeth (University of Toronto, 2007)
The CIO related this narrative to working-class Canadians through new, union channels of communication and through a myriad of union-minded social interactions. Together - the CIO's narrative of victory and its subaltern public sphere that communicated this narrative - helped the CIO overcome formidable obstacles to organizing. The Canadian CIO's 1930s momentum had stalled by 1939, but by 1944 it was the country's largest labour organization and was influencing Canadian politics. Using union newspapers, organizing literature, minutes, correspondence, oral interviews, government and corporate records, and the daily press, this dissertation describes and analyzes how the CIO organized thousands of wartime workers into unions in spite of significant obstacles. This study then examines the institutions the CIO developed to create a union "mini-public sphere," where workers debated and developed union positions on issues facing them as workers, family members, citizens and military veterans. The CIO was successful in turning private, workplace issues such as union recognition and bargaining rights into public issues that government was forced to deal with, and its organizing successes and its entry into politics witnessed burgeoning support for the social democratic CCF, a phenomenon that encouraged mainstream political parties to adopt more progressive platforms. The CIO's breakthrough was based not just on worker-empowering wartime labour shortages. Its skill in using modern communications was also a factor in its wartime success, as well as its use of the war as a central character in these communications efforts. CIO communications used a narrative that elided workers with warriors as partners in a "people's war" to defeat the nation's enemies and build a new social order. The CIO told workers that if they organized into unions, they would have the power to shape a peace that, unlike after the Great War, would benefit this worker-warrior partnership. Victory was thus defined not merely as defeating the Axis but creating a modern, new Canada, where workers would have citizenship rights in the workplace and where citizenship entailed a fairer, more egalitarian society. The CIO's talk about rights extended to women workers, and its arguments for equal pay and women's seniority were increasingly based on women's human rights.

The Split in the AFL-CIO: Implications for the Canadian Labour Movement - Declerck, Sarah (McMaster University, 2007)
In July 2005, six unions withdrew from the central labour federation in the United States, the AFL-CIO. In September 2005, joined by a seventh union, the disaffiliated unions formed a rival labour federation called Change to Win (CTW). On the surface according to Stem, leader of the CTW coalition, what divides the two sides of the split is a disagreement over whether or not to place greater emphasis on organizing new members or altering the political climate in the US in order to facilitate orgamzmg. This thesis explores some of the earlier debates within the union renewal literature in the US and in Canada and exposes many ofthe similarities between the 1995 "New Voices" leadership ofthe AFL-CIO and the CTW leadership. Through a description and analysis of the events that led to the split in the AFL-CIO, the limitations ofthe debates that led to the split are revealed and the strategies for union renewal advanced by the proponents of CTW are critiqued. Drawing on interviews with elected leaders and staff from some of the Canadian sections of the CTW unions, one of the largest Canadian unions, the Ontario Federation of Labour and the Canadian Labour Congress, this thesis examines some of the implications of the split in the AFL-CIO on the Canadian labour movement. As trade unionists in Canada consider different approaches to union renewal, one option is to embrace an approach similar to the CTW approach: greater cooperation with employers and a more "efficient" business unionism. Another approach is union renewal with a socialist character; developing working-class capacities to construct socialist alternatives and renew the labour movement as an instrument of working-class struggle.

Les accidents mortels en milieux de travail dans le district judiciaire de Montréal de 1890 à 1930 : recension et analyse à partir des rapports d'enquête des coroners - Dionne, Jean-Claude (Université de Montréal, 2007)
L’objet de ce mémoire est la recension et l’analyse des accidents mortels survenus dans les milieux de travail du district judiciaire de Montréal durant la période de 1893 à 1930. À partir des témoignages contenus dans les rapports d’enquête des coroners, nous analyserons les opinions des travailleurs, des contremaîtres, des coroners et des inspecteurs afin de connaître leur point de vue sur les accidents et de vérifier dans quelle mesure ils partagent les valeurs libérales de cette époque. Pour constituer notre corpus d’information, nous avons dépouillé chacun des 1527 dossiers des rapports d’enquête des coroners effectuée entre le premier janvier 1893 et le 31 décembre 1930. Ils constituent notre principale source à partir de laquelle nous établirons l’ampleur des accidents mortels et également analyserons les témoignages recueillis par les coroners, Pour fin d’analyse, nous avons réparti ces données sous les quatre décennies couvertes par notre étude et élaboré des tableaux statistiques établissant la distribution annuelle et décennale de ces accidents de même que l’âge et le sexe des victimes. Nous avons également distribué ces accidents par secteurs d’activités économiques et par catégories d’accidents. Si les employeurs, les contremaîtres et les inspecteurs des manufactures adhèrent aux principes de l’idéologie libérale de l’époque en attribuant aux travailleurs la responsabilité première des accidents de travail, les coroners et les travailleurs considèrent, par contre, dans une forte proportion (72 %) que les causes de ces accidents sont associés à des défaillances des divers éléments des lieux de travail et aux processus de production. Ils sont donc plus enclins à attribuer la responsabilité aux employeurs.
https://doi.org/1866/17912

[e]motions, Moments, and Transnational Connections: The Lived Experiences of Two Labour Migrants in Canada's Seasonal Agricultural Workers' Program - Ferguson, Nelson (Concordia University, 2007)
Labour migrants have been routinely categorised within social scientific thought as either abstracted economic entities or as victims of global processes beyond their understanding. A striking majority of attempts to understand processes of migration, especially in regards to "unskilled" Mexican migrant workers, have been informed primarily by macro-level economic approaches, while the social and individual factors at play have been largely pushed to the side. As such, the social lives and individual diversities of these migrants have received meagre academic attention. In acknowledgment of this gap, this current thesis focuses on the lived experiences of Hector-Alberto and Durango, two individuals engaged in a cycle of migration as participants in Canada's managed migration program, the Seasonal Agricultural Workers' Program. Through an ethnographic description of the everyday experiences of Hector and Durango, three relevant themes are explored: their individual relations to their work, their family, and their co-workers. As such, the present work aims to explore the varied experiences of migration and frame labour migrants as significant social actors rather than abstracted units or victims of social forces. The author encourages an engagement in a broader investigation of the "migrant experience"; to look beyond the idea of transnational migration as simply physical movements across national boundaries, but rather as groupings of processes with profound and diverse meanings to those involved. Perhaps such a perspective would play a role in revealing the complex myriad of interacting processes which combine under the umbrella term of "migration".
Keywords: Social sciences

The Working Class After the Vanguard: Process and Plurality in the Theory and Practice of Working Class Organization - Green, Brian Stephen (University of British Columbia, 2007)
This thesis examines what the two sides of class– capital and working class –have meant in left parlance, what these meanings imply about class struggle, and how they were put into political practice through Communist Parties and trade unions. Ideas about class and strategies for class struggle continue to be central to the left, as the various ways these are conceptualized give rise to very different answers to some common and persistent questions: Who is legitimately a worker and when? Why, how and with what result are certain struggles delayed or subsumed within others? At what point does self-criticism cross over to counter-revolutionary dissent? And what might continuing schisms over these questions tell us about traditional left organizations? The thesis traces the development of 'the left' from its key conceptual subject, the working class, through its two most widely-adopted organizational strategies in order to examine the poverty of the left's analytical and political traditions, particularly as regards (1) the notion of socialism as an alternative management plan and (2) ideas about capital and working class that stressed the embodiments of power relations rather than those relations themselves, and which were lifted directly from capital's own definitions of productivity. Finally, the thesis argues that insights from long-neglected Marxisms, certain critical post-structuralisms and the political strategies of some emergent anti-capitalist networks together offer the opportunity to produce a more fluid, and more liberatory left, imbued with: (1) an understanding of class as a relationship that does not inhere to individuals or organizations, and (2) a notion of the working class as a permanent resistance that has nothing whatever to do with a particular ideology or strategy; with (3) an analysis which emphasizes situational relationships of power that are at once racialized, gendered, sexualized, and classed; and (4) a political approach which draws means and ends together in an emphasis on resistance as the troubling of order, and revolution as a process of refusal.

"The Both of Us Have Battled": The Practices and Politics of Female Partners in the Canadian Seasonal Agricultural Workers Program - Hanson, Christina (Simon Fraser University, 2007)
Through an analysis of qualitative, ethnographic data, I locate the narratives of nine Mexican women married to migrants within the context of capitalist globalization, state policies, and local gender ideologies. In doing so, advocate for a theoretical approach to migration which combines elements of structural theories of migration and network theoretical approaches. These women's narratives position them at the juncture of capitalism and other social relations, and show them to be active agents in migration. Not only is their labour critical to the maintenance of migration patterns and the capitalist relations into which migrants and non-migrants are incorporated, but women's labour is also imbued with social meanings.
Keywords: Canada – Mexico – Migration; Canadian Seasonal Agricultural Workers Program; Gender and migration; Mexico – Emigration and Immigration – Social Aspects – Case studies; Non-migrating women and globalization; Seasonal Agricultural Workers Program (Canada); Social aspects of migration; Temporary foreign worker programs; Women – Mexico – Social Conditions

Plus ça change? A Comparative Analysis of the Seasonal Agricultural Workers Program and the Pilot Foreign Worker Program for Farm Workers in Quebec - Lowe, Sophia J. (Ryerson University, 2007)
For the last 40 years, migrant farm workers from the Caribbean and Mexico have been recruited to work temporarily on Canadian farms under the Seasonal Agricultural Workers Program (SAWP). In 2002, the pilot Foreign Worker Program (FWP) for low skilled migrant workers was initiated in the province of Quebec and under this program began the recruitment of Guatemalan migrant farm workers. Since the program's start, the number of Guatemalan migrants has nearly tripled and there seems to be a decline in the number of workers hired under the SAWP in Quebec. This paper examines the FWP's development, set-up, consequences and operation alongside the SAWP and shows how the Canadian state is expanding the number and flexibility of temporary worker programs. This paper draws attention to the neo-liberal context of migrant farm labour in Canada, pointing to the ways in which Canada's federal policies governing seasonal agricultural migrants and the agricultural labour market are exploitative and racist.
Keywords: Foreign Worker Program; Migrant; Seasonal Agricultural Workers Program; easonal; foreign labour; racism; temporary

Fast Food Alienation: Service Work and Alienation in British Columbia, 1968-1998 - Milloy, Jeremy Strachan (Simon Fraser University, 2007)
Since World War II, service work has become the major employment sector in North America. One of the most recognizable forms it takes is in the fast food industry, a multi-billion dollar business with outlets all over the globe. Little has been written about the history of this work, central to the functioning of the global economy and a key part of the move from an industrial economy to a consumer one. This move has changed work by examining BC's White Spot chain, which unlike almost any other has been unionized for over three decades. Drawing on union records an d oral interviews, it analyzes fast food unionism, evaluates organizing in the sector, and draws out workplace dynamics and processes; arguing that labour practices in this sector have been crucial in making work more exploitative.

The Empire Within: Montreal, the Sixties, and the Forging of a Radical Imagination - Mills, Sean William (Queen's University, 2007)
This thesis explores the wide variety of ways in which radical intellectuals and activists in Montreal used and adapted Third World decolonization theory to build a broad movement of solidarity and anti-colonial resistance from 1963-1972. Beginning in the early 1960s, activists and intellectuals in Montreal began drawing upon the language of Third World decolonization to resituate their understandings of themselves, their society, and the world in which they inhabited. Through their engagement with Third World liberation theory – and the closely related language of Black Power – radical intellectuals in Montreal sought to give new meaning to the old conception of humanism, and they worked to drastically expand the geographical frame of reference in which Quebec politics were generally understood. After analyzing the shifting meaning of decolonization in the period leading up to the late 1960s, this thesis explores the ways in which various groups adopted, built upon, challenged, and shaped the conception of Quebec liberation. Montreal’s advocates of women’s liberation, the city’s Black activists, defenders of unilingualism, and labour radicals were all deeply shaped by the intellectual and urban climate of Montreal, and by ideas of Quebec decolonization. They developed their own individual narratives of liberation, yet linked by the flexible language of decolonization, these narratives all greatly overlapped, forming a vast movement which was larger than the sum of its parts. If the concept of decolonization was extremely powerful, however, it was also highly ambiguous and contradictory, and activists only slowly came to an understanding of the multi-layered nature of colonialism in Quebec. By the early 1970s, the idea of decolonization was slowly abandoned by those advocating radical social change in the city. This thesis makes three interrelated arguments. First, it argues that radicalism in Quebec in the 1960s cannot be understood outside of the larger international context in which it emerged. Second, it attempts to rethink the ways in which different groups and movements during the 1960s interacted and fed upon each other’s analyses and learned from each other. And, finally, by looking at the centrality of Third World decolonization to the development of dissent in Montreal, it hopes to add new perspectives to the growing field of international Sixties scholarship, by insisting that history of the ‘West’ was profoundly shaped by its interactions with the Third World.

Women's Experiences and Representations of Diversity Management and Organizational Restructuring in a Multinational Forest Company - Mills, Suzanne Elizabeth (University of Saskatchewan, 2007)
This thesis examines the relationship between worker identity and workplace practices from the perspectives of white and Aboriginal women working in a multinational forest company in the northern prairies. Over the course of three manuscripts I demonstrate the salience of ascribed and constructed identities of women to their experiences and representations of forest employment and corporate discourse. Setting the context for the remainder of the thesis, the first manuscript presents an analysis of employment segregation by gender and Aboriginal identity in Canada’s forest sector in 2001 using segregation indices. Results demonstrate that forest employment was vertically segregated by both gender and Aboriginal ancestry in the forest sector in 2001. Men and women of First Nations ancestry were over represented in less-stable and lower paying occupations in woods based forest industries, and both white and First Nations women were over represented in forest services and clerical occupations. To explore women’s perceptions of company practices of diversity management and restructuring, I then analysed interviews with women working in forest processing using critical discourse analysis. In my second manuscript, I demonstrated how women’s representations of diversity management practices were linked to their social identities in terms of Aboriginal identity and class. Yet, as a whole, these representations prompted a questioning of the meaning of difference within diversity management, and of diversity management’s ability to further the interests of marginalised workers. My third manuscript examining representations of restructuring, argues that there is a two way relationship between women’s identities as workers and their representations of restructuring. Whether women reproduced or resisted restructuring was linked to their presented work identities and restructuring and practices in turn were helping to shape women’s worker subjectivities. Results from this thesis demonstrated that how women represent themselves and workplace practices is related to their different experiences in the specific set of social relations of forestry work in the northern prairies.

Constituting Authority: Policing Workers and the Consolidation of Police Power in Vancouver, 1918-1939 - Russwurm, Lani (Simon Fraser University, 2007)
Policing in Vancouver was transformed by the labour unrest of the interwar period, culminating in a campaign carried out by a new civic regime that assumed power in response to a general strike threat. Complicating the process was that police workers were considered unreliable for policing labour disputes, especially since they unionized under the threat of a general strike in 1918. The challenge of “constituting authority” was therefore to render the police a reliable instrument against working class unrest. This study traces the development of policing through the postwar spate of waterfront strikes to the 1930s anticommunist campaign that carried the struggle into the political arena. Even as police power was being consolidated in the municipal police institution, rank and file police were undermined by tactics long used against other workers, namely labour spies and police specials. Like other workers, police resisted, modifying the process of change as a result.

The Stelco Saga: Restructuring and Resistance in the Neo-Liberal Era - Stone, Brendan (McMaster University, 2007)
Global market conditions have led to large corporate bankruptcies in recent years, particularly in the steel sector. Bankruptcy restructuring under the u.s. Chapter 11 or Canadian Companies' Creditors Arrangement Act [CCAA] places employee pensions at risk. In response to concessionary restructuring, the U.s. arm of the United Steelworkers [USW] intervened in several steel sector bankruptcies, developing restructuring solutions that led to partial or near-complete restoration of pensions and collective agreements. In Canada, during Stelco's troubled bankruptcy process between 2004 and 2006, Steelworker locals employed this interventionist method to prevent pension and collective agreement concessions. Scholars, such as Frost and Bacon, implicitly provide a rationale for union intervention into bankruptcy restructuring. They argue that union intervention in general corporate restructuring allows workers a greater voice in the process, leads to optimal results, and prevents union irrelevance. Frost outlines several criteria for maximizing union success during restructuring: the strength of union intra-organizational and external ties; the responsiveness of the union leadership towards the interests of the membership; and the ability of the union to access information and participate at all levels of the process. Many of Frost's recommendations were critical to the success of the USW locals at Stelco in achieving their bargaining and restructuring goals. Unlike in the more cooperative restructuring examples studied by Frost and Bacon, however, Stelco's Canadian locals employed a very assertive stance, since management exhibited initial hostility to union intervention. The union also found it necessary to enlist the help of government. While union intervention in bankruptcies remains a controversial process, it is one possible solution for troubled manufacturing unions, represents an overall USW push towards greater involvement in management, and may even lead towards an exit for labour from the discarded "post-war compromise."

Mouvements sociaux, syndicats et action politique à Montréal : l'histoire du FRAP (1970-1974) - Comby, Marc (Université de Montréal, 2006)
Ce mémoire relate l’expérience du Front d’action politique des salariés à Montréal (FRAP) de 1970 à 1974, un parti municipal émanant directement des milieux syndicaux et populaires. Après avoir présenté les grands traits de la conjoncture sociale, économique et politique de la décennie 1960 au Québec, nous analysons les conditions objectives qui ont favorisé l’émergence du FRAP à Montréal (problèmes sociaux, administration municipale autoritaire, logements insalubres, etc.). Le FRAP est fondé en mai 1970 et présente des candidats contre le maire Jean Drapeau aux élections du 25 octobre suivant. La Crise d’octobre et l’imposition de la Loi des mesures de guerre déroutent le FRAP qui ne fait élire aucun candidat. Les mois et années qui suivent, les groupes sociaux s’éloignent du FRÀP et ce dernier a vainement espéré que les organisations syndicales de la région de Montréal concrétisent l’idée qui avait été à l’origine de sa création, à savoir un parti politique propre aux travailleurs et aux travailleuses. Le FRAP met fin à ses activités au début de l’année 1974 quelques mois avant la naissance d’un nouveau parti municipal, le Rassemblement des citoyens de Montréal (RCM).
https://doi.org/1866/16834

A Detailed Profile of Union - Non-Union Wage Inequality in Canada: 1997-2004 - Easton, Mark David (University of Waterloo, 2006)
This thesis is focused on examining the extent of union-nonunion wage inequality in Canada from 1997 to 2004, using data from the Canada Labour Force Survey collected by Statistics Canada. The research is either directly or indirectly guided by two main measures of union-nonunion wage inequality. The first measure is the wage differential , which examines the difference between the union and nonunion wage after controlling for other relevant factors in a regression model; and the second measure is an account of wage dispersion or wage spread, which effectively explains how internally equitable the union-nonunion wage distribution is in relation to the average wage, after controlling for other relevant factors in a regression model. Each chapter tackles a different hypothesis or subject relating to Canadian union-nonunion wage inequality as investigated from the Canada Labour Force Survey Dataset, and is guided by an effort to explore issues or patterns not previously addressed in the extant literature. The initial analyses found that the union-nonunion wage differential across Canada was normally eleven to sixteen percent from 1997 to 2004. The research also examined three advanced topics in Canadian union-nonunion wage inequality. Analyses of the industry, occupational, and demographic trends in Canada over the past eight years showed that there is some evidence to suggest that demographic changes in union density does affect union-nonunion wage inequality, but this relationship is not conclusive. This research also addressed the unusual finding of higher hourly wages among parttime females. This difference was not present after conducting a more rigorous regression analysis within both sectors. However, it was found that the marginal male wage premium could largely be explained by the combined effects of establishment size among males in the union sector, as well as educational attainment among males in the union sector. Further investigation of some unexpected interaction effects of union status and establishment size and union status and job tenure in relation to the wage, revealed that these combined effects still generated comparative over the nonunion group, but only up to a certain level of tenure or establishment size. Finally, an analysis of whether union density has mattered at all in Canada for promoting higher wages, reveals that the general effects of union density on the wage are relevant only within a certain wage range and within certain industries.
Keywords: Social sciences

Protection of Migrant Agricultural Workers' Rights - Gutierrez, Gonzalez Israel (McMaster University, 2006)
This thesis investigates several issues related to the provisions afforded by aspects of the Canadian welfare state to protect the rights of migrant labour participating in the Canadian Seasonal Agricultural Workers Program. In the introduction and literature review, I provide the background of the program and present the nature of the issues that surround it. I also outline the problems that migrant agricultural workers face while participating in the program. These are mainly due to the few provisions that are extended to this secondary sector labour group, a group of workers that is barely visible to Canadian society. In the main part of the thesis, I analyze the two instruments that allow the entry of these workers into Canada and the different pieces of Canadian legislation that are relevant to protecting legitimate rights of any person who works in this country. More importantly, I also present findings derived from interviews with migrant agricultural workers and key informants from advocacy groups and the labour movement regarding those provisions. Based on their in Sights and on the dual market theory, I scrutinize the position of the Canadian welfare state concerning the legitimate provisions migrant workers should be entitled to and how the globalization context influences that position. I conclude with a series of ideas that, in my opinion, could positively affect this labour group's welfare status.

Globalization and the Mexican-Canadian Seasonal Agricultural Worker Program: Power, Racialization and Transnationalism in Temporary Migration - Hennebry, Jenna L. (University of Western Ontario, 2006)
This research investigates the formation and maintenance of power relations within the organization and everyday practices of work and transnational living, and the social and economic impacts among Mexican migrants and their families participating in the Seasonal Agricultural Worker Program (SAWP). Through the analysis of the qualitative data collected through ethnographic case studies in Mexico, 350 hours of participant observation, and semi-structured interviews with 25 migrant workers, 5 farmers and 5 representatives from other state and non-state intermediaries, findings have emerged pertaining to three research themes: power, racialization and transnationalism. This research finds that Mexican migrant workers are consistently located in subordinate power positions in the organization and the everyday practices of the SAWP; and governments, employers, and other intermediaries have significant control over migrants' daily lives and their migration parameters. Racialization processes in both the institutional and everyday practices of the SAWP produce, maintain, and legitimize a system of temporary migration characterized by imbalanced power relations and the unequal allocation of resources and rights through the differentiation of the "Mexican migrant worker" with reference to race and ethnicity. Migrant workers and their families actively participate in transnational practices that are integral to seasonal migration, including the family networks that facilitate entry into the program, the "migration work" performed by women, and the use of information and communication technologies (ICTs). This essential "migration work" involves preparing the family for migration and sustaining the transnational family through managing and/or working within family farms and small businesses, receiving and managing international remittance transfers and telephone calling, managing and utilizing remittances for daily living and development, and performing carework. These findings support the "transnationalization of culture" hypothesis, and indicate that a gendered culture of migration is emerging within the SAWP. It is argued that the SAWP is an exemplar of "time-space compression" in action which leads to the exploitation and subordination of "Mexican migrant workers." Temporary migration systems like the SAWP are seen as recursively related to globalization, where foreign labour dependence and remittance economies are created and perpetuated through globalization and a "migration industry" powered by new information and communication technologies.
Keywords: Globalization; Mexican-Canadian Seasonal Agricultural Worker Program; Racialization; Seasonal agricultural workers; Social sciences; Temporary migration; Transnationalism

Le Conseil central des syndicats nationaux de Montréal (CSN) à l'heure de la radicalisation syndicale : 1968-1980 - Poirier, Stéphanie (Université de Montréal, 2006)
Ce mémoire porte sur le syndicalisme québécois dans les années 1960 et 1970 alors qu’il traverse une phase de bouleversement et qu’il radicalise son idéologie. Nous nous penchons plus particulièrement sur le cas de la CSN qui affermit sa critique du capitalisme avec la publication de textes d’orientation socialiste tels que Il n'y a plus d’avenir pour le Québec dans le système actuel et Ne comptons que sur nos propres moyens. Parmi les instances de la centrale, il y a les conseils centraux régionaux dont celui de Montréal, le plus imposant en terme d’effectifs (près de 60 000 en 1968). Rassemblant la frange la plus militante de la centrale, il a pour rôle l’éducation et l’action politique des membres. Le Conseil central des syndicats nationaux de Montréal (CCSNM) se trouve au centre de la tourmente sociale et nationale au cours de ces deux décennies alors qu’il est dirigé par la figure imposante et colorée de Michel Chartrand, président de 1968 à 1978. Dans l’historiographie, le Conseil central de Montréal est souvent considéré comme un haut lieu de la radicalisation syndicale. En analysant son discours et ses actions, nous démontrons qu’il prend effectivement des positions radicales et qu’il défend des opinions nationalistes. Malgré le fait qu’il tente de passer à l’action politique et milite pour la création d’un parti de travailleurs, le Conseil se caractérise principalement par son discours contestataire et sa critique acerbe du capitalisme. Nous verrons qu’il développe une position nationaliste indépendante au cours de la période, en se dissociant du projet du Parti québécois, qu’il juge bourgeois. Bien que les relations entre la CSN et le Conseil soient tendues, ce dernier a tout de même un impact important sur la CSN, particulièrement au niveau de la protection de la langue française et sur la position adoptée par la centrale au référendum de 1980. Le Conseil constitue donc un acteur important de la radicalisation de la société québécoise des années 1960 et 1970 en influençant la CSN, le mouvement syndical ainsi que les milieux de gauche à Montréal.
https://doi.org/1866/16824

L'image des syndicats dans les éditoriaux de trois quotidiens montréalais lors de la première année du gouvernement québécois dirigé par Jean Charest (avril 2003 - avril 2004) - Posca, Jean-Simon (Université du Québec à Montréal, 2006)
Ce travail décrit et fait l'analyse de l'image des syndicats dans les éditoriaux des quotidiens payants montréalais lors de la première année au pouvoir du gouvernement québécois dirigé par Jean Charest (avril 2003 à avril 2004). Il se concentre sur les éditoriaux traitant des luttes entre les syndicats et le gouvernement Charest. Il examine les éditoriaux relatifs au syndicalisme parus dans Le Devoir, La Presse et The Gazette. Le travail présente et explique les ressemblances et les divergences apparaissant entre les différents journaux dans l'image que ceux-ci renvoient des syndicats.

"A Very Conservative Radical": Reverend Robert Connell's Encounter with Marxism in the BC CCF - Price, Christine (Simon Fraser University, 2006)
The historiography of the British Columbia Cooperative Federation differs from that of other provincial CCF groups for its lack of attention to the participation of religious reformers in shaping the party's early history. Yet the first CCF House Leader in the province, Reverend Robert Connell, was a fervent believer in the social gospel and in the goals of ecumenism. His attempts to bring "Christian principles" into politics resulted in a battle between reformers and radicals in the party, ultimately resulting in his departure from political life. The division of the BC CCF in 1936 as a result of what has become known as the "Connell Affair" created a loss of momentum for the party which lost its status as Official Opposition in the 1937 provincial election. This event presents a unique opportunity to study the interaction of a social gospel inspired Christian reformer with firmly irreligious supporters of Marxism.

Organized Labour and the Constitutional Question - Savage, Larry (York University, 2006)
This dissertation examines Canada's constitutional question through the lens of the labour movements in both English Canada and Quebec. The existence of two distinct labour movements in Canada has meant that political struggles that have typified national politics are also in evidence in labour politics. The sovereignty-association partnership agreement between the Canadian Labour Congress and the Quebec Federation of Labour provides a good example of the pervasiveness of this dynamic and discourse. The dissertation examines this relationship specifically, and the constitutional politics of labour organizations in English Canada and Quebec, more generally, with a view to explaining how Canada's constitutional questions have been reflected in the politics of organized labour.
Keywords: Constitutional question; Social sciences; Sovereignty-association partnership agreement; organized labor

Masters and Servants: The Hudson's Bay Company and Its Personnel, 1668-1782 - Stephen, Scott P. (University of Manitoba, 2006)
During its long first century (1670-1782), the Hudson’s Bay Company (HBC) developed personnel practices not on the basis of abstract policy but by patching together experiments and expedients. Its initial vulnerability increased the value of loyal and experienced servants, and frequent shortfalls in wartime recruitment allowed old hands to demand and receive higher wages and gratuities. Peace after the Treaty of Utrecht in 1713 allowed the Company to prune its payroll and to resume the carefully optimistic expansion that French attacks had interrupted in 1686. This required a larger labour force, but recruitment processes remained relatively unchanged from previous years (although Orkneymen became increasingly prominent). Expanding operations in the mid-eighteenth century imposed greater regularity on existing ad hoc methods of recruiting and retaining personnel, but labour needs did not expand rapidly enough to unduly strain those methods. Increasing inland travel and trade after 1743 placed new demands on servants by requiring that ‘extraordinary’ labour become ‘ordinary’. The Committee discovered that this could only be done with ‘encouragement’, the slow pace of which hampered inland ventures into the 1780s. Inland operations changed the nature of HBC service and influenced the way master, factor, and servant interacted; they also illuminated the practices and assumptions which had been prevalent since Utrecht and probably before. The HBC drew its labour force from the competitive labour ‘market’ of early modern Britain: the movement of men to and from the Bay was an aspect of domestic labour mobility. The relationship between the Committee and their employees was that of master and servants, heavily influenced by the circumstances of trading in Hudson Bay. Labour relations within HBC posts were framed by the dominant social construct of early modern Britain, the patriarchal household-family, made up of a master (the patriarch) and a family of kin, apprentices, and servants. Men at all levels of the Company hierarchy could try to shape the reality of their HBC experiences, but did so in terms of commonly accepted ideals. Deferential behaviours and strong vertical ties existed alongside tension and negotiation: the Committee and their servants all understood the nature of ideal master-servant relationships, but they also had experience of the realities of life in various kinds of households. The Company’s servants internalized and practised the expected values of deference and submission, but did so without abandoning or deferring their own self-interest; indeed, they could use their mastery of the language to advance their own interests. The household-factory was the fundamental social unit of HBC establishments. Although membership changed, the institution maintained continuity over time. Furthermore, each household-factory was internally held together, and bound to other household-factories and to the London Committee by ties of patronage, brokerage, and friendship, that mediated the network of horizontal and vertical relationships.

Faith and Factory: Russian Mennonite Workers in Twentieth-Century Manitoba - Thiessen, Janis Lee (University of New Brunswick, 2006)
[This thesis is] a labour history of Russian Mennonites employed in three Mennonite-owned factories in Manitoba: Friesens Corporation of Altona, Loewen Windows of Steinbach, and Palliser Furniture of Winnipeg. Each of these businesses had a primarily Mennonite workforce at their founding, and eventually became the largest employers in the community in which they were established. This comparative microhistory makes a significant contribution to the literature: though approximately one-quarter of North American Mennonites are working-class, few scholarly works have investigated their experiences. The history of immigration of these Mennonites is important in understanding their adaptation to North American capitalism. Immigrants had common experiences of some aspects of settlement, such as language acquisition and finding employment. Immigrants exhibited a variety of responses to government efforts to promote assimilation, and demonstrated different attitudes toward job security and expectations for their children, in part because of their diverse prior experiences of war, religious conservatism, and prejudice in their country of origin. The result was the development of an increasingly urban and heterogeneous Mennonite community in Manitoba, which perhaps contributed to the failure to develop a strong sense of class consciousness among them. The historical development of Mennonite religious thought in the twentieth century is connected to the geographical shift of North American Mennonites from rural to urban environs. This move necessitated a re-assessment of Mennonite religious beliefs, particularly of their understandings of 'Gelassenheit ', to nonresistance, and 'agape' love. The Christian's responsibility to the world came to be stressed at the expense of traditional values such as submission to the community and separation from the world. Religious belief had a role in restraining the behaviour of both workers and owners, encouraging the former to accept work discipline, and limiting the latter in their conspicuous consumption. In a case study, Barthes' semiological approach is used to demythologize an advertising campaign at Loewen Windows as a means of examining the linkages between religion and capitalism. The role of religion differentiated the operation of paternalism at these businesses from their non-Mennonite counterparts. Though Mennonite workers rarely expressed their views in class-conscious ' language', the 'content' of their remarks, particularly with respect to the labour process and their autonomy, points to the existence of a class division in these factories. The nature of their employment as factory workers affected not only their job mobility and security, the speed of their work, their sleeping patterns and social lives, but also their identity. Class differences between Mennonite employers and employees clearly existed; class consciousness on the part of workers is less evident. With the transformation of Friesens Corporation, Loewen Windows, and Palliser Furniture from small family businesses to large corporations, the relationship between Mennonite workers and their employers was reinterpreted. Employers made use of Mennonite religious motifs to craft a common ethos, but increased ethnic diversity in the workforce at Palliser Furniture, together with objective class differences between workers and owners at all three companies, resulted in some splits in the unity of the Mennonite workplace. The interplay of competing interests nonetheless resulted in redefinitions of ownership rights and their meaning for workers with respect to profit sharing and employee share ownership, as well as several unsuccessful attempts to unionize. The tension between Burkholder's emphasis on social responsibility, as exhibited by labour's demands for economic justice, and Hershberger's insistence on avoidance of confrontation was evident in the struggle of Manitoba Mennonites with their response to labour activism in the 1970s. Pacifism often had been dismissed as passivity in the past; now the adherence to the principle of nonviolence could be seen as an excuse for accepting economic exploitation. Mennonite support for cooperatives and credit unions could have translated into support for labour unions, but in late twentieth-century Manitoba, it did not. Though North American Mennonites' attitudes toward unions may have undergone change during this period, they continued to avoid becoming members. The conclusion explores whether Mennonite involvement in industrial capitalism is (or can ever be) in any way distinct from that of secular participants. Are there theological resources within Mennonitism that can mount an effective challenge to the negative results of global capitalism? This work is a modest attempt to contribute to the debate, both within the Mennonite community and without, regarding the possibilities for social and economic transformation. It is also an attempt to argue for the relevance of the consideration of religion in scholarly discourse in general, and historical study in particular.
https://archives.mhsc.ca/index.php/52ky-4qm6-qwb4
Keywords: Employment; Family-owned business enterprises; History; Labor; Manitoba; Mennonites; Religous aspects

Direct Action, Subsidiarity and the Counterhegemonic: Three Case Studies of Antipoverty Activism in Twentieth Century Canada - Thompson, David Alexander (University of Victoria, 2006)
An analysis of three poor people's movements in twentieth century Canada serves to wrest the ideas and activist tradition of Canada's poor people from historical obscurity. Between 1932 and 1935, the Communist-inspired Vancouver unemployed councils engaged in direct actions to challenge Depression-era social policy, capital and the police. The arrival of the modern post-war welfare state did not end poverty; however. Vancouver antipoverty activists were circumscribed by society's relative affluence and organizational and sectarian debates within labour councils and the antipoverty movement. Finally, since 1989 the Toronto-based Ontario Coalition Against Poverty (OCAP) has extended antipoverty activism to include the issues of immigrants, First Nations, women and children. Drawing on theorist Antonio Gramsci and the socialist-anarchist tradition, this thesis posits that direct action and a subsidiarity relationship between activists and their community are essential to the success and longevity of poor people's movements.

"Still Raining, Market Still Rotten": Homeless Men and the Early Years of the Great Depression in Vancouver - McCallum, Todd (Queen's University, 2005)
Single transient homeless men are one of the archetypal figures of the chaotic decade known as the Great Depression. They are also a misunderstood group, commonly associated with a degraded and hopeless existence. This thesis focuses on homeless men, both on the road and in Vancouver, in the period from the fall of 1929, with the collapse of North American stock markets, until the spring of 1932, with the breakdown of the provincial government's relief camp scheme. It argues that those involved in the relationships of charity provision, whether homeless recipient or government bureaucrat, characterized the world of relief with the same terms they used to understand the normalized world of the capitalist economy. Homeless transients flocked to Vancouver by the thousands. Many became the rank-and-file backbone of Communist-led protest movements. Consistently, these movements demanded relief at union rates, challenged the gendered, racial and national categories that divided the unemployed, and rejected outright the oppressive relief measures accorded transients. In response, the municipal government sought to introduce Fordist methods of business management, rationalizing the processes of relief provision with an eye to efficient administration and surveillance. Relief was not a one-sided transaction-a gift from one party to another-but an exchange. When offering the poor food, shelter, fuel and clothing, public and private charities became involved in commercial relationships with the city's service industries. Businesses across Vancouver clamoured to get their share of relief money, hoping to translate some of the money spent on the unemployed into profit. With state-run relief camps, governments created one of the sharpest contradictions of the 1930s, unemployed workers who worked for a living, but for substandard rates of relief. Officials seized upon the crisis to initiate a program designed to develop British Columbia's economic infrastructure. The work of the jobless would thus pay dividends by enabling an increased rate of economic growth once the crisis had passed. In these ways, relief became an industry. The hundreds of people who wrote about tramps during the 1930s twinned the objectification and the commodification of transiency. Whether espousing a humanitarian or a hateful view of hoboes, these authors almost unanimously agreed that the tramping life had to be destroyed. Hoboes would vanish from the Canadian landscape because their lives were without value. For their part, the hoboes who put words on paper ranged across a host of subjects pertaining to life on the road and life in the city. While some cried out against what they saw as the oppressions of transient life and envisioned a future in which they would be reintegrated into society, others lauded the camaraderie and mutuality amongst tramps. For this group, the hobo life was an end in itself, valued because it enabled them to live free from the exploitation that was the lot of wage workers.
OCLC: 59135675
Keywords: Academic Dissertation; Academic theses; Thèses et écrits académiques

Industry, Ideology, and Social Formation in British Columbia, 1849-1885 - Morton, Jamie (University of Victoria, 2005)
This study examines how the systems of production of the commodity exporting industries of pre-1885 British Columbia contributed to the social formation of the region. Such industries provided the economic base for post-contact development and non-Native settlement of the region, mediated by the cultural values of immigrant and indigenous populations. The intent here is to synthesize a more inclusive model to clarify how these economic and cultural factors intersected to produce a distinct regional society. Beginning with Ian McKay’s suggestion to interpret the history of Canada as a process of naturalizing the liberal order, this study moves the analysis away from microstudies of individual industries or social groups in order to emphasize the way in which a broader vision became naturalized. This approach avoids some of the simple dichotomies of class and race that have informed much of the historiography of BC, in favour of a more nuanced analysis that emphasizes the negotiated process that leads to social consensus. Beginning with the merchant capitalist relations of the fur trade, and accelerating with the 1858 gold rush, BC became understood as a place that provided opportunities for economic and social mobility through participation in commodity exporting ventures. A consensus emerged that emphasized the producer ethic [the economic and cultural value of independent producers], and the creation of a meritocratic socio-political environment to support opportunities for achieved, rather than ascribed, social position. This attracted Euro-North American immigrants hoping to escape social restrictions or proletarianization by achieving independent producer status. Such a goal meant that these immigrants resisted waged labour, creating a chronic shortage that impeded industrial development. This was filled with Chinese immigrants or Aboriginal participants, attracted by the prospect of converting earnings into increased status in their originating societies. Combining the demand for labour with racial ideology, certain jobs were racialized, and BC industries were typified by split labour markets, with an upper echelon comprised of occupationally-mobile Euro-North American workers, and a lower echelon defined by race as well as skill, with little opportunity for mobility. In turn, this contributed to naturalizing ideology concerning race, class, and social position. The emphasis on the producer ethic contributed to an artificial division between “producers” and “agents,” with the former celebrated, while the latter, arguably more important to the systems of production by providing links to export markets, are portrayed less favourably. A commodity exporting, producer-centric variant of the liberal order was naturalized in nineteenth century BC, providing the logic for social and political development, and explaining how certain groups were valued, and either integrated into or excluded from hegemonic society. The degree to which individuals or groups conformed to the naturalized values of the emerging society largely determined their social position in the nineteenth century, and their subsequent treatment in the historiography.

From Conquest to Capitalism: The State, Class, and Capital in British North America, 1760-1860 - Peters, John (York University, 2005)
This thesis traces the transformations in state, class, and politics in British North America from 1760-1860, and how these facilitated the emergence of wider economic change. Building on recent studies in political economy, Marxist and economic history, as well as historical sociology, it employs a class power model of historical change to explain how and why colonial Canada's political economy developed. The argument also draws upon comparative political economy to highlight how different class structures and different forms of political institutionalization shaped political economic regimes and long-run forms of economic growth. The case study analysis of British North America within a wider comparative context demonstrates that class interests, institutions, and policy making were critical to state building and changes in state-society relations, above all to state 'autonomy' and class 'embeddedness'. Agrarians and commercial classes struggled over economic benefits and the reins of political power. But how these classes forged coalitions and how their conflicts were institutionalized within the state determined whether or not new productive dynamics emerged. By the mid-19th century, with greater autonomy, colonial governments across the North American colonies designed institutions, laws, and policies to improve taxation, build infrastructures, enhance the rule of law, and extend the contractual equalities necessary to commercialize the economy. With greater class embeddedness, broader class coalitions of agrarians and merchants actively reshaped agrarian property and agricultural labour to conform to the structures of a market economy, and enacted new market law to allow for the expansion of free labour markets, trade, commerce, and small manufacturing. Looked at comparatively, the thesis claims, 19th century colonial British North America emerged as a 'Liberal Settler' society, led by a diverse coalition of agrarians and merchants. Despite its many state and class particularities, this crystallization of settlers, merchants, and Imperial market-directed politics made colonial Canada a variant of Britain's own liberal political economy, and very similar to other growing settler countries such as the United States. Exploring the connections between state, class, and politics, the thesis concludes, can tell us much about why and how these distinct historical patterns emerged, and why 19th century political economies changed in ways that fostered the development of capitalism.
Keywords: Capital; Capitalism; Conquest; Political economy

The Making of CUPE: Structure, Democracy and Class Formation - Ross, Stephanie (York University, 2005)
This thesis explores the nature and challenges of democracy within unions through an historical examination of the emergence and early years of the Canadian Union of Public Employees (CUPE). Formed by a merger of two pre-existing unions in 1963, CUPE casts new light on the Marxist, Michelsian and Institutionalist theoretical approaches to union democracy. The thesis calls into question the narrow and ahistorical link made between centralization, oligarchy and effectiveness on the one hand, and decentralization, democracy and ineffectiveness on the other. Instead, the case of CUPE shows that unions are subject to contradictory pressures and that neither centralization nor decentralization is inherently more democratic. Union democracy is part of an historical process of class formation, in which both union purposes and the boundaries of the democratic community (which can make legitimate claims on members' solidarity and self-discipline) are struggled over. As such, it is possible that decentralizing forces can place narrow and sectionalist priorities over the interests of the broader community. Moreover, the thesis argues that the use of merger as a method of forging greater class unity is itself problematic. The merger which created CUPE involved a protracted struggle over which model of union would prevail. The compromise which was reached entrenched a self-reinforcing cycle of autonomy-seeking by union locals which, over the long term, prevented the development of an effective national union capable of carrying out the democratic will of the membership as a whole. As such, through an historical excavation of the roots of contemporary crises in CUPE, the thesis points to the important way in which the outcomes of past decisions come to structure future political possibilities for unions and other social justice organizations.
Keywords: Canadian Union of Public Employees; Class formation; Democracy; Labor Unions; Social sciences

Oshawa Autoworkers: Social Integration and Oppositional Class Consciousness Among the Unionized Workers of General Motors - Roth, Reuben N. (University of Toronto, Ontario Institute for Studies in Education, 2005)
Many social theorists (Goldthorpe, Lipset, Giddens, Hout, Brooks and Manza) have portrayed members of the Western industrial working-class as accommodative and resistant to a class-based social revolution. They suggest that an affluent proletariat has seen its oppositional class-consciousness subverted and transformed by the 'cash nexus' into various forms of social integration. With reference to Mann's (1973) measures of class-consciousness typologies and Livingstone and Mangan's (1996) study of Hamilton steelworkers, I explore expressions of working-class consciousness among organized workers at one of Canada's largest industrial union locals, the Canadian Auto Workers (CAW) Local 222 at General Motors, in Oshawa, Canada. I accomplish this via an examination of the existence and degree of working-class imagery, class identity, and oppositional working-class consciousness among this group of workers on the basis of measured responses to a survey questionnaire (N=102), in-depth interviews, and participant observation. My thesis asserts that Oshawa autoworkers' material advantage is insufficient to transform their proletarian consciousness. I have found that among Oshawa autoworkers there is a shared view of Canadian society as class-based, a clear working-class self-identification and measurable forms of oppositional working-class consciousness.
Keywords: Autoworkers; General Motors; Ontario; Oppositional class consciousness; Oshawa; Social integration; Social sciences; Unionized

Engaging Women’s History Through Textiles: Enhancing Curricula with Narratives of Historical Memory - Wheeler, Eileen Margaret (University of British Columbia, 2005)
During the late nineteenth and early twentieth centuries, racism, in the form of white supremacy, shaped relations between whites and Chinese British Columbians. In resisting and accommodating to white supremacy, the Chinese were active participants, along with the members of the dominant society, in shaping these relations. White supremacy was consequently a dynamic system, one whose many parts were continually in flux, and whose central constructs—notions of "race" and British Columbia as "a White Man's province"—were largely political in nature. The thesis argues that white supremacy, as both ideology and organization, was deeply imbedded in British Columbia society. Exclusion based on "race" was incorporated into government institutions as they were remade at Confederation in an effort to enhance the power of white male property-owners. By the early twentieth century, ideological constructs of "the Chinaman" and "the Oriental" were used as foils in the creation of identities as "whites" and as "Canadians." The official public school curriculum transmitted these notions, while schools themselves organized supremacy in practice by imposing racial segregation on many Chinese students. In reaction, the Chinese created their own institutions and ideologies. While these institutions often had continuities with the culture of South China, the place of origin of most B.C. Chinese, they were primarily adaptations to the conditions of British Columbia, including the realities of racism. Chinese language schools played an especially important role in helping to create a Chinese merchant public separate from the dominant society. This public was at once the consequence of exclusion and the greatest community resource in resisting white supremacy. The study concludes by questioning the workability of contemporary anti-racist strategies which treat racism as a marginal phenomenon, or as merely a set of mistaken ideas. Instead, it suggests that such strategies must recognize that racism is one of the major structures of Canadian society.

The Communist Party of Canada during the Great Depression: Organizing and Class Consciousness - Burger, Anne (Simon Fraser University, 2004)
Canada experienced its worst economic crisis during the Great Depression of the 1930s with unprecedented numbers of Canadians suffering extreme economic and social hardship. Survival and struggle to change those conditions became as much a mark of the times as the economic circumstances themselves. The Communist Party of Canada (CPC) was one organization that played a significant role in this national upsurge of struggle. The Party believed that the worsening material conditions would engender class consciousness of Canadian workers, leading to the overthrow of the capitalist system to achieve a worker-farmer socialist state. The Party was instrumental in organizing workers, farmers, the unorganized and the unemployed, however, it was not successful in raising Canadian working class consciousness to a revolutionary level. The factors that will be analyzed as being the main contributing factors to the Party's limitations are the CPC1srelationship with the Comintern, repression by the Canadian state, and dominant ideology that prevailed in Canada during the Depression. From its inception in 1921 the CPC worked assiduously to meet the needs of Canadian workers in a rapidly changing economy in the 1920s and one that was also collapsing in the Depression. In many ways it recognized Canadian workers' needs in these times and was at the head of the labour movement fighting for workers' needs and defending them. However, the CPC was somewhat hamstrung by its very close relationship with the Comintern allowing this international communist body to dictate almost every move it made whether or not it was the best for Canadian workers. State repression of the CPC and labour movement, also had a curbing effect on the advancement of the CPC in its work with Canadian workers, forcing the Party underground, decimating its leadership and intimidating Party activists, unions and workers. Finally, dominant ideology during the Depression, in spite of serious threats by alternate sets of ideas, particularly those promulgated by the CPC, largely stood its ground as defender of the present capitalist system that relied on the exploitation of Canadian workers for its survival.

Acting in the Name of Culture? The Participation of Organized Labour in the Canadian Broadcasting Policy Process - Coles, Amanda (Toronto Metropolitan University, 2004)
The thesis examines the role, efficacy and influence of the five national English-language independent film and television production sector unions in the Canadian broadcasting policy network. While labour is typically classified as a civil society organization within policy networks studies, this thesis will examine the blanket applicability of this typology in analysing labour's engagement with issues that involve both their vested economic/industrial interests as well as broader social/cultural goals, using the unions' engagement with the issue of Canadian dramatic programming from 1998 to present as a case study.

Reconsidering Staple Insights: Canadian Forestry and Mining Towns - Dignard, Louise (Carleton University, 2004)
The purpose of the thesis is essentially to elaborate, and to a lesser extent to test the relevance of a theoretical framework focussing simultaneously on the spheres of industry, work and community in staple-specific contexts, explicitly in Canadian forestry and mining single-industry towns (SITS). The framework builds two ideal types of these towns by drawing from the main approaches that have addressed the topic in political economy, labour and community studies. The core underlying argument is that a reconsideration of some neglected staple insights constitutes a legitimate endeavour. The framework stresses that forestry SITs have more: of an elite model of power structure, separate work and community social arrangements, individualistic income strategies, as well as lower class consciousness and numerous contradictory class locations; while mining SITs have more: of a class model of power structure, overlapping work and community arrangements, income strategies framed in secondary relations terms, as well as a higher class consciousness and fewer contradictory class locations. After a brief introductory chapter, the second, third and fourth ones extensively review and interpret the literature, gathering empirical material and theoretical considerations useful to the comparative theoretical framework. The latter is detailed and its claim circumscribed in Chapter five; its relevance is tested in the two last chapters by using it as a backdrop to explain staple specific patternings regarding the organization of work in the main resource sector and women's experience in the family.
Keywords: Forestry and mining towns; Single-industry towns; Social sciences; Staple insights

Exploring Decentralisation in Canada: Devolution of Labour Market Policy - Gray, Erin (University of Wales, Swansea, 2004)
This thesis entails the study of both why and how decentralisation of government authority takes place. Decentralisation in Canada is explored by investigating a federal proposal for the devolution of active labour market policies from federal to provincial governments, and by closely examining the positions taken by both levels of government during the development of two federal-provincial labour market agreements in the mid-1990s. The two bilateral agreements chosen for this examination are, the Canada-Nova Scotia Agreement on a Framework for Strategic Partnerships, and the Canada-Alberta Labour Market Development Agreement. The central focus of this research is to examine the extent to which federal and provincial governments’ positions on the devolution of policy are influenced by ‘political’ and ‘public’ interests. The first argument holds that political imperatives influence governmental priorities, attitudes, and motivations as decisions about devolution are made. The second argument maintains that governmental positions on devolution are founded on the motivation to promote the best outcomes for the public at large. This study employs a research focus that is qualitative in nature, and it draws from interpretive and constructivist approaches to inquiry. Interviews were conducted with civil servants who represent federal and provincial interests in the provinces of Alberta and Nova Scotia. A comparative analysis of the evidence found that both political and public interests influenced federal and provincial positions on devolution. This research illustrates that while political and public interests might be separated analytically, in real cases of policy-making they overlap. Nonetheless, the evidence tips the scales towards a political interest explanation much more clearly and convincingly than a public interest interpretation.

Economies of Justice: Workers and Labour Reformers in Late-Victorian Canadian Industrial Fiction - Janes, Daniela Alexandra (University of Toronto, 2004)
In this dissertation I propose the existence of a distinct and previously unacknowledged sub-genre in the Canadian social-reform writing of the 1890s, namely the industrial novel. I concentrate on several late-Victorian Canadian examples: Agnes Maule Machar's Roland Graeme: Knight: A Novel of Our Time (1892), Robert Barr's The Mutable Many (1896), and Albert Richardson Carman's The Preparation of Ryerson Embury: A Purpose (1900). These novels each reflect the expansion of industrial production in the Victorian period and the concomitant social effects of urban industrialism upon the labouring poor. I undertake an examination of these works that analyses the relationship between the novels' middle-class protagonists and the workers whose rights they are defending, seeing in the narrative patterns, imagery, and intertextual references both the articulation of an alternative kind of social justice and a tension emerging between political dissent and political conservatism. These novels of labour unrest caution against violent revolution and instead preach a doctrine of reconciliation and compromise, rooted in a reorientation of conventional notions of justice, a rejuvenation of social institutions, and the imperative of individual moral responsibility. First I focus on Machar's representation of Christian socialism, and how the language of "brotherhood" acts as an antidote and alternative to the morally degenerative effects of industrialism. Machar parallels the labour reform movement to the Christian belief in an afterlife: both are predicated upon faith and deferral, the commission of good works in the present for the benefit of some future blessing. Next, I examine Barr's novel about two strikes in a London factory, looking in particular at issues of leadership and representation. I propose that his novel works to reveal the complexities inherent in any project in which one man must speak for a crowd of others, as the end of the novel amply deconstrates the failure of communication. Finally, in my examination of Carman's novel, I analyse his refashioning of conventional notions of justice. I argue that Carman's narrative suggests the sterility of intellectual debate in the absence of any commitment to social action. I conclude by connecting the late-Victorian Canadian industrial novel to early twentieth-century literary responses to labour advocacy, urbanism, and industrialism.
Keywords: Agnes Maule Machar; Albert Richardson Carman; Industrial fiction; Labor reform; Language; Robert Barr; Workers; literature and linguistics

Analysis of a Worker-Based Participatory Action Research Approach to the Identification of Selected Occupational Health and Safety Problems in Canada Using Mapping - Keith, Margaret Mary (University of Stirling, 2004)
There are limitations to conventional occupational health and safety research approaches and practices and numerous barriers to overcome in order to achieve progress. Occupational health and safety is impacted by the broader social-political environment. Corporatism affects the directions, ideas and practice of regulators, educators, the labour movement, scientists, medical professionals, and society as a whole, thus inhibiting workers' power to influence change. The thesis therefore explores both the wider influences and barriers to occupational health and safety advances, focusing particularly on the Canadian situation, through the general research questions: What has influenced occupational health and safety policies and practices, especially in Canada? What are some of the limitations of conventional occupational health and safety research and practices? To what extent can participatory action research and mapping address identified limitations? These questions are explored from the perspective of the population potentially at risk. New theories and approaches to occupational health and safety research are then applied in this thesis in order to explore a more specific multi-part research question: Can mapping within worker-based participatory action research be used to explore occupational health and safety conditions? In particular, can mapping contribute to occupational health and safety improvements at a local level and beyond; establish workers' previous exposures for compensation purposes; support efforts to bring about justice through compensation for workers affected by unsafe working conditions; and raise worker and public awareness of health and safety? These questions are explored through two different case studies, which examine, in depth, occupational health and safety action and possible remedies. Casino gaming workers in Windsor, Ontario, Canada undertook a collaborative study to investigate and improve current health and safety conditions. Former Holmes foundry and asbestos insulation workers in Sarnia, Ontario, Canada undertook a collaborative study to provide evidence of exposures and ensuing health problems to support claims for compensation. The outcomes of the case studies shed light on the bigger Canadian health and safety picture and demonstrate that mapping as a data collection method used within a participatory action research approach can accomplish a broad range of objectives. Mapping can raise workers' awareness, facilitate communication, build solidarity and cohesiveness, foster community support, mobilise workers to take action to reduce hazards or win compensation, in turn influencing employers, the compensation board and government agencies. The case studies accomplished the shared objective of raising worker and public awareness. The casino workers also gained occupational health and safety improvements and the Holmes workers were successful in gaining compensation.

The Business of Women: Gender, Family, and Entrepreneurship in British Columbia, 1901-1971 - Buddle, Melanie Anne (University of Victoria, 2003)
This study examines female self-employment in British Columbia from 1901 to 1971. Entrepreneurial women comprised a small proportion of the total female labour force but they exhibited differences from the rest of the labour force that deserve attention. The study relies on the Census of Canada to gain perspective on trends in female self-employment over a broad time period; qualitative sources are also utilized, including Business and Professional Women’s Club records, to illustrate how individual businesswomen reflected patterns of age, marital status, and family observed at a broad level. The role of gender in women’s decisions to run their own enterprises and in their choice of enterprise is also explored. While the research focus is British Columbia, this study is comparative: self-employed women in the province are compared to their counterparts in the rest of Canada, but also to self-employed men, and to other working women, in both regions. Regionally, women in British Columbia had higher rates of self-employment than women in the rest of the country between 1901 and 1971. Self-employed women in both British Columbia and Canada were, like wage-earning women, limited to a narrow range of occupational types, but they were more likely to work in male-dominated occupations. Self employed women were also older and more likely to be married, widowed or divorced than wage-earning women; in these aspects, they resembled self-employed men. But there were gender differences: whether women worked in female or male-dominated enterprises, they stressed their femininity. The need to take care of their families, particularly if they had lost a spouse through death or desertion, provided additional rationale for women’s presence in the business world. Family, marital status, age, gender and region all played a role in women’s decisions to enter into self-employment between 1901 and 1971.

The Search for Solidarity: The Industrial and Political Roots of the Cooperative Commonwealth Federation in British Columbia, 1913-1928 - Isitt, Benjamin (University of Victoria, 2003)
Born out of the industrial and political struggles of organized labour at the end of the First World War, the BC CCF was a product of organizational and ideological conflict in the 1910s and 1920s. This study explores the shift of BC socialism towards industrial action, which culminated in the One Big Union and the sympathetic strikes of 1919. It then examines the emergence of anti-Communism on the Left, shaped by the experience of political unity and disunity during the 1920s. These two factors fundamentally influenced the ideology and strategy adopted by the Cooperative Commonwealth Federation (CCF) in British Columbia. The ideological and tactical divisions of the 1930s were contested during the 1910s and 1920s. The collapse of the One Big Union, combined with deteriorating relations with the Communist Party, shifted BC socialists away from industrial militancy and toward parliamentary forms of struggle.

Searching for the Springs of Health: Women and Working Families in Winnipeg's 1918-1919 Influenza Epidemic - Jones, Esyllt Wynne (University of Manitoba, 2003)
In the winter of 1918-1919, a pandemic of influenza crossed the globe, killing as many as 50 million people. This dissertation is a local study of influenza in Winnipeg, Canada. It dissects the social responses to the disease from four different perspectives: that of the public health and medical authorities; middle class Anglo-Canadian women volunteers who provided nursing care and material relief to the city's poorer influenza victims; working class and immigrant families; and organized labour. The dissertation argues that the influenza epidemic, coming on the heels of the devastating Great War, and arriving in the midst of class, ethnic, and gender conflicts, played a role in deepening the social cleavages of Winnipeg society in the period, particularly those of class and ethnicity. Class and ethnic tension was not the inevitable outcome of the epidemic. Rather, it was the result of the social inequality of the disease's impact–working families represented a disproportionately high number of influenza's victims–and the failure of public authorities to mount a compassionate and cooperative community effort to fight the disease. The volunteerism of middle class Anglo-Canadian women, too, failed to build the bonds of community. Labour believed that the state response to influenza was a betrayal of principles of justice and public good. Workers' families bore the brunt of public closures and layoffs. A spirit of mutualism sustained families and neighbourhoods through the disease, and contributed to the mobilizing successes of the workers' movement in 1918-1919. The trauma of the epidemic suggested the fragility of the social order, and workers' capacity to build an alternative society. Their vision of social transformation included the creation of the "springs of health": a living wage, quality housing, and equal access to a democratic medical system. Many working families, nevertheless, found it difficult to recover from the loss of spouses and children. Their stories suggest that influenza had a long-term impact upon the evolution of post-war Canada that we are only just beginning to understand.

Divided We Stand: A Study of the Development of the Conflict Between the International Union of Mine, Mill and Smelter Workers and the United Steelworkers of America in Sudbury, Ontario (1942-1969) - Miller, Jason A. (McMaster University, 2003)
During the height of the Cold War, a new form of conflict among Canadian workers emerged along political lines. In some cases, the major source of conflict shifted from that of union versus management to left-wing union versus right-wing union. This thesis focuses on such an inter-union battle between the International Union of Mine, Mill and Smelter Workers and the United Steelworkers of America in Sudbury, Ontario from 1942 to 1969. ln this analysis, which attempts to incorporate the perspectives of the unions, the mine operators, and the Catholic Church and its affiliate organizations, it will be shown that despite the profound influence of the union executives, the media, the Church, and other prominent figures, the final decision regarding which union to join was ultimately made by the rank-and- file members at Inco and Falconbridge (with the miners at Inco choosing the Steelworkers as their bargaining agent while the miners at Falconbridge chose to remain with Mine-Mill).
https://macsphere.mcmaster.ca/bitstream/11375/12227/1/fulltext.pdf

Workers, Labour Unions and the Law: Canadian Labour Unions in the New World of Bilateral Freedom of Association - Sauve, David (Carleton University, 2003)
What are the consequences for the Canadian Labour movement in holding contradictory positions concerning freedom of association? The research into this question conceptualizes Canadian unions as partners with capital and the state in a legally constructed regime of labour relations and collective bargaining. Pertinent Supreme Court of Canada cases concerning labour unions and freedom of association demonstrate that labour unions are inconsistent in their claims concerning freedom of association. This study reveals that while labour unions claim freedom of association is unilateral, that is, workers do not have a right to dissociate, the courts have found that freedom of association is bilateral and workers have a constitutional right to not associate or associate with whom they choose. To date, the courts have also found that infringing on workers' freedom of association is justified under the 'Charter'. However, in the future, the courts may well find these infringements are not justified.

Bankers and Bomb Makers: Gender Ideology and Women's Paid Work in Banking and Munitions During the First World War in Canada - Street, Kori (University of Victoria, 2003)
During the First World War, some Canadian women found themselves in new and unfamiliar environments, doing jobs apparently unavailable to them before the war. Many of those women were successful in the new opportunities available to them. The focus of this study is twofold. First, it examines the scope and the nature of women's work in two industries, banking and munitions, during the war. This is an important step because we still know very little about women's experience of the war. Understanding how many women worked and in what capacity is essential to understanding the nuances of women's wartime experience. Women who worked in banking and munitions were not a homogeneous group. The composition of the wartime workforce is also analysed. The war's impact on wage rates for women is also examined. Second, the study focuses on the nature of the impact of wartime participation on gender ideology. In particular, the study seeks to determine if gender ideology was affected by women's expanded opportunities in masculine occupations during the war. Often, the historiography regarding women and war is characterised by a binary discourse that seeks to determine whether on not wars liberate women. Rather than engage in that debate, this study attempts to avoid it as much as possible. Women's experience of the war in these two industries was complex. The study explores how women could both challenge and reaffirm ideas about gender; how attitudes towards and about women could change and remain the same; and how employee and employers alike strove to undermine and maintain the sexual division of labour and labour processes that were threatened by the entrance of large numbers of women into jobs defined as men's work. Women's participation both challenged and reinforced traditional notions about gender. Essentially, despite being successful ‘bankers’ women remained unsuitable for a career in banking. Similarly, regardless of their participation in munitions factories, metal shops remained no place for women. Quantitative, oral interview and qualitative sources including contemporary newspapers and magazines, were used. In particular, a great deal of the evidence was derived from several databases constructed for this project.

Class, Politics and Social Change: The Remaking of the Working Class in 1940s Canada - Camfield, David (York University, 2002)
This interdisciplinary dissertation aims to develop social and political theory capable of understanding social class as a structured process and relationship mediated by gender, race and other social relations and taking place in time and specific socio-material contexts, in order to analyse working classes as historical formations. It also aims to use this perspective and the existing body of historical scholarship to conduct a theoretically-rigorous study of the remaking of the Canadian working class in the 1940s. Arguing that recent theoretical work on class formation is inadequate, the dissertation critically appropriates ideas drawn from classical and contemporary scholarship to outline a theory of working classes as historical formations. An account of how dominant classes exercise power in capitalist societies is a necessary complement to this theory; the overview developed theorizes the existence of capitalist rule in differentiated forms and as inherently, but not primarily, ideological. From this perspective, the dissertation analyses the remaking of the Canadian working class in the paid workplace, community and household spheres in the 1940s. It argues that between 1941 and 1947 a broad but uneven process of class recomposition took place, focussing on such issues as the character of struggles in this period, their participants, their organizations and ideologies in order to illuminate the dynamics of change in working-class formations. In the course of struggle, both the working-class formation and capitalist rule were altered in important ways. The new formation that stabilized in the late 1940s featured improved living standards and greater unity against capital at the most elementary level. It was also shaped in important respects by a particular configuration of racist, sexist and heterosexist social relations. Unions changed from within and without, becoming generally committed to a responsible and bureaucratic practice. The CCF became the undisputed party of the English-Canadian workers' movement, weakening and marginalizing political radicalism. Although it is misleading to interpret this as working-class incorporation, working-class capacities to change society had been constrained and undermined in new ways, in part as a result of the very reforms workers wrested from employers and state power.

The Political Economy of Indian Health and Disease in the Canadian Northwest - Daschuk, James W. (James William) (University of Manitoba, 2002)
The dissertation identifies the origins of the present disparity of health conditions between Indian communities and mainstream society in western Canada. It examines the relationship between economics and health of Indian populations in the Canadian northwest from the early eighteenth century to the end of the nineteenth century. It documents the development of the fur trade in relation to changes in the geographical distribution of aboriginal societies resulting from the differential impact of introduced European diseases. For a period of one hundred and fifty years, infections that came as a consequence of trade were the primary source of mortality due to illness among First Nations. In addition, social pathologies resulting from European trade strategies affected the well being of communities in the northwest. Climate and environment contributed to the differential success of many groups integrated into the global economy through the fur trade. Canada's acquisition of the northwest changed this pattern. Its commitment to the terms of Treaties opened the west for agricultural development and settlement. The Dominion's development strategy, the National Policy, coincided with the extinction of the bison, undermining the ability of plains Indians to compel the government to deliver on their Treaty commitments. To facilitate the implementation of its economic and political order, the Dominion used its famine relief strategy as a means to subjugate them. By the early 1880s, tuberculosis emerged as a full blown epidemic among the Indians of the plains. The spread of tuberculosis through the Indian population of the plains was the result of the protracted period of malnutrition. Punitive measures imposed after the brief armed resistance to Dominion hegemony further weakened the population already largely infected with the disease. Severe mortality weakened the population already largely infected with the disease. Severe mortality resulted from the spread of acute infectious disease among the compromised population. Within fifteen years of signing Treaties many plains populations declined to their demographic nadir.

The Engineering of an Enemy: The Catholic Church, United Steelworkers, Canadian Labour Congress, and International Union of Mine, Mill, and Smelter Workers Local 598 - Enoch, Simon (McMaster University, 2002)
As global politics realized a fundamental realignment with the end of the Second World War, the Canadian state desired the formation ofa national consensus over its newly developed Cold War policies. It set about this task through the use of anti-communist rhetoric to facilitate a repressive and intolerant atmosphere where dissent of state policies could be identified as subversive and dangerous. In promulgating this Cold War ideology, Ottawa was wary of the illiberal approach that characterized American McCarthyism. Rather, Ottawa adopted a strategy of "privatizing" its anti-communism through the use of extra-state actors. By "farming" out its repressive activities, Ottawa could portray itself as a neutral defender of liberal values, while at the same time facilitating a climate of repression that would further its policy aims. Attendant to this, the extra-state actors used this state facilitated framework in order to advance their own interests and agendas. This strategy was starkly illustrated by the USWA raids against IUMMSW Local 598 in 1962. The interests of the state, the Catholic Church, CLC, and USWA coalesced around the elimination of Mine Mill local 598 as a representative of miners in northern Ontario. The Catholic Church sought the elimination of a progressive secularizing force in the Sudbury community that threatened the Church's institutional reproduction. For Steel, the acquisition of over 17,000 dues-paying members and the elimination ofIUMMSW as a competitor in the membership rich northern Ontario mining communities. While the state prospered from the virulent anti-communist environment and the elimination of a potentially militant union from control over the largest source of nickel in the non-Communist world. Thus the boundaries demarcating the state from civil society are less clear than some would have us believe. The USWA/Mine Mill events illustrate the nuance in the relationship between the state and private actors in the mobilization of ideological hegemony.

Representing Vancouver’s Working Girls, 1890-1930 - McMaster, Lindsey (University of British Columbia, 2002)
My dissertation addresses representations of the young women of Vancouver's working class, who, in the first part of the twentieth century, became touchstones for judgements on city life, work, and morality. Young, single, wage-earning women were something new and troubling to the middleclass administrators and social critics of the time. While the city's numerous single working men, with their overcrowded dwellings and tendencies to unionize, were considered somewhat disorderly, the necessity of their presence was never questioned. "Working girls,"on the other hand, seemed to embody all that was unnerving and unnatural about modern times: the disintegration of the family, the independence of women, and the promiscuity of city life. These kinds of anxieties were not unique to Vancouver: the issue of wage-earning women was deemed a "social problem" in various western cities. But Vancouver's singular geopolitical situation meant that these anxieties were exacerbated and amplified in distinct and curious ways. In 1922, for instance, a law was passed "for the protection of women and girls" which prohibited white women from working alongside Asian men. What combination of racism, paternalism, and moral panic gave rise to such legislation? And how did the women react to being controlled and judged by such assumptions? Rather than viewing the problems of wage-earning women as coextensive with those of working men - problems of wages, working conditions, and workers' rights - social administrators and reformers focussed largely on the moral implications of women's entrance into the workplace, particularly insofar as it represented a break from traditional Victorian ideals of domestic femininity. Denied the recognition afforded male workers as members of the labour force and economic agents, working women suffered various disadvantages in the workplace, their wages barely enough to survive on, and their rights as workers ignored by employers and union leaders alike. The tendency in historical accounts of Canada to overlook or underestimate the importance of women's work is undoubtedly in part due to the ideological disinclination to see or to represent women as workers rather than as wives and mothers. This is why my analysis focusses on the politics of gender and representation, for it is through representational conventions that women were pressured to embody a traditional domestic role, and likewise it is through a representational agenda that women were denied recognition as valuable workers.

Cross-Movement Coalitions and Political Agency: The Popular Sector and the Pro-Canada/Action Canada Network - Bleyer, Peter (London School of Economics and Political Science (LSE), 2001)
Through a historical account of the Pro-Canada/Action Canada Network (PCN/ACN), this dissertation examines coalition formation among social movements. It argues that the complex process of cross-sectoral coalition formation and thus the potential for convergence of social movements can best be understood by combining elements of different analytical frameworks. This dissertation draws on elements of the two dominant paradigms for the study of social movements, resource mobilization theory and new social movement theory. Specifically, it utilizes the formers' attention to the specifics of organization and structure and the latter's focus on the discursive formation of identities. Both are then combined with the uniquely Canadian but theoretically underdeveloped concept of the popular sector and a neo-gramscian perspective on social formation and mobilization that draws on political economy and class-analytical traditions. With its formation in 1988 around opposition to the Canada - U.S. Free Trade Agreement, the PCN/ACN was an early example of a broader trend for trade and investment to become key arenas for social and political contention at the turn of the century. This dissertation challenges the assumptions of most analytical frameworks concerning the limits to coalition formation and argues that the nature of the unifying issue is an important determinant of the potential for the growth and deepening of social alliances. After reviewing the historical conjuncture in which the PCN/ACN emerged, this dissertation traces the history of key sectors and member organizations - labour, women and ecumenical justice - paying specific attention to their approach to political engagement and the issue of free trade. As a result, it establishes the necessary background to understand both the initial basis for unity and the Network's progression beyond a lowest common denominator alliance around a single issue, to a broader mandate. This dissertation provides empirical evidence on which to judge the potential of social movements to displace other discourses and agencies on the left. Given the contemporary interest in the role of social movements, NGOs and civil society, this dissertation provides some essential signposts for two types of practitioners: academics seeking to understand outcomes and activists hoping to determine them.

A House Like No Other: An Architectural and Social History of the Ukrainian Labour Temple, 523 Arlington Avenue, Ottawa, 1923–1967 - Hunchuck, Suzanne Holyck (Carleton University, 2001)
Traditional architectural histories of Canada have tended to define the Ukrainian architectural presence only in terms of the sacro-religious or the rustico-picturesque. The more complex reality—that of the community's secularity, urbanity, and proletarianization throughout its history—is demonstrated by a third building type, the chytalnia or reading room, of which a Labour Temple is a socialist/pro-communist variant. These institutions were often found in urban centres where they were frequently located in industrial vernacular houses. Their study therefore confounds conventional notions of Ukrainian piety and rusticity, of a historical geography that consists exclusively of rural Prairie settlement, and of formalist paradigms regarding architectural form. Similarly, the architectural history of Ottawa has been predicated upon monumentality and picturesque settings to the neglect of regional vernacular forms, as well as upon a bilingual/bicultural ethnoculture that negates the polyethnic nature of the city. This study posits the Ottawa Ukrainian Labour Temple as a case study for exploring the limitations of traditional historiography regarding vernacular architecture, Ukrainians in Canada, and industrial vernacular housing in Ottawa.
Keywords: Communication and the arts; Ontario; Social sciences

On the Hook: Welfare Capitalism on the Vancouver Waterfront, 1919-1939 - Parnaby, Andrew (Memorial University, 2001)
In 1923, after nearly three decades of class conflict on the Vancouver waterfront, the Shipping Federation of British Columbia, an umbrella organization of shipping, stevedoring, and warehousing interests, undertook a far-reaching agenda of welfare capitalism. Drawing on wider currents of progressive reform which were cresting in the interwar period, and inspired by the example set by its counterpart in Seattle, the Shipping Federation created new joint political structures, adopted a range of paternalist initiatives, and decasualized the waterfront workplace. From its vantage point, this was a "good citizens" policy, and it was designed to: build bridges across the class divide, gain greater control of the work process, stave off the intervention of unions and the state, and, in the end, mould a more efficient and compliant waterfront workforce. The creation and implementation of this reform agenda, the ways in which white and aboriginal waterfront workers negotiated the politics of paternalism and labour market reform, and the long-term ramifications of this dynamic are at the core of this thesis. – Welfare capitalism shaped patterns of life and labour on the waterfront significant ways: informal ways of regulating the workplace atrophied; labourism was revived; and some waterfront workers acquired a reasonable standard of living. The trade-off at work, here, was this: only those employees who divested themselves of more radical political sensibilities, and adhered to waterfront employers' broader vision of an efficient, decasualized workplace, could hope to secure a living wage and fulfill their obligations as breadwinners, husbands, and citizens. For aboriginal longshoremen, most of whom were from the Squamish First Nation, this bargain was especially difficult to negotiate for it came freighted with the additional challenges associated with being "Indian" in a white society. Unlike their white counterparts who passed muster, they were marginalized from the waterfront during this time as decasualization's new time-work discipline conflicted with their more traditional sensibilities and ongoing need to work at a variety of tasks to ensure material and cultural survival. – Straddling labour history, aboriginal history, and the burgeoning literature on law and society, this thesis rejects conventional interpretations of welfare capitalism that conceptualize it as either a failed experiment in industrial democracy, or a drag on the emergence of the welfare state. In doing so, it re-positions welfare capitalism in the context of the wider return to normalcy following the Great War, and the powerful reform impulses that took aim at family, citizen, and nation. Rather than forestalling the welfare state, this citizen-worker complex–which manufactured a new sense of entitlement amongst white waterfront workers–was part of a broader cultural shift that would, after the trials of the Great Depression and challenge posed by the Communist Party of Canada, eventually underwrite the state's very expansion. On a broad level, then, this analysis illustrates how the prevailing liberal-capitalist order was successfully rehabilitated after the Great War and 1919, and how, in the long-term, it successfully contained, by consent and coercion, those forces which were antithetical to the prevailing economic and political status quo.
Keywords: British Columbia; Labor market reform; Paternalism; Social sciences; Vancouver; Waterfront; Welfare capitalism

"And There's Nothing Goes Wrong": Industry, Labour, and Health and Safety at the Fluorspar Mines, St. Lawrence, Newfoundland, 1933-1978 - Rennie, Richard Charles (Memorial University, 2001)
In 1933, an American entrepreneur offered the people of St. Lawrence, a small town on the south coast of Newfoundland, the prospect of escaping rampant unemployment and meager public relief by starting a mine to extract the area's vast deposits of fluorspar, which is used in the manufacture of steel, aluminum, and various chemical products. Coming in the context of the Great Depression and the collapse of the fishing industry, the mining industry was eagerly embraced by residents of St. Lawrence and surrounding communities. Several mines were subsequently established, by both the original American company, the St. Lawrence Corporation of Newfoundland, and later by the Aluminum Company of Canada (Alcan). The fragile prosperity that accompanied the industry from the 1930s until closure of the last Alcan mine in 1978, however, exacted a heavy price. Many St. Lawrence workers lost their lives to industrial diseases caused by dust and radiation in the mines. – This thesis explores the history of industry, labour, and health and safety at the St. Lawrence mines. This study focuses on the struggle by workers and their union for recognition of workplace hazards, improved working conditions, and adequate compensation for industrial disease victims and their families. The thesis argues that, rather than being passive victims of an unavoidable tragedy, workers at St. Lawrence were aware of the adverse health impacts of their work from the very early years of mining, and fought constantly over several decades to have their concerns addressed. Furthermore, the thesis argues that the disaster which ultimately unfolded at St. Lawrence was primarily the result of industry and government authorities ignoring or downplaying legitimate concerns and thereby shirking their moral and legal responsibilities.

Disorganized Labour: Canadian Unions and Constitutional Reform - Savage, Larry (Brock University, 2001)
Constitutional reform dominated the Canadian public policy agenda during the 1980s and early portion of the 1990s. As a pressure group operating within a federal system, the Canadian Labour Congress (CLC) has been unable and unwilling to confront the issue of constitutional reform. The CLC's confederal structure, combined with its political relationship with the New Democratic Party (NDP), has prevented the CLC from acting as a progressive force for positive constitutional change. Ideological and philosophical differences between the Quebec Federation of Labour and the NDP convinced the CLC to remove itself from the patriation debate in the early 1980s. Labour's short-sighted non-involvement in the process of patriating the Constitution eliminated the possibility of having collective rights enshrined in the Charter of Rights and Freedoms. Subsequently, the Supreme Court of Canada ruled that the right to strike and bargain collectively were not constitutionally protected. The Meech Lake and Charlottetown Accords provided organized labour with a renewed opportunity to promote a pro-union, class-based, constitutional rights discourse, but the CLC's internal cleavages over language, region, and identity, once again, proved too powerfiil a force to overcome. The Canadian labour movement's vision of social justice and economic equality has been obstructed by its unwillingness to adequately confront divisive constitutional issues. However, in an era of rights discourse and neo-liberalism, constitutional reform may provide organized labour with the best opportunity to have its voice heard.

"The Hand that Rocks the Cradle Rocks the World": Women in Vancouver's Communist Movement, 1935-1945 - Thorn, Brian T. (Simon Fraser University, 2001)
The period between 1935 and 1945 was a key one for the Communist Party of Canada [CPC or CP] due to the tumult of the Great Depression and the Second World War. Women were key players in the success that the CPC had during this period, one in which Communist and other left-wing movements grew and were more 'respectable' than they were during the Cold War that would follow. Yet women were secondary players in the Communist movement in Vancouver. While CP women played crucial roles in raising money for the Party, setting up fighting organizations such as the Vancouver Housewives league, and supporting the Allied war effort, CP members of both sexes pushed Party women into more traditional 'feminine' roles of wives, mothers, and ornaments. The Vancouver Communist Party offered a substantial challenge to Canada''s liberal state and the CP provided radical women with an outlet to channel their abilities against capitalism. In the end, however, the CP failed to alter substantially the fundamental division of labour between radical men and women. Communists upheld the mainstream doctrine of "separate spheres": they believed that men were workers, labour organizers, and producers while left-wing and working class women were domestic, passive, and consumers. This thesis concludes that while we cannot expect radical organizations to be completely separate from the gender ideals of the period in which they existed, the CPC did little to challenge traditional gender roles.

" Getting a Grand Falls Job": Migration, Labour Markets, and Paid Domestic Work in the Pulp and Paper Mill Town of Grand Falls, Newfoundland, 1905-1939 - Botting, Ingrid Marie (Memorial University, 2000)
While it has been generally understood that domestic service was an institution of particular importance to working-class women and to middle-class householders in North America in the late 19th and early 20th centuries, we still know little about the interwar years, a period during which the occupation declined in overall importance, but still defined many women's working lives. In the 1920s and 1930s, a vast majority of women who grew up in Newfoundland's coastal communities, where household production and the family fishery remained the mainstay of the economy, spent part of their lives performing domestic tasks for pay. To begin to understand the historical and cultural significance of domestic service to women's lives in Newfoundland, this dissenation uses a case-study approach. It focuses on the pulp and paper mill town of Grand Falls, where there was a steady demand for domestics by mill workers and their families, the town's elite, and hotels and boarding houses during the 1920s and 1930s. One of a number of single-resource towns supported by Newfoundland's economic diversification policies of the late 19th and early 20th centuries, Grand Falls was built in the interior of the island by the Harmsworth brothers of Britain in 1905. By tracing domestics' lives and experiences from countryside to company town, into the household = as workplace - and then into their married lives, the study explores themes relating to the gendered nature of uneven development. For instance, many Grand Falls employers shared much in common with the women they hired, in terms of religion, ethnicity and social origin., which raises interesting questions about the gender and class dimensions of an employer/employee relationship that has traditionally been characterized as one of domination and subordination. It also considers that relations of gender and class within the company town were formed in conjunction with factors such as migration patterns, pre-existing concepts of the gender division of labour within household production, company paternalism and social stratification within the workplace, the household and the town. The ways in which these factors overlapped and shaped the lives of domestics forms the backdrop of this study.

Le mouvement ouvrier montréalais, 1918-1929 : structure et conjoncture - Dansereau, Bernard (Université de Montréal, 2000)
Cette thèse traite de l'évolution du mouvement ouvrier montréalais de 1918 à 1929. Nous examinons les diverses organisations ouvrières, tant leur structure et leur composition, que les différentes idéologies qui coexistent dans les groupes ouvriers de la région montréalaise. Après avoir retracé les origines de ces organisations, leur évolution au cours de la Première Guerre mondiale, nous analysons leur développement au cours de la décennie qui suit la fin guerre. Nous cherchons, au delà des présupposés et des généralités, à comprendre le processus d'évolution du mouvement ouvrier montréalais. L'analyse de l'évolution des syndicats et des organisations politiques permet de saisir toute la complexité de rapports sociaux et les difficultés pour les travailleurs d'occuper une place significative. Notre analyse décrit aussi la place des diverses composantes nationales présentes dans le mouvement ouvrier montréalais. Nous insistons sur la place des travailleurs francophones et sur le rôle des travailleurs juifs jusqu'ici méconnu. Nous subdivisons cette tranche historique en trois périodes qui recoupent des conjonctures spécifiques. Les années de l'immédiat après-guerre sont marquées par une très forte agitation ouvrière alors que de très nombreux ouvriers et ouvrières se dotent de syndicats et revendiquent de meilleures conditions de vie et de travail. Le syndicalisme international de métier voit sa prédominance contestée par le syndicalisme canadien et le syndicalisme révolutionnaire. À droite de l'échiquier syndical, le syndicalisme catholique s'installe définitivement au Québec et constitue une des caractéristiques majeures du mouvement ouvrier québécois. L'effervescence ouvrière ne débouche pas sur des organisations politiques fortes malgré l'existence d'un parti ouvrier qui obtient quelques gains électoraux alors que les organisations de gauche doivent se réorganiser, victimes notamment de la répression gouvernementale et patronale. La crise, qui s'enclenche dès le milieu de 1920, affecte considérablement des organisations ouvrières lorsque le capitalisme tient à revenir aux situations qui prévalaient avant la guerre. Les organisations syndicales cherchent à résister à cette stratégie mais le nombre de syndicats décroît. Toutefois, cette baisse du membership syndical ne ramène pas le nombre de syndiqués au niveau de 1913 parce que, parmi les syndicats apparus dans la foulée de la révolte ouvrière, de nombreux syndicats résistent efficacement, dont des syndicats canadiens et des syndicats catholiques. La gauche se réorganise autour du Parti communiste canadien, creusant un fossé entre eux et le reste des militants ouvriers. Le Parti ouvrier du Canada entreprend sa lente marginalisation. Au milieu de la décennie, profitant d'une reprise économique, le mouvement ouvrier se relève. Les syndicats se réorganisent, leur membership augmente et leurs revendications deviennent plus offensives montrant ainsi un regain de militantisme. Mais les divisions s'accentuent dans les rangs syndicaux alors que les syndicats canadiens et catholiques contestent de plus en plus le leadership occupé par les syndicats internationaux de métier. Au plan politique, le Parti communiste occupe pratiquement toute la place, les socio-démocrates se voyant relégués à quelques bastions.
https://doi.org/1866/28793

The New Democratic Party and the Union Vote. - Dowler, Kevin John Gordon (University of Windsor, 2000)
The following study examines the NDP and the union vote. The NDP and labour unions have been officially linked since the NDP's formation in 1961. Despite the initial optimism of the NDP-labour link, the change from the CCF to the NDP has resulted in limited electoral success, especially at the federal level. The partnership between labour and the NDP has met with limited electoral fortunes. Although their tendency to vote NDP is higher than that of other groups, the vast majority of union members still vote for other parties. Federal election studies have repeatedly shown that 10 percent of non-union members, 20 percent of union members, and 30 percent of NDP affiliated union members vote for the NDP. The question is why do the remaining 70 to 80 percent of union members fail to vote for the NDP. This study aims to address this problem using survey research. The first chapter reviews the link between the NDP and labour and voting determinants in Canada. The second chapter looks at the research design and methodology of this thesis. Chapter three and four examines the results of the statistical analysis. Finally, chapter five summarizes with a discussion and concluding remarks.

Devenir seigneur en Nouvelle-France: mobilité sociale et propriété seigneuriale dans le gouvernement de Québec sous le régime français - Grenier, Benoît (Université Laval, 2000)
Analysant la mobilité sociale dans le gouvernement de Québec sous le Régime français, ce mémoire aborde la propriété seigneuriale en tant qu'illustration de la promotion sociale dans la vallée du Saint-Laurent au XVIIe et au XVTIIe siècle. Cette analyse, portant sur une soixantaine d'individus aux origines modestes, issus notamment de la paysannerie, ayant accédé à la propriété seigneuriale, se veut une contribution a l'étude de la promotion sociale en Nouvelle-France. Quatre parties constituent l'essentiel de ce mémoire. L'origine de ces individus et les modes d'élévation sociale sont étudiés dans une première servant de cadre contextuel et de présentation sociodémographique. Les trois chapitres suivants visent à répondre plus directement à la problématique de l'étude, à savoir l'impact socio-économique de la propriété seigneuriale chez ces seigneurs aux humbles origines. La durabilité de la propriété seigneuriale, ainsi que le fait d'y résider ou non et le peuplement de la seigneurie sont les éléments étudiés dans le deuxième chapitre. Le troisième chapitre aborde la question du prestige tributaire de la seigneurie, en s'intéressant aux appellations attribuées aux seigneurs, de méme que les fortunes seigneuriales, pour connaître l'incidence économique de la propriété seigneuriale. Dans un dernier temps, le quatrième chapitre met en relief les alliances matrimoniales des familles seigneuriales, également révélatrices du possible impact de la possession d'une seigneurie. Au sein de cette société française d'Ancien Régime, transplantée sur les rives du Saint- Laurent, d'importantes mutations s'opèrent. L'une de ces transformations est perceptible par la plus grande possibilité de mobilité sociale, quasi inexistante en France. Par l'analyse des destins d'hommes dont la naissance ne laissait en rien présager un tel parcours, ce mémoire vise a comprendre l'enjeu de la propriété seigneuriale pour de tels individus ainsi que ses répercussions.

Days and Nights: Class, Gender and Society on Notre-Dame Street in Saint-Henri, 1875-1905 - Lord, Kathleen (McGill University, 2000)
The everyday life of people on the street has not received the attention it deserves in the history of late nineteenth and early twentieth-century Quebec. This dissertation joins a small number of recent studies which redress this omission. It makes a significant contribution to existing examinations of North American cities and Canadian social history through the use of categories which are rarely employed and questions that are seldom posed in investigations of working-class history during the period of industrialization. A holistic treatment of Marxist philosophy provides the theoretical underpinnings for a sensitive engagement with daily street life in an urban milieu. As a site of intense sociability, Notre-Dame Street, the main street of the industrial suburb of Saint-Henri, offers a unique perspective on the intricate use of public space and its relations to social space. This thesis covers the period between the years of town incorporation in 1875 and annexation to the City of Montreal in 1905. Notre-Dame Street underwent significant transformations in this period. A main street of a small town on the outskirts of Montreal became the principal commercial street of a bustling industrial city. The 1890s was a decade of particularly marked shifts, characterized by significant population growth and dramatic changes in physical form. Class and ethnic tensions intensified as a result. A 1891 labour dispute at Merchants Manufacturing, a textile factory, took to the streets, and the local elite contested George A. Drummond's refusal to pay municipal taxes in 1897. Resistance to monopoly control of utilities was evidenced by the use of petitions and protets or notarized letters. Workers' parties, journalists, and municipal reform leagues increasingly challenged the hegemony of the local elite whose persistent practices of overspending resulted in a substantial debt and annexation. The study of a local street in an industrializing community demonstrates the prevailing social and political distribution of wealth and power. It reveals significant differences between the various class ideologies which were played out in the management of the public space of the street. An economic liberal ideology was instrumental to the development of the modern Western city through the creation of divisions between public and private spaces. Social usage, the visible presence of the working and marginal classes and women on city streets, suggests a different reality. A reconstruction of daily street life from a diversity of written and visual sources indicates that women, men, and children inhabited and frequented homes, shops, and offices, travelling to and from work, and various places of recreation. The rhythm of everyday street life was punctuated by unusual events of a celebratory, criminal, and tragic nature, which emphasize the connections between spatial structures and subjective experience. The local management of public space thus involved class antagonisms, characterized by negotiation, transgression, and resistance. This dissertation argues that the politics of this public space benefited the class interests of a grande bourgeoisie of Montreal and a local petite bourgeoisie, to the detriment of the working classes. These conflicting class interests were played out in a variety of different ways. The exclusion and appropriation of social and symbolic spaces were characterized by distinct property ownership and rental patterns. An anglophone grande bourgeoisie of Montreal owned vacant and subdivided lots. A francophone petite bourgeoisie dominated property ownership, and a majority of renters lived in flats on the main street and on adjoining streets. The shaping of the physical infrastructure was distinguished by the growth of monopolies and minimal local intervention. The civic manifestation of the ordered and ritualistic celebration of the parade emphasized a Catholic identity. Attempts to impose an appropriate and genteel code of behaviour on city streets led to the moral regulation and social control of criminal behaviour.
OCLC: 56684820
Keywords: Academic Dissertation; Academic theses; Thèses et écrits académiques

Leadership and Staff in the Union of Northern Workers from 1967 to 1996 - Powell, Christopher William (Memorial University, 2000)
The Union of Northern Workers, known as the Northwest Territories Public Service Association prior to 1987, is the largest labour union in the Northwest Territories. Northern labour is a little explored field in Canadian history, and as such, this work surveys new ground. Trade unionism in the North's private sector began at the close of the Second World War. The UNW, however, like most public sector unions in Canada, had its roots in the 1960s. This study examines issues pertaining to the union's leadership and staff from 1967, when correctional workers in Yellowknife first organized, until the 1996 convention, when the union took steps to divide into two separate unions in anticipation of the creation of Nunavut in 1999. From its start, the union's geographic jurisdiction distinguished the UNW as unique among Canada's public service unions. It and its predecessor, the NWTPSA represented workers in Canada's most northern reaches. The challenges of life in the North were as real for the union as they were for its members. A relatively small membership spread across such a huge land mass presented obstacles with regards to leadership and service. Also, cultural factors differentiated the organization from others. With an increasing native membership, mostly Inuit, lnuktitut became the union's second language. Distinguishing the union institutionally was its component status within the Public Service Alliance of Canada. The quality of the relationship between these two bodies regularly fluctuated between excellent and belligerent. Similarly, the union's relationship with the Nonhwest Territories Federation of Labour degenerated from founding member to pariah status, in spite of the UNW comprising the overwhelming majority of the Federation's membership. As the union grew from a fly-by-night, seat-of-the-pants organization of less than 100 members at its inception, to over 5,000 when it divided, leadership and staffing gained increasing importance. To meet the challenges of representing northern workers, the union increasingly attempted to professionalize its leadership cadre. The effect of this was an increasing distance between members and leaders which ultimately resulted in the secession of the Nunawt membership.
Keywords: Northwest Territories; Social sciences

"Support Pending": The Canadian Autoworkers' Struggle for Adjustment Assistance at a Time of Industrial Change, 1960-65 - Roy, James A. (Carleton University, 2000)
In 1960 the Canadian United Auto Workers suggested to the government that in order to save the automobile industry, rationalization with the American industry was a viable and desired option. Over the next five years, as the government gradually moved towards integration, the union stood behind the principle, yet at the same time stated tha protection for dislocated and laid-off workers must be part of the deal for union support to be forthcoming. The union, which felt that the costs of government-induced layoffs should be fully borne by the state, did not waver in its commitment to securing safeguards, even though from 1960 to the Auto Pact in 1965 it became increasingly apparent that the granting of adequate protection was not on the government's agenda. The layoff of 1,600 workers in 1965 resulted in the withdrawal of Canadian UAW support for the trade deal and highlighted the significance and importance of the over-riding condition of support, the protection of workers from the consequences of state actions.

Deploying Discourses of Employability and Domesticity: Women's Employment and Training Policies and the Formation of the Canadian Welfare State, 1935–1947 - Stephen, Jennifer Anne (University of Toronto, Ontario Institute for Studies in Education, 2000)
The period 1935 to 1947 provides an excellent opportunity to investigate the ways in which the employment and training policies of Canadian welfare state forms delineated the boundaries of gender, race, class and nation in ways that actively constituted (il)legitimate social and economic forms of work, of motherhood, of sexuality and citizenship. Covering attempts starting in the Depression and accelerating during the Second World War into the postwar period, this study tracks the constitution and deployment of government attempts at mapping the female labour supply, of monitoring the activities of women in the labour market, of charting and opening up to scrutiny the conditions of women's labour force attachment: all in an effort to predict and prescribe patterns of women's employment and problems of female unemployment. I approach government reports, studies, commissions and committees as policy events—exercises in governance—as markers for policy analysis which signified important shifts in governmental approaches to the phenomenon of female participation in the formal waged economy. Viewed during the war as a crucial national resource, central to the war effort, women war workers would be cast as a largely ‘unskilled female labour reserve’ by war's end. I examine how ideas about mental testing, intelligence and human capacities—ideas that comprised the foundation of the mental hygiene programme during this period—informed employment and training policies in the formation of the Canadian welfare state for the period 1935–1947. During the Depression, studies of the labour force produced classifications of unemployed women and men. Scrutiny of female employment patterns resulted in the production of categorical knowledges about employability. These practices were further elaborated through the unprecedented research opportunities presented by the war. Suitable vocation, aptitude, and measures of intelligence: these concepts were drawn upon as part of a growing apparatus of employment policy intended to facilitate the smooth transition into the postwar period. I argue that the roster of policies and programmes devised in the name of postwar rehabilitation constituted ideas about female employability which were deeply imbued with the principles of scientific racism and sexism at the core of the mental hygiene program. Vocational planning, counselling and training practices reorganised relations of employment and of unemployment in ways that reflected the managing principles of the risk society. Postwar planning drew upon and constituted new areas of activity for government and community agencies, creating opportunities for the deployment of knowledge-practices such as personnel selection while opening up the interior of the subject as an object of governance, by assessing and calibrating allegedly innate human capacities.
Keywords: Domesticity; Education; Employment and training policies; Social sciences; Welfare state; Women

The Workers' Educational Association: A Study in Social Change and Resistance in Canadian Working Class Culture. - Benjamin, Amanda (Concordia University, 1999)
This thesis examines the effects of the Workers' Educational Association of Toronto (WEA) on social change in Canada between 1917-1945. This study attempts to establish the social importance of this organization in the history of adult education in Canada. The WEA was an educational organization that attempted to provide a link between labour and learning by making educational opportunities available to the working class. The data for this study were obtained from an analysis of the Ontario and Canadian WEA archives. The thesis first examines the history of the WEA and demonstrate its place in the history of adult education in Canada. Secondly, this study suggests that the WEA was the impetus for change in Canada, and in particular for Toronto's working class. The study found that the WEA used a form of critical pedagogy to achieve its goals which brought about social change. This study reinforces the usefulness of critical pedagogy as an approach for adult education when social change is an objective.

From Protest to Powerlessness: A Marxist Analysis of the Ontario NDP - Crow, Daniel W. (Brock University, 1999)
Using Marxist state theory as an analytical framework, this thesis explains the problems faced by the Ontario New Democratic Party government (1990-1995) in implementing a social democratic agenda. Not only was the government constrained in its ability to implement progressive policy, but it was also pushed to implement a Social Contract (involving legislated wage cuts to public sector employees) that alienated the party's base of support, making it more difficult for the party to organize in the future. Although this study relies predominantly on a reinterpretation of existing research on the topic, some primary research is used in the analysis, including interviews with members of the labour movement and former MPPs and analysis of the news media's treatment of the party/ government. Historical and class analytical perspectives are used to explain the evolution of the ONDP's structure and policies, as well as to assess the relative strength of the working class and its ability to support a social democratic political agenda. It was found that the ONDP' s unwillingness to develop a long term plan for social democracy, and its inability to act as a mass party or to build a strong working class movement, made it more difficult for the party to succeed when it formed the government. Moreover, the class nature of the capitalist state, along with pressure exerted by a well mobilized capitalist class, worked to limit the government' s options.

"Trouble Enough": Gender, Social Policy and the Politics of Place in Vancouver and Saskatoon, 1929-1939 - Healy, M. Theresa (Simon Fraser University, 1999)
Relief policy in English Canada in the 1930s was the forerunner of the Canadian welfare state. As practised, the strength of relief lay in local responsibility but this was also a weakness. The aims of relief policy were undermined by the politics of place: the impact of specific historical and spatial circumstances at the local level. Relief policy was not uniformly enforced nor were the outcomes exactly as intended. The objectives, to provide minimal necessities, to exclude individuals and families from relief rolls, to control gender and familial roles, and to impose middle class societal prescription, were not met. Instead, a complex negotiation of responsibilities and expectations was undertaken. Relief recipients, were able to win some concessions. Further, the fragility of social categories used to implement relief policies was crystallized. The conflict between the ideals of policy and people's realities becomes apparent when two very different cities are compared. Using extensive oral history interviews and contemporary relief policy documents and relief department records, this research shows that while the principles of relief were almost identical in Saskatoon and Vancouver, the practice of relief in these two cities revealed the dependency of relief policy upon face to face delivery. Designed to eliminate potential abuse by recipients, the system barely controlled it. Further, local responsibility also ensured that citizens had access to the mechanisms of local politics and tools for change. The local population in Saskatoon was able to win considerable and significant improvements to relief while Vancouver's system remained virtually untouched, in spite of dramatic and revolutionary local activities which reached the national stage.

Between the Scylla and Charybdis of Anarchy and Despotism: The State, Capital, and the Working Class in the Great Depression, Toronto, 1929-1940 - Klee, Marcus Aurelius (Queen's University, 1999)
The Great Depression of the 1930s was the culmination of severe contradictions building within a maturing capitalist world economy, and has been credited, in conjunction with the Second World War, for structuring the post-war compromise around a national welfare state, full employment, Keynesian fiscal policy, demand management, and the expansion of trade union rights. Despite the importance of this decade in Canadian history, and the highly developed literature on the Roosevelt administration and the American New Deal, few writers have attempted to probe the finer contours of the Great Depression in Canada. This thesis is broadly structured around the threat of social disorder which state officials and social workers perceived to be rooted in the economic malaise of the decade. Attempts to manage the poor through municipal welfare schemes and efforts to regulate the family through newly developed “socialized tribunals” were paired with a campaign to contain juvenile delinquency and structure the leisure time of working-class adolescents. The order that social workers sought to impose on the working-class family and child was materially related to struggles to bring order to the economy. The ideological retreat from laissez-faire capitalism by business and the state coalesced with a burgeoning and militant union movement that propelled the state towards active intervention in the economic, social, moral, and political relations of capital and labor. Pushed in part by an escalation in strike-related violence, the state tentatively embarked on a program of economic control through the Industrial Standards Act, opened legal space for union activities, and attempted to introduce the first minimum wage for male workers. The thesis explores the role of unions, representing both men and women, skilled and unskilled, in structuring the re-organization of capitalism in Toronto's transportation, construction, and service industries, yet draws upon the paradigm of state-centered regulatory regimes which emerged in the state's treatment of the unemployed, the family, and youth. Policies designed to contain 'chiseling' employers, wayward youth, and cheating husbands all faltered because the state was unwilling or incapable of stepping too heavily into the private sphere or interfering with the prerogatives of private property. The resulting half-measures produced a set of contradictions inherent in initiatives designed to accommodate both labor and capital and generated intense struggles against the 'sweatshop,' while bringing the twin issues of the family wage and relief-subsidized competition to the forefront of political and economic mobilization. The largely ineffectual attempts to bring order to political, economic and social life witnessed the emergence of a nascent regulatory state, tied to significant pockets of organized capital, and contingently supported by organized labor. This particular constellation of social forces not only attained a degree of ideological prominence during the depression, but was of profound importance in shaping the second-half of the twentieth century.
Keywords: Anarchy; Capital; Despotism; Great Depression; Ontario; Social sciences; State; Toronto; Working class

La carrière polyvalente de Gustave Francq, figure marquante du syndicalisme international au Québec (1871-1952) - Leroux, Éric (Université de Montréal, 1999)
Cette thèse porte sur la carrière du syndicaliste Gustave Francq (1871-1952). Grâce aux nombreux postes d'importance qu'il a occupés dans le mouvement syndical et à la visibilité qu'il a obtenue par la publication d'un journal hebdomadaire durant près de 30 ans, Francq est considéré comme une figure marquante du syndicalisme international au Québec dans la première moitié du )0(e siècle. Personnage polyvalent, il se distingue des autres syndicalistes de son époque, entre autres, par la multiplicité de ses champs d'intérêt: typographe et syndicaliste, il compte aussi à son actif une carrière d'homme d'affaires, de journaliste, de militant politique et de haut fonctionnaire au gouvernement du Québec. La thèse vise à rendre compte du personnage dans sa globalité et sa complexité, c'està-dire en examinant tant sa vie professionnelle que sa vie privée. Pour ce faire, nous abordons sa carrière sous trois angles: l'action syndicale, l'action politique et l'action sociale. Au Québec, il est certes l'un des plus importants défenseurs du syndicalisme de métiers et de la Fédération américaine du travail (FAT). Il prône l'organisation des travailleurs sur la base des syndicats de métiers, reconnaît la légitimité du système capitaliste, favorise les relations harmonieuses entre le Capital et le Travail et témoigne d'une grande confiance dans l'État comme arbitre des relations de travail. À cet égard, il se distancie des positions fondamentales du syndicalisme de métiers, telles que défendues par la FAT. Au début de sa carrière, Francq touche à l'action politique ouvrière. Défendant des positions travaillistes, il dirige le Parti ouvrier de Montréal de 1906 à 1916 et s'oppose systématiquement aux socialistes. Il remet cependant en question son engagement politique entre 1916 et 1921 avec la montée des socialistes au sein du Parti ouvrier et la multiplication des défaites des candidatures ouvrières. 11 se rapproche alors considérablement du Parti libéral avec lequel il a des affinités. Sur le plan social, il mène plusieurs combats depuis le début du siècle pour améliorer les conditions de vie de l'ensemble de la classe ouvrière. Ses principales revendications touchent la réforme du système scolaire québécois, la démocratisation de l'administration municipale montréalaise, la promotion des coopératives de consommation et de production et l'amélioration de la législation des accidents de travail. Au cours de sa carrière, Francq siège donc à diverses commissions gouvernementales comme la Commission fédérale d'appel du travail (1918), la Commission de la charte de la ville de Montréal (1920), la Commission des accidents de travail (1923) et la Commission du salaire minimum des femmes dont il occupe la présidence de 1925 à 1937. Intellectuel du mouvement ouvrier, Francq défend des positions libérales et travaillistes au début du siècle, pour évoluer progressivement vers une position de libéral réformiste au tournant des années 1920. Or si sa conception de l'action politique ouvrière se transforme rapidement au lendemain de la Première Guerre mondiale, il témoigne d'une grande fidélité idéologique tout au long de sa vie à l'égard du syndicalisme de métiers et de son rôle de réformateur social. Croyant à la nécessité et à la possibilité d'améliorer le système socio-économique et les institutions politiques, il est animé de préoccupations sociales majeures axées sur une meilleure répartition de la richesse et un engagement substantiel de l'État dans le champ des politiques sociales. Malgré leur importance numérique, peu d'historiens se sont penchés sur l'étude des syndicats internationaux au Québec, et ce, même si leurs effectifs dépassent largement ceux des syndicats catholiques depuis le début du siècle. S'inscrivant dans le renouvellement des études à caractère biographique, notre thèse vise donc à mettre de l'avant la carrière d'un des principaux dirigeants du syndicalisme international au Québec.
https://doi.org/1866/28812

Defining Work: Gender, Professional Work, and the Case of Rural Clergy - Mellow, Muriel (McGill University, 1999)
The goal of this thesis is to question conventional definitions of work through the detailed study of a professional group—specifically rural clergy—whose work falls outside the parameters of accepted definitions of work. According to the feminist literature, work and non-work are differentiated typically by dichotomies which privilege a masculine model of work and devalue women's experience; thus, "real work" is defined as an activity which is paid rather than unpaid, public rather than private, instrumental and intellectual rather than emotional. Professional work definitions also obscure the way in which "work" relies on activities which are linked with the feminine in these dichotomies. Through in-depth qualitative interviews with rural clergy, I explore the extent to which women and men draw on these gendered dichotomies to define work. In some ways, the approach of clergy counters conventional work norms: for them, emotional labour is a priority, work is not limited to a specific time or place, and public and private lives frequently overlap. I demonstrate how clergy define their work in terms of obligation, context, visibility, and time. Furthermore, I also argue that clergy delineate work in terms which still reflect a masculinized work norm specific to their profession. This "clergy masculinized mode" professionalises emotional labour by separating it from the facilitating work of female volunteers; it assumes a worker free from domestic demands in order to fulfil professional obligations within a flexible time frame; and it overlooks how the overlap of the public and private spheres is sustained by the work of wives. Thus, delineating work is particularly problematic for female clergy because professional demands are confounded with demands for adjunct work typically performed by women. My findings (1) highlight alternative markers of work which are suggestive for feminist theory; 2) point to a gap in theorizing about the gendering of work when conventional dichotomies fail to reinforce each other (as in the case of public, yet unpaid, volunteer work); and 3) recognize the possibility that varying masculinities define work.
OCLC: 721250783
Keywords: Electronic Thesis or Dissertation; Rural clergy; Sex role in the work environment

Paternalism and Identity: The Role of Personal Labour Organization in the Formation of Group Identity Among the Metis in the Rupertsland Fur Trade and the Aboriginal People in the Northern Australian Cattle Industry - Parker, Leanna (University of Saskatchewan, 1999)
The question of the origins of a Metis identity in Canada is one that has been contemplated by several scholars. These scholars have taken various approaches to the question, many focusing solely on the social and political aspects of Metis history. While such approaches can be useful, they ignore the crucial influence of the economic and labour relations of the Rupertsland fur trade in the development and expression of a distinct Metis identity in western Canada. The unique economic and labour relations of the Rupertsland fur trade, identified by H. Clare Pentland as personal labour relationships, allowed a cohesiveness and inter-connectedness to develop between the Aboriginal labourers and their European employers which emphasized the interdependencies inherent in the industry. However, while personal labour relations were an important catalyst for the development and expression of a distinct Metis identity, it is too simplistic to suggest that it was these relations alone that encouraged such a phenomenon. The northern Australian cattle industry utilized similar economic and labour relations and yet a distinct mixed descent identity did not develop in Australia. Therefore, the external influences in the industry must also be examined. The four most important external influences that encouraged the development of a Metis identity in Canada and discouraged a similar event in Australia were: the needs of the colonial employers in regards to land tenure; the economic opportunities available to the people of mixed descent; the educational opportunities available to the people of mixed descent; and, the time depth of contact in both industries. These four external influences combined with the use of personal labour organization in the Rupertsland fur trade encouraged the development and expression of a distinct Metis identity in Canada.

Organizing the Bench: Medical Laboratory Workers in the Maritimes, 1900–1950. - Twohig, Peter Lawrence (Dalhousie University, 1999)
Medical laboratory technology is the third largest health profession in Canada. Yet, these workers are largely invisible, both to the public and historiographically. Even recent studies of laboratory medicine make only fleeting reference to workers at the bench. This study examines the origins of the laboratory workforce at the Pathological Institute in Halifax in particular, and the Maritime provinces more generally. It utilizes hospital, university and archival records to demonstrate how this workforce was created as part of a "health care team" and the implications this had for the workers themselves. As Canadian hospitals grew in number and bed capacity over the opening decades of the twentieth century, they also grew in complexity. Hospitals added new services, including departments such as dietetics, x-ray and expanded laboratory facilities. As these services matured, the routine work passed from physicians working alone to specially trained workers. Yet, this process was not uniform and remained remarkably incomplete. In the first half of the twentieth century, laboratory workers did not share a common education, training experience, or labour process. Hospital workers in the Maritimes and elsewhere did not necessarily perform discrete tasks and many, notably nurses, assumed duties in the laboratory. The workers themselves had diverse educations and work experiences. Well into the 1950s, the "laboratory worker" was a diffuse concept. The demands of patients and physicians for enhanced services, the constraints of budgets, recruitment and retention problems, and the interests and desires of workers themselves combined to shape laboratory work. Viewed from the laboratory, the story of the twentieth century Canadian hospital is not one of ever-expanding specialization, but rather a complex milieu where the social relations of skill and gender found bold articulation.
Accepted: 2014-10-21T12:35:52Z

The Transformation of the Canadian Labour Movement from International to National Union Dominance: Tracing the Roots of Breakaways - Duff, Lenore (Carleton University, 1998)
This thesis examines the dramatic shift from international to national union dominance in Canada. Within this context, this analysis explores breakaway activity, and discusses the broader significance of this phenomenon in relation to the labour movement in Canada. It identifies factors critical to the development of international unions. and factors related to their decline, both in Canada as reflected in breakaways, and in the United States as reflected in the general decline of the labour movement. and concludes that contextual factors and individual responses have been central to this process. Ultimately. this thesis illustrates existing distinctive elements of the Canadian labour movement. and suggests that these became more apparent over time. It identifies changes that occurred in objective and subjective conditions that led to the expression of this distinctiveness in a series of breakaways that contributed to the 'Canadianization'. if not the dramatic differentiation, of the labour movement in Canada.

The International Unions and the Workers' Revolt in Quebec, 1914-1925 - Ewen, Geoffrey (York University, 1998)
This thesis contributes to our understanding of both international unionism and of the labour revolt in Quebec, two neglected areas in Quebec labour history. It examines the industrial conflict of the war years and the post-war revolt in 1919 and 1920, a period of militancy characterized by rapid trade union growth and aggressive strike action by international unions. During the same period workers renewed their interest in independent political action and briefly attained a small measure of success. A major focus of this study is the ethnic, religious, political and gender divisions within the international unions and the labour party in Quebec. The labour revolt was, however, ultimately unsuccessful. While this was because employers were generally stronger than organized workers, especially in the depression of the 1920s, it also faltered on profound divisions within the Quebec working class. The emergence of a Catholic labour movement as a serious rival to secular international unions created one of the most important divisions within the Quebec working class. This thesis constitutes a significant revision to our understanding of the formative years of this confessional movement. While there is a large body of work on Catholic organizations, few studies have examined either their role in the 1919 labour revolt, or the specific nature of the rivalry with the international unions. Inter-union rivalry in the years from 1916 to 1925 is an important theme of this study. Catholic union promoters conducted an experiment in the industrial relations of social harmony which involved attempting to replace class conflict with harmonious relations with employers. While eschewing strike action, Catholic unions and their supporters often helped employers undermine international union strikes in the hope of destroying and supplanting the more aggressive secular organizations. The result was that the Catholic labour movement impeded the growth of the American-based unions and contributed to the defeat of the workers' revolt.
Keywords: Catholic labour movement

Activists in the Age of Rights: The Struggle for Human Rights in Canada, 1945-1960 - Lambertson, Ross (University of Victoria, 1998)
From 1945 to 1960 Canada began to move into what has been called “the age of rights.” At the end of the Second World War the nation paid lip service to “British liberties,” but both the state and private individuals frequently violated the libertarian rights of political radicals as well as the egalitarian rights of certain unpopular ethnic and religious minorities. By 1960 a discourse of human rights had largely replaced the British liberties approach, and the country enjoyed a far higher level of respect for minority rights, in part because of a number of legal changes—Supreme Court decisions, anti-discrimination legislation, and a Bill of Rights. This dissertation examines this shift, focussing upon the activities of members of the Canadian “human rights policy community.” Relying largely upon primary resources, it presents a number of case studies, demonstrating how human rights activists dealt with the deportation of Japanese Canadians, the Gouzenko Affair, the problem of discriminatory restrictive covenants, the Cold War, the need for an effective fair accommodation law in Ontario in general and the town of Dresden in particular, and the struggle for a bill of rights. In presenting these case studies, this dissertation also focusses upon the activities of a number of key interest groups within the human rights community: the coalition known as the Cooperative Committee on Japanese Canadians, the Canadian Jewish Congress, the Jewish Labour Committee, and a number of civil liberties organizations (especially the liberal Civil Liberties Association of Toronto and the communist Civil Rights Union). Attention is paid to the reasons for their successes and failures; within the general context of economic, social, and cultural changes, special attention is paid to the way in which these interest groups made their own history, using their own history, using the resources available to them.

Workin' on the Contract: St Lucian Farmworkers in Ontario, A Study of International Labour Migration - Larkin, Sherrie N. (McMaster University, 1998)
This dissertation examines the seasonal round of St Lucian contract workers who travel to Ontario every year for temporary employment in the Foreign Agricultural Resources Management Service program (FARMS). The study's focus is divided among Ontario growers as employers, St Lucian agricultural workers as employees, residents of a rural town in Southwestern Ontario, and governmental departments that influence the FARMS program in Canada and in St Lucia. The main argument of the dissertation is that labour migration has been an integral part of St Lucian history since emancipation on the island. It is both an economic strategy and a symbol of the freedom emancipation promised. While factors external to the island, such as the need for agricultural labour in Ontario and a long history of connections between Canada and the British West Indies influence where St Lucians travel, the propensity of these men and women to leave the island and return can only be explained in terms of St Lucia's history as a British colony. Within this history, labour migration emerges in conjunction with other strategies of enduring yet resisting the plantation economy that characterized the island for centuries. Although "workin' on the contract" in Canada is used by St Lucians for individual social and economic goals, it derives its meaning from the shared cultural beliefs and values of the island's society.
Accepted: 2014-06-18T17:05:31Z

Farm Wives' Work: A Comparative Study of Dairy and Potato Farming in New Brunswick, Canada - Machum, Susan Tracey (University of Edinburgh, 1998)
Using a comparative case study research design, the thesis examines the similarities and differences in farm wives' work on family owned and operated dairy and potato farms in New Brunswick, Canada. New Brunswick, Canada was selected as the research site because of the opportunity it provided to study two highly contrasting but comparable farm industries. Potato production is an intense and seasonal process, involving the planting, tending and harvesting of a field crop. Dairy farms are all-year operations involving animal husbandry and milk collection on a daily schedule. Potatoes are sold in 'open', uncertain markets; milk is sold in a 'closed' market protected and regulated in the provincial Milk Marketing Board. The differing labour demands, marketing arrangements and other conditions surrounding the production and sale of milk and potatoes made them ideal industries to study the effects of a farm's commodity on farm wives' work. The family, farm and work histories of fourteen farm wives on potato farms and sixteen farm wives on dairy farms were gathered, between November 1995 and September 1996, using an in-depth, open-ended interview format. What the farm sets out to produce effectively establishes its labour requirements, its work rhythms, as well as the marketing and pricing arrangements farm families will face. As a result, the farm's commodity provides the key for understanding the various ways farm wives' become 'incorporated' into their husband's work. Dairy farmers are not engaged in the same work as potato farmers even though both are called farmers and there are similarities in their work. It is not enough to study farm wives' work without ascertaining the particularities of being a dairy farmer's wife or a potato farmer's wife. At the same time both sectors must contend with agricultural restructuring, the cost-price squeeze and the economic uncertainties facing their rural communities. In examining the implications of this case study for future research on farm women's work, the thesis adds we must re-evaluate the spatial locations of work - household, on farm, off farm and community - and analytic dichotomies of work - productive and reproductive, paid and unpaid, direct and indirect - in order to better appreciate how farm wives contribute to family farming and how family farming contributes to farm wives' work.

"We Indians Were Sure Hard Workers:" A History of Coast Salish Wool Working. - Olsen, Sylvia Valerie (University of Victoria, 1998)
In the study of the economic and labour history of the West Coast Native people of British Columbia most research has centered on activities such as fishing, farming and forestry. This thesis turns the attention from what was primarily men's work in the dominant society to the Coast Salish wool working industry where women worked with the help of their children and husbands. I examine the significant economic and cultural contribution Coast Salish woolworkers had on West Coast society, the meeting place woolworkers' sweaters provided between the Coast Salish and the newcomers and the changes which took place in the industry during the last century. This story includes many voices most of which are recorded in newspapers, correspondence and journals, and in the memories of those that lived and worked in the industry.

No Jobs, Lots of Work: The Gendered Rise of the Temporary Employment Relationship in Canada, 1897-1997 - Vosko, Leah F. (York University, 1998)
This dissertation examines the history and evolution of the employment relationship associated with the contemporary temporary help industry in Canada from the late nineteenth to the late twentieth century. Using gender as a central lens of analysis, it explores how, and to what extent, this employment relationship is becoming a nom for a more diverse group of workers in the Canadian labour market. In so doing, the dissertation develops the following argument: with the shift away from the standard employment relationship since the early 1970s and the coincident nse of the temporary employment relationship – two developments indicative of the ferninization of employment – workers situated at the expanding margins of the labour market are increasingly treated like commodities. A growing body of scholarship argues that the nature of employment is changing, citing the spread of non-standard forms of employment and women's rising and/or consistently high labour force participation rates as evidence of this claim. This dissertation confirms that important changes are indeed taking place in the labour market but it argues that the tenor and direction of these changes oniy corne into Full view when they are examined in light of continuity as well as change. To this end, it probes the shape of dualism in the Canadian labour market historically, paying particularly attention to its gendered and racialized character, through a case study of the temporary employment relationship. The dissertation begins by providing a conceptual map for understanding and interpreting contemporary employment trends that engages in three broader theoretical inquiries: the investigation of labour power's peculiar commodity statu under capitalism; the exploration of the rise and decline of the standard employment relationship as a normative mode1 of employment; and the examination of the gendered character of prevailing employment trends. Following this overview, the body of the dissertation traces the history of the temporary employment relationship in Canada, examining how its three core actors – the temporary heip agency, the customer and the worker – have adapted to shifting employment trends and gendered employment noms and negotiated developments at the regdatory level over the course of the twentieth century. In probing the evolution of the temporary employment relationship, it devotes special emphasis to examining the role and fùnction of early precursors to the modem temporary help agency (e-g., private employment agents such as general labour agents and so-called padrones), its immediate forerunners (Le., the 'classic' temporary help agency of the 1950s) and its most recent manifestation (Le., the employment and staffing service). AIthough the dissertation focuses on the Canadian context, it also traces developments at the international and supra-national level throughout the twentieth century, developrnents that have often mirrored, frequently affected, and occasionally even prefigured trends in Canada. Interdisciplinary in its focus, the dissertation approaches the evolution of the temporary employment relationship from a range of angles, building on scholarship fiom the fields of Law, History, Political Econorny, Sociology and Industriai Relations. The research methodoIogies used include: archivaVhistorica1 research; field observation; interviews with temporary help workers, agency managers and customers as well as government officials, representatives from organized labour and industry leaders; and analysis of industry, government and legal documentation at the municipal, provincial, national and supra-national levels.
OCLC: 1306069848
Keywords: Academic Dissertation; Academic theses; Thèses et écrits académiques; dissertations

Learning to Be 'Uncivil': Class Formation and Feminisation in the Public Service Alliance of Canada, 1966-1996 - Warskett, Rosemary Elizabeth (Carleton University, 1998)
What kinds of associations did Canadian 'civil servants' form in the postwar period? Why and how did they learn to become 'uncivil', transforming themselves into militant unionists during the 1980s and 1990s? These questions are addressed theoretically and empirically through a case study of the Public Service Alliance of Canada (PSAC). In 1966, PSAC leaders adopted a consultative, harmonious approach to staff relations, organizing the newly formed union to reflect the federal civil service's structure and practice. Class and gender divisions were submerged, hidden beneath the historical and ideological construction of the civil service as a distinctive, politically neutral category. Cracking apart of the unity of federal 'civil servants' began to occur in the 1960s. Class and gender divisions started to come to the fore with the expansion of the Canadian federal state, the increase of women in administrative support roles, and the enactment of collective bargaining rights. During the 1970s and 1980s, working class formation and capacity developed within the Canadian labour movement in concert with feminism, even though the legal structuring of labour relations continued to limit this class and gender formation. In this respect the Public Service Staff Relations Act and the Public Service Employment Act continued to reproduce the practices of the social category of civil servants. Nevertheless, within the PSAC, collective bargaining, the right to strike and the pay equity provisions of the Canadian Human Rights Act produced openings for learning and strategizing around subordinate class and gender issues and demands. Predominately female clerical workers, successfully challenged the structure and practices of the traditional 'civil service' associations. They learned to strategize and to incorporate a working class, feminist discourse into the union's practices. In the process the demand for pay equity was redefined and transformed into a demand of wage equity for all members, thus becoming a source of solidarity during the PSAC's 1991 general strike. PSAC activists learned to use openings in state structures to transform union agency, despite the existence of a legal regime that continues to constrain the development of working class and feminist capacities.
Keywords: Social sciences

In Quest of Emotional Gratification and Cognitive Consonance: Organized Labour and Québec Separatist Nationalism, 1960-1980 - Guentzel, Ralph Peter (McGill University, 1997)
This thesis examines the reaction of organized labour to Quebec separatist nationalism for the period between 1960, the year of the creation of the Rassemblement pour l'independance nationale and the beginning of the Quiet Revolution in Quebec, and 1980, the year of the first referendum on Quebec's constitutional status. The thesis investigates four labour organizations: the Canadian Labour Congress (CLC), the Federation des travailleurs et travailleuses du Quebec (FTQ), the Confederation des syndicats nationaux (CSN), and the Centrale de l'enseignement du Quebec (CEQ). It shows in which ways the positions of the four centrals have been informed by their members' national identifications and the emotional and cognitive mechanisms that resulted from these identifications.
Keywords: Labor unions – Québec (Province) – Political activity.; Québec (Province) – History – Autonomy and independence movements.

The Abuses of Literacy: The Making of a Worker 'Basic Skills' Crisis in England and North America - Hoddinott, Susan (University of Warwick, 1997)
Over the past two decades there has emerged a generalized critique of the quality of the labour supply in industrialized countries in relation to concerns about corporate profitability and national competitiveness. Frequently, the critique has focused, in whole or in part, on the so-called 'literacy' or 'basic skills' competencies of workers. This thesis examines the problematizing of workers' literacy competencies at a time when general educational attainments in Western countries have reached unprecedentedly high levels. Both broad-based and historically informed, the study focuses on the United States, Canada and England over the period of the mid-1980s through the early 1990s. The motives of the agencies and interests which have proclaimed a worker 'basic skills crisis', as well as the processes through which their claims have been disseminated, are analyzed. The ideological and material contexts in which these claims have resonated are described. The thesis concludes that the workforce basic skills 'crisis' is a socially constructed one which has little or no basis in fact. It is an issue which has had utility for a number of interests (including business, labour, educationalists and the state sector), however, and this, it is argued, accounts for the role they have taken in its social construction. The evidence presented here establishes that the workforce literacy issue has had real consequences for workers. It has operated to scapegoat sections of the working class and to further marginalize less formally qualified workers in their workplaces and in the labour market. This-the industrial relations context in which the putative workforce 'basic skills crisis' has operated-forms the principal focus of the thesis. The impacts on workers of actions stemming from the acceptance of the idea of a basic skills crisis-including increasing scrutiny of literacy and language competencies of workers and the promotion and establishment of 'basic skills' programmes of questionable value in workplaces-ought to give cause for many who have endorsed claims of a 'crisis' and embraced workplace literacy to re-evaluate their position.

The Seasonal Agricultural Workers Program in Ontario: From the Perspective of Jamaican Migrants - Knowles, Kimberly Jane (University of Guelph, 1997)
The phenomenon of offshore migrant labour in Canada poses an interesting challenge to the literature dealing with unfree labour relations in capitalist societies. This thesis uses in-depth interviews with Jamaican migrant labourers in Ontario, along with supporting statistical data to further our understanding of the subjective domain of labour relations in agriculture. According to the literature The Seasonal Agricultural Workers Program constitutes a system of unfree labour, and many employers in the Ontario agricultural sector benefit from this system. Jamaican migrant workers do not necessarily share this view of unfreedom. While recognising the definite restrictions as defined in the contract, these migrants accept the conditions of employment as a trade off for the opportunity of material advancement not available to them in Jamaica. This discrepancy over the definition of unfree labour reflects the disparities between the North and the South, and needs to be addressed.
Keywords: Social sciences; unfree labor

The Law of Servants and the Servants of Law: Judicial Regulation of Labour Relations in Montreal, 1830-1845 - Pilarczyk, Ian C. (McGill University, 1997)
Labour relations in Montreal during the years 1830 to 1845 were characterized by flux. The encroachment of expanding industrialization brought with it new social phenomena and pressures, new technology, and a fundamental restructuring of employment relationships. Master-servant relations still contained elements of the deeply stratified and paternalistic labour relationships ingrained in the cultural and social fabric of earlier eras, but increasingly began to exhibit the rudiments of purely contractual relationships which would come to define the modern industrial era. Courts came to play an increasingly important role in resolving labour disputes between parties. While historically the law favored the strict contractual and socio-economic interests of masters, courts began to enforce the reciprocal duties owed by masters to their servants. Servants were accorded greater access to the courts to protect their interests, with the knowledge that they had recourse to extra-judicial means of protest if the law was not sufficiently responsive.

"Kitchen Economics for the Family;" Paid Education and the Canadian Autoworkers Union - Roth, Reuben N. (University of Toronto, Ontario Institute for Studies in Education, 1997)
This thesis examines the Paid Education Leave (PEL) program of the Canadian Autoworkers Union (CAW), fomerly the Canadian Region of the United Autoworkers Union (UAW). This four-week program takes place at the CAW Family Education Centre in Port Elgin, Ontario and potentiatly provides 90% of the CAW's members with class-based, union-centred, labour education. Interviews conducted with key CAW sources uncover PEL's histoncal roots. A chronicle of the stniggle to establish PEL is detailed in relation to the International Labour Organization (ILO) Convention 140 on Paid Educational Leave. Thematic oral-history interviews were conducted with six CAW Local 222 members, al1 former participants of PEL. Interviews are used to illustrate a detailed description of the program's pedagogy and curriculum. Interview respondents were Generai Motors (GM) of Canada workers located in Oshawa, Ontario. Several policy and programmatic suggestions are made, including increased understanding of, and elevated respect for, informal learning.

Race, Class, Women and the State: The Case of Domestic Labour in Canada. - Schecter, Tanya (McGill University, 1997)
This thesis examines the history of female immigrant domestic labour in Canada from a socialist feminist perspective. Over the past hundred years, Canadian immigration policy with respect to domestic workers became increasingly regressive with the shift in the racial composition of foreign female domestics. The women's movement contributed to this change as gains in Canadian women's public rights did not effectively challenge the dominant social paradigm of women's roles, and so left intact the public-private divide and the sexual division of labour to which were allied biases of race and class. The women's movement thus became an unwitting participant in the formulation of regressive immigration policies which rebounded on the women's movement itself, reinforcing its internal divisions.

Railway Bound: The CBRE, the ACCL and the Development of a National Working-Class Community, 1908-1930 - Sheffer, Warren James (Queen's University, 1997)
The 1920s is generally seen as a period of defeat for Canadian labour. With the rise of monopoly capital, strike activity and union membership steadily declined in the face of wage cuts, new technologies and corporate welfare schemes. The continental alliance of the American Federation of Labor (AFL) and the Trades and Labor Congress of Canada (TLC) that, for the most part, provided labour's leadership during this crisis, proved ineffective. By 1927 a secessionist movement challenged the legitimacy of the AFL/TLC alliance. In March of that year, the Canadian Brotherhood of Railroad Employees (CBRE), gathered with the One Big Union (OBU), the Canadian Federation of Labour (CFL), and communist-influenced unions, including the Mine Workers' Union of Canada and the Lumber Workers' Industrial Union, to form the All-Canadian Congress of Labour (ACCL). It is the focus of this thesis to bring the Congress front and centre and to provide an alternative interpretation of its effort to build a national labour movement in the 1920s–one that was neither opportunistic, anti-communist, nor right-wing. Instead, this thesis supports the contention that the ACCL was a counter-hegemonic, working-class initiative that aimed to improve the political representation and material conditions of the Canadian worker.
Keywords: Canadian Brotherhood of Railway; Transport and General Workers – History

Producing Nurses: Nursing Training in the Age of Rationalisation at Kingston General Hospital, 1924-1939 - Wishart, James Michael (Queen's University, 1997)
In 1924, the General Hospital at Kingston, Ontario, began a process of rationalisation, following Taylorist principles of scientific management. In concurrence with the restructuring of other N orth American hospitals, and with the advice given in professional literature, the Governors of K.G.H. secured the services of R.F. Armstrong, a civil engineer. His mandate was to facilitate the transformation of K.G.H. into an efficient, economical modem health institution which would attract not just indigent patients, but also upper-class, paying clients. Part I of this paper analyses the process by wrhich rationalisation was wreaked upon student nurses in the K.G.H. Nurse Training School, considering these women not primarily as students but as an unpaid labour force. I argue that administrators employed a combination of paternalism and scientific management in an attempt to conform student-wrorkers into an 'ideal nurse labourer', as defined by historically specific discourses of gender, class, and Canadian nation/race which converged in the image of the Nurse. Balancing this 'top-down' approach, Part II of the paper attempts to reconstruct student-workers' experiences of and responses to nursing training. Using nurses' cultural productions and oral interview's, I explore the concept of 'everyday resistance' in the contexts of the Nurses' Home and the hospital workshop, arguing that the continual supervision and surveillance endured by student-workers did not preclude successful attempts to wrrite their own script for their experience of nursing. To the contrary, nurses-in-training developed a culture of mutuality which provided them with the resources to resist and ameliorate the most repressive and totalising aspects of hospital labour and residence life. The result of this reconsideration of nursing training is an increased understanding of student nurse labourers as individuals with hopes and expectations of their own, rather than simply dutiful, obedient daughters in the hospital 'family' who accepted their subordination to the 'ethic of service'.
Keywords: Education; Health and environmental sciences; Ontario; Social sciences

Radicalism in Decline: Labour and Politics in Industrial Cape Breton, 1930-1950. - Earle, Michael John (Dalhousie University, 1996)
Cape Breton, the site of major strikes during the 1920s, remained a hotbed of political radicalism and trade union militancy for many years. In the 1930s the Communist Party had considerable influence, and most of the coal miners joined the Amalgamated Mine Workers of Nova Scotia, a CP-led breakaway from the United Mine Workers of America. Ideological opposition to the columnists was spearheaded by the Catholic-inspired Antigonish Co-operative Movement, but this did not prevent the communist leader, J. B. McLachlan, from getting substantial votes in elections. The change of communist policy to the "united front" weakened the party's influence, although communists and the officers of the re-united miners' union were able to help the Sydney steelworkers finally establish a union, and to successfully press the provincial government to pass the 1937 Trade Union Act. Left and right in Cape Breton were also able to work together during the 1937 provincial election. The unity line of the communists, along with the impact of the Antigonish movement on Catholic voters, prepared the way for the UMW affiliation to the CCF in 1938, and during the CCFers won the local seats in both the federal and provincial legislatures. However, the CCF could never win elections elsewhere in the Maritimes, and the move of CCF policies to the right in the post-war years only served to gradually undermine its support in Cape Breton. In the UMW the dissatisfaction of the miners with their bureaucratic officers brought about the 1941 slowdown, one of the most costly wartime industrial disputes, and productivity fell. The union policies advocated by the CCF (and the CP during the war), helped end opposition to the mechanization of the mines. Following defeat in the 1947 strike, the miners had to accept modernization on the company's terms, although this meant the loss of jobs. The steelworkers' union won a national strike in 1946, but thereafter was unable to hold wage rates for Sydney at a level equal to those paid in Ontario steel plants. The militancy and radicalism of the miners and steelworkers of earlier years had almost completely disappeared by 1950. Dramatic anti-communist episodes in both the steelworkers' and miners' unions in the 1949-50 period marked the triumph of union bureaucrats and Cold War politicians over radicalism in Cape Breton.
Accepted: 2014-10-21T12:37:41Z

Winnipeg Meat Packing Workers' Path to Union Recognition and Collective Bargaining - Grover, John Hanley (University of Manitoba, 1996)
This thesis explains why in the 1940s, Winnipeg meat packing workers secured sustainable industrial unionism. By tracing the development of the Winnipeg meat packing industry and investigating previously unsuccessful organizational drives, it is suggested that success in the 1940s corresponded to three broad contributing factors. The most significant factor was changing local conditions. With the gradual introduction of mass production techniques to the Winnipeg meat packing industry beginning in the early 1920s, the reorganization of Winnipeg packinghouse work occurred. The large scale introduction of semi-skilled workers changed the face of meat packing, as packinghouse work became deskilled without any significant degree of automation. During this period, craft unionism in the meat packing industry failed on a national pattern. This failure coincided with the 1930s experiment in industrial unionisn by Winnipeg workers'at Western Packers workers. Western Packing's workers' introduction to industrial unionism also provided the successful 1940s drive with links to the Communist Party. An overall strengthening in North America of the labour movement beginning in the 1930s provided the second broad contributing factor to success in the 1940s. With the birth of the CIO in the United States and Canada, Winnipeg meat packing workers gained at the very minimum inspiration. The impact of Wor1d War II accounted for the final contributing factor for success in the 1940s. With a wartime demand creating full employment and the governmentts desire to maintain production, organized labour found itself in a position of unparalleled power. In combination, a spirit of militancy arose among Canada's labour movement. From these conditions, meat packing workers in Winnipeg chose and pursued industrial unionism with great success. By the end of World war II, workers in Winnipeg possessed an effective union organization and had won union shops and wage increases. Ultimately however, the union's national success created a centralized, bureaucratic union movement which consequently provided a loss of local autonomy.
Accepted: 2012-06-01T19:04:19Z

Work, Employment and Unionization in Transition Houses: A Case Study of One Canadian Province - MacDonald, M. Maureen (University of Warwick, 1996)
Transition houses are small feminist organizations, providing emergency shelter to women and children who have been abused. They also are workplaces whose social organization divides women as managers and workers. This research, an institutional ethnographic case-study of nine transition houses in one Canadian province, examines how relations between the state and transition house have led to greater institutional power and control over transition house work, by women who are paid managers. This results in a reconstituted struggle for equality between women inside these settings. Mangerialism in the Canadian transition house movement has not been theorized.The argument advanced here is that conflict between workers and managers in transition houses is an inevitable outcome of the on-going struggle to develop feminist praxis within contradictory relations, shaped and influenced by transition house/state relations, dominant managerial discourses, and the exigencies of transition house work. In an attempt to resist and to limit managerial power and control over the labour process and over feminist praxis, transition house workers look for ways to develop their own collective power. Unionization as a vehicle for collective action is an obvious choice and it is one that transition house workers are pursuing.

Harnessing Confrontation: The Growth and Consolidation of Industrial Legality in Canada, 1943-1950 - McInnis, Peter S. (Peter Stuart) (Queen's University, 1996)
This study examines the critical years in which the Canadian industrial relations system assumed many of its lasting characteristics. Specifically, it explores the actions of management, unions, and the federal state under the exceptional conditions of the wartime "command economy" and later, with the transition back to a peacetime footing. Frustrated with the inadequacy of existing collective bargaining legislation, and sensing that this period signalled a realignment in the labour-capital relationship, Canadian workers took advantage of special wartime conditions to press home their demands for basic workplace rights framed by a more equitable labour code. The result of this campaign was the establishment of a new legal framework which defined the respective roles for all three groups over the next thirty years. Of particular importance is an investigation of the ambivalent legacy achieved by the Canadian labour movement with its pursuit of the essential rights of free association and collective bargaining. Building on the intense workplace struggles of the war years, labour pushed federal authorities to support mandatory collective bargaining, compulsory wage deductions of union dues, finally entrenching these reforms under the Industrial Relations and Disputes Investigation Act (1948).
Keywords: Social sciences; labor; management; unions; workplace rights

Families in the Souris Coalfields, 1925-1935 - Morier, Christopher David (University of Saskatchewan, 1996)
This study of families in the Souris coalfields in southeastern Saskatchewan in the 1920s and 1930s argues that women and children in the mine communities were active and enterprising individuals. In the absence of modem-day conveniences and comforts, families in the mine camps devised a variety of strategies and techniques for survival. Perseverance and hardiness marked these coal families, and a strong and able wife and mother was vital to a family's independence, empowerment, and survival. Such women were commonplace in the Souris coal camps, and mining families were characterized by an ability to adapt, respond, and adjust to demands and circumstances of the mining lifestyle. Interviews with ex-coal camp residents provide much of the information in this study. While historians of deep-seam coal mines across Canada are quite correct in emphasizing the grueling, dangerous, and demanding working conditions of the underground miners, coal communities above-ground deserve recognition as dynamic and active entities as well. Traditional labour-focused examinations of the coal industry fail to acknowledge that male miners were members of a minority group in the Souris coal camps - women and children made up the bulk of the population, and played important roles in the communities. These camps were home to hundreds of hardworking and practical families, and this thesis recognizes the independence and tolerable lifestyles that these families strove to achieve.

Strategies of Survival Among Illegal Migrants in Montreal - Raposo, Cremilde (Concordia University, 1996)
This thesis using a case study approach examines the migration and employment strategies of illegal migrants in the labour market in Montreal. The migratory flows discussed are permanent in nature. The thesis also examines the role of networks in initiating the migration process and in securing employment in Montreal. It includes an examination of the conditions of employment and the sectors of employment. It argues that illegal migrants work in the secondary labour market, that is on the fringes of the formal economy or in the informal economy. Income disparities between North and South countries ensure that migrants continue to live and work illegally in Montreal. This raises a discussion of the strategies used by migrants to change their status to a legal status. The thesis discusses the experiences of both women and men. It posits the view that women are migrant workers in their own right and not only as dependents of male migrants. This is attributed to the increase in service sector jobs and the increased demand for paid domestic labor in the Canadian economy. It is concluded that immigration policies allow and maintain illegal migration and that there is a demand for this kind of labour in the Montreal economy. Furthermore, illegal migrants fulfill a particular labour market need.

The Making of Protective Labour Legislation in British Columbia: The 1912 Royal Commission on Labour and Its Aftermath - Venables, Kenneth A. (Simon Fraser University, 1996)

Improper Property: Squatters and the Idea of Property in the Eastern Townships of Lower Canada, 1838-1866 (Quebec). - Whan, Eric (McGill University, 1996)
Drawing on the manuscript records of the Department of Crown Lands, its published reports, and case law, this thesis examines the illegal occupation of rural land, known as squatting in the Eastern Townships of Quebec in the period 1838 to 1866. By 1838, demographic pressure in the seigneuries, inflated land prices due to speculation, and inaccessible public land granting practices had made squatting a commonplace strategy for land acquisition. The responses to squatting of the Department of Crown Lands, the Legislature and the judiciary are analysed for what they implied about ideas of property in Lower Canada. While the Department of Crown Lands' policy of pre-emption affirmed that squatters held rights to public land because they laboured to cultivate and improve it, the legislature refused to acknowledge that squatters could acquire such rights on private land; nine out of ten bills intended to ensure ejected squatters a systematically determined remuneration for improvements made by them on the private property of absentees failed to pass into law during the period. Most were rejected by the Legislative Council which defended the interests of landed wealth. Lower Canadian courts, meanwhile, struggled to sort out laws relating to squatting. Ultimately they found that while squatters on private property owned their improvements, they had no right to the land itself. Thus the judiciary applied a bifurcated concept of property to rural land in Lower Canada despite the prevalence of liberal theories of absolute property rights during the nineteenth century.

Conflict Within the Union: Struggles Among Sydney Steel Workers, 1956-1972 - Crawley, Ron (Carleton University, 1995)
The thesis addresses the importance of intra-union struggles as a mediating factor in understanding the relationship between changes in union policies and strategies and the larger socio-economic environment. Examination of these intra-union struggles, the thesis argues, is necessary for a fuller understanding of the development of the union and the steel workers' ongoing contestation with the steel company. It examines the significance of intra-union conflict in the establishment of responsible" unionism and "industrial democracy" within the Canadian steel industry and in the context of international, national and local aspects of the union. During the period 1936-1972 the steel workers were organized within Local 1064 of the United Steel Workers of America which, according to the findings of the thesis, was marked by intra-union conflict almost from its inception. Conflict between an establishment-dominated leadership and its supporters and oppositional forces, which took different forms and displayed various degrees of influence within the local over time, was an integral part of the union's political life. Arguments drawn from Marxist theory and from the work of Michels are compared and evaluated in light of the historical record of the steel workers and their attempts to build an effective organization. The thesis demonstrates that oppositional activity within the union was crucial to understanding the development and direction of the union. The establishment and maintenance of "responsible" unionism and "industrial democracy" were mediated by intra-union struggles. The findings of the study offer support for both a Marxist and a Michelsian theory of change within such organizations.

Collective Memory and the Definition of Place: A Monument for the Winnipeg General Strike of 1919 - Hyland, Gillian Crawford (University of Manitoba, 1995)
ln acknowledging and incorporating significant episodes of the past into the present landscape, monuments can provide the inhabitants of a place with an interactive heritage: a heritage based on the fusion of past and present, deepening a sense of place by providing the means to possess a common identity, that is to belong to a fellowship of place. The intent of this practicum was the development of a contextually based monument which relies on an integration of elements and contextual relationships to convey its meaning. With this goal in mind, the evolution of the monument was studied in order to gain a better understanding of it as a theoretical concept and valid functional element. The intent of this study was the development of programmatic guidelines for a contextually based monument. The Winnipeg General Strike of 1919 provided the perfect subject for the design of a commemorative monument which would be based on an application of the developed program. Site selection for this specific commemorative monument was based on the applicability to historical criteria and thematic issue derived from a study of the Winnípeg General Strike. ln addressing and defining each of the requirements, the design has achieved its purpose in illustrating the practical application of a theoretical concept, the contextual monument.

Law and Labour Unrest in Ontario's Textile Industry; Cornwall, 1936 and Peterborough, 1937. - Landry, Laura (Carleton University, 1995)
This thesis examines two textile industry strikes in the late 1930s and how federal and provincial labour law combined with criminal law to affect the strike outcomes. By using the 'Strikes and Lockouts' file, period newspaper microfilm and negotiation manuscripts, I reconstruct the 1936 Cornwall Courtaulds and the 1937 Peterborough Dominion Woollens and Worsted strikes. Both strikes occurred during the course of the *Royal Commission Investigation on the Textile Industry (Turgeon Report)* which provides much statistical data to supplement newspaper reports; both involved primary textile production in southern Ontario during the Hepburn administration; and both industrial conflicts involved women workers. I have used a political economy approach to elaborate on the development of the federal *Industrial Disputes Investigation Act (I.D.I.A.)*, the provincial *Industrial Standards Act (I.S.A.)*, and the provincial/municipal use of section 501 of the *Criminal Code*. I conclude that labour law does not progress in a linear fashion but is characterized in its administration by the co-existence of both voluntarist and repressive legal measures. While the broader historic political climate would influence the social acceptance of a strike, the regulation of industrial conflict is ultimately strategically constrained by the criminal law. Finally, women were active in both strikes, whether on the picketline or aiding the strike.

Attitudinal Militancy in A Canadian Postal Plant - Lewis, David Lloyd (McMaster University, 1995)
One tenet of labour process theory is the contention that, when confronted by degraded work, people will resist through militant behaviour or in other ways. However, that "resistance hypothesis" has been tested rarely. Canadian postal workers have manifested some considerable militancy, for instance through legal and wildcat strikes and through frequent recourse to the grievance mechanism. Too, their work has been subjected to technological change often pointed to as a prime example ofjob degradation. But not all aspects of postal work have been subjected to technological change. Thus, postal workers constitute a test ofthe "resistance hypothesis:" if degraded work provokes militancy, then ceteris paribus postal workers involved in automated work will be more militant than those who are not. In this study, a group of postal workers employed in "Cancity" in 1985-6 (N=152) were surveyed regarding their attitudes and experiences. Factor analytic techniques were used to construct a scale of attitudinal militancy, and hierarchical set analysis - summarised using dummy variable path coefficients - was used to examine the causal links between this outcome and logically prior factors, including job degradation, employment history, and achieved and ascribed statuses including sex. The results indicate that job degradation does have an impact on attitudinal militancy, but that this impact is modest at best, and weakens as other influences are taken into account.

Gender, Class and Community: The History of Sne-Nay-Muxw Women’s Employment - Littlefield, Loraine (University of British Columbia, 1995)
This thesis documents the employment history of Sne-nay-muxw women. The Sne nay-muxw, a Coast Salish peoples, live on the southeast coast ofVancouver Island close to the city ofNanaimo. Nanaimo was established by the Hudson’s Bay Company in 1852 as coal mining town. Coal dominated the economy until the early 20th century when forestry related production became important. Today a service economy has eclipsed both the primary and secondary industries. Within these economies a distinct gender, race and class segregation structured Sne-nay-muxw women’s employment opportunities. This study examines the nature of this segregation, the Sne-nay-muxw domestic economy and the gender ideology that promoted both women’s inclusion and exclusion in. wage labour. A central question posed in this thesis is why Sne-nay-muxw women today perceive their traditional roles to be within the home despite their historical participation in the labour force. Feminist anthropology provides the theoretical and methodological approach used for this study. It is accepted that women’s experiences in the labour force are different not only from men but also from other women based upon relational inequalities ofrace and class. Historical data was collected from a variety of sources; published and unpublished government reports, missionary accounts, letters and journals. Nineteen women and eight men were interviewed in the community for both historic and contemporary accounts of employment experiences. History reveals that during the mining economy Sne-nay-muxw women were excluded from working in the mines and limited to employment as domestic servants. The introduction of Chinese labour, decreasing coal demands and increased technology forced many women to migrate with their families to the canneries on the Fraser river and the hop fields in Washington state. In the forestry related production economy, Sne-nay-muxw women’s opportunities were limited despite the expansion of employment for women in the service sector. State policies and inferior education were significant factors in this exclusion. At this time Sne-nay-muxw women continued to migrate with their families to the fish camps on Rivers Inlet and the berry fields in Washington state. In the last two decades the service economy has dominated in Nanaimo. Sne-nay-muxw women have found increasing job opportunities on and off reserve in administration, management and professional service delivery programs. While this employment is part of the wider trend for women in the service economy, Sne-nay-muxw women’s opportunities remain segregated by gender, race and class. Women’s participation in the labour force is shown to be linked to the organization of their domestic economy. Before 1920 this economy incorporated both subsistence production and farming with seasonal wage labour. After this time the Sne-nay-muxw became increasingly dependent upon wage labour. However, extended family and kinship networks have remained important for support and cooperation. This form ofhousehold organization did not constrain women’s participation in the labour force. Today extended families remain the central organizing principle in Sne-nay-muxw lives. Sne-nay-muxw women’s identity and opportunities for education and employment remain linked to their membership in these families. Shifts in women’s participation in the labour force is shown to be accompanied by acceptance of a domestic ideology. During the mining economy when women actively sought wage labour, they acquired domestic skills needed for wage labour but did not accept an ideology that promoted their dependency upon men. Historical evidence indicates that they retained a significant degree of autonomy in their lives. With men’s increased security of employment in the forestry economy, the idealized role ofwomen as housewives was promoted. Families that were able to realize women’s exclusion from the labour force gained status and prestige in the community. Finally, in the service economy, the Sne-nay-muxw gender ideology includes women’s participation in the labour force to occupations linked to their domestic and nurturing roles.

Work, Wages and Welfare in Aboriginal-Non-Aboriginal Relations, British Columbia, 1849-1970 - Lutz, John S. (University of Ottawa, 1995)
This dissertation focuses on the work-for-pay exchange between aboriginal people and immigrants of European stock–the two most prominent cultural groups in the early history of British Columbia–and follows the patterns of this exchange from its origins through to the 1970s. It examines both the material and the rhetorical construction of the "Indian" as a part of British Columbia's labour force, a process described as racialization, and emphasizes, as well, the transformation of meaning inherent in cross-cultural exchange. It is a province-wide analysis, the core of which is a micro-history of one aboriginal group, the Songhees people, who live in the area now occupied by Victoria, the capital city. This examination challenges the long-standing view that aboriginal people were bystanders in the economic development and industrialization of British Columbia outside, and after, the fur trade. From the establishment of the Colony of Vancouver Island in 1849, through Confederation with Canada in 1871 and to the 1885 completion of the Canadian Pacific Railway, aboriginal people comprised the majority of the population in present-day British Columbia, and the majority of the work force in agriculture, fishing, trapping and the burgeoning primary industries. This dissertation charts the subsequent decline in participation of aboriginal people in the capitalist economy from 1885 to 1970. Using a micro-historical study and close attention to aboriginal voices it offers a set of explanations for the changing proportions of work, both paid and unpaid, and state welfare payments. The micro-history reveals that the Songhees people engaged in two distinct but connected economies and were already familiar with forms of labour subordination prior to the European introduction of a capitalist economy. The Songhees participation in paid labour for Europeans was facilitated by these existing forms of labour organization and depended on the co-existence of their other economies; the Songhees used earnings from capitalist paid labour to expand their non-capitalist economies. After 1885, new state policies repressed the non-capitalist aboriginal economics and therefore diminished the underlying motivation for aboriginal participation in capitalist work. At the same time, an influx of labour-market competition and a variety of racialized laws and practices restricted the Songhees' ability to get work. Increasingly they were left with seasonal, low-skill and low-wage labour, a niche that maintained them so long as it was combined with a subsistence economy and involved the full participation of adult and adolescent family members. In the late 1940s and 1950s this pattern too was remade. Legal restrictions dramatically limited the subsistence economies; technological change curtailed the demand for seasonal labour in the canning, fishing and agricultural sectors, particularly affecting aboriginal women workers; and, compulsory schooling regulations began to reduce labour available to the family economy. At the same historic moment when the combined wage and subsistence economies ceased to be able to support them, the state extended some existing social welfare programs, such as Old Age Pension, to Indians, and expanded other programs, including Family Allowance, to all Canadians. In examining the patterns of aboriginal-non-aboriginal exchange relations over the long-term, this dissertation argues that high rates of unemployment and welfare-dependency among contemporary aboriginal communities are relatively recent historical phenomena, with observable roots and causes.

"A Modern Weapon for Modern Man": Marxist Masculinity and the Social Practices of the One Big Union, 1919-1924 - McCallum, Todd (Simon Fraser University, 1995)
In March 1919, more than 230 union representatives gathered in Calgary for the Western Labor Conference. There, they initiated plans for a revolutionary industrial organizatin, the One Big Union, which embodied the internationalist principles of Marxist unionism. Within its first year, the One Big Union (OBU) issued over 70,000 membership cards, and was a powerful symbol of working-class demands for the end of class exploitation. However, given its patriarchal inheritance, the OBU was always something more than just a class organization. It was an attempt by working men to organize around a specific sense of gender identity, which I have called Marxist masculinity, in order to reconstitute the social bases of male power. The first chapter outlines the events surrounding the creation of the OBU in 1919 and the wave of general strikes that swept through Canada that summer. In particular, it sketches the relationship between class politics and a masculine structure of feeling, and how this relationship influenced the OBU's ideology. The second chapter discusses three elements around which Marxist masculinity was constructed. To begin, the experiences of women in the OBU are situated in relation to the organization's policies regarding membership in individual unions and the Women's Auxilliary. As well, it examines the personal lives of OBU leaders and the naturalized assumptions about heterosexuality which governed their politics. The final chapter discusses the purge of Tom Cassidy and Catherine Rose, two dedicated activists fired because of rumours of their sexual involvement. The OBU leadership wanted to prevent a public moral panic around issues of "free love" and was thus determined to have the matter kept quiet. In taking this position, OBU leaders regulated the gender and sexual identities of union members through concepts of proper masculine and feminine socialist behaviour.

"We'll Hang All Policemen from a Sour Apple Tree!": Class, Law, and the Politics of State Power in the Blubber Bay Strike of 1938-39 - Parnaby, Andy (Simon Fraser University, 1995)
In the wake of President Roosevelt''s New Deal for labour in the United States, the International Woodworkers of America (IWA) experienced tremendous organizational growth in both Oregon and Washington. Fearing the arrival of the IWA in British Columbia, the provincial government enacted the Industrial Conciliation and Arbitration (ICA) Act as a means to preserve the industrial peace through state regulation of the class struggle. It was at the company town of Blubber Bay on Texada Island that the Act was tested for the first time in an eleven-month strike [during1938-39] between Local 163 of the IWA and the Pacific Lime Company. With the failure of the legislation to broker a settlement, the union's campaign for recognition was subsequently enveloped by clashes over the common law rights of private property which limited workers' mobility in the community and the criminal laws of unlawful assembly that jailed strike leaders. Through an investigation of the state, company and union this project demonstrates that statutory, criminal and common laws in question were dedicated to the reproduction of capitalist social relations by regulating or eliminating the collective political activities of working people at Blubber Bay and, by extension, the arrival of the IWA in BC. As well, such struggles reveal the fundamentally conceptions of legality put forth by the union. Furthermore, this project illuminates the ways in which the expansion of formal collective bargaining contained class struggle and how the law and legal process shaped the political choices of working people. Indeed, the Blubble Bay conflict provides a window into the role of the state in labour/capital relations; in particular, its capacity through consent and coercion to legitimize its role as arbiter of competing class interests, secure allegiance to the rule of law, and diffuse oppositional challenges to the existing order.

Interpreting Their Powerlessness: The Case of Filipino Domestic Workers in Vancouver - Sanchez, Grace B. (University of British Columbia, 1995)
This thesis points to an oversight in the literature about foreign domestic workers. Foreign domestic workers have, too often, been portrayed as one-dimensional victims — a group of powerless women vainly struggling for a respectable place in Canadian society. This portrayal, however, while it can explain their disadvantage along class and gender analyses, assumes a concept of power which dismisses their ability to resist. This thesis argues that foreign domestic workers, although occupying a highly disadvantaged position relative to others in society, are not only victims but actors. This argument acknowledges that their lives in Canada are only part of their grander life histories. When foreign domestic workers are placed at the centre of analysis, as subjects rather than objects, I was able to investigate a multifaceted notion of power. Fifteen foreign domestic workers from the Philippines were interviewed and specific questions were asked about their day to day lives, their background, and their ambitions. Their answers reveal a profound understanding of who they are as women, and as domestic workers. Some clearly understand the connections between the economic crisis in the Philippines and their role in that crisis. The interviews also show that domestic workers contemplated their situations beyond the present, and that they recount their lives in episodes of opportunities as well as constraints. Finally, what is most revealing is the strategies they employ to get through their days. Overall, the interviews with foreign domestic workers illustrate that when they are viewed as active social agents, they articulate power at various levels corresponding with their overlapping social roles and multiple levels of struggle.

Against Capital: The Political Economy of Aboriginal Resistance in Canada - Simmons, Deborah Lee (York University, 1995)
This thesis evolved out of an attempt to analyze aboriginal agency and resistance in the aftermath of the Mohawk conflict at Oka, Quebec, which took place in the summer of 1990. However, the existing political economy literature on aboriginal oppression founded in the "staple theory" outlined by Harold Adams Innis does not account for the historical significance of aboriginal resistance in Canada. The thesis undertakes a critique of the inherent assumptions in staple theory–its anthropologism, its fetish of the commodity form, and its geographical determinism–which effectively reduce aboriginal peoples to the position of passive victims in contemporary capitalist society. An alternative historiography is then proposed which considers Canadian economic and political development as the outcome of struggle. The agency of aboriginal peoples is understood in terms of their specific and changing historical position as producers, from the early fur trade to the forging of a capitalist economy and post-colonial state. If the rise of commodity wheat production is the key to the transition to capitalism in Canada, it follows that the aboriginal struggle to retain their land rights was an important obstacle to such development. The aboriginal struggle for land continues to be an obstacle to capitalist expansion; in the current context of economic integration under the North American Free Trade Agreement, such resistance has international implications. In the current climate of scapegoating and cutbacks which accompany the restructuring process, aboriginal aspirations for land and self-determination also coincide with the aims of other social movements to oppose such attacks. In fact, aboriginal self-determination is central to the broader project for social change in Canada.
Keywords: Mohawk; Social sciences

Collective Bargaining and Pay Equity: A Study of Pay Equity Bargaining in Two Canadian Provinces - Skipton, Susan Margaret (University of Warwick, 1995)
The aim of this study was to explore the interrelationship between collective bargaining and pay equity. A qualitative case study methodology was used. Eighty-six interviews were conducted with union and management pay equity negotiators, labour lawyers, Pay Equity Commission Review Officers, and other informants. A collection of documentary evidence supplemented these interviews. The empirical work focused on explaining issues of structure, style and power in pay equity bargaining and the complex intertwinings of the structural properties of gender and class were considered crucial to an explanation of these. The key structural dynamic in the negotiation of pay equity was found to be the degree and effectiveness of a labour-feminist politic combined with employer/state commitment, which are themselves interconnected and represent the transformative face of gender and class power relations. The thesis, in providing a theoretically informed discussion of detailed case study material, contributes towards the debate on the effectiveness of collective bargaining as a vehicle for implementing equal pay policy. It also informs the debate on labour-management cooperation in labour relations, especially in public sector collective bargaining. Because legislated pay equity is bargained within a new set of legal parameters, the study may also aid our understanding of the relationship between collective bargaining and the law. Finally, the thesis attempts to unravel the interwoven complexities of gender and class power relations in the collective bargaining process.

"We Are Only Loggers": Loggers and the Struggle for Development in Newfoundland, 1929-1959 - Sutherland, Dufferin (Simon Fraser University, 1995)
A poor but independent Dominion in the British Empire until 1949, Newfoundland and Labrador is now Canada's poorest province. This thesis argues that capital's uneven development of Newfoundland helps to explain its economic, social, and political troubles in this century. The uneven course of development left Newfoundland with an archaic fishery, enclaves of modern industry dependent on outport labour and external forces, and a state which lacked sufficient resources to save itself or its people during the Great Depression. The uneven pattern of development also impeded the full development of a proletariat which might have challenged the island's dominant interests and created a more equal and prosperous society. The outcome of these "developments" was confederation with Canada and enduring economic and social problems. Focusing on the period 1929-1959, the thesis develops this argument through a study of the pulp and paper industry, one of Newfoundland's major land-based enterprises in this century. It reveals that forest capital's reliance on seasonal outport labour in its woods operations propped up merchant operations in the inshore fishery. Merchant capital profited from fishers' work in the woods as wages paid debts and purchased fishing and consumption supplies. Throughout the period, the Newfoundland state defended forest capital's interests, and not incidentally the course of uneven development. It did so because the industry's mills and company towns were among the few successes of a national policy to diversify an economy dependent on the export of a single staple. Forest capital exploited fabled interior resources and employed thousands in its mills and woodlands which reduced pressure on an unproductive fishery and on a state often burdened with heavy relief bills. Although Newfoundland loggers confronted the combined power of capital and the state, they struggled to resist their exploitation and to improve the lives of their households and communities. In this way, they challenged the course of development in Newfoundland. During the 1930s, loggers staged strikes and joined Newfoundland's first loggers' union. In 1940, disruptive class conflict ended when forest capital and the state spearheaded the creation of the Woods Labour Board. The Board, which included representatives of capital, labour, and the state, inaugurated a conservative period of class collaboration, and continuous production until the tumultuous 1959 International Woodworkers of America strike. During the 1940s and 1950s, the Board helped forest capital accumulate profits in an industry dominated by Fordist-like production forces in the mills and primitive production forces in the woods. The Board's downward pressure on wages and conditions, union representatives separated from their members, and a work force dominated by outport fishers who continued to require seasonal wages, explains the 1959 conflagration. The dissertation concludes that the loggers' 1959 defeat by the combined forces of capital and state followed an historical pattern determined by the uneven pattern of development. This pattern, therefore, helps to explain enduring poverty in outport Newfoundland and the difficulties workers faced to challenge the conditions of their existence.

Capital, Labour and Lumber in A. R. M. Lower's Woodyard: James Maclaren and the Changing Forest Economy, 1850-1906 - Hammond, Lorne F. (University of Ottawa, 1994)
In reaction to A.R.M. Lower's forest studies, which emphasize the role of markets and tariffs, it is argued that both capital and labour demonstrate extensive agency during the transition between Canada's exports of lumber to Britain and the United States. A series of micro-studies explore the socio-economic transition from colonial to corporate forestry, within a regional framework integrating rural and urban experiences. The succession between economies is examined, from fur to lumber, land speculation, to merchant capital and pioneer sawmilling, to the Ottawa Valley capitalist. The example, James MacLaren, used kinship capital pools and strategic business alliances to rise to the position of independent capitalist lumberman and Bank president. The labour institutions upon which his business was based, the shanty and the timber cove, were anchored to a web of household economies, both urban and rural. Families drew on monthly shanty wages. The shanty was common ground for small kin-groups of local farm workers, urban sawmiil workers, migrant workers, and a core of professional lumberers, resident in Ottawa. Staggered waves of arrival and departure show flexibility in when one decided to leave the farm for the shanty, implying it was a complementary institution. MacLaren's cove in Quebec City also accommodated rural workers amid numerous small non-union strikes. Across the harbour, timber ship labourers, divided over ethnicity and technology, coalesced violently into one of the country's strongest unions. As industrial lumber barges replaced rafts, sawmills replaced coves as export points. MacLaren used both to sell to British and U.S. markets simultaneously, expanding his investments into Vermont and New York. His capital was redeployed in resource developments, such as mining and railways, or local real estate, in a regional pattern that cut across the "Empire of the St. Lawrence". His connections were with American investors or competitors–Cleveland steel elites or the House of Morgan. The Bank of Ottawa, built upon his gathering of local groupings of capital, eventually found regional identity a hinderance in raising capital. Unable to make inroads into other markets, it merged with the Bank of Nova Scotia. In 1904 a successful appeal was made to the State to close timber limits against settlement. This was to make forests more acceptable as collateral to make the transition to pulp and paper. Couched in the discourse of fire, the closing of the forest common marks the true end of the frontier. For Quebec, this is the final abandonment of agrarian colonisation for a development model based on state supported large scale corporate forestry, mining and hydro-electric development.
See also this summary: https://quescren.concordia.ca/en/search?page-len=1&sort=score&page=35&all=labour

The Canadian State and Native Migrant Labour in Southern Alberta's Sugar Beet Industry - Laliberte, Ronald F. (University of Saskatchewan, 1994)
Recent studies of labour have clearly established that the capitalist state is very involved in the recruitment, relocation and retention of migrant labour forces. Most of the literature tends to analyze migrant labour within the broader social, political and economic context of expanding capitalism. Consequently, studies tend to focus on how the use of migrant labour is profitable to capitalism because it is cheap and easy to exploit. Such studies, however, neglect the ways in which the state actually intervenes in the labour market in order to facilitate the flow of migrant workers to places of employment. Therefore, this thesis explores the relationship between the migration of labour, the state and the reserve army of labour through an analysis of the Native migrant work force in the sugar beet industry in southern Alberta.

Shrink, Cut...Dye?: NAFTA and Women's Work in the Canadian Clothing Industry - Vosko, Leah F. (Simon Fraser University, 1994)
[This thesis] is an interdisciplinary examination of the effects of North American trade liberalization on women workers in Canada's clothing sector. This thesis takes a four-pronged approach to assess the decline of Canadian clothing manufacturing under the Canada-U.S. Free Trade Agreement (FTA) and the potential implications of the recently adopted North American Free Trade Agreement (NAFTA). First, I present a historical sketch of women's work in the Canadian clothing industry. Second, I examine employment trends in Canadian clothing manufacturing since 1980, demonstrating that this sector embarked on a downward trajectory after the introduction of the FTA. Third, I investigate how intra-sectoral and inter-sectoral relations in clothing and textiles industries throughout North America contribute to the vulnerable status of the Canadian clothing industry under free trade. Fourth, the thesis culminates with a detailed examination of the clothing and textile provisions contained in the NAFTA text. This final analysis reveals several tangible consequences of the agreement. The findings of this study highlight the tenuous status of the Canadian clothing industry under the NAFTA. As an outgrowth of the FTA, the NAFTA is poised to intensify the recent erosion of this important manufacturing industry since it institutes highly restrictive rules governing North American clothing trade. As such, the NAFTA endangers the status of the clothing industry as a primary industrial employer of women in Canada.
OCLC: 46502073
Keywords: Academic Dissertation; Academic theses; Thèses et écrits académiques

Work, Discipline and Conflict in the Hudson's Bay Company, 1770 to 1870 - Burley, Edith (University of Manitoba, 1993)
The Hudson's Bay Company is usually seen as a group of explorers and fur traders, an image reinforced by fur trade historians who focus on officers, native-European relations, women, and "fur trade society," while paying scant attention to the majority of the HBC's men who were labourers and tradesmen. The notion that trading posts resembled traditional households in which subordinate members were subsumed has come to dominate the discussion of HBC employees, thereby relegating them to the margins of Canadian history. Labour historians tend to ignore the HBC altogether. But, the posts and ships of the HBC were workplaces and, therefore, "contested terrain," as indeed was the pre-industrial household itself. The assumption, shared by the London committee and fur trade historians, that order and subordination were the norm in such traditional settings means that conflict and disobedience are considered almost aberrant and attributed to ethnic peculiarities. The HBC has thus come to be seen as a monolithic, paternalistic organization in which all members were united in a mentalite characteristic of the harmonious, pre-industrial society from which most of them were drawn. However, pre-industrial social relations were negotiated, not imposed from the top. This thesis rests on the assumption that such negotiation occurred in the HBC and explores this relationship for the period 1770-1870, a century of drastic change for the company. The HBC's archives preserve the journals, logs, and reports of unusual events, which officers and ships' captains had to submit, correspondence between them and the London committee, letters from HBC recruiters, petitions from servants asking for assistance or demanding justice, and a variety of personal letters. These records document the behaviour and views of both officers and servants and reveal that conflict was very much a part of life in the HBC. Regardless of ethnicity and like other workers, HBC men negotiated the terms of their engagements, retained customs and habits their superiors abandoned, engaged in private trade, were frequently disobedient and defiant, tried to control the pace and conditions of their work, and acted collectively to increase wages or oppose unfair treatment.

"To Each According to His Need, and from Each According to His Ability. Why Cannot the World See This?": The Politics of William Ivens, 1916-1936 - Butt, Michael William (University of Manitoba, 1993)
Following capitalism's arrival on the Canadian Prairies, the desire to challenge the existing order grew within a number of sharply divided communities. Immediately following World War I, moderates and radicals alike responded to the grim realities of unemployment, starvation wages, poor working conditions, and unsanitary housing by challenging a contradictory system of social relations in a battle over the meaning of "democracy". It was a golden age of social criticism, as pioneer reformers reached out to the large community audiences. In colleges, in churches, and in a radicalized press, the arrival of reform was heralded as the coming of a new day. Few persons were as outspoken or were able to gain as wide an audience as William Ivens. As a Methodist minister, a Labour Church leader, a working-class intellectual, and eventually as a member of the Manitoba Legislative Assembly, William Ivens challenged the existing order. He represented a tendency in Western Canadian thought throughout the 1910s, 1920s, and 1930s. His Labour Church as a working-class institution helped forge a political space in the community. Ivens offered Manitobans a new social order based not on competition, but rather on co-operation. His tendency was the result of passing various elements of Marxism, and Labour Marxist thought through the lens of a non-conformist Christianity and Methodism. The end result was an ethical socialist social philosophy that effectively addressed the social problems of the period. As a spokes-person and as an agitator for social reform, Ivens' ethical socialist outlook achieved a consensus among radical and moderate labourists. His importance as an activist in the community and the type of reforms that he was advocating, make him an important, interesting and worthwhile study in Western Canadian history.

Disability, Discrimination and Equal Opportunities: A Comparative Study of Legal Models Addressing the Employment Rights of Disabled Persons, with Particular Reference to Britain and the United States - Doyle, Brian John (University of Salford, Department of Business and Management Studies, 1993)
Against the background of growing demands in Britain for anti-discrimination legislation covering disabled persons, the study examines the case for reform, and the shape which such legislation might take, in the employment field. Using the socio-legal tradition, the meaning of disability is explored and the demography, nature and experience of disability is described. The evidence of employment discrimination against disabled persons is evaluated and their position in the labour market is plotted. Existing law on disabled employment rights in Britain is set out and its strengths and weaknesses weighed. The employment rights of disabled workers in the European Community, the United States, Canada and Australia are narrated. Then, using comparative legal methodology, a number of problems and issues in the regulation of disability-related employment discrimination (and the promotion of equal opportunities) are recounted and critically analysed. These problems and issues include the definition of disability discrimination, identification of the protected class, fitness for work and employment qualification, use of reasonable accommodation and positive action, preferential treatment and the role of quotas, and enforcement strategies and remedial action. The experience of the United States is recruited as the primary basis of comparison and lessons for suggested legal reforms in Britain are pointed out. Some general conclusions on the efficacy of disability discrimination laws are drawn. The study surveys a wide variety of primary and secondary legal materials, including legislation and case law, and reviews the pertinent literature drawn from legal scholarship and other relevant disciplines. It does so in the context of a theoretical perspective that borrows from the body of legal theory and concepts developed in race and gender discrimination law.

Production and Reproduction in Waged Domestic Labour Processes: A Case Study of Housekeeping Services Franchises in Southern Ontario - Moss, Jane Pamela (McMaster University, 1993)
This thesis is a study of the commodification of domestic labour in a particular type of domestic labour firm, housekeeping services franchises, in southern Ontario. Specifically, I investigate the labour-related experiences of the women employed in these franchises. There are two goals: (1) to draw out, describe, and analyse the relations and processes within which women engage while employed as workers in housekeeping services franchises and (2) to devise conceptual tools that can be used to refine and enhance explanations of waged domestic labour processes. I designed the project in three phases. I was employed at a housekeeping services franchise in Hamilton for three and a half months in the Spring of 1990. During the Fall of 1990 and Winter and Spring of 1991 I carried out multiple-depth conversations with 14 women employed as franchise housekeepers and ten interviews with managers/owners of franchises in southern Ontario and head office personnel. The analysis and write-up began in May 1991 and was completed in February 1993. The thesis as a report of this research can be divided into three areas, methodology, theory, and topic. Methodologically, I implement a set of feminist principles drawn from a feminist marxist framework. Theoretically, I offer a set of abstractions which together conceptualise waged domestic labour processes in a post-1973 organisation of production relations: 'total labour', production regime, class formation, and gender formation. These concepts in part explain and in part interpret workers' experiences of waged domestic labour processes. Topically, I extend domestic labour studies to include waged domestic labour processes that generate surplus value. I focus on the transformation of the traditional relation of "mistress and maid" to that of "mistress and manager" and "manager and maid".

Experiencing Patriarchy: Women, Work and Trade Unionism at Eaton's - Aylward, Sandra Elizabeth (McMaster University, 1992)
This research tested the applicability of Sylvia Walby's theoretical model of patriarchy to a case study of women working and unionizing at the T. Eaton Co. The focus was on the two time periods 1947-1952 and 1984-86 when a unionization drive was underway at Eaton's. In-depth interviewing was conducted with over ninety participants in the events. Support was found for the aspects of Walby's model that pertain to patriarchal relations within paid work. In addition, forms of women's resistance and empowerment were examined specifically in relation to the 1984 unionization events. It was found that women's political action contains components that traditional politics do not explain. Overall, the findings of this case study strongly support Walby's position that gender inequality in society as a whole cannot be understood without the concept of patriarchy (1990).
https://macsphere.mcmaster.ca/handle/11375/15503 OCLC: 28494841
Keywords: Academic theses; Thèses et écrits académiques; dissertations

Class and Gender in the Toronto Printing Trades, 1870-1914 - Burr, Christina Ann (Memorial University, 1992)
The purpose of this study was to examine class and gender relations in the Toronto printing trades during a period of intensive industrial capitalist growth between 1870 and 1914. Consistent with socialist feminism, it is argued that the experience of class cannot be comprehended without a consideration of gender relations. – During the late nineteenth century segmentation and specialization occurred within the Toronto printing industry with technological innovations in the production process, the emergence of the daily press, and a proliferation of firms specializing in a product line or in a particular aspect of the production process. Throughout the period from 1870 to 1914 male workers dominated the Toronto printing trades. Women were segregated in those jobs socially designated as unskilled, specifically, pressfeeding, and folding, stitching, and collating in the binderies. – The bulk of the study focuses on printing-trades workers employed at the Methodist Book and Publishing House, a large Church-owned multi-faceted printing and bookbinding establishment. An analysis of a select group of printing-trades workers derived from the firm's extant payrolls for the fiscal years 1882-83 and 1890-91, and for the calendar year 1902, and identified by occupation through linkages with the city directories, revealed a hierarchical and gender division of labour typical of the broader late nineteenth- and early twentieth-century Toronto printing industry. Developing the argument that to understand fully the complex interaction of patriarchy and capitalism we must go beyond the workplace and consider the family, the household economies of the sample group of Methodist Book Room workers were analysed using linkages between the decennial census manuscripts and the municipal tax assessments. The majority of Book Room workers studied lived in subsistence-level conditions and tended to rely on the income of one or more secondary wage earners. A breadwinner wage was a reality only for comparatively few skilled male printing-trades workers. – In the latter part of the study, the trade unionism of Toronto printing-trades workers was explored. Male unionists in Toronto Typographical Union, Local 91 successfully defended their skilled-worker status with industrial capitalist incursions and effectively excluded women compositors from membership in the local typographical union. Considerable attention was also given to the organization of bookbinders, including the formation of the short-lived Women's Bindery Union. – The study is thus an attempt at a convergence between socialist feminist theory, and working-class and labour-history, feminist history, and family history.

The Impact of Royal Commissions on Public Policy: Worker’s Compensation in British Columbia, 1941-1968 - Chaklader, Anjan K. (University of British Columbia, 1992)
During the years 1941 to 1968, issues relating to workers’ compensation in British Columbia were subjected to the unprecedented number of three royal commissions. An explanatory framework that evaluates the merits of the commissions and their recommendations, both perceived and otherwise, and the degree to which governments adopted the recommendations, is presented in this paper. The framework is designed to make use of the available relevant primary sources, particularly minutes of the commission proceedings, newspaper accounts and legislative statutes. All three of the Commissions were thorough, well-received exercises whose recommendations were almost wholly adopted by B.C. governments, though in differing time frames. The need for the second Commission, which was created a mere six years after the finish of the first, primarily arose because of rapid developments in the B.C. labour movement during the mid-1940’s. An infusion of leaders with communist ties caused it to harden demands for workers’ compensation benefits and reforms. The first Commission had been considered a success by all parties, but the context of its recommendations had changed due to the increase in labour’s militancy. This second Commission was also considered to be reasonably successful. However, dissatisfaction with a Workmen’s Compensation Board that had completely turned over shortly after the second Commission, led to demands, particularly by labour, to create another commission to review its work and procedures. Board members, at that time, were subject to long tenures and were without any formal mechanism with which to be reviewed. Critical to the success of the three Commissions was the independent, non-partisan nature of their proceedings and recommendations. Because of this, the credibility accorded to the recommendations, particularly by labour, caused the Commissions to supercede the traditional mode of cabinet or legislative committtee deliberation for public policy formation in this case. The series of Commissions ended because of satisfaction with the Workmen’s Compensation Act, a much higher turnover rate of the Board and increased strength of the provincial labour-backed New Democratic Party. Thus, the Commissions and the three B.C. Supreme Court Justices that served as the Commissioners, must go down in history has having played a significant role in the evolution of occupational safety and health policy in British Columbia.

Social Experiments and Social Policy Formulation: A Study of the Manitoba Basic Annual Income Experiment - Farthing, Gerald Brian (London School of Economics and Political Science (University of London), 1992)
In 1973 the Government of Canada and the ten provinces agreed to undertake jointly a complete review of Canada's social security system. The review and development of policy options was scheduled to be completed by 1975 with the implementation of chosen options to take a further two or three years. A prominent and much debated policy option with respect to income security was a guaranteed annual income. In 1974 the Government of Canada and the Province of Manitoba agreed jointly to undertake a guaranteed annual income experiment called the Manitoba Basic Annual Income Experiment. The primary research purpose of the experiment was to provide information respecting the labour supply response of the recipients of a system of guaranteed annual income payments. The experiment officially ended in March, 1979, but did not report on the labour supply response. This study examines the history and fate of the Manitoba Basic Annual Income Experiment. Two major conclusions are drawn. The first conclusion is that the Government of Canada had decided shortly after the experiment had begun that it would not support a one-tiered guaranteed annual income program such as was being tested by the experiment. The second conclusion is that social policy research that requires the use of rigorous and complex social science methodology should be considered an important part of the normal policy-making process, but should be conducted by a research body that is independent of the initiating government(s).

Beyond Regina: The On to Ottawa Trek in Manitoba and Ontario - Hewitt, Steven Roy (University of Saskatchewan, 1992)
Beyond Regina examines the reaction in Manitoba and Ontario to the On to Ottawa Trek, specifically in the cities the marchers would have passed through had they not been stopped in the capital of Saskatchewan: Winnipeg, Fort William and Port Arthur, Sudbury, Toronto and Ottawa. Two major studies on the Trek appeared in the 1980s, Victor Howard's We Were the Salt of the Earth and Lome A. Brown's When Freedom Was Lost. Both monographs offer copious detail on the Trekkers and their journey from Vancouver to Regina, something necessary to provide true context to the event. A national mantle is claimed for the march by the respective authors but the lack of substance in this area effectively renders the event a regional protest movement. The thesis examines in particular the extent and nature of Trek support in various Manitoba and Ontario cities. It seeks to provide a broader perspective on the On to Ottawa Trek and therein a more comprehensive portrait of the event.

Bureaucracy, Class, and Ideology: The Vancouver Trades and Labour Council, 1889-1909 - Leier, Mark (James Mark) (Memorial University, 1992)
This dissertation is an examination of bureaucracy, class, and ideology in the labour movement. It seeks to understand what is meant by the term labour bureaucracy and to determine the degree to which bureaucracy shaped ideology in the Vancouver Trades and Labour Council from 1889 to 1909. – The first section is an analysis of the theoretical literature and historiography of the labour bureaucracy. As well as providing an overview of the topic, the thesis tries to formulate a different definition of the labour bureaucracy, one that focuses on the power of the bureaucrats, rather than their ideology. The second section is a study of the officials and leaders that made up the VTLC from its beginning in 1889 to the founding of the B.C. Federation of Labour twenty years later. In this section, the ideology of the council is examined to evaluate the impact of bureaucracy on the labour movement. The policies and structure of the council are studied in detail to show how the separation of the leaders from the led developed over time and to demonstrate why bureaucratic solutions - the hiring of experts, reliance on government intervention, the routinization of procedures, and the creation of labour institutions - were taken and to outline the effect they had. The conflict between labourists and socialists is examined closely to suggest first that bureaucracy is not limited to labour leaders of any single ideology, and second, that the needs of the labour movement and the demands of bureaucracy itself tended to soften ideological battles. Even with the ascension of socialists to the council in 1907-1909, continuity remained the hallmark of the labour council, in part because socialists had no particular commitment to rank-and-file control of the labour movement. Finally, the lives and class positions of the labour leaders are illustrated to try to shed some light on the ways in which bureaucracy, class, and ideology become intertwined.
OCLC: 1319163467
Keywords: Academic theses; Thèses et écrits académiques; dissertations

A History of the Ottawa Allied Trades and Labour Association, 1897-1922: A Study of Working-Class Resistance and Accommodation by the Craft Worker - Sykes, Peggy J. (Carleton University, 1992)
This thesis is a history of the Ottawa Allied Trades and Labour Association in the years 1897 to 1922. The Association is a predecessor of the city's contemporary labour council, Ottawa and District Labour Council. In the years 1897 to 1922, the council derived its authority from its craft union membership, which was affiliated to the Dominion Trades and Labour Congress and the American Federation of Labor. Recent studies have altered traditional interpretations of the events in Canadian labour history, particularly following World War I. It has been generally accepted that the radicalism of the working-class was confined primarily to the western regions. A reinterpretation postulates that the events of 1919 were nation-wide. This thesis attempts to demonstrate that the Ottawa Allied Trades and Labour Association played a part in the working-class revolt of 1919, and that this radicalism was based upon prior experiences of collective bargaining and mobilization.
Keywords: Ontario; Social sciences

Farm Women and Their Work in Delta, British Columbia, 1900-1939 - Szychter, Gwendolyn Mary (Simon Fraser University, 1992)
This thesis explores and categorizes the economic contribution of farm women in the Fraser Delta during the period 1900-1939. The sources were mainly oral history interviews, as well as personal diaries, local newspapers, and government documents. In the particular social and economic context in which they ran their households and raised their families, the twenty-four women whose lives were explored shared many common characteristics, but an effort was made to convey a sense of these women as individuals as well as members of a larger group....

Agribusiness and Hired Farm Labour in the Ontario Tomato Industry - Wall, Ellen (McMaster University, 1992)
Using the Ontario processed tomato industry as a case study, this dissertation examines how the situation facing hired labour in Ontario agriculture is influenced by the growth of agribusiness. The trend to mechanize harvest operations symbolizes the development of agribusiness. Explanations for changes in labour markets, labour process, and control and organization of work activity that accompany mechanization are explained with reference to established models for change in contemporary agricultural structure. The utility of these models, which include evolutionist, integrationist, and historicist perspectives, is tested with original data. In general, the evolutionist model is found to be the most satisfactory Data were gathered during 1988-1989 by various methods: historical research, interviews, and participant and non-participant observation. This study concludes that, with mechanization, the farm labour market changes and takes on features similar to the labour market for work classified as unskilled and low status in non-farm industries. It is also evident that hired agricultural workers (and many of the growers who employ them) lose control over work activity and conditions when tomatoes are machine harvested. The primary benefactors from such changes are the major processing firms whose influence continues to dominate the agro-food industry. This investigation into hired farm labour and agribusiness is significant because it is among the first to address the situation facing hired agricultural workers in Ontario. As well, it not only adds new material to scholarly debates about changes in agricultural structure, but also contributes to Canadian political economy studies.

Against the Grain: Accommodation to Conflict in Labour-Capital Relations in Prairie Agriculture, 1880-1930 - Danysk, Cecilia (McGill University, 1991)
Between the 1880s and the Great Depression agriculture emerged and matured as the mainstay of the prairie economy. Farm workers were essential to the developing economy and society, but their place in the rural west was ambiguous. During the pioneering period, labour shortages and accessible land gave farm workers bargaining strength in the labour market and a niche in prairie society. A cooperative working relationship and a shared ideology resulted in a lack of overt conflict between labour and capital. But as lands were taken, farm workers faced more and more the necessity of remaining as wage labourers. Their position became institutionalized. The First World War highlighted the conflict that was fundamental to labour-capital relations, as farm workers and farmers alike bolstered their economic positions. Labour and capital entered the post-war decade recognizing the increasing divergence of their aims. Their relationship became more overtly conflictual. Throughout this transformation, farm workers used strategies to influence the shape and rate of change in the industry and to maintain significant control over their own working lives. They responded as members of the working class, as active agents in relationships with their employers and with capitalism.

A Union on the Hill: The International Union of Mine, Mill and Smelter Workers and the Organization of Trail Smelter and Chemical Workers, 1938-1945 - Roth, David Michael (Simon Fraser University, 1991)
Using union records, newspapers and relevant secondary sources this thesis examines the complex process of union organization at a local level, an area of union activity that has received little attention from Canadian labour historians. In 1938, the International Union of Mine Mill and Smelter Workers began a drive to organize workers at the Consolidated Mining and Smelting Company's industrial complex in Trail, British Columbia. Although the campaign took place in an era of explosive trade union growth, the attempt to establish a local in Trail was long and difficult, succeeding only in 1945. The following study analyzes the various factors which limited or aided Local 480's growth during this seven year period. The historical development of both company and union is examined along with organizational strategies, management reaction, worker response and the effect of labour legislation. This thesis argues that, while all the above factors were important, labour legislation had the greatest impact on the organization process and was instrumental in the successful completion of Local 480's campaign.

Defining the Chinese Other: White Supremacy, Schooling and Social Structure in British Columbia Before 1923 - Stanley, Timothy John (University of British Columbia, 1991)
During the late nineteenth and early twentieth centuries, racism, in the form of white supremacy, shaped relations between whites and Chinese British Columbians. In resisting and accommodating to white supremacy, the Chinese were active participants, along with the members of the dominant society, in shaping these relations. White supremacy was consequently a dynamic system, one whose many parts were continually in flux, and whose central constructs—notions of "race" and British Columbia as "a White Man's province"—were largely political in nature. The thesis argues that white supremacy, as both ideology and organization, was deeply imbedded in British Columbia society. Exclusion based on "race" was incorporated into government institutions as they were remade at Confederation in an effort to enhance the power of white male property-owners. By the early twentieth century, ideological constructs of "the Chinaman" and "the Oriental" were used as foils in the creation of identities as "whites" and as "Canadians." The official public school curriculum transmitted these notions, while schools themselves organized supremacy in practice by imposing racial segregation on many Chinese students. In reaction, the Chinese created their own institutions and ideologies. While these institutions often had continuities with the culture of South China, the place of origin of most B.C. Chinese, they were primarily adaptations to the conditions of British Columbia, including the realities of racism. Chinese language schools played an especially important role in helping to create a Chinese merchant public separate from the dominant society. This public was at once the consequence of exclusion and the greatest community resource in resisting white supremacy. The study concludes by questioning the workability of contemporary anti-racist strategies which treat racism as a marginal phenomenon, or as merely a set of mistaken ideas. Instead, it suggests that such strategies must recognize that racism is one of the major structures of Canadian society.

Woods Cree Women's Labour Within the Subsistence-Based Mixed Economy of Pelican Narrows, Saskatchewan - Youngs, Colleen (University of Saskatchewan, 1991)
The subsistence-based mixed economy of Northern Canada is both productive and essential to community life and survival (Berger, 1977; Brody, 1981 ; Wenzel, 1981; Asch, 1982; Fait, 1982; Usher, 1982). Usher further states that this economy needs to be maintained for its economic value and fundamental linkages to social and cultural conditions. Most researchers state that the productivity of this economy depends on the interdependency of women's and men's work; however, within the extensive literature on this subject few writers examine the labour of women. The purpose of this thesis is to document and analyze Woods Cree women's labour within the subsistence-based mixed economy. Their labour, which is embedded in the profoundly different voice of Woods Cree culture, is best understood through detailed case studies. Oral histories were collected from three generations of Woods Cree Women aged sixteen to seventy, covering the period between 1900 and 1989. Usher's analytical framework of the anatomy of the Northern economy is a most useful model; however, it required some adjustment in order to address gender affected production. The feminist critiques of Delphy and Nicholson are used in analyzing the nature of women's labour. The research found that although Woods Cree women's labour has changed over time and space, it is still essential to the functioning and maintenance of the subsistence-based mixed economy.

Children of the Industrial Age: Children, Work, and Welfare in Late Nineteenth-Century Ontario - Bullen, John (University of Ottawa, 1990)
...This study describes and analyzes the extent to which work, as a philosophical concept and as an economic reality, influenced the lives of working-class children in late nineteenth-century urban Ontario. Chapter I examines the impact of industrialization and urbanization on the working-class family and describes how the concepts of work and social control intersected to feed the development of welfare programmes based on middle-class objectives. Chapter II examines the conditions and experiences of children in the paid labour force, focussing particularly on the family economy, labour legislation, and the response of reformers and trade unionists. In addition, chapter II discusses the link between a child's economic responsibilities and his or her opportunities for personal development and social mobility. Chapter III applies the themes of chapter II to youngsters who worked in the home and on the street. Chapter IV describes the work experiences of children who spent part of their early lives in orphanages or foster homes and analyzes the reform impulse behind this style of welfare. Chapter V applies the themes of chapter IV to youngsters committed to reformatories, refuges, and industrial schools. Chapter VI examines the treatment, work experiences, and social development of needy British children who filled the roles of agricultural labourers and domestic servants in Canadian homes and discusses the motivations behind this programme. Chapter VII examines the connection between youngsters' work responsibilities and school attendance and analyzes the education system's approach to the issue of children and work. Throughout the text, the thesis argues that child labour composed a critical element of a complex social culture, deeply rooted in a capitalist economy, that defined work in both a material and philosophical sense. At the material level, working children made essential contributions to families that could not survive in the city on parental wages alone. Simultaneously children provided cheap labour for self-serving employers in industrial, commercial, and domestic settings. At the philosophical level, most members of nineteenth-century society believed that hard, honest work held the key to life-long success and happiness. This view prevailed among middle-class reformers who additionally believed that child labour under proper supervision would preserve social order and avoid future welfare costs by creating a class of efficient and compliant workers. The failure of this culture of work to balance its social and economic motivations, however, led to suffering and exploitation for youngsters more often than it created personal opportunity and social harmony. As the poorest, most powerless, and least secure members of industrial society, children of the working class most visibly bore the scars inflicted by a social system designed to serve middle- and upper-class interests.
OCLC: 23836592

Competing Perspectives on the Knights of Labor: With Special Reference to South-Central Ontario, 1883-1886. - Graves, Greg (Carleton University, 1990)
The Noble and Holy Order of the Knights of Labor was the leading labor organization in North America during the late nineteenth century. The entire history of the Knights in Canada spans approximately thirty years (1875-1907). In the early to mid-1880s the Order expanded rapidly throughout the cities, towns, and villages of Ontario. After the mid-1880s, the number of local assemblies across Ontario began to decline. A significant percentage of the Ontario work-force was drawn to the Knights over the course of their history. The Knights were the first North American union to organize workers based on an all-inclusive style of membership. All workers, regardless of skill level, gender, ethnicity, and religion were welcome into the Noble and Holy Order. Historians and social scientists have advanced several competing perspectives on the Knights of Labor. This thesis evaluates the positions that the competing 'labor schools' have advanced on the Order, with special reference to south central Ontario in the 1880s. The evaluation the competing labor schools is based on a content analysis of the late-nineteenth century labor press. The main sample selected for this thesis is Hamilton's Palladium of Labor (1883-1886). A combination of primary and secondary data sources are examined in order to build support for one of the competing perspectives that has been advanced on the Knights.

Women, War, and Work Female Textile Workers in Cornwall, Ontario, 1936-1946 - Scheinberg, Ellen Carrie (Queen's University, 1990)
Over the past two decades, the majority of works written on women's experiences during the Second World War have focused on those middle-class women who temporarily toiled in the war industries. This study attempts to redress the imbalance that exists in this field by examining the lives of working-class women in the textile mills of Cornwall, Ontario from 1936-1946. By relying on the Marxist Feminist dual structural theory, this study attempts to illustrate the centrality of patriarchal capitalism in determining women's lives in the mills during this period. Rather than experiencing a period of financial and social opportunity during the 1940s, as many mainstream scholars contend, Cornwall's female textile workers continued to be relegated to the lower-skilled, low paying, "female" positions in the mills, even during the prosperous war years. This continuation of a segmented work force is attributed to the patriarchal and capitalist structures that in essence were responsible for the women's inferior position in the mills. Rather than remaining passive victims, these women devised certain strategies aimed at resisting these two oppressive forces within the mills. Women were thus often able to establish their own types of organizational structures that occasionally allowed them to stand up against their aggressors in the mills.
Keywords: Women textile workers – Ontario – Cornwall – History – 20th century

Labour Versus the State: The Conflicting Policy Interests and Ideas of the Canadian Trade Union Movement and the Federal Conservative Government, 1984-1988. - Wise, Bruce (Carleton University, 1990)
The subject of this research is the conflicting policy interests and ideas of Canadian organized labour and the federal Conservative government between 1984 and 1988. This conflict is placed within the context of the political and economic changes accompanying the international restructuring of capital and focusses on the opposition of the Canadian trade union movement to federal economic development policies. The struggle of ideas and interests surrounding specific policy areas is detailed. These areas include deficit reduction, the privatization of Crown corporations and government services, deregulation of certain economic activities and sectors and comprehensive bilateral free trade with the United States. Labour's opposition is shown to have manifested in a new strategy for building a broad-based coalition with other popular interests, in an effort to defeat the Conservative government and their policies at the polls. The research work concludes with speculation as to the future of labour and popular-coalition politics.

From Plant to Politics: The Canadian UAW, 1936-1984 - Yates, Charlotte A. B. (Charlotte Alyce Bronwen) (Carleton University, 1990)
This thesis studies the historically varied political strategies pursued by the Canadian branch of the International Union, United Automobile, Aerospace and Agricultural Implement Workers in the union's attempts to shift the balance of power in its favour between 1936 and 1984. In so doing, the thesis examines and explains the Canadian UAW's changing relations to governments, corporations and political parties. Particular emphasis is placed on explaining the conditions under which this union pursued militant forms of political action. The analytical framework used in this work is constructed around an understanding of unions as strategic actors which make choices under limits arising from the historical, political-economic and internal conditions in which the union operates. In turn, a union's strategic capacity–defined as its ability to pursue a particular course of action successfully–is understood as being determined by both external conditions, such as the state of the economy, and by the internal resources and dynamics of the union. The most important external constraint on the Canadian UAW's strategic pursuits was the construction/destruction of the Fordist mode of regulation, which was organized around a wage/productivity trade-off and encouraged the institutionalization of labour-management relations, union control of membership militancy and the practice of 'responsible' unionism. At the same, it is argued that the Canadian UAW shaped the nature of this compromise and the timing of its own acceptance of this arrangement. More specifically, the Canadian UAW's distinctive organizational structure and collective identity are argued to have delayed the union's acceptance of the practices of 'responsible' unionism and influenced the particular regulatory mechanisms put into place in the Canadian auto industry. Overall, this study finds that, in contrast to current interpretations of union postwar political behaviour, Canadian Autoworkers continued to pursue militant, mobilization-based forms of political action until the early 1960's. It was only at this time that Canadian Autoworkers appeared to accept constraints on their militancy in exchange for improved wages and benefits and greater access to political decision-making. This period of detente between the UAW, governments and corporations was short-lived, however, owing both to emergent strains within the union between the rank and file and the leadership and the crisis of Fordism. Consequently, the UAW, in an attempt to protect its organizational integrity and position of strength in the workplace and society, returned to militant forms of political action, the effects of which were a shift in the balance of power in favour of the union and Canadian Autoworkers' split from their International union.
OCLC: 23693105

Social, Economic and Political Factors Influencing the Supply and Demand of Foreign Domestic Workers - DeVan, Mary Elizabeth (University of British Columbia, 1989)
This thesis addresses the issue of foreign domestic workers. The government of Canada has been involved in the recruitment of people to perform domestic service for households since the turn of the century. The devaluation of domestic labour and increasing employment opportunities for Canadian women resulted in a constant shortage of labour to fill the demand. A variety of programs have been initiated to solve the "servant problem" culminating in the Foreign Domestic Movement in 1981. Within this policy foreign domestics are classified as a category of migrant labour and, as such, are formally denied citizenship rights. The majority of workers who come to Canada as foreign domestics under this program are Filipino women. These women often migrate to Canada as domestic workers due to limited options for employment in their home country. Their need to remain in Canada due to limited options in the Philippines, the lack of political rights in Canada, and the restrictions placed on workers who enter Canada under the Foreign Domestic Movement combine to situate these women in a position of dependence and vulnerability. In addition, live-in domestics perform devalued labour within an isolated work setting, and are often not included within provincial labour standards. These conditions keep wages depressed and lessen the ability to bargain for improved conditions of employment. The thesis problem is examined within an historic context. In addition to a literature review of the specific topic and related areas of gender and migrant labour, the data are from Statistics Canada, Employment and Immigration and the Special Collections Division of the University of British Columbia. The data shows : the labour market activity of Canadian women, the shift away from domestic service as other alternatives became open, the increasing number of dual income earning families, and the number of foreign domestics recruited to provide domestic service for Canadian households. Interviews with a variety of people draw out the particular factors leading to the reasons for the supply and demand of this group of workers. In addition, the interviews point to specific problems frequently experienced by women who work as live-in domestics.

A Comparative Approach to the Study of Community and Work in Canadian Mining and Forestry Towns - Dignard, Louise (Carleton University, 1989)
The purpose of the thesis is to compare mining and forestry single-industry-towns in Canada in terms of their community and work structures. More specifically, what is examined is how these structures interconnect at local levels and impact upon social relations and class consciousness. Following a critical review of selected literature in political economy, labour and community studies, insights from Harold Innis' staple theory are expanded in order to link these three theoretical approaches and to justify the analysis of community and work in specific resource contexts. Drawing from this discussion, a comparative model of forestry and mining town structures is outlined. The main underlying idea is that the overall structure of forestry towns could be seen as more modern–in spite of its traditional elements–for it is more diversified and opaque, whereas that of mining towns is more archaic–despite the modern features of its industry–because of the greater control industry has on economic and community life. This theoretical model however needs further empirical testing.

Woodworkers and Legitimacy: The IWA in Canada, 1937-1957 - Gray, Stephen (Simon Fraser University, 1989)
During the late 1930s and early 1940s, as a part of broad North American phenomenon of industrial militancy and labour law reform, the International Woodworkers of America (IWA) became recognized as the legitimate bargaining agency for most woodworkers throughout the Pacific coast. In British Columbia, as a basis for consolidating trade unionism and furthering the class struggle within the important forest industry, a well-organized cadre of communist trade union militants channelled the syndicalist and revolutionary traditions of earlier twentieth century woodworkers organization into District One of the IWA, and into compliance with state institutions governing industrial relations that emerged during World War Two. By 1948, though, the quest for legitimacy had entrammelled the communist leaders of District One in a restrictive web of institutional, bureaucratic and political relationships from which they sought escape by serving ties with the union they had struggled hard to establish. Their fledgling Woodworkers' Industrial Union of Canada, considered illegitimate by both the state and the mainstream labour movement, attracted only a small minority of woodworkers and enjoyed a very short, unremarkable history. Through a detailed examination of union, industry and state records of industrial relations activity, this thesis provides both narrative and analysis of a complex course of events leading from the era of the open shop, through the attainment or union recognition and a period of consolidation, to a final confrontation in 1947-48 within the Canadian IWA between two distinct visions of trade union practice. Ultimately, the early, militant woodworker traditions, subsumed within communist industrial unionism, proved to be in contradiction with the institutional structures governing relations between labour and capital in postwar Canada. The post-1948 leaders of IWA District One more closely reflected the emerging North American reality in their approach to trade unionism and industrial relations than did their predecessors. Out of the intense struggles of the 1930s and 40s, a full-blown business unionism emerged by the latter 1950s as the governing programme of the modern Canadian IWA, albeit a programme not universally accepted by rank-and-file woodworkers....
Keywords: British Columbia; History; Iron and steel workers; Labor laws and legislation; Labor unions; Miners; Organizing; Trail

In the Buzzard's Shadow: Craft Subculture, Working-Class Activism, and Winnipeg's Custom Tailoring Trade, C1882-1921 - Hample, John Erwin (University of Manitoba, 1989)
Winnipeg tailoring craftworkers formed four unions during 1882-1921. This master's thesis in Canadian labour history finds that their institutionally-differentiated practice of labour organization expressed a sustained remedial effort to codify, enforce and reformulate elements of their craft subculture. They mounted this effort in response to the competitive constraints of clothing sector capitalism as these conditioned workplace experience in the city trade as well as the tailors' identifications with other working-class Winnipeggers. The study first discusses the reproduction of tailoring craft subculture in the energing city market, and offers a periodized sketch of the 'double jeopardy' which merchant tailors faced as master artisans and as clothing sector capitalists. The remaining chapters employ this periodization to organize discussion of the course of working-class activism pursued by the tailors. During c1882-1900, the integration of national markets in sewn clothing and in tailoring craft labour power exhausted the jour tailors' earliest attempts - the 'Winnipeg Operative Tailors Union' (fl. 1882) and Harmony Local Assembly 9036 of the Knights of Labor (fl. 1886-87) - to devise a viable labour organization. Only with the chartering of Journeymen Tailors' Union Local 70 (fl. 1892- 1919) was this achieved. During c1901-13, Local 70 secured significant wage and other concessions from boss tailors. Wheat Boom-era economic development, coupled with a persisting city-market skills scarcity, broadly favoured such gains. Meanwhile, JTU Local 70 inbibed ideas about industrial unionism and social radicalisn which were encouraged by such figures as John T. Mortimer (d1908), a Socialist Party of Canada activist. During c1914-21, the custom tailors' experience was overshadowed by the exigencies of war-making, the labour revolt, and of the post-war recession. Paradoxically, Local 70 momentarily became in 1918 the largest JTU local in Canada, yet soon bolted from the international parent body to reconstitute itself as Tailors' Industrial Unit Number One of the One Big Union. The study interprets this development in terms of Local 70's war-time isolations from the south and the east, which were counterbalanced by an epochal quickening of working-class activist identifications and social conflict in the city itself. But the new OBU Unit retained the jour tailors' craft-bounded distinctiveness within the OBU's organizational structure, and was blooded in 1921 attempting to enforce a contractual measure inherited from Local 70. The study's major primary sources include the local labour press, as well as an intensive reading of the JTU's journal, The Tailor, 1887-1921. The study's general approach is indebted chiefly to perspectives suggested by the work of Gregory S. Kealey, Herbert Gutman, Eric Hobsbawm, David Montgomery, Geoffrey Crossick, and David H. Bensman.

Freedom of Association in Canada: The Dilemma for Trade Unions in a Liberal Society - Hudson, Stephanie Lee (University of British Columbia, 1989)
Trade unions in a liberal society are caught on the horns of a dilemma over freedom of association. In respect to the Canadian Charter of Rights and Freedoms, unions are faced with relying on the positive freedom to associate as a defence for union security clauses, and, at the same time, denying freedom from association claims of those who do not wish to participate in union membership and/or union activities. The aim of this thesis is to explore that dilemma, and to assess some of the possible strategies union leaders could employ to come to terms with it. The dilemma that trade unions face consists of several elements. The source of the dilemma is found in the conflict over negative and positive liberty and the nature of freedom, and more specifically over competing visions of freedom of association in the trade union context. This conflict has found its way into the courts; in particular, the Lavigne case, which challenges political expenditures by unions (in certain circumstances), has generated much controversy and resulted in two opposing judicial decisions. However, the courts are not the only arena in which an attempt is being made to balance the competing claims of liberty; the political realm offers another avenue through which trade unions could attempt to influence labour legislation. However, unlike other intervenors such as women's or aboriginal groups, the trade union movement was largely absent from pre-Charter Joint Committee hearings. In hindsight it is quite clear that labour's non-participation represented a missed opportunity to influence the wording of freedom of association in a way that would make challenges from a negative liberty standpoint more difficult. In addition, the post-Charter prospects of lobbying government to implement legislation which would prevent negative liberty claims from succeeding (possibly through the "notwithstanding" clause in the Charter) appear quite dismal. Thus, a trade union strategy which would look for a political avenue out of its dilemma was not implemented pre-Charter and looks doubtful post-Charter. Nonetheless, in terms of the individual and his freedom (of association) in a liberal society, a fair balance between negative and positive liberty claims should be struck; one which allows limited coerion of the individual in the form of union security (the agency shop), but also restricts trade unions in the form of limits on political expenditures. This balance may, however, seriously threaten the political role of the trade union community. But, while individuals retain their right to exercise negative liberty claims, whether or not they exercise them depends upon their moral beliefs. And an individual convinced of the importance of the trade union community and the threat to that community posed by negative liberty claims, will be much less likely to exercise his right to invoke freedom from association. Unions might be able to meet this difficulty, however, by working towards a consensus about the importance of the trade union community and, more particularly, its political objectives. Such a strategy may be the most suitable alternative that trade unions can adopt in a liberal society.

The Canadian Working Class and Industrial Legality, 1939-1949 - Matheson, David William Tudor (Queen's University, 1989)
With few expections trade union histories, even those emanating from the broad left, trace the development of the union movement through a series of hard-won victories codified in modern collective bargaining law. This thesis joins with more recent critical approahcees to industrial legality in a fundamental quesstioning of the effect of progressive legal victories. American scholarship especially has begun to probe the limitations imposed by a framework of rigid legal rules that work as much to circumscribe the expression of workers' interests as they do to promote them. In an attempt to understand this two-sidedness of industrial legality, the first chapter of the thesis embarks on a theoretical examination of law, paying particular attention to the meaning of the base/superstructure configuration. The chapter builds on the original writings of Marx and Engels - which never fully developed a theory of 'law' - bringing their concepts into the context of twentieth-century capitalism and highlighting the role of class struggle. In this way, the law is revealed as growing out of, and sharing, the essential values that constitute cpaitalist accumulation - values that elevate property and the procewss of production and accumulation above the aspirations of the working class. The second chapter traces the development of industrial legality in Canada, situating it in terms of class formation, class struggle, and the role of the state. This is a synthetic account of the formative years of Canadian industrial legislation, setting the stage for the analysis of collective agreements that follows. Chapter 3 explores the developing content of collective agreements forged in the 1940s through a sample of 120 contracts signed between employers and the Steelworkers, Packinghouse Workers, and Mine, Mill and Smelter Workers. Of particular interest is the effect of management rights clauses, union security and seniority clauses, and grievance procedures. Finally, the last chapter will consider the dilemmas facing unions that now find themselves caught in the web of legality, with alienated memberships and the possibilities for class-action severely circumscribed.
OCLC: 24215238
Keywords: Academic theses; Thèses et écrits académiques

Skilled Service and Women's Work: Canadian Nursing, 1920-1939 - McPherson, Kathryn Mae (Simon Fraser University, 1989)
This thesis examines the experiences, attitudes and actions of the women who trained and worked as graduate nurses during the 1920-1939 years–of the third generation of hospital-trained Canadian nurses. The 1920s and 1930s were decades of crisis for Canadian nursing, and the occupation's majority, working in the private duty sector, was most severely affected by the problems of oversupply and underemployment. The economic crisis was national in scope, and endemic to the health care system, and was therefore exacerbated rather than created by the depression of the 1930s. In order to analyze the structure and content of the occupation during these years of crisis, a wide variety of national sources were consulted, supplemented by a detailed case study of nursing in the prairie metropolis of Winnipeg, Manitoba. This research on Canadian nursing during the 1920s and 1930s adds another chapter to the growing scholarly literature on Canadian women and work. It also contributes to the secondary literature on the social history of medicine and of labour in two particular ways. First, as the largest health care workforce, the actions of graduate nurses during the 1920s and 1930s, their agency, served as a critical, force within the development of the Canadian health care system, a force frequently overlooked within medical history. Secondly, the third generation of Canadian nurses borrowed from the organizational strategies of both professionals and trade unions, but neither concept fully captured the reality of nurses' occupational identity as women and as workers. This thesis argues that the third generation of Canadian nurses was recruited from sex-segregated female labour market. The many rituals and routines which constituted nursing technique were based on a theoretical understanding and practical application of the germ theory. As such, nursing practice during the interwar years must be defined as scientific. Nurses' scientific skills permitted practioners to integrate caring and curing, and thereby to create their own definition to what constituted skilled service. Out of this self-definition came a specific occupational identity which was reflected in the many associations designed to reflect nurses' interests. As the interwar decades progressed, conflict developed within nursing organizations as to appropriate solutions to the economic crisis. The compromise solution, hospital employment of graduate nurses, initiated the demise of both the apprenticeship system of hospital staffing, and private duty nursing. This solution successfully prevented the fracturing of nursing organizations in the 1920s and 1930s, but also facilitated the transformation of hospital staffing which would occur in the World War II years. This research suggests that the scholarly literature on professionalism, and on labour organizations, must more fully account for gender as a historical determinant. In suggesting a historical periodization for Canadian nursing history, and in focussing on the third generation of Canadian nurses who struggled through the economic crisis of the interwar decades, this thesis contributes to the growing body of scholarly literature dedicated to placing nursing history in history.

Economic Restructuring and Technological Change: Resistance and Control Among Inside Workers and Letter Carriers at Canada Post Corporation, St. John's, Newfoundland - Ripley, Paul (Memorial University, 1989)
This thesis is a comparative study of the changing work experience and relations of two groups of Canadian postal employees in St. John's, Newfoundland. Two related factors are identified as underwriting these changes: technological based reorganization of work and the demand of a conservative state for a move to a private sector model of operations. The latter factor includes the requirement for a deficit free, and even profit-generating, operation at Canada Post Corporation and the divestment of public ownership. Underlying this empirical analysis is a theoretical interest in the labour process, technology and the managerial problem of control. – I argue in this thesis that among inside postal workers, members of the Canadian Union of Postal Workers, technological change and the bureaucratic reorganization of work which has surrounded it has undermined their ability to resist management incursions on the shop floor. The subsequent shift in the frontier of control has enabled management to implement a number of productivity and efficiency measures, which from the workers' point of view, has had a major negative effect on their work experience and relations. Moreover, the recent move toward privatization and the generation of more flexible, casual labour further undermines the ability of workers to defend themselves. – While inside workers have had a continuous history of conflict over the degradation of work through technological change, letter carriers have experienced a relatively stable, institutionalized relationship with management during the past 15 years. This relationship, in contrast to the inside workers', may be characterized as "consent" based. However, with growing pressure on management to solve the economic "crisis" at Canada Post, the status quo between letter carriers and management is eroding and an ultimately antagonistic set of interests is being revealed. – The data from this comparative study lead to the conclusion that recent interest in the notion of consent within the labour process literature has definite theoretical and empirical limits which become apparent in examining production relations in periods of economic instability. On the other hand, the question of control of labour and technologicl change cannot be addressed in formulistic, determinist fashion. Rather, the unique organizational and historical characteristics of "each" labour process must be understood in its own context.

On the Stroll: Free Agents and Bonded Labour in the Street Prostitution Industry - Robertson, Margaret Susan (University of Saskatchewan, 1989)
This study analyzes the concept of alienated labour in the practice of street prostitution in Canada's prairie region and explores the relationship between profit-making relations in street prostitution and the exploitation of street prostitutes in this region. It begins with a brief introduction to the themes of social control that dominate within the Sociology of Prostitution and a discussion of the sources and limitations of data employed. The basic proposition that is drawn from this discussion is that the exploitation of street prostitutes is secured in the organization of the labour process of street prostitution. The review of relevant literature is organized around the basic themes of supply, demand and profit.. This organizational scheme allows the evaluation and critique of the loose application of economic concepts to the causal analysis of prostitution. It concludes with the finding that prostitution is the expression of a profit-making relation and establishes a basis for the analysis of the appropriation of labour within profit-making relations. In light of the focus on the regulation of working activity in economic organization, Marx's theory and method of historical materialism is identified as a fruitful conceptual framework for the analysis of this relation. The discussion of subjective interpretations of Marx's theory of alienation is followed by a detailed discussion of the ontological continuity and epistemological focusing of Marx's intellectual outlook. This leads into an explication of Marx's theory of alienation. A detailed description of the street prostitution commodity market and the street prostitution industry is constructed around the producer's relation to the product and activity of labour in the circulation and production of commodified intimacy. This is followed by a specific analysis of the concept of alienated labour as it is expressed in the social relations of production of the street prostitution industry. The conclusion that is reached is that two forms of alienated labour can be identified within the street prostitution industry in the Canadian prairie region. As free agents, the working activity of prostitutes is subject to regulation by the market and overall structure of the street prostitution industry, and the appropriation of labour is expressed in circulation. As bonded labour the working activity of prostitutes is subject to regulation by the social relations of production that are established between male owners and female workers. As such, the appropriation of labour is accomplished through relations of dependency and domination that are expressed in the production of commodified intimacy and the exploitation of the prostitute is stripped of any appearance of freedom.

Charles H. Millard, Architect of Industrial Unionism in Canada - Wilson, Jeffrey L. (Wilfrid Laurier University, 1989)
In 1937 the strike at General Motors in Oshawa resulted in the first major victory for the Congress of Industrial Organizations (CIO) in Canada. The president of the Oshawa local was Charles Millard (1896-1978), who subsequently played an influential role in most of the major developments in organized labour between 1937 and 1956. He was the first National Director of the Canadian branch of the United Steel Workers of America in 1943, a position which he retained until his retirement in 1956. Under his leadership the steelworkers’ union became a dominant force in the Canadian Congress of Labour (CCL), taking a very active role in political action initiatives, and achieving a number of strategic victories through strike action. Millard was personally involved in the creation of the CCL and its subsequent development. He was also very active in opposing the Communist faction within organized labour, and labored throughout his career to further the relationship between organized labour and the Co-operative Commonwealth Federation (CCF). Despite Millard’s many significant contributions during what was a formative period for both organized labour and the CCF, he has been mostly ignored. This thesis sketches Millard’s life, focusing on the major events in which he was involved.

The Long Distance Feeling: A History of the Telecommunications Workers Union - Bernard, Elaine (Simon Fraser University, 1988)
...In this thesis we examine the history of the telephone workers, from their earliest organizing efforts to their public campaigns of today. In restricting the restructuring of their work, telephone workers have often been in the leadership successfully applying and developing militant labour tactics, from the first successful "hello girls" strike of 1902 to the dramatic provincial-wide seizing of exchanges by telephone workers in 1981. The history of the Telecommunications Workers Union provides a valuable case study of workers' efforts to build and maintain their union in [the] face of massive and continual technological change.

Labour Law and Union Growth: The Case of Ontario - Forrest, Anne (University of Warwick, 1988)
What role the law should play in encouraging the growth of trade unions is a matter of considerable controversy in Canada, the United States, and the United Kingdom. Limits to growth in other sectors of the economy coupled with heightened employer hostility to unionism have made the extension of collective bargaining to the tertiary sector the most pressing task for unions in the 1980s. In a limited way, the Canadian procedure for certifying and recognizing unions is being considered as a model for labour law reform. And there is much to recommend the Canadian system. It is far more efficient than its American counterpart. There are fewer delays, fewer unlawful interventions by employers, and a substantially higher likelihood that newly organized unions will be granted certification. Even so, unions have failed to break into the trade, finance, and services industries that are so critical to their future. Taken as a whole, Canadian labour law tends to block rather than promote the growth of unions in the unorganized sectors of the economy. The certification procedure is only one aspect of a legal regime that has as its primary purpose the preservation of industrial peace, not the encouragement of union growth. By shaping bargaining structure and regulating bargaining tactics, Canadian labour law tilts the balance of power in favour of employers. Small, fragmented unions are frequently pitted against large corporations and as there is nothing to stop antiunion employers from using their overwhelming strength to frustrate the collective bargaining process, efforts to organize the tertiary sector have failed.

Voluntarism and Compulsion: The Canadian Federal Government's Intervention in Collective Bargaining from 1900 to 1946 - Fudge, Judith (University of Oxford, 1988)
In February 1944 the Canadian federal government introduced Order in Council PC 1003, a system of compulsory collective bargaining which has been conventionally characterized as the culmination of the gradual evolution in federal labour relations policy towards the greater recognition of trade unions and collective bargaining. The issue addressed in this thesis is whether this characterization is accurate. As against the tendency to present federal intervention in collective bargaining as having developed towards some inevitable maturity, the account presented herein seeks to draw attention to the suppressed alternatives of history. Thus, the thesis begins with an examination of PC 1003'S historical antecedents dating back to 1900. This is followed by an examination of the developments during the Second World War. Instead of concentrating upon federal collective bargaining policy as a means of responding to wartime pressures by establishing a mechanism for mediating and resolving disputes between labour and capital, the thesis emphasizes the extent to which the policy was part of the large post-war settlement. By ignoring this, the conventional account has failed to provide any guidance for understanding either the actual provisions wheich were introduced or the longevity of PC 1003 as the dominant institutional model for Canadian labour relations. By contrast, if PC 1003 is understood as part of an attempt to forge a post-war settlement between labour and capital it is possible to identify the general thrust of the Order. Although it represented a fundamental shift in Canadian labour policy in that employers were compelled to recognize unions for the purpose of collective agreements, PC 1003 did not radically alter the balance of power to make it easier to organize or constrain managerial prerogatives. In fact, PC 1003 was consistent with the federal government's historical preoccupation with promoting responsible unions and attaining industrial peace and stability.

The Political Apparatuses of Production: Generation and Resolution of Industrial Conflict in Canada and Britain - Haiven, Larry (University of Warwick, 1988)
This study explores the subject of cross-national variations in industrial conflict, looking specifically at a 'matched set' of factories in Canada and Britain. The comparison between these two countries is intriguing. Since 1943, Canadian governments have sought to regulate industrial conflict by a distinct formula whose three pillars are a) legally enforceable collective agreements meant to circumscribe disputable issues, b) the outlawing of strikes during the term of the collective agreement, and c) the substitution, for industrial action, of a well-defined grievance and arbitration procedure to settle the disputable issues arising during that term. Dispute resolution is formal, collective agreements are comprehensive and arbitral jurisprudence is encyclopaedic. In Britain, on the other hand, dispute resolution has been left almost entirely to the parties themselves. Collective agreements are not enforceable and sketch the barest details of co-regulation. An ill-defined body of 'custom and practice' still governs in most day-to-day disputes. Strikes are legally possible for all groups of employees at any time on any issue related to the workplace. And arbitration, though available, is voluntary and widely shunned by both parties. Dispute resolution is highly informal. While one might, from this comparison, predict a higher level of strike activity in Britain, Canada has equalled or surpassed Britain over the past twenty-five years in industrial conflict. Why might this be so? The study reviews several sets of theories on cross-national variations in industrial conflict and finds that the Canada-Britain comparison does not fit any of them. Suggesting a synthesis of the "institutional" and "political economy” theoretical approaches, it proposes to concentrate on the political struggle over production at the shop floor in a "politics of production" approach. Defining four "political apparatuses of production" (interests, rights, adjustments and enforcements), the study examines how these "microinstitutions" for conflict-handling articulate with three key loci on the frontier of control where conflict can erupt (discipline, the structuring of the internal labour market and job control). Through the use of intensive interviews in four workplaces (two in each country) in the brewing and aluminium fabrication industries and the analysis of general data on industrial relations in the two countries, the analytical framework is applied to examine the generation and resolution of industrial conflict.

A Study of the Point St. Charles Shops of the Grand Trunk Railway in Montreal, 1880-1917 - Hoskins, Ralph F. H. (McGill University, 1988)
This study concentrates on the choice of the site for the railway's Montreal terminus (and shops) in 1853, and on analyzing the shops' payrolls for the period 1880-1917. The most important findings are: [1.] The site chosen at the head of the Victoria Bridge was farm land purchased from four religious communities. It had been recommended in 1852 in an independent report based largely on its proximity to the water which would permit easy trans-shipment between rail and water transport. [2.] The Shops were divided into the Motive Power and Car Departments; the former being mainly a metal-working area with anglophones strongly predominating, the latter a wood-working area with francophones predominating (from 1902 onwards). [3.] Working hours in the Shops generally amounted to 7 1/2 to 9 hours per day or to 45 to 55 hours per week. The skilled metal workers usually earned more than the skilled woodworkers. [4.] The majority of the workers, including 90% of the anglophones, lived within two miles (3.2 km) of the Shops. Early in the period, 82% of the fraancophones did likewise but, by l9l7, this had dropped to 55%.
OCLC: 18982173
Keywords: Academic theses; Thèses et écrits académiques; dissertations

Mining in the Settler Dominions: A Comparative Study of the Industry in Three Communities from the 1880s to the First World War - Mouat, Jeremy (University of British Columbia, 1988)
This dissertation examines the evolution of the mining industry in three British dominions during the late nineteenth and early twentieth centuries. Adopting a case study approach, it describes the establishment and growth of mining in Rossland, British Columbia; Broken Hill, New South Wales; and Waihi, New Zealand. Separate chapters trace developments in each area, focussing on the emergence of organised labour, the growth of mining companies and the sophistication of mining operations. These underline the need to consider diverse themes, maintaining that the mining industry's pattern of growth can be understood only by adopting such a broad approach. Following the three case studies, the final chapters of the dissertation offer a comparative analysis of Rossland, Waihi and Broken Hill. The study emphasises the similarities of these three communities, especially the cycle of growth, and identifies a crucial common denominator. Despite differences in climate, in the type and nature of the ore deposit and in the scale of mining activity, all three areas experienced a common trajectory of initial boom followed by subsequent retrenchment. The changing character of the resource base forced this fundamental alteration of productive relations. In each region, the mineral content of the ore declined as the mines went deeper. In addition, with depth the ore tended to become more difficult to treat. Faced with a decline in the value of the product of their mines, companies had to adopt sweeping changes in order to maintain profitable operations. This re-structuring was accomplished in a variety of ways, but the most significant factors, common to Rossland, Broken Hill and Waihi, were the heightened importance of applied science and economies of scale. Both developments underlined the growing importance of the mining engineer and technological innovations, principally in milling and smelting operations. In addition, new non-selective extractive techniques reduced the significance of skilled underground labour. The re-structuring of the industry not only had similar causes but also had a similar effect. The comparative chapter on labour relations, for example, argues that these managerial initiatives were closely associated with militant episodes in each community. While the leading companies in Rossland, Waihi and Broken Hill successfully reduced their working costs, they all faced the same ultimate end. Their long-term success or failure reflected the skill with which they coped with the inevitable depletion of their ore body. The common experience of Rossland, Waihi and Broken Hill demonstrates the importance of placing colonial development within a larger context. Regional historians should make greater use of the comparative approach, rather than continuing to focus on the unique and the particular.

Modes of Incorporation and Racialization: The Canadian Case - Satzewich, Victor Nicholas (University of Glasgow, 1988)
This thesis makes a contribution to three areas of sociological thought. First, it is concerned with the elaboration and extension of the political economy approach to migration as it is represented in the work of Stephen Castles and his various co-authors. It suggests that the work of Castles, et al., is relatively silent on the role of the state, and ideological relations in the structuration of migration. In seeking to further refine the political economy framework as it is applied to migration, this thesis draws upon two other sets of literature which, in part, have emerged as counters to some of the more economistic of their formulations. In this light, the second area of sociological literature I draw upon is the recent work on the concepts of free and unfree labour. Finally, this thesis is informed by an analysis of recent debates on the concept of racialization. In synthesizing these three strands of sociology, this thesis advances the theoretical claim that political economy oriented theorists should focus on modes of incorporation, or the manner in which foreign-born labour articulates with capital and the state. Within this context, four distinct modes of incorporation under capitalism are identified. These modes of incorporation are designated as: free immigrant labour, unfree immigrant labour, free migrant labour and unfree migrant labour. This thesis suggests that agents are subject to particular modes of incorporation, in part, on the basis on the process of racialization. This thesis uses the cases of late nineteenth and early twentieth century Chinese migration to Canada, and the post-1945 migration of farm labourers, from a number of source countries, including, specifically, the Netherlands, Poland, Germany, and the Caribbean, to the south western Ontario fruit and vegetable industry to highlight the centrality of the state in the process of migration, and the differential modes of incorporation of foreign-born persons into sites in production relations. Furthermore, the process of racialization is seen to have an impact on whether particular groups are allowed entry to a social formation, and upon how they are incorporated into sites in production relations.

The Health of Nations: Public Health and the Social Reproduction of the Working Class in Canada and Britain, 1900-20 - Sears, Alan (University of Warwick, 1988)
The first two decades of the twentieth century saw a dramatic period of innovation and expansion in public health programmes in Britain and Canada. This thesis argues that this period of growth and change in public health was one aspect of a major reorientation of social policy. This reorientation had two major features. First, the national working classes of Britain, Canada and other countries were increasingly delimited through immigration controls and similar means of regulating international mobility. Secondly, new social programmes were developed which attempted to improve the physical, mental and moral condition of these delimited working classes, on the basis that their well-being was the foundation of national productivity. Public health played a major role in both the delimitation and improvement of national working classes. In Canada, the first major programme of immigration controls was introduced in this period, centering around the selection or rejection of immigrants on the basis of medical inspection conducted according to public health criteria. In both Britain and Canada, new public health programmes were developed which aimed to improve the condition of the working class. This was to be accomplished primarily through home visiting programmes which attempted through education and Inspection to establish standards for the domestic labour of women as mothers and home-makers. This thesis examines the contribution of public health to this reorientation of social policy primarily through the analysis of the theoretical work of key policy-makers as reported in professional journals and government documents. These officials displayed a keen sociological understanding of the broader significance of their activities in the development of a productive national working class prepared for work or war. Indeed, they understood clearly that the health of nations is an important basis of the wealth of nations.

A Social History of Pulpwood Logging in Newfoundland During the Great Depression - Sutherland, John Dufferin (Memorial University, 1988)
The Great Depression which struck all western nations in the 1930s was a period of great hardship for Newfoundlanders. Its burdens fell particularly hard on the island's loggers and their families. During the 1930s, for at least part of the year, nearly 6,000 Newfoundlanders toiled in the woods. While some worked full-time, many laboured part-time to supplement their meagre earnings from the fishery. Their labour contributed significantly to a forest products industry which, during the 1930s, was regularly valued at over $15 million a year and, in many years, made up over 50 per cent of the value of the island's exports. And yet, despite their numbers and their contribution to Newfoundland's economy we have heard very little of these loggers' lives and as Greg Kealey puts it, "their struggles to minimize their oppression and to improve the lives of their families and their class." This thesis examines the working lives of Newfoundland loggers during the Great Depression, their labour processes, strikes, collective actions and attempts to organize in the latter half of the decade. In 1930 there were no unions specifically for loggers. By 1939, however, there were three unions, the Newfoundland Lumbermen's Association, the Newfoundland Labourers' Union, and the Workers' Central Protective Union all of which represented loggers in the regions where they were based. The Fishermen's Protective Union was also still active in the 1930s negotiating agreements on behalf of loggers on the northeast coast of the island. This thesis looks at the emergence, structure, and effectiveness of the unions and at their damaging rivalries. In doing so, it charts the changes these organizations forged in the relations between labour and capital in the Newfoundland woods before World War II.

Hospital-Based Nursing and the Labour Process, Ontario, 1850-1922 - Teichroew, Les I. (Carleton University, 1988)
This thesis examines the historical development of hospital-based nursing and its labour process in Ontario between 1850 and 1922. By building upon feminist critiques of Marxist theory, the thesis seeks to apply class and gender as empirically significant concepts. The analysis proceeds at two levels of abstraction. First, it locates the emergence of nursing vis-a-vis the growth of hospital-based care, both of which were influenced by broader changes in society, the economy and family. Secondly, it links changes in the content and control over nurses' work to those broader social changes, and more specifically to the struggles between physicians, hospital administrators, and nursing superintendents at the level of the workplace, namely the hospital.
OCLC: 19517013

The Causes and Effects of the 1981 Hospital Strike in Ontario: Fiscal Crisis, Changing Labour Process and the Role of Gender in Public Sector Conflict - White, Patrick Jerry (McMaster University, 1988)
In 1981 the Canadian Union of Public Employees (CUPE) staged a strike in Ontario Hospitals. This dissertation is an exploratory case study of the causes and effects of that strike. The dissertation employs elements of the labour process theory to evaluate the hospital worker's action and in so doing provides an opportunity to contribute to the on-going debate concerning this theory. The study is centred on the hospitals of Greater Hamilton and Burlington Ontario. It assesses the role of political environment, union structure and action, and gender in creating and sustaining the conditions for strike action in the public sector. The economic and political situation leading to the strike is analyzed with a view to understanding how the fiscal crisis in Canada led to the strike. Labour legislation and the fiscal policies of the federal and provincial governments had an impact on hospitals and their workers. Labour legislation in the hospital sector destroyed collective bargaining at a time when changes unpopular with the workers were taking place in the hospital. This encouraged the decision to strike. The majority of hospital workers in 1981 were women. The dissertation explores, through interviews and archival data, a possible link between gender and the decision to strike. Some changes in the organization of hospital work broke an important care-giving link between women workers and patients. The repercussions of the strike include charges for the union, for women, and the wider political consequences such as the further undermining of the Hospital Labour Disputes Arbitration Act. The dissertation concludes that the strike was caused by labour process changes made by management faced with government cost cutting measures. These changes were particularly upsetting to the majority of workers who were women. The illegality of the strike did not deter the decision to strike because the government labour legislation had destroyed the 'normal' bargaining process. Therefore workers felt that there was no real choice but to strike.

Migrant Seasonal Agricultural Labour: Race and Ethnic Relations in the Okanagan Valley - Wong, Lloyd Lee (York University, 1988)
This thesis examines the race and ethnic relations between migrant seasonal agricultural workers in the Okanagan Valley of British Columbia, Canada, from the turn of the century to the present. This analysis includes Chinese, Doukhobor, Japanese, Indian, and French agricultural workers. The research problem is one of determining the nature of race and ethnic relations between these groups and the predominantly English host community, where it was hypothesized that racism, ethnic prejudice, and ethnic discrimination would be prevalent. Historical research was conducted using existing local literature and archival data from local museums and newspaper companies. Survey research was conducted on contemporary migrant seasonal agricultural workers and consisted of a questionnaire. The thesis begins with a description of the Okanagan Valley and a literature review of agricultural labour in Western Europe, the United States, and Canada. Segmented labour markets and, race and ethnic relations provide the theoretical framework for the study. The secondary labour market explains the concentration of racial and ethnic minorities in agriculture. A theoretical model of French-English ethnic relations explains the ethnic discrimination of French migrant seasonal agricultural workers. The historical research findings show that racism was experienced by Chinese and Japanese workers, and ethnic discrimination was experienced by Doukhobor workers. The survey research included a general documentation of demographic and social data for current migrant workers, and these data indicate they are similar to workers elsewhere. The housing and working conditions of these workers are poor. Workers are exposed to dangerous chemical pesticides. The main survey research findings centre on the ethnic discrimination experienced by French migrant workers. This discrimination occurred primarily in their leisure activities, and to a lesser extent, in the area of employment. There was no evidence of a split-labour market on the basis of wages alone. The thesis ends with a discussion on the possible legislative and social policy implications of the findings in the areas of health and safety, and racial/ethnic prejudice and discrimination. There is a discussion of discrimination and the law, educational programs, and the necessary changes in community processes and structures.
OCLC: 1077901827
Keywords: Social sciences

Labour Relations and Indian Self-Determination: A Fort Alexander Case Study - Anderson, Brian (University of Saskatchewan, 1987)
This case study examines a labour relations issue which initially involves teacher employees of the Sagkeeng Education Authority of the Fort Alexander Band on one hand and the Sagkeeng Education Authority and the Fort Alexander Chief and Council on the other. The events of the issue transpire between 1981 and 1986.Teacher employees, concerned with working conditions and job security, organized as a local of the Manitoba Teachers' Society which was certified under the Canada Labour Code. The Chief and Council of the Fort Alexander Band rejected the formation of the local and the applicability of the Canada Labour Code to labour relations on the reserve. Teachers were fired for union activities. Hearings were held by the Canada Labour Relations Board. Orders were issued by the Labour Board and a collective agreement was imposed by the Labour Board. The Chief and Council refused to follow the Labour Board's orders, and contempt of court hearings were held by the Federal Court. Fort Alexander officials, including the Chief and Council, were initially fined and subsequently jailed. The Minister of Indian Affairs, David Crombie, promised to initiate Department studies to examine the possibilities and implications of changing the labour relations regime to reflect Indian self-government. The dispute was eventually settled out of court but the issue of Indian government jurisdiction over labour relations remains unresolved.Conceived and sanctioned by the Manitoba Teachers' Society, the Canada Labour Relations Board and the Federal Court as a labour dispute, the researcher argues that the issue is more readily understood within the context of Indian self-determination and self-government. Concepts concerning philosophical, socio-economic, cultural, legal, political and historical aspects of the relationship between Indian peoples and the Canadian state are brought to bear on the issue. Concepts of group rights versus those of individual rights are examined.It is argued that the current labour relations legal regime is inconsistent with Indian self-determination and self-government. The researcher suggests jurisdiction over labour relations should be determined by First Nations' governments as consistent with the goals of self-determination and self-government. Conceptions of Indian labour relations jurisdiction are suggested.

Through the Lense [Lens] of Syndicalism: Fragmentation on the Vancouver and British Columbia Left Before the Great War - Leier, Mark (James Mark) (Simon Fraser University, 1987)
This thesis is an examination of the Industrial Workers of the World and its relations with capital, organized labour, and the socialist movement in British Columbia before the First World War.

Co-operation and Conflict: The CCF and the Canadian Congress of Labour in Saskatchewan, 1944-1956 - Lindsay, Robert A. (University of Saskatchewan, 1987)
The purpose of this study is to examine CCF-CCL relations in the Saskatchewan public service during the early years of the government of Tommy Douglas. While much has been written about the Co-operative Commonwealth Federation (CCF) and the Canadian Congress of Labour (CCL), both as separate organizations and as political 'allies', little has been said about their relations in Saskatchewan. Yet, the CCF formed the government in Saskatchewan for five consecutive terms between 1944 and 1964, and it was in this agrarian province that the true test of the CCF-CCL relationship occurred. Saskatchewan was the one location where unions that supported the CCF were faced with a social democratic government which was also their employer. The difficulty the two sides encountered while trying to reconcile industrial relations with their political relations forms the subject of this study.

Shipbuilding at Quebec, 1763-1893: The Square Rigger Trade - Marcil, Eileen Reid (Université Laval, 1987)
From the seventeenth century on, deforestation due to the abusive use of wood by the iron industry, excessive naval construction and the extraordinary demand for timber for reconstruction following the Great Fire of London in 1666 led increasingly to the construction of British merchant ships in her North American colonies. Following American Independence, vessels built in the thirteen colonies were no longer entitled to British Registry, and shipbuilders in Quebec and the Maritime Provinces were able to take full advantage of the British demand. When Napoleon blockaded the Baltic, thereby endangering the British supply of timber from northern Europe, a fast-growing Canadian timber trade served as a tremendous stimulus to local shipbuilding. This is a study of the construction of square riggers at Quebec between 1763 and 1893, as revealed principally by the shipping registers of the port, notarial records, Lloyd's Survey Reports, newspaper advertisements and reports, city directories and census reports. It describes the historical background of the trade and local conditions affecting it, identifies the Quebec shipbuilders, pinpointing when and where they worked, describes the shipyards and various aspects of the shipbuilding business, takes a look at the workers and the specialized shipbuilding trades and outlines the techniques they used. It describes and classifies the vessels that were built giving details of their materials and equipment, and looks briefly at their purchasers. The writer concludes that the production of the Quebec shipyards filled a specific need for spacious, light, fast carriers, until the third quarter of the nineteenth century when improved metallurgical technology allowed their place to be taken by metal-hulled ships. The main appendices contain a collection of plans of shipyard sites and lists of the sixteen hundred and thirty vessels of over one hundred tons built at Quebec and four hundred and sixty-seven others built elsewhere on the river, all of which were registered at Quebec. No complete plans of ships built at Quebec were uncovered during the research, but a number of drawings of construction details and mid-ship section plans form another appendix.
OCLC: 21147624
Keywords: Academic theses; Construction navale Québec (Province); Québec; Shipbuilding; Shipbuilding Québec (Province); Thèses et écrits académiques; dissertations

Newfoundland Labour and World War I: The Emergence of the Newfoundland Industrial Workers' Association - McInnis, Peter S. (Peter Stuart) (Memorial University, 1987)
The story of the Newfoundland Industrial Workers' Association (NIWA) is one which has largely been passed over in the writing of the island's labour history. Yet this organization figures prominently in the events which helped shape the labour-capital relationship during the World War I years. As the Canadian and international record will testify, these years were critically important to the development of modern working-class organizations, while maintaining a direct link to the previous struggles of an earlier era. Centred in St. John's, but exerting an Island-wide influence, the NIWA arose out of a pressing need for working people to confront the economic and political realities of their class in a manner intended to redress the subservient and exploitive circumstances to which they were subjected. This thesis examines the NIWA in terms of its structure, membership, and mandate and attempts to place this movement into the larger context of the international labour revolt of 1917 to 1920. In doing so, it argues that class formation, development, and conflict is central to history.

A Tradition in Jeopardy: Building Trades Workers' Responses to Industrial Capitalism in Winnipeg, 1880-1914 - Berkowski, Gerry E. (University of Manitoba, 1986)
Between 1880 and 1914, when Winnipeg experienced its first era of urban and industrial growth, the building industry shaped the contours of the city's economic, social, and political environments. Architects designed, contractors supervised, and workers built the infrastructure that was necessary for commercial and industrial expansion. Residential neighbourhoods, warehouses, office buildings, and factories provided the housing and workplaces for thousands of immigrants who settled in the city in the late nineteenth century. The various trades of the building industry were essential to the conversion of Winnipeg from a pioneer town in the 1870s to the west's major transportation and distribution center in 1914. Skilled building trades workers were vital to this dynamic transformation. In particular, the carpenters, bricklayers, painters, and plumbers who came to Winnipeg in the 1880s were the first of thousands employed in the mass production of buildings for modern commercial and residential use. Together with typographers and railway employees, who also possessed a great deal of craft skill, these were among the most important workers involved in the emergence of Winnipeg's early labour movement. Industrial capitalism transformed the building industry after 1880, and the lives of thousands of skilled workers. The entrepreneurs who came into the city from eastern Canada, the United States, and Britain brought the logic of general contracting to the local industry. Soon it was the dominant form of business, characterized by ferocious competition and mass production. To survive and prosper in such an environment employers adopted new methods of production and corporate organization which had a severe impact on the workplace and the skilled worker. As industrial capitalism matured in the 1890s and took hold with greater intensity in the 1900s, the workplace became more important as the object of change. Despite extensive business re-organization and the use of machines, the entire transformation from 1880 to 1914 was possible because of employers' manipulation of the labour market, the cheapest and most accessible of all resources...

Working Class Politics, Racism and Sexism; the Making of a Politically Divided Working Class in Vancouver, 1900-1939. - Creese, Gillian Laura (Carleton University, 1986)
This dissertation addresses the articulation of class, ethnic, and gender relations among the working class in Vancouver during its formative period, between 1900 and the eve of the Second World War in 1939. The historical development of a labour market segregated by ethnicity and gender is traced, and the effect of labour market segregation, ethnic relations of white domination, and patriarchal relations of male domination on the political practices of the working class is assessed. It is shown that the economic and political marginality of Asian and women workers in British Columbia affected their involvement in the Vancouver labour movement. Although many Asian and women workers played an active role in labour struggles, both were in a much weaker position than white male workers. Moreover, the practices of the predominantly white male labour movement reinforced the marginal position of Asian workers through exclusion, and women workers through the perpetuation of relations of dependence. Political divisions within the labour movement reflected the salience of ethnicity and gender in defining workers' lives, while at the same time reproducing the subordination of Asians and women within the labour market and throughout civil society. Conditions facilitating solidarity within the working class began to develop during the severity of the economic depression of the 1930s, when socialist politics were strengthened, and when Asian worker's and women workers began to place their own issues on the political agenda of the Vancouver labour movement.

On the Fringes: Capital and Labour in the Forest Economies of the Port Alberni and Prince George Districts, British Columbia, 1910-1939 - Hak, Gordon H. (Gordon Hugh) (Simon Fraser University, 1986)
The Port Alberni and Prince George districts of British Columbia experienced the beginnings of an extensive forest industry at about the same time, the second decade of the twentieth century, and both regions were destined to become substantial lumber centres. Yet in their early period of development, before the major changes of the 1940s, the two communities had distinct growth patterns: by 1939 the Port Alberni district had emerged as a prosperous lumber-producing centre housing an active, coordinaed working class while the Prince George district remained an economic backwater with a weak forest industry base, an ill-formed class, and quiscent labour movement. Simple economic or geographic explanations do not begin to address the complexity of the histories of the two regions. Only by closely examining the lumber companies, the sawmill workers, the loggers, and the broader community can the local historical contexts be understood. Further, exogenous factors such as western Canadian working-class initiatives, the role of the provincial state, and the shifting international lumber trade must also be taken into account. Business decisions, union drives, strike action, and political structures were all intertwined in shaping the velopment of these fringe areas of the province. By comparing the two forest districts this thesis not only highlights the various elements that interacted in creating the forest economics and forest-based communities, it also sheds light on the development of British Columbia's most important industry and the history of the western Canadian working class.

Education for a New International Labour Solidarity: Case Study of the CUSO-OXFAM Labour Project - Hesch, Richard Allan (University of Saskatchewan, 1986)
The thesis identifies the ways in Which the CUSO-OXFAM Labour Project (COLP) has worked to strengthen international labour solidarity in Saskatchewan. COLP is a development education project mandated to work primarily With the working-class in Saskatchewan. COLP's ideology contrasts with that of the Canadian Labour Congress (CLC) leadership as manifested in the international labour solidarity movement by developing class-consciousness rather than economism, pluralism, and social democracy. In contrast to existing practice, COLP has taken its internationalist educational programs directly to rank-and-file trade unionists rather than circulating its information amongst the union leadership alone. COLP's curriculum falls within the tradition of progressive labour education programs in the Western English-speaking world and is demarcated from the ideology of standard labour education programs in Canada, the United states, and Great Britain. Standard labour education programs today are characterized by their reproduction of pluralism and economism, and are organized according to an intellectually fragmenting and skills-based curricular ideology. Alternative and progressive labour education programs have enjoyed the support of radical or progressive trade unions, but have been opposed or consciously ignored by dominant labour centrals. COLP shares these characteristics. The Saskatchewan Labour Information Project (SLIP) provided a precedent for class-conscious development education with workers when it was organized in 1976. After SLIP's demise, its ideology was carried into the formation Of COLP in 1980. COLP's steering committee and coordinator work closely together to develop a policy and practice which advances international labour solidarity in Saskatchewan. COLP receives support from unions in the forefront of the class struggle in this province, but is not endorsed by the Saskatchewan Federation of Labour or the CLC. Dependence on state funding from the Canadian International Development Agency (CIDA) may have limited COLP's ability to articulate an alternative ideology for the international solidarity movement to that of the CLC. COLP aims to educate for a class-conscious international labour solidarity movement in Saskatchewan. To this end, the project's curriculum design is consistent with both radical development education theory and a dialectical materialist theory of education. Curriculum has been implemented in a dialectical fashion as well, although limitations imposed by COLP's trade union context have prevented a fully successful implementation. The ideology transmitted through the project's curriculum content contrasts 'With that of standard labour education programs by promoting class-consciousness in its fullest sense. Tours to Nicaragua organized by COLP have been particularly significant in this regard. The advancement of internationalist class-consciousness in Canadian labour education comes at a time of crisis for the North American labour movement and presents a necessary alternative to the social democratic ideology which dominates Western labour internationalism.

Technological Change and Mining Labour: Copper Mining and Milling Operations at the Britannia Mines, British Columbia, 1898-1937 - Hovis, Logan W. (University of British Columbia, 1986)
Most recent studies of the relationship between technological change and mining labour in the western metal-mining regions of North America have concentrated on the impact of the mechanization of the industry that took place during the second half of the nineteenth century. The distinct impression is left that the increased use of machinery — especially the machine drill — was the chief factor in reducing the skill levels associated with mining as a craft tradition. Preoccupation with machinery has led to the assumption that by the beginning of the twentieth century the transformation to modern forms of mining was essentially complete and the traditional miner an anachronism. Mining as practiced prior to 1900 differed qualitatively and quantitatively from the subsequent period of "modern mining;" but the introduction of machinery per se was less important to the reorganization of the patterns of work in the mines than the redesigning of the engineering systems in which workers and machines were employed — a process which gained its full momentum in the decades after 1900. This transformation involved the gradual abandonment of low-volume, high-value, selective mining methods in favour of higher volume, non-selective methods which emphasised the quantity rather than the quality of the ore mined. The change redefined the nature of work in and around the mines, putting an end to a tradition of mining practice that was at least as old as the methods described in Agricola's De Re Metalica, something the initial mechanization of mining had never been intended to accomplish. Under selective mining practices, machinery was used to assist the skilled miner in his traditional task. Under non-selective or mass mining techniques, a new generation of engineers trained in the applied sciences redefined the miner's work as solutions were sought to the problems of an increasingly complex geology in a climate of rapid economic expansion, chronic over-production, generally declining metal prices, and ever increasing production costs. The efforts and successes of these engineers were amply demonstrated in the fields of mining, metallurgical, and human engineering. The impact of the change is evident in varying degrees throughout the metal-mining community; but by focusing on copper mining — the technological leader from 1900 to 1930 — the full impact of the industrial sciences on mine labour is evident.

Class Conflict and Political Factionalism: A History of Local 213 of the International Brotherhood of Electrical Workers, 1901-1961 - McDonald, Ian (Simon Fraser University, 1986)
British Columbia's economy is heavily reliant on electrical processes, yet little is known of the electrical workers.... A major purpose of this thesis is to analyze the electrical workers through a sixty-year history of an important and often controversial union: Local 213 of the International Brotherhood of Electrical Workers (IBEW). ...Three themes characterize the history of Local 213: the first is the union's struggle for better wages and better working conditions against recalcitrant employers. The second is the relationship between Local 213 and different varieties fo socialism in British Columbia. Electrical workers generally supported cautious social democratic practices, but there have been important exceptions. The third theme is the intervention of outside forces, in particular the international office of IBEW, whenever the electrical workers appeared to support either radical leaders or radical proposals.... From author's abstract. Contents: The structure of the electrical industry in British Columbia to 1961 – Boomers, grunts and narrowbacks: the radical tradition, 1901-1919 – The defeat of radicalism, 1919-1922 – The Morrison years, 1922-1939 – Radicalism renewed, 1939-1953 – Unholy alliance, 1953-1955 – Towards militancy at Lenkurt. Bibliography (pages 280-89).

The Size of the Labour Force in the Montreal Fur Trade, 1675-1790: A Critical Evaluation - Murphy, Brian D. (University of Ottawa, 1986)
Contents: Introduction – The Congés de traite as a method to control the fur trade, 1681-1715 – The institutionalization of the Congés, 1715-1768 – The trade licences: a new instrument to control the fur trade, 1760-1790 – The notorial contracts and private contracts, 1680-1821 – A conservative estimate of the labour force – Conclusion. Appendix: The diet of the Engagé.

The Montreal Garment Industry, 1871-1901 - Payette-Daoust, Michelle (McGill University, 1986)
The firat half of the nineteenth century witnessed the graduaI integration of Montreal garment production into the developing exchange economy, which resulted in the dismantling of the traditional artisanal organization of production and ushered in production for both retail and wholesale distribution,so that by 1860 a fledgling ready-made garment industry existed in the city. Between 1871 and 1901, the garment industry was the largest employer in the city, and one of the most important industries in terms of the of the value of' its production. Furthermore, Montreal held the position of Canadian garment capital throughout our period. Focussed primarily on the manufacture of men's wear, the garment industry in Montreal was heavily dominated by the largest wholesale manufacturers, who specialized in the production of low-priced, cheap quality garments which were aimed essentially at the rural labouring population and at shantymen of every province. The success of the city's ready-made garment producers can be explained both by tremendous expansion of the market for their goods, which occured in the second half of the nineteenth century, and by their ability to exploit a vast reserve of of essentially rural, semi-skilled labour. This situation of labour abundance made possible the organization of labour known as contracting or putting out, which remained the dominant mode of organization well into the twentieth century, and created dismal working conditions of long hours at extremely low wages for which the industry will always be remembered.

Working on the Margins: A Labour History of the Native Peoples of Northern Labrador - Ross, Philip D. (McGill University, 1986)
This study is an analysis of the changes in the social formations of the Inuit and Innut populations of northern Labrador as a consequence of interaction with Western capital, from approximately 1500 to the present. It is concluded that the significant changes which have taken place can only be explained'if they . are placed within a unified theoretical framework that combines both macro and micro levels of analysis. This requirement stems from the impact of the global nature of capital, and from the specific characteristics of the indigenous social formations in northern Labrador. To facilitate the analysis, the history of the penetration of capital into northern Labrador has been divided ioto political-economic periods: mercantile: 1500-1926, and welfare state: 1926-present. The former is further subdivided into two phases: the competitive phase: 1500-1763, during which no one European power held sway; and the monopoly phase, 1763-1926, during which either Britain or one of its colonies was jurally the sole European authority. Finally, the welfare period, 1916-present, which includes a transitional period, 1926-1942, is characterized by the increasing importance of wage labour and state agencies. Each of these periods is examined in terms of the internal and external relations between and amongst the European and native social formations which led to mutual modifications.

The Evolution of Modern Catholic Social Teaching on Labour and Social Justice - Campbell, Hugh J. (Wilfrid Laurier University, 1985)
The task of this thesis is to show that from the nineteenth century to the present Catholic Scoial Teaching recognized increasingly the need for social justice in the areas of labour and society. In order to do this, I propose to research carefully the major official Church documents on Catholic social teaching on human labour from Pople Leo XIII’s Enevelical, Rerum Novarum (The Condition of Labour), 1891, up to Pope John II’s Enevelical Laborem Exercens (On Human Work), 1981. I will also attempt to define what Catholic Social Teaching is and explain what are the principles which make up the social teaching of the Catholic Church—principles which are drawn from scripture, concepts of natural law and the sciences. Reference will also be made to Karl marx where his philosophy on labour is applicable. To support the position of the Catholic Church in its teaching on social justice in the workplace while at the same time given that position clarity from my own point of view, I will speak briefly on my evolution as a worker, a union steward, and Catholic layman. I believe this is necessary because what I am today and how I feel about social justice (or the lack of it), especially in the workplace, has its roots in my early tradition and gradually evolved. Just as the Catholic Church in its writings down through the ages has consistently recognized the plight of the worker, I, too, as a worker, gradually became aware of many visible injustices in the workplace, although I was relatively powerless to do anything about them. In developing my thesis, I will draw upon my thirty-eight years’ experience as a member of Canada’s work-force, thirty-four of which were spent in the telecommunication field. By referring to specific work-related problems I encountered over the years, I will demonstrate why there is such a need for social justice in the workplace, and why I as both Catholic and worker ultimately became a strong advocate for some form of legal machinery to help resolve these problems. I will briefly touch on some incidents that immediately preceded the majority vote for the Communication Workers of Canada (CWC) as the bargaining agent for the Phone Company’s craft and clerical employees in place of the Employees’ Association. As one of the first union stewards and Chairman of the Political Action Committee for the CWC, I will relate a few of the many cases I resolved for fellow workers, in contrast with what the Association has been able to do for this group of workers. I will show why I agree wholeheartedly with the Catholic Church’s present position on and support of the trade union movement as a vehicle for social justice in the workplace. All of the Popes with whom I will be dealing, Leo XIII, Pius XI, Pius XII, John XXIII, Paul VI, John Paul II, called for social justice in the workplace and advocated unions as bargaining agents for the worker. Their writings and those of other brilliant Catholic churchmen and laymen demonstrate how the Catholic Church has evolved in the area of social justice and labour. It is this broader Catholic support which has allowed me to find my proper place as a worker advocate. Thus, autobiographical reflection will provide the impetus which inspired me to analyze the papal enevelicals of the Catholic Church.

Arthur W. Puttee: Labourism and Working-Class Politics in Winnipeg, 1894-1918 - Dewalt, Bryan (University of Manitoba, 1985)
The thesis addresses the problem of Arthur W. Puttee's 1918 breach with the Winnipeg Trades and Labor Council after twenty years of work within the labour move¡ent as a journalist and politician. The breach is accounted for through an exploration of the ideology that underlay his political decisions. Structured biographically, the thesis uses various primary sources, most notably Puttee's weekly newspaper, the Voice, and his speeches as a labour member of parliament, to trace a continuity in his beliefs from the beginning of his career in the 1890s to its end in 1918. The concept of "labourism", recently elaborated by Craig Heron to describe the ideology of Canadian craftsworkers who worked for independent political action by labour, is used to characterize Puttee's beliefs. The study reveals a central contradiction in Puttee's labourism. He challenged many aspects of the emerging system of monopoly capitalism and demanded for labour the right as producers of wealth to full democratic representation in government. He was opposed to monopoly, the crude exploitation of workers, and government by "special interests" rather than the "people". But Puttee had no systematic critique of capitalist social relations and believed that labour constituted only one segment of a businessmen, and "fair" employers. He viewed the state as ideally the instrument for the will of the "people" and the defender of the "public'' interest. This contradiction in Puttee's beliefs became most apparent in the radicalized labour atmosphere of 1918, when, as a labour member of Winnipeg City Council, he opposed a general strike of unionized city workers in the name of the broader public interest he sought to represent broader community of producers that included farmers, small businessmen, and "fair" employers. He viewed the state as ideally the instrument for the will of the "people" and the defender of the "public interest." This contradiction in Puttee's beliefs became most apparent in the radicalized labour atmosphere of 1918, when as a labour member of Winnipeg City Council, he opposed a general strike of unionized city workers in the name of the broader public interest he sought to represent.

Changing Ghettos: Women Clerical Workers in Ottawa During the Second World War - Doherty, John (Carleton University, 1985)
This thesis studies the changing work of women during the Second World War and examines their life outside of work in the Ottawa community. Nine women were interviewed to understand the transition experienced by women during the war. The experiences of these women are placed within the context of the political and social developments of the 1930's and 1940's. Through these women's lives we can examine the transition from domestic service to clerical work and the impact this had on women's lives. It was during the war that women emerged as the majority of clerical workers in Canada and accelerated a growing trend of women working in the paid labour force. While the trend towards women working had begun in the post World War I era, the national mobilization during the war was unprecedented in Canadian history and opened new job opportunities for women.While the new job opportunities for women represented an improvement in wages and working conditions from domestic service, clerical work soon emerged as another job ghetto for women which did not allow women the opportunity for advancement. In these jobs women, especially married women, faced many barriers and the conditions at work and outside of work are explored.

"The Modern Chivalry": Women and the Knights of Labor in Ontario, 1880-1891 - Dubinsky, Karen (Carleton University, 1985)
The Noble and Holy Order of the Knights of Labor was the most significant labor organization in nineteenth century North America. Part trade union, part social reform movement, the Knights organized hundreds of thousands of workers across the continent, and initiated countless major strikes, particularly during the 1880's. The Knights were the first major union to attempt to make unions accessible to a broad range of workers. At a time when most unions were the preserve of highly skilled, white, male workers, the Knights organized blacks, some immigrants and women. This thesis examines the relationship between women and the Knights of Labor in Ontario in the 1880's. The Knights organized women workers, and they also supported an impressive 'feminist' platform of social reform. They endorsed every major feminist demand in the nineteenth century, from suffrage to temperance to equal pay. In Canada, they campaigned successfully for the first sexual harassment legislation. This platform is particularly significant when set next to prevailing restrictive notions of femininity and 'true womanhood'. Yet the Knights were also a male dominated organization. While the 'space' they opened for working class women was important, it was not without its own set of limitations and restrictions. Within the context of contemporary debates about the intersections of class and gender, this thesis examines the contradictions and tension in the Order's feminist ideology.
Keywords: Knights of Labor (Canada)

Textile Workers and Textile Strikes in Cornwall, Sherbrooke, and St. Gregoire De Montmorency, 1936-1939 - Ellis, Ralph (University of Ottawa, 1985)
This thesis examines textile workers, unions and their strikes at Cornwall, Sherbrooke and St. Gregoire de Montmorency from 1936 to 1939. Via a community study approach, several themes important to textile unionism in particular and industrial unionism in general will be covered. All three places were mill towns. How did this affect political, financial and moral support? How did the corporate structure of the firms involved influence the outcome of the strikes? Were there differences between workers in terms of militancy and their reactions to unionism? What was the role of women at the rank-and-file and leadership levels in the union? –Excerpt.

Solidarity Coalition: The Struggle for Common Cause - Nelson, Patricia Ann (University of British Columbia, 1985)
This thesis is a case study of the Solidarity Coalition, a social protest movement which united labour and community groups In opposition to right-wing restraint legislation. It considers why this unprecedented extra parliamentary force failed to persuade the government to withdraw the offending legislation and attempts to explain the dominance of the labour agenda in the modest successes it did achieve. Interviews with participants in the Coalition and other significant political actors provide the information used in the analysis of this protest phenomena. The thesis incorporates a detailed study of the evolution of the Coalition and its organizational structure and Internal processes within the context of the larger political system and with reference to theoretical literature concerning protest movements. I argue that the emergence of the Coalition as a diverse and broad based movement in reaction to a right wing attack on the social contract is predictable, however, the outcomes of the protest action are less so. Analysis of the Coalition suggests that organizational contradictions within its structure, external and unforseen circumstances, and the strength of government intransigence were influential factors shaping both the development of the protest movement and the outcomes of its actions. The commitment to common cause, fuelled by moral outrage and espoused by labour and community groups, was not sufficient to withstand the divisive tendencies inherent in the structure of the Coalition, or the Inertia that must be overcome by large groups to achieve collective goods. Labour proved to be the more powerful actor within the Coalition due to its financial and organizational resources and its significant noticeabilIty factor as a member of the CoalItion. I argue that consistent with the theory of the logic of collective action that the labour agenda eventually dominated within the Coalition, influencing the parameters of the settlement achieved, and in part, accounting for the failure of the Coalition to meet Its collective goal of withdrawal of the restraint legislation.

The Organization of Production and the Heterogeneity of the Working Class: Occupation, Gender and Ethnicity among Clothing Workers in Quebec - Teal, Gregory L. (McGill University, 1985)
Much Marxist literature on industrialization has assumed that production has been carried out on an increasingly large-scale, centralized basis since the nineteenth century, and that as workers become concentrated together in production, and as the labour process becomes more uniform, there is a homogenization of the working class . This thesis challenges these assumptions and attempts to develop a critical, Marxist anthropology of industry and labour through an examination of the clothing industry and clothing workers in Quebec. In the 19th century the clothing industry in Quebec developed largely on the basis of outwork and sub-contracting. This hindered the development of large-scale factory production, and created a fragmerited, dispersed labour force. ln the 1930s, clothing workers responded to the decentralization of production and intense competition between clothing manufacturers by organizing unions, but these tended to reinforce the occupational, gender and ethnic divisions within the labour force. These dynamics are examined in their contemporacy form in the context of a clothing factory where the production process is sub-divided into distinct phases which separate workers by gender, occupational category, and department. Workers reinforce this fragmentation by defining their interests on the basis of their occupational group. Within the largest group, the female sewing machine operators, competition between individual operators combines with an informal ethnic division of labour to further separate workers from one another. Analysis of the structure of the clothing industry shows that not aIl capitalist production is increasingly large-scale or centralized. And rather than being increasingly homogeneous, the clothing proletariat is is marked by a nincreasingly hierarchical and heterogeneous organnization.

The Administration of Relief to the Unemployed in Vancouver during the Great Depression - Belshaw, John Douglas (Simon Fraser University, 1984)
Unemployment in Vancouver, Canada, during the Great Depression posed a significant threat' to the continuation of political and social norm. The emergence of a large body of workers without jobs, many of whom could vote at the civic level, demanded the attention and intervention of private and government agencies. The response of the City of Varcouver and two major Christian denominations to the unemployment crisis is the subject of this thesis, The documentary evidence utilized came mainly from collections at the Vancouver School of Theology, the Catholic Charities and the City of Vancouver Archives. The inadequacy and abuse of contemporary statistical resources perpetuated a view of the unemployed that emphasizod their potential for social disruption. Despite the fact that most of Vancouver's jobless citizens were permanent residents, community leaders and rglief planners took their cues from the single unemployed transients, a group that was pore likely to derail revolutionary ideas with an extension of its limited relief programmes, However, both church and state were constrained by the shortage of money. Consequently, in the absence of a strong social work ideology, relief was more a reflection of political and fiscal considerations than of the shifting needs of the unemployed. Relief was, simply put, the least expensive means of reintegrating the dispossessed into the established social milieu.
OCLC: 15937891
Keywords: Academic Dissertation; Academic theses; Aide sociale Colombie-Britannique Vancouver; British Columbia Vancouver; Church work with the unemployed; Church work with the unemployed British Columbia Vancouver; Chômeurs Services Colombie-Britannique Vancouver; Public welfare; Public welfare British Columbia Vancouver; Social conditions; Social policy; Thèses et écrits académiques; Unemployed Services for; Unemployed Services for British Columbia Vancouver; Vancouver (B.C.) Social conditions; Vancouver (B.C.) Social policy

Unskilled Labourers on the Public Works of Canada, 1840-1880 - Bleasdale, Ruth E. (University of Western Ontario, 1984)
This study of canal and railway labourers on Canada's public works provides a detailed analysis of an important segment of the developing industrial working class during the years of transition to industrial capitalism. By examining changes in the industry, the composition of the workforce, and the labourers' behaviour and perceptions of that behaviour, it traces both the process of class formation and the growth of class tensions. Beginning with an analysis of the public contract system, it defines the nature of the relationship between contractors and governments and traces the impact of the technological revolution and the growth of a body of indigenous contractors within the industry. Despite important advances within the industry, work on construction sites changed little, continuing to depend primarily on the energies of unskilled labourers who enjoyed little material reward for their back-breaking and dangerous labour. The forty-year period, however, witnessed a significant change in the composition of the workforce. Migrants from within Canada displaced Irish immigrants as the major source of unskilled labour, and the workforce on construction sites became increasingly ethnically heterogeneous. This change in the composition of the workforce effected a modification of the stereotype of the unruly, drunken, and violent public works labourer.;Labourer's perceptions of themselves also changed during these years. In the early years of construction strong factional, ethnic, and sectarian bonds generated violent conflict amongst the diverse groups brought together in the workplace. At the same time such bonds were a powerful source of unity during the frequent strikes waged by the Irish labourers who dominated the workforce. Over the period the basis of identification shifted from ethnicity to class. The easing of tensions between ethnic groups and the unity of the various ethnic groups during frequent strikes demonstrated an increasing ability to unite in pursuit of common class interests. Although the labourers remained outside formal union structures, they sustained an aggressive struggle with employers and acquired the experience of militance and solidarity on which the working class movement of future decades could build.

The Working Class Family Economy: Montréal, 1861-1881 - Bradbury, Bettina (Concordia University, 1984)
The family economy of the working class in the period of early industrial capitalism is examined in this thesis. Changes in the involvement of family members in wage labour, in education, in non-wage and domestic labour at home as well as in patterns of marriage, childbearing and residential arrangements are assessed. Analysis is based on data collected from the manuscript censuses for two working class Montreal wards, Ste. Anne and St. Jacques between 1861 and 1881. This is complemented by information from other contemporary quantitative and descriptive sources. The roles of fathers, children and mothers are examined in separate chapters for age and gender combined with class position to determine people's roles in the family and in the wider economy. Within the working class, the level and regularity of men's wages set the contours of the family economy conditioning the need for and the nature of other survival strategies. Differences of around 25 cents a day translated over a year into the possibility of divergent standards of living, roughly dividing the working class into separate, identifiable fractions. Each favoured particular survival strategies and exhibited different patterns of family labour commitment, marriage, reproduction and residence. Over this period the contours of working class youth were reshaped. Growing numbers of children aged six to twelve attended school. An increasing proportion of older children were drawn into wage labour. Boys were more likely to work for wages than girls. Girls worked in a narrower range of jobs and for a shorter span of their lives. On marriage most ceased wage earning. With whatever money others earned, they tried to ensure that the family's wage labourers faced each day sufficiently fed, clothed and rested to work. And, in abysmal living conditions they produced and socialized the next generation of workers. Occasionally seeking wage labour themselves, raising animals or gardens, or sharing their homes helped some women to come closer to balancing family budgets. Working class women remained, however, both economically and legally dependent on their husbands. This dependence was highlighted in the problems that widows faced when they tried to raise and feed a fatherless family.
OCLC: 17477409
Keywords: Academic theses; Thèses et écrits académiques; dissertations

An Examination of Conditions Surrounding the Subordination of Nursing Labour in Canadian Hospitals During the Nineteenth Century - Falcon, Nicholas Coyle (Carleton University, 1984)
This thesis presents an examination of the processes surrounding the subordination of nursing labour in Canadian hospitals during the nineteenth century. Special emphasis is placed on the appropriation by hospitals of, first, the nursing practices of female lay practitioners, and second, the knowledge and skills which lay at the heart of those practices. In addition, the conditions of female labour at the end, of the nineteenth century are examined in order to explain why women subordinated their labour to hospitals.

Canada and the International Labour Organization in the Interwar Period, 1919-1940 - Hucul, Jeffrey Gordon (University of Windsor, 1984)
In 1919, Canada, by virtue of its central role in the conduct of World War I, took its place as a member of the international community in the League of Nations and in the first representative body for world labour, the International Labour Organization. This thesis examines Canada's relations with the I.L.O. in the interwar period (1919-1940). It is hypothesized that Canada's role in the I.L.O. in this period reflected not the concerns and ideals of the organization per se, but rather the political and constitutional goals of the Dominion government. Consequently, social reform in Canada, as implied in the principles of the constitution of the I.L.O., was usually of secondary importance to the governments of Canada during this period, and especially to Canadian industry, which were often united in thwarting the efforts of Canadian labour and the I.L.O. to influence social reform in Canada. Indeed, both Canadian governments and industry, came to recognize in the constitutional issue a useful vehicle to slow down the pace of social reform during this period....

Communism and the Canadian Working Class During the Great Depression: The Workers' Unity League, 1930-1936 - Manley, John (Dalhousie University, 1984)
The Communist Party of Canada's (CPC) attempts to operate the United Front tactics laid down by Lenin and the Comintern in 1920-22 foundered on the CPC's failure to come to terms with the profound character of labour's post-war defeat or with its own marginality. The task of creating a mass party capable of leading, in the not-too-distant future, a revolutionary struggle for power encouraged the CPC to ignore the laborious and modest process of building support around small workplace issues and to prefer working through a spurious united front organization, the Trade Union Educational League, which was little more than a mouthpiece for a succession of abstract propaganda campaigns. When none of these propelled the party to mass status, but rather drove a wedge between it and the Trades and Labour Congress, the ground was prepared for acceptance of the diametrically opposite tactics of the "Third Period", which with much justice have been criticised for their political stupidity. The tardiness with which the CPC applied them underlined the fact that, however much the leaders of the labour movement might have "betrayed" the rank and file, it was hard to see them as "social fascists" who had to be combatted with even more vigour than that usually reserved for the bosses. From the beginning, when they terminated an interesting alliance between the CPC and national unionism, to the end, when they retarded the CPC's recognition of the possibilities opened up by the emergence of the CIO, these tactics had negative consequences. Yet they also helped bring limited political gains for the CPC, which entered the latter half of the 1930s stronger than it had ever been, and organizational advances for the Canadian working class, in the shape of at least the first few bricks in the foundations of mass industrial unionism. In addition, the complementary unemployed movement mobilized tens of thousands of workers and their families against the asperities of the depression. By 1936, the CPC had undeniably "carved out" for itself, a decent niche in the labour movement.
Keywords: Education

Canadian Women in Radical Politics and Labour, 1920-1950 - Sangster, Joan (McMaster University, 1984)
This thesis examines the role of women in Canadian socialist parties from the 1920's to the post-World War II period, by focusing on women involved in the Communist Party of Canada (CPC) and the Cooperative Commonwealth Federation (CCF), the primary manifestations of organized socialism during these years. Concentrating on two regions, Ontario and the West, the thesis explores three major themes: the distinct role women played within each Party, the Party's view of the woman question, and the construction of women's committees within each Party. The thesis explains why women were drawn to the socialist movement, assesses the successes and failures of each Party's program for women's equality, and suggests how and when feminist and socialist ideas intersected within the Canadian Left. The written history of the Canadian Left has largely neglected socialists' views of the woman question and women's role in the CPC and CCF. Although 'women were concentrated in less powerful positions, they did play an important, and distinctive, role in the making of Canadian socialism. Moreover, attention to women's social and economic inequality was a concern of Canadian socialists. Between 1920 and 1950, however, women's emancipation was never a priority for socialists. This thesis explains some of the reasons, both internal and external to the movement, for the secondary status of the woman question. Because the CCF and CPC emerged from different ideological traditions, their views of the woman question varied, and this thesis contrasts the two Parties' definition of women's issues and their commitment to women's emancipation. At the same time, there were some similarities between the two Parties, such as their attempts to link women's maternal and domestic roles with their political consciousness. The thesis also suggests ways on which socialists' ideas resembled the earlier ideology of womanhood and reform termed 'maternal feminism' and how their ideas, shaped by a different class perspective and social context, differed from the earlier feminists.

Proletarian Spirits: A Social History of the English-Language Labour Press in Canada to 1900 - Verzuh, Ronald William (Carleton University, 1984)
This social history traces the English-language Canadian labour press from 1842 to 1900. It focuses on the role labour newspapers played in battling the appalling social conditions of Victorian Canada,and analyzes their successes and failures in trying to improve the lives of working-c1ass Canadians. Although the original theoretical framework called for a survey of the effects of labour journalism on the passage of progressive social legislation, little such legislation appeared on statute books before 1900.The thesis therefore attempts to show how the papers presented social issues in housing, health, welfare, employment,social security and several other key social development areas,through the use of anecdotal evidence and, the critical assessment of the opinions of historians. The underlying theoretical assumption of the thesis was that labour papers would provide a progressive view on all social issues.Although this image did not always prove true, the thesis does unearth evidence of the role of the labour press in the development of a mass working-clas sconsciousness and the creation of a unique working-class culture.The thesis further attempts to show how labour editors of the late 1800s were the pioneers of a radical intellectual and journalistic tradition which found expression in the weekly journals that represented the fledgling Canadian labour movement.
Keywords: Social sciences

Times of Trouble: Labour Quiescence in Winnipeg, 1920-1929 - Hall, David E. (University of Manitoba, 1983)
This thesis originated in my curiosity over the last decade or more, as to the fate of the "golden age" of labour radicalism in Winnipeg after the First World War. As a radical and trade unionist I wanted to understand why this radicalism declined so drastically over the half century to the leve1s it existed in the city's unions in 1969 when I first got involved in the labour movement. The logical place to start looking for answers was the decade following the general strike and preceding the depression of the thirties. In researching and writing this thesis I have found some answers, although they have seldom been simple, about the effects of the twenties on union radicalism. The task has been made more difficult and at the same time more stimulating by the almost total lack of work by labour historians on the twenties. To the extent that the period has been dealt with at all it was as a prelude to the great depression and the rise of the C.I.O. in Canada, or as a postscript to work on labour and radicalism before and during the post war upsurge and in Winnipeg, the general strike...

Resistance to Exploitation: East Indians and the Rise of the Canadian Farmworkers Union in B.C - Jhappan, Carol R. (University of British Columbia, 1983)
British Columbia has an undistinguished history of racial discrimination against ethnic minorities, most notably against "Asiatics", such as the Chinese, the Japanese and East Indians. Members of these "visible" minorities were allowed into the province in the past as cheap labo

All the Wrong People: The Trial and Career of Labour Lawyer, J. L. Cohen - Estok, David Michael (Carleton University, 1982)
Jacob Lawrence Cohen was a prominent Canadian labour and civil rights lawyer in the 1930's and 1940's. Cohen was instrumental in negotiating a number of landmark labour disputes that helped pioneer legislation in Canada. He also defended a number of trade unionists, many of whom were Communist, imprisoned under the War Measures Act. His staunch defense of society's underdogs brought him a great deal of respect and notoriety. Cohen's career reflected many of the tensions of Canadian society in the period. The growth of industrial unionism, the development of progressive labour legislation and a growing fear of Communism, all touched him professionally and personally. His brilliant career ended abruptly in 1946 after his conviction of assault. His trial raises a number of questions about the judicial system. After a four year struggle in the courts, Cohen's law practice resumed in 1950 but he failed to regain his former prominence. He died in May 1950. J.L. Cohen had a great impact in developing and fighting for progressive labour laws to deal with the changing society of the 1930's and the 1940's. He was in the centre of a turbulent period in Canadian history as counsel in diverse and unpopular legal cases. Many of his struggles helped legitimize the aspirations of the labour movement and develop the legal and jurisdictional regulations that govern all trade unions today.

The State, Organised Labour, and Wage Controls in Canada - Kraft, Allan David (McMaster University, 1982)
The focus of this thesis is the Liberal government's program of mandatory wage and price controls introduced on October 14, 1975. Beginning with a brief discussion of the marxist theory of the state, the thesis examines prior experiences with wage restraint programs, the evolution of post-war industrial relations, and the emergence of symptoms of economic crisis toward the end of the 1960's. Thereafter it considers the progress of state efforts to introduce wage/ price restraint, the social forces which shaped the pattern of state intervention, the actual operations of the Anti-Inflation Board, and the character of organised labour's opposition to compulsory controls. The thesis argues that state intervention into the sphere of wage bargaining is one concrete example of the deeper contradictions which lie at the basis of the state structure. With the end of the long boom of post-war expansion, the underlying tendencies toward a crisis of capital accumulation became manifest. The deteriorating effectiveness of established techniques of economic management, and the failure of the Liberal government to develop a coherent program of capitalist planning set the immediate context for the program of wage and price controls. The objective of controls was to restrict the rate of wage increases, thereby easing the downward trend in profit levels and relaxing the fiscal crisis of the state. The record of the Anti-Inflation Board revealed two general characteristics of the current economic and social crisis. First, the capitalist state is virtually powerless to exercise any influence over the long term pattern of inflation and slump. At the present stage of capitalism, attempts to plan economic development simply exacerbate the inherent anarchy of capitalist production. Second, the weakness of organised labour's opposition to controls indicates the urgent necessity for a restructuring of the economic and political organisation of the working class in order to defend the economic and social gains of the postwar period.

Ethnicity and Class Conflict at Maillardville/Fraser Mills: The Strike of 1931 - Williams, M. (Simon Fraser University, 1982)
During the Depression Canadian workers faced a series of assaults on their wages and working conditions. Threatened by shrinking markets, Canadian employers moved to reduce labour costs. When the Canadian Western Lumber Company at Fraser Mills, B.C., attempted to follow the pattern being set throughout the Canadian economy, the millworkers went out on strike. Lasting for two and half months, the labour protest by the millworkers and their families ended in success. The success of the 1931 strike stands in sharp contrat to the generally abysmal performance of organized labour during the thirties. The strength of this particular protest was derived from two totally unrelated factors. The strike was led by the militant Lumber Workers' Industrial Union, an affiliate of the Workers' Unity League. During the thirtiees the Workers' Unity League was one of the most dynamic labour organizations in Canada. The real strength of the protest, however, lay in features to the community. The worker community of Maillardville/Fraser Mills was remarkably stable and socially cohesive. This was largely due to the existence of a persistant, tightly organized community of French-Canadian workers. The workforce at Fraser Mills had a well-defined associational network which not only faciliated organization prior to the strike but also ensured its success once the strike was underway. This study of the Fraser Mills strike of 1931 analyzes the relationship between labour protest and the community from which it emerged.

CAIMAW [Canadian Association of Industrial Mechanical and Allied Workers] : Portrait of a Canadian Union - Atherton, Patricia Gwen (University of British Columbia, 1981)
This study of CAIMAW's history attempts to explain why some Canadians in recent times have abandoned international unions to found and develop an independent Canadian union, to determine whether such an independent union is identifiably different from those unions traditionally operating in Canada, and to identify the factors that operate in favour and mitigate against the success of Canadians in their attempt to create and develop such a union. Personal interviews with the major figures related to this study comprise an essential source of information. Due to the cooperation extended by CAIMAW, a search of union files was conducted and constitutions, pamphlets, correspondence, newspaper articles, union publications and other relevant documents were examined. Published sources provided secondary information for the majority of this paper. A societal mood in the 1960's of labour militancy, uncertainty arising from adaptation to change, a desire for Canadian self-assertion, and a corresponding resentment of American influence in Canadian affairs combined to set the stage for the formation of breakaway independent Canadian unions in Winnipeg and Vancouver. Lack of control over their own affairs and the imposition on the membership of unpopular union decisions by international officers created unrest among these Winnipeg and Vancouver workers, and a demand for greater membership decision making authority. Refusal by the international unions involved to respond to this demand resulted in a coalition of union dissidents and nationalists in a common cause, the rejection of their international unions and the founding of their own, independent national unions. The merger of the Winnipeg and Vancouver breakaway unions gave rise to a constitutional battle seated in philosophical differences with overtones of regionalism. It was a struggle between business unionism and social unionism, and a corresponding struggle between centralized authority and local autonomy. The resolution of this struggle in the rejection of business unionism and centralized authority laid the foundations for the policies and practices of CAIMAW as it operates today. These policies and practices make CAIMAW a union that is identifiably different from traditional international unions in terms of greater decision-making power for the rank and file, different methods of bargaining, and a different organizational structure. These differences do not, however, appear to have hindered CAIMAW's ability to win benefits for its membership that are at least comparable to those won by international unions. An independent union such as CAIMAW faces difficulties in its formation and development due to the established place of international unions in Canadian labour institutions. But weaknesses within these institutions such as interunion and intraunion divisions have allowed CAIMAW to survive and, indeed, grow. CAIMAW can draw support from union dissidents, nationalists and socialists of the New Left, groups which traditional labour institutions in Canada have failed to accommodate. To the extent that a society creates institutions in accordance with its needs, there exists an important place for CAIMAW in Canada.

Teacher Union: Myth or Reality? - Braithwaite, John Anthony (McGill University, 1981)
This study sought to determine whether the St. Lawrence-Richelieu Teachers' Association (SRTA) was a union or a professional association. The question was tackled by subjecting the SRTA to various definitions of unionism and professionalism, and by examining the operational behaviour of the teacher organization in recent years. It was found that with respect to the definitions of the terms established in the thesis the SRTA cannot be called a union or a professional association per se. However, although the organization has exhibited traits of unionism and/or professionalism throughout its evolution, it is clear that the SRTA is today closer to a union than to a professional association.
Keywords: Saint Lawrence-Richelieu Teachers’ Association.; Teachers’ unions – Québec (Province).

Farm Apprentice to Agricultural Proletarian: The Hired Hand in Alberta, 1880-1930 - Danysk, Cecilia (McGill University, 1981)
Farm labourers formed an important segment of the agricultural work force in Alberta betweeen 1880 and 1930. The work they performed was arduous, poorly paid and insecure, but was accepted by most as a necessary first step toward farm ownership. During the early years of settlement, the perception of farm labour as an apprenticeship was confirmed by the ready availability of agricultural land. But settlement expansion in the years before the First World War greatly reduced opportunities for farm ownership, leading to a redefinition of hired workers. By the 1920s, they were no longer farm apprentices but an agricultural proletariat. At the same time, rapid agricultural development and a number of social and economic changes led to a relative decline in their working and living conditions. There was almost no attempt by farm workers to resist these changes. Despite their importance within the agricultural work force, a number of formal and informal constraints made it difficult for them to challenge their deteriorating position. Hampered by isolation, economic pressures and government controls, farm workers were above all restrained by their own inability to recognize that the perception of their position as farm apprentices was no longer valid.
OCLC: 15955208
Keywords: Academic theses; Agricultural laborers; Agricultural laborers Prairie Provinces History; Agriculture; Agriculture Prairie Provinces History; Agriculture Provinces des Prairies Histoire; History; Prairie Provinces; Thèses et écrits académiques; dissertations

Dependency, Class Relations and Politics in Rouyn-Noranda, Quebec [from the 1940s to the 1970s] - Glenday, Daniel (Carleton University, 1981)
This thesis is the study of class relations within a dependent capitalist environment. Upon defining the conceptual and geographical basis for this study, an explanatory framework is advanced which borrows from C.B. Macpherson and the work of numerous theorists of the dependency school. A detailed historical analysis of the external structures of domination, the corporation and the trade union, the internal dynamics of social change, and the dominated class of the petite bourgeoisie and the working class, is offered. In the process of our analysis, an alternate interpretation for the rise of Social Credit in Quebec during the 1960s is offered.

The Adaptation of the Quebec Protestant School System to Centralized Collective Bargaining: A Case Study - Krause, Peter J. H. (McGill University, 1981)
This study traces the development of the collective bargaining process for teaching personnel tram 1964 to 1969 in the Protestant Education System of Quebec and describes the effects that this development had on the Quebec Association of Protestant School Boards (QAPSB) and the Provincial Association of Protestant Teachers of Quebec (PAPT). The study includes an analysis of certain sections of the Education Act and other legislation sanctioned by Quebec's Legislative Assembly dealing with the collective bargaining process as it relates to school boards and teachers. The following questions are addressed in this study: 1) to what extent did the Government of Quebec change its participation in the process of determining conditions of employment for teachers during the period from 1964 to 1969; 2) in what respects did the QAPSB and PAPT redefine their respective approaches to the establishment of conditions of employment for teachers; 3) what aspects did QAPSB and PAPT reorganize internally and to what degree did they establish formaI liason between themselves and their Roman Catholic counterparts at the Provincial level?
OCLC: 15891313
Keywords: Academic Dissertation; Academic theses; Thèses et écrits académiques

Immigration, Ethnicity and the Labour Market: The Chinese in Montreal - Pao-Mercier, Laura Yuen-Ha (McGill University, 1981)
This thesis examines the labour market experience of Chinese post-war immigrants in Montreal's ethnic and general labour markets. It provides empirical information on the Chinese ethnic labour market in Montreal and assesses the theoretical relevance of the distinction of an ethnic labour market from the general labour market for the understanding of the socio-economic attainment of immigrants in Canada. The findings reveal significant segmental differences in the composition of the labour force, employment characteristics, mobility patterns, and monetary returns to human capital investment. These indicate the distinctiveness of the ethnic labour market and provide support for Wiley's (1968) thesis of the ethnic mobility trap. Theoretical implications of these findings for studies of occupational achievements of immigrants in Canada are discussed.

Ethnicité et fragmentation du mouvement ouvrier : la situation des immigrants juifs au Québec, 1920-1940 - Szacka, Alexandra E. (Université Laval, 1981)

"The Balance Wheel of the Industrial System": Maximum Hours, Minimum Wage, and Workmen's Compensation Legislation in Ontario, 1900-1939 - Campbell, Jane Elizabeth (McMaster University, 1980)
Recent attempts to extend Marx's analysis of capitalism by developing a class-based theory of the role and functions of the capitalist state have turned on the debate between the "instrumentalist" and "structuralist" perspectives. Subsequent critiques and extensions of these two conceptions of the relations between the state and the major classes within capitalist society have raised the issues of the role of class struggle in the development of state structure and policy as well as the impact of the capitalists state itself on the nature of class relations. Although theorists have pointed to the mutually conditioning effects characterizing the relationship between the state and social classes, there has bee little empirical examination of this relationship. The precise nature of the kinds of mechanisms linking various social classes and the state together with the concrete effects of these links on state and class relations required further specification. In response to this significant gap in the development of the theory of the capitalist state, the present research was formulated to address the issue of specifying the forms of mediation between the state, industrial capitalists and labour through an analysis of the history of maximum hours, minimum wage, and workmen's compensation legislation in Ontario between 1900 and 1939. These areas of legislation were chosen because of their significance, for both capitalists and workers; they represent a potential drain on accumulated surplus for owners of capital and a potential improvement in subsistence and working conditions for labour. The development of legislation in each of these areas thus provided a focus for examining relations between owners of industrial capital, wage labour, and the state. The major sources of data for the primary analysis covering the period from 1900 to 1939 consisted of private papers, published and unpublished government documents located in the Public Archives of Ontario and the Public Archives of Canada, labour newspapers, and the journal of the Canadian Manufacturers' Association. The analysis of relations between workers, employers, and the state around limitations on working hours, minimum wage regulation, and the establishment of a workmen's compensation program identifies a number of modes by which capitalist domination in the workplace is mediated to the level of political relations. These modes of mediation function through mutually reinforcing economic, political and ideological forms and have as their primary effect the frustration of the political organization of labour as a class. Capitalist modes of mediation are parallelled and supported by the modes of mediation adopted by the state in its role of managing class relations. In the process of the development of the areas of legislation which are the focus of this study, the state functioned to maintain the hegemony of capitalist social relations of production by transforming the economic class struggle and processing labour demands in such a way that subsequent state policy and structure were guided in the direction of comparability with prevailing class relations of domination and subordination.

A History of the Newfoundland Federation of Labour, 1936-1963 - Gillespie, Bill (Memorial University, 1980)
Throughout its history the Newfoundland Federation of Labour has pursued two primary goals - to spread trade union organization and to lobby government to adopt legislation favourable to the interests of working people. The degree to which the Federation has been successful has depended upon the quality and dedication of its leadership, economic conditions and the willingness of government to be influenced. An unstable, rural economy delayed the emergence of a Newfoundland Labour Movement until the mid-1930s. Once it did emerge, however, Newfoundland workers responded enthusiastically. The NFL's founding meeting in 1937 at Grand Falls was followed by a country-wide organizing drive. Despite a six year lull caused by World War II, by the late 1940s the Newfoundland labour force was the most highly operated in North America. Unlike their counterparts in Britain, however, Newfoundland trade unionists were unable to translate their numerical strength into political power. The explanation lies in a combination of the NFL's relationship to sections of the North American Labour Movement opposed to direct political action, divisions within the Newfoundland Labour Movement, and a set of political circumstances unique to Newfoundland. – Although the NFL was a national labour central until Confederation with Canada in 1949, it was dominated by unions affiliated to the American Federation of Labour. The AFL's opposition to direct political action is well documented. However, in a country with strong ties to Great Britain the success of the British Labour Party provided an alternate model. Even so, there were only two serious attempts between 1937 and 1963 to emulate British practice. For the most part the NFL was less "political" than even the AFL. Initially this was because from 1933 to 1949 Newfoundland was governed by a commission of civil servants appointed by Britain. In a country without a system of electoral politics, direct political action did not seem a pressing concern. When electoral politics were restored and J.R. Smallwood became premier of Canada's tenth province, Smallwood granted the NFL almost every request it made for legislative reform. As a result the NFL saw no need to develop an independent political base in order to guarantee its influence with government. The fault with this approach was demonstrated during the IWA Strike of 1959. Smallwood suddenly turned against the Federation and without a political base of its own the NFL was powerless to protect the interests of Labour. Smallwood's subsequent attacks on the NFL sent it into a ten year period of decline; however, it is the thesis of this dissertation that the NFL's failure to give sufficient weight to the changed environment brought about by the return to electoral politics was as much the cause of its decline as any external factor.

Organised Labour and Social Democracy in Britain and Canada - McBride, Stephen K. (McMaster University, 1980)
This thesis deals with the working class of two advanced capitalist countries and focuses upon ideological conflict within working class organizations such as trade unions and political parties. The outcome of such conflicts within working class organizations is considered to be an expression of the state of working class consciousness at a given time. Within this broad context particular attention is paid to the ideology of social democracy which has been dominant in working class organizations in both countries during the modern period albeit to different degrees. The thesis uses a comparative approach and pays considerable attention to the interaction between the working class and its societal environment- the political economies of the two countries, the activities of the capitalist class and the impact of its ideology upon the working class. Using this approach the thesis deals with the emergence of social democracy as the hegemonic working class ideology, its main features particularly as they were developed in the post-war period, the emergence of possible contradictions between social democratic parties and ideology, and their working class supporters, and, utilizing an historical analysis of previous ideological shifts in working class organisations, the possibility of social democracy being superceded in its hegemonic role is considered. In dealing with such matters the issues of nationalization and incomes policies were judged to be especially salient and are discussed in some detail. In the course of this study theories which posited an end to ideological conflict in the advanced capitalist societies are considered and rejected. The past, present and future of social democracy, of ideological conflict, and of the working class itself, was found to be considerably more dynamic, complex and open to change than such theories had imagined.

Men, Money, Machines: Studies Comparing Colliery Operations and Factors of Production in British Columbia’s Coal Industry to 1891 - Gallacher, Daniel Thomas (University of British Columbia, 1979)
Coal mining in nineteenth century British Columbia was confined almost exclusively to the tidewater coal measures of Vancouver Island where it was expanded rapidly from 1871 to 1891. This dissertation's purposes are to describe the coal industry's rise, account for its fast growth in the seventies and eighties, and assess the coal trade's general impact upon the region's economy. The approach is thematic, focusing in turn upon coal lands, capital, management, labour, technology, markets, production, and productivity. Standard research, organization, and interpretation methods for economic history are followed, including thorough descriptive use of statistical data. Comparisons are intensive and far-reaching, resulting in a close-knit framework upon which important conclusions are based. No effort has been made, however, to offer extensive biographical information on the coal trade's leading personalities. These studies confirm the coal industry's rapid expansion, and determine that all factors of production can explain that phenomenon with a high degree of certainty, though market demand and management technique do so more readily than other agents. It is shown that management methods and styles evolved quickly, the most effective being the owner-manager type as practiced by Robert Dunsmuir, the industry's most successful proprietor. Risk capital was drawn from various sources, including mainly British direct investments, local savings, partnerships (often involving foreign investors), and ploughed-back profits. Entrepreneurs and promoters were active in attempting to develop coal properties from 1864 on, though only those highly experienced in mining and management succeeded. Chronic worker shortages, coupled with the physical problems associated with coal mining in mountainous terrain, forced coal operators to opt early for labour saving technology imported almost exclusively from Britain. The introduction of large numbers of Oriental colliers by Dunsmuir after 1870, (who were willing to work at half the wages whites would), slowed the technological advance of the industry, but not annual rates of production increases. Considerable friction between white workers and management resulted from the latter's initiatives with Oriental labour, while the owners' policy of severely restricting wage-rates caused further serious labour problems, including a high number of work stoppages. Mine safety, job security, and general working conditions also were contentious issues. B.C.'s early collieries relied heavily upon the California market which often was unsteady, but which accounted for approximately seventy-five percent of all sales during the years 1849-91. Domestic users were mainly shipping companies, light industry, and households. Much of the local market was handled at the pithead. The major coal companies streamlined their channels of distribution by opening their own sales offices in Victoria and San Francisco, and. in the case of Dunsmuir, by also building a collier fleet and a railway of his own. The coal industry had a major influence upon southern Vancouver Island's economy, but not a large impact upon the remainder of the province. No determined "attempts were made by coal proprietors or other capitalists to create secondary industries linked to coal production, though colliery owners did invest in land, transport, and retail-wholesale ventures designed either to service their mining activities or to diversify their personal holdings. Such moves occurred later-on, however, as the main thrust of their initial efforts was to establish and maintain the coal trade with California.

Cooperation and Conflict: Relations Among the Teachers' Associations in Québec, 1959-1969 - Wright, W. Alan (McGill University, 1979)
A vital element in 'the transformation of Québec society during the period of "la révolution tranquille" was the establishment of a modern education system. As the government of Québec took initiatives to remodel education, the Corporation des Enseignants du Québec (CEQ), the provincial Association of Protestant Teachers (PAPT), and the Provincial Association of Catholic Teachers (PACT), became more involved in the mainstream of Québec education. The scope of the teachers' associations' actions evolved, they grew as organizations, and they emerged as militant unions in Québec's work force. While the teachers' associations worked in isolation from one another at the beginning of the ten-year period, there was movement towards greater cooperation in the mid-sixties and there were constant contacts during the latter part of the decade: these contacts involved significant cooperation but the associations were also in conflict over several issues. Cooperation among the associations was most highly developed in relation to economic and labour relations concerns. Serious conflict arose over the issues of language, school board reorganization and membership jurisdiction.
Keywords: Teachers' unions – Québec (Province)

Deportation Under the Criminal Code and the Immigration Act, 1919-1936 - Dick, Eric Lyle (University of Manitoba, 1978)
The 1919 sedition and deportation ammendments in Canada were not merely the product of anti-radical hysteria induced by the Winnipeg General Strike, but were consistent with the ideological propensity of the Conservative-Unionist and Bennett governments to suppress alien and left-wing dissent. This tendency was reflected in earlier, anti-radical enactments by Borden's government under the War Measures Act, providing, among other things, for the summary internment and deportation of suspected alien radicals. For the most part the stringent measures passed in 1919 represented the conversion of wartime powers to peace-time legislation. The conservative ideology that inspired these amendments was manifested in the vigorous application of deportation powers by immigration and other officials during the Red Scare of 1919-20 and the depression of the early thirties. It was further sustained by the stubborn refusal of the Conservative majority in the Senate to approve repeal legislation repeatedly passed by the House of Commons, even in the context of domestic stability in the 1920s. Ultimately, conservative reaction was superseded by liberalism in the form of civil liberties legislation passed by Mackenzie King's government. The emergence of the repeal of Section 98 of the Criminal Code as a major issue in the 1935 Dominion election and Bennett's corresponding defeat had demonstrated the Canadian public's desire that its governments address themselves, not to the suppression of radicalism, but to the solution of economic problems underpinning social unrest.

The Strikes in Winnipeg in May 1918: The Prelude to 1919? - Johnson, Albert Ernest (University of Manitoba, 1978)
While realizing the necessity of being aware of the work of others, in order to get a reasonably adequate view of the events of May 1918 in Winnipeg, it has been necessary to make extensive use of primary sources, contemporary newspapers, interviews, and archival material. Wherever possible the information closest to the source has been used. Contemporary newspapers have been particularly valuable primary sources because they tended to report in depth about meetings, speeches, agreements, and announcements. Fortunately, by making comparisons with official documents, now available, it has been possible to verify that in general, newspaper reports were reasonably accurate. Except for the Telegram, most newspapers kept their news gathering function quite sharply separated from their editorial function. Interviews have been conducted with the realization that elderly people do not always remember the past as it really was. Their perceptions are, nevertheless, interesting...

Ideology Surrounding Women's Work in Canada, 1931-1956 - Boutilier, Ann Marie (McMaster University, 1977)
Ideology determines how one experiences the world, shapes beliefs and expectations. Ideology is rooted in the structural dynamics of the social formation within which it exists. The articulation of the ideological with the economic structure can become problematic at certain points in time. This thesis uses a structural analysis to explore how changes in the economy have affected women in the Canadian labour force and how these changes related to the ideology surrounding women's work. Integral to this thesis is an analysis of how the State, through its labour policy, its government publications, and so on, does at times mediate between the economic situation and the dominant ideology as reflected in the popular media. This ideology is manifested through the institutional structure of the State as it influences both labour policy and the media.+ This thesis presents empirical data on the changes that took place in Canada between 1931 and 1956 in the ideology surrounding women's work. We take articles appearing in popular magazines and government publication of the era to be manifestations of the dominant ideology. We analyze materials in Maclean's, Chatelaine, Saturday Night, and the National Home Monthly. We analyzed government publications relating to labour policy; focussing on the Labour Gazette, and several reports and publications of government committees. The thesis begins with a theoretical outline. We discuss the concept of ideology and consider its role in the reproduction of class relations, the concept of a reserve army of labour, and finally, a brief summary of the concepts outlined above. We conclude the first chapter with a discussion of the methodologies used in our qualitative and quantitative analyses. The second, third and fourth chapters use qualitative analyses of periodicals to trace the articulation of the ideoloeical with the economic. Specific references are made to the media, to labour policy and to changes in the economy. These chapters deal with three distinct time periods – with the Depression, with the World War Two years, and the period 1946 to 1956. In Chapter 5 we present a quantitative content analysis of selected magazines over the three periods. Our analyses of variations in the frequency of publications of articles relating to women's work and their activities both inside and outside the home confirm the shifts in emphasis over the period 1931 to 1956 that emerge from the earlier quantitative analyses. However, while the content and tone of articles does change with time, as is revealed in the qualitative analysis, the majority of articles have always related to traditionally domestic and feminine concerns. The data show an increasing professionalization of the housewife role. We conclude with a discussion of the importance of ideology in determining what is defined as women's work, and the importance of the control of women's labour market participation to the maintenance of the existing capitalist economic order.

A Political History of Saskatchewan, 1905-1929 - Brennan, James William (University of Alberta, 1977)
https://era.library.ualberta.ca/items/e1602b48-2236-4082-a895-735bfb85d9d8 OCLC: 317466009
Keywords: Academic Dissertation; Academic theses; History; Political parties; Political parties Saskatchewan History; Saskatchewan; Saskatchewan Politics and government 1905-1929; Thèses et écrits académiques

A History of the Mine Workers' Union of Canada, 1925-1936 - Seager, Allen (McGill University, 1977)
The Mine Workers' Union of Canada was a trade union, centred in the coal fields of the Province of Alberta, which existed between the years 1925 and 1936, and included a membership of between 2,000 and 4,900 mine workers during that period. The formation of the union came about as a result of the break-up of District 18 of the United Mine Workers of America in 1924-1925. From the onset, its leadership was composed of differing elements, from conservatives who opposed the U.M.W. of A. for nationalistic reasons, to members of the Communist Party. The M.W.U.C. was one of the founding members of the All Canadian Congress of labour in 1927, and its President, Frank Wheatley, was a Vice-President of the Congress, until his ouster from the miners' union in 1930. miners' union in 1930. Early in that year the Communists, led by Harvey Murphy, began a drive to have the M.W.U.C. disaffiliate from the A.C.C.L., and join the new revolutionary trade union central, the Workers' Unity League. They were apparently successful, for in May of 1931, the union's membership voted by a 73% margin to affiliate with the W.U.L. Later that year the Communist Party of Canada was outlawed and the M.W.U.C. itself was declared to be an "unlawful association" in the courts. Anti-communist and anti-union sentiments on the part of employers led to long and bitter strikes, the most important of which took place in the Crows' Nest Pass in 1932. Finally, after six years of intense struggle on both the industrial and political fronts, the Workers Unity League was disbanded by the Communist Party. In June of 1936, the membership of the Mine Workers' Union of Canada voted to return to the U.M.W. of A. and the union passed into history.
Keywords: Social sciences

A Test of Social Conflict Theory: The Case of the Winnipeg General Strike - Thomas, Lillian Jean (University of Manitoba, 1977)
The problem to be investigated in this study centres on discovering how urban conflict first emerges as a visible force. Those circumstances which led to the outbreak of open conflict in Winnipeg will be examined to test four competitive social conflict theories. Each theory establishes a series of assumptions about how conflict will emerge. The substantive implicatjons of these assumptions will be compared with the available information on the actual conditions evident at the moment of the emergence of the strike. Through this comparison, this jnvestigation will determjne which theory or theories best describes how the incident of urban confljct actualiy emerged to produce the Winnipeg General Strike of 1919. This research has concentrated on urban conflict, rather than rural conflict, because the urban culture more accurately reflects the structural make-up of our society. In Canada, over l6 million people live in cities. That represents 76.1% of the total population of Canada, and this figure is rising by 2.9% per annum. Thus, with an increasing majority of our population residing in urban centres, the problems of urban living and its resultant conflicts, have become an increasingly salient feature of the composition of Canadian society. This investigation will be performed by centering specifically on urban unrest, rather than analyzing turmoi1 at a regiona1 or national level. Canadian history has had few examples of wide-scale conflict. Most forms of insurgence within Canada have been limited to either a single industry or a single city. This may be because Canadian cities are isolated from each other, and extend across the country in a series of pockets located along its southern border. This separation may have made it difficult, in the past, to transport issues to other communities. As telecommunications had greatly improved the linkages between urban centres by l919, this may explain why some sympathy for the Winnipeg General Strike was expressed jn other cities by means of minor sympathy strikes, although there was little long term unified protest outside the city itself. Therefore, limited by Canadian experience, this work will confine itself to the emergence of conflict within an urban centre.

Government Employee Unionism and the Ideology of Public Service in Canada, 1911-1939 - Thomson, Anthony (Dalhousie University, 1977)
Contents: Chapter 4, Militancy in the Canadian Civil Service, 1918-1920 – Chapter 5, The Response to Classification and Reorganization – Chapter 6, The Ascendancy of the "Service Ethic." [Only these chapters are available from the website.]
See also the excerpt, "Early Unionization in the Canadian Post Office": https://www.acadiau.ca/~thomson/postofficeunionism.pdf OCLC: 15823704
Keywords: Canada. Civil service. Collective bargaining; Canada. Collective bargaining; Canada. Government employee unions; Civil service; Government employees; Government employees. Government employee unions

Labour, Capital and the State: Canadian Railroads and Emergent Social Relations of Production, 1850-1879 - Barkans, John Victor (McMaster University, 1976)
The impact of rail road development on Canadian society has recently become a much debated topic. A significant interpretation of Canadian economic development posits a fundamental contradiction between mercantilists and industrialists, arguing that the former have maintained supremacy over the latter and that this has retarded the emergence of industrial capitalism. Further, it is claimed that Canada's railways were designed to promote mercantile interests and functioned to impede the transition from a mercantile to an industrial economy. The above formulation, however, largely employs strictly economic criteria to characterize Canadian society. This thesis presents an alternate framework, one which attempts to view social reality from the bottom-up, that is from the point of view of the producers and their work relationship. Using the criteria developed for this framework, it is argued that railroad development between 1850 to 1879 marked the transition from a mercantilist to an industrial capitalist society and, moreover, that these transportation projects were the backbone of this social change.
OCLC: 841625736

Histoire des travailleurs québécois : la CSN et la FTQ de 1939 à 1970 - Boucher, Jean (Université Laval, 1976)
Ce travail est le résultat de recherches entreprises depuis l’été 1973 en vue de l'obtention d'une maîtrise au Département d'Histoire de l'Université Laval. Il vise à combler un vide dans l‘historiographie sur le mouvement syndical québécois au XXe siècle. Nous espérons que la tâche accomplie permettra â la classe de travailleurs de mieux percevoir en général la société dans laquelle elle évolue ainsi que de connaître plus particulièrement la réalité historique, souvent complexe, du syndicalisme ouvrier. –Avant-propos

Labour Relations in the Saskatchewan Coal Mines During the 1930s - Makahonuk, Glen Richard (University of Saskatchewan, 1976)
Labour relations are concerned with the dynamic interactions among workers, unions, employers, and government. These groups are engaged in a struggle for power; that is, the ability to achieve one's objectives despite resistance. This struggle usually results in a power conflict. The power conflict mayor may not create 'good' labour relations; that is, the establishment of mutual cooperation among the groups. The power conflict usually results in 'poor' labour relations as expressed by strikes. Strikes seem to be the main feature of labour relations. Practically all the evidence accumulated on labour relations is concerned with strikes or the threat of strikes. Consequently, the evidence used in this thesis is concerned with the ten strikes which occurred in the coal mines of the Estevan-Bienfait area of Saskatchewan during the 1930s. The ten strikes were concerned with different issues. Strikes on September 8, 1931, October 3, 7, 17, 1938, and October 16, 1939, primarily involved wages, working conditions, and union recognition. The January 28 and February 23, 1932 strikes were caused by the refusal of some miners to join the Mine Workers Union of Canada and pay their dues. The strikes on February 22, 1932 and November l0, 1937 were concerned with the rein statement of a dismissed miner. The February 24, 1932 strike involved a sympathy display for the miners striking because their checkweighman was dismissed. These strikes occurred during the depression when both operators and miners found themselves in very difficult situations. There was little cooperation between management and labour as each group sought, in its own way, to increase its power, and to improve its economic position. Government attempts to restore peace and harmony to the troubled coal industry were also fraught with frustration. Labour relations in the Saskatchewan coal mines during the 1930s were characterized by conflict, frustration, and frequent work disruptions. This thesis examines the labour relations of that troubled industry.

Les syndicats nationaux au Québec, 1900–1930 - Rouillard, Jacques (Université d'Ottawa, 1976)
Le propos de notre thèse consiste à tracer l'évolution des syndicats nationaux au Québec pendant la période 1900-1930. Par syndicalisme national, nous entendons les syndicats qui ont préféré s'organiser sur une base nationale plutôt que de s'affilier à une fédération internationale. Ces syndicats se divisent entre deux tendances: l'une, non-confessionnelle, basée sur un nationalisme politique; l'autre, confessionnelle, identifiée aux syndicats catholiques. Au tournant du siècle, les fédérations internationales qui se lancèrent à la conquête du Canada, augmentèrent de façon importante le nombre de syndicats affiliés. De 1898 à 1902, leur nombre doubla au Québec pendant qu'il triplait dans le reste du Canada. Au cours de leur expansion, les internationaux se heurtèrent aux syndicats nationaux déjà bien établis au Québec, particulièrement parmi les ouvriers de la chaussure. Il en résulta une série de conflits qui culminèrent avec l'expulsion des syndicatsnationaux du Congrès des Métiers et du Travail du Canada en 1902. Ces syndicats se regroupèrent alors dans le Congrès National des Métiers et du Travail du Canada dont l'objectif était d'amener les travailleurs canadiens â se donner des structures syndicales autonomes. Le Québec répondit à l'appel du CNMTC, mais les autres provinces ne se montrèrent pas aussi réceptives à la cause nationale. Réduit à devoir s'appuyer à peu près uniquement sur le faible réservoir de travailleurs québécois, le Congrès national, tout comme les fédérations nationales d'ailleurs, ne comptaient plus avant la Guerre que des effectifs extrêmement réduits. Plusieurs syndicats avaient incliné vers les fédérations internationales, d'autres - c'est le cas de ceux de la ville de Québec - préférèrent l'indépendance à une affiliation nationale. C'est parmi ces syndicats rëfractaires â une affiliation internationale que le clergé trouva ses éléments les plus dynamiques lorsqu'il s'attela à la tâche de former des syndicats catholiques. Leur nationalisme les rendait rëfractaires au syndicalisme international; restait pour le clergé à les convaincre d'associer à ce nationalisme la doctrine sociale de l'Eglise. A partir de la Guerre, le syndicalisme national se perpétua donc au Québec sous une formule confessionnelle. Ce qui amena le clergé â s'intéresser à l'organisation des travailleurs, ce furent les tendances "socialistes" et "anticléricales" qui se sont manifestées au sein des syndicats internationaux. Certaines de leurs réclamations concernant le système d'éducation et le droit de propriété privée ont alarmé les milieux cléricaux qui cruent pouvoir mettre les travailleurs catholiques à l'abri de leur influence. On chercha donc à implanter des syndicats catholiques, formule qu'avaient mis au point les catholiques sociaux en Europe. Née en période de difficultés économiques et mal adaptée aux réalités du monde du travail, la première vague de syndicats catholiques avant la Guerre aboutit à un fiasco complet. Fort de l'expérience acquise, le second groupe de syndiqués catholiques venus se greffer au mouvement après la Guerre, connut plus de succès. Et, à mesure que croissaient leurs effectifs, les chefs du mouvement crurent le moment venu en 1921 de se structurer au plan national en jetant les bases de la Confédération des Travailleurs Catholiques du Canada. Acculée à de sérieuses difficultés de recrutement et en butte â l'hostilité du patronat, la centrale radicalisa certainesde ses options dans les années 20. La négociation de conventions collectives devint prioritaire parmi ses préoccupations pendant que la grève et l'atelier syndical ferme ne lui sont plus apparus comme aussi condamnables. Dès cette époque, commença à s'établir un fossé entre l'idéologie véhiculée par les syndicats catholiques et leurs pratiques syndicales quotidiennes. Cet écart qui est apparu dès la fondation de la CTCC ira en s'accentuant par la suite.

Canadian Railways and the International Brotherhoods: Labour Organization in the Railway Running Trades in Canada, 1865-1914 - Tuck, Joseph (University of Western Ontario, 1976)
The railway boom in mid-nineteenth century British North America added a new occupational group to the working class of the area—the men in the 'running trades' who operated the trains. By the mid-eighteen eighties, these men had become members of trade unions, the 'railway brotherhoods,' which had their headquarters and most of their members in the United States. These unions were the Brotherhood of Locomotive Engineers, the Brotherhood of Locomotive Firemen, the Order of Railway Conductors, and the Brotherhood of Railroad Brakemen (which became the Brotherhood of Railroad Trainmen in 1889). This 'Americanization' of the running trades in Canada had several causes, including a tendency for Canadian railroaders, like industrial workers elsewhere, to think in international terms when it came to unionization. Clearly, however, certain differences between Canada and the United States, and the presence of the border itself, might make it difficult at times for the international brotherhoods to serve adequately the needs of their Canadian members. This study examines their efforts in this regard. The approach is basically chronological. The period examined is from approximatley the middle of the nineteenth century to the outbreak of the World War in 1914, and covers several major areas: the entry of the brotherhoods into Canada and expansion afterwards; the elimination of rival organizations; relations with Canadian governments and railway managements; and the administration of the brotherhoods' Canadian wings....

The Road to Receivership: Unemployment and Relief in Burnaby, North Vancouver City and District and West Vancouver, 1929-1933 - Bradbury, Bettina (Simon Fraser University, 1975)
The poor and destitute have traditionally been ther esponsibility of municipalities in Canada.This responsibility became ananachronism with the mass industrial unemployment of the 1930's. Lacking the resources to provide relief alone, municipalities became dependent on help from the senior governments. Annual Relief Acts of the dominion government gave assistance, but stressed always municipal and provincial responsibility for relief. For the municipalities each new Act demanded both administrative and financial changes which had to be complied with in order to receive the badly needed help. Of all the three levels of government the municipalities bore the brunt of the unemployment problem of the 1930's. Local councils were in daily contact with the unemployed and their plight. Responsibility rested with them. Yet their inflexible and diminishing revenues did not allow them to take the initiative in solving the problem of unemployment. In British Columbia the problems of transients and of Vancouver City have absorbed most attention. Unknown or ignored is the impact of the depression years on the surrounding suburbs. In 1930 Vancouver's bedroom suburbs were Burnaby, North Vancouver City, North Vancouver District and West Vancouver. In the winter of 1932 to 1933, in the depth of the depression, the first three defaulted on bond payments and were taken over by a provincially appointed commissioner. West Vancouver in contrast retained solvency and hence local responsibility and control. The Dominion Acts were not designed to counteract the disparities between provinces and municipalities either in the incidence of unemployment or in their ability to cope with it. Burnaby, North Vancouver City and North Vancouver District were predominantly working class suburbs, many of whose residents and taxpayers lost their jobs. West Vancouver, by contrast, was a consciously middle class, residential suburb whose residents were much less susceptible to unemployment. As suburbs, unlike a city, have no major industries to compensate for non-payment of taxes by their residents, this basic occupational difference led to bankruptcy in Burnaby and North Vancouver City and District. The history of the attempts of these suburban councils to provide relief for the growing numbers of unemployed between 1929 and 1933 not only contrasts the difficulties of providing relief in working class and middle class suburbs, but also illustrates the problems that arose from insistence on municipal responsibility for relief. Daily contact with the growing numbers of unemployed and the obvious inadequacy of municipal and even provincial revenues convinced municipal officials in British Columbia that the dominion government should take control and assume responsibility for unemployment relief.They were not merely 'passing the buck'. The worldwide nature of the depression supported their contention that unemployment was not a local problem with a local solution. Neither the provincial nor dominion governments would accept primary responsibility for relief. Only in the municipalities which wentbankrupt was a senior government forced to assume responsibility and take control.
OCLC: 688667663
Keywords: Academic theses; Text; Thesis; Thèses et écrits académiques; dissertations; doctoral dissertations; masters theses; theses

L'évolution du travail de la femme au Québec de 1940 à 1970 - Gosselin, Francine Barry (Université Laval, 1975)
OCLC: 1273936475
Keywords: Academic theses; Femmes – Travail – Québec (Province); Thèses et écrits académiques; dissertations

No Compromise — No Political Trading: The Marxian Socialist Tradition in British Columbia - Johnson, Ross Alfred (University of British Columbia, 1975)
At the turn of the century, socialist groups of several different hues were active in British Columbia. Out of this variegated skein emerged the Socialist Party of Canada. For almost two decades it dominated left-wing politics in B.C., wielding extensive power in the labour movement and leaving behind it an ideological legacy which eventually filtered into the fledgling CCF. This study documents the conditions which led to the SPC's ascendancy, discusses its relationship with the early labour movement and examines the extent of Marxist influence on later socialist developments in the province. The dissertation employs an historical approach, supplementing library resources with correspondence and interviews with members of the old SPC. When reformist attempts of the late nineteenth century failed to improve conditions for the B.C. worker, labourism lost out to radicalism. The SPC was national in name only, for its doctrinaire Marxism evoked a significant response only in the unique political, industrial and social milieu of British Columbia. The rapid resource exploitation which gave rise to empires early in the province's history created a classical Marxist situation in some areas. The absence of party alignments in the early years of socialist activity, plus a following of radical immigrants from Britain, the U.S., and eastern Canada afforded the Marxists a large audience to which they addressed themselves with tireless propaganda efforts. Many SPC members were active in the labour movement as well, and were able to prevent the formation of a labour party for many years. When other parties finally did form with labour support, they were much farther to the left than were earlier labour parties. In large part this was due to the ambitious education program which characterized the socialist movement from its inception and ultimately became the Marxist's chief raison d'etre. Candidates were run solely for educational purposes. Once elected, however, SPC legislators found themselves in a balance of power position for a time and consequently their legislative accomplishments were considerable. The failure to adapt to Marxist theory to changing B.C. circumstances ultimately cost the Party credibility. Unable to withstand internal pressures or to respond to the political challenges of World War I, inflation, conscription, labour unrest, and the Russian Revolution, the SPC was gradually replaced by other groups on the left. However, the Party's adherence to a one-plank no-compromise platform did preserve the Marxist ideal in the province for later socialist groups.

The Sunshine and the Shade: Labour Activism in Central Canada, 1850-1860 - Appleton, Paul Campbell (University of Calgary, 1974)
Not much is known about the origins of the labour movement in the pre-Confederation Canadas. The fifties in particular are well worth a closer examination than they have received at the hands of Canadian labour historians. The mid-century decade saw labour pass through the sunshine of the greatest boom of the century, and the shadow of the severe depression which followed the Crash of 1857. The years between 1853 and 1855 were surprisingly turbulent in terms of strike action among both skilled and unskilled men in the Canadas. After a generation of passivity, Canadian labour embarked on a path which led to the birth of a genuine labour movement in the Canadas. Though the scale of the movement was small by comparison with that of Britain or the United States, it was no less vigorous and dynamic during the years which saw the birth of the "new unionism" in both America and Britain. The labour activism of the fifties was largely a response to inflationary pressures brought on by the great railway development boom. In addition, the Canadas were coming more and more under the influence of the forces unleashed by the industrial revolution, and technological innovation created pressures which helped to spur strike action and union organizing activity. The leaders of the "wages movement" and the "insurrection of labour" were working men in the traditional crafts and trades. The most active were those in what might be called the "middle trades," which took in the building trades, shoemakers, tailors, and others who were not among the labour aristocrats of their time. The labour force was dominated by the recent immigrants, and the men who founded the unions of the fifties were men with strong traditions of labour. Many of them were Irish, and the Irish deserve credit for being the co-founders of the unions of the fifties. In Canada the Irish had successfully penetrated a number of the middle rank trades, and many were active participants in the unions of their day. After 1854, unionism had a foothold in the major Canadian cities. Linkage with the parent movements was precipitated by the post-1857 depression. Pragmatic, wage-conscious, and basically non-ideological in character, the Canadian unions did not differ significantly from the British or American unions of their day, except in ways which were a function of the differing scale of the three societies. The 1854 climax of unrest among skilled men was a significant turning point in the relations between labour and capital in the Canadas. The breakthrough was most visible in the Toronto-Hamilton region, which was the focal point of labour activity. Labour in the two cities exhibited a dynamism which was unprecedented in Canada up to that time. The sixties, which brought the further growth of trade unions, and affiliation with American unions, saw the logical extension of a process which was begun in earnest a decade earlier.

East Indian Immigration into Canada, 1905-1973 - Bhatti, F. M. (University of Surrey, 1974)
The migration of East Indians to the Dominions was an unorganised exercise. Indian membership in the British Empire gave them the status of British subjects and Imperial citizens but the Dominions were opposed to coloured migrants. By 1900 Australia and New Zealand had established their immigration policies for 'Whites only'. Canada experienced the East Indian migration after 1900. It coincided with that of other Orientals, namely Chinese and Japanese. Meanwhile ideas of social Darwinism prevailed in the North American continent. There arose an organised labour movement on the Pacific Coast. These factors reinforced the anti-Oriental feeling which resulted in the outbreak of anti-Asiatic riots at Vancouver. Exclusion of East Indians was the basic policy of Imperial and Canadian leaders. But an open ban on Indians could create a difficult situation with the possibility of its exploitation by anti-British elements in India. Therefore, effective but indirect restrictions were imposed on East Indian immigration. However, at times, such prohibitory immigration regulations could not sustain the test in the law courts. The migration question reached its climax with the arrival of the Komagata Maru in Vancouver but the failure of this enterprise completely reversed the migration trend. In its repercussions it contributed to the eruption of anti-British unrest and a revolutionary movement in the Punjab. Demands for equal treatment of Indians echoed all over India, After the First World War restrictions on Indian wives and children to join their husbands and fathers in Canada became a focal point. This matter was settled under the arrangement of Reciprocity of Treatment made in the Imperial War Conference (1918), Restrictions on further migration from India remained in practice, With the granting of independence to India and Pakistan, Canada sensed the urgency of coming to an understanding and arrangement With them. India could use this excuse for leaving the Commonwealth. Canada agreed to accept a small fixed number of South Asian immigrants. By the 1960s Canadian economic needs for skilled manpower increased tremendously while ideas of social Darwinism waned. The arrival of a large number of Europeans from various parts of Europe changed the Canadian outlook. Economic prosperity and radical changes in Canadian commercial and industrial life set aside the Asiatic take-over fear. Characteristics of South Asian migrants changed to a very great extent. Worldwide development of rapid transportation and communication helped to create a better understanding. Canada decided to apply her immigration regulations without racial regard. This transformation of the Canddian immigration policy from complete exclusion to equal acceptance has economic and social reasons. It is a paradox of history to find East Indians being excluded when India was part of the British Empire and now being accepted when the Empire is part of history.

Community and Conflict: A Study of the Working Class and Its Relationships at the Canadian Lakehead, 1903-1913 - Morrison, Jean F. (Lakehead University, 1974)
Labour history is frequently equated with the internal workings of trade unions and radical parties in isolation from the society on which they are based. This paper treats these institutions as important, though not the sole expressions of working class activity. It discusses reactions to labour unrest and industrial conflict from within the working class, and from without, and the effect of these reactions on community relationships. This paper demonstrates how the relationship of the working class with the middle class changed from one of amity in 1903 to one of hostility in 1913, and that this came about in two ways: (1) through the changing relationships of the principle sub-groupings within the working class, organized labour, the immigrant communities, and the radical parties; and, (2) through changes in middle class attitudes brought about by reactions to this first development and by changes in the local economy. The primary catalyst for change was violence which occurred in four labour disputes during the period. In examining the source of violence and the means of its suppression, the paper will argue that while cultural conditioning influenced the actions and attitudes of those involved, the nature of their class relationships was the decisive factor.
Accepted: 2009-12-18T16:39:51Z

Conflict in the British Columbia-Cooperative Commonwealth Federation and the 'Connell Affair' - Wickerson, Gordon Stanley (University of British Columbia, 1973)
The B.C.-CCF was formed in late 1932 shortly after the formation of the national CCF party. In November of the following year the B.C. party ran in its first election and secured sufficient support to become the official opposition. The party's executive, spurred by the prospects and hopes of its eventual election as government and in response to its need for a moderate image, selected a retired Anglican minister as House leader. The choice of Robert Connell as House leader was not, however, unanimous. Diehard socialists with different interpretations of society and the role the party should play in achieving social change, fought Connell*s leadership and received sufficient support to mount an intensive intraparty campaign of harassment and criticism. Connell's critics were successful, as a result, in making his leadership intolerable and the subsequent weight of circumstances led him to imprudently reject party convention decisions because they favoured his left wing opponents. This action both isolated him from the rank and file and gave his critics, then in control of the party's executive, an excuse to expel him for his treachery and apostasy. His leadership ended less than three years after it had begun and he became one of three B.C. party leaders dethroned during this period by his party.

Organized Labour in Saskatchewan: The TLC [Trades and Labor Congress] Years, 1905-1945 - Cherwinski, W. J. C. (Walter Joseph Carl) (University of Alberta, 1972)
In view of the existence of a predominantly agricultural economy in the province of Saskatchewan, especially in the years before the Second World War, one might assume that the study of organized labour would lack significance. But the very presence of a movement from the beginning of the province, a movement which continued to exist and even grow, albeit slowly, was in itself important. ...It is one of the objectives of this project to examine the extent to which organized labour, usually considered a force of the left, compared with and contributed to this radical tradition. However, the largest part of this study, based essentially on a wide variety of manuscript sources, is concerned with the historical development of the movement in the years 1905 to 1945, the years dominated by the Trades and Labor Congress of Canada....

The Development of Winnipeg's Socialist Movement, 1900 to 1915 - Chisick, Ernest (University of Manitoba, 1972)
This study is concerned with the development of Winnipeg's socialist movement in the 1900 to 1915 period. It will focus on this small segment of the city's labor movement. It is evident that the mainstream of Winnipeg socialism was involved with the trade union movement both in terms of dual membership and political activity. The exception to this occurred in the four years from 1904 to 1908, when Winnipeg's Socialist Party of Canada local was involved neither in cooperative nor in independent municipal and provincial politics. It existed as a set of some 150 dogmatic Marxist propagandists awaiting the inevitable collapse of the capitalist system. The dominance of this group was short-lived, and the Winnipeg socialists reaffirmed their faith in the democratic-liberal traditions of the British working-class movement. Those European immigrants who became involved in the city's socialist movement after 1907 only helped strengthen this tradition, for their leadership preferred the parliamentary approach of the socialists in Germany to the uncompromising dogmatism of the Socialist Party of Canada.... From author's introduction.
Accepted: 2009-11-30T21:36:59Z

An Anthropological Study of Longshoremen and of Industrial Relations in the Port of St. John's, Newfoundland, Canada - Mars, Gerald (University of London, 1972)
This thesis examines the social organisation of longshoremen and their families and its implications for industrial relations in the Port of St. John's, Canada. The analysis focusses on effects of an extreme in casual labour markets operating against a background of chronic unemployment. Although concentrating on activities within the port it is essential to place these within Newfoundland's geographic, economic, political and legal contexts; these accordingly form the basis of Chapter 1, which also introduces the actors. Chapter 2 sets the longshore family within the context of Newfoundland's rurally based kinship system and shows how structural divisions and alliances derived from within the family are manifest on the dock. It demonstrates how physical strength and prestige are related and as men age, wives and sons assume familial authority. Religion is ezamined in Chapter 3 as providing a social bond for pious women through whom are allocated scarce resources, both economic and social. Economic resources, as collectively organised welfare payments, are offered in cases of family misfortune, whilst piety permits social mobility of children. Mothers are thus able to alleviate some disadvantages of a father's low class occupation. Chapters 4, 5, 6 and 7 concentrate on the longshore work gang as basic unit of work and leisure. Chapter 4 examines how gang workers cooperate and emerge able collectively to modify the foreman's apparently absolute powers in hiring, firing and discipline. The methods by which collective opposition is mounted and prior structural divisions overcome are analysed through an extended case study, the subject of Chapter 5. Chapter 6 examines how pilferage is organised in the docks; analyses alliances and dependencies involved and the institutionalised limits set. It then considers implications of limits as an aspect of longshore morality and an indication of managerial collusion. The articulation of gang organisation derived from work and that found in leisure activities is considered in Chapter 7. The gang is examined as an insurance agency parallel to women's organisations discussed in Chapter 3. Integration and membership within gangs is derived from conformity to work and sociability norms - particularly in drinking. Relationships within drinking groups are then considered in detail. Some men, outsiders to these norms, are found in the gangs; their special role as gang spokesmen against management is considered as they articulate with the Union's political life. Chapter 8 considers Union political activity and relations with employers together. Membership participation is constrained by divisive aspects of membership and Union structure. These are moveable when preconditions allow cross wharf alliances. Resulting turbulence can be focussed on Executives or through them to Employers. In the concluding chapter I briefly summarise the argument.

The Development of Education in the Canadian Labour Congress - Maynard, Claire (University of British Columbia, 1972)
This study traces the development of union education within the Canadian Labour Congress and its predecessors. During the period when union education in Canada originated immediately after World War II, there were two large Canadian Congresses, the Trades and Labor Congress (T.L.C.), and the Canadian Congress of Labour (C.C.L.). The C.C.L., formed in 1940, and its affiliated industrial unions had a pressing need for union education to familiarize its members with union principles. The T.L.C. as a long-established (1883) affiliation of craft unions had a tradition of loyalty toward union aims and was less interested in educational programs. When the two Congresses merged in 1956 and became the Canadian Labour Congress the expansion and growth of membership increased the need for education within the unions. Before the unions organized educational programs for their own members other agencies such as the Mechanics Institute and the Workers' Educational Association attempted to provide a program of liberal arts programs. The programs contributed toward the development of the individual competencies of workers who were not necessarily union members. The peripheral organizations declined as the unions became more adept at administering union education programs. The C.C.L. with its larger affiliated unions is considered to be the originator of union education in Canada. Howard Conquergood, A.L. Hepworth, and Andy Andras, executives of the first education committee in the C.C.L., had a lasting influence on union education trends. The characteristic methods used in union education programs were week-long and weekend schools devoted to giving the student a thorough knowledge of the union as a viable organization dedicated to furthering the economic and social interests of the member. The rise in membership is identified as a factor in the development of the union education program. With the merger of the T.L.C. and the C.C.L. in 1956 to form the Canadian Labour Congress (C.L.C.), more resources could be directed to education. A description is given of the role of the labour movement in adult education through various co-operative activities such as the Labour University Conference in 1956, the National Citizens Forum, and the Canadian Trade Union Film Committee. The co-operation of the C.L.C., McGill University, and the Université de Montreal, led to the establishment in 1963 of the Labour College of Canada as an institution of higher education for trade union members. The College provides an eight-week residential program for workers of Canada and also those of foreign countries. Also pointed out is the broad interest shown by the unions in International affiliations and the study of education in emerging countries. The study concludes by identifying general trends in union education in the past and suggesting some new directions and program areas for union education in the future.

Economic Background of the Winnipeg General Strike: Wages and Working Conditions - Sutcliffe, Joseph Harry (University of Manitoba, 1972)
This study attempts to present an economic background to the Winnipeg General Strike and in particular examine in detail the wages and working conditions that prevailed prior to and during those eventful days. In the past the Winnipeg General Strike has been considered from primarily a political and social viewpoint. If we accept the views of Mr. Robson, K.C., head of the Royal Commission that investigated the strike, the economic issues are of more importance.

The Estevan Strike and Riot, 1931 - Hanson, Stanley Duane (University of Saskatchewan, 1971)
Having organized as a local of the Mine Workers' Union of Canada (MWUC) only a few days previously, the miners ot the Souris coalfield walked off the job on September 8, 1931 to reinforce their demands for increased wages and improved working conditions. The seasonal and fluctuating nature of the Saskatchewan industry, the reduction in realization by operators from the sale of lignite, wage reductions in late 1930 and early 1931, and certain unsatisfactory working and living conditions may be identified as underlying causes of the dispute. Three factors ultimately precipitated the wildcat strike: the absence of any established grievance mechanism, the coal operators' refusal to recognize the MWUC, and the refusal of James Sloan, MWUC president, to accede to demands for the establishment of a conciliation board under The Industrial Disputes Investigation Act. On September 29 some 300 to 400 striking miners and their families clashed with police on the streets of Estevan, Saskatchewan in a bloody riot resulting in three deaths, a number of injuries, and the conviction of several participants on charges arising out of the confrontation. The tragic events of "Black Tuesday" helped bring about a settlement, but not an altogether desirable one. The authorities, it would seem, beginning in early October, launched a campaign aimed at placing the bulk of responsibility for affairs on "outside agitators," at depriving the miners of the support and assistance of anyone from outside the district, at undermining unity among the miners, and at bringing the parties together under their scarcely impartial auspicies. The result was a settlement which, while granting some concessions to the miners, was violated in varying degrees at once by the operators. Not surprisingly, before a royal commission set up to examine the causes of the strike had completed its report, there was talk among miners of further strike action. It is also not altogether surprising that there was no official inquiry into the riot itself.
Keywords: Coal miners; Estevan; Estevan. Riots; SASKATCHEWAN; Strikes and lockouts

La condition socio-économique des travailleurs de la ville de Québec, 1896-1914 - Larocque, Paul (Université Laval, 1970)
L'étroite interdépendance des phénomènes économiques et sociaux explique le choix de l'année 1896 comme point de départ de cette brève étude de la condition des travailleurs de Québec: à partir de 1896, une phase de croissance succède à une longue période de récession économique; cette conjoncture plus favorable accélère le développement d'une infrastructure industrielle dans la province. Seul le déclenchement de la première guerre mondiale modifiera quelque peu le rythme de cette croissance. C'est à l'intérieur de cette période assez longue, soit de 1896 à 1914, que nous voulons élaborer un cadre général deréférence dans lequel pourront par la suite s'insérer plusieurs études particulières. L'état embryonnaire des recherches surl'histoire des travailleurs québécois nécessite d'abord un travail de défrichage, une perspective globale sans laquelle on ne saurait comprendre ni le sens des revendications ouvrières, ni la montée du syndicalisme dans les principales agglomérations urbaines. –Introduction
"Le présent travail [par Paul Larocque] résume une thèse de maîtrise présentée à l'université. Laval en 1971" : https://www.lltjournal.ca/index.php/llt/article/view/2318/2726

Pursuit of Status: Professionalism, Unionism, and Militancy in the Evolution of Canadian Teachers' Organizations, 1915-1955. - Roald, Jerry Bruce (University of British Columbia, 1970)
The hypothesis of the thesis is that Canadian teachers have sought to gain some control over their professional lives through organisation. The study traces the evolution of the Canadian teachers' organizations from a period of vigorous ascendency between 1916 and 1921 to the middle of the 1950s. By then the organizations had formed their main features and shaped their occupational ideology. The simplest theoretical statement, framework, or model of the thesis is that teachers have attempted to escape from or at least to modify the bureaucratic environment which prescribed the conditions of their vocation. While teachers largely united in seeking this escape, they were not of one mind as to the appropriate means or alternatives: professionalism, unionism, or a combination of both. To most teachers, professionalism and unionism seemed polar and incompatible. The conclusion reached in the study is that teachers’ organizations evolved as "professional unions," largely because of the teachers' need to cope with their salaried and employee status while clinging to the aspiration of professionalism and public service. The thesis rests extensively on primary sources: the records and files of the teachers' organizations, journals of the organisations, contemporary newspapers and magazines, and documents housed in the various archives of Canada. The thesis is not a definitive study of all the issues that have concerned teachers or their organizations. Rather, it is keyed to those issues and situations that have involved a debate over unionism and professionalism, or which have caused teachers to adopt more militant postures. Admittedly the study is pro-teacher, essentially a result of the sources consulted. A deliberate attempt, however, has been made to record the teachers' reactions to their own historical experience, the trustees, and government. The study is divided into six chapters. The first, tracing the years of formation and survival (1915-1930), explains the causes for teacher organization and the teachers' goals. It probes their occupational ideologies. The second chapter investigates the teachers' strikes of the 1920's, and ponders the meaning of these strikes and the issues of teacher militancy. The third chapter deals with the impact of the depression and the war (1930-1945) on the evolution of the organized profession. This chapter reveals the extent of economic retrenchment on teachers' salaries, the spirit of organizational experimentation, and the renewed militancy as the depression receded and the war ensued. The fourth chapter shows how the teachers' "professional unionism" is rooted in their acceptance of the essentials of trade unionism. The fifth chapter records the teachers' courtship with organized labour–affiliation. In particular, it traces in detail the experiment of the British Columbia Teachers' Federation with affiliation, with public admission of trade unionism. The last chapter deals with the achievement of statutory or automatic membership, an organizational development which is singularly the most significant in the history of the Canadian teaching profession.

Western Federation of Miners and the Royal Commission on Industrial Disputes in 1903 with Special Reference to the Vancouver Island Coal Miners' Strike. - Orr, Allan Donald (University of British Columbia, 1968)
The Dominion government appointed a Royal Commission in April 1903 to investigate the causes of strikes that began in February between the Canadian Pacific Railway Company and the United Brotherhood of Railway Employees at Vancouver and the Wellington Colliery Company and the Western Federation of Miners at Extension and Cumberland on Vancouver Island. The Boyal Commissioners were instructed to report whether in their opinion these and other American unions should have their activities in Canada curtailed. After a month of hearings the Commissioners reported that the United Brotherhood and the Western Federation were undesirable unions for Canadian workingmen to join. The Commissioners concluded that both unions had conspired to bring about strikes in the Wellington Colliery mines. The Nanaimo Miners' Union, Local 177 of the Western Federation, was accused by the Commissioners of assisting in the conspiracy to tie up the coal mines in the adjacent towns. As the Canadian Pacific Railway Company depended in part on the Wellington mines for steam coal for its trains at Vancouver, it was apparent that the unions concerned tried to break the strike for recognition between the railway company and the union in favour of the union. The Commissioners also reported that these American unions were spreading revolutionary socialism in British Columbia. The main result of this political action, concluded the Commissioners, was to instil in workingmen a belief in the inevitability of class conflict between themselves and their employers. The transportation and mining industries of the province were in danger of having their businesses seriously disrupted if these foreign unions remained in Canada. The Commissioners stated that a few socialists in Vancouver, Nanaimo, Extension and Cumberland were responsible for encouraging these radical unions to organize the workers. The question as to whether the Western Federation actually caused the strikes on the island has never been seriously explored. Historians have been divided on the question and on their assessment of the validity of the Commissioners' Report. The official hearings disclosed that James Dunsmuir, the president and owner of Wellington Collieries, locked out his miners once they had formed unions. The Commissioners argued that the conspiracy plan depended on the predictable reaction of Dunsmuir to the formation of unions in his mines. In the past he had never permitted unions to exist for long in his mines before he dismissed the union leaders. It has never been satisfactorily demonstrated whether the miners joined the Western Federation for reasons of their own and then struck for union recognition or whether they were, as the Commissioners alleged, tricked into the Federation only to find themselves locked out. The Commissioners admitted in the Report that Wellington Collieries and other large employers of labour bore some responsibility for the fact that working men organized unions in order to protect themselves from the arbitrary and unjust treatment they often received from managers and foremen. Although the Commissioners stated that shorter hours and higher wages would make workingmen more content, they did not report that grievances over working conditions and wages were the real reasons why the miners joined the Western Federation. Yet the official hearings of 1903 contained ample evidence that the strikes at Extension and Cumberland occurred for reasons that lay primarily within and not outside the coalfield. The Commissioners misinterpreted the reasons why the miners joined the Western Federation because their attention was directed solely to the issue of the advance of American unions into Canada. An analysis of the official evidence of the Commission reveals that the miners formed unions at Wellington Collieries in 1903 in order to resolve problems that had become traditional sources of dispute on the coalfield. The traditional problems that embittered relations between miners and companies were geological, social and economic in character. The faulted condition of the coal seams made mining both difficult and dangerous. Since 1871 Wellington miners had organized unions to fight for improvements in safety and working conditions underground. However, the increased employment of illiterate and inexperienced Oriental workers increased the dangers of mining to all concerned. Miners demanded the exclusion of Oriental workers from the mines for another important reason than the question of safety. Oriental workers competed for the jobs of mine labourers and were often used in place of white miners during strikes. During strikes in 1877, in 1883 and in 1903 Chinese workers kept the mines running while white miners were locked out. In contrast to the Wellington mines, unions emerged at the Nanaimo mines and working conditions steadily improved after 1883. A miners' union grievance committee was established in the mines by 1883. An eight hour day, oriental exclusion and union recognition were in effect in the Nanaimo mines by 1891. Attempts by union leaders from Nanaimo in the years 1890 to 1901 failed in their purpose of organizing the Dunsmuir mines. When the Nanaimo miners joined the Western Federation of Miners in 1902 in order to improve their weak bargaining power, miners in the adjacent Dunsmuir mines saw their opportunity to join the Federation. With the financial and moral support of a large union behind them the Dunsmuir miners demanded union recognition as the first step in their plan to negotiate improvements in wages and working conditions.

The Regina Riot: 1935 - Stone, Gladys May (University of Saskatchewan, 1967)
The depression of the 1930's confronted Canadians with shrinking markets, falling prices, a drought-stricken Prairie region and mass unemployment. Consequently there was an enormous burden of relief and welfare. Financial support from the Dominion was needed in all areas, but since not all areas were affected equally some required more assistance than others. The federal government gave grants and loans to the provinces to assist "('with relief costs and Ln some cases increased provincial subsidies. To alleviate distress the Dominion also carried on a public works program and established relief camps for single men. Not everyone viewed the depression in the same way. In 1930 the Workers' Unity League was established to organize labour into "revolutionary unions" for the struggle against capitalism. The League worked under the assumption that a time of crisis was favorable both in terms of the expansion of the League and the onslaught on the existing system. At the midpoint of the 1930's several hundred men on the initiative of a union established in the relief camps by the Workers' Unity League left these camps in British Columbia. After months in Vancouver they started on a trek to Ottawa to present six demands to the government. They were stopped in Regina. On July 1, 1935 a riot, which has been termed the Regina Riot, broke out in the city. Although some writers have referred briefly to this event a detailed study has not been made. The writer hopes to make a small contribution to the examination of the events of the 1930's by examining the Regina Riot. The main purpose of this study is to trace the events which culminated in a serious riot. The examination is primarily concerned with a study of the events in an attempt to explain why there was a Regina Riot. Although the riot was related to the broader problems of the depression and government policies in coping with the depression, these aspects are touched upon only to the extent that they related specifically to the events surrounding the riot. Relief camps are discussed, but it is outside the scope of this study to make a detailed evaluation of this or any other type of relief measure. Although the leader of the trek was an avowed Communist and the organization in the camps had been established by a Communist organization, the question of Communism in the 1930ls is not examined except where it applies specifically to the events of this study. The movement of the men out of the camps to Vancouver and their stay in Vancouver involved to a greater or lesser degree the striking relief camp men, the municipal, provincial and federal governments, as did the trek eastward. The decisions and actions of each are examined. The trek was stopped in Regina by the federal government. that very important decision resulted in a confrontation of the strikers and the federal government and also involved in the dispute the provincial government. The events of this period are examined, along with the incidents that touched off the actual riot. Finally the inquiry into the riot and the eventual disposition of the relief camps are discussed.

The Formative Years of the Trade Union Movement in Saskatchewan 1905-1920 - Cherwinski, Walter Joseph Carl (University of Saskatchewan, 1966)
The choice of the years 1905 to 1919 as the formative years of the trade union movement in Saskatchewan was by no means arbitrary. The years 1905 marked the formation of the first permanent, non-railway local union. The intervening years until 1919 were years of further formation and consolidation, of recognition and entrenchment, of expansion and demise, of hope and of failure. The fifteen years in question were the heyday of the craft unions, and more specifically of the building trades which expanded to meet the demands of a new and rapidly developing province. Like the people of the province, generally these unions expressed great optimism for the future. At times their expansion showed a distinct lack of rhyme or reason, but then no one was overly concerned with caution. Besides, there was no reason to be cautious when crops were good and there was an ever-increasing number of acres from which these crops could be gleaned. Only with the war was this optimistic speculation checked; only then did organized labour realize that security was an obscure quantity, quick to disappear, and that the position of the workingman had to be bolstered by means which were at variance with the established order. The upheaval of 1919 which resulted produced a Thermidorean reaction, the legacy of which had its effects throughout the 1920's and even into the 1930's.

The 1900 Strike of Fraser River Sockeye Salmon Fishermen - Ralston, Harry Keith (University of British Columbia, 1965)
This study sees the 1900 strike on the Fraser River as providing the setting in which trade unions began in the fisheries of British Columbia, and analyzes both the strike itself and its background from that point of view. In the two decades to 1890, the Fraser River salmon canning industry grew relatively slowly, limited by the problems of developing techniques for processing, finding labor for packing, and accumulating capital from profits. In the 10 years to 1900, these difficulties had been mostly overcome, and fresh capital, attracted by sizeable profits, nearly tripled the number of canneries. This boom ended in a crisis of over-expansion, marked by strikes and company mergers. One unforeseen effect of license limitation in the seasons I889-I89I was a change from paying fishermen a daily wage to paying them at so much per fish, and consequently the start of a series of disputes between canners and fishermen over fish prices. Though in general prices rose throughout the 1890*s, the individual fishermen failed to benefit, partly because of price cuts and limits on deliveries during periods of a heavy supply of fish, and partly because of the increasing number of fishermen licensed in each succeeding year. In an attempt to increase their bargaining strength, white resident fishermen campaigned for changes in federal fishery regulations to restrict competition from Japanese and American fishermen, and to reduce the number of cannery licenses. The first fishermen's organization, formed in 1893 to further this end, did not survive its unrelated involvement in a strike that year against price cuts. The amendments to the fishery regulations in 1894 and, to an even greater degree, in 1898 reflected the success of this group in gaining their ends by political means. To try to redress the balance, the canners created in 1898 their own closely-knit organization, the British Columbia Salmon Packers’ Association. The difficulties of the seasons of 1898 and 1899, basically caused by over-expansion, led the canners to tighten their organization further by creating in January, 1900, the Fraser River Canners’ Association, a cannery combine with power to set maximum fish prices and production quotas for each cannery, and to levy fines on violators of its decisions. About the same time, and partly in reaction to the canners' move, separate unions of fishermen were organized, first at New Westminster, then at Vancouver. The Vancouver union tried and failed to enroll Japanese fishermen who formed in June, 1900, the Japanese Fishermen's Benevolent Society. The Canners’ Association refused to negotiate prices with fishermen's union representatives or to set a minimum price for sockeye. When the sockeye season opened July 1 the fishermen struck, demanding 25 cents a fish through the season. By July 10, the strike included all fishermen on the river—white, Japanese and Indian. After another week, the Canners' Association felt forced to negotiate and in a series of meetings the two sides came close to settlement. At this point, however, the canners broke off negotiations and made a separate agreement with the Japanese for 20 cents for the first 600 fish in a week and 15 cents thereafter. The canners then provoked an "incident" as an excuse for three friendly justices of the peace to call out the militia to Steveston. In spite of the Japanese defection and the presence of the militia, the remaining strikers held out for another week. Mediation by E. P. Bremner, Dominion Labor Commissioner, and Francis Carter-Cotton, publisher of the Vancouver News-Advertiser, secured them a negotiated settlement which, though not including any union recognition, guaranteed 19 cents throughout the season. This success led to the creation in January, 1901, of the Grand Lodge of British Columbia Fishermen's Unions, the first coast-wide fishermen's organization in British Columbia. The strike marked the beginning of continuous union activity in the industry and the start of a tradition of radical leadership that persists to the present day.

The Locomotive Engineers' Strike on the Grand Trunk Railway in 1876-1877 - Ayer, Shirley Ann (McGill University, 1961)
In the midst of swirling snow and bitter temperatures, Grand Trunk locomotive engineers and firemen struck work on December 29, 1876. Hundreds of men were involved as this four-day Canadian strike marked the beginning of one of the greatest years of labor unrest in North American history. From the evening of December 29, 1876, to the morning of January 3, 1877, the Grand Trunk men refused to work and tried to persuade others not to take their places. [...]This study of the Grand Trunk strike is based primarily upon material found in the Canadian newspapers, the Monthly Journal of the Brotherhood of Locomotive Engineers and public records.

The Construction of the First Lachine Canal, 1815-1826 - Tulchinsky, Gerald J. J. (McGill University, 1960)
This thesis purports to be a narrative account of the factors leading up to the building of the Lachine Canal and the problems dealt with, while it was under construction. In his research, the author found that sources, primary and secondary, bearing directly on the canal, were scarce. This may help to explain the inability to come to more definite conclusions concerning sorne matters raised here. Hugh G.J. Aitken's Welland Canal Company often served as a guidepost while this work was in progress. Although the author found it impossible to emulate that excellent study, it is hoped that this thesis will cast sorne light on an unexplored area of Canadian economic history.
http://www.collectionscanada.gc.ca/obj/thesescanada/vol2/QMM/TC-QMM-112940.pdf

The British Columbia Labour Movement and Political Action, 1879-1906 - Loosmore, Thomas Robert (University of British Columbia, 1954)
The period under study is the formative period of working-class political action in this province. The conditions and events of this time form the foundation upon which the Socialist Party of Canada, the Federated Labor Party, the Co-operative Commonwealth Federation, and the Labor Progressive Party grew to be important factors in British Columbia affairs. Consideration of this period is therefore highly relevant to any evaluation or assessment of these organizations. The wage-workers of British Columbia began to organize into unions in significant numbers in the 1880's. Being concerned with improving their lot as workers, some of the unionists turned toward the idea of taking class action on the political field in order to obtain favorable legislation. In the economic sphere, the main complaint of the workers during this period was that the many Chinese in the province worked long hours for low wages, and thus tended to lower the living standards of those who had to compete with them. Another complaint with economic as well as political aspects was that much of the land and resources of British Columbia had been alienated to such corporations as the Esquimalt and Nanaimo Railway Company and the Canadian Pacific Railway. In their political action the workers demanded a solution of these grievances, and in the case of the latter were strongly attracted to the doctrine of "single tax." They also expressed a wish for government-sponsored arbitration and conciliation procedures which would settle labor-management disputes in a peaceful manner. The demands for political reform were occasioned by the use of government in the interests of the wealthy element of the community, and were very much influenced by American and socialist ideas. The basic principle involved was that of “direct democracy”, including the initiative, referendum, and recall, and it persisted throughout the whole period in various forms. The first election to be contested by labor candidates was the provincial election of 1886. Pour candidates ran in Victoria and Nanaimo, and all were defeated. At this time the Knights of Labor was at the peak of its power. The organization soon declined, and its place was occupied in most cases by trade unions. In 1890 the Nanaimo miners' union succeeded in electing two members to the British Columbia legislature. Although these members were unable to carry through any of their own measures, their presence led to the passage of a mechanics' lien law and an arbitration and conciliation act. In 1894 the miners’ candidates were defeated but the Nationalist Party of Vancouver, a labor organization, succeeded in getting Robert Macpherson elected. Although not always strictly a labor representative, Macpherson was generally a protagonist of the cause of labor. In the 1896 federal election the Nationalists also initiated the successful candidature of Rev. George R. Maxwell, who remained in parliament until his death in 1902. In 1898 Nanaimo labor recovered part of the lost ground by electing Ralph Smith to Victoria. Smith changed to the federal field in 1900, was elected, and remained in parliament until 1911. However, he was very closely linked to the Liberal Party, and in 1902 was repudiated by the Nanaimo miners. The 1900 provincial election was the high point of labor political action in this period. Labor Candidates with reform programs appeared in Vancouver and Nanaimo. The Western Federation of Miners in the southern Interior supported non-labor candidates pledged to defend the new eight-hour law for metal-miners. All the W.F.M.-backed candidates and one Nanaimo labor man were elected. This election saw the first appearance of the term "Socialist” as the official designation of a candidate — Will MacClain. The period 1900-1906 witnessed the decline of reformist ”laborism” and the rise of socialism as a political force in the province, culminating in the capture of a Labor Party convention by members of the Socialist Party of Canada. A study of this period has a special relevance to the present political situation in British Columbia. We are now in a time of re-alignment and re-orientation of political forces, the understanding of which demands an appraisal of past political changes. The events and situations recounted and analyzed here, since they are concerned with a period of political experimentation, may afford us useful light on present changes.

The Ethnic Division of Labour in Montreal from 1931-1951 - Rennie, D. L. C. (Douglas Lloyd Claver) (McGill University, 1953)
The people who live in the City of Montreal are exceedingly various. There are officially two languages and unofficially dozens. Many areas of the city provide examples of "culture islands"–Those fast-disappearing settlements of "alien" peoples who preserve their alien ways of life in a new country, and so impart to the latter "atmosphere" and "flavour". To serve and satisfy the various demands of these people there are many and different institutions making it possible for individuals, if they wish, to live their entire lives in their native atmospheres.

Canadian Knights of Labor with Special Reference to the 1880’s - Chan, Victor O. (Victor Oscar). (McGill University, 1949)
Discusses the rise and decline of the Canadian Knights of Labor, including their economic ideas and political activities. Originating from the US, the Knights were established in the 1880s in Canada, where they rapidly became influential advocates of of labour reform (e.g., the 8-hour day). Concludes that their decline in the late1890s was precipitated by internal dissension and the lack of a clear program. The research is drawn mainly from contemporary newspaper accounts.
OCLC: 880687761
Keywords: Electronic Thesis or Dissertation; Knights of Labor (Canada); Labor movement – Canada – History

Collective Bargaining in the Wartime Crown Companies of Canada. - Hanson, J. C. (McGill University, 1949)
The corporate management system which was utilized by the Government of Canada in order to meet the demands of war involved that Government, both directly and indirectly, with the Labour Movement. This thesis attemptsto outline the development of collective bargaining in that segment of the war economy which was directly controlled by Government through agencies which it created; that is, this thesis will deal with the salient pointsof collective bargaining in those wartime creatures of the Dominion of Canada - the crown companies which were established by the Department of Munitions and Supply in order to prosecute the war. ...During World War II, the relations between the Canadian Government and its organized and unorganized employees became the subject of much confused debate and bitter argument. It is important, in view of what has been said heretofore, that the wartime labour relations of the Canadian government and its agencies, on the one hand, and the trade union movement, on the other hand, should not be lost sight of in planning for full employment. If the experiences of the war are remembered and applied in the national interest, much controversy and strife can be avoided as and when the policy of full employment is put into practice.
Keywords: CANADA – LABOUR; Collective Bargaining

A History of the Alberta Teachers' Association: Magistri Neque Servi [Masters not Servants] - MacNab, Kathleen Marsh (University of Alberta, 1949)
Organization of the teachers of Alberta was, in the words of the late Dr. J.W. Barnett, "the product of rebellion," rebellion against conditions which developed during the First World War. Education in Alberta was, in some respects, at a very low ebb. The teachers, disgusted with the seeming hopelessness of their position, existing at what was merely a subsistence level and knowing no security in their positions, were leaving the profession in large numbers. ...It was fortunate that among the teachers of Alberta there were some who were convinced of the value of their service and who were willing to brave resentment and disapproval and to devote themselves to the difficult task of forming an organization of teachers outside the control of government officials. –Introduction, Chapter 1
Keywords: Alberta Teachers' Association

A Survey of Labour Relations in the Metal-Mining Industry of British Columbia - McKay, Dean Reginald (University of British Columbia, 1948)
The scope of this work has been limited to a discussion of employer-employee relationships in the field of metal mining and does not include consideration of labour problems in connection with the production of coal, non-metallic ores, or structural materials. The Introductory part deals with the early history of gold, mining and the subsequent discovery and development of the base-metal resources of the province. In this connection, a study is made of the geographical distribution and extent of these natural resources. A series of charts indicate* the locations of the major producing areas within British Columbia. The expansion of the industry through the years is now considered and developments are traced leading to the present scale of operations. Comparative graphs are presented indicating production scales, average price movements and employment statistics with regard to each of the major metals produced in the province. Attention is now directed to the development of trade unionism in the industry. This deals with the early history of the Western Federation of Miners and the later growth of the International Union of Mine, Mill and Smelter Workers, which now represents organized labour in the metal mines. The role of government in labour relations is shown to be an important factor. A study is made of the effects of such legislative enactments, as, the Industrial Disputes investigation Act, the Wartime. Labour Relations Regulations Act (P.O.1003), and the Industrial Conciliation and Arbitration Act of British Columbia. Under the provisions of the last-mentioned act, which provides definite procedures for collective bargaining, some eighteen agreements are now in effect. Two of these actual agreements between the union and major producers have been made the subject for special study in the presentation of this phase of the subject. The strike record of the industry is now dealt with and the account of events leading up to the strike of 1946 among the gold producers is presented as being illustrative of the procedures followed. The present impasse of 1948 involving the same producers is shown to be an aftermath of the 1946 dispute. The discussion is concluded with an appraisal of present working conditions obtaining in the industry and current trends and indications are considered which would appear to have a bearing on future employer-employee relationships and the general welfare of the labour force, in the metal-mining industry.

Some Aspects of the Socialist Movement in British Columbia, 1898-1933 - Grantham, Ronald (University of British Columbia, 1942)
Discusses factors conducive to the growth of BC socialist movement in the early 20th century including British Fabianism, left-wing unions, political and economic tensions between Eastern and Western Canada, and Vancouver's influence as an industrial and ideological hub. Chronicles political developments and labour activity with particular reference to newspaper accounts.

Vocational Training Facilities for Women in Montreal - Boulkind, Mabel (McGill University, 1938)
Today every citizen secures some minimum of education; and the majority of parents regard the schooling of their children as a matter to be taken for granted. The school leaving age, of course, varies with the standards of the community and its laws. But all public school students, particularly of adolescent age, must sooner or later consider this academic work partly as the training for some specific occupation, career, or job. The important question before the community today, then, is a classification of the relationships between the educations we give and the vocations we seek. Such a problem involves an understanding of the primary school system and its adequacy; the relation of elementary to secondary and higher types of education; the facilities for technical and commercial training, the demands of current and future industry, and the present methods (and lack of them) by which young persons pass from school to employment.
Keywords: Vocational education – Canada.; Women – Education – Canada.

The Development of Teachers' Organizations in Canada - Buck, Geoffrey John (University of Manitoba, 1938)
The pages of this "historical thesis" have been developed with the realization that many teachers, and others interested in the professional activities of teachers, would like to have made available a compilation of material concerning Canadian teachers' organizations. The facts presented deal with the Canadian Teachers' Federation, and provincíal organizations affiliated with the Dominion body; and while not as complete as could be desired they do give a panoramic picture from West to East of the twelve provincial organizations united into a co-operative whole by the Canadian Teachers' Federation. Canadian teachers' organizations have had some share in the development of Canadian educational systems and methods. The recognition by two of our provincial governments of the principle of exclusive membership in statutory professional teachers' organizations will doubtless enable teachers and educational specialists to use their influence more effectively. –Author's preface

French and English in the Institutional Structure of Montreal: A Study for the Social and Economic Division of Labour - Jamieson, Stuart Marshall (McGill University, 1938)
The survival of the French Canadians as a distinct ethnic group in the midst of a much larger and more pervasive English-speaking society is, in many ways, usique in the history of race and culture contact. Numbering some 60,000 at the time of the British conquest of Canada in 1163, the French, by virtue of a high rate of natural increase, have grown to almost 3,000,000 in this country. The traditions and customs peculiar to French Canada center around the most cherished elements of its culture: the French language and the Catholic religion. These, in contrast to English Protestantism, are the main distinguishing factors between the two major ethnic groups in the Province of Quebec. Essentialy local and personal, and wedded to the soil, the traditional French Canadian culture, while protected by constitutional guarantees, developed and expanded in a state of comparative isolation. During the last few decades, however, secular conditions essential to the maintenance of cultural separateness have been disappearing steadily. Economic expansion, spreading from technically more advanced societies to undeveloped regions, has been the universal agent of culture contact and concentration of population in large urban centres....
https://dam-oclc.bac-lac.gc.ca/eng/b121012a-19fd-4bcd-9f6a-4f665fa8c1ed OCLC: 925889227
Keywords: Academic Dissertation; Academic theses; Electronic thesis or dissertation; Sociology; Thèses et écrits académiques

The Means and Modes of Living of European Immigrants in Montreal - Gibbard, Harold A. (McGill University, 1934)
Immigration is intended as an adjustment from one set of conditions to a more satisfactory environment. This thesis attempts to cover the adjustments in the means and modes of living of two irmnigrant groups in Montreal, Canada, the Italians and the Finns, and to present several general hypotheses concerning the assimilation process in these fields. The effects of the economic depression on these processes are noted. Spatial adjustment and chances in family organization are included in so far as these relate to our main points of reference. The principal source of information has been the family budgets of representative samples of the two groups. The Italians, of agricultural backgrounds, have settled near the periphery of Montreal. They have entered the building trades, dock labour, and factory trades. They exhibit a strong family unity. They are assimilating slowly towards the French. The Finnish men are migratory. Their employment is largely in the lumbering, mining,,farming and building industries. The women are domestic servants. The Finns have settled in a downtown area. They are assimilating quickly towards the English.
OCLC: 919429178
Keywords: Electronic Thesis or Dissertation; Europeans – Montréal – Québec (Province); Québec (Province) – Emigration and immigration; Sociology

The Occupational Adjustment of the British Immigrant in Montreal - Reynolds, Lloyd G. (McGill University, 1933)
It is perhaps not surprising that existing studies of British migration to Canada deal primarily with settlement on the land. The Canadian government has made strenuous efforts to encourage immigration of this sort; there is something of glamour, too, about the movement to the last frontier on the prairies of western Canada. Yet all the while immigration has been flowing in equal volume into the industrial centres of the east. While the eyes of the nation were fixed on schemes of Empire settlement, tens of thousands of Britishers were slipping almost unnoticed into Toronto, Montreal and other metropolitan areas. In 1921 there were 54,807 persons of British birth resident in Montreal; sinoe that time over 75,000 new immigrants from Britain have given the Province of Quebec (in effect, Montreal) as their destination. A movement of this size cannot but have had profound repercussions both upon the life of the city and upon the lives of the immigrants themselves. The study of these repercussions constitutes an almost unexplored field.

Socialism in Canada - Troop, George R. (McGill University, 1922)
...It is in the hope of at arriving at an understanding of the reason for the comparative failure of the Socialist movement in Canada that I am attempting this brief outline of its origin and progress. –From introduction